3D-Analysis of a non-planispiral ammonoid from the Hunsruck Slate: natural or pathological variation? - Stilkerich, Julia; de Baets, Kenneth; Smrecak, Trisha A. (PeerJ, 2017)
We herein examine the only known non-planispirally coiled early Devonian ammonoid, the holotype specimen of Ivoites opitzi, to investigate if the host was encrusted in vivo and if these sclerobionts were responsible for the trochospiral coiling observed in this unique specimen. To test if the presence of runner-like sclerobionts infested the historically collected specimen of Ivoites opitzi during its life, we used microCT to produce a three-dimensional model of the surface of the specimen. Our results indicate that sclerobionts grew across the outer rim (venter) on both sides of the ammonoid conch at exactly the location where the deviation from the planispiral was recognized, and where subsequent ammonoid growth would likely preclude encrustation. This indicates in vivo encrustation of the I. opitzi specimen, and represents the earliest documentation of the phenomenon. Further, this suggests that non-planispiral coiling in I. opitzi was likely pathologically induced and does not represent natural morphological variation in the species. Despite the observed anomalies in coiling, the specimen reached adulthood and retains important identifying morphological features, suggesting the ammonoid was minimally impacted by encrustation in life. As such, appointing a new type specimen-as suggested by some authors-for the species is not necessary. In addition, we identify the sclerobionts responsible for modifying the coiling of this specimen as hederelloids, a peculiar group of sclerobionts likely related to phoronids. Hederelloids in the Devonian are commonly found encrusting on fossils collected in moderately deep environments within the photic zone and are rarely documented in dysphotic and aphotic samples. This indicates that when the ammonoid was encrusted it lived within the euphotic zone and supports the latest interpretations of the Hunsrck Slate depositional environment in the Bundenbach-Gemunden area.
Keywords: Epicole; Pathology; Computed tomography; Hederelloidea; Ammonoidea; Epizoa; Heteromorph; Three-dimensional reconstruction; CT scan; Intraspecific variation

3D morphological analysis of cement over the first 24 hours of hydration by holographic and near-field ptychographic-tomography - Valentini, Luca; Sowoidnich, Thomas; da Silva, Julio Cesar; Schulbert, Christian; Naber, Christoph; Neubauer, Jürgen; Bellmann, Frank (ESRF Coherence Workshop, 2019)

3D MORPHOLOGY OF POST MORTEM ACROTHORACICAN BORINGS IN FAMENNIAN HETEROCORALS – A MORPHOLOGICAL DIVERSIFICATION OR A CONTINUUM ICHNOSPECIES? - Dworczak, Patrycja G.; Jarochowska, Emilia; López Correa, Matthias; Berkowski, Błażej (Annales Societatis Geologorum Poloniae, 2022)
Barnacle borings were found in six heterocoral skeletons. They are present as small (up to 2.9 mm long), slender, pouch-shaped borings with tapering, slit-like openings. The investigated borings were made by acrothoracican cirripedes, which mostly do not have a shell and bore into hard substrates to protect their “naked” bodies. The first occurrence of borings in skeletons of the heterocoral Oligophylloides Różkowska, 1969 from the Upper Devonian Tafilalt Platform was reported recently by Weyer in 2016. Here, the authors present the results of a detailed study of heterocoral remains with numerous acrothoracican borings from Jebel Bou Ifarherioun (Famennian, Anti-Atlas, Morocco). The borings were found on the basal part but also on broken branches and stems of the heterocoral corallum and occurred post mortem. There is no indication of a syn vivo coral-barnacle interaction with borings in tissue-covered areas. The authors used micro-CT scans to visualize the 3D morphology of the pits, their orientation, and distribution. Additionally, the 3D morphology of an assemblage of 75 pits was used to carry out ordination and cluster analyses, which showed that previously proposed ichnospecies may be a continuum of morphological variability. In the basis of measurements by the present authors, the studied borings do not fit any known ichnotaxa. The absence of bourrelets excludes the possibility that the borings studied belong to the ichnogenus Rogerella Saint-Seine, 1951. Hence, the results seem to contradict a synonymization that was proposed by Bromley and D’Alessandro (1987) and subsequent authors and leave room for further research and discussion on this topic. Although the inferred boring organism is a filter feeder and, thus, depends on currents, the authors did not find a preferential orientation of the borings. The samples considered here are the best-preserved Devonian barnacle borings to date.
Created from Fastlane, Scopus look-up
Keywords: Acrothoracican barnacles; bioerosion; Heterocoralia; Late Devonian; Morocco

Abnormal forms of acritarchs (phytoplankton) in the upper Hirnantian (Upper Ordovician) of Anticosti Island, Canada - Delabroye, Aurélien; Munnecke, Axel; Servais, Thomas; Vandenbroucke, Thijs R.A.; Vecoli, Marco (Review of Palaeobotany and Palynology, 2012)
A detailed study of Late Ordovician-early Silurian acritarchs (Palaeozoic phytoplankton) from Anticosti Island (Québec, Canada) revealed an unusually high abundance of abnormal forms from the upper Hirnantian carbonate strata (uppermost Ordovician) of the Ellis Bay Formation in the western part of the island (member 6, . Spinachitina taugourdeaui chitinozoan Biozone). The objective of this paper is to describe these abnormal forms in detail. Two species are particularly affected: . Disparifusa psakadoria Loeblich and Tappan, 1978 presents abnormally hypertrophied central vesicles, whereas . Peteinosphaeridium laframboisepointense nov. sp. has appendices that are fused along their length. The abnormal forms of acritarchs occur in rocks deposited during periods that are near time-equivalents to those of maximum ice-sheet extensions on Gondwana during the Hirnantian glaciation. Although this stratigraphic level corresponds to an interval of strong perturbations of the global carbon cycle, the exact factors causing the observed malformations remain unknown. © 2011
Keywords: Hirnantian; Laurentia; Ordovician-Silurian boundary; Phytoplankton; Teratology

Abundant taxa determine beta diversity - Roden, Vanessa; Kießling, Wolfgang (Taphos 2017 Vienna - Programme and Abstracts, 2017)

A Case Study On Bioerosion In Fossil Cephalopods From The Upper Carboniferous Buckhorn Asphalt Quarry Lagerstätte, Oklahoma, USA - Seuß, Barbara; Nützel, Alexander (GSA, 2018)
Cephalopod remains from the Desmoinesian (Pennsylvanian, Upper Carboniferous) Buckhorn Asphalt Quarry (Oklahoma, USA) were studied intensively over the past decades. However, this is the first study that focusses exclusively on bioerosion affecting their shells. Research on bioerosion in these fossils was possible due to soaking of sediments and shells with hydrocarbons, during or shortly after time of deposition, that sealed open space and prevented strong diagenesis. The shells derive from the ‘cephalopod coquina’ that represents the deepest-water deposit within the single cycle of trans- and regression in the outcrop. The cephalopod remains comprise fragments of both, orthoconic and coiled nautiloid specimens as well as those from ammonoids. The shells were cast and investigated with a scanning electron microscope. The study revealed a diverse association of ichnotaxa and ichnoforms (twenty-two in total, eight of them new – among them six ichnoforms could derive from foraminiferans - and twelve with their oldest record in the Carboniferous) comprising chlorophyte, cyanobacterial, and rhodophyte traces. Fungal and spongial traces as well as those of so far unknown origin are also recorded. Most common are Ichnoreticulina elegans (a chlorophyte trace), a new morphotype of Scolecia isp. (probably produced by cyanobacteria) as well as the fungal (Schizochytrium sp.) trace Flagrichnus profundus, the ‘extremely thin form’ (likely the Conchocelis-stage of Porphyra sp. or Bangia sp.), and the ‘superthin form’ that is produced by some unknown organotroph. Straight nautiloids are intensively bored by I. elegans and Scolecia n. isp. while in the shells of coiled cephalopods F. profundus, the ‘extremely thin form’, and the ‘superthin form’ are most abundant. The ichnotaxon associations in the shells indicate different modes of deposition: Shells of coiled specimens seem to have drifted for a while and were therefore more prone to bioerosion by autotrophs until they sank to the seafloor, while those of the orthocones sank more rapidly with deposition in the deep euphotic to dysphotic zone of the ichnobathymetrical scheme. A comparison with the studies on extant Nautilus supports the idea that ichnotaxa present in Carboniferous cephalopods have gone lost with the extinction of thes

Accelerated increase in plant species richness on mountain summits is linked to warming - Steinbauer, Manuel; Grytnes, John-Arvid; Jurasinski, Gerald; Kulonen, Aino; Lenoir, Jonathan; Pauli, Harald; Rixen, Christian; Winkler, Manuela; Bardy-Durchhalter, Manfred; Barni, Elena; Bjorkman, Anne; Breiner, Frank T.; et al. (Nature, 2018)
Globally accelerating trends in societal development and human environmental impacts since the mid-twentieth century are known as the Great Acceleration and have been discussed as a key indicator of the onset of the Anthropocene epoch. While reports on ecological responses (for example, changes in species range or local extinctions) to the Great Acceleration are multiplying, it is unknown whether such biotic responses are undergoing a similar acceleration over time. This knowledge gap stems from the limited availability of time series data on biodiversity changes across large temporal and geographical extents. Here we use a dataset of repeated plant surveys from 302 mountain summits across Europe, spanning 145 years of observation, to assess the temporal trajectory of mountain biodiversity changes as a globally coherent imprint of the Anthropocene. We find a continent-wide acceleration in the rate of increase in plant species richness, with five times as much species enrichment between 2007 and 2016 as fifty years ago, between 1957 and 1966. This acceleration is strikingly synchronized with accelerated global warming and is not linked to alternative global change drivers. The accelerating increases in species richness on mountain summits across this broad spatial extent demonstrate that acceleration in climate-induced biotic change is occurring even in remote places on Earth, with potentially far-ranging consequences not only for biodiversity, but also for ecosystem functioning and services.<br

Accounting for uncertainty from zero inflation and overdispersion in paleoecological studies of predation using a hierarchical Bayesian framework - Smith, Jansen; Handley, John C.; Dietl, Gregory P. (Paleobiology, 2021)
The effects of overdispersion and zero inflation (e.g., poor model fits) can result in misinterpretation in studies using count data. These effects have not been evaluated in paleoecological studies of predation and are further complicated by preservational bias and time averaging. We develop a hierarchical Bayesian framework to account for uncertainty from overdispersion and zero inflation in estimates of specimen and predation trace counts. We demonstrate its application using published data on drilling predators and their prey in time-averaged death assemblages from the Great Barrier Reef, Australia. Our results indicate that estimates of predation frequencies are underestimated when zero inflation is not considered, and this effect is likely compounded by removal of individuals and predation traces via preservational bias. Time averaging likely reduces zero inflation via accumulation of rare taxa and events; however, it increases the uncertainty in comparisons between assemblages by introducing variability in sampling effort. That is, there is an analytical cost with time-averaged count data, manifesting as broader confidence regions. Ecological inferences in paleoecology can be strengthened by accounting for the uncertainty inherent to paleoecological count data and the sampling processes by which they are generated.
CRIS-Team Scopus Importer:2021-09-24

A chaetetid sponge assemblage from the Desmoinesian (Upper Moscovian) Buckhorn Asphalt Quarry lagerstätte in Oklahoma, USA - Seuß, Barbara; Senowbari-Daryan, Baba; Nützel, Alexander; Dittrich, Sebastian; Neubauer, Jürgen; Neubauer, Jürgen (Rivista Italiana Di Paleontologia E Stratigrafia, 2014)
The first detailed study on chaetetids from the Buckhorn Asphalt Quarry Lagerstätte is presented. Among the investigated specimens we found two samples (chaetetid specimens 2 and 6) that are different from all others in the quarry. Thin sections of these display a complex fragmentation of these Buckhorn chaetetids. Additionally, one of these samples contains two chaetetid morphotypes growing side by side, thus, in the same paleoenvironment. These specimens differ in their mode of growth (laminar and domical), which suggests that chaetetid growth was most likely influenced by genetic factors rather than by the paleoenvironment. We observed a feature, not hitherto reported as far as we are aware, on the surface of chaetetids; namely a regular clustering of seven tubules surrounding a central tubule. This feature could have had an exhalant function. Mineralogical analyses of the skeleton indicate primary high magnesian-calcite mineralogy, which is in accordance with reports in the literature. Cements precipitated during diagenesis are either calcite or dolomite and, where associated with microbial mats, they may contain a distinct amount of manganese. The comparison of the chaetetid skeletons from the Buckhorn Asphalt Quarry leads to the impression, that they represent various morphotypes or even species. Because of the lack of unique features, we have refrained however, from describing new species.
UnivIS-Import:2015-04-14:Pub.2014.nat.dgeo.IGM.LP.achaet
Keywords: Buckhorn asphalt quarry; Chaetetida; Hypercalcified sponges; Pennsylvanian; Taphonomy

A continental comparison indicates long-term effects of forest management on understory diversity in coniferous forests - Schmiedinger, Andreas; Kreyling, Jürgen; Steinbauer, Manuel; Macdonald, Ellen; Jentsch, Anke; Beierkuhnlein, Carl (Canadian Journal of Forest Research-Revue Canadienne De Recherche Forestiere, 2012)
Promotion of species diversity has become a major goal in forestry. This requires an understanding of the impacts of management disturbance on species diversity relative to natural drivers such as climatic or edaphic conditions on the relevant temporal scales, i.e., centuries. We examined the effects of long-term management disturbance on understory plant diversity in coniferous forests by comparing structure types (ages since disturbance) between regions with comparable abiotic settings but contrasting management history, i.e., management for centuries in central Europe versus the first logging in primary forests in western Canada. We systematically sampled three age classes after disturbance and compared their alpha diversity and species composition. The structure types (age classes) showed similar differences in alpha diversity in both landscapes, while the response of species compositions differed between the two. Fewer late-successional specialists occurred in the European landscape. Within the setting of our study, the structure types, which reflect the time since major forest management disturbance, affected understory species richness and composition at least as strongly as environmental conditions such as climate, soil, and tree layer diversity across the broad altitudinal gradients that we sampled. Our results suggest that forest management affects the diversity of coniferous forests, with management for centuries disadvantaging late-successional specialists. Furthermore, it appears that human action is becoming the major determinant of diversity of coniferous forests, emphasizing the need for sustainable management schemes.

Acritarch distribution along an inshore-offshore transect in the Gorstian (lower Ludlow) of Gotland, Sweden - Stricanne, Ludovic; Munnecke, Axel; Pross, Jörg; Servais, Thomas; Munnecke, Axel; Munnecke, Axel (Review of Palaeobotany and Palynology, 2004)
To better understand palaeoecological signatures in Palaeozoic acritarch assemblages, the distribution of palynomorphs has been quantitatively studied in eight localities from the Gorstian, lower Ludlow (Late Silurian) of Gotland, Sweden. The localities are situated along an inshore-offshore transect comprising shallow marine lagoonal environments to distal shelf facies. Process-bearing acritarchs and sphaeromorphs constitute the main components within the palynomorph assemblages. The lateral distribution of palynomorphs exhibits characteristic features at three different levels as follows. (1) With regard to the overall composition of the palynomorph assemblages, the abundance of process-bearing acritarchs increases towards the distal shelf, while the abundance of sphaeromorphs decreases. (2) At the generic level, the acritarchs Micrhystridium and Dilatisphaera are more abundant in the proximal facies, while Evittia, Percultisphaera and Oppilatala are more common in distal environments. (3) At an infrageneric level, Micrhystridium morphotypes with shorter processes are mainly present in proximal environments, while those with longer and ramified processes occur in more distal shelf environments. The palynomorph distribution along the inshore-offshore transect highlights the potential of acritarchs and prasinophytes as palaeoenvironmental indicators. © 2004 Elsevier B.V. All rights reserved.
Keywords: acritarchs; Gotland; Ludlow; palaeoecology; palynomorphs; Silurian

Adaptive Behavior of Dynamic Orthoester Cryptands - Shyshov, Oleksandr; Brachvogel, Rene-Chris; Bachmann, Tobias; Srikantharajah, Rubitha; Segets, Doris; Hampel, Frank; Puchta, Ralph; Von Delius, Max (Angewandte Chemie International Edition, 2017)
The integration of dynamic covalent bonds into macrocycles has been a tremendously successful strategy for investigating noncovalent interactions and identifying effective host–guest pairs. While numerous studies have focused on the dynamic responses of macrocycles and larger cages to various guests, the corresponding constitutionally dynamic chemistry of cryptands remains unexplored. Reported here is that cryptands based on orthoester bridgeheads offer an elegant entry to experiments in which a metal ion selects its preferred host from a dynamic mixture of competing subcomponents. In such dynamic mixtures, the alkali metal ions Li+, Na+, K+, Rb+, and Cs+ exhibit pronounced preferences for the formation of cryptands of certain sizes and donor numbers, and the selection is rationalized by DFT calculations. Reported is also the first self-assembly of a chiral orthoester cryptate and a preliminary study on the use of stereoisomers as subcomponents.
Keywords: cryptands; dynamic combinatorial chemistry; supramolecular chemistry; host–guest chemistry; NMR spectroscopy

Adding fossil occupancy trajectories to the assessment of modern extinction risk - Kießling, Wolfgang; Kocsis, Ádám (Biological Letters, 2016)
Besides helping to identify species traits that are commonly linked to extinction risk, the fossil record may also be directly relevant for assessing the extinction risk of extant species. Standing geographical distribution or occupancy is a strong predictor of both recent and past extinction risk, but the role of changes in occupancy is less widely assessed. Here we demonstrate, based on the Cenozoic fossil record of marine species, that both occupancy and its temporal trajectory are significant determinants of risk. Based on extinct species we develop a model on the additive and interacting effects of occupancy and its temporal changes on extinction risk. We use this model to predict extinction risk of extant species. The predictions suggest a moderate risk for marine species on average. However, some species seem to be on a long-term decline and potentially at a latent extinction risk, which is not considered in current risk assessments.

Adding Some Samples - Munnecke, Axel (Microfacies of Carbonate Rocks - Analysis, Interpretation and Application, 2009)
Due to the work by Erik Flügel, who passed away far too early in 2004, microfacies investigations of carbonate rocks have a long tradition in our institute in Erlangen (Germany). He stimulated several generations of geologists in the field of carbonate sedimentology, and it is a great honor for me to provide a small additional chapter to the present book. The chapter presents examples from a variety of depositional environments and ages. The thin sections have been prepared for the international microfacies courses held in Erlangen regularly since 1974. The chapter has two goals. On one side, thin sections have been chosen which complement the previous chapters, and provide some additional information, on the other, this chapter is intended as some sort of self-test. Before reading the figure captions you might try to study the pictures and build your own interpretation
Keywords: microfacies; carbonate rocks; samples; interpretation; thin sections

Addressing priority questions of conservation science with palaeontological data - Kießling, Wolfgang; Raja, Nussaïbah Begum; Roden, Vanessa; Turvey, Samuel T.; Saupe, Erin E. (Philosophical Transactions of the Royal Society B-Biological Sciences, 2019)

A derived sauropodiform dinosaur and other sauropodomorph material from the Late Triassic of Canton Schaffhausen, Switzerland - Rauhut, Oliver W.M.; Holwerda, Femke Marleen; Furrer, Heinz (Swiss Journal of Geosciences, 2020)
Although sauropodomorph dinosaurs have been known for a long time from the Late Triassic of central Europe, sauropodomorph diversity and faunal composition has remained controversial until today. Here we review sauropodomorph material from the Canton Schaffhausen, Switzerland. The material comes from three different but geographically close localities and represents at least three different taxa. Apart from the common genus Plateosaurus, the material includes remains of two different large, robustly built sauropodomorphs. One of these is described as a new taxon, Schleitheimia schutzi n. gen. et sp., on the basis of an unusual ilium and associated axial and appendicular material. Schleitheimia represents a derived basal sauropodiform and possibly the immediate outgroup to Sauropoda, and thus is the most derived sauropodomorph known from the Late Triassic of Europe. These results thus highlight the diversity of sauropodomorphs in the Late Triassic of central Europe and further indicate widespread sauropodomorph survival across the Triassic-Jurassic boundary.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Late Triassic; Sauropod origins; Sauropodomorpha; Switzerland

A discussion and proposal concerning the use of the term calcispheres - Versteegh, Gerard J.M.; Servais, Thomas; Munnecke, Axel; Streng, Michael; Vachard, Daniel (Palaeontology, 2009)
The terminology and grouping of spherical, calcareous microfossils of unknown biological affinity, usually referred to as calcispheres, are diffuse. The term calcispheres is inconsistently used, the morphological and taxonomical concepts are mostly ill-defined and a formal definition is lacking. To resolve this issue, we propose, in analogy with the erection of the Acritarcha for organic microfossils of unknown origin, a new group called Calcitarcha, including all calcareous microfossils with a central cavity for which the biological affinities remain unknown. © The Palaeontological Association, 2009.
Keywords: calcareous microfossil; calcisphere; Calcitarcha; Nomenclature; pithonelloid; gilianelloid

A first glimpse on the taphonomy and sedimentary environment of the Eocene siliceous sponges from Chiampo, Lessini Mts, NE Italy - Frisone, Viviana; Preto, Nereo; Pisera, Andrzej; Agnini, Claudia; Giusberti, Luca; Papazzoni, Cesare Andrea; De Angeli, Antonio; Beschin, Claudio; Mietto, Paolo; Quaggiotto, Ermanno; Monaco, Paolo; Dominici, Stefano; et al. (Bollettino Della Societa Paleontologica Italiana, 2020)
A diverse assemblage of bodily preserved sponges has been recovered from a lower Lutetian tuffite horizon in the Chiampo Valley, Lessini Mountains, Italy. The sponge assemblage is dominated by hexactinellids and lithistids. Using uniformitarian criteria, the composition of the assemblage suggests a water depth greater than 200 m. Sponges are often preserved in growth position including sponge clusters. Taphonomic processes facilitating sponge preservation include rapid burial of a living sponge community and early diagenetic calcification. Different modes of attachment suggest heterogeneous substrate conditions. The associated fauna, such as abundant pteropods in the matrix and in-situ preserved crinoids, confirms a rather deep-water environment. However, there are also common benthic elements of shallow-water origin. Although some of these elements show signs of transport, others, such as decapod crustaceans, do not. Moreover, trace fossils indicate high-energy environments. To reconcile these observations, we propose rapid, tectonically triggered sea-level changes.
CRIS-Team WoS Importer:2021-01-29

A first Palaeozoic-type echinoderm group representative from the Mesozoic - Reich, Mike; Stegemann, Tanja R.; Hausmann, Imelda M.; Roden, Vanessa; Nützel, Alexander (GeoBonn 2018, Living Earth - Abstracts, 2018)

A first report of the Ludlow Lau Event from the Prague Basin (Barrandian, Czech Republic) - Buggisch, Werner; Fryda, Jiri; Lehnert, Oliver; Manda, Štěpán (Serie Correlación Geológica, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dgeo.IGM.LG.afirst

A generalization of the taxon cycle - Steinbauer, Manuel (Journal of Biogeography, 2017)

A geographic database approach to the KT boundary - Kießling, Wolfgang; Claeys, Philippe (Geological and biological effects of impact events, 2001)
UnivIS-Import:2015-04-20:Pub.2001.nat.dgeo.IGM.LP.ageogr

Aggradation and carbonate accumulation of Holocene Norwegian cold-water coral reefs - Titschack, Jürgen; Baum, Daniel; De Pol-Holz, Daniel; López Correa, Matthias; Forster, Nina; Flögel, Sascha; Hebbeln, Dierk; Freiwald, André (Sedimentology, 2015)
Cold-water coral ecosystems present common carbonate factories along the Atlantic continental margins, where they can form large reef structures. There is increasing knowledge on their ecology, molecular genetics, environmental controls and threats available. However, information on their carbonate production and accumulation is still very limited, even though this information is essential for their evaluation as carbonate sinks. The aim of this study is to provide high-resolution reef aggradation and carbonate accumulation rates for Norwegian cold-water coral reefs from various settings (sunds, inner shelf and shelf margin). Furthermore, it introduces a new approach for the evaluation of the cold-water coral preservation within coldwater coral deposits by computed tomography analysis. This approach allows the differentiation of various kinds of cold-water coral deposits by their macrofossil clast size and orientation signature. The obtained results suggest that preservation of cold-water coral frameworks in living position is favoured by high reef aggradation rates, while preservation of coral rubble prevails by moderate aggradation rates. A high degree of macrofossil fragmentation indicates condensed intervals or unconformities. The observed aggradation rates with up to 1500 cm kyr-1 exhibit the highest rates from cold-water coral reefs so far. Reef aggradation within the studied cores was restricted to the Early and Late Holocene. Available datings of Norwegian cold-water corals support this age pattern for other fjords while, on the shelf, cold-water coral ages are reported additionally from the early Middle Holocene. The obtained mean carbonate accumulation rates of up to 103 g cm-2 kyr-1 exceed previous estimates of cold-water coral reefs by a factor of two to three and by almost one order of magnitude to adjacent sedimentary environments (shelf, slope and deep sea). Only fjord basins locally exhibit carbonate accumulation rates in the range of the cold-water coral reefs. Furthermore, cold-water coral reef carbonate accumulation rates are in the range of tropical reef carbonate accumulation rates. These results clearly suggest the importance of cold-water coral reefs as local, maybe regional to global, carbonate sinks.
UnivIS-Import:2016-06-01:Pub.2015.nat.dgeo.IGM.LP.aggrad
Keywords: Aggradation rate; Carbonate accumulation rate; Cold-water coral carbonate factory; Cold-water coral reef; Holocene reef development

A giant boring in a Silurian stromatoporoid analysed by computer tomography - Beuck, Lydia; Wisshak, Max; Munnecke, Axel; Freiwald, André (Acta Palaeontologica Polonica, 2008)
This study describes the largest known Palaeozoic boring trace, Osprioneides kampto igen. et isp. nov., found within a stromatoporoid Densastroma pexisum from the Upper Visby Formation (lower Wenlock, Silurian) on the island of Gotland, Sweden. Differences between the physical properties of the stromatoporoid, and the dense micritic infilling of the borings allowed the application of the CT-scan technology for the 2D and 3D-visualisation of this rare trace. The additional application of a stereoscopic technique on these CT images and movies enhances its value for unravelling spatial orientations. This non-destructive method has a great potential for future macro- as well as microboring analyses, The trace maker, most likely a worm, infested the hosting colony post-mortem with up to 120 mm long borings measuring 5-17 mm in diameter. Smaller forms of Trypanites and Palaeosabella within the same stromatoporoid preferentially occur in the outer coenosteum and occasionally in abandoned borings of O. kampto. The stratigraphic position of O. kampto follows the "Great Ordovician Biodiversification Event" in time, and reflects the increase in diversity of boring species. Borings with penetration-depths of 120 mm are, however, unique findings for the Palaeozoic and were not exceeded until some 260 million years later (Bajocian, Middle Jurassic) when the "Mesozoic Marine Revolution" led to convergent reinventions as a result of enhance predation, grazing pressure, and ecospace competition.
Keywords: Bioerosion; trace fossil; Osprioneides; stromatoporoid; computed tomography; Silurian; Gotland

A Hirnantian (latest Ordovician) reefal bryozoan fauna from Anticosti Island, eastern Canada: Taxonomy and chemostratigraphy - Ernst, Andrej; Munnecke, Axel (Canadian Journal of Earth Sciences, 2009)
The Natiscotec outcrop on Anticosti Island, Canada (Ellis Bay Formation, Laframboise Member, Hirnantian, Late Ordovician), exposes a patch reef some 20-30 m in diameter, 2-3 m thick, with abundant rugose corals, as well as favositids and heliolitids. Reef capping and flanking sediments include typical Hirnantian brachiopods, such as Hirnantia, Hindella, and Eospirigerina. Within the reef peloidal microbialites encrusting bryozoan colonies are common. The bryozoan fauna includes three cystoporates, seven trepostomes, and three phylloporines. Two genera and two species are new: the cystoporate Natiscotecella tenuis n. gen. and n. sp. and the phylloporine Dilaminocladia natiscotecensis n. gen. and n. sp. Three more species are also new: the cystoporates Ceramopora clara n. sp. and Acanthoceramoporella spinigera n. sp. and the trepostome Revalotrypa honguedensis n. sp. Furthermore, we identify the three trepostomes Atactoporella aff. ortoni (Nicholson, 1874), Hallopora elegantula (Hall, 1852), and Monotrypella cf. aequalis Ulrich, 1882, and a phylloporine Parachasmatopora porkunensis Lavrentjeva, 1985. Four species are identified at generic level and in open nomenclature: the three trepostomes Lioclemella sp., Calloporella sp., and Trepostomata sp. and a phylloporine ? Ralfinella sp. The bryozoan fauna shows some affinities with the Late Ordovician fauna of Scandinavia. Stable carbon isotope investigations from brachiopod shells of the same outcrop yield values for d13C of up to +6.7%, which represent the highest values reported from the Anticosti succession so far. This indicates that the stratigraphic position of the outcrop is at or close to the peak of the globally recognized Hirnantian δC excursion.
Keywords: Hirnantian; Ordovician; Anticosti Island; Bryozoan Fauna; Taxonomy; Chemostratigraphy

A Late Barrêmian and Early Aptian Vertebrate Fauna of Garbsen near Hanover, Lower Saxony - Biermann, Stefanie; Roden, Vanessa; Karl, Hans-Volker; Reich, Mike (Terra Nostra 2009/3, 2009)

A Late Devonian actinopterygian suggests high lineage survivorship across the end-Devonian mass extinction - Giles, Sam; Feilich, Kara; Warnock, Rachel; Pierce, Stephanie E.; Friedman, Matt (Nature Ecology & Evolution, 2022)
An actinopterygian fossil with unexpected anatomical features from 7 million years before the end-Devonian mass extinction suggests complex patterns of divergence and diversification around the Devonian/Carboniferous boundary for ray-finned fishes.
CRIS-Team WoS Importer:2022-12-02

A Late Ordovician planktic assemblage with exceptionally preserved soft-bodied problematica from the Martinsburg Formation, Pennsylvania - Meyer, Mike B; Ganis, G. Robert; Wittmer, Jacalyn M.; Zalasiewicz, Jan A.; de Baets, Kenneth (Palaios, 2018)
Here we report a locality containing exceptionally preserved (soft-bodied) fossils of mid-Late Ordovician age from the geologically complex Martinsburg Formation in central Pennsylvania. The fossils, which resemble specimens from Burgess Shale-type deposits, include enigmatic specimens (problematica) and phyllocarid arthropods (with preserved appendages) which are associated with graptolites. The locality is notable for preservation of a low diversity community of soft-bodied planktic animals, likely captured and rapidly buried by a turbidity current. The problematica lack sufficient anatomical detail for confident systematic placement; however, they can be superficially compared to a number of possible metazoans including: nominally/non- shelled mollusks (including veligers), cnidarians, lophophorates, or possibly aberrant tube-dwelling priapulids or polychaetes. Overall, the problematica may belong to one (or several) extinct clades or some unknown clade of animal life. The complex geologic history of the region has reduced the resolution of the problematica’s original exceptional preservation, yet the fossils retain many key features. Hence, this locality has implications for our understanding of exceptional preservation, its alteration over geological history, and the planktic communities of ‘‘The Great Ordovician Biodiversification Event’’ (GOBE) in the planktic real

Algae, calcitarchs and the Late Ordovician Baltic limestone facies of the Baltic Basin - Kröger, Björn; Penny, Amelia; Shen, Yuefeng; Munnecke, Axel (Facies, 2020)
The Late Ordovician succession of the Baltic Basin contains a characteristic fine-grained limestone, which is rich in calcareous green algae. This limestone occurs in surface outcrops and drill-cores in an extensive belt reaching from Sweden across the Baltic Sea to the Baltic countries. This limestone, which is known in the literature under several different lithological names, is described and interpreted, and the term “Baltic limestone facies” is suggested. The microfacies, from selected outcrops from the Åland Islands, Finland and Estonia, consists of calcareous green algae as the main skeletal component in a bioclastic mudstone-packstone lithology with a pure micritic matrix. Three types of calcitarch, which range in diameter from c. 100–180 μm, are common. Basinward, the youngest sections of the facies belt contain coral-stromatoporoid patch reefs and Palaeoporella-algal mounds. The Baltic limestone facies can be interpreted as representing the shallow part of an open-marine low-latitude carbonate platform.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Calcitarch; Dasycladacales; Lithographic limestone; Ordovician; Shallow-water carbonates

Allogenic succession in Late Ordovician reefs from southeast China: a response to the Cathaysian orogeny - Li, Qijian; Li, Yue; Kießling, Wolfgang (Estonian Journal of Earth Sciences, 2015)
Several Late Ordovician (late Katian) reef complexes are known from the border area of Jiangxi and Zhejiang provinces in southeast China. We studied two coral-stromatoporoid reefs exposed in the Xiazhen Formation at Zhuzhai (Yushan, Jiangxi). The reefs have a combined thickness of 7.4 m and are metazoan-dominated with most reef-builders in growth position. Stromatoporoids and tabulate corals constitute the framework of the reefs. Stromatoporoids (mostly Clathrodictyon) dominate the first unit and show a vertical increase in proportion and dominance from the middle part to the top of the unit, whereas tabulate corals (dominated by Catenipora and Agetolites) are the main reef-builders in the second unit where stromatoporoids are rare. We attribute this change to a greater tolerance of tabulate corals to turbidity, allowing them to thrive in the muddy facies of the upper unit. This facies change is probably related to the increasing terrestrial input from the northwestward expansion of the Cathaysian Land during the late Katian. The Cathaysian orogeny also led to a short-term exposure of the sea floor in the study area, which terminated the reef growth.
UnivIS-Import:2015-07-08:Pub.2015.nat.dgeo.IGM.LP.alloge
Keywords: Allogenic succession; Cathaysian orogeny; Coral-stromatoporoid reefs; Late Katian; Xiazhen Formation

Altered volcanic ashes in Palaeocene and Eocene sediments of the Eureka Sound Group (Ellesmere Island, Nunavut, Arctic Canada) - Reinhardt, Lutz; Estrada, Solveig; Andruleit, Harald; Dohrmann, Reiner; Piepjohn, Karsten; von Gosen, Werner; Davis, Donald W.; Davis, Bill (Zeitschrift der Deutschen Gesellschaft für Geowissenschaften, 2013)
Keywords: Smectite-bentonite; Crandallite; Bentonite geochronology; Mount Lawson Formation; Margaret Formation

A Maastrichtian microbial reef and associated limestones in the Roca Formation of Patagonia - Kießling, Wolfgang; Scasso, Roberto A.; Aberhan, Martin; Ruiz, Lucas; Weidemeyer, Sven (Fossil Record, 2006)
We describe a small microbial reef and associated limestones occurring in a Maastrichtian transgressive succession of mixed carbonate-siliciclastic lithologies at Sierra Huantraico near Chos Malal (Neuquén, Argentina). Strontium isotope data suggest that the reef is of earliest Maastrichtian age. The small reef (0.8 m thick, 2 m wide) is mostly composed of peloidal bindstone, dense stromatolite-cement crusts and thrombolite. Except for some ostracods, no metazoan fossils were found in the reef structure, although the majority of peloids are fecal pellets, probably of larger crustaceans. Small foraminifers with calcite tests and probable green algae have also been noted. Sedimentological data and fossils within and immediately above the reef suggest that the reef was formed in a transgressive systems tract under freshwater to brackish-water conditions. Limestones above the reef are serpulid-bryozoan packstones and intraclast-ooid grainstones. These limestones yield a mixture of typical non-tropical (common serpulids and bryozoans) and typical tropical aspects (common dasycladaceans and ooids). This mosaic is explained by salinity fluctuations, which in our case dominate over temperature in determining the grain associations. (© 2006 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IGM.LP.amaast
Keywords: Carbonate sedimentology; reef biology

A major anomaly in the carbon cycle during the late Cisuralian (Permian): Timing, underlying triggers and implications - Liu, Chao; Du, Yuansheng; Jarochowska, Emilia; Yan, Jiaxin; Munnecke, Axel; Lu, Gang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2018)
Keywords: Kungurian; Mass-balance calculation; Methane; Negative excursion; Organic carbon isotopes

A mild and efficient procedure for alkenols oxyselenocyclization by using ionic liquids - Kostic, Marina; Verdia, Pedro; Fernandez-Stefanuto, Veronica; Puchta, Ralph; Tojo, Emilia (Journal of Physical Organic Chemistry, 2019)
A mild and efficient procedure for the oxyselenocyclization of unsaturated alcohols by treatment with phenylselenyl chloride using ionic liquids as solvents/catalyzers has been developed. The reaction proceeds instantaneously under mild conditions with absolute regioselectivity, using primary, secondary, tertiary, and aromatic alcohols, as well as monosubstituted, disubstituted, and trisubstituted alkenols. This procedure provides a new method for the synthesis of substituted tetrahydrofurans and tetrahydropyrans ethers, the precursors of many biologically active metabolites, avoiding the use of toxic and corrosive catalysts. There are no previous reports of selenium-mediated cyclofuncionalization reactions in ionic liquids. Taking into the account the good results obtained with [MMIM][MSO 4 ], its ease preparation, low viscosity, low price, and its capacity to be recovered and reused, it was selected as the solvent/catalyzer. Quantum-chemical calculations (MP2(fc)/6-311 + G**//B3LYP/6-311 + G**) has shown that the intramolecular cyclization is promoted by the hydrogen bond formed between the ionic liquid anion and the hydroxyl group of the alkenol.
CRIS-Team Scopus Importer:2019-05-02
Keywords: catalysis; ionic liquids; oxyselenocyclization; quantum-chemical calculations; sustainable chemistry

Ammonites from the latest Aalenian-earliest Bathonian of La Baume (Castellane area, SE France): palaeontology and biostratigraphy - de Baets, Kenneth; Cecca, Fabrizio; Guiomar, Myette; Verniers, Jacques (Swiss Journal of Geosciences, 2008)
Middle Jurassic strata are naturally exposed around the village called La Baume, near Castellane (Alpes de Haute Provence, SE France). We have realized both a detailed log and a bed-by-bed sampling for ammonite biostratigraphy in a 68 metres thick succession of subpelagic marls and limestones ("Calcaires A Zoophycos") that spans the Middle Jurassic from uppermost Aalenian to lowermost Bathonian. The subpelagic succession can be roughly subdivided into three members. Ammonites from the Upper Aalenian Concavum Zone, all Lower Bajocian Zones (Discites Zone, Laeviuscula Zone including Ovale Subzone, Humpriesianum Zone), one Upper Bajocian Zone (Parkinsoni Zone) and probably one lower Bathonian Zone (Zigzag Zone) were found. A major gap of both the Niortense Zone and the Garantiana Zone, which was not previously described, was detected at the boundary between members 2 and 3. The main palaeontological interest of the ammonite fauna from La Baume is the richness and diversity of the family Sonniniidae, which is the subject of a systematic study and figurated along with some biostratigraphically significant forms. Biostratigraphical results and open problems are discussed.
Keywords: ammonites; Aalenian-Bathonian interval; France; biodiversity; taxonomy; biostratigraphy

Ammonoideen und Gastropoden aus dem Oberen Toarcium und Unteren Aalenium der Tongrube Mistelgau (Frankenalb) - Schulbert, Christian; Nützel, Alexander (Programm und Kurzfassungen, 2002)
UnivIS-Import:2015-04-16:Pub.2002.nat.dgeo.IGM.LP.ammono

Ammonoid Embryonic Development - de Baets, Kenneth; Landman, Neil; Tanabe, Kazushige (Ammonoid Paleobiology: From anatomy to ecology, 2015)

Ammonoid Intraspecific Variability - de Baets, Kenneth; Bert, Didier; Hoffmann, René; Monnet, Claude; Yacobucci, Margaret M.; Klug, Christian (Ammonoid Paleobiology: From anatomy to ecology, 2015)

Ammonoid Paleobiology: From anatomy to ecology - Klug, Christian; Korn, Dieter; de Baets, Kenneth; Kruta, Isabelle; Mapes, Royal H. (Springer, 2015)
This two-volume work is a testament to the abiding interest and human fascination with ammonites. We offer a new model to explain the morphogenesis of septa and the shell, we explore their habitats by the content of stable isotopes in their shells, we discuss the origin and later evolution of this important clade, and we deliver hypotheses on its demise. The Ammonoidea produced a great number of species that can be used in biostratigraphy and possibly, this is the macrofossil group, which has been used the most for that purpose. Nevertheless, many aspects of their anatomy, mode of life, development or paleobiogeographic distribution are still poorly known. Themes treated are biostratigraphy, paleoecology, paleoenvironment, paleobiogeography, evolution, phylogeny, and ontogeny. Advances such as an explosion of new information about ammonites, new technologies such as isotopic analysis, tomography and virtual paleontology in general, as well as continuous discovery of new fossil finds have given us the opportunity to present a comprehensive and timely "state of the art" compilation. Moreover, it also points the way for future studies to further enhance our understanding of this endlessly fascinating group of organism

Ammonoid Paleobiology: From macroevolution to paleogeography - Klug, Christian; Korn, Dieter; de Baets, Kenneth; Kruta, Isabelle; Mapes, Royal H. (Springer, 2015)
This two-volume work is a testament to the abiding interest and human fascination with ammonites. We offer a new model to explain the morphogenesis of septa and the shell, we explore their habitats by the content of stable isotopes in their shells, we discuss the origin and later evolution of this important clade, and we deliver hypotheses on its demise. The Ammonoidea produced a great number of species that can be used in biostratigraphy and possibly, this is the macrofossil group, which has been used the most for that purpose. Nevertheless, many aspects of their anatomy, mode of life, development or paleobiogeographic distribution are still poorly known. Themes treated are biostratigraphy, paleoecology, paleoenvironment, paleobiogeography, evolution, phylogeny, and ontogeny. Advances such as an explosion of new information about ammonites, new technologies such as isotopic analysis, tomography and virtual paleontology in general, as well as continuous discovery of new fossil finds have given us the opportunity to present a comprehensive and timely "state of the art" compilation. Moreover, it also points the way for future studies to further enhance our understanding of this endlessly fascinating group of organism

An 11-yr exclosure experiment in a high-elevation island ecosystem: Introduced herbivore impact on shrub species richness, seedling recruitment and population dynamics - Irl, Severin; Steinbauer, Manuel; Babel, Wolfgang; Beierkuhnlein, Carl; Blume-Werry, Gesche; Messinger, Jana; Palomares Martínez, Angel; Strohmeier, Stefan; Jentsch, Anke (Journal of Vegetation Science, 2012)
Questions: Do introduced herbivores and fire explain the mono-dominance of one legume shrub (Adenocarpus viscosus subsp. spartioides) above the tree line on an oceanic island, given the fact that a number of other legume shrub species are potentially present? What drives the observed landscape-scale life–death pattern within the mono-dominant shrub species population? Location: The sub-alpine scrub vegetation of La Palma (Canary Islands, Atlantic Ocean). Methods: An 11-yr exclosure experiment with sites distributed along an elevation and orientation gradient was used to identify the influence of introduced herbivore pressure on four endemic shrub species and their seedling recruitment. Further, we assessed the population dynamics and spatial pattern of the dominant shrub species A. viscosus subsp. spartioides. Habitat and vitality characteristics were investigated, assessing spatial topographic features and tree ring-based age estimates. Linear mixed models, ANOVAs, linear regression and variation partitioning were used as statistical analysis tools. Results: Outside of the exclosures A. viscosus subsp. spartioides was virtually mono-dominant in the study area, even though other shrub species seem better suited in the absence of introduced herbivores. The presence of introduced herbivores significantly reduced seedling recruitment within all target species, except for A. viscosus subsp. spartioides. Mean age of A. viscosus subsp. spartioides increased with elevation, although vitality analyses indicated that the sub-alpine scrub is elevated above its growth optimum. Three out of four investigated shrub species showed differences in growth height depending on elevation and island orientation. Conclusion: Introduced herbivores and fire are identified as key disturbances enhancing the occurrence of A. viscosus subsp. spartioides, a commonly less competitive species. However, Genista benehoavensis, a single island endemic shrub species, seems to be better adapted to the harsh climate conditions of the sub-alpine scrub in the absence of introduced herbivores than any other shrub species.
Keywords: Alien herbivore; Canary Islands; Competition; European rabbit; Fenced plots; Invasive mammals; Legume shrub; Oceanic island; Shrub community; Summit scrub

An acid-free method of microfossil extraction from clay-rich lithologies using the surfactant Rewoquat - Jarochowska, Emilia; Tonarová, Petra; Munnecke, Axel; Ferrová, Lenka; Sklenář, Jan; Vodráková, Stanislava (Palaeontologia Electronica, 2013)
Marine rocks characterized by high clay content provide excellent conditions for fossil preservation, particularly for organic-walled microfossils such as retiolitid graptolites and chitinozoans. Nevertheless, the phyllosilicate minerals, which constitute the clay component, make microfossil extractions difficult. The problem results from the tendency of phyllosilicates to form aggregates in low pH values, as standard methods of microfossil extraction employ acids for rock digestion. Consequently, the use of acids for clay-rich rocks is often inefficient and time-consuming. We propose a method of rock disintegration using the surfactant Rewoquat and compare it with two commonly applied approaches: digestion in buffered acetic acid and in HCl-HF. Using examples from the Mulde Brick-clay Member from the Silurian of Gotland and the Daleje Shale from the Devonian of the Prague Basin we observed that disintegration in Rewoquat was faster (days) than digestion in acid (months), and allowed to recover calcareous in addition to organic-walled fossils. The yield and preservation was comparably good, except for conodonts, which were strongly etched after using HCl-HF. Retiolitid graptolites recovered using Rewoquat were preserved in 3D and showed a lower degree of fragmentation. The fossil content of the residue obtained using Rewoquat was higher due to dispersion of clay aggregates. For observation of delicate fossils we recommend to coat the sample with the surfactant. Application of Rewoquat can reveal the most delicate forms and growth stages, and thus provide a better insight into the ontogeny, autecology, and body size distributions of a number of fossil groups. © Paleontological Society November 2013.
UnivIS-Import:2015-04-14:Pub.2013.nat.dgeo.IGM.LP.anacid
Keywords: Acid digestion; Calcareous; Clay dispersion; Fossils; Microfossils; Organic-walled; Phosphatic; Three-dimensional preservation

Analysis of septal spacing and septal crowding in Devonian and Carboniferous ammonoids - Beck, Sophie Marie; de Baets, Kenneth; Klug, Christian; Korn, Dieter (Swiss Journal of Palaeontology, 2021)
Septal crowding is widely known as a sign of maturity in conchs of ammonoids and nautiloids. However, reduced septal spacing may also occur as a consequence of adverse ecological conditions. Here, we address the question how septal spacing varied through ontogeny in representatives of some of the major clades of Devonian and Carboniferous ammonoids. We found that the degree of ontogenetic variation is similar between clades and that variation is only weakly linked with conch form. The results show that septal crowding alone is insufficient to identify adulthood in ammonoids; intermediate septal crowding is a common phenomenon and occurs in various growth stages. Changes in septal distances during ontogeny were, in addition to adulthood of the individuals, a passive reaction likely caused by fluctuating environmental conditions.
Keywords: Ammonoidea; Devonian; Carboniferous; Septal distances; Ontogeny

An assessment of the suitability of individual rhythmic carbonate successions for astrochronological application - Westphal, Hildegard; Hilgen, Frits; Munnecke, Axel (Earth-Science Reviews, 2010)
A manual is presented to assist in assessing the suitability of individual calcareous rhythmites for high-resolution stratigraphic applications and orbital dating. While the astrochronological approach offers an unprecedented high temporal resolution for stratigraphy, caution is required to carefully choose suitable rhythmites for the analysis. Diagenesis is known to distort or mimic primary signals in particular in carbonate rhythmites. To keep orbital dating a reliable method, the choice of sedimentary successions has to be undertaken with utmost scrutiny. Here, we review and evaluate the methods that have been used for assessing the record of primary signals in calcareous rhythmites. The goal is to provide the orbital stratigrapher with tools for a straightforward and systematic assessment of such successions. © 2010 Elsevier B.
Keywords: Astrochronology; Chronostratigraphy; Climate archive; Differential diagenesis; GSSP; Orbital forcing

Ancestry, Origin and Early Evolution of Ammonoids - Klug, Christian; Kröger, Björn; Vinther, Jakob; Fuchs, Dirk; de Baets, Kenneth (Ammonoid Paleobiology: From macroevolution to paleogeography, 2015)

Ancient Reef Traits, a database of trait information for reef-building organisms over the Phanerozoic - Raja Schoob, Nussaibah Begum; Dimitrijevic, Danijela; Krause, Mihaela Cristina; Kießling, Wolfgang (Scientific Data, 2022)
Trait-based approaches are increasingly relevant to understand ecological and evolutionary patterns. A comprehensive trait database for extant reef corals is already available and widely used to reveal vulnerabilities to environmental disturbances including climate change. However, the lack of similar trait compilations for extinct reef builders prevents the derivation of generalities from the fossil record and to address similar questions. Here we present the Ancient Reef Traits Database (ARTD), which aims to compile trait information of various reef-building organisms in one single repository. ARTD contains specimen-level data from both published and unpublished resources. In this first version, we release 15 traits for 505 genera and 1129 species, comprising a dataset of 17,841 trait values of Triassic to mid-Holocene scleractinian corals, the dominant reef-builders in the modern ocean. Other trait data, including for other reef-building organisms, are currently being collated.
CRIS-Team WoS Importer:2022-07-29

An early Hettangian coral reef in southern France: Implications for the end-Triassic reef crisis - Kießling, Wolfgang; Roniewicz, Ewa; Villier, Loic; Léonide, Philippe; Struck, Ulrich (Palaios, 2009)
The oldest known Jurassic coral reef is exposed in the Ardche region of southern France. This reef site, consisting of at least three reefal bodies, is of early Hettangian age and thus immediately postdates the end-Triassic mass extinction, which is well known for its catastrophic effect on reef building. Bulk carbonate carbon isotopes of the limestones below the reef are likely to record environmental perturbations subsequent to the mass extinction. The main reef is surprisingly well developed (20 m in thickness, 200 m in lateral extent) and composed of at least four genera and six species of coralsnot only holdover genera from the Triassic, but also one newly evolved genus (Phacelophyllia), contributed to reef construction. Just like their latest Triassic counterparts, the reef is dominated by phaceloid corals with a considerable contribution of microbialite. The reef predates similarly well developed structures by almost ten million years. The shelf setting of the reef renders it unlikely that refuges around oceanic islands are needed to explain survival of corals across the end-Triassic mass extinction. © 2009 SEPM (Society for Sedimentary Geology).
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.anearl

Anetoceratinae (Ammonoidea, Early Devonian) from the Eifel and Harz Mountains (Germany), with a revision of their genera - de Baets, Kenneth; Klug, Christian; Korn, Dieter (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2009)
"Cyrtoceratites arduennensis", one of the stratigraphically oldest ammonoids and type species of the ambiguously defined genus Anetoceras, was first described from the Eifel Mountains. It has been misinterpreted several times and is here re-described, based on the holotype and additional material from the type area. Anetoceras arduennense (STEININGER, 1853) has a crioconical conch with whorls almost touching the preceding volution. The revision of the subfamily Anetoceratinae leads to the result that only five genera (Metabactrites, Borivites, Ivoites gen. Nov. as a replacement name for Teneroceras, Anetoceras, and Erbenoceras) can be regarded valid, which probably represent a phyletic series.
Keywords: Emsian; Agoniatitina; systematics; Germany; coiling; morphometrics

A new Early Jurassic gastropod from Ellesmere Island, Canadian Arctic – one of the oldest known holoplanktonic gastropods - Nützel, Alexander; Schneider, Simon; Hülse, P; Kelly, SRA; Teichert, Sebastian; Veit, R (Jahrestagung der Paläontologischen Gesellschaft, 2015)

A new interpretation of the sedimentary cover in the western Siljan Ring area, central Sweden, based on seismic data - Juhlin, Christopher; Sturkell, Erik; Ebbestad, Jan Ove; Lehnert, Oliver; Högström, Annette E. S.; Meinhold, Guido (Tectonophysics, 2012)
Two new reflection seismic profiles over the Paleozoic successions of the western part of the Siljan Ring impact structure show a contrasting seismic signature. The more southerly c. 10. km long Mora profile reveals a highly disturbed structure, with only a few kilometers of relatively horizontally layered structures observed. However, interpretations of refracted arrivals in the data, that can be correlated to reflections, indicate the Silurian clastic rocks to be about 200. m thick in the central part of the profile. Weak reflections from about 600. m depth suggest a 400. m thick Ordovician limestone sequence to be present. Cores from the area show a mainly shale lithology for the Silurian and only a thin sequence of Ordovician strata, suggesting a rapid thickening of the Ordovician towards the north. On the more northern c. 12. km Orsa profile clear reflections from the Paleozoic successions are seen along the entire profile, except on the southernmost few kilometers. Based on interpretations of refracted arrivals, the Silurian succession appears to be considerably thinner here, and possibly absent at some locations. The Ordovician is also interpreted to be thinner in this area, with a maximum thickness of about 200-300. m along most of the profile. A deeper reflection from about 2. km within the crystalline basement may represent a dolerite sill. The lack of clear basement reflections on the Mora profile can be attributed to near-surface conditions and the acquisition geometry. The seismic data and recent coring in the area suggest the presence of a deeper paleo-basin towards the southwest with significantly more shales being deposited and the Paleozoic successions being severely disturbed. The shallow coring and seismic data will help form the basis for locating future boreholes for deeper drilling to study impact processes and the Paleozoic evolution of central Sweden. © 2012 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LG.anewin
Keywords: Borehole; Impact crater; Ordovician; Reflection seismic; Refraction seismic; Silurian

A new look at ancient reefs - Flügel, Erik; Kießling, Wolfgang (Phanerozoic reef patterns, 2002)
UnivIS-Import:2015-04-20:Pub.2002.nat.dgeo.IGM.LP.anewlo

A new name for Triassic algal species Solenopora concentrica Senowbari-Daryan, Link & Isintek 2006 - Senowbari-Daryan, Baba; Link, Michael; Isintek, Ismail (Facies, 2007)
The Triassic algal species Solenopora concentrica Senowbari-Daryan, Link & Isintek (2006) is renamed to S. isoconcentrica.
UnivIS-Import:2015-04-14:Pub.2007.nat.dgeo.IGM.LP.anewna
Keywords: Triassic; Anisian; Karaburun; Turkey; Algae; Solenopora concentrica; Isoconcentrica

A new Pycnodontid (Actinopterygii) in the late Jurassic of the Solnhofen Archipelago - Kölbl-Ebert, Martina; Ebert, Martin; Schulbert, Christian (Research & Knowledge, 2017)
Pycnodontiformes are an extinct order of Actinopterygian fi shes, present from the Late Triassic (Norian) to the Eocene. With their mostly deep, laterally compressed bodies and comparatively large fi ns, these fi shes were mostly highly manoeuvrable reef fi sh. The genus Macromesodon Blake, 1905 (sensu Poyato-Ariza and Wenz, 2004) is divided again in the genus Macromesodon, with Macromesodon macropterus (Agassiz, 1834) as the only species and the genus Apomesodon Poyato-Ariza and Wenz, 200
Keywords: Fossil Fish; Pycnodontiformes; Late Jurassic; Solnhofen Archipelago

A new species of Conchicolites (Cornulitida, Tentaculita) from the Wenlock of Gotland, Sweden - Vinn, Olev; Jarochowska, Emilia; Munnecke, Axel (Estonian Journal of Earth Sciences, 2014)
A new cornulitid species, Conchicolites crispisulcans sp. nov., is described from the Wenlock of Gotland, Sweden. The undulating edge of C. crispisulcans sp. nov. peristomes is unique among the species of Conchicolites. This undulating peristome edge may reflect the position of setae at the tube aperture. The presence of the undulating peristome edge supports the hypothesis that cornulitids had setae and were probably related to brachiopods.
UnivIS-Import:2015-04-14:Pub.2014.nat.dgeo.IGM.LP.anewsp_5
Keywords: Baltica; Cornulitids; Silurian; Tentaculitoids; Tubeworms

A new species of Tiaracrinus from the latest Emsian of Morocco and its phylogeny - Klug, Christian; de Baets, Kenneth; Naglik, Carole; Waters, Johnny A. (Acta Palaeontologica Polonica, 2014)
We describe a new species of the unusual crinoid Tiaracrinus, T jeanlemenni sp. nov. from the latest Emsian of the famous mudmound locality Hamar Laghdad, Morocco. It differs from the previously known species in the higher number of ribs and the vaulted rib-fields, which is corroborated by the comparison of simple quantitative characters and ratios as well as by the results of a cluster analysis and a Principal Component Analysis. Based on the new material and the published specimens, we discuss the phylogeny of the genus and suggest that T oehlerti and T moravicus represent the ancestral forms of this small clade.
Keywords: Crinoidea; mudmounds; phylogeny; morphometry; symmetry; Devonian; Morocco

A new subdisarticulated machaeridian from the Middle Devonian of China: Insights into taphonomy and taxonomy using X-ray microtomography and 3D-analysis - Gügel, Benjamin; de Baets, Kenneth; Jerjen, Iwan; Schuetz, Philipp; Klug, Christian (Acta Palaeontologica Polonica, 2017)
Machaeridians are an extinct group of armoured annelids, which are mainly known from isolated sclerites present from the Ordovician to the Permian. Based on articulated specimens with preserved soft-tissues and trace fossils, derived machaeridians are interpreted to have an infaunal burrowing mode of life. However, the taphonomy of sclerite associations is still largely unstudied. We herein investigated associated sclerites from the Middle Devonian of China using micro-computer tomography and 3D-analysis. These sclerites belong to a single individual and lie in close proximity. The absence of indications for current alignment, major bioturbation or other processes causing a disarticulation as reflected in the randomly arranged dacryoconarids suggest that the sclerites became disarticulated in the course of the normal decay processes, perhaps aided by scavenging and incomplete burial. The unique morphology of the sclerites indicates that the specimen presented here belongs to a previously undescribed species, which we describe herein as Lepidocoleus kuangguoduni sp. nov.
Keywords: Annelida; Lepidocoleidae; tomography; SPIERS; taphonomy; Devonian; China; Guangxi

A new thalamid sponge from the Upper Triassic (Norian) reef limestones of the Antalya region (Turkey) - Senowbari-Daryan, Baba; Link, Michael (Acta Geologica Hungarica, 1998)
The small thalamid sponge Discosiphonella minima n. sp. is described from four reef block samples at three different localities near Antalaya (southern Turkey). The relationship between Paleozoic and Upper Triassic representatives of Discosiphonella are discussed.
Keywords: Systematic Paleontology; Sponges; Sphinctozoa; Discosiphonella; Upper Triassic; Norian; Antalya; Turkey

A new upper Middle Ordovician–Lower Silurian drillcore standard succession from Borenshult in Östergötland, southern Sweden: 1. Stratigraphical review with regional comparisons - Bergström, Stig M.; Calner, Michael; Lehnert, Oliver; Noor, Amir (Gff, 2011)
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LG.anewup

An exceptionally preserved Carboniferous faunal assemblage from the Buckhorn Asphalt Lagerstätte (Oklahoma, USA) - Seuß, Barbara; Wisshak, Max; Nützel, Alexander; Schulbert, Christian (Annual Meeting of the Paläontologische Gesellschaft,, 2008)
The Pennsylvanian Buckhorn Asphalt Quarry in Oklahoma (USA) is an Impregnation Lagerstätte containing the best-preserved Palaeozoic mollusc fauna in the world. Besides preserved Mg-calcite, microstructures, and early ontogenetic shells, it is the only Late Palaeozoic Lagerstätte with conservation of original aragonite known to date. The outstanding preservation is due to an early impregnation by migrating hydrocarbons intruding the mixed siliciclastic-carbonatic sediments of the Buckhorn Asphalt. Deposition took place during a transgressive-regressive cycle near the coast – indicated by landplant remains and high siliciclastic input. The sediments comprise coarse conglomerates to mudstones, and shell beds. Some sediments in the quarry were probably deposited by mass flows, while others are more or less autochthounous. In total the shelly invertebrate fauna comprises more than 155 species and about 120 genera which is unusual for Late Palaeozoic deposits. This corroborates that aragonite dissolution produces a major bias in the fossil record. However, most mollusc genera in the Buckhorn Asphalt Lagerstätte are known as replaced shells from other Pennsylvanian deposits. According to this the preservation bias via dissolution might be overestimated. The fauna is dominated by molluscs, especially gastropods with more than 50 genera, cephalopods, and bivalves. The faunal assemblage is complemented by foraminiferans, ostracodes, bryozoans, brachiopods, and further fossils in smaller amounts like vertebrate and echinoderm remains. Chaetetids represent the largest benthic macro-organisms at the top of the regressive intervals. The preservation of planktotrophic larval shells indicates a high primary production in the ocean waters of the Buckhorn area - an important information, as remains of producer organisms are generally scarce in Late Palaeozoic deposits. The biodiversity of endolithic biota, as indirectly recorded by bioerosion ichnotaxa in the shells, reveals a total of 18 known ichnospecies and the new ichnotaxon Aurimorpha varia, reflecting the most diverse Palaeozoic microboring assemblage known to date. The ichnocoenosis is dominated by Eurygonum nodosum, Scolecia filosa, and Fascichnus dactylus (all of them are cyanobacterial traces). Further traces are e.g. Fascichnus frutex, Planobola macrogata, and Cavernula coccidia. 17 out of 19 reported ichnospecies are known to neoichnology and are present in similar ichnocoenosis of Recent shallow-euphotic seas showing the longevity of microedolithic taxa and therefore their value as palaeoenvironmental indicators. 2/3 of the recorded ichnotaxa were reported for the first time from the Carboniferou

An island view of endemic rarity—Environmental drivers and consequences for nature conservation - Irl, Severin; Schweiger, Andreas; Medina, Felix; Fernández-Palacios, José Maria; Harter, David; Jentsch, Anke; Provenzale, Antonello; Steinbauer, Manuel; Beierkuhnlein, Carl (Diversity and Distributions, 2017)
Aim: Rarity—an important measure for conservation biogeography—can vary over many orders of magnitude. However, it is unclear which regional-scale abiotic conditions drive processes affecting rarity of endemic species on islands. To support conservation efforts, we (1) assess the main abiotic drivers of endemic rarity, (2) determine how well existing protected areas (PAs) coincide with hotspots of endemic rarity and (3) introduce and evaluate a new hypervolume-based rarity estimator. Location: La Palma (Canary Islands).   Methods: We recorded all present endemic vascular plant species in 1,212 plots covering the entire island. We calculated endemic rarity (corrected range-rarity richness for endemics) using a rarity estimation approach based on kernel density estimations (hypervolume approach). We performed a sensitivity analysis based on multiple linear regressions and relative importance estimations of environmental drivers to estimate the performance of the hypervolume-based rarity estimation compared to standard methods (occurrence frequency, convex hulls, alpha hulls).   Results: Climate variables (mean annual temperature, climatic rarity, precipitation variability) best explained archipelago endemic (AE) and single-island endemic (SIE) rarity. Existing PAs covered the majority of AE and SIE rarity, especially national and natural parks as well as the Natura 2000 sites. In our study system, hypervolumes performed better than standard measures of range size.   Main conclusion: Both AE and SIE rarity on La Palma show a clear spatial pattern, with hotspots of endemic rarity found at high elevations and in rare climates, presumably owing to geographical and climatic constraints and possibly anthropogenic pressure (e.g., land use, introduced herbivores, fire). Areas of high rarity estimates coincide with the distribution and extent of PAs on La Palma, especially since the recent addition of the Natura 2000 sites. The hypervolume approach is a promising tool to estimate species range sizes, and can be applied on all scales where point/plot data are available.
Keywords: conservation biogeography; corrected weighted endemism; endemic plant species; evolutionary pattern; hypervolume; island ecology; Natura 2000; protected areas

A novel dendroecological method finds a non-linear relationship between elevation and seasonal growth continuity on an island with trade wind-influenced water availability - Weigel, Robert; Irl, Severin; Treydte, Kerstin; Beierkuhnlein, Carl; Berels, Johanna; Field, Richard; Miranda, José Carlos; Steinbauer, Alana; Steinbauer, Manuel; Jentsch, Anke (AoB Plants, 2019)
Climatic seasonality drives ecosystem processes (e.g. productivity) and influences plant species distribution. However, it is poorly understood how different aspects of seasonality (esp. regarding temperature and precipitation) affect growth continuity of trees in climates with low seasonality because seasonality is often only crudely measured. On islands, exceptionally wide elevational species distribution ranges allow the use of tree rings to identify how growth continuity and climate–growth relationships change with elevation. Here we present a novel dendroecological method to measure stem growth continuity based on annual density fluctuations (ADFs) in tree rings of Pinus canariensis to indicate low climatic seasonality. The species ranges from 300 to more than 2000 m a.s.l. on the trade wind-influenced island of La Palma (Canary Islands), where we measured three decades of tree-ring data of 100 individuals distributed over ten sites along the entire elevational range. The successfully implemented ADF approach revealed a major shift of stem growth continuity across the elevational gradient. In a remarkably clear pattern, stem growth continuity (percentage of ADFs) showed a hump-shaped relationship with elevation reaching a maximum at around 1000 m a.s.l.. Low- to mid-elevation tree growth was positively correlated with the Palmer Drought Severity Index PDSI (indicating aridity) and sea surface temperature (indicating trade wind-influenced moderation of water supply), while high elevation tree growth was positively correlated with winter temperature (indicating a cold induced dormancy period). We conclude that ADFs are a useful method to measure stem growth continuity in low-seasonality climates. Growth of Pinus canariensis on the Canary Islands is more frequently interrupted by winter cold at high elevations and by summer drought at low elevations than in the trade wind-influenced mid elevations, where growth sometimes continues throughout the year. Climate change-associated alterations in trade wind cloud formation might cause non-analogue growth limitations for many unique island specie

Antarctic Bioconstructional Bryozoans from Terra Nova Bay (Ross Sea): Morphology, Skeletal Structures and Biomineralization - Lombardi, Chiara; Kuklinski, Piotr; Spirandelli, Edoardo; Bruzzone, Giorgio; Raiteri, Giancarlo; Bordone, Andrea; Mazzoli, Claudio; López Correa, Matthias; van Geldern, Robert; Plasseraud, Laurent; Thomas, Jérôme; Marin, Frederic (Minerals, 2023)
Among Antarctic bryozoans, some species are able to develop calcitic bioconstructions promoting habitat complexity, but the processes leading to biomineral formation are mostly unknown. The present work investigated three Antarctic bryozoans, from morphological to skeletal features, including the organic matrix associated with the skeleton (SOM). Cellarinella nutti Rogick, 1956 and Reteporella frigida Waters, 1904 were collected in November 2018 from a shallow site (25 m) and Cellarinella njegovanae Rogick, 1956 from a deep site (110 m) at Terra Nova Bay (Ross Sea, Antarctica). Both Cellarinella species showed 5–6 “growth check lines” (gcl) on their laminae. The morphometrical characterization conducted on the growth bands (gb) and zooids, within the band across bands, revealed a variability in length with time (C. nutti: from 4099 µm for gb1 to 1449 µm for gb6; C. njegovanae: from 1974 µm for gb 3 to 7127 µm for gb2). Zooid length varied within gb, from the proximal to the distal part of the bands, but differences also occurred across bands. The shortest zooids ( 625 µm) were found at the proximal part and the longest ( 1190 µm) in the middle part of the gb in C. nutti, whereas in C. njegovanae the shortest zooids ( 660 µm) were found in the distal part and the longest ( 1190 µm) in the proximal part of the gb. Micro-CT analyses indicated the ratio of basal zooidal walls (RbwT gcl/gb) ranged from 3.0 to 4.9 in C. nutti and from 2.3 to 5.9 in C. njegovanae, whereas Reteporella frigida did not form any gcl on either side of the colony. Preliminary characterizations of the SOM for the three species evidenced a mixture of proteins and polysaccharides with properties similar to those of better-known biominerals, in terms of quantity and electrophoretic behavior. In addition, a “lectin fingerprint” has been established for the first time in bryozoans, displaying the presence of chitin or chitin-related saccharides. Understanding the complexity of the processes regulating skeleton formation is a key aspect in comprehending the adaptation of bioconstructional ecosystems and the survival of the associated biodiversity under the future ocean
Keywords: Bryozoa; Antarctica; calcifying ecosystem; growth check lines; zooid morphometrics; skeletal organic matrix (SOM); seawater stable isotopes; climate change

An unusual microbial-rostroconch assemblage from the Mulde Event (Homerian, middle Silurian) in Podolia, Western Ukraine - Jarochowska, Emilia; Munnecke, Axel; Kozłowski, Wojciech (GFF, 2014)
The Homerian (middle Silurian) Mulde Event is an extinction event affecting hemipelagic organisms associated with a positive stable carbon isotope excursion, and an increased proliferation of microbial deposits. The Event is recorded in the Bagovytsya section (Podolia, Ukraine), representing a carbonate ramp setting in the East European Craton, and recording the δ13Ccarb excursion with values reaching +5.17%. The associated facies include oncolitic beds, mud-mounds and thrombolitic buildups dominated by cyanobacteria and microproblematica with proposed bacterial affinities. The associated faunal assemblage includes a high proportion of rostroconchs and abundant gastropods and trilobites. The co-occurrence of grazing organisms and microbial sediments suggests that the microbial preservation was not caused by decreased grazing rates. © 2014 © 2014 Taylor & Francis.
UnivIS-Import:2015-04-14:Pub.2014.nat.dgeo.IGM.LP.anunus
Keywords: anachronistic facies; Baltica; carbon isotope excursion; East European Craton; lundgreni event; oncoids

A Paleobiology Database szerepe a modern őslénytani kutatásban - Kocsis, Ádám; Pálfy, József; Sághi, Kristóf (Foldtani Kozlony, 2015)

Aphanitic buildup from the onset of the Mulde Event (Homerian, middle Silurian) at Whitman's Hill, Herefordshire, UK: ultrastructural insights into proposed microbial fabrics - Päßler, Jan-Filip; Jarochowska, Emilia; Ray, David C.; Munnecke, Axel; Worton, Graham J. (Estonian Journal of Earth Sciences, 2014)
A microbial origin has been proposed for matrix-supported, low-diversity buildups reported from different palaeocontinents during the onset of the Mulde positive carbon isotope excursion. We have investigated a small aphanitic buildup from the Lower Quarried Limestone Member of the Much Wenlock Limestone Formation, exposed at Whitman’s Hill (Herefordshire), corresponding to the central part of the Midland Platform (UK). Up to 50% of the rock volume in this buildup consists of mottled micrite. The SEM studies revealed that the micrite is largely detrital and does not show features characteristic of calcareous cyanobacteria or leiolites. The aphanitic character of the buildup is suggested to be controlled by the depositional rate, and the widespread occurrence of matrix-supported reefs in this interval to be driven by a mid-Homerian rapid eustatic transgression.
UnivIS-Import:2015-04-14:Pub.2014.nat.dgeo.IGM.LP.aphani
Keywords: Automicrite; Lower Quarried Limestone Member; Midland Platform; Much Wenlock Limestone Formation; Oncoids; Wenlock Series

A Piranha-like pycnodontiform fish from the Late Jurassic - Kölbl-Ebert, Martina; Ebert, Martin; Bellwood, David R.; Schulbert, Christian (Current Biology, 2018)
Pycnodontiformes are an extinct order of ray-finned fishes from the Triassic to Eocene [1, 2], with a characteristic crushing dentition reflecting a highly specialized diet [3]. However, our discovery of a new pycnodontiform from the Late Jurassic (ca. 152 Ma) Plattenkalk deposits of the Solnhofen Archipelago revealed long, pointed teeth along the vomer and triangular teeth with cutting edges along the prearticulars. This is the earliest evidence of specialized flesh cutting in a ray-finned fish. The dentition pattern, tooth shape, jaw morphology, and mechanics are all indicative of a feeding apparatus suitable for slicing flesh or fins, thus pioneering a new ecological niche. Evidence suggests that it may have exploited aggressive mimicry in a striking parallel to the feeding patterns of modern piranha. Remarkably, fossil fishes recovered from the same deposits as the new pycnodontiform show injuries to fins and fin bases. As a marine piranha-like fish contemporary with dinosaurs, it is the oldest known flesh-eating actinopterygian, revealing remarkable convergent evolution with modern piranhas. Kölbl-Ebert et al. describe a new pycnodontiform fish, Piranhamesodon pinnatomus, from the Jurassic. It has specialized morphological features for cutting flesh, including piranha-like teeth. As a marine fish contemporary with dinosaurs, it is the oldest known flesh-eating ray-finned fish, exhibiting remarkable convergent evolution with piranhas.
UnivIS-Import:2019-08-15:Pub.2018.nat.dgeo.IGM.LP.apiran
Keywords: aggressive mimicry; convergent evolution; functional morphology; Late Jurassic; marine fishes; piranha-like dentition; Piranhamesodon; predation; Pycnodontiformes; Solnhofen Archipelago

A possible link between coral reef success, crustose coralline algae and the evolution of herbivory - Teichert, Sebastian; Steinbauer, Manuel; Kießling, Wolfgang (Scientific Reports, 2020)
Crustose coralline red algae (CCA) play a key role in the consolidation of many modern tropical coral reefs. It is unclear, however, if their function as reef consolidators was equally pronounced in the geological past. Using a comprehensive database on ancient reefs, we show a strong correlation between the presence of CCA and the formation of true coral reefs throughout the last 150 Ma. We investigated if repeated breakdowns in the potential capacity of CCA to spur reef development were associated with sea level, ocean temperature, CO2 concentration, CCA species diversity, and/or the evolution of major herbivore groups. Model results show that the correlation between the occurrence of CCA and the development of true coral reefs increased with CCA diversity and cooler ocean temperatures while the diversification of herbivores had a transient negative effect. The evolution of novel herbivore groups compromised the interaction between CCA and true reef growth at least three times in the investigated time interval. These crises have been overcome by morphological adaptations of CCA.

Aragonite calcite sea effects on calcifying organisms and reefs - Eichenseer, Kilian; Balthasar, Uwe; Smart, Christopher W.; Stander, Julian; Haaga, Kristian A.; Kießling, Wolfgang (Annual Meeting of the Palaeontological Association, 2019)
Phanerozoic changes in the oceanic Mg/Ca ratio and temperature gave rise to alternating episodes of abiotic aragonite and calcite precipitation. These aragonite–calcite sea conditions control the abiotic precipitation of calcium carbonate (CaCO3) polymorphs. Experiments have demonstrated that aragonite–calcite sea conditions affect growth rates and skeletal secretion of some marine calcifiers, but questions remain on how these effects operate on ecological scales. Here we create a Phanerozoic model of aragonite and calcite sea conditions to test whether they affect marine calcification on a global scale. We find that aragonite–calcite sea conditions predict the ecological success of fossil calcifiers relative to their aragonitic or calcitic shell composition during the Ordovician–Middle Jurassic. The loss of coupling between shell mineralogy and environment coincides with the onset of deep sea CaCO3 sedimentation and the advent of the modern carbon cycle. However, preliminary results from the distribution of reefs through time indicate that reef systems are affected differentl

A rare find: protoconch in Cretaceous nerineid “gastropod dinosaurs” - Schulbert, Christian; Nützel, Alexander; Kollmann, Heinz; Kaim, Andrzej (Abstracts of the 90th Annual Meeting of the Paläontologische Gesellschaft, 2019)
Nerineoidea is a very diverse fossil group of mostly high-spired gastropods, some of them quite large and with complex folds and protrusions in the aperture respectively whorls. The family ranges from the Jurassic to the end-Cretaceous mass extinction event so that the group can be referred to as “gastropod dinosaurs”. There are several hundred to a few thousand named species. Despite this high diversity, only very few protoconchs have been reported because nerineoids occur mostly in shallow water mixed siliciclastic/calcareous sediments that are prone to strong diagenetic alteration and are thus not favourable for the preservation of tiny, delicate gastropod protoconchs. We found well-preserved protoconchs in the nerineids Aptyxiella granulata Münster and A. flexuosa (Sowerby) from Cretaceous deposits of the Gosau Group at the Pletzach Alm in Austria. It is a smooth heterostrophic larval shell. The high-spired taxa in question is also well-documented in terms of external shell ornaments and the fold pattern within whorls. The latter are documented by internal moulds as well a micro-ct scans. The new find sheds new light on the discussions of the phylogenetic position of Nerineoidea either close to Tubiferidae (“opisthobranchs”) or Pyramidellidae. The systematic position of nerinid gastropods (Tubiferidae) is supported by the position of the exhalant opening at the posterior end of the aperture as a consequence of the shifting of the pallial cavity to the right side. Furthermore, the parietal and the palatal plaits which obviously had no function in muscle attachment delimit a posterior space proceeding from early ontogenetic whorls to the penultimate whorl. It is opening to the anterior part of the whorl in a narrow slit and is considered as equivalent to the pallial caecum of the Heterobranchia. Besides this morphological distinction, a comparabale diet of these generally large gastropods to that of modern Pyramidellidae seems unlikely.<br
Keywords: Nerineoidea

Arctic rhodolith beds – a biodiverse ecosystem endangered by microplastics? - Teichert, Sebastian; Pyko, Ines; Löder, Martin; Mordek, Marlene; Schulbert, Christian; Wisshak, Max; Laforsch, Christian (Status Conference Research Vessels 2020, 2020)

A reconstruction of Turkey's potential natural vegetation using climate indicators - Raja, Nussaïbah Begum; Aydin, Olgu; Cicek, Ihsan; Turkoglu, Necla (Journal of Forestry Research, 2019)
Turkey, containing three of the world's biodiversity hotspots, is a hub for genetic biodiversity. However, the vegetation cover has drastically changed in recent decades as a result of substantial transformations in land-use practices. A map of the potential natural vegetation can be used to represent the biodiversity of a country, and therefore a reference to effectively develop conservation strategies. The multinomial logistic regression is used to simulate the probability of different biomes occurring in the country using elevation, climatological data and natural vegetation data. A correlation test was applied to the climatological data to determine which predictors influence vegetation the most. These were temperature, precipitation, relative humidity and cloudiness. The Ordinary Kriging method was employed to transform the data into the format for the multinomial logistic regression model. The model showed that temperature was the most influencing factor with respect to Turkey's vegetation and distribution follows a similar distribution as the various macroclimates. Broadleaf forests are mostly found in the Black Sea region, which is also the wettest region of the country. The Marmara region is the only other region where there are broadleaf forests. Mixed forests and shrublands are mostly located in Central Anatolia due to the region's low humidity which favours herbaceous flora. Coniferous forests were dominant in the Aegean and Mediterranean regions, attributed to high temperatures.
CRIS-Team WoS Importer:2019-11-15

Are coral reefs victims of their own past success? - Renema, Willem; Pandolfi, John; Kießling, Wolfgang (Science Advances, 2016)
Keywords: anthropogenic stress; climate change; coral; ecology; staghorn coral

A revised 87Sr/86Sr curve for the Silurian: Implications for global ocean chemistry and the silurian timescale - Cramer, Bradley D.; Munnecke, Axel; Schofield, David I.; Haase, Karsten; Haase, Alexandra; Munnecke, Axel (Journal of Geology, 2011)
Recent recalibration of the Silurian timescale and improved global chronostratigraphic correlation of Silurian strata significantly altered the Silurian 87Sr/86Sr curve and the temporal extent of available data. Whereas previous Silurian 87Sr/86Sr composites showed a generally monotonic increase throughout the Silurian, revisions to the Silurian timescale now require a major increase in the rate of change in 87Sr/86Sr at or near the onset of the Gorstian Age of the Ludlow Epoch. Similarly, improved chronostratigraphic correlations between Silurian outcrops on Anticosti Island, Canada, and Gotland, Sweden, indicate that the middle part of the Telychian Age, which is roughly 10%-15% of the total duration of the Silurian period, is undersampled and underrepresented in Silurian 87Sr/86Sr composites. A revised Silurian 87Sr/86Sr curve based on 241 new and published analyses confirms the significant increase in the rate of change of 87Sr/86Sr toward more radiogenic values near the base of the Ludlow Series. On the basis of these data, we propose that the rapid trend toward more radiogenic 87Sr/86Sr values is indicative of increased weathering of old sialic crust exposed during the Silurian uplift of portions of Baltica, Laurentia, and Avalonia. Importantly, however, the actual rate of change of 87Sr/86Sr will remain equivocal until the durations of Silurian epochs and ages are better constrained. © 2011 by The University of Chicago. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.nat.dgeo.IGM.LP.arevis

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Patino, Jairo; Whittaker, Robert J.; Borges, Paulo A. V.; Maria Fernandez-Palacios, Jose; Ah-Peng, Claudine; Araujo, Miguel B.; Avila, Sergio P.; Cardoso, Pedro; Cornuault, Josselin; De Boer, Erik J.; De Nascimento, Lea; Gil, Artur; et al. (Journal of Biogeography, 2017)
Aims: The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography, by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon-scanning approach to identify 50 fundamental questions for the continued development of the field. Location: Worldwide. Methods: We adapted a well-established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results: Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions: Collectively, this cross-disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.
Keywords: biodiversity conservation; community ecology; extinction; global change; island biogeography theory; island biology; island evolution; island macroecology; research priorities

A second horizon scan of biogeography: Golden ages, Midas touches, and the Red Queen - Dawson, Michael N.; Axmacher, Jan C.; Beierkuhnlein, Carl; Blois, Jessica; Bradley, Bethany A.; Cord, Anna F.; Dengler, Jürgen; He, Kate S.; Heaney, Lawrence R.; Jansson, Roland; Mahecha, Miguel D.; Myers, Corinne; et al. (Frontiers of Biogeography, 2016)
Keywords: Anthropocene; Biodiversity conservation; Birds; Ecoinformatics; Functional diversity; Island biogeography; Macroecology; Mammals; Paleoecology; Phylogenetics; Plants; Species distribution modelling (SDM)

A simpler method of determining beta diversity to address diversity patterns in the Cassian Formation (Triassic, Dolomites) - Roden, Vanessa; Kießling, Wolfgang (Fossils: Key to evolution, stratigraphy and palaeoenvironments - Programme, Abstracts, Field trip guides, 2016)

Assessing mechanisms of environmental change: Palynological signals across the Late Ludlow (Silurian) positive isotope excursion (δ13C, δ18O) on Gotland, Sweden - Stricanne, Ludovic; Munnecke, Axel; Pross, Jörg (Palaeogeography, Palaeoclimatology, Palaeoecology, 2006)
The Silurian is characterised by strong environmental changes, as indicated by several pronounced positive δC and δO excursions. The mechanisms responsible for these isotopic shifts are a matter of much debate. The purpose of the present study is a quantitative high-resolution evaluation of the palynomorph distribution across the Late Ludlow (Ludfordian) isotope excursion on Gotland. Marine and terrestrial palynomorphs have been chosen as palaeoenvironmental indicators because they are widely distributed and exceptionally well preserved. Moreover, the combined analysis of marine and terrestrial palynomorphs allows the reconstruction of contemporaneous palaeoenvironmental change in the marine and terrestrial realms. To correlate our results with the carbon isotope stratigraphy, we have sampled only localities with published isotope data from diagenetically unaltered brachiopod shells. Our results show that fluctuations in the composition of the acritarch assemblages are closely correlated with the stable isotope development. Low abundances of acritarchs occur in times of high stable isotope values and vice versa, indicating that an increase in marine productivity cannot have been the reason for the positive δC excursion. The results are in good agreement with climatic models for the Silurian assuming alternating humid and arid climatic conditions in low latitudes. Times of high stable isotope values correspond to arid climatic conditions in low latitudes, with low input of terrestrial nutrients resulting in impoverished acritarch and conodont communities, whereas times of low stable isotope values correlate with humid climate, high nutrient input, and abundant and diverse acritarch communities. The major change in acritarch communities took place during the increase of the stable isotope values after hemipelagic planktonic or nektonic organisms (graptolites, conodonts) have been affected. This indicates that environmental changes connected with the stable isotope excursion first affected deeper-water settings and later the photic zone. The absolute abundance of terrestrial spores closely mirrors the marine δC and δO development, showing that both the marine and the terrestrial realm were synchronously affected by the climatic changes. The high abundance of spores during the isotope excursion might be explained by increased aeolian input. © 2005 Elsevier B.V. All rights reserve
Keywords: Acritarchs; Bioevents; Gotland; Ludlow; Palynomorphs; Productivity; Silurian; Spores; Stable isotopes

Assisted Colonization: A Question of Focal Units and Recipient Localities - Kreyling, Jürgen; Bittner, Thorsten; Jaeschke, Anja; Jentsch, Anke; Steinbauer, Manuel; Thiel, Daniel; Beierkuhnlein, Carl (Restoration Ecology, 2011)
Assisted colonization as an adaptation strategy to conserve or restore biodiversity in the face of climate change deservedly evokes controversy. Assisted colonization is perceived by some as a last option for conserving endangered species and by others as a risky and unwise management effort due to current gaps of knowledge. Based on the pros and cons of the recent debate, we show that the current discussion mainly focuses on the assisted colonization of rare and endangered species beyond their natural range of distribution. We suggest that a more useful approach for the conservation of endangered species could occur by focusing on the relevant foundation or keystone species, which ensure ecosystem integrity for a multitude of dependent species by governing the habitat structure and micro-climate of the site. Examples of foundation species include dominant tree species in forests or dominant corals in coral reefs. For a given conservation or restoration need (e.g. conservation of rare species), we recommend the assisted colonization of pre-adapted ecotypes of the relevant foundation species from climates similar to future expectations for the target site. This approach could lead to climate-safe habitats for endangered species with minimal adverse effects on recipient ecosystems.
Keywords: Adaptation strategy; Assisted migration; Core species; Ecosystem engineers; Managed relocation; Managed translocation; Species conservation

A systematic approach to relate plant-species diversity to land use diversity across landscapes - Jentsch, Anke; Steinbauer, Manuel; Alt, Martin; Retzer, Vroni; Buhk, Constanze; Beierkuhnlein, Carl (Landscape and Urban Planning, 2012)
Land use change is a major driver of biodiversity patterns, therefore conservation management in cultivated landscapes should seek to optimize land use diversity. Especially under changing environmental conditions there is an increasing need of identifying management options for preserving biodiversity. However, the design of historical data sets is often inappropriate for detecting biodiversity responses to ongoing rapid changes. Here, we present an approach to quantify plant species diversity and relate it to land use diversity.   Data mining took place at the landscape scale in two mountainous regions of Central Europe, differing in natural and cultural history. Within these landscapes a representative systematic rectangular grid (7 × 7 plots of 1 ha) was sampled. At each plot polygons of uniform land use were mapped and presence–absence data of plant species were recorded. Plant species diversity differed significantly between landscapes: species richness and within landscape beta diversity in the calcareous mosaic landscape was higher than in the siliceous mosaic landscape. Land use diversity explained the significant variation in species richness. The relationship between plant species diversity and land use diversity is consistent in different cultivated landscapes and on multiple scales. The chosen sampling approach integrates the advantage of random but grid-based sampling with land use polygon specific information. This enables not only to investigate also similarity pattern (in land use and species composition) but also an integration of further information on the patch scale, if needed.
Keywords: Additive partitioning; Biodiversity monitoring; Germany; Land use patch; Scaling effects; Systematic grid

A transition from Court Jester to Red Queen in the ecological success of Phanerozoic marine calcifiers - Eichenseer, Kilian; Balthasar, Uwe; Smart, Christopher W.; Stander, Julian; Kießling, Wolfgang (EGU General Assembly Conference Abstracts, 2018)
The vast Phanerozoic fossil record of marine calcifiers allows for quantitative assessment of environmental influences on past life. Calcifying organisms build their shells from calcite and/or aragonite, and the metabolic cost of shell secretion is influenced by the interplay of mineralogy and environment. Mg:Ca ratio and temperature control whether abiotic calcium carbonate is precipitated as calcite or aragonite, and variations in those conditions are likely to have affected calcifying organisms throughout Earth history. Here, we combine a model of seawater Mg:Ca ratio with δ18O temperature reconstructions to quantify calcite-aragonite sea conditions from the Ordovician - Pleistocene. We correlate calcite-aragonite sea conditions with the ecological success of aragonitic taxa at stage resolution, calculated as Summed Common species Occurrence Rate (SCOR) based on genus-level occurrences from the Paleobiology Database. Calcite-aragonite sea conditions significantly co-vary with the ecological success of aragonitic taxa in the Palaeozoic, but correlation ceases in the Mesozoic. We attribute this to the escalation of marine life through time: The end-Permian mass extinction and subsequently the Mesozoic Marine Revolution led to the prevalence of increasingly mobile, metabolically active, and predatory taxa. A Palaeozoic Court Jester world, in which environmental constraints shaped the success of marine calcifiers, gave way to the modern Red Queen world, where biotic interactions reign.

A triász és a jura időszak határán lezajlott globális krízis és annak nyomai magyarországi rétegsorokban - Haas, János; Győri, Orsolya; Kocsis, Ádám; Lantos, Zoltán; Palfy, Jozsef (Foldtani Kozlony, 2018)
The mass extinction at the end of the Triassic Period was one of the largest extinction events in the Phanerozoic and it was the result of a global environmental crisis. In connection with this, the last two decades have seen increasing research efforts to gain more knowledge and thus a better understanding of this event. These efforts have included detailed studies of numerous stratigraphic sections worldwide. The review presented here attempts to summarize the major results of multi-faceted international research on the stratigraphic and fossil record of the end-Triassic event, discussing proposed cause-and-effect relationships and possible scenarios. In addition, there is also an overview of studies made in recent decades on the Triassic-Jurassic boundary sections in Hungary, with an emphasis on their relevance to global research into the Triassic-Jurassic boundar
Keywords: global environmental crisis; mass extinction; Triassic-Jurassic boundary

A tsunami deposit at the Cretaceous-Tertiary boundary in Argentina - Scasso, Roberto A.; Concheyro, Andrea; Kießling, Wolfgang; Aberhan, Martin; Hecht, Lutz; Medina, Francicso A.; Tagle, Roald (Cretaceous Research, 2005)
A coarse-grained sandstone bed of Cretaceous/Paleogene (K/Pg) boundary age occurs in a homogeneous neritic shelf mudstone sequence (Jagüel Formation) in the Neuquén Basin of Argentina. This bed, 15–25 cm thick, contains abundant plagioclase, broken shells and sharks' teeth. Sedimentological features include an erosive base, abundant rip-up clasts, normal grading and hummocky cross-bedding. The K/Pg boundary age of the bed was confirmed by calcareous nannofossils. Similar to other sections in the Gulf Coast region and the Danish Basin, a “dead zone” significantly depleted in macrofossils is evident in the basal 1 m above the clastic layer. In combination, these features suggest that the clastic layer represents a tsunami deposit that was related to the Chicxulub impact event in Yucatan/Mexico. Mechanisms of tsunami wave amplification in this extremely distal and somewhat protected setting are poorly understood but the funnel-shape of the basin may have promoted the unusually strong sedimentological response.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LP.atsuna
Keywords: Tsunami; Cretaceous/Paleogene boundary; Mass extinction; Patagonia; Argentina

Attached and free-living crustose coralline algae and their functional traits in the geological record and today - Teichert, Sebastian (Facies, 2024)
Crustose coralline algae (CCA) are important ecosystem engineers and carbonate producers today and in the geological past. While there is an increasing number of publications on CCA every year, it is evident that there are many misunderstandings and inconsistencies in the assignment of CCA to taxonomic and functional groups. This is partly because CCA are treated by biologists, ecologists and palaeontologists as well as covered by studies published in journals ranging from geo- to biosciences, so that there is often a mixture of terminology used and differing scientific focus. In this review, a comprehensive overview is given on what is known about CCA, their functional traits and their roles in environments from the present and the past. In this context, some bridges are built between the commonly different viewpoints of ecologists and palaeontologists, including suggesting a common and straightforward terminology, highlighting and partially merging different taxonomic viewpoints as well as summarizing the most important functional traits of CCA. Ideally, future studies should seek to quantitatively analyse potential implications for CCA and their associated organisms under ongoing global chang
Keywords: crustose coralline algae; ecosystem engineers; functional traits; palaeoecology; rhodoliths

Aufbruch und Untergang: Vom Werden und Vergehen des Lebens. - Kießling, Wolfgang (Als das Leben laufen lernte, 2007)
Keywords: Evolution; Massenaussterben; Biodiversität

Auf und Nieder - die wechselvolle Entwicklungsgeschichte von Riffen in der Tiefenzeit. - Kießling, Wolfgang (Abgetaucht, 2008)
Keywords: Riffevolution; Biodiversität

Aus dem Archiv der Paläontologischen Gesellschaft II: Die Paläontologische Zeitschrift im Wandel der Zeit - Reich, Mike; Biermann, Stefanie; Roden, Vanessa (79. Jahrestagung der Paläontologischen Gesellschaft in Bonn, 5.-7. Oktober 2009, 2009)

Author Correction: Colonial history and global economics distort our understanding of deep-time biodiversity (Nature Ecology & Evolution, (2021), 10.1038/s41559-021-01608-8) - Raja, Nussaïbah Begum; Dunne, Emma; Matiwane, Aviwe; Khan, Tasnuva Ferdous Ming; Nätscher, Paulina; Ghilardi, Aline Marcele; Chattopadhyay, Devapriya (Nature Ecology & Evolution, 2022)
In the version of this article initially published, the designation “Central” America was omitted in an Extended Data Fig. 2c panel heading and the caption as well as in the Extended Data Fig. 3 caption. The figure and captions have been updated to clarify “Central and South America” in each instance.
CRIS-Team Scopus Importer:2022-02-11

Barkerina dobrogiaca Neagu, 2000, a Valanginian marker taxon from the northern Neotethysian margin - Schlagintweit, Felix; Bucur, Ioan I.; Granier, Bruno; Koch, Roman (Cretaceous Research, 2019)
Barkerina dobrogiaca Neagu (Valanginian of Romania), a medium-sized complex benthic foraminifera, is described from the Valanginian of the Pontides, NE Turkey. Barkerina dobrogiaca differs from the type-species B. barkerensis Frizzell & Schwartz (Albian of Texas) by its small size, and comparably thin septula and test wall. The present paper is a further contribution to the knowledge of inventory and faunal assemblages of Valanginian shallow-water carbonates. Compared to the classical Urgonian (Hauterivian to lower Aptian) these are still incompletely known. Together with another form reported from the Barremian of Romania, it also shows that representatives of Barkerina Frizzell & Schwartz are well present in the Neotethysian realm.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Biostratigraphy; Early Cretaceous; Exoskeleton; Foraminiferida; Paleobiogeography; Systematics

Bayesian analysis of biodiversity patterns via beam trawl versus video transect—a comparative case study of Svalbard rhodolith beds - Straube, Eileen; Neumann, Hermann; Wisshak, Max; Mathes, Gregor; Teichert, Sebastian (Biodiversity and Conservation, 2024)
Knowledge of spatial biodiversity patterns is important for ecosystem assessment. Rhodoliths, free-living calcareous algae, are biotic components that structure the sea floor through their complex calcareous skeletons and their tendency to accumulate in an area to form rhodolith beds. Thereby, rhodoliths are considered to act as ecosystem engineers promoting local biodiversity. In this study, the biodiversity of rhodolith beds in Mosselbukta, Svalbard, was investigated to analyse the proposed link between local biodiversity and the presence of rhodoliths by evaluating beam trawl and underwater video transect data. The comparative analysis of two sampling methods addressing the same research question allowed us to assess the suitability of these two methods. To test our hypothesis and the utility of the two methods, evaluations of the two data sets were carried out separately by using Bayesian statistics. The results confirm a positive relationship between the presence of rhodoliths and local biodiversity with a posterior probability of 70% for the video transects and 85% for the beam trawl data. The similarity of the results of the two methods suggests that both methods are well-suited for the analysis of local biodiversity patterns. The combination of the two methods, with their individual strengths and weaknesses, has provided stronger support for the results and a broader view on different components of the biodiversity in the Svalbard rhodolith beds.<br
Keywords: Arctic; method comparison; rhodoliths; quantitative analysis; crustose coralline algae

Beta diversity in Triassic and modern marine communities - Roden, Vanessa; Hausmann, Imelda M.; Zuschin, Martin; Kießling, Wolfgang (5th International Palaeontological Congress, 2018)

Beta diversity in Triassic and modern reef basin assemblages - Roden, Vanessa (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)

Between-taxon matching of common and rare species richness patterns - Reddin, Carl James; Bothwell, John; Lennon, Jack (Global Ecology and Biogeography, 2015)
Keywords: Indicator; Intertidal ecology; Marine; Rarity; Spatial; Species richness; Surrogacy

Bevocastria magna n. sp., eine neue Cyanobakterie aus den obertriassischen Riffkalken des Taurus-Gebirges (Türkei) - Senowbari-Daryan, Baba; Link, Michael (Palaeontologische Zeitschrift, 2004)
Bevocastria magna n. sp., an extremely large nodular species of the genus Bevocastria, is described from Upper Triassic (Norian) reef limestones of a locality south of the town of Dereköy (SW Antalya, Turkey). The nodule of B. magna looks like skeletons of chaetetid sponges which occur commonly at the same locality. B. magna is the first report of the genus from the Triassic deposits of Turkey.
UnivIS-Import:2015-04-14:Pub.2004.nat.dgeo.IGM.LP.bevoca
Keywords: Cyanobacteria; Bevocastria; n. sp.; Triassic; Norian; Taurus-Mts.; Turkey

Bibliographie der Geologischen Blätter für Nordost-Bayern - Baier, Alfons; Schulbert, Christian (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2011)
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LAG.biblio

Bicoelia corticifera, a new inozoid sponge from the Upper Triassic (Norian) reef boulders of Taurus Mountains (South Turkey) - Senowbari-Daryan, Baba; Link, Michael (Turkish Journal of Earth Sciences, 2014)
Upper Triassic Norian reef boulders, exposed in a locality in the Central Taurids, southern Turkey, yielded a high number of hypercalcified sponges, including Sphinctozoans, Inozoans, Spongiomorphids, and Chaetetids. The reef boulders are exposed near the fountain Tavuk Çeşme, located at the road leading from the town of Aksu to Yenişarbademli. Geologically this locality belongs to the Anamas Akseki Autochthon. In this paper a new inozoan sponge, Bicoelia corticifera nov. sp., is described from Tavuk Çeşme. It is a cylindrical and unbranched sponge, found in several thin sections. The sponge is characterized by 2 axial spongocoels, and the sponge wall is composed of fine reticulate fiber skeleton and a distinct outer wall. Usually several specimens grow closely side by side.
UnivIS-Import:2015-04-14:Pub.2014.nat.dgeo.IGM.LP.bicoel
Keywords: Sponge; Inozoa; Bicoelia; Triassic; Norian; reef; Central Taurids; Taurus Mountains; Turkey

BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Smith, Jansen; Rillo, Marina C.; Kocsis, Ádám; Dornelas, Maria; Fastovich, David; Huang, Huai Hsuan M.; Jonkers, Lukas; Kießling, Wolfgang; Li, Qijian; Liow, Lee Hsiang; Margulis-Ohnuma, Miranda; Meyers, Stephen; et al. (Global Ecology and Biogeography, 2023)
Motivation: We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present-day to millions of years ago. Main Types of Variables Included: BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain: The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm2 to grid cells of 100 km2. Time Period and Grain: BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement: The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format: SQLite, Comma-separated values.
CRIS-Team Scopus Importer:2023-08-04
Keywords: deep-time; global; palaeobiology; species richness; temporal; timescale; turnover

Biodetrital carbonates on the Adriatic continental shelf imprinted by oxidation of seeping hydrocarbons - Taviani, Marco; Franchi, Fulvio; Angeletti, Lorenzo; Correggiari, Anna Maria; López Correa, Matthias; Masselli, Vittorio; Mazzoli, Claudio; Peckmann, Jörn (Marine and Petroleum Geology, 2015)
The gas-productive Bonaccia area located at ca. 80-90 m below sea level offshore Ancona (Central Adriatic Sea) is site of hydrocarbon-derived carbonate production. The carbonates include large dm-sized slabs (bryozoan limestone), smaller concretionary aggregates, mudstones and pipes. The mudstones and botryoidal aragonite cements within limestones show δ13C values as low as -47.8‰ VPDB, consistent with seepage of isotopically light hydrocarbons (e.g. methane). These hydrocarbon-derived carbonates commonly incorporate abundant shell remains, deriving from the prevalently coarse bioclastic-rich muddy deposits from post-glacial transgressive units. It is, therefore, hypothesized that hydrocarbon-rich fluids permeated the post-glacial sediments, resulting in seafloor seeps that were inhabited by chemosymbiotic lucinid bivalves and burrowing callianassid shrimps; fossils and traces of which have been found in the Bonaccia carbonates. Microbial oxidation of the reduced compounds contained in the seep fluids led to a locally patchy carbonate cementation of the sediments at the seep sites. The pipes are interpreted as decapod burrows that subsequently served as conduits for hydrocarbon leakage. Seepage is probably still active at present as testified by gas production at the study site. Interestingly, seep carbonates exhumed by erosion served as hard substrate for fouling benthos (i.e., bryozoans, oysters and red algae) in the Holocene. The main products of the processes at the Bonaccia study site are composite bryozoan-dominated limestones, whose multi-step and complex history was unfold thank to radiocarbon dating of key components and precise stratigraphic control. The Bonaccia case-study can serve as a model for the interpretation of ancient analogs, such as bryozoan dominated limestones and mudstones of Paleozoic to Mesozoic age, which are not uncommon in the geological record. It further calls for caution in assuming that the presence of dominant macrobenthic fossil in old hydrocarbon-derived limestones implies its ecological connection to active seepage.
UnivIS-Import:2016-06-01:Pub.2015.nat.dgeo.IGM.LP.biodet
Keywords: Adriatic sea; Cold-seep carbonates; Hydrocarbons; Quaternary

Biodiversity and Host–Parasite (Co)Extinction - van Dijk, Jeroen; de Baets, Kenneth (The Evolution and Fossil Record of Parasitism, 2021)
Parasitism is one of the most common modes of life, and yet it is often disregarded or ignored in nature conservation. We are at the brink of the sixth mass extinction and in order to assess the extinction risk of both parasites and their hosts, we first need to fully understand the role and function of parasites in ecosystems. Parasites might play an active role in their host’s extinction, and coextinction has been postulated to be the most common mode of extinction. However, parasites may be able to survive their host’s extinction through host switching, perhaps to a more abundant host, for example. The dilution effect has been described as an important natural defense mechanism for the host: higher biodiversity is associated with lower infection risk. Discussed here is the importance of biodiversity and host–parasite associations and (co)extinction, and the role the fossil record has in filling the knowledge gap regarding deep-time host–parasite interactions.
Keywords: Biodiversity; Co-extinction; Dilution effect; Host–parasite associations; Fossil record; Host switching

Biodiversity and palaeoecology of a marine basinal fauna from Misurina (Late Triassic Cassian Formation, Italy) - Hausmann, Imelda M.; Nützel, Alexander; Roden, Vanessa (88th Annual Conference of the Paläontologische Gesellschaft, 2017)

Biodiversity dynamics and environmental occupancy of fossil azooxanthellate and zooxanthellate scleractinian corals - Kießling, Wolfgang; Kocsis, Ádám (Paleobiology, 2015)
Scleractinian corals have two fundamentally different life strategies, which can be inferred from morphological criteria in fossil material. In the non-photosymbiotic group nutrition comes exclusively from heterotrophic feeding, whereas the photosymbiotic group achieves a good part of its nutrition from algae hosted in the coral's tissue. These ecologic differences arose early in the evolutionary history of corals but with repeated evolutionary losses and presumably also gains of symbiosis since then. We assessed the biodiversity dynamics and environmental occupancy of both ecologic groups to identify times when the evolutionary losses of symbiosis as inferred from molecular analyses might have occurred and if these can be linked to environmental change. Two episodes are likely: The first was in the mid-Cretaceous when non-symbiotic corals experienced an origination pulse and started to become more common in deeper, non-reef habitats and on siliciclastic substrates initiating a long-term offshore trend in occupancy. The second was around the Cretaceous/Paleogene boundary with another origination pulse and increased occupancy of deep-water settings in the non-symbiotic group. Environmental factors such as rapid global warming associated with mid-Cretaceous anoxic events and increased nutrient concentrations in Late Cretaceous-Cenozoic deeper waters are plausible mechanisms for the shift. Turnover rates and durations are not significantly different between the two ecologic groups when compared over the entire history of scleractinians. However, the deep-water shift of non-symbiotic corals was accompanied by reduced extinction rates, supporting the view that environmental occupancy is a prominent driver of evolutionary rates. ©
UnivIS-Import:2015-07-08:Pub.2015.nat.dgeo.IGM.LP.biodiv

Biodiversity patterns across the Late Paleozoic Ice Age - Seuß, Barbara; Roden, Vanessa; Kocsis, Ádám (Palaeontologia Electronica, 2020)

Biodiversity research: data without theory – theory without data - Rillig, Matthias C.; Kießling, Wolfgang; Borsch, Thomas; Gessler, Arthur; Greenwood, Alex D.; Hofer, Heribert; Joshi, Jasmin; Schröder, Boris; Thonicke, Kirsten; Tockner, Klement; Weisshuhn, Karoline; Jeltsch, Florian (Frontiers in Ecology and Evolution, 2015)
Keywords: Biodiversity; Ecology

Bioerosion in fossil cephalopods - a case study from the Upper Carboniferous Buckhorn Asphalt Quarry Lagerstätte, Oklahoma, USA - Seuß, Barbara; Nützel, Alexander (Facies, 2019)
The Mid-Pennsylvanian (Desmoinesian-Virgilian) deposits from the Buckhorn Asphalt Quarry Lagerstätte near Sulphur, Oklahoma, are characterized by siliciclasticcarbonate rocks. One of these deposits is the 'cephalopod coquina' that contains a large amount of orthocerid and coiled nautiloid, and ammonoid shell remains. These were used for a detailed study on bioerosion in cephalopod shells in order to help in the reconstruction of the paleoenvironment and to increase the general knowledge on bioerosion in fossil cephalopods. More than 50 shell fragments were cast and investigated. The shells cast and investigated in this study comprise a diverse set of ichnotaxa-/forms. Besides chlorophyte and cyanobacterial traces, also rhodophyte, fungal and spongal traces are present as well as those of unknown origin. In addition, there are six ichnoforms that might have foraminiferans as producers. In orthoceratids, Ichnoreticulina elegans and a curly morphotype of Scolecia isp. are most common while the abundance in coiled cephalopods is dominated by the 'superthin form', the 'extremely thin form', and Flagrichnus profundus. In total twenty-two ichnotaxa and - forms were recognized and twelve of these have their oldest record in the Carboniferous. The succession of ichnotaxa/-forms in the casts of orthocones suggests deposition in the deep euphotic to dysphotic zone of the Buckhorn sea while shells of coiled specimens had drifted for a while; they were therefore more prone to bioerosion by autotrophs until they sank to the seafloor.<br
Keywords: Nautiloidea; ammonoidea; Bioerosion; fossil record; shells; bathymetry

Bioerosion in shells of modern Nautilus - Results from the investigation of live caught specimens - Seuß, Barbara; Wisshak, Max; Mapes, Royal H.; Landman, Neil (9th International Symposium 'Cephalopods present and past, 2014)
Over the past 20 years, Royal H. Mapes a nd colleagues caught specimens of the living Nautilus in various regions of the Southern Pacific Ocean. Many of these shells were encrusted by epiliths (foraminiferans, ostracods, goose barnacles). Additionally, the shells showed strong signs of bioerosion, i.e. numerous small irregular holes penetrating deep into the shell. Because bioerosion is a major factor in the degradation of carbonate skeletal material a study was carried out on four shells (one specimen of N. pompilius from Vanuatu, three specimens of N. macromphalus from New Caledonia) to investigate these holes in detail. The shells were broken into pieces and a set of epoxy resin casts was prepared for analyses with the scanning electron microscope. The analyses revealed that the small holes are the openings of two, so far undescribed, microbioerosion traces which are most likely produced by naked foraminiferans. Traces of these foraminiferans commonly occur in dense clusters in the shell of up to many dozen individuals. Because these traces were not reported from other substrates before, we conclude, that these boring naked foraminiferans are host specific. In addition to the two boring foraminiferans we found two further traces on the shells outside of Nautilus. These etchings derive from test-bearing foraminiferans, likely from some genera of the Rosalinidae. As of now, there is no indication that any of the foraminiferans, naked or with a test, were parasitic but instead they used the Nautilus shells as substrate to settle respectively to live in. Our study presents the first report on syn-vivo bioerosion in Nautilus shells and demonstrates that shell degradation in Nautilus already starts during lifetime of the cephalopo

Bioerosion in shells of modern Nautilus - Taphonomy of deep-marine versus backshore collected Nautilus macromphalus conchs (New Caledonia); 2014) - Seuß, Barbara (9th International Symposium 'Cephalopods present and past', 2014)
During field trips and research cruises into the New Caledonia region numerous shells of Nautilus macromphalus were collected by Royal H. Mapes and colleagues. On six of the shells a bioerosion study was carried out. Specimens: Four of the specimens derive from a backshore collection (AMNH 97753-56) on beaches on the island of Lifou. The shells were initially deposited in the shallow water and transported onto the beaches by waves and currents. Some specimens are heavily encrusted by non-calcareous and calcareous algae, bryozoans, serpulids, etc. and have largely lost their brownish-red color stripes while others are well-preserved and still display sharp reddish-brown color stripes and are only slightly encrusted.The second set of specimens are two deep-water dredged shells (AMNH 55916, -20). One shell derives from a setting half way from Grand Terre and the Isle of Pines and was collected in 395m water depth. The second shell was collected in 598m water depth at the Lansdowne Bank. Both shells are broken and highly abraded. Bioerosion: Bioerosion is defined as "the removal of consolidated mineral or lithic substrate by the direct action of organisms” (Neumann 1966) and is a combination of mechanical and chemical processes that destroy inorganic and biogenic carbonate. All of the shells show intensive signs of bioerosion. A detailed study was carried out to investigate the ichnocoenosis, i.e., the assemblages of ichnotaxa. ff. https://www.researchgate.net/publication/274667678_Bioerosion_in_shells_of_modern_Nautilus_-_Taphonomy_of_deep-marine_versus_backshore_collected_Nautilus_macromphalus_conchs_New_Caledonia_2014<br

Biogeochemical analysis of the calcification patterns of cold-water corals Madrepora oculata and Lophelia pertusa along contact surfaces with calcified tubes of the symbiotic polychaete Eunice norvegica: evaluation of a mucus calcification hypothesis - Oppelt, Alexandra; López Correa, Matthias; Rocha, Carlos (Deep-Sea Research Part I-Oceanographic Research Papers, 2017)
<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">The scleractinian cold-water corals (CWCs), including the species <em style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">Madrepora oculata<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> and especially <em style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">Lophelia pertusa<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">, have been studied extensively in an attempt to decipher environmental signals recorded during biomineralisation in order to extract environmental chronologies. However, understanding the mechanisms of carbonate precipitation is a prerequisite to interpret variations in geochemical signatures locked into the skeleton during coral growth; to date results are still inconclusive. Here a novel approach, comparing the calcification patterns within the coral microstructure of species <em style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">L. pertusa<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> and <em style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">M. oculata<span style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> and the geochemistry along the contact surfaces with calcified polychaete tubes is undertaken to provide additional information on the mechanisms of biomineralisation in colonial corals. The fact that no significant difference in microstructures, variations in growth rate, or geochemical composition between the corallite theca and the calcified polychaete tube was detectable leads to the conclusion that both have been deposited by the coral tissue in <em style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">L. pertusa<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> and <em style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">M. oculata<span style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">. Based on prior knowledge on the symbiotic relationship between CWCs and the polychaete <em style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">Eunice norvegica,<span style="box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> an involvement of mucus in the calcification of the parchment tubes had been suspected. However, we found only evidence for aragonite precipitated by coral tissue, without evidence for an involvement of mucus in the calcification.
UnivIS-Import:2017-11-06:Pub.2017.nat.dgeo.IGM.LP.biogeo
Keywords: Biomineralization; Eunice norvegica; Lophelia pertusa; Madrepora oculata; Mucus calcification; Symbiosis

Biogeochemical formation of calyx-shaped carbonate crystal fans in the subsurface of the Early Triassic seafloor - Heindel, Katrin; Richoz, Sylvain; Birgel, Daniel; Brandner, Rainer; Klügel, Andreas; Krystyn, Leopold; Baud, Aymon; Horacek, Micha; Mohtat, Tayebeh; Peckmann, Joern (Gondwana Research, 2015)
Keywords: Diagenetic carbonate; End-Permian extinction; Lipid biomarkers; Rare earth elements; Subseafloor

Biogeographical distribution of Hyrrokkin (Rosalinidae, Foraminifera) and its host-specific morphological and textural trace variability - Beuck, Lydia; López Correa, Matthias; Freiwald, André (Current Developments in Bioerosion, 2008)
The parasitic foraminifer Hyrrokkin sarcophaga predominantly infests the cold-water coral Lophelia pertusa and the co-occurring bivalve Acesta excavata, showing a commensal or parasitic behaviour. It occurs also on some other corals (e.g., Caryophyllia sarsiae), bivalves (e.g., Delectopecten vitreus) and sponges (Geodia sp.), typically in aphotic environments. The aim of the study is to describe its traces from various host substrates, to characterise its parasitic behaviour and to map the geographical distribution of the genus Hyrrokkin. Epoxy-resin casts of H. sarcophaga traces in A. excavata, C. sarsiae, D. vitreus and L. pertusa, and of H. carnivora traces in A. excavata, were SEM analysed. The boring pattern is in all cases characterised by a shallow groove of up to 7 mm in diameter (max. 2 mm deep), from which 'whip'-shaped extensions protrude vertically into the substrate. In A. excavata the foraminifer can penetrate the entire valve to the mantle cavity, producing a thick shaft of fused 'whips'. This parasitic attack is answered by a strong callus formation of the mollusc. One individual foraminifer can repeatedly bypass the organic-rich callus, resulting in a thick aragonite pinnacle. The trace surface texture is xenoglyph and changes with the penetrated host-microstructures. This is especially obvious on deeply penetrating trace portions (e.g., 'whip'-shaped filaments) and is a strong indication for a chemical penetration mode (etching). The trace of Hyrrokkin is described as Kardopomorphos polydioryx igen. n., isp. n. On the substrates without the shaft, related to parasitic behaviour, Hyrrokkin might feed directly on adjacent external host tissue. H. sarcophaga is known along the North Atlantic continental margin from polar to subtropical latitudes and H. carnivora occurs on the continental margin of Mauritania, Congo and Guinea. In the Mediterranean we could document the parasitism of H. sarcophaga from Last Glacial A. excavata. Traces or detached foraminifer tests occur in Early Pleistocene cold-water coral deposits on Sicily and Rhodes. Recent H. sarcophaga has not been observed above 11°C and is scarce near 5°C water temperature. Hyrrokkin sp. was reported from the Canadian Pacific on fossil sponges and was observed on Acesta patagonica in the Beagle Channel (Chile). © 2008 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2008.nat.dgeo.IGM.LP.biogeo
Keywords: Acesta; Bioerosion; Cold-water corals; Foraminifer; Hyrrokkin; Lophelia; Parasitism

Biogeographic ranges do not support niche theory in radiating Canary Island plant clades - Steinbauer, Manuel; Field, Richard; Mara Fernandez-Palacios, Jose; Irl, Severin D. H.; Otto, Rudiger; Schaefer, Hanno; Beierkuhnlein, Carl (Global Ecology and Biogeography, 2016)
Keywords: Adaptive radiation; climate; competition; divergence; ecological character displacement; endemic plants; ghost of competition past; niche conservatism; sister clades; speciation

Biogeography of Paleozoic Ammonoids - Korn, Dieter; de Baets, Kenneth (Ammonoid Paleobiology: From macroevolution to paleogeography, 2015)

Bioluminescence in deep-sea isidid gorgonians from the Cape Verde archipelago - Raddatz, Jacek; López Correa, Matthias; Rüggeberg, Andres; Dullo, Wolf-Christian; Hansteen, Thor (Coral Reefs, 2011)
Cold-water corals, and in particular numerous gorgonian species, occur abundantly on the deep slopes of the Cape Verde archipelago (Fig. 1a). Among them, the isidid gorgonian genus Keratoisis occurred frequently. A living Keratoisis sp. was ROV collected (KIEL 6000) from 3,052 m (1642.3¢N, 2534.9¢W) in the Charles Darwin Volcanic Field (1b) during METEOR cruise M80/3. A strong luminescence was accidentally observed when this bamboo coral arrived on deck in the early evening hours just before sunset. The entire stem and branch tissue showed a dull blue luminescence. Additionally, when touched, it emitted a very strong blue light (Fig. 1c) that persisted for a few seconds. Coral tissue lit up strongest and flash like at the point of stimulation, and the illumination spread in a wave across the coenenchyme of the distal branches. The most intense light emission originated from the non-retractile sclerite-rich feeding polyps and remained visible for several minutes before it slowly faded. This phenomenon could be reproduced several times within hours. Luminescence in octocorals has been observed in the alcyonarian Anthomastus sp., as well as in isidid gorgonians (Isidella, Keratoisis, and Lepidisis), primnoid gorgonians (Primnoisis and Thouarella), and in Iridigorgia and Acanthogorgia (Herring 1987). Muzik (1978) documented bioluminescence in the isidid gorgonian Lepidisis olapa off Hawaii, and Etnoyer (2008) mentioned luminescent capabilities for Isidella tentaculum from the northeast Pacific. Just recently, bioluminescence was reported for Keratoisis flexibilis and for the zoanthid Gerardia sp. from the Gulf of Mexico (http://oceanexplorer.noaa.gov/explorations/09bioluminescence/). Likely due to the scarce availability of direct deep-sea sampling and observation, there are no further Atlantic records for bioluminescence in the Keratoisidinae outside the Gulf of Mexico. Our additional observations support that bioluminescence in Keratoisis and in other deep-sea gorgonians is rather common and deserves detailed in situ observations.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.biolum

Biomarker evidence for the origin of seep 1 oil and solid bitumen from the Late Devonian Siljan impact structure, Sweden - Ahmed, Manzur; Lehnert, Oliver; Fuentes, David; Meinhold, Guido (Organic Geochemistry, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LG.biomar

Biostratigraphic and chemostratigraphic correlation for the base of the Middle Ordovician between Yichang and Western Zhejiang areas, South China - Zhang, Yuandong; Munnecke, Axel; Cheng, Junfeng; Xiao, Liu; Chen, Xu (Acta Geologica Sinica - English Edition, 2011)
The base of the Middle Ordovician (i.e. Dapingian Stage) has been defined at the first appearance datum (FAD) of conodont Baltoniodus? triangularis at Huanghuachang, Yichang, China, but the precise correlation of the boundary to regions of other facies remain to be resolved. Herein we review the biostratigraphy and chemostratigraphy of the Huanghuachang Global Standard Stratotype-Section and Point (GSSP) section, and present our latest stratigraphic work on the nearby Chenjiahe section in Yichang, and the Hengtang Quarry section, Jiangshan, Zhejiang, which is regarded as representative of slope facies. The conodont and graptolite biostratigraphy as well as chemostratigraphy of the Chenjiahe section indicate that the base of the Middle Ordovician also falls within the graptolite Azygograptus suecicus Zone, and coincides with a high or maximum δ13C value within a minor positive carbon isotope excursion, suggesting that the base boundary can be readily recognized across the entire Yangtze Gorges area. The integrated graptolite and conodont biostratigraphy and chemostratigraphy of the Hengtang section, Jiangshan, indicates that the basal boundary probably falls within the graptolite Isograptus caduceus imitatus Zone that overlies the Azygograptus suecicus Zone, and coincides with a remarkable drop of δ13C. This difference indicates that a multi-disciplinary approach is critical to identify the base boundary in those regions where the Baltoniodus? triangularis is absent.
Keywords: Chemostratigraphy; Graptolite biostratigraphy; Middle ordovician; Slope facies; South china

Biostratigraphic precision of the Cruziana rugosa group: a study from the Ordovician succession of southern and central Bolivia. - Egenhoff, Sven; Weber, Bernd; Lehnert, Oliver; Maletz, Jörg (Geological Magazine, 2007)
Cruziana ichnospecies have been repeatedly reported to have biostratigraphic significance. This study presents a re-evaluation of the arthropod ichnotaxa of the Cruziana rugosa Group from bio- and/or lithostratigraphically well-defined Lower to Upper Ordovician siliciclastic sections of southern and central Bolivia. With the exception of Cruziana rouaulti, the ichnofaunas contain all the members of the Cruziana rugosa Group throughout the Ordovician (Arenig to Caradoc) successions in Bolivia. The Bolivian material therefore indicates that these arthropod ichnofossil assemblages are suitable for recognizing Ordovician strata in Bolivia. These findings cast doubt on their use as reliable indicators for a global intra-Ordovician (Arenig to Caradoc) biozonation of Peri-Gondwanan sedimentary successions. © 2007 Cambridge University Press.
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LG.biostr
Keywords: Biostratigraphy; Bolivia; Cruziana; Ordovician

Biostratigraphy and sequence stratigraphy of the Toarcian Ludwigskanal section (Franconian Alb, Southern Germany) - Arp, Gernot; Gropengießer, Sebastian; Schulbert, Christian; Jung, Dietmar; Reimer, Andreas (Zitteliana, 2021)
Extensive construction work at the canal cutting of the Ludwigskanal near Dörlbach, Franconian Alb, provided the opportunity to re-investigate a scientific-historical and biostratigraphically important reference section of the South-German Toarcian. The 16 m thick section, described bed by bed with respect to lithology and macrofossils, starts within the Upper Pliensbachian Amaltheenton Formation, covers the Toarcian Posidonienschiefer and Jurensismergel Formation, and ends in basal parts of the Opalinuston Formation. Carbonate contents are high in the Posidonienschiefer and successively decline within the Jurensismergel to basal parts of the Opalinuston. The high carbonate contents in the Posidonienschiefer are associated with comparatively low organic carbon contents. However, organic carbon contents normalized to the silicate fraction are similarily high if compared to other regions in Germany. Only the persistence of high organic carbon levels into middle parts of the Upper Toarcian differs from those of most regions in central Europe. Ammonite biostratigraphy indicates a thickness of >9 m for the Upper Pliensbachian, 1.15–1.20 m for the Lower Toarcian, 5.04 m for the Upper Toarcian, and >0.5 m for the Lower Aalenian. Despite the low sediment thickness, all Toarcian ammonite zones and almost all subzones are present, except for major parts of the Tenuicostatum Zone and the Fallaciosum Subzone. On the basis of discontinuities, condensed beds, and correlations with neighbouring sections in Southern Germany, a sequence stratigraphic interpretation is proposed for the Toarcian of this region: (i) The Posidonienschiefer Formation corresponds to one 3rd order T-R sequence, from the top of the Hawskerense Subzone to a fucoid bed at the top of the Variabilis Subzone, with a maximum flooding surface at the top of the Falciferum Zone. (ii) The Jurensismergel Formation exhibits two 3rd order T-R sequences: The first ranges from the basis of the Illustris Subzone (i.e., the Intra-Variabilis-Discontinuity) to the top of the Thouarsense Zone, with a maximum flooding surface within the Thouarsense Zone. The “belemnite battlefield” reflects a transgressive “ravinement surface” within the first Jurensismergel Sequence, not a maximum regression surface at its basis. The second sequence extents from the erosive basis of the Dispansum Zone to the top of the Aalensis Subzone, with a maximum flooding surface at the Pseudoradiosa-Aalensis Zone boundary. Finally, the Opalinuston starts with a new sequence at the basis of the Torulosum Subzone. Transgressive system tracts of these 3rd order T-R sequences are commonly phosphoritic, while some regressive system tracts show pyrite preservation of ammonites. The maximum regression surfaces at the basis of the Toarcian and within the Variabilis Zone reflect a significant submarine erosion and relief formation by seawater currents, while this effect is less pronounced at the basis of the Dispansum Zone and basis of the Torulosum Subzone (i.e., the boundary Jurensismergel-Opalinuston Formation
Keywords: Ammonoidea; Jurensismergel; Lower Jurassic; Posidonienschiefer; sealevel changes; Southern Germany; stratigraphy

Biotic interactions in species distribution modelling: ten questions to guide interpretation and avoid false conclusions - Dormann, Carsten; Bobrowski, Maria; Dehling, Matthias; Harris, David; Hartig, Florian; Lischke, Heike; Moretti, Marco; Pagel, Jörn; Pinkert, Stefan; Schleuning, Matthias; Schmidt, Susanne; Sheppard, Christine; et al. (Global Ecology and Biogeography, 2018)
Aim: Recent studies increasingly use statistical methods to infer biotic interactions from co- occurrence information at a large spatial scale. However, disentangling biotic interactions from other factors that can affect co-occurrence patterns at the macroscale is a major challenge. Approach: We present a set of questions that analysts and reviewers should ask to avoid errone- ously attributing species association patterns to biotic interactions. Our questions relate to the appropriateness of data and models, the causality behind a correlative signal, and the problems associated with static data from dynamic systems. We summarize caveats reported by macroeco- logical studies of biotic interactions and examine whether conclusions on the presence of biotic interactions are supported by the modelling approaches used. Findings: Irrespective of the method used, studies that set out to test for biotic interactions find statistical associations in species’ co-occurrences. Yet, when compared with our list of questions, few purported interpretations of such associations as biotic interactions hold up to scrutiny. This does not dismiss the presence or importance of biotic interactions, but it highlights the risk of too lenient interpretation of the data. Combining model results with information from experiments and functional traits that are relevant for the biotic interaction of interest might strengthen conclusions. Main conclusions: Moving from species- to community-level models, including biotic interactions among species, is of great importance for process-based understanding and forecasting ecological responses. We hope that our questions will help to improve these models and facilitate the inter- pretation of their results. In essence, we conclude that ecologists have to recognize that a species association pattern in joint species distribution models will be driven not only by real biotic interac- tions, but also by shared habitat preferences, common migration history, phylogenetic history and shared response to missing environmental drivers, which specifically need to be discussed and, if possible, integrated into models.
Keywords: biotic interactions; communities; co-occurrence; environment; residual structure; species distribution models

Bivalve Mollusks as Hosts in the Fossil Record - Huntley, John Warren; de Baets, Kenneth; Scarponi, Daniele; Linehan, Liane Christine; Epa, Y. Ranjeev; Jacobs, Gabriel S.; Todd, Jonathan A. (The Evolution and Fossil Record of Parasitism: Coevolution and Paleoparasitological Techniques, 2021)
Parasites are ubiquitous in modern ecosystems, occupy one of the most successful life modes, promote ecosystem stability, and, despite their typically diminutive size and lack of a mineralized skeleton, are commonly identified in the fossil record. Bivalve mollusks have occupied marine aquatic environments since the Cambrian, comprise an excellent fossil record, and often preserve traces of interactions with their parasites. Here we review parasite-host interactions of living bivalves and the record of parasitism of bivalves that reaches as far back as the Silurian. Escalation in parasite-host bivalve interactions seems to have occurred in both the middle Paleozoic and the late Mesozoic to Cenozoic, similar to trends documented in other antagonistic interactions.
Keywords: Parasites; Pathogens; Paleoecology; Phanerozoic; Climate

Bivalves from the Finis Shale (Virgilian) of North Central Texas – analysis of life habits and palaeoecology - Friedel, Julia C.; Amler, Michael R.W.; Seuß, Barbara (Jahrestagung der Paläontologischen Gesellschaft, 2019)

Bivalves from the Pennsylvanian Finis Shale (Virgilian) of North Central Texas - Notes on taxonomy, life habits and palaeoecology - Friedel, Julia C.; Amler, Michael R.W.; Seuß, Barbara (GSA Annual Meeting, 2019)

Brackish water algal reefs – facies analysis as a tool to identify palaeoenvironmental variations in Miocene deposits (Mainz-Weisenau, Germany) - Nohl, Theresa; Knoblach, Julia; Teichert, Sebastian (Geological Journal, 2021)
Brackish-water carbonates are far less studied than their marine or limnic counterparts. However, their association with few, specialized species enables the documentation of fine-scale changes in the depositional environment. The Cenozoic Mainz Basin (Germany) was only sporadically connected to the North Sea and the Paratethys, exposing several transitions from marine to fresh water influence. Focusing on one outcrop of the Rüssingen Formation of Mainz-Weisenau (Aquitanian, Miocene), we present a detailed analysis of the faunal and sedimentological responses to changing salinities and water depth, including algal reef growth and facies development. The deposits include allochthonous limestones surrounding an autochthonous reef complex and several smaller reef patches. The allochthonous facies is dominated by the gastropod Hydrobia inflata, and the reef facies is mainly made up by the green alga Cladophorites sp. The algal thalli are overgrown by cryptocrystalline, organic precipitations, and laminated, chemical precipitations. Locally, quiver-shaped structures of Trichoptera sp. protective cases occur. The depositional setting was a shallow, low energy, and brackish environment supersaturated by carbonate. We could not confirm a general trend of reducing salinities as reported for the Rüssingen Formation. Our results question previously reported episodic desiccation events, because apparent caliche horizons actually represent thin beds of increased Cladophorites growth. Set-up, distribution of the reef facies, and reef debris indicate short-time variations of temperature, salinity and water depth. We conclude that these variations are based on the geographic position at the edge of an algal reef barrier, separating the Mainz Basin from the Rhine Rift Valley.<br
Keywords: algal reefs; brackish deposits; Cladophorites sp.; facies development; microbial calcite precipitation

Bryozoan fauna of the Boggy Formation (Deese Group, Pennsylvanian) of the Buckhorn Asphalt Quarry, Oklahoma, USA - Ernst, Andrej; Seuß, Barbara; Taylor, Paul; Nützel, Alexander (Palaeobiodiversity and Palaeoenvironments, 2016)

Bryozoan-rich stromatolites (bryostromatolites) from the Silurian of Gotland and their relation to climate-related perturbations of the global carbon cycle - Claußen, Anna Lene; Munnecke, Axel; Ernst, Andrej (Sedimentology, 2021)
Bryozoan–stromatolite associations (bryostromatolites) formed conspicuous reef structures throughout the Sheinwoodian (Wenlock) to Ludfordian (Ludlow) stratigraphy on Gotland but have not been described so far. They are mainly composed of encrusting bryozoans forming a complex intergrowth with porostromate and spongiostromate microbes and are different from the abundant stromatoporoid–coral–algal reefs with respect to their composition. In the bryostromatolite different growth stages can be identified. The observed succession can be taken as evidence for cyclic environmental changes during reef formation. Stenohaline reef-dwelling organisms, such as echinoderms, sponges, corals and trilobites, indicate fully marine salinities. Ten localities exposing bryostromatolites were discovered. Individual bryostromatolites are small with few decimetres up to one metre in size, and occur solely in shallow marine areas. Common features of these reefs on Gotland are cauliflower-like growth, a high bryozoan diversity, a high abundance of phosphatic fossils and components such as bryozoan pearls and inarticulate phosphatic brachiopods, enhanced bioerosion, Palaeomicrocodium crusts, vadose silt and gypsum pseudomorphs. The high abundance of Palaeomicrocodium, as well as the alternation with other crust-forming contributors, suggest that it could have been formed directly at the palaeo-sea surface, probably in times of minor but high-frequency sea-level fluctuations. Vadose silt and pseudomorphs after gypsum in reef cavities indicate subaerial exposure shortly after reef growth. The high amount of phosphatic components indicates a high nutrient input, probably by dust. All bryostromatolites were formed in times of strongly elevated δ13C values. The unusual combination of sedimentological and palaeoecological features, as well as their occurrence exclusively during strong positive δ13C excursions, are evidence that the bryostromatolite development responded to climatic/oceanographic changes, which may have played an important role in reef control.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Palaeomicrocodium; phosphate; reef; stable carbon isotopes; subaerial exposure

Bryozoans from the lower Silurian (Telychian) Hanchiatien Formation from southern Chongqing, South China - Ernst, Andrej; Li, Qi Jian; Zhang, Min; Munnecke, Axel (Journal of Paleontology, 2021)
Eight bryozoan species are described from the Hanchiatien Formation (lower Silurian, Telychian) of southern Chongqing, South China. Four species are new: the trepostomes Asperopora sinensis n. sp., Trematopora jiebeiensis n. sp., and Trematopora tenuis n. sp., and the fenestrate Moorephylloporina parvula n. sp. One species, the cystoporate Hennigopora sp. indet., is described in open nomenclature. Moorephylloporina parvula n. sp. is eurytopic, occurring in all types of facies within the bioherms. Erect Moorephylloporina Bassler, 1952, Trematopora Hall, 1852, and Leioclema Ulrich, 1882 formed pioneering communities on weakly cemented substrata, whereas encrusting Fistulipora M'Coy, 1849, Hennigopora Bassler, 1952, and Asperopora Owen, 1969 occurred on hardgrounds and formed densely compact framestones. Robust branched Trematopora and Leioclema tend to occur out of the reef core (framework) where they could have formed reef-flank thickets in more agitated conditions. The generic composition of the studied fauna correlates with other localities in South China, and they show general paleobiogeographic relations to Siberia and Indiana, USA. UUID http://zoobank.org/3326dd2f-7c9e-43bc-9dab-84047b274f89
CRIS-Team Scopus Importer:2021-03-26

Buckman’s Rules of Covariation - de Baets, Kenneth; Monnet, Claude; Yacobucci, Margaret M. (Ammonoid Paleobiology: From macroevolution to paleogeography, 2015)

Buoyancy mechanisms limit preservation of coleoid cephalopod soft tissues in Mesozoic Lagerstätten - Clements, Thomas; Colleary, Caitlin; de Baets, Kenneth; Vinther, Jakob (Palaeontology, 2017)
Coleoid cephalopods are characterized by internalization of their shell, and are divided into the ten-armed Decabrachia (squids and cuttlefish) and the eight-armed Vampyropoda (octopuses and vampire squid). They have a rich fossil record predominantly of the limited biomineralized skeletal elements they possess: arm hooks, statoliths, mouthparts (the buccal mass) and internal shell (gladius or pen), although exquisitely preserved soft tissue coleoids are known from several Lagerstatten worldwide. Recent studies have shown that although morphological similarities between extant decabra-chian gladii and fossil examples exist, no known examples of fossil decabrachians are currently known. However, molecular clock data and phylogenetic bracketing suggest that they should be present in Lagerstatten that are rich in vampyropod soft tissue fossils (i.e. Hakel and Hadjoula Lagerstatten, Cretaceous, Lebanon). We propose that a hitherto unknown taphonomic bias pertaining to the differing methods of buoyancy control within coleoid groups limits preservation potential. Both negatively and neutrally buoyant decabrachians use chemical buoyancy control (ammonia) whereas vampyropods do not. In the event of rapid burial in an environment conducive to exceptional preservation, ammonia dramatically decreases the ability of the decabrachian carcass to generate the required pH for authigenic calcium phosphate replacement, limiting its preservation potential. Moreover, the greater surface area and comparatively fragile dermis further decrease the potential for fossilization. This taphonomic bias may have contributed to the lack of preserved labile soft-tissues in other cephalopods groups such as the ammonoids.
Keywords: coleoid; cephalopod; buoyancy; calcium phosphate; taphonomy; bias

Burned and devoured-Introduced herbivores, fire, and the endemic flora of the high-elevation ecosystem on La Palma, Canary Islands - Irl, Severin; Steinbauer, Manuel; Messinger, Jana; Blume-Werry, Gesche; Palomares Martínez, Angel; Beierkuhnlein, Carl; Jentsch, Anke (Arctic, Antarctic, and Alpine Research, 2014)
Novel disturbance regimes (e.g., introduced herbivores and fire) are among the major drivers of degradation in island ecosystems. High-elevation ecosystems (HEEs) on islands might be especially vulnerable to these disturbances due to high endemism. Here, data from an 11-year exclosure experiment in the HEE of La Palma (Canary Islands) are presented where mammalian herbivores have been introduced. We investigate the combined effect of herbivory and fire on total species richness, seedling richness, and seedling establishment on the whole system and a subset of highly endangered species (target species). Total species richness, seedling species richness, and seedling establishment decreased with herbivory. Five out of eight target species were exclusively found inside the exclosures indicating the negative impact of introduced herbivores on endemic high elevation flora. Target species were generally affected more negatively by introduced herbivores and were subject to significantly higher browsing pressure, probably owing to their lack of defense strategies. A natural wildfire that occurred six years before data sampling substantially increased total species richness and seedling richness in both herbivory exclosure and reference conditions. We conclude that species composition of the HEE has been severely altered by the introduction of non-native herbivores, even though fire seems to have a positive effect on this system.

Calcareous algae from the Triassic (Anisian reef boulders and Norian reef limestones) of Karaburun, western Turkey - Senowbari-Daryan, Baba; Link, Michael; Isintek, Ismail (Facies, 2006)
Invertebrate Anisian and Norian reef boulders were found in the Gerence and Güvercinlik Formations, respectively, exposed in northeastern part of the Karaburun Peninsula, western Turkey. Halimedacean green algae and solenoporacean red algae, usually associated with other reef building organisms are described in this paper. The following taxa were determinated: halimedaceans: Egericodium hungaricum Flügel, Velledits, Senowbari-Daryan and Riedel, Aternasus irregularis n. gen., n. sp.; solenoporaceans: Solenopora cf. alcicornis Ott, Solenopora triasina Vinassa de Regny, Solenopora vachardi n. sp., Solenopora concentrica n. sp., Solenopora paraconcentrica n. sp., Tauristorea parallela Senowbari-Daryan and Link, Tauristorea discursa n. sp., and Parachaetetes cassianus (Flügel). The monospecific genus Aternasus n. gen. is the most abundant alga within the Anisian reef boulders. The solenoporaceans are represented by several taxa but the individual species are less abundant. E. hungaricum, T. parallela Senowbari-Daryan and Link, and S. triasina Vinassa de Regny are described from the Norian reef limestones embedded in Güvercinlik Formation, all other taxa from the Anisian reef boulders embedded in the Gerence Formation. © Springer-Verlag 2005.
UnivIS-Import:2015-04-14:Pub.2006.nat.dgeo.IGM.LP.calcar
Keywords: Algae; Anisian; Karaburun; Norian; Triassic; Turkey

"Calcispheres" as a source of lime mud and peloids evidence from the early Middle Devonian of the Prague Basin, the Czech Republic - Berkyová, Stanislava; Munnecke, Axel (Bulletin of Geosciences, 2010)
Several types of peloids are present in the Lower and Middle Devonian limestones of the Prague Basin (uppermost part of the Třebotov Limestone of the Daleje-Třebotov Formation and Choteč Formation, uppermost Emsian-Eifelian) and are interpreted as being of calcispheral, echinoderm, and/or calcimicrobial origin. Possible mechanisms of peloid formation, the mode of life of calcispheres and their role in the accumulation of Paleozoic lime mud are discussed. Mass occurrences of peloids and calcispheres are characteristic features of the Choteč Formation (Eifelian, costatus-kockelianus conodont zones). It is concluded that specific environmental conditions, such as a higher nutrient load, existed during the sedimentation of this unit, probably in response to the Basal Choteč event.
Keywords: Calcispheres; Devonian; Lime mud; Micritization; Peloids; Prague basin

Calcium isotope record of Phanerozoic oceans: Implications for chemical evolution of seawater and its causative mechanisms - Farkaš, Juraj; Eisenhauer, Anton; van Geldern, Robert; Munnecke, Axel; et al. (Geochimica Et Cosmochimica Acta, 2007)
A total of 280 brachiopods of Ordovician to Cretaceous age, complemented by published data from belemnites and planktonic foraminifera, are used to reconstruct the evolution of calcium isotope composition of seawater (δCa) over the Phanerozoic. The compiled δCa record shows a general increase from ∼1.3‰ (NIST SRM 915a) at the beginning of the Ordovician to ∼2‰ at present. Superimposed on this trend is a major long-term positive excursion from the Early Carboniferous to Early Permian as well as several short-term, mostly negative, oscillations. A numerical model of the global cycles of calcium, carbon, magnesium and strontium was used to estimate whether the recorded δCa variations can be explained by varying magnitudes of input and output fluxes of calcium to the oceans. The model uses the record of marine Sr/Sr ratios as proxy for seafloor spreading rates, a record of oceanic Mg/Ca ratios to estimate rates of dolomite formation, and reconstructed atmospheric CO, discharge and erosion rates to estimate continental weathering fluxes. The model results indicate that varying magnitudes of the calcium input and output fluxes cannot explain the observed δCa trends, suggesting that the isotope signatures of these fluxes must also have changed. As a possible mechanism we suggest variable isotope fractionation in the sedimentary output flux controlled by the dominant mineralogy in marine carbonate deposits, i.e. the oscillating 'calcite-aragonite seas'. The ultimate control of the calcium isotope budget of the Phanerozoic oceans appears to have been tectonic processes, specifically variable rates of oceanic crust production that modulated the hydrothermal calcium flux and the oceanic Mg/Ca ratio, which in turn controlled the dominant mineralogy of marine carbonates, hence the δCa. As to the causes of the short-term oscillations recorded in the secular δCa trend, we tentatively propose that these are related to variable rates of dolomite formation and/or to changing chemical composition of the riverine flux, in particular Ca / HCO and Ca / SO ratios, induced by variable proportions of silicate vs. carbonate weathering rates on the continents. © 2007 Elsevier Ltd. All rights reserve

Cambrian to Lower Ordovician reefs on the Yangtze Platform, South China Block, and their controlling factors - Zhang, Yuanyuan; Li, Qijian; Li, Yue; Kießling, Wolfgang; Wang, Jianpo (Facies, 2016)
The Yangtze Platform, South China Block, maintained an epicontinental sea in the Cambrian and Ordovician with oldlands surrounding its northern and western margins and a southeastern slope belt. Many Cambrian to Lower Ordovician reef complexes are known from the Yangtze Platform for which an updated spatiotemporal framework is provided, their biotic composition and architecture is presented, and the reef development is discussed in a global context. The biotic structures of reef units on the Yangtze Platform largely match the evolutionary pattern in terms of composition and architecture. Microbes and calcareous algae are key components in all reefs but metazoan reef-builders are better suited to identifying macroevolutionary patterns. Large-scale dolomitization in Cambrian Series 4 on the one hand prevents recognition of metazoan reefs and on the other hand may indicate hypersaline environments, which prevented metazoan reef growth and only permitted small-scale stromatolites in a few regions. Ordovician metazoans appear to have played substantial roles in reef-building earlier on the Yangtze Platform than elsewhere. Specifically bryozoan and Calathium-lithistid sponge reefs diversified during the Early Ordovician. Climate and eustatic sea-level changes and their related impact on water energy, turbidity, and salinity determined the growth and demise of reefs. The morphology and arrangement of reefs were controlled by the topography of the sea floor.
UnivIS-Import:2016-06-01:Pub.2016.nat.dgeo.IGM.LP.cambri
Keywords: Cambrian; Early Ordovician; Paleogeography; Reefs; South China Block; Yangtze Platform

Cambro-Ordovician sea level fluctuations and sequence boundaries: the missing record and the evolution of new taxa - Lehnert, Oliver; Miller, James F.; Leslie, Stephen A.; Repetski, John E.; Ethington, Raymond L. (Special Papers in Palaeontology Series, 2005)
The evolution of early Palaeozoic conodont faunas shows a clear connection to sea-level changes. One way that this connection manifests itself is that thick successions of carbonates are missing beneath major sequence boundaries due to karstification and erosion. From this observation arises the question of how many taxa have been lost from different conodont lineages in these incomplete successions. Although many taxa suffered extinction due to the environmental stresses associated with falling sea-levels, some must have survived in these extreme conditions. The number of taxa missing in the early Palaeozoic tropics always will be unclear, but it will be even more difficult to evaluate the missing record in detrital successions of higher latitudes. A common pattern in the evolution of Cambrian-Ordovician conodont lineages is appearances of new species at sea-level rises and disappearances at sea-level drops. This simple picture can be complicated by intervals that consistently have no representatives of a particular lineage, even after extensive sampling of the most complete sections. Presumably the lineages survived in undocumented refugia. In this paper, we give examples of evolution in Cambrian-Ordovician shallowmarine conodont faunas and highlight problems of undiscovered or truly missing segments of lineages. © The Palaeontological Association.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LG.cambro
Keywords: Cambrian; Conodont record; Evolution; Ordovician; Sea-level changes; Sequence stratigraphy

Cambro-Ordovician sponge spicule assemblages in the Ordovician of the Argentine Precordillera and paleoenvironmental ties - Jaanussen, Dorte; Lehnert, Oliver (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 1997)

Cameral deposits in a sublethally damaged Pennsylvanian “Michelinoceras sp.” from the Buckhorn Asphalt Lagerstätte in Oklahoma, USA - Seuß, Barbara; Mapes, Royal H.; Klug, Christian; Nützel, Alexander (Annual Meeting of the Palaeontological Association, 2010)
The recovery of two well-preserved chambers of the phragmocone of Pseudorthoceras sp. from the Buckhorn Asphalt Lagerstätte provides nw insight into the controversy over how cameral deposits are developed in orthoconic nautiloids. The specimen has two oval openings in the conch, a result of penetrating the outer test and present cameral deposits. The animan survived the attack and was able to still precipitate cameral deposits, astonishing because in the orad chamber the bite-marks opened the chamber to the seawater. Three hypotheses of cameral deposit precipitation can be tested: (1) direct precipitation from the cameral fluid; (2) precipitation from the cameral fluid with a reoccurring organic template/membrane; (3) secretion by a cameral tissue. (1) and (2) cannot be supported because the precipitation chemistry of the cameral fluid is altered and cannot be controlled by the animal. (3) remains possible: the penetration marks would be sealed by cameral tissue regeneration and cameral deposits would be precipitated directly by such tissue. Thus, the cameral fluid chemistry would appear not to be important for cameral deposit precipitation. Anyhow, this hypothesis remains problematic: there are no known openings that would allow tissure connections from the siphuncle through the connecting ring to the cameral deposit

Cameral deposits in a sublethally damaged Pennsylvanian Pseudorthoceras sp. from the Buckhorn Asphalt Lagerstätte in Oklahoma, USA - Seuß, Barbara; Mapes, Royal H.; Klug, Christian; et al. (Annual Meeting of the Paläontologische Gesellschaft, 2010)
The recovery of two well-preserved chambers of the phragmocone of Pseudorthoceras sp. from the Buckhorn Asphalt Lagerstätte provides nw insight into the controversy over how cameral deposits are developed in orthoconic nautiloids. The specimen has two oval openings in the conch, a result of penetrating the outer test and present cameral deposits. The animan survived the attack and was able to still precipitate cameral deposits, astonishing because in the orad chamber the bite-marks opened the chamber to the seawater. Three hypotheses of cameral deposit precipitation can be tested: (1) direct precipitation from the cameral fluid; (2) precipitation from the cameral fluid with a reoccurring organic template/membrane; (3) secretion by a cameral tissue. (1) and (2) cannot be supported because the precipitation chemistry of the cameral fluid is altered and cannot be controlled by the animal. (3) remains possible: the penetration marks would be sealed by cameral tissue regeneration and cameral deposits would be precipitated directly by such tissue. Thus, the cameral fluid chemistry would appear not to be important for cameral deposit precipitation. Anyhow, this hypothesis remains problematic: there are no known openings that would allow tissure connections from the siphuncle through the connecting ring to the cameral deposit

Carbon and oxygen isotope fractionation in the Late Devonian heterocoral Oligophylloides: Implications for the skeletogenesis and evolution of the Heterocorallia - Dworczak, Patrycja Genowefa; López Correa, Matthias; Jakubowicz, Michal; Munnecke, Axel; Joachimski, Michael; Mazzoli, Claudio; Berkowski, Blazej (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
The order Heterocorallia is an enigmatic, anatomically distinct group of calcifying Palaeozoic corals with unclear affinities to other, either extinct or modern cnidarian lineages. Here, we present results of microstructure and stable isotope studies on exceptionally well-preserved skeletons of two species of the heterocoral Oligophylloides from the Famennian (Upper Devonian) of the Anti-Atlas, Morocco and the Holy Cross Mountains, Poland. The investigations provide new information on the skeletogenesis and isotope fractionation effects in Palaeozoic heterocorals. In order to estimate the possible role of diagenetic alteration on the observed carbon and oxygen isotope ratios, we have conducted several preservation tests, including transmitted-light, scanning-electron, fluorescence and cathodoluminescence microscopy, Raman spectroscopy, and trace element analyses. The least- and most-altered skeleton portions identified based on this approach are typified by clearly different isotopic signatures. The least-altered parts of the specimens reveal carbon and oxygen isotope ratios close to those of contemporaneous marine-equilibrated calcites. The moderately-pronounced, positive correlations between the δ13C and δ18O values observed for these coralla may reflect relatively minor vital fractionation effects, obscured to some degree by diagenetic overprint. The results suggest that the isotope fractionation mechanisms of the heterocorals differed markedly from the significant kinetic fractionation characteristic of the modern scleractinian corals. Rather, the moderate, if any, extent of non-equilibrium fractionation during skeletogenesis in the Heterocorallia resembled the typical, environmental and metabolic CO2-dominated fractionation effects shown by most other marine calcifiers. These include the extinct rugose corals, modern hydrocorals and, in particular, modern octocorals, with which the heterocorals show notable architectural and structural similarities.<br
Keywords: Heterocorallia; Cnidaria; Carbon and oxygen isotopes; Microstructure; Morocco; Poland

Carbonate budget of a cold-water coral mound (Challenger Mound, IODP Exp. 307) - Titschack, Jürgen; Thierens, M; Dorschel, Boris; Schulbert, Christian; Freiwald, André; Kano, A; Takashima, C; Kawagoe, N; Li, X (Marine Geology, 2009)
Cold-water coral ecosystems represent a worldwide distributed carbonate factory, which is so far not considered in global carbonate budget estimations. The herein presented study evaluates the carbonate budget of a complete cold-water coral mound sequence from Challenger Mound (Belgica Mound Province, Porcupine Seabight, SW offshore Ireland; drilled during IODP Expedition 307) reaching back to the Late Pliocene (< 2.7 Ma) especially focusing on the different carbonate sources (coral-derived aragonite versus background-sediment-derived calcite-dominated carbonate). Cores from adjacent drift deposits were examined for comparison studies. Challenger Mound, which developed in a fast growth phase (unit M1; 2.7 to 1.6 Ma) and a slower growth phase or mound-decline (unit M2; 0.8 Ma until today), separated by a so called 'mound crisis', displays increased carbonate accumulation rates for both phases (17.3 g/(cm2 × ka) for unit M1 and 5.7 g/(cm2 × ka) for unit M2) compared to adjacent drift deposits. But only about 33 to 40 wt.% of the carbonate is derived from corals. Bulk sedimentation rates of on- and off-mound deposits suggest a decline of Challenger Mound since the onset of drift deposition in the area about 1.2 Ma ago. Yet total carbonate accumulation rates as well as hemipelagic Background-Sediment-Derived Carbonate accumulation rates from Challenger Mound (unit M2) still exceed the carbonate accumulation rates of the adjacent drift deposits. The selective enrichment of Background-Sediment-Derived Carbonate (by a factor of 2.0) in a CWC Mound is herein observed for the first time. This might be caused by the different hydrodynamic behaviour and slower settlement of marine fluff rich in calcareous detritus, compared to siliciclastic sediments, and its effective baffling by the coral framework and/or the active catch of the calcareous plankton by the corals. The carbonate accumulation rates of Challenger Mound are about 4 to 12% of the carbonate accumulation rates of tropical shallow-water reefs but exceeds the carbonate accumulation rates of continental slopes by a factor of 3.9 to 11.8. The carbonate production for the entire Belgica Mound Province is estimated with 3.2 × 103 t/a for unit M1 and 1.0 × 103 t/a for unit M2. © 2009 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.carbon
Keywords: carbonate budget; carbonate source; Challenger Mound; cold-water coral mound; IODP Expedition 307; NE Atlantic

Carbonate concretions in Miocene mudrocks in NW Algeria: types, geochemistry, and origins - Nemra, Abdelkrim; Ouali Mehadji, Abdelkader; Munnecke, Axel; Belkhedim, Salim; Belkebir, Lahcen (Facies, 2019)
Carbonate concretions have been recorded in many recent and ancient marine sediments around the world. The Middle Miocene marl of the Tenes area, situated in the northeast of the Lower Chelif Basin in NW-Algeria, contains such carbonate concretions but with a variety of different structures and morphologies. Three different basic types are distinguished: nodular (spheroidal, ellipsoidal, disc, and irregular), stratiform, and tubular concretions, the last locally have a central conduit. The close association between carbonate concretions and synsedimentary deformation structures (synsedimentary faults, slumps) and normal faults, pronounced in the Ounsour Anhas outcrop, indicates synsedimentary instability related to upward fluid movement. The concretions were formed by precipitation of micritic carbonate within the host marl at shallow burial depth, probably in the active microbial methanogenesis zone. Strongly varying δ13C values (− 9.82 to + 5.85‰ PDB) are interpreted as the result of the balance between 13C-enriched (residual CO2 from methanogenesis) and 13C-depleted (microbial organic matter decomposition) CO2 added to the pore solutions. δ18O values (− 2.39 to + 1.71‰ PDB) indicate that carbonate concretion growth occurred during early diagenesis conditions, from marine-derived pore-wate

Carbon isotope development in the Ordovician of the Yangtze Gorges region (South China) and its implication for stratigraphic correlation and paleoenvironmental change - Zhang, Yuandong; Cheng, Junfeng; Munnecke, Axel; Zhou, Chuanming (Journal of Earth Science, 2010)
This study was supported by the Chinese Academy of Sciences (No. KZCX2-YW-122), the Ministry of Science and Technology (Nos. 2006CB806402, 2006FY1203000-4), and the National Natural Science Foundation of China (No. 40532009).
Keywords: Yangtze region; Carbon Isotopes; Ordovician

Carbon isotope record of Late Cambrian to Early Ordovician carbonates of the Argentine Precordillera - Buggisch, Werner; Lehnert, Oliver; Keller, Martin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
A more than 2000-m-thick Cambrian-Ordovician carbonate platform succession developed on the exotic Argentine Precordillera terrane during rifting from Laurentia and drifting towards Gondwana. On base of these carbonates, a carbon isotope curve could be developed for the Cambrian-Ordovician. We measured δ13Ccarb and δ13Corg values on bulk rocks, selected components and diagenetic cements. Whereas the carbon isotope signals of intertidal and supratidal rocks are altered by diagenesis, most subtidal carbonates exhibit primary marine values. We can report reliable curves for the Middle-Late Cambrian transition and for the latest Cambrian to earliest Middle Ordovician. The δ13C curve matches well with the published data from global Cambrian-Ordovician boundary sections. Excursions and shifts in the carbon isotope curve correspond to events in sequence stratigraphy. This indicates the interdependence on sea level which rules the productivity and/or preservation of organic carbon and therefore the partition between Corg and Ccarb burial. © 2003 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dgeo.IGM.LG.carbon
Keywords: Argentina; Cambrian; Carbon isotopes; Ordovician; Precordillera

Cave finds indicate elk (Alces alces) hunting during the Late Iron Age in the Bavarian Alps - López Correa, Matthias; Pasda, Kerstin; Stojakowits, Philipp; Häck, Bernhard; Prieto, Jérôme; al-Fudhaili, Najat; Mayr, Christoph (E&G : Quaternary Science Journal, 2020)
The finding of a partially preserved elk skeleton from the Bavarian Alps is reported. Remnants of an adult male were found, together with skeletal elements of juvenile moose calves, at the base of a talus cone in the pit cave Stiefelschacht, next to Lenggries (southern Germany). The adult's bones exhibited anthropogenic traces like cut marks and were radiocarbon-dated to the Late Iron Age. A projectile hole in the left shoulder blade and cut marks on the bones are indicative of hunting and meat usage. The elk remains were associated with several wild and domestic species such as ungulates and hare but were not, however, accompanied by archaeological artefacts. Other archaeological sites of the Late Iron Age are so far not known within a distance of less than 30 km to the Stiefelschacht. While the presence of elk during prehistoric times in the Alps has already been known before, the finds and the location are unique in that they are the first evidence of elk hunting during the Late Iron Age in the northern Alp

Cenomanian-Coniacian (Upper Cretaceous) bivalves of the Sergipe Basin, Brazil: Order Pholadomyida - Ayoub-Hannaa, Wagih; Bengtson, Peter; Fürsich, Franz; Andrade, Edilma de Jesus (Revista Brasileira de Paleontologia, 2015)
Twenty-two species of the bivalve order Pholadomyida, belonging to six genera and seven subgenera of the families Pholadomyidae, Pleuromyidae and Poromyidae are described from the Cenomanian–Coniacian Cotinguiba Formation of the Sergipe Basin, north-eastern Brazil. Eleven species, Pholadomya (Ph.) cf. agrioensis Weaver, Ph. (Ph.) kasimiri Pusch, Ph. (Ph.) nodulifera Münster, Ph. (Ph.) occidentalis Morton, Ph. (Procardia) vignesi Lartet, Pleuromya ligeriensis (d’Orbigny), Pl. servesensis Choffat, Liopistha (L.) aequivalvis (Goldfuss), L. (Psilomya) elongata Stanton, L. (P.) globulosa (Forbes) and L. (Sergipemya) gigantea (J. Sowerby) are recorded from the Sergipe Basin for the first time. The new subgenus Sergipemya of the genus Liopistha, family Poromyidae, is erected on the basis of morphological characters such as numerous commarginal ribs, large and highly inflated valves, a well-developed rounded umbonal anterior ridge bordering a deep depression on the anterior part, and the presence of two unequal cardinal teeth with a cardinal tear-shaped socket in the left valve. The pholadomyid fauna of Sergipe closely resembles that of other Tethyan regions in western and southern Europe, northern and western Africa and the Middle East. The distribution patterns of the taxa were probably influenced by east–west-directed currents. Southern Tethyan pholadomyids reached western Africa and north-eastern South America via the Trans-Saharan Seaway.
UnivIS-Import:2017-12-18:Pub.2015.nat.dgeo.IGM.LP.cenoma
Keywords: Pholadomyida; taxonomy; palaeobiogeography; Cretaceous; Cotinguiba Formation; Brazil

Cenomanian (Upper Cretaceous) bivalves from the Hameimat Massifs, north of Tebessa, Algeria: Systematics, biostratigraphy, palaeoecological and taphonomical remarks Bivalves cénomaniens (Crétacé supérieur) des Massifs de Hamiemat, nord de Tébessa, Algérie : Systématique, biostratigraphie, et implications paléoécologiques et taphonomiques - Mendir, Samira; Salmi-Laouar, Sihem; El Qot, Gamal M.; Ayoub-Hannaa, Wagih; Ferré, Bruno (Annales De Paleontologie, 2021)
In the eastern Saharan Atlas, particularly in the northern area of Tebessa Province (NE Algeria), the widely outcropping Cenomanian strata display a highly diversified macrofauna, among which bivalves are prominently represented. Twenty-eight bivalve species are here reported for the first time from the Cenomanian of Hameimat Massifs. Based on the stratigraphic distribution of these bivalves, five bivalve zones were recognized, i.e., Costagyra olisiponensis - Gyrostrea delettrei, Rhynchostreon suborbiculatum - Exogyra conica, Ceratostreon flabellatum, Ilymatogyra africana, and Pycnodonte vesicularis vesiculosa - Rastellum carinatum zones. Correlation to the ammonite biozones of the same region as follows: the Costagyra olisiponensis - Gyrostrea delettrei and the Rhynchostreon suborbiculatum - Exogyra conica zones occur respectively in the Sharpeiceras schlueteri and Mantelliceras saxbii subzones of the lower Cenomanian Mantelliceras mantelli Zone. The Ceratostreon flabellatum Zone is correlated with the middle Cenomanian Acanthoceras rhotomagense Zone. The Ilymatogyra africana Zone is correlated with the upper Cenomanian Calycoceras naviculare and the Metoicoceras geslinianum zones. Finally, the Pycnodonte vesicularis vesiculosa - Rastellum carinatum Zone represents the uppermost Cenomanian. Detailed analysis of biometrical and morphological features of these bivalve specimens provides the most reliable tool within the scope of palaeo-environmental reconstitution and the many palaeo-ecological variables that had driven the development and distribution of these macro-invertebrates. Comparison of these new data to those of adjacent south Tethyian areas supports the homogeneity of the Cenomanian bivalve faunas. Such an affinity underlines more vividly the favorable marine communications and currents driving the geographic dispersal of these bivalves during the Cenomanian.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Algeria.; Biozonation; Bivalves; Cenomanian; Eastern Saharan Atlas; Systematics

Cephalopoda - Seuß, Barbara; Mapes, Royal H. (IGCP 596 Climate Change and Biodiversity Patterns in the Mid-Palaeozoic, 2016)

Cephalopod palaeobiology: evolution and life history of the most intelligent invertebrates - Klug, Christian; Bonnaud-Ponticelli, Laure; Nabhitabhata, Jaruwat; Fuchs, Dirk; de Baets, Kenneth; Cheng, Ji; Hoffmann, Rene (Swiss Journal of Palaeontology, 2022)
Sigurd von Boletzky was a cephalopod researcher who was world-renowned for his enthusiasm for his field of research, for his friendly and calm personality, and, of course, his publications. He dedicated most of his life as active researcher on the development, biology and evolution of coleoids. Nevertheless, he was always curious to learn about other cephalopods as well. Sigurd passed away in Switzerland on September 28th 2020. We dedicate this text and volume to his memory.
CRIS-Team WoS Importer:2022-06-03

Chaetetids from the Upper Carboniferous Buckhorn Asphalt Quarry Lagerstätte, Oklahoma - Seuß, Barbara; Senowbari-Daryan, Baba; Nützel, Alexander (Annual Meeting of the Paläontologische Gesellschaft, 2013)
Chaetetid sponges from the Desmoinesian Buckhorn Asphalt Quarry Lagerstätte represent the largest benthic organisms in this outcrop (max. diameter: 21 cm, max. height: 8.3 cm). Deposition of the chaetetid-bearing sediments occurred in a shallow (euphotic zone II-III) marine setting near the palaeo-equator. The siliciclastic-carbonatic sediments from the Lagerstätte were impregnated by migrating hydrocarbons during or shortly after deposition hence, fossil preservation is generally outstanding. Chaetetid skeletons from the quarry originally consisted of high Mg-calcite. Two morphotypes are present, comprising domical and laminar growth, which indicates genetic rather than environmental control. Internal skeletal features comprise tabulae, spine-like projections, pseudoseptae, growth disturbances, and greyish structures. Tubule diameter and length is variable, and spicules are absent. Skeletal fragmentation is common and indicates complex taphonomic mechanisms. Some specimens display large incisions indicating physical impact. The skeletal surface is also often covered by microbial mats associated with Mn-carbonatic cement

Chaetetids from the Upper Carboniferous Buckhorn Asphalt Quarry Lagerstätte, Oklahoma - Seuß, Barbara; Senowbari-Daryan, Baba; Nützel, Alexander (Annual Meeting of the Palaeontological Association, 2013)
Chaetetid sponges from the Desmoinesian Buckhorn Asphalt Quarry Lagerstätte represent the largest benthic organisms in this outcrop (max. diameter: 21 cm, max. height: 8.3 cm). Deposition of the chaetetid-bearing sediments occurred in a shallow (euphotic zone II-III) marine setting near the palaeo-equator. The siliciclastic-carbonatic sediments from the Lagerstätte were impregnated by migrating hydrocarbons during or shortly after deposition hence, fossil preservation is generally outstanding. Chaetetid skeletons from the quarry originally consisted of high Mg-calcite. Two morphotypes are present, comprising domical and laminar growth, which indicates genetic rather than environmental control. Internal skeletal features comprise tabulae, spine-like projections, pseudoseptae, growth disturbances, and greyish structures. Tubule diameter and length is variable, and spicules are absent. Skeletal fragmentation is common and indicates complex taphonomic mechanisms. Some specimens display large incisions indicating physical impact. The skeletal surface is also often covered by microbial mats associated with Mn-carbonatic cement

Challenges and directions in analytical paleobiology - Dillon, Erin; Dunne, Emma; Womack, Tom; Kouvari, Miranta; Larina, Ekaterina; Claytor, Jordan Ray; Ivkić, Angelina; Juhn, Mark; Milla Carmona, Pablo; Robson, Selena Viktor; Saha, Anwesha; Villafaña, Jaime; et al. (Paleobiology, 2023)
Over the last 50 years, access to new data and analytical tools has expanded the study of analytical paleobiology, contributing to innovative analyses of biodiversity dynamics over Earth's history. Despite—or even spurred by—this growing availability of resources, analytical paleobiology faces deep-rooted obstacles that stem from the need for more equitable access to data and best practices to guide analyses of the fossil record. Recent progress has been accelerated by a collective push toward more collaborative, interdisciplinary, and open science, especially by early-career researchers. Here, we survey four challenges facing analytical paleobiology from an early-career perspective: (1) accounting for biases when interpreting the fossil record; (2) integrating fossil and modern biodiversity data; (3) building data science skills; and (4) increasing data accessibility and equity. We discuss recent efforts to address each challenge, highlight persisting barriers, and identify tools that have advanced analytical work. Given the inherent linkages between these challenges, we encourage discourse across disciplines to find common solutions. We also affirm the need for systemic changes that reevaluate how we conduct and share paleobiological research.<br

Challenging asymmetric cements as indicators of vadose diagenesis: “pseudo‑gravitational” cements from the lower Pliensbachian of the Traras Mountains in NW Algeria - Belkhedim, Salim; Munnecke, Axel; Benhamou, Miloud; Nemra, Abdelkrim; Sadji, Radouane (Facies, 2019)

Changes in calcareous nannoplankton assemblages around the Eocene-Oligocene climate transition in the Hungarian Palaeogene Basin (Central Paratethys) - Nyerges, Anita; Kocsis, Ádám; Palfy, Jozsef (Historical Biology, 2020)
The Eocene-Oligocene climate transition (EOT) is the last major greenhouse-icehouse climate state shift in Earth history, ending the warm, ice-free early Palaeogene world and ushering in the Antarctic glaciation. This study is focused on the Hungarian Palaeogene Basin within the Central Paratethys, aiming to characterise the effect of the global cooling event in the calcareous nannoplankton assemblages and to reconstruct the palaeoenvironmental evolution of the region. Calcareous nannoplankton biostratigraphy is focused on documenting the NP21 Zone. Hierarchical cluster analysis allowed us to distinguish five successive assemblages. Thereby defined phases are compared with recently published trends in delta O-18 values and foraminiferal changes. Taxa with a preference for oligotrophic and warm surface waters dominate the lowest assemblage. The next assemblage contains taxa that indicate oligotrophic conditions but temperate surface water at the onset of the EOT. Nannoplankton abundance drops to a minimum in the third phase, when taxa adapted to cool surface waters gradually became dominant. A gradual rebound of nannoplankton abundance is observed in the fourth phase, possibly reflecting regional climate change related to the uplifting Alpine chain. After the end of the EOT, the youngest assemblage includes mostly eurytopic taxa which could tolerate an increased rate of freshwater and terrestrial influx.
CRIS-Team WoS Importer:2020-01-21

Changes in corallite sizes of scleractinian corals across major hyperthermal events - Dimitrijevic, Danijela; Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (Progressive Palaeontology 2021 - Online, 2021)
Global warming today is taking its toll on coral reefs globally, particularly affecting scleractinian corals which rely on their symbionts for nutrition. In the past, hyperthermal events have probably triggered evolutionary losses and gains of symbiosis in corals. Accordingly, we expect photosymbiotic corals to be more strongly affected than non-symbiotic corals. Corallite sizes have been used as a proxy for the efficacy of photosymbiosis with smaller corallite sizes associated with higher photosymbiotic autotrophy in colonial corals. Using a new database on corallite sizes of fossil corals collected from existing literature and data on modern corals from the Coral Trait Database combined with occurrences from the Paleobiology Database, we test how the dependency on photosynthetic diet in corals may have increased their extinction risk. We expect corals to be selected against small corallite sizes during hyperthermal events. Based on a survey of 353 fossil and recent coral genera we establish trends in corallite sizes across the Triassic–Jurassic, Pliensbachian–Toarcian, Barremian–Aptian, Cenomanian–Turonian, and Paleocene–Eocene. We find a significant increase in corallite diameter of all corals at three of these events. Colonial corals had 0.8 times larger corallites in the Aptian than in the Barremian suggesting stronger heterotrophy at this hyperthermal event. However, generalized linear modelling suggests that the extinction of scleractinian corals seems to be non-selective with regards to their corallite sizes. This indicates that processes other than warming, such as increased sediment input could be the cause of this change.<br

Changes in foraminiferal assemblages and environmental conditions during the T-OAE (Early Jurassic) in the northern Lusitanian Basin, Portugal - Reolid, M.; Duarte, L. V.; Rita, Patricia (Palaeogeography, Palaeoclimatology, Palaeoecology, 2019)
The foraminiferal assemblages and other microfossils from the Rabacal area (Maria Pares section) in the Lusitanian Basin (Portugal) provide new insights regarding the Toarcian Oceanic Anoxic Event (T-OAE). Complementary analysis of the delta C-13, total organic carbon (TOC) and geochemical redox and palaeoproductivity proxies reflect environmental changes that affected the microfossil assemblages. Detailed analyses of foraminiferal assemblages (their diversity, abundance, morphogroups and lifestyle) and geochemistry led us to discern phases of the biotic crisis and subsequent stages of recovery. Environmental instability, which began in the lattermost part of the Polymorphum Zone, is marked by a lesser abundance of foraminifera and ostracods, increased opportunist foraminifera, fluctuations in TOC values and the enrichment factor of phosphorous (P-EF), as well as the onset of a negative carbon isotopic excursion (CIE). The peak phase of the biotic crisis corresponds with the lowest values for foraminiferal diversity and abundance (including a barren sample for benthic microfossils). The abundance and diversity of echinoderms, brachiopods, dinoflagellate cysts and calcareous nannofossils dropped sharply during the peak phase. This biotic crisis also entails extinction of the Order Metacopina and a local disappearance of echinoderms and brachiopods. Anoxic conditions at sea bottom did not develop, given the almost continuous record of foraminifera and trace fossils, yet oxygen-depleted conditions occurred. The lower part of the Levisoni Zone contains thin nodular limestones corresponding to a tempestitic-turbiditic facies. In this context, the re-oxygenation of bottom waters was favoured, as indicated by the presence of Thalassinoides and the low values of TOC and redox-sensitive elements (Mo, Ni and U). The survival phase in the wake of the biotic crisis is characterized by greater diversity and abundance of foraminifera and echinoderms (holothuroids and ophiuroids). The lowest delta C-13 values are recorded during this phase, with a dominance of opportunist (Eoguttulina) and facultative opportunist (Paralingulina tenera) foraminifera. Finally, recovery after the biotic crisis is evidenced by high values for specialists and potentially deep infaunal foraminifera, indicating oxic conditions in the sediment.
CRIS-Team WoS Importer:2019-04-16

Changes in terrestrial floras at the Triassic-Jurassic Boundary in Europe - Barbacka, Maria; Pacyna, Grzegorz; Kocsis, Ádám; Jarzynka, Agata; Ziaja, Jadwiga; Bodor, Emese (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Keywords: Floral change; Hettangian; Plant diversity; Rhaetian

Characteristic pattern of species diversity on the canary islands - Steinbauer, Manuel; Beierkuhnlein, Carl (Erdkunde, 2010)
We use an island specific presence/absence data set for the Canary Islands' Arthropoda, Spermatophyta, Fungi, Lichenes, Bryophyta, Mollusca, Chordata, Pteridophyta, Annelida and Nematoda to assess the relative influence of environmental and historical factors on species distribution and endemism. Species richness and the percentage of island endemic species as well as similarity indices for island comparisons were calculated for all species groups. Hierarchical partitioning is used to identify the independent and joined influence of 21 environmental and historical variables. The pattern of species richness is best explained by island elevation. Elevation reflects a variety of factors that contribute to habitat diversity. A similar pattern is detected for the "percentage of single island endemics" (pSIE), a factor associated with speciation. Variables associated with geographical distance have highest explanatory power for biotical similarity of islands. Various Canary Islands species groups show strong distance-decay within the archipelago. According to our findings, speciation is not necessarily driven by species richness or island age alone. Thus, we conclude that correlations between species richness and pSIE, identified in previous studies, could represent an artefact related to differing degrees of isolation between zonal altitudinal ecosystems. This would lead to an increase of speciation with altitude resulting in higher values for pSIE on high altitude islands.
Keywords: Alpha-diversity; Atlantic ocean; Beta-diversity; Distance decay; Island biogeography; Macaronesia; Speciation; Species turn-over; Species-area

Chemical characterisation is rough: the impact of topography and measurement parameters on energy-dispersive X-ray spectroscopy in biominerals - Shirley, Bryan; Jarochowska, Emilia (Facies, 2022)
Energy dispersive X-ray microscopy (EDX) is a widely available, inexpensive method of characterizing the in-situ elemental composition of samples in Earth and life sciences. Common protocols and textbooks focussing on material sciences address EDX analysis of metallic samples that can be polished perfectly, whereas geoscientists often investigate specimens with prominent topography and composed of light, difficult to resolve elements. This is further compounded by the scarcity of literature surrounding the methodology of SEM-EDX in the field of palaeontology, leading to common misinterpretations and artefacts during data acquisition. Here, the common errors in elemental composition obtained with EDX arising from surface topography and from parameters subject to user decisions are quantified. As a model, fossil bioapatite (conodonts) and abiotic Durango apatite are used. It is shown that even microscale topography can distort measured composition by up to 34%, whereas topographic features such as tilt with respect to the electron beam lead to differences of up to 85%. Working distance was not the most important parameter affecting the results and led to differences in composition of up to 13%, whereas the choice of standard and its levelling with the sample surface led to inaccuracy reaching 33%. EDX results can be also affected by beam damage and the effects of acceleration voltage on sample acquisition and resolution are quantified. An estimate is provided of the severity of errors associated with samples which cannot satisfy preparation requirements for EDX fully, such as holotypes, and with user decisions. Using a palaeontological example, recommendations are offered for the best parameters and the relative importance of error sources are assessed.
CRIS-Team WoS Importer:2022-04-08

Chitinozoan biostratigraphy and carbon isotope stratigraphy from the Upper Ordovician Skogerholmen Formation in the Oslo Region. A new perspective for the Hirnantian lower boundary in Baltica - Amberg, Chloé E. A.; Vandenbroucke, Thijs R.A.; Nielsen, Arne Thorshøj; Munnecke, Axel; Mclaughlin, Patrick I. (Review of Palaeobotany and Palynology, 2017)
The end-Ordovician has received wide attention because it hosts major global events including mass extinctions, glaciations, significant sea-level fluctuations, and large-scale perturbations of the Earth's carbon cycle. Knowing the order and timing of these events and their components is crucial for understanding these environmental changes. Here, we use stable carbon isotope stratigraphy in combination with chitinozoan biostratigraphy to correlate the Upper Ordovician Belonechitina gamachiana chitinozoan Biozone. Its position has long been a matter of debate; some argue that it is of late Katian age and others that it is of early Hirnantian age. The Skogerholmen Formation from the Oslo-Asker District in Norway has been correlated with the lower-middle Pirgu Baltic Stage, hitherto believed to correspond to the international upper Katian Stage. Our study, however, reveals the presence of B. gamachiana, diagnostic of the eponymous Biozone, in the descending trend of a modest carbon isotope excursion in the lower part of this formation. This is strikingly similar to data from coeval end-Ordovician sections in North America, where the prevailing evidence suggests an early Hirnantian age for the B. gamachiana chitinozoan Biozone. This new correlation suggests that the lower Hirnantian boundary may be positioned within the Pirgu Baltic Stage.
Keywords: Baltica; Biostratigraphy; Carbon isotopes; Chitinozoans; End-Ordovician; Hirnantian

Chitinozoan biostratigraphy at the Late Ordovician GICE event in the Borenshult-1 Drillcore (Sweden). - Pouille, Lauren; Delabroye, Aurelian; Vandenbroucke, Thijs R.A.; Calner, Michael; Lehnert, Oliver; Vecoli, Marco; Danelian, Taniel (Review of Palaeobotany and Palynology, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LG.chitin

Chronosphere: Earth System History Variables - Kocsis, Ádám; Raja, Nussaïbah Begum (GSA 2020 Connects Online, 2020)
Researchers focusing on global-scale ecological and evolutionary patterns are faced with the overwhelmingly increasing volume and diversity of data compilations. The complexity of the relevant research questions necessitates the interconnected use of multiple datasets (the source variables) that are often regularly updated. Finding these data and incorporating them in the analytical workflow can be time consuming and often lead to difficulties and conflicts in version control. The goal of the ‘chronosphere’ project is to offer a portal to these data and to allow their immediate use by compiling frequently accessed representations on a server that keeps track of different versions. These data are available through an R package of the same name (available on the CRAN servers), that downloads a specific version of a dataset and attaches it to the R environment. The project focuses on data used in biogeography, macroecology and macroevolution, from large datasets to small tables published as supplementary information to research articles. Currently available data include major sources such as the Paleobiology Database, the PaleoReefs Database, and the paleogeographic reconstructions of the PaleoMAP project. ‘chronosphere’ will also be used to distribute the output of BRIDGE HadCM3L family deep-time climate models. To facilitate the use of deep-time spatial data, the R package includes functions that utilize either the GPlates Web Service or the GPlates desktop application to reconstruct the positions of present-day coordinates and spatial features using a user-specified reconstruction model. An efficient container class is also implemented to facilitate the work with raster and vector data layers that are organized in multi-dimensional arrays. These features were proven especially useful in the classroom environment, where the fast download and transformation of data are important. Providing data in a consistent form within the R programming framework, ‘chronosphere’ allows the fast reproducibility, and ultimately the tracing of scientific results with the same codebas

Climate change and marine life - Richardson, Anthony J; Brown, Christopher D.; Brander, Keith; Bruno, John F.; Buckley, Lauren; Burrows, Michael T.; Duarte, Carlos M.; Halpern, Benjamin S.; Hoegh-Guldberg, Ove; Holding, Johnna; Kappel, Carrie V.; Kießling, Wolfgang; et al. (Biology Letters, 2012)
A Marine Climate Impacts Workshop was held from 29 April to 3 May 2012 at the US National Center of Ecological Analysis and Synthesis in Santa Barbara. This workshop was the culmination of a series of six meetings over the past three years, which had brought together 25 experts in climate change ecology, analysis of large datasets, palaeontology, marine ecology and physical oceanography. Aims of these workshops were to produce a global synthesis of climate impacts on marine biota, to identify sensitive habitats and taxa, to inform the current Intergovernmental Panel on Climate Change (IPCC) process, and to strengthen research into ecological impacts of climate change.
Keywords: climate change; marine science; detection and attribution

Climate change and the latitudinal selectivity of ancient marine extinctions - Reddin, Carl James; Kocsis, Ádám; Kießling, Wolfgang (Paleobiology, 2018)
Geologically rapid climate change is anticipated to increase extinction risk nonuniformly across the Earth's surface. Tropical species may be more vulnerable than temperate species to current climate warming because of high tropical climate velocities and reduced seawater oxygen levels. To test whether rapid warming indeed preferentially increased the extinction risk of tropical fossil taxa, we combine a robust statistical assessment of latitudinal extinction selectivity (LES) with the dominant views on climate change occurring at ancient extinction crises. Using a global data set of marine fossil occurrences, we assess extinction rates for tropical and temperate genera, applying log ratios to assess effect size and Akaike weights for model support. Among the classical “big five” mass extinction episodes, the end-Permian mass extinction exhibits temperate preference of extinctions, whereas the Late Devonian and end-Triassic selectively hit tropical genera. Simple links between the inferred direction of climate change and LES are idiosyncratic, both during crisis and background intervals. More complex models, including sampling patterns and changes in the latitudinal distribution of continental shelf area, show tropical LES to be generally associated with raised tropical heat and temperate LES with global cold temperatures. With implications for the future, our paper demonstrates the consistency of high tropical temperatures, habitat loss, and the capacity of both to interact in generating geographic patterns in extinctions.<br
Keywords: marine invertebrates; Phanerozoic; Paleobiology Database; model selection; generalized least squares; habitat loss; temperature related stressors

Climate change disrupts core habitats of marine species - Hodapp, Dorothee; Roca, Irene T.; Fiorentino, Dario; Garilao, Cristina; Kaschner, Kristin; Kesner-Reyes, Kathleen; Schneider, Birgit; Segschneider, Joachim; Kocsis, Ádám; Kießling, Wolfgang; Brey, Thomas; Froese, Rainer (Global Change Biology, 2023)
Driven by climate change, marine biodiversity is undergoing a phase of rapid change that has proven to be even faster than changes observed in terrestrial ecosystems. Understanding how these changes in species composition will affect future marine life is crucial for conservation management, especially due to increasing demands for marine natural resources. Here, we analyse predictions of a multiparameter habitat suitability model covering the global projected ranges of >33,500 marine species from climate model projections under three CO2 emission scenarios (RCP2.6, RCP4.5, RCP8.5) up to the year 2100. Our results show that the core habitat area will decline for many species, resulting in a net loss of 50% of the core habitat area for almost half of all marine species in 2100 under the high-emission scenario RCP8.5. As an additional consequence of the continuing distributional reorganization of marine life, gaps around the equator will appear for 8% (RCP2.6), 24% (RCP4.5), and 88% (RCP8.5) of marine species with cross-equatorial ranges. For many more species, continuous distributional ranges will be disrupted, thus reducing effective population size. In addition, high invasion rates in higher latitudes and polar regions will lead to substantial changes in the ecosystem and food web structure, particularly regarding the introduction of new predators. Overall, our study highlights that the degree of spatial and structural reorganization of marine life with ensued consequences for ecosystem functionality and conservation efforts will critically depend on the realized greenhouse gas emission pathway.
CRIS-Team Scopus Importer:2023-03-03
Keywords: climate change; climate projections; environmental niche models; habitat suitability; marine biodiversity; RCP

Climate velocity and the future global redistribution of marine biodiversity - Molinos, Jorge G.; Halpern, Benjamin S.; Schoeman, David S.; Brown, Christopher D.; Kießling, Wolfgang; Moore, Pippa J.; Pandolfi, John; Poloczanska, Elvira S.; Richardson, Anthony J; Burrows, Michael T. (Nature Climate Change, 2016)
Anticipating the effect of climate change on biodiversity, in particular on changes in community composition, is crucial for adaptive ecosystem management but remains a critical knowledge gap. Here, we use climate velocity trajectories, together with information on thermal tolerances and habitat preferences, to project changes in global patterns of marine species richness and community composition under IPCC Representative Concentration Pathways (RCPs) 4.5 and 8.5. Our simple, intuitive approach emphasizes climate connectivity, and enables us to model over 12 times as many species as previous studies. We find that range expansions prevail over contractions for both RCPs up to 2100, producing a net local increase in richness globally, and temporal changes in composition, driven by the redistribution rather than the loss of diversity. Conversely, widespread invasions homogenize present-day communities across multiple regions. High extirpation rates are expected regionally (for example, Indo-Pacific), particularly under RCP8.5, leading to strong decreases in richness and the anticipated formation of no-analogue communities where invasions are common. The spatial congruence of these patterns with contemporary human impacts highlights potential areas of future conservation concern. These results strongly suggest that the millennial stability of current global marine diversity patterns, against which conservation plans are assessed, will change rapidly over the course of the century in response to ocean warming.
UnivIS-Import:2016-06-01:Pub.2016.nat.dgeo.IGM.LP.climat
Keywords: Climate-change ecology

Climate vs. topography - spatial patterns of plant species diversity and endemism on a high-elevation island - Irl, Severin D. H.; Harter, David E. V.; Steinbauer, Manuel; Gallego Puyol, David; Maria Fernandez-Palacios, Jose; Jentsch, Anke; Beierkuhnlein, Carl (Journal of Ecology, 2015)
Keywords: Canary Islands; Climatic rarity; Climatic stability; Island ecology; Landscape ecology; Landscape scale; Mini-continent; Multimodel inference; Spatial ecology

Climatic, depositional and environmental controls on early carbonate cementation in fluvial and shallow marine sandstones - Janßen, Meike; Caracciolo, Luca; Bonnell, L. M.; Lander, R. H.; Munnecke, Axel; Beltrán-Triviño, A.; Muto, F.; Stollhofen, Harald (Marine and Petroleum Geology, 2023)
Sandstones with carbonate cements are found in a variety of depositional settings (e.g. fluvial, lacustrine, deltaic, shallow marine) with abundances ranging from just a few volume percent to pervasive pore-filling cements and are of major interest due to their impact on reservoir quality. Despite the widespread occurrence of such cements, predictive models for eogenetic carbonate cementation have yet to be developed. Hence, investigations on the controls and distribution of early carbonate precipitation are necessary to improve the accuracy of predictions of the nature and distribution of diagenetic alterations. We conducted a petrological and petrophysical analysis of early near-surface carbonate cementation in siliciclastic and mixed siliciclastic-carbonate sandstones from fluvial and shallow marine environments to reconstruct eogenetic processes and their associated controls. Furthermore, sediment burial scenarios up to a loading of 50 MPa were simulated with the reservoir quality prediction software Touchstone to evaluate the impact of carbonate cements on the compaction behaviour of the rocks. Results highlight the importance of climate, depositional environment and detrital composition and texture in regards to the precipitation processes of near-surfaces carbonate cements and burial development. Our data shows that the presence and distribution of early carbonate cements reflects a complex interaction of several parameters, such as the composition and texture of detrital material in the source area, the availability and infiltration of meteoric or marine waters and the presence of precursor carbonate during deposition. Burial simulations demonstrate the strengthening effect of early carbonate cementation and its influence on the development of intergranular volume and porosity during burial with up to five times less porosity loss due to compaction than without near-surface cementation.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Carbonate cementation; Intergranular volume; Mixed siliciclastic-carbonate sediments; Near-surface diagenesis; Reservoir quality

Coastal upwelling drives intertidal assemblage structure and trophic ecology - Reddin, Carl James; Docmac, Felipe; Bothwell, John; Harrod, Chris; et al. (PLoS ONE, 2015)

Colonial history and global economics distort our understanding of deep-time biodiversity - Raja Schoob, Nussaibah Begum; Dunne, Emma; Matiwane, Aviwe; Khan, Tasnuva Ferdous Ming; Nätscher, Paulina; Ghilardi, Aline Marcele; Chattopadhyay, Devapriya (Nature Ecology & Evolution, 2021)
Sampling biases in the fossil record distort estimates of past biodiversity. However, these biases not only reflect the geological and spatial aspects of the fossil record, but also the historical and current collation of fossil data. We demonstrate how the legacy of colonialism and socioeconomic factors, such as wealth, education and political stability, impact the global distribution of fossil data over the past 30 years. We find that a global power imbalance persists in palaeontology, with researchers in high- or upper-middle-income countries holding a monopoly over palaeontological knowledge production by contributing to 97% of fossil data. As a result, some countries or regions tend to be better sampled than others, ultimately leading to heterogeneous spatial sampling across the globe. This illustrates how efforts to mitigate sampling biases to obtain a truly representative view of past biodiversity are not disconnected from the aim of diversifying and decolonizing our discipline.

Colonialism shaped today’s biodiversity - Raja, Nussaïbah Begum (Nature Ecology & Evolution, 2022)
CRIS-Team Scopus Importer:2022-10-28

Colospongia cribriforma nov. sp. and Parastylothalamia minima nov. sp. ("Sphinctozoa", Porifera) from the Norian of Taurus Mountains, Turkey - Senowbari-Daryan, Baba; Link, Michael; Riedel, Peter (Revue de Paléobiologie, 2015)
Two chambered hypercalcified sponges, Colospongia cribrifera nov. sp. and Parastylothalamia minima nov. sp. are described from the Norian reef boulders exposed around the town of Terziler, Taurus Mountains, south Turkey. Colospongia cribrifera is characterized by partly perforated and partly imperforated chamber walls and additionally sieve-like plates or cribribulla in the chamber exowalls. Parastylothalamia minima is one of the smallest chambered sponge known in the fossil record. The siphonate sponge is characterized by evenly perforated chamber walls and by scattered pillars within the chamber interiors.
UnivIS-Import:2017-11-07:Pub.2015.nat.dgeo.IGM.LP.colosp
Keywords: Colospongia; Parastylothalamia; Triassic; Norian; Reef; Taurus Mountains; Turkey

Combined radiolarian-ammonite stratigraphy for the Late Jurassic of the Antarctic Peninsula: Implications for radiolarian stratigraphy - Kießling, Wolfgang; Scasso, Roberto A.; Zeiss, Arnold; Riccardi, Alberto; Medina, Francicso A. (Geodiversitas, 1999)
New biostratigraphic data from co-occurring radiolarians and ammonites in Upper Jurassic sequences of the Antarctic Peninsula (Byers Peninsula on Livingston Island and Longing Gap, Graham Land), permit a revised and more refined regional stratigraphy. The new data also allow a revision of the chronostratigraphic assignment of some American radiolarian zones established by Pessagno and collaborators: The boundary of Zone 3-4 is assigned to the latest Kimmeridgian, contrasting the former assignment to the early/late Tithonian boundary. The boundary between Subzone 4 beta and 4 alpha is assigned to the early Tithonian, but was usually correlated with the early late Tithonian/late late Tithonian boundary. The new chronostratigraphic data from Antarctica are used together with recent results of Baumgartner and collaborators to revise the age assignment of the North American Late Jurassic radiolarian zones.
UnivIS-Import:2015-03-05:Pub.1999.nat.dgeo.IGM.LP.combin
Keywords: Biostratigraphy; Micropalaeontology; Cephalopods

Concluding IGCP 503: Towards a holistic view of Ordovician and Silurian earth systems - Harper, David A.T.; Li, Jun; Munnecke, Axel; Owen, Alan W.; Servais, Thomas; Sheehan, Peter M. (EPISODES, 2011)
IGCP 503 'Ordovician Palaeogeography and Palaeoclimaté was established in 2004 primarily to identify the main drivers, both biological and geological, of the Great Ordovician Biodiversification Event. From the outset of the project it was clear that this event was part of a larger-scale, long-term, multifaceted process that included the end Ordovician extinction and Silurian recovery, if not more. IGCP 503 thus developed a major network that included scientists whose interests spanned the entire Lower Palaeozoic and encompassed a range of disciplines from classical palaeontology and palaeoecology through isotope geochemistry to climate modellin
Keywords: Ordovician; palaeogeography; palaeoclimate; GOBE; great ordovician biodiversification event; IGCP; Silurian recovery; Ordovician event; lower palaeozoic

Conodont biostratigraphy in the Early to Middle Ordovician strata of the Oslobreen Group in Ny Friesland, Svalbard - Lehnert, Oliver; Stouge, Svend; Brandl, Philipp (Zeitschrift der Deutschen Gesellschaft für Geowissenschaften, 2013)
The remotely located Cambro-Ordovician strata in Ny Friesland, NE Spitsbergen, Svalbard, are referred to the Oslobreen Group, which is composed of the Tokammane, Kirtonryggen and Valhallfonna formations. Herein we record the conodont succession of the Kirtonryggen and Valhallfonna formations. Collections of well-preserved conodonts (CAI 1) have been recovered from the Lower to lower Middle Ordovician interval in the region. Eight regional conodont zones are established in this preliminary study of the Oslobreen Group exposed at Hinlopenstretet, NE Svalbard. In ascending order these zones are: Rossodus manitouensis, Macerodus dianae, Oneotodus costatus, Oepikodus communis, O. evae, O. inter-medius, Periodon aff. flabellum-Periodon hankensis and Periodon macrodentatus. The yield is relatively poor for the Kirtonryggen Formation, but the oldest Ordovician conodont faunas span the Trema-docian Rossodus manitouesis through Macerodus dianae zones followed by the Floian Oepikodus communis Zone. The taxa are typical of the tropical North American Midcontinent faunal province that dominated the region until open marine associations invaded the shallow shelf (i.e. Evae transgression). The pandemic Oepikodus evae becomes frequent and is succeeded by O. intermedius in abundance in the lower Valhallfonna Formation (Olenidsletta Member). The upper strata are characterised by the Periodon-Paroistodus assemblage characteristic for outer shelf and slope environments around Laurentia. In total, this formation comprises the Floian and Dapingian stages and ends in the early Darriwilian Periodon macroden-tatus Zone in this region. The Ny Friesland faunas show affinities to coeval assemblages from Northeast Greenland and West Newfoundland. © 2013 E. Schweizerbart'sche Verlagsbuchhandlung, Stuttgart, Germany.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LG.conodo
Keywords: Conodont biostratigraphy; Ny Friesland; Ordovician; Svalbard (Spitsbergen); Tremadocian

Conodonts in Silurian hypersaline environments: Specialized and unexpectedly diverse - Jarochowska, Emilia; Viira, Viive; Einasto, Rein; Nawrot, Rafał; Bremer, Oskar; Männik, Peep; Munnecke, Axel (Geology, 2017)
Hypersaline environments are commonly assumed to be barren of metazoans and therefore are avoided by paleontologists, yet a number of early Paleozoic jawless vertebrate groups specialized to live in such settings. Sampling bias against restricted settings resulted in substantial underestimation of their diversity. Rare studies venturing into such environments yielded multiple new species of conodonts, suggesting that the diversity and habitat range of these hyperdiverse predators of the early oceans are equally underestimated. We describe here autochthonous conodont fauna from evaporite-bearing horizons from the middle Silurian of Estonia that provide evidence for efficient osmoregulation in this group. Based on a global compilation of coeval conodont assemblages, we show that marginal-marine, periodically emergent environments were characterized by higher conodont diversity than open-marine shallow settings. This diversity is due to a high number of species occurring in these environments only. The high degree of specialization is also reflected by the highest within-habitat variability (β diversity) in marginal settings. Most conodont species had narrow environmental niches and, unlike in marine invertebrates, extreme environments were inhabited by the most specialized taxa. Such environments represent a large proportion of early Paleozoic tropical epicratonic basins. Our analysis allows quantification of the degree to which mid-Silurian conodont diversity is underestimated as a result of sampling bias against marginal-marine settings.
Keywords: Hypersaline environments; conodonts; invertebrates; quantification; Paleozoic; diversity; beta diversity; Estonia; Silurian

Constraining the Deep Origin of Parasitic Flatworms and Host-Interactions with Fossil Evidence. - de Baets, Kenneth; Dentzien-Dias, Paula; Upeniece, Ieva; Verneau, Olivier; Donoghue, Philip C. J. (Advances in Parasitology, 2015)
Novel fossil discoveries have contributed to our understanding of the evolutionary appearance of parasitism in flatworms. Furthermore, genetic analyses with greater coverage have shifted our views on the coevolution of parasitic flatworms and their hosts. The putative record of parasitic flatworms is consistent with extant host associations and so can be used to put constraints on the evolutionary origin of the parasites themselves. The future lies in new molecular clock analyses combined with additional discoveries of exceptionally preserved flatworms associated with hosts and coprolites. Besides direct evidence, the host fossil record and biogeography have the potential to constrain their evolutionary history, albeit with caution needed to avoid circularity, and a need for calibrations to be implemented in the most conservative way. This might result in imprecise, but accurate divergence estimates for the evolution of parasitic flatworms.

Continuous evolutionary change in Plio-Pleistocene mammals of eastern Africa - Bibi, Faysal; Kießling, Wolfgang (Proceedings of the National Academy of Sciences of the United States of America, 2015)
UnivIS-Import:2016-06-01:Pub.2015.nat.dgeo.IGM.LP.contin
Keywords: Africa; Bovidae; Mammals; Plio-Pleistocene; Turnover

Contrasting shallow and deeper water marine assemblages of the highly heterogeneous biota from the Late Triassic Cassian Formation, northern Italy - Nützel, Alexander; Hausmann, Imelda M.; Reich, Mike; Roden, Vanessa (GeoBonn 2018, Living Earth - Abstracts, 2018)

Coral community shifts across major reef crises - Dimitrijevic, Danijela; Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (ICRS 2021, 14th International Coral Reef Symposium, 2021)
Coral communities today are negatively affected by anthropogenic greenhouse gas release causing global warming and ocean acidification. Natural greenhouse gas release by massive volcanism is thought to have caused one of the Big Five mass extinctions at the end of the Triassic period (200 million years ago). This hyperthermal event triggered one of the greatest reef crises and the most substantial evolutionary crisis in the history of scleractinian corals. While the diversity dynamics of corals are well studied, research on changes in community composition at this time is still lacking. We provide a quantitative assessment of community changes at the level of morphological traits (ie corallite sizes, growth form, and colony form). Using our new Reef Traits Database (RTD), we show that corallite sizes of colonial corals increased substantially after the end-Triassic reef crisis. We conclude that a change towards increasing heterotrophy in reef coral communities best explains the observations across the end-Triassic reef crisis. Additionally, we test how much of the trend in corallite size is governed by selective extinction, origination, and changes in relative abundance across coral communities. Therefore, the fossil record showcases the balance of evolutionary adaptation versus extinction and the lasting community changes in response to climate change over longer time frames than we could cover by studying the extant coral communities. We conclude that a change towards increasing heterotrophy in reef coral communities best explains the observations across the end-Triassic reef crisis. Additionally, we test how much of the trend in corallite size is governed by selective extinction, origination, and changes in relative abundance across coral communities. Therefore, the fossil record showcases the balance of evolutionary adaptation versus extinction and the lasting community changes in response to climate change over longer time frames than we could cover by studying the extant coral communities. We conclude that a change towards increasing heterotrophy in reef coral communities best explains the observations across the end-Triassic reef crisis. Additionally, we test how much of the trend in corallite size is governed by selective extinction, origination, and changes in relative abundance across coral communities. Therefore, the fossil record showcases the balance of evolutionary adaptation versus extinction and the lasting community changes in response to climate change over longer time frames than we could cover by studying the extant coral communities.<br

Coralline red algae from the Silurian of Gotland indicate that the order Corallinales (Corallinophycidae, Rhodophyta) is much older than previously thought - Teichert, Sebastian; Woelkerling, William; Munnecke, Axel (Palaeontology, 2019)
Aguirrea fluegelii gen. et sp. nov. (Corallinales, Corallinophycidae, Rhodophyta) is described from the mid‐Silurian of Gotland Island, Sweden (Högklint Formation, lower Wenlock). The holotype is of dimerous construction and includes a uniporate conceptacle with a sporangium, thus providing evidence that taxa of the Corallinales/Corallinaceae existed at least 300 million years earlier than previously documented. Aguirrea fluegelii cannot be unequivocally placed in any of seven currently recognized lineages/subfamilies/groups of the Corallinaceae as not all diagnostic characters are preserved, and thus is accorded incertae sedis status within the family Corallinaceae and order Corallinales. Extant evolutionary history studies of Corallinophycidae involving molecular clocks now require updating using new calibration points to take account of the much earlier unequivocal mid‐Silurian record of uniporate conceptacle‐bearing taxa of Corallinales/Corallinaceae as well as the parallel record of Graticula, a genus attributed to the Sporolithale
Keywords: Aguirrea fluegelii; conceptacles; Corallinaceae; Corallinales; coralline red algae; Gotland

Corallite sizes and their link to extinction risk of scleractinian corals across the Triassic-Jurassic boundary - Dimitrijevic, Danijela; Raja, Nussaïbah Begum; Kießling, Wolfgang (GSA 2020 Connects Online, 2020)
The end-Triassic mass extinction and reef crisis was a significant crisis in the evolution of scleractinian corals. The crisis is thought to have been caused by volcanically induced global warming. Accordingly, we would expect photosymbiotic corals to be more strongly affected than non-symbiotic corals. However, although corallite integration has decreased across the Triassic-Jurassic boundary, the extinction of scleractinian corals seems to be non-selective with regards to their inferred photosymbiotic mode. Using our new Reef Traits Database (RTD) we test how corallite sizes may have changed across the Triassic-Jurassic boundary. Corallite sizes have been used as a proxy for the efficacy of photosymbiosis with smaller corallite sizes associated with higher photosymbiotic autotrophy in colonial corals. As such, we use maximum corallite diameter to investigate how the dependency on a photosynthetic diet may have increased the extinction risk of certain corals at the end-Triassic mass extinction. Based on a survey of nearly 2000 measurements we establish trends in corallite sizes across the Triassic-Jurassic. We find that there was a significant increase of corallite diameter at the Triassic-Jurassic boundary suggesting stronger heterotrophy. Corallite sizes were 1.8 times larger after the mass extinction, which is the strongest change across the entire 100 myr interval. Generalized linear modeling suggests that the increase of corallite diameters was due to the selective extinction of corals with smaller corallite

Corallite sizes of reef corals: decoupling of evolutionary and ecological trends - Dimitrijevic, Danijela; Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (Paleobiology, 2023)
Corallite sizes reflect a continuum in the efficacy of photosymbiosis in colonial reef corals, with smaller corallite sizes generally associated with higher autotrophy. Using a large compilation of reef-coral traits and corallite diameters as a proxy, we test here the hypothesis that photosymbiotic efficacy has increased over the evolutionary history of scleractinian corals. To gain a more comprehensive understanding of the evolutionary versus ecological patterns of corallite sizes of reef corals, we used three analytical methods: (1) occurrences-weighted within-bin analyses as a proxy for abundance or ecological dominance to depict ecological patterns; (2) unweighted range-through analyses; and (3) unweighted sampled-in-bin analyses to represent diversity in terms of taxonomic richness, enabling us to trace evolutionary patterns. By-genus, range-through analysis indicates a slightly positive trend of corallite sizes toward the Recent. However, the occurrences-weighted assessment shows a pronounced negative trend of corallite sizes in colonial corals since the Mesozoic. Random walk and directional evolution are both statistically supported to explain this long-term decrease. A driven trend is evolutionarily plausible, giving reef corals a selective advantage in the oligotrophic environments they largely occupy today.

Coral Patch and Ormonde seamounts as a product of the Madeira hotspot, Eastern Atlantic Ocean - D'Oriano, Filippo; Angeletti, Lorenzo; Capotondi, Lucilla; Laurenzi, Marinella A.; López Correa, Matthias; Taviani, Marco; Torelli, Luigi; Trua, Teresa; Vigliotti, Luigi; Zittelini, Nevio (Terra Nova, 2010)
New detailed swath bathymetry and bottom samples from Coral Patch and Ormonde seamounts provide constraints on the emplacement of the Madeira hotspot in the Eastern Atlantic Ocean. Swath bathymetric data document that Coral Patch is a composite structure, made up of at least nine distinct volcanic centres. Lithified pelagic carbonates infilling fissures in lava blocks constrain a minimal age for the volcanism in the Early Miocene and represent the first documentation of Coral Patch acting as an offshore terrigenous-starved seamount. At Coral Patch, as already observed at the Ormonde seamount, volcanism was emplaced on top of a pre-existing relief resulting from the regional tectonic compressive regime. © 2010 Blackwell Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.coralp
Keywords: seamounts; cold-water corals

Coral Reefs - Kießling, Wolfgang; Heiss, Georg A. (Biodiversity and Ecosystem Insecurity: A planet in peril, 2011)
Keywords: Coral reefs; Biodiversity; Crisis

Coring tools have an effect on lithification and physical properties of marine carbonate sediments - De Vleeschouwer, David; Nohl, Theresa; Schulbert, Christian; M. Bialik, Or; Auer, Gerald (Scientific Drilling, 2023)
The International Ocean Discovery Program (IODP) JOIDES Resolution Science Operator typically uses an advanced piston corer (APC) in soft ooze and sediments and an extended core barrel (XCB) in firm sediments. The coring tool exchange typically occurs around the same depth in adjacent holes of the same site. However, during IODP Expedition 356, the coring tool switch occurred at different depths: IODP Sites U1463 and U1464 are marked by a stratigraphic interval (> 25 m thick) that was XCB cored in one hole and APC cored in other holes. Shipboard scientists remarked that APC-cored sediments were unlithified or partially lithified, while XCB-cored sediments were fully lithified. This difference in sedimentological description of the same formation seems to be an effect of coring technique. To provide further insight, we assessed the physical properties (bulk density, porosity, and P-wave velocity), downhole wireline logging data, scanning electron microscope (SEM) images, and micro-computed tomography (µCT) scans of those intervals. We find systematic differences between the different coring techniques. XCB cores are characterized by systematically lower bulk density, higher porosity, and higher P-wave velocity than APC cores. Downhole logging data suggest that the original P-wave velocity of the formation is better preserved in XCB cores, despite the typical “biscuit-and-gravy” core disturbance (i.e. well-preserved core fragments surrounded by squelched core material). In conjunction with SEM and µCT images, we conclude that the APC tool destroyed early lithification by breaking cements between individual grains. Moreover, µCT images reveal denser packing and smaller pore volumes in the APC cores. These sedimentary changes likely occur when the APC pressure wave passes through the sediment. The destruction of grain-to-grain cements provides an explanation for the significantly lower P-wave velocities in APC cores. Interestingly, the gravy sections in XCB drilled cores mimic the destruction of early lithification and reduction of pore volume. We conclude that APC remains the tool of choice for recovering soft sediments, especially for paleoclimate purposes. However, for the study of lithification, XCB biscuits provide a more representative image of the formation. For the study of early diagenesis, further studies are required to ascertain the preservation of key sedimentary features using existing and new drilling tool

Corrigendum to: Marine invertebrate migrations trace climate change over 450 million years (Global Ecology and Biogeography, (2018), 27, 6, (704-713), 10.1111/geb.12732) - Reddin, Carl James; Kocsis, Ádám; Kießling, Wolfgang (Global Ecology and Biogeography, 2020)
JUSTIFICATION The original results to Reddin, Kocsis, and Kiessling (2018) included an error in the code that intended to match geographical grid cells between neighbouring ages (“matched-cells” hereafter), via a nonsensical call to the subset() function. After correcting this coding mistake, we checked these results against those acquired with the matched-cells step omitted entirely. The results held only when the matched-cells step was omitted. This invalidated our original belief that matched-cells would help “homogenize geographical sampling coverage between consecutive ages”. The restriction to matched-cells results in a median loss of 23% of survivor species compared to without matched-cells (median = 118 survivor species per age to median = 153 without matched-cells). Additionally, we suspect that the two spatial corrections for sampling variation interfere with one another, that is, the use of (a) matched-cells and (b) subtraction of the sampling focus from the median genus range centre (to calculate the latitudinal deviation). We therefore reproduce the analyses without limiting data to matched-cells and present the updated results, including the five changed results figures, here. In summary, the changes to the results are minor and the scientific conclusions remain as originally stated. UPDATED VERSIONS OF KEY FIGURES All results hold following the omission of the matched-cells step, albeit with slightly weaker strength, with the central correlation decreasing from rho = 0.30 (p =.01) to rho = 0.24 (p =.034; Figure 1). Following the order of presentation in the original paper, the central correlation rises, as before, with (a) hemisphere-switching, but to rho = 0.39 (95% CIs = 0.19–0.56, optimum threshold = 126; Figure 2) instead of the original rho = 0.48 (95% CIs = 0.29–0.64, optimum threshold = 108 genera). The central correlation for the Southern Hemisphere remained insignificant (rho = 0.08, p =.6). If (b) the median latitudinal deviation was supplemented with the 0.2-quantile latitudinal deviation, when the Northern Hemisphere median occurrence palaeolatitude vacated the tropics, a substantial improvement to the central correlation is no longer observed (small increase to Rho = 0.26, 95% CIs = 0.04–0.46, rather than the original increase to rho = 0.40, 95% Cis = 0.19–0.57; see next paragraph). However, as in the original version, combining both hemisphere-switching and integrating the 0.2-quantile deviation (steps a and b), raised the central correlation to rho = 0.35 (95% CIs = 0.14–0.53), but did not improve upon using hemisphere-switching alone. (c) Weighting the correlation from the hemisphere-switching approach by the age inverse extinction rate resulted in the highest correlation strength, at rho = 0.41 (95% CIs = 0.2–0.58; Figure 3) instead of the original rho = 0.56 (95% Cis = 0.39–0.70). 1 Figure (Figure presented.) Latitudinal range shifts of Northern Hemisphere marine genera (black lines) are correlated with low latitude mean shallow seawater temperature (red lines, right-hand y axis). Temperature calculated from fossil shell oxygen isotopes following Veizer and Prokoph (2015). Grey shading around the thick black line shows bootstrapped 95% confidence intervals. For both variables, thick lines show a moving window of three consecutive bins. Thin lines show the unsmoothed bin-to-bin changes. This is the updated original Figure 2. Contributing genera median range centre = 23.6°. There is now no gap in the latitudinal deviation time series for the Northern Hemisphere. Latitudinal deviation mean is 0.60° (absolute mean = 1.93°). Geological periods are lightly shaded and abbreviated as O = Ordovician; S = Silurian; D = Devonian; C = Carboniferous; P = Permian; Tr = Triassic; J = Jurassic; K = Cretaceous; Pg = Palaeogene; N = Neogene 2 Figure (Figure presented.) The effect of changing a threshold minimum number of genera in “hemisphere switching” on the correlation of latitudinal deviation with climate. When the minimum threshold is reached, latitudinal deviations are sourced from the opposite hemisphere. Dotted lines show the correlation without any hemisphere switching, for northern and southern palaeo-hemispheres separately. Filled circles are p <.05. Serial autocorrelation in times series removed by generalized differencing. This is the updated original Figure 3. Optimum threshold of sampled genera = 126 3 Figure (Figure presented.) Time series of latitudinal range shifts of marine genera (black lines) improved by hemisphere switching alongside low latitude shallow seawater temperature (red lines, right-hand y axis). Details as in Figure 1. This is the updated original Figure 4. Contributing genera median range centre = 27.6°. Latitudinal deviation mean is 0.38° (absolute mean = 1.89°). All other descriptions as in Figure 1. O = Ordovician; S = Silurian; D = Devonian; C = Carboniferous; P = Permian; Tr = Triassic; J = Jurassic; K = Cretaceous; Pg = Palaeogene; N = Neogene The latitudinal deviation quantiles still show an increase in strength of relationship with climate from higher to lower quantiles (Figure 4, rho = −0.58, n = 9, p =.11; down from the original rho = –0.78, n = 9, p =.02), but the trend is only significant when the sampling focus vacated the tropics, approximately after the Carnian age (rho = −0.83, n = 9, p =.008; Figure 4; also see original Figure 1 at 230 myr). This is presumably because the highest and lowest quantiles are more affected by noise and only become useful when the median sampling focus is no longer opportunely positioned, that is, when the sampling centre vacates the tropics. Prior to the Norian age (Triassic), the correlation between latitudinal deviation and climate with hemisphere switching (i.e. step (a), above) is significant even without smoothing (rho = 0.34, 95% Cis = 0.04–0.58, ages n = 43). The slopes of warm and cool ages remain significantly different to each other (Z-statistic = −3.23, p =.0006; Figure 5). 4 Figure (Figure presented.) Correlation strength between shallow seawater temperature and genus latitudinal range shifts decreases from more equatorward (0.1-quantile, median palaeolatitude = 12.7°) to poleward genera (0.9-quantile, median palaeolatitude = 39.0°; quantile steps of 0.1). Solid symbols show Spearman's rho coefficients that 95% confidence intervals (dashed lines) overlap zero. Serial autocorrelation in times series removed by generalized differencing. This is the updated original Figure 5. The latitudinal means for the coloured lines are the mean sampling latitudes. The strongest correlation over all ages is with the 0.5-quantile (i.e. median, given in main text) but when the quantile time series are split, the post-Carnian 0.2-quantile has the strongest correlation (rho = 0.35, p =.036) 5 Figure (Figure presented.) Poleward migrations are more likely to be recorded by lower latitude sampling foci, (a) especially during warm ages (red line and points, age seawater temperature > Phanerozoic mean, slope = −0.20, p =.0005, n = 33). Each point represents one geological age. Blue line and points represent cool ages (age seawater temperature < Phanerozoic mean, slope = −0.02, n.s., n = 45). (b) Termplots of the independent effects of the predictor variables in a multiple regression including both temperature and sampling latitude as predictor variables for latitudinal deviations. Points are the partial residuals. This is the updated original Figure 6 The interpretation of these results is unchanged. Thanks are owed to Gwen S. Antell for noticing this error. The code was updated in the Dryad repository on January 10, 2020. The authors apologise for this error.
CRIS-Team Scopus Importer:2020-06-23

Costinuculana magharensis n. gen. n. sp (Bivalvia, Nuculanidae) from the Middle Jurassic of Gebel Maghara, North Sinai, Egypt - Ayoub-Hannaa, Wagih; Abdelhady, Ahmed Awad; Fürsich, Franz (Journal of Paleontology, 2017)
<div class="row" style="box-sizing: border-box; margin: 0px -0.64286rem; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; line-height: inherit; font-family: "Noto Sans", Helvetica, Roboto, Arial, sans-serif; font-size: 16px; vertical-align: baseline; max-width: none; width: auto; color: rgb(51, 51, 51);"> <div class="large-10 medium-10 small-12 columns" style="box-sizing: border-box; margin: 0px; padding: 0px 0.64286rem; border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; vertical-align: baseline; width: 742.125px; float: left; position: relative;"> <div class="description" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: 13px; vertical-align: baseline; -webkit-font-smoothing: antialiased; color: rgb(89, 89, 89); line-height: 1.6em !important;"> <div class="abstract" data-abstract-type="normal" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; vertical-align: baseline;"> <p style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-stretch: inherit; line-height: 1.6; font-family: inherit; font-size: 1em; vertical-align: baseline; text-rendering: optimizeLegibility;"> The nuculanid bivalve <span class="italic" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: italic; font-variant: inherit; font-weight: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; vertical-align: baseline;">Costinuculana magharensis new genus new species is described from the middle to upper Bathonian Kehailia Formation of Gebel Maghara, North Sinai, Egypt. <span class="italic" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: italic; font-variant: inherit; font-weight: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; vertical-align: baseline;">Costinuculana differs from other genera of the family Nuculanidae by the presence of opisthocline ribs along the rostrum. These ribs are variable in shape and size, straight to folded posteriorly, bifurcate ventrally and occasionally postero-dorsally, and cover an area <span class="italic" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: italic; font-variant: inherit; font-weight: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; vertical-align: baseline;"> 45% of the total valve length from the posterior end. The life position of <span class="italic" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: italic; font-variant: inherit; font-weight: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; vertical-align: baseline;">C. <span class="italic" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: italic; font-variant: inherit; font-weight: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; vertical-align: baseline;">magharensis n. gen. n. sp. is reconstructed on the basis of a functional interpretation of its morphology and by comparison with closely related Recent forms. The asymmetrical commarginal ribs facilitated the burrowing process. The posterior oblique ribs are asymmetrical in cross-section with a steeply concave side in the burrowing direction and slightly convex side in the opposite direction. They probably kept the bivalve in a stable position once the desired depth had been reached. The thick oblique ribs probably also increased the strength of the rostrum and offered resistance against durophagous predators, being presumably partly exposed above the sediment-water interface. Based on the associated fauna, <span class="italic" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: italic; font-variant: inherit; font-weight: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; vertical-align: baseline;">Costinuculana n. gen. lived in a low-energy environment characterized by a fine-grained, soft substrate.
UnivIS-Import:2017-12-18:Pub.2017.nat.dgeo.IGM.LP.costin
Keywords: new genus; new species; Bivalvia; Nuculanidae; Costinuculana magharensis; Bathonian Kehailia Formation; Gebel Maghara; Egypt; Middle Jurassic

Coupling of geographic range and provincialism in Cambrian marine invertebrates - Na, Lin; Kocsis, Ádám; Li, Qijian; Kießling, Wolfgang (Paleobiology, 2022)
The Cambrian saw a dramatic increase in metazoan diversity and abundance. Between-assemblage diversity (beta diversity) soared in the first three Cambrian stages, suggesting a rapid increase in the geodisparity of marine animals during the Cambrian radiation. However, it remains unclear how these changes scale up to first-order biogeographic patterns. Here we outline time-traceable provinces for marine invertebrates across the Cambrian period using a compositional network based on species-level fossil occurrence data. Results confirm an increase in regional differences of faunal composition and a decrease in by-species geographic distribution during the first three stages. We also show that general biogeography tends to be reshaped after global extinction pulses. We suggest that the abrupt biogeographic differentiation during the Cambrian radiation was controlled by a combination of tectonics, paleoclimate, and dispersal capacity changes.
CRIS-Team WoS Importer:2022-12-30

Crustose coralline red algae frameworks and rhodoliths: Past and present - Rebelo, Ana Cristina; Teichert, Sebastian; Bracchi, Valentina A.; Rasser, Michael W.; Basso, Daniela (2022)

Cryptic biostalactites in a submerged karst cave of the Belize Barrier Reef revisited: Pendant bioconstructions cemented by microbial micrite - Gischler, Eberhard; Heindel, Katrin; Birgel, Daniel; Brunner, Benjamin; Reitner, Joachim; Peckmann, Jörn (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Microbial carbonates are important components of postglacial tropical coral reef frameworks. Curious calcium carbonate protrusions in a submarine karst cave in the Belize Barrier Reef platform were initially interpreted as being largely the product of physicochemical precipitation around a meshwork of serpulid tubes. New petrographical, mineralogical, geochronological, and inorganic and organic geochemical data suggest that sulfate-reducing bacteria played a substantial role in carbonate formation, just as in cryptic settings of other modern, tropical coralgal reefs. The bacterial involvement in carbonate authigenesis is indicated by the content and isotopic composition of carbonate-associated sulfate, the presence of non-isoprenoidal sn-1-mono-O-alkyl glycerol monoethers (MAGEs) and terminally-branched fatty acids, and the observation that the majority of molecular fossils assigned to sulfate-reducing bacteria are tightly associated with the carbonate mineral lattice. The carbonate protrusions that were formerly named pseudostalactites, are termed biostalactites here to underline the significance of biological activity during carbonate formation. The Belize biostalactites are composed of four carbonate phases including serpulid tubes, lithified sediment, and microbial carbonate, as well as unconsolidated sediment usually found in macroborings of bivalve molluscs. Lithified sediment and microbial carbonate are fine-grained with clotted, mottled, and peloidal textures. While serpulid tubes are aragonitic, lithified sediment and microbial carbonates are mixtures of high-magnesium calcite and aragonite. Magnesium-calcite content increases with increasing consolidation. Lithified sediment and microbial carbonate are interpreted as fine, biodetrital sediment that was subsequently cemented by authigenic micrite. Scalenohedral high-magnesium calcite and acicular aragonite cements played a subordinate role in cementation. Carbon and oxygen stable isotope ratios of lithified sediment and microbial carbonate exhibit similar ranges as modern reefal microbialites. Our study exemplifies that heterotrophic bacteria can be a crucial agent that contributes to the formation of carbonate build-ups by cementing skeletal frameworks in cryptic environments.
UnivIS-Import:2017-12-18:Pub.2017.nat.dgeo.IGM.LP.crypti
Keywords: Carbonate; Holocene; Microbialite; Reef; Sulfate reduction

Cryptic diversity along the onshore-offshore gradient: marginal marine environments were a cradle of early vertebrates - Jarochowska, Emilia; Viira, Viive; Einasto, Rein; Nawrot, Rafał; Bremer, Oskar; Männik, Peep; Munnecke, Axel (Macroecology 2019 - Bridging local patterns and global challenges, 2019)

Current measures for distance decay in similarity of species composition are influenced by study extent and grain size - Steinbauer, Manuel; Dolos, Klara; Reineking, Björn; Beierkuhnlein, Carl (Global Ecology and Biogeography, 2012)
Aim: The relationship between geographic distance and similarity in species composition is regularly used as a measure of species turnover and beta diversity. Distance–decay analyses are applied, cited and compared despite the variable extent, and different grain sizes of records (e.g. plots, islands, states) are regularly used within such analyses. Currently, differences among distance–decay relationships that cover different grain sizes and extents are attributed to ecological processes that are suspected to operate differently over varying extents and grain sizes. We assess whether the implicit assumption that the distance–decay relation is independent of grain size and study extent is valid, or whether sampling design could be the underlying cause for observed differences. Location: An artificial one-dimensional ‘landscape’. Methods: The distance–decay relationship was quantified in simulated communities. Grain and study extent were varied systematically. In each sampled data set the linear relation of Simpson and Sørensen similarity to geographic distance (on both log-transformed and original scales) between 100 even-sized equidistant plots was assessed using linear regression and generalized linear regression with a log-link function. Regressions were applied either including or removing zero similarities from the data. Results: Both the slope (measuring turnover) and the goodness of fit measure r2 (quantifying the influence of space on species composition) of the distance–decay relationship were strongly influenced by grain and study extent. Approaches that are able to cope with zero similarity values of large distance comparisons were less dependent on grain and extent. Main conclusions: Reported differences between landscapes detected by current distance–decay measures cannot be explicitly traced back to ecological scale-specific processes. Instead, they can largely be attributed to sampling design and are highly sensitive to grain size and study extent. More appropriate approaches for the study of distance–decay and the understanding of scale-specific processes are required.
Keywords: Beta diversity; Biodiversity; Dissimilarity; Ecological gradient; Sørensen similarity; Scale dependence; Simpson similarity; Species turnover

d13C chemostratigraphy in Lower-Middle Ordovician succession of Öland (Sweden) and the global significance of the MDICE - Calner, Mikael; Lehnert, Oliver; Wu, Rongchang; Dahlqvist, Peter; Joachimski, Michael (Gff, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LG.d13cch

d13C chemostratigraphy in the upper Tremadocian through lower Katian (Ordovician) carbonate succession of the Siljan district, central Sweden. - Lehnert, Oliver; Meinhold, Guido; Wu, Rongchang; Calner, Mikael; Joachimski, Michael (Estonian Journal of Earth Sciences, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LG.d13cch_3

d18O record from conodont apatite across the Lower-Middle Ordovician boundary on the Yangtze platform (Western Hubei, South China). - Lehnert, Oliver; Stouge, Svend; Joachimski, Michael; Buggisch, Werner (Acta Palaeontologica Sinica, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LG.d18ore

Das Belemnitenschlachtfeld von Mistelgau - Schulbert, Christian (Der Steinkern, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.dasbel
Keywords: Belemnitenschlachtfeld; Mistelgau

Das Hessische Landesmuseum Darmstadt - Geschichte und Neukonzeption - Roden, Vanessa (Conference: Centenary Meeting of the Paläontologische Gesellschaft, 2012)

Das Potenzial coralliner Rotalgen als SST-Proxy und für die Evaluierung globaler Klimamodelle: eine Fallstudie in Neuseeland - Kropac, Elena; Mölg, Thomas; Teichert, Sebastian (Tagungsband zur 39. Sitzung des Arbeitskreises Klima, 2021)
Globale Klimamodelle (General Circulation Models; GCMs) sind das aktuell wichtigste Instrument der Klimawissenschaft, um Aussagen und Projektionen über das Klima der Zukunft zu treffen. Sie liefern zudem Daten-Input für regionale Atmosphärenmodelle, mithilfe derer der sog. „Klima-Impakt“ großräumiger Klimaänderungen auf regionaler und lokaler Ebene berechnet werden kann. Um möglichst akkurate Projektionen und Inputdaten zu gewährleisten, müssen GCMs bestmöglich mit Klimaaufzeichnungen der Vergangenheit evaluiert werden, wobei der Fokus auf der sog. "historischen Periode" von 1850 bis zur Gegenwart liegt. Die Evaluierung ist für den Zeitraum vor 1950, und insbesondere für die Südliche Hemisphäre, aufgrund der stark eingeschränkten Verfügbarkeit und Qualität von Beobachtungsdaten jedoch schwierig. Im Rahmen des im Februar 2021 angelaufenen Projekts „NZ-PROXY“ werden krustenbildende coralline Rotalgen (KCA) als Klimaindikatoren eingesetzt, um – analog zu dendrochronologischen Rekonstruktionen der terrestrischen Lufttemperatur – die Beobachtungszeitreihe der Meeresoberflächentemperatur (SST) in Neuseeland bis 1850 zu verlängern. KCA zeichnen sich im Vergleich zu anderen marinen Klima-Indikatoren u.a. durch ihre weltweite Verbreitung, zeitlich hochaufgelöste Information und relativ leichte Zugänglichkeit aus. Der mithilfe der KCA neu gewonnene, historische SSTDatensatz soll für die Evaluierung von GCMs in der Neuseelandregion verwendet werden und somit die Auswahl geeigneter GCM-Inputdatensätze für regionale Atmosphärenmodelle und die Verbesserung regionaler Klimamodellierung ermöglichen. Aufgrund seiner einzigartigen geographischen Lage ist Neuseeland von ozeanischer und atmosphärischer Klimavariabilität gleichermaßen beeinflusst; Variationen der SST schlagen sich dort auf einer Vielzahl von räumlichen und zeitlichen Skalen nieder und sind bis hin zu Temperaturanomalien und Gletschermassenbilanzänderungen im Hochgebirge der Südlichen Alpen statistisch detektierbar. Eine korrekte Simulation der SST durch GCMs ist daher essentiell und kann im Rahmen der regionalen Modellierung dazu beitragen, die physikalischen Mechanismen zu entschlüsseln, die großräumige SST-Signale in lokale Klimaanomalien umwandeln. Im Vortrag werden der Forschungsansatz sowie erste Ergebnisse aus Laboranalysen und Modellierungen vorgestellt. <br

Dead end for endemic plant species? A biodiversity hotspot under pressure - Kidane, Yohannes O.; Steinbauer, Manuel; Beierkuhnlein, Carl (Global Ecology and Conservation, 2019)
Tropical high mountains are hosting important hot spots of biodiversity on small mostly remote areas. Recently, these precious ecosystems are under threat from land use change and climate change coupled with other local drivers of biodiversity loss. Along the East African Afroalpine ecosystems, area above the treeline have experienced long-term spatial isolation and extreme climatic conditions (climatic factors such as low mean temperature, diurnal freeze-thaw cycles and other energy-related factors) which lead to the formation of "Sky Island" like ecosystems that are rich in endemics and unique. The Bale Mountains of Ethiopia are home to the largest tropical alpine plateau in Africa, with no spacious high summits that provide space for upward shift of species. Here, we studied plant species diversity and distribution patterns and tested potential future impacts of climate change induced warming on those patterns. This study is based on distribution data acquired from nested circular plots along an elevational gradient ranging from 2000m asl to the highest elevation (4385 m asl). We find hump shaped species richness patterns on both aspects, i.e. the dry north-eastern and the wet monsoon exposed south-western escarpment. In addition, the proportion of endemic species increases monotonically towards the summit on all slopes. Based on our data and literature, we project future climate impact for three regional warming scenarios (+2 degrees C, + 3 degrees C and + 4 degrees C). We quantify the future range of 114 endemic plant species based on their current occurrence records applying a lapse rate of 0.6 degrees C per 100 m of elevation. We find that future climate change would significantly alter species distribution patterns with pronounced impact on the unique ecosystems and endemic species restricted to the afroalpine plateau. Very likely this will be leading to the extinction of many endemic species. Published by Elsevier B.V.
CRIS-Team WoS Importer:2019-08-09

Decoding sea surface and paleoclimate conditions in the eastern Mediterranean over the Tortonian-Messinian Transition - Kontakiotis, G.; Besiou, E.; Antonarakou, A.; Zarkogiannis, S. D.; Kostis, A.; Mortyn, P. G.; Moissette, P.; Cornée, J. J.; Schulbert, Christian; Drinia, H.; Anastasakis, G.; Karakitsios, V. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2019)
New sedimentological, micropaleontological and geochemical data from the Upper Miocene pre-evaporitic sedimentary sequence of the Faneromeni section (Crete Island, eastern Mediterranean) revealed a stepwise restriction of the Mediterranean Sea preceding the Messinian Salinity Crisis (MSC), which was modulated by a sedimentary cyclicity responding to orbital parameters. This cyclicity is manifested by lithological alternations from laminated to indurated homogeneous marls and clayey limestones, and covers the Tortonian-Messinian Transition (TMT; 7.6–6.7 Ma). This time window covers the successive closure of the marine Mediterranean-Atlantic gateways, which culminated in the onset of the MSC. In the present study, we present the first evidence for changes in the upper water column reflected by sea surface temperature (SST) and salinity (SSS) variations that correlate with pronounced paleoclimatic fluctuations. Planktonic foraminiferal isotopes, in combination with paired mixed layer Sr/Ca-derived SST data, reveal that the very warm late Tortonian interval has been followed by a strong long-term cooling ( 10 °C) and desalination ( 10‰) trend during the earliest Messinian, attributed to the paroxysmal phase of the so-called “siphon” event. In particular, the climate shift that occurred at the end of a global carbon isotope (δ13C) decrease suggests that changes in the carbon cycle were instrumental in driving late Miocene climate dynamics (cooling and aridity) in the progressively isolated eastern Mediterranean Sea. The observed salinity variability during this time interval also provides further insights about seasonal freshwater inputs and gives new support to the much-debated hydrologic regime (linear salinity increase vs step-function evolution with strong salinity fluctuations) preceding the deposition of evaporites. The novel methodology of foraminiferal Sr/Ca paleothermometry and results of this study could have numerous potential applications to other regions and relevant extreme geological events. Therefore, in the near future we expect this approach to add important new information to our understanding of Neogene climates.
CRIS-Team Scopus Importer:2019-08-16
Keywords: Hydrological cycle; Late Miocene; Messinian Salinity Crisis (MSC); Sea surface salinity (SSS); Siphon cooling event; Sr/Ca paleothermometry

Deeper insights: The potential of X-ray micro-computed tomography (μCT) in microplastic studies - Löder, Martin; Wittmann, Marie; Teichert, Sebastian; Schulbert, Christian; Oster, Jakob; Laforsch, Christian (MICRO 2020 - Fate and Impacts of Microplastics: Knowledge and Responsibilities, 2020)
Since the topic of microplastics and the detection of these small plastic particles is becoming increasingly important in science, it is necessary to establish methods that allow for a non-destructive detection of microplastics in research objects. Especially with respect to the detection of environmentally relevant concentrations of microplastics in experimental organisms without destroying their body structures X-ray micro-computed tomography (μCT) is a very promising technique. We report first results of experiments with radiopaque polyurethane microplastics. Ten terrestrial and aquatic invertebrate species were selected as experimental organisms to provide a cross-section of different invertebrate taxa. In nine of the ten organisms used, microplastic particles could be easily detected by μCT, and in most cases the exact position of the plastic in the digestive tract of the individual organisms could also be determined. In animals with a solid cuticle, the method is also well suited for detecting external structures. In order to be able to make more precise statements about the position of the microplastics in the body structure of the animals radio-opaque staining methods are available and have to be tested in future studies. The method described here is particularly suitable for non-destructive detection of microplastics in organisms at low natural microplastic concentrations in experiments on the uptake and trophic transfer of microplastics.<br

Deep-time climate legacies affect origination rates of marine genera - Mathes, Gregor; Kießling, Wolfgang; Steinbauer, Manuel J. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Biodiversity dynamics are shaped by a complex interplay between current conditions and historic legacy. The interaction of short- and long-term climate change may mask the true relationship of evolutionary responses to climate change if not specifically accounted for. These paleoclimate interactions have been demonstrated for extinction risk and biodiversity change, but their importance for origination dynamics remains untested. Here, we show that origination probability in marine fossil genera is strongly affected by paleoclimate interactions. Overall, origination probability increases by 27.8% [95% CI (27.4%, 28.3%)] when a short-term cooling adds to a long-term cooling trend. This large effect is consistent through time and all studied groups. The mechanisms of the detected effect might be manifold but are likely connected to increased allopatric speciation with eustatic sea level drop caused by sustained global cooling. We tested this potential mechanism through which paleoclimate interactions can act on origination rates by additionally examining a proxy for habitat fragmentation. This proxy, continental fragmentation, has a similar effect on origination rates as paleoclimate interactions, supporting the importance of allopatric speciation through habitat fragmentation in the deep-time fossil record. The identified complex nature of paleoclimate interactions might explain contradictory conclusions on the relationship between temperature and origination in the previous literature. Our results highlight the need to account for complex interactions in evolutionary studies both between and among biotic and abiotic factors.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Climate change; Evolution; Fossil record; Macroevolution; Paleoclimate

Deglacial–Holocene Svalbard paleoceanography and evidence of meltwater pulse 1B - Tian, Skye Yunshu; Yasuhara, Moriaki; Hong, Yuanyuan; Huang, Huai-Hsuan; Iwatani, Hokuto; Chiu, Wing Tung Ruby; Mamo, Briony; Okahashi, Hisayo; Rasmussen, Tine L. (Quaternary Science Reviews, 2020)
Better understanding of deglacial meltwater pulses (MWPs) is imperative for future predictions of human-induced warming and abrupt sea-level change because of their potential for catastrophic damage. However, our knowledge of the second largest meltwater pulse MWP-1B that occurred shortly after the start of the Holocene interglacial remains very limited. Here, we studied fossil ostracods as paleoenvironmental indicators of water depth, salinity, and temperature in two marine sediment cores from Storfjorden, Svalbard margin (the Arctic Ocean), to investigate near-field (i.e. areas located beneath continental ice sheets at the Last Glacial Maximum) evidence of MWP-1B. The depositional environment changed from a cold bathyal environment to a warmer bathyal environment at ∼11,300 yr BP indicating incursion of warm Atlantic water into the Nordic seas, and eventually to a cold neritic environment by ∼11,000 yr BP because of melting of the Svalbard-Barents Sea ice sheet and resultant isostatic rebound. This process corresponds to rapid relative sea-level fall of 40–80 m of MWP-1B from ∼11,300 to 11,000 yr BP.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Arctic ocean; Holocene; Micropaleontology; Neoglaciation; Ostracoda; Paleoceanography; Sea level change; The last deglaciation

Demise of the last two spire-bearing brachiopod orders (Spiriferinida and Athyridida) at the Toarcian (Early Jurassic) extinction event - Vörös, Attila; Kocsis, Ádám; Palfy, Jozsef (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Brachiopods were severely hit by several mass extinctions which fundamentally shaped their long evolutionary history. After the devastating end-Permian extinction, the fate of the four surviving orders differed significantly during the Triassic and Jurassic. Two orders, the rhynchonellids and terebratulids are extant today, whereas spiriferinids and athyridids, which possess spiral brachidia, suffered heavy losses at the end of the Triassic and became extinct in the Early Jurassic Toarcian event. Although the doom of the spire-bearing orders has been thought to be related to physiological traits, extinction selectivity across the end-Triassic and Toarcian event has not been rigorously assessed previously, and the reasons for their demise at the later and lesser Toarcian event, rather than at the earlier and greater end-Triassic crisis remained unexplored. Using primarily the Paleobiology Database, we constructed diversity curves, estimated taxonomic rates, and assessed the temporal changes in geographic distribution of the two spire-bearing and two other orders in the Triassic-Jurassic interval. After shared trends and similar origination rates in the post-Permian recovery leading to a Late Triassic diversity maximum, the end-Triassic extinction was selective and preferentially eliminated the spire-bearers. In contrast to the rebound of rhynchonellids and terebratulids, spire-bearers failed to recover in the Early Jurassic, and their repeated selective extinction at the Toarcian event led to their final demise. The end-Triassic event also terminated the worldwide geographic distribution of spire-bearers, confining them to the Western Tethys, whereas the other groups were able to re-establish their cosmopolitan distribution. The morphologically diverse spire-bearers represent specialized adaptation, which further increased their extinction vulnerability compared to the other groups with conservative biconvex shell morphology. Another key difference is the physiological disadvantage of the fixed lophophore and passive feeding of spire-bearers, which became critical at times of increased environmental stress. The spire-bearing spiriferinids and athyridids were “dead clades walking” in the Early Jurassic and their disappearance in the Early Toarcian represents the last major, order-level extinction event for the brachiopods.
Keywords: Diversity; Paleobiology Database; End-Triassic; Mass extinction; Paleobiogeographic distribution

Der Jurensismergel von Mistelgau - Schulbert, Christian (Der Steinkern, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.derjur
Keywords: Jurensismergel-Formation; Mistelgau

Describing Ammonoid Conchs - Klug, Christian; Korn, Dieter; Landman, Neil; Tanabe, Kazushige; de Baets, Kenneth; Naglik, Carole (Ammonoid Paleobiology: From anatomy to ecology, 2015)

Desmekalamos fuersichi nov. gen., nov. spec., ein Mikroröhrchen (Cyanophycee ?) aus den norischen Riffkalken des Taurus-Gebirges, Süd-Türkei - Senowbari-Daryan, Baba; Link, Michael (Beringeria, 2007)
Aus den norischen Riffschuttkalken des Taurus-Gebirges (Trias, Südtürkei) wird ein koloniebildendes Mikroröhrchen als Desmekalamos fuersichi nov. gen., nov. sp. beschrieben. Die Röhren rollen sich gesellig und irregulär verteilt um einen zentralen, sekundär mit Kalzit gefüllten Hohlraum auf. Durch die Bündelung der Röhrchen sowie durch biogen induzierte Aragonit-Nadeln um die einzelnen Mikroröhrchen herum entsteht eine größere, dickwandige und im Durchlicht dunkel erscheinende Makroröhre, die bevorzugt innerhalb mikrobieller Krusten im Riffbiotop auftritt. In der Wand der Makroröhre erscheinen die einzelnen Röhrchen von Desmekalamos fuersichi im Durchlicht meist als kleine, helle Punkte oder als kurze Schläuche, was mit Bohrungen von Mikroorganismen verwechselt werden kann. Die systematische Zuordnung von Desmekalamos fuersichi wird diskutiert. Höchstwahrscheinlich handelt sich hierbei um Cyanophyceen.
UnivIS-Import:2015-04-14:Pub.2007.nat.dgeo.IGM.LP.desmik
Keywords: Desmekalamos; Cyanophyta; Trias; Nor; Riff; Taurus-Gebirge; Türkei

Desmoinesian (Middle Pennsylvanian) orthocerid cephalopods from the Buckhorn Asphalt Lagerstätte in Oklahoma, Midcontinent North America - Niko, Shuji; Seuß, Barbara; Mapes, Royal H. (Paleontological Research, 2018)
UnivIS-Import:2017-01-09:Pub.2016.nat.dgeo.IGM.LP.bryozo
Keywords: Bryozoa; Oklahoma; Palaeoecology; Pennsylvanian; Preservation; Taxonomy

Detecting initial aragonite and calcite variations in limestone-marl alternations - Nohl, Theresa; Steinbauer, Manuel; Sinnesael, Matthias; Jarochowska, Emilia (Sedimentology, 2021)
Limestone-marl alternations are commonly used for high-resolution cyclostratigraphic studies and palaeoenvironmental reconstructions, but diagenetic studies indicate that not all limestone-marl alternations reflect genuine differences in the initial sediment composition driven by environmental changes. Differences in the ratios of diagenetically inert trace elements between limestones and marls indicate changes affecting the terrigenous fraction of the precursor sediment. Contrarily, limestone-marl alternations without these differences can be the product of: (i) variations in CaCO3 input (aragonite, calcite); (ii) distortion of the latter by diagenetic CaCO3 redistribution; or (iii) diagenetic CaCO3 redistribution in a homogeneous precursor sediment. The aim of this study is to provide a method to differentiate these cases and to identify variations in the proportion of calcite and aragonite in the precursor sediment composition. The model of differential diagenesis assumes that the concentration of diagenetically inert elements is inversely proportional to the amount of redistributed CaCO3. Consequently, the difference between ratios of diagenetically inert elements from two adjacent beds is a measure for CaCO3 redistribution. This is quantifiable by the vector length between ratios from two adjacent beds. The approach is illustrated here by evaluation of a case study from the Silurian of Gotland, Sweden. Trace elements were compared according to their solubility during diagenesis. All elements bound to clay minerals or calcite show similar patterns of vector length, while vector length of elements which fit into the aragonite lattice, and are diagenetically mobile, differ. The vector length approach provides a tool to test the diagenetic origin of limestone-marl alternations, to identify initial variations in CaCO3 input and to test a limestone-marl alternation's suitability for cyclostratigraphic analyses.
CRIS-Team WoS Importer:2021-06-04

Devonian pearls and ammonoid-endoparasite co-evolution - de Baets, Kenneth; Klug, Christian; Korn, Dieter (Acta Palaeontologica Polonica, 2011)
Raised shell projections on the inner shell walls that form pits on the internal moulds of Devonian ammonoids have been known for several decades. New specimens from Morocco reveal novel details or these structures; most, if not all, of which consist of a capsule of ammonoid shell that covers tiny tubes attached to the outer (= lateral or ventral) shell wall from the inside. In accordance with comparable Recent occurrences of similar structures in molluscs, we use the term "pearls" for these structures and the pits they form on the internal moulds. The nature of these encapsulated tubes is described and discussed. Because of the presence of these tubes inside the pearls, pearl arrangement, and their similarity to Recent mollusc occurrences, the tubes are interpreted as traces of parasitoses. The pearls and pits were grouped into five types based on differences in morphology, size, and arrangement. Then, having used these traits to perform a simple cladistic analysis, the resulting cladogram was compared to the phylogeny of ammonoids. Based on this comparison, it appears likely that the parasites underwent a co-evolution with the ammonoids, which lasted 10 to 15 Ma. Patterns of evolutionary events include co-speciation, "drowning on arrival" (end of parasite lineage near base of a new host clade), and "missing the boat" (parasite lineage does not adapt to a new host clade, thus not evolving a new parasite clade). Because of the lack of fossilised soft tissue, only speculations can be made about the systematic affiliation of the parasites, their life-cycle, infection strategy, and ecological framework. Some co-occurring bivalves also have pits reminiscent to structures caused by trematodes in Recent forms. Based on the available information, the tubes are interpreted as artefacts of trematode infestations, which, if correct, would extend the fossil record of parasitic trematodes into the Early Devonian.
Keywords: Ammonoidea; Trematoda; parasite; pearl; co-evolution; Devonian; Morocco; Algeria; Germany

Diagenesis makes the impossible come true: intersecting beds in calcareous turbidites - Westphal, Hildegard; Lavi, Jonathan; Munnecke, Axel (Facies, 2015)
Constructing a time-frame of the past is fundamental for any geological interpretation, and the recognition of orbital cycles preserved in the stratigraphic record has revolutionized our understanding of the global timescale, especially for the Cenozoic. In the past decades, astrochronological and cyclostratigraphic approaches based on Milankovitch cycles have become a widely used tool for precisely dating stratigraphic boundaries by calibrating sedimentary units with astronomically tuned timescales. In many cases, strikingly rhythmic limestone-marl alternations are used for such approaches. Astrochronological approaches as a basic principle rely on the fundamental assumption that such rhythmites reflect fluctuating environmental conditions caused by variations in incident solar radiation such as changes in sea level, temperature, or weathering. Nevertheless, in many cases, the crucial question as to whether such rhythmites represent primary cycles or are purely of diagenetic origin has never been positively decided. In those cases, stratigraphic dating with this method is left unreliable. Here, the ability of diagenesis to produce rhythmic bedding lacking any relation to primary sedimentary signals is demonstrated. The Miocene succession discussed here shows two cemented sets of beds with different inclinations, one parallel to the sedimentary layering, the other, coeval, but in an oblique direction. These two sets merge and do not show distinct boundaries, thus indicating synchronous cementation. It is interpreted that minor early synsedimentary tectonic stress introduced an oblique anisotropy. During early differential diagenesis, this dual anisotropy influenced the geometry of the cemented layers, giving the impression of intersecting layers.
Keywords: Astrochronology; Diagenesis; Limestone-marl alternations; Miocene; Stratigraphy; Turbidites

Diagenesis of plattenkalk: Examples from the Solnhofen area (Upper Jurassic, southern Germany) - Munnecke, Axel; Westphal, Hildegard; Kölbl-Ebert, Martina (Sedimentology, 2008)
The Upper Jurassic (Tithonian) plattenkalk successions in the Solnhofen/ Eichstätt area consist of alternations of thin-bedded, laminated, fine-grained, very pure limestones (so-called 'flinz beds') and softer interlayers with slightly lower carbonate contents that are also laminated and show a foliaceous weathering appearance ('fäule beds'). These successions are world famous for their exceptionally well-preserved fossils. In contrast to the well-studied wealth of fossils, little is known about the origin and diagenesis of the host rock. The reason for this discrepancy might lay in the monotonous appearance of these fine-grained mudstones that require electron microscopical examination. Study of samples from the Solnhofen-Eichstädt area implies that flinz and fäule beds have undergone differential diagenesis. The ultrastructure of the flinz beds is characterized by interlocking microspar crystals, whereas the fäule beds show smaller and less interlocking crystals. The ratios of diagenetically inert trace elements lack clear differences between the two interlayered lithologies. While most authors agree that the flinz-fäule rhythm reflects rhythmically changing environmental conditions, primary rhythms can be taken as proven only where statistically significant differences in diagenetically resistant proxies are found. The absence of clear primary differences between flinz and fäule beds, however, leaves the question of primary differences unsolved. It is concluded that diagenesis has had a strong influence on the genesis of the lithological rhythm, and that any primary rhythm underlying the diagenetically mature rhythm is less clear than generally assumed. © Journal compilation © 2008 International Association of Sedimentologist
Keywords: Upper Jurassic; Tithonian; Plattenkalk; Solnhofen; Diagenesis

Diagenesis of Upper Jurassic concretions from the Antarctic Peninsula - Kießling, Wolfgang; et al. (Journal of Sedimentary Research, 2001)
Early-diagenetic calcite concretions are widespread in mudstone-tuff sequences deposited in Late Jurassic oxygen-deficient basins of the Antarctic Peninsula. Although obscured or destroyed in host rocks, original components and sedimentary structures are well preserved in concretions, in spite of significant mineralogical and geochcmical change during growth. Early diagenesis led to a rapid and almost total variation in the mineralogy within the concretions, independently of the original host lithologies. Siliceous particles were replaced by chlorite and zeolites in suboxic, alkaline, and moderately reducing conditions on the sea floor and in the first centimeters of burial. These conditions also led to localized early formation of phosphate concretions. Pyrite developed subsequently because of high sulfide abundance in the sulfate reduction zone. Most calcite precipitation took place in the lower part of the sulfate reduction zone in a strongly alkaline environment where sulfide content had been lowered by pyrite precipitation. In this stage, the remaining siliceous elements were dissolved or replaced by calcite. Later diagenetic changes include enlargement of zeolites, minor changes in clay minerals, and the formation of calcite veins. The wide range of δ 13C values in cement and vein calcite (-1.4‰ and -20.23‰ PDB) is explained by mixed carbon sources from organic matter oxidation and dissolution of calcareous shells. The low δ 18O of calcite (-2.34‰ to -19.72‰ PDB) is the result of recrystallization in contact with high-temperature diagenetic or hydrothermal fluids flushed through micro-fractures in the concretions, which also produced extensive vein formation. Copyright © 2001, SEPM (Society for Sedimentary Geology).
UnivIS-Import:2015-03-09:Pub.2001.nat.dgeo.IGM.LP.diagen

Dickenzuwachs der exotischen Thuja plicata und der einheimischen Picea abies in Ab-hängigkeit von Klima und Witterung in Süddeutschland - Schlüter, Rebecca; Steinbauer, Manuel; Remmele, Sabine; Aas, Gregor (Allgemeine Forst- und Jagdzeitung, 2015)

Did plankton evolution trigger the Ordovician diversifications? - Lehnert, Oliver; Vecoli, Marco; Servais, Thomas; Nützel, Alexander (Acta Palaeontologica Sinica, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LG.didpla

Die Ammonitenfauna und Stratigraphie der Tongrube Mistelgau bei Bayreuth (Oberfranken) - Schulbert, Christian (Berichte der Naturwissenschaftlichen Gesellschaft Bayreuth, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dgeo.IGM.LP.dieamm

Die Bedeutung der Conodontenstratigraphie in der Klastenforschung am Beispiel der Tertiärabfolgen von Ellesmere Island (kanadische Arktis). - Lehnert, Oliver; Nowlan, Godfrey; Lee, Carmen (Archiv für Geschiebekunde, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dgeo.IGM.LG.diebed

Die moderne Computer-Tomographie (Modell v|tome|x s 240 von GE/Phoenix) am Lehrstuhl für Paläoumwelt (GZN, Erlangen) – Methodik und Anwendungsbeispiele - Schulbert, Christian; Koch, Roman (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2017)
Keywords: Mikro-Computer-Tomographie

Die Tongrube Mistelgau bei Bayreuth - Schulbert, Christian (Erdgeschichtliche Zeitreise durch Nordbayern, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dgeo.IGM.LP.dieton
Keywords: Tongrube; Mistelgau

Die Tongrube Mistelgau - Schulbert, Christian (Der Steinkern, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.dieton
Keywords: Tongrube; Mistelgau

Differential niche dynamics among major marine invertebrate clades - Hopkins, Melanie; Simpson, Carl; Kießling, Wolfgang (Ecology Letters, 2014)
The degree to which organisms retain their environmental preferences is of utmost importance in predicting their fate in a world of rapid climate change. Notably, marine invertebrates frequently show strong affinities for either carbonate or terrigenous clastic environments. This affinity is due to characteristics of the sediments as well as correlated environmental factors. We assessed the conservatism of substrate affinities of marine invertebrates over geological timescales, and found that niche conservatism is prevalent in the oceans, and largely determined by the strength of initial habitat preference. There is substantial variation in niche conservatism among major clades with corals and sponges being among the most conservative. Time-series analysis suggests that niche conservatism is enhanced during times of elevated nutrient flux, whereas niche evolution tends to occur after mass extinctions. Niche evolution is not necessarily elevated in genera exhibiting higher turnover in species composition. © 2013 The Authors. Ecology Letters published by John Wiley & Sons Ltd and CNRS.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.differ
Keywords: Carbonate environments; Climate change; Niche conservatism; Species turnover; Substrate affinity; Terrigenous clastic environments

Digging deeper into colonial palaeontological practices in modern day Mexico and Brazil - Cisneros, Juan; Raja Schoob, Nussaibah Begum; Ghilardi, Aline Marcele; Dunne, Emma; Pinheiro, Felipe; Regalado Fernández, Omar Rafael; Sales, Marcos; Rodríguez-de la Rosa, Rubén; Miranda-Martínez, Adriana; González-Mora, Sergio; Bantim, Renan; de Lima, Flaviana; et al. (Royal Society Open Science, 2022)
Scientific practices stemming from colonialism, whereby middle- and low-income countries supply data for high-income countries and the contributions of local expertise are devalued, are still prevalent today in the field of palaeontology. In response to these unjust practices, countries such as Mexico and Brazil adopted protective laws and regulations during the twentieth century to preserve their palaeontological heritage. However, scientific colonialism is still reflected in many publications describing fossil specimens recovered from these countries. Here, we present examples of ‘palaeontological colonialism’ from publications on Jurassic–Cretaceous fossils from NE Mexico and NE Brazil spanning the last three decades. Common issues that we identified in these publications are the absence of both fieldwork and export permit declarations and the lack of local experts among authorships. In Mexico, access to many fossil specimens is restricted on account of these specimens being housed in private collections, whereas a high number of studies on Brazilian fossils are based on specimens illegally reposited in foreign collections, particularly in Germany and Japan. Finally, we outline and discuss the wider academic and social impacts of these research practices, and propose exhaustive recommendations to scientists, journals, museums, research institutions and government and funding agencies in order to overcome these practices.<br

Digital skull anatomy of the Oligocene North American tortoise Stylemys nebrascensis with taxonomic comments on the species and comparisons with extant testudinids of the Gopherus–Manouria clade - Evers, Serjoscha W.; Al Lawati, Zahra (Swiss Journal of Palaeontology, 2024)
The anatomy of North American tortoises is poorly understood, despite a rich fossil record from the Eocene and younger strata. Stylemys nebrascensis is a particularly noteworthy turtle in this regard, as hundreds of specimens are known from Oligocene deposits, and as this species is one of the earliest fossil turtles to have been described in the scientific literature. Since its initial description based on a shell, many specimens with more complete material have been referred to Stylemys nebrascensis. Here, we review and confirm the referral of an important historic specimen to Stylemys nebrascensis, which includes shell, non-shell postcranial, and skull material. This allows us to document unique skull features of Stylemys nebrascensis (e.g., an unusual ‘poststapedial canal’ that connects the posterior skull surface with the cavum acustico-jugulare) and to refer another well-preserved skull to the species. Based on computed-tomography scanning of these two skulls, we provide a detailed description of the cranial and mandibular osteology of Stylemys nebrascensis. Stylemys nebrascensis has a combination of plesiomorphic skull characteristics (e.g., retention of a medial jugal process) and derived traits shared with extant gopher tortoises (e.g., median premaxillary ridge) that suggest it may be a stem-representative of the gopher tortoise lineage. This supports the hypothesis that extant and fossil tortoises from North America form a geographically restricted clade that split from Asian relatives during the Paleogene.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Cranial evolution; Digital anatomy; Systematics; Taxonomy; Testudinidae; Tortoises; Turtles

Dissecting Calathium-microbial frameworks: The significance of calathids for the Middle Ordovician reefs in the Tarim Basin, northwestern China - Li, Qijian; Li, Yue; Zhang, Yuandong; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
As an obconical macrofossil with porous double-wall, . Calathium was commonly present in reefs of Early to early Middle Ordovician age. The . Calathium-bearing reefs thrived globally during the Early Ordovician, but this ecosystem collapsed in Middle Ordovician. A rare case of . Calathium-microbial reefs was found from the middle part of the Yijianfang Formation (Darriwilian, late Middle Ordovician) of the Bachu area, located in the northwestern margin of the Tarim Basin, northwestern China. Surrounded by bioclastic grainstones, patch reefs here are well-developed and vary in size, with 1-4. m in thickness and 2-18. m in diameter. Three facies types are distinguished within the reef limestones: (1) . Calathium-microbial framestone, (2) echinoderm-Calathium bafflestone, and (3) bryozoan-microbial bindstone. As a dominant type, the . Calathium-microbial framestone shows a three-dimensional skeletal framework that is mainly constructed by . Calathium and stabilized by microbialites. Although most specimens are toppled, . Calathium displays well-developed lateral outgrowths, which connected individuals of the same species. Morphological characters of . Calathium in thin sections show that calathids are hypercalcified sponges rather than receptaculitid algae. Unlike the Early Ordovician lithistid sponge-Calathium reefs, the Tarim reefs studied herein contain very few lithistid sponges. Instead, bryozoans are fairly common and act as the most important non-microbial encrusters, attaching to the walls of . Calathium. Noticeably, the co-occurrence of pelmatozoans and . Calathium is similar to those reported from Late Ordovician calathids-echinoderm reef communities from Tennessee. The presence of . Calathium-microbial reefs in Tarim indicates that locally calathids were major reef builders, at least before the latest Middle Ordovician.
Keywords: Calathium reef; Darriwilian; Microbialite; Northwestern China; Tarim Basin

Distinguishing Biologically Controlled Calcareous Biomineralization in Fossil Organisms Using Electron Backscatter Diffraction (EBSD) - Päßler, Jan-Filip; Jarochowska, Emilia; Bestmann, Michel; Munnecke, Axel (Frontiers in Earth Science, 2018)
Although carbonate-precipitating cyanobacteria are ubiquitous in aquatic ecosystems today, the criteria used to identify them in the geological record are subjective and rarely testable. Differences in the mode of biomineralization between cyanobacteria and eukaryotes, i.e., biologically induced calcification (BIM) vs. biologically controlled calcification (BCM), result in different crystallographic structures which might be used as a criterion to test cyanobacterial affinities. Cyanobacteria are often used as a “wastebasket taxon,” to which various microfossils are assigned. The lack of a testable criterion for the identification of cyanobacteria may bias their fossil record severely. We employed electron backscatter diffraction (EBSD) to investigate the structure of calcareous skeletons in two microproblematica widespread in Palaeozoic marine ecosystems: Rothpletzella, hypothesized to be a cyanobacterium, and an incertae sedis microorganism Allonema. We used a calcareous trilobite shell as a BCM reference. The mineralized structure of Allonema has a simple single-layered structure of acicular crystals perpendicular to the surface of the organism. The c-axes of these crystals are parallel to the elongation and thereby normal to the surface of the organism. EBSD pole figures and misorientation axes distribution reveal a fiber texture around the c-axis with a small degree of variation (up to 30°), indicating a highly ordered structure. A comparable pattern was found in the trilobite shell. This structure allows excluding biologically induced mineralization as the mechanism of shell formation in Allonema. In Rothpletzella, the c-axes of the microcrystalline sheath show a broader clustering compared to Allonema, but still reveal crystals tending to be perpendicular to the surface of the organism. The misorientation axes of adjacent crystals show an approximately random distribution. Rothpletzella also shares morphological similarities with extant cyanobacteria. We propose that the occurrence of a strong misorientation relationship between adjacent crystals with misorientation axes clustering around the c-axis can be used as a proxy for the degree of control exerted by an organism on its mineralized structures. Therefore, precisely constrained distributions of misorientations (misorientation angle and misorientation axis) may be used to identify BCM in otherwise problematic fossils and can be used to ground-truth the cyanobacterial affinities commonly proposed for problematic extinct organisms.

Distraction sinking and fossilized coleoid predatory behaviour from the German Early Jurassic - Klug, Christian; Schweigert, Günter; Fuchs, Dirk; de Baets, Kenneth (Swiss Journal of Palaeontology, 2021)
Exceptional fossil preservation is required to conserve soft-bodied fossils and even more so to conserve their behaviour. Here, we describe a fossil of a co-occurrence of representatives of two different octobrachian coleoid species. The fossils are from the Toarcian Posidonienschiefer of Ohmden near Holzmaden, Germany. The two animals died in the act of predation, i.e. one had caught the other and had begun to nibble on it, when they possibly sank into hypoxic waters and suffocated (distraction sinking). This supports the idea that primitive vampyromorphs pursued diverse feeding strategies and were not yet adapted to being opportunistic feeders in oxygen minimum zones like their modern relative Vampyroteuthis.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Cephalopoda; Coleoidea; Jurassic; Palaeoecology; Taphonomy

Distribution and habitats of Acesta excavata (Bivalvia: Limidae) with new data on its shell ultrastructure - López Correa, Matthias; Taviani, Marco; Freiwald, André; Hall-Spencer, Jason (Cold-water Corals and Ecosystems, 2005)
Acesta excavata is the largest known bivalve associated with the Lophelia pertusa communities along the northeast Atlantic continental margin, but has also been found along steep cliffs, devoid of bathyal corals, and on more subdued topographies. During the Pleistocene, including the last glacial, A. excavata was widespread in the Mediterranean, but is in the Recent fauna known only from four Mediterranean sites. A new possible live-record from the Canyon du Var off Nice is presented. Radiocarbon dating (AMS 14C-method) on an A. excavata assemblage from the Strait of Sicily yielded a Late Pleistocene age of 39.9 ka. Biometric parameters indicate that Pleistocene Mediterranean shells achieved about the same maximum sizes as their Recent Atlantic counterparts, but individuals have been slightly smaller on average. The subspecies Acesta excavata sublaevis Nordsieck, based on a subfossil juvenile Mediterranean shell, is not considered a valid taxon. Mineralogical composition and ultrastructure of A. excavata have been analyzed using thin-sections, Feigel staining, x-ray diffractometry (XRD) and SEM-imaging. Its wide distribution, large size (15 cm) and simple shell architecture makes it a prime candidate for palaeoenvironmental studies in cold-water coral settings.
UnivIS-Import:2015-04-20:Pub.2005.nat.dgeo.IGM.LP.distri
Keywords: Acesta; North Atlantic; Mediterranean Sea; biogeography; ultrastructure; ecology

Distribution of Chicxulub ejecta at the KT boundary. Catastrophic Events and Mass Extinctions - Kießling, Wolfgang; et al. (GSA Special Paper, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IGM.LP.distri

Distribution of Microplastics in the Marine Environment - Strafella, Pierluigi; López Correa, Matthias; Pyko, Ines; Teichert, Sebastian; Gomiero, Alessio (Handbook of Microplastics in the Environment, 2021)

Diversification trajectories and evolutionary life-history traits in early sharks and batoids - Kießling, Wolfgang; et al. (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2009)
Different interpretations on the timing of early diversification and radiation of modern sharks and batoids (Neoselachii) in the Earth's history exist and are related to discrepancies in taxonomic and phylogenetic interpretations favouring a Late Triassic or earliest Jurassic diversification and subsequent radiation event, respectively. Sampling standardization based on pooled taxonomic occurrences made it possible to overcome the problem of a much richer neoselachian record in the Late Jurassic than earlier on. The standardized pattern of genus richness is one of low and fairly constant diversity in the Late Triassic and earliest Jurassic with a steep rise in the Toarcian (ca 180Myr ago), representing the maximum diversification rate in the Jurassic towards a Middle and Late Jurassic plateau. The major Toarcian diversification agrees with the conclusions based on phylogenetic analyses, but is in conflict with older interpretations based on raw data. Early Jurassic expansion of neoselachians was opportunistic in the aftermath of the end-Triassic mass extinction and the reasons for their rapid diversification and radiation probably include small body size, short lifespans and oviparity, enabling faster ecological reorganizations and innovations in body plans for adapting to changing environmental conditions.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.divers

Diversity and morphological evolution of Jurassic belemnites from South Germany - Dera, Guillaume; Toumoulin, Agathe; de Baets, Kenneth (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Belemnites are extinct cephalopods whose evolutionary history is representative of successful adaptive radiations during the Mesozoic. Nevertheless, a detailed understanding of the dynamics and palaeoenvironmental drivers of this evolution is still lacking. In order to fill this gap, we analyze the diversity and morphological disparity of Jurassic rostra from South Germany, and compare these patterns with other Euro-Boreal trends. We show that, after an early apparition of few dissimilar groups during the Hettangian Sinemurian interval, belemnites experienced four periods of diversification (i.e., Early Pliensbachian, Middle Late Toarcian, Early Bajocian, and Oxfordian) marked by morphological disparifications of rostra towards forms potentially optimized for different hydrodynamic properties. These adaptive radiations were interrupted at regional scale by four biological crises corresponding to morphological bottlenecks (i.e., Pliensbachian Toarcian, Aalenian, Late Bajocian, and Kimmeridgian). Most of them were morphoselective, except the Aalenian extinction, which could be related to a prominent sea level fall. By comparing our results to palaeoenvironmental data, we show that warm temperate seawater temperatures might have favoured the diversification of belemnites, potentially by accelerating their metabolic rates, the population turnovers, and the evolutionary rates on the long term. Conversely, cooling or hyperthermal events correspond with biological crises. Migrations towards refuge areas located in the Arctic and Mediterranean domains could have been key factors for rapid post-crisis recoveries. Finally, the available data suggest a trend towards increased streamlining of the rostrum through the Jurassic. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Belemnite; Cephalopod; Evolution; Morphological disparity; Extinction

Diversity and palaeoecology of tropical marine soft-bottom assemblages from the Late Triassic (Cassian Formation, northern Italy) - Hausmann, Imelda M.; Nützel, Alexander; Reich, Mike; Roden, Vanessa (5th International Palaeontological Congress, 2018)

Diversity of Life through Time - Simpson, Carl; Kießling, Wolfgang (Encyclopedia of Life Sciences (ELS), 2010)
UnivIS-Import:2015-04-02:Pub.2010.nat.dgeo.IGM.LP.divers

Diversity partitioning during the Cambrian radiation - Na, Lin; Kießling, Wolfgang (Proceedings of the National Academy of Sciences of the United States of America, 2015)
UnivIS-Import:2017-01-09:Pub.2015.nat.dgeo.IGM.LP.divers
Keywords: Alpha diversity; Beta diversity; Cambrian radiation; Low competition; Pannotia

Diversity, stand characteristics and spatial aggregation of tree species in a Bangladesh forest ecosystem - Uddin, Mohammad Belal; Steinbauer, Manuel; Beierkuhnlein, Carl (Diversity, 2011)
Assessing biodiversity and the spatial structures of forest ecosystems are important for forestry and nature conservation. However, tropical forests of Bangladesh are only sparsely investigated. Here we determined biodiversity (alpha, beta and gamma), spatial species turnover and stand characteristics of one of the few remnant tropical forests in Bangladesh. Two differently protected areas of Satchari forest were compared. We recorded tree species composition, in a systematic plot design, measured diameter at breast height for each individual tree (to assess basal area), and calculated decay in similarity of tree species composition with geographical distance. The distance-decay was assessed separately for the whole study area and for two subsamples from Satchari National Park and Satchari Reserve Forest. Satchari National Park (strictly protected) had, despite its smaller area, a higher Alpha and Gamma diversity, but a lower Beta diversity than Satchari Reserve Forest. Variation in species composition was not significant between the two differently protected areas. Basal area increased significantly with protection status although tree individuals were of equal size in both areas. Plots in the Reserve Forest were associated with higher species turnover than in the National Park. We suggest anthropogenic disturbance, which occurs in the less strictly protected Reserve Forest, is the main driver for the detected spatial heterogeneity in species composition.
Keywords: Beta diversity; Conservation; Diameter at breast height; Distance-decay; Indian Subcontinent; Management; National park; Reserve forest

Do environmental attributes, disturbances and protection regimes determine the distribution of exotic plant species in Bangladesh forest ecosystem? - Uddin, Mohammad Belal; Steinbauer, Manuel; Jentsch, Anke; Mukul, Sharif Ahmed; Beierkuhnlein, Carl (Forest Ecology and Management, 2013)
Introduction of exotic plant species in the tropics has occurred since the colonial period, and has mostly been for timber production. However, due to uncontrolled distribution and lack of awareness, many of these species became invasive, and have been increasingly reported as a source of threats to native ecosystems. We investigated the exotic species richness, their traits, and biogeographic origin in the Satchari Forest in the north-eastern region of Bangladesh, one of the very few intact terrestrial ecosystems remaining in the country. Boosted Regression Trees and Detrended Correspondence Analysis were performed to determine the contribution of various environmental attributes, protection regimes, and disturbances to explain the distribution of exotic species within Satchari Forest. Among the environmental variables, native species richness, elevation gradient, and soil nutrient parameters were found as good predictors of both exotic species’ presence and richness in the area. In our analysis, number of exotic species showed a unimodal relationship with native species in the reserved forest, where the relationship was negative in the surrounding area. An increase in exotic species with the presence of higher anthropogenic disturbance events, thereby with lower conservation restrictions as well as with lower protection status, was also evident. Our study suggests that enforcing greater protection status and preventing human use can be the best ways to protect native species composition in forest ecosystems with greater conservation values in tropical developing countries.
Keywords: Exotic species; Land-use; Protected area; Satchari; Tropical forest

Do skeletal Mg/Ca ratios of Arctic rhodoliths reflect atmospheric CO2 concentrations? - Teichert, Sebastian; Voigt, Nora; Wisshak, Max (Polar Biology, 2020)
The rhodolith-forming coralline red algal species Lithothamnion glaciale is the key ecosystem engineer of rhodolith beds on the coast of Svalbard. Because it significantly increases local biodiversity in this high-Arctic environment, we investigate the potential impact of changing environmental parameters on its calcite skeleton. Using energy-dispersive X-ray spectroscopy and environmental data from the Norwegian government’s environmental monitoring, we show that the magnesium concentration within an analysed algal calcite skeleton decreases linearly and significantly over a 40-year time span (R2 = 0.267, pperm < 0.001). Mg/Ca ratios show the most significant correlation with atmospheric CO2 concentrations (R2 = 0.614, p < 0.001), and lower correlations to sea ice cover and seawater temperature. This raises the question of whether the Mg/Ca in the rhodolith skeleton is reflecting an increase in aqueous pCO2 that drives ongoing ocean acidification. Since such a change in geochemistry may alter the stability of the calcite skeleton, our results could imply an impact on the future role of the rhodoliths as ecosystem engineers and consequently on Arctic biodiversity.<br
Keywords: Coralline algae; Ecosystem engineers; Lithothamnion glaciale; Mg/Ca ratio; Ocean acidification; Rhodoliths; Svalbard

Drivers for plant species diversity in a characteristic tropical forest landscape in Bangladesh - Steinbauer, Manuel; Uddin, Mohammad B.; Jentsch, Anke; Beierkuhnlein, Carl (Landscape Research, 2017)
The importance of understanding biotic patterns in managed tropical landscapes is increasingly recognised. Bangladesh is a country with a long human land-use history and constitutes almost a blind spot in vegetation science on the landscape scale. Here, we analyse patterns and drivers of plant species richness and community composition along a land-use intensity gradient in a forest landscape including tea gardens, tree plantations and nature reserves (Satchari Reserved Forest) based on multivariate approaches and variation partitioning. We find richness as well as composition of tree and understory species to directly relate to a disturbance gradient that reflects protection status and elevation. This is astonishing, as the range in elevation (70 m) is small. Topography and protection remain significant drivers of biodiversity after correcting for human disturbances. While tree and non-tree species richness were positively correlated, they differ considerably in their relation to other environmental or disturbance variables as well as in the spatial richness pattern. The disturbance regime particularly structures tree species richness and composition in protected areas. We conclude by highlighting the importance of explicitly integrating human–biosphere interactions in any nature protection strategy for the study region.
Keywords: cultural landscapes; Disturbances; forest reserves; land-use pressure; similarity; tropical forests

Drivers of beta diversity in modern and ancient reef-associated soft-bottom environments - Roden, Vanessa; Zuschin, Martin; Nuetzel, Alexander; Hausmann, Imelda M.; Kießling, Wolfgang (PeerJ, 2020)
Beta diversity, the compositional variation among communities, is often associated with environmental gradients. Other drivers of beta diversity include stochastic processes, priority effects, predation, or competitive exclusion. Temporal turnover may also explain differences in faunal composition between fossil assemblages. To assess the drivers of beta diversity in reef-associated soft-bottom environments, we investigate community patterns in a Middle to Late Triassic reef basin assemblage from the Cassian Formation in the Dolomites, Northern Italy, and compare results with a Recent reef basin assemblage from the Northern Bay of Safaga, Red Sea, Egypt. We evaluate beta diversity with regard to age, water depth, and spatial distance, and compare the results with a null model to evaluate the stochasticity of these differences. Using pairwise proportional dissimilarity, we find very high beta diversity for the Cassian Formation (0.91 +/- 0.02) and slightly lower beta diversity for the Bay of Safaga (0.89 +/- 0.04). Null models show that stochasticity only plays a minor role in determining faunal differences. Spatial distance is also irrelevant. Contrary to expectations, there is no tendency of beta diversity to decrease with water depth. Although water depth has frequently been found to be a key factor in determining beta diversity, we find that it is not the major driver in these reef-associated soft-bottom environments. We postulate that priority effects and the biotic structuring of the sediment may be key determinants of beta diversity.
CRIS-Team WoS Importer:2020-05-29

Drivers of beta diversity in Triassic reefs and reef basins - Roden, Vanessa; Hausmann, Imelda M.; Kießling, Wolfgang (Annual Conference of the Paläontologische Gesellschaft, 2019)

Earliest Cretaceous high latitude reefs in Tres Lagunas (Chubut Province, Argentina) - Kießling, Wolfgang; et al. (Actas del XV Congreso Geológico Argentino, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IGM.LP.earlie

Early cephalopod evolution clarified through Bayesian phylogenetic inference - Pohle, Alexander; Kroeger, Bjoern; Warnock, Rachel; King, Andy H.; Evans, David H.; Aubrechtova, Martina; Cichowolski, Marcela; Fang, Xiang; Klug, Christian (BMC Biology, 2022)
Background: Despite the excellent fossil record of cephalopods, their early evolution is poorly understood. Different, partly incompatible phylogenetic hypotheses have been proposed in the past, which reflected individual author’s opinions on the importance of certain characters but were not based on thorough cladistic analyses. At the same time, methods of phylogenetic inference have undergone substantial improvements. For fossil datasets, which typically only include morphological data, Bayesian inference and in particular the introduction of the fossilized birth-death model have opened new possibilities. Nevertheless, many tree topologies recovered from these new methods reflect large uncertainties, which have led to discussions on how to best summarize the information contained in the posterior set of trees. Results: We present a large, newly compiled morphological character matrix of Cambrian and Ordovician cephalopods to conduct a comprehensive phylogenetic analysis and resolve existing controversies. Our results recover three major monophyletic groups, which correspond to the previously recognized Endoceratoidea, Multiceratoidea, and Orthoceratoidea, though comprising slightly different taxa. In addition, many Cambrian and Early Ordovician representatives of the Ellesmerocerida and Plectronocerida were recovered near the root. The Ellesmerocerida is para- and polyphyletic, with some of its members recovered among the Multiceratoidea and early Endoceratoidea. These relationships are robust against modifications of the dataset. While our trees initially seem to reflect large uncertainties, these are mainly a consequence of the way clade support is measured. We show that clade posterior probabilities and tree similarity metrics often underestimate congruence between trees, especially if wildcard taxa are involved. Conclusions: Our results provide important insights into the earliest evolution of cephalopods and clarify evolutionary pathways. We provide a classification scheme that is based on a robust phylogenetic analysis. Moreover, we provide some general insights on the application of Bayesian phylogenetic inference on morphological datasets. We support earlier findings that quartet similarity metrics should be preferred over the Robinson-Foulds distance when higher-level phylogenetic relationships are of interest and propose that using a posteriori pruned maximum clade credibility trees help in assessing support for phylogenetic relationships among a set of relevant taxa, because they provide clade support values that better reflect the phylogenetic signal.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Bayesian phylogenetics; Cephalopoda; Endoceratoidea; Fossilized birth-death process; Multiceratoidea; Nautiloidea; Orthoceratoidea; Phylogeny; Posterior clade probabilities; Tree similarities

EARLY EVOLUTIONARY TRENDS IN AMMONOID EMBRYONIC DEVELOPMENT - de Baets, Kenneth; Klug, Christian; Korn, Dieter (Evolution, 2012)

Early Ordovician lithistid sponge-Calathium reefs on the Yangtze Platform and their paleoceanographic implications - Kießling, Wolfgang; Li, Qijian; Li, Yue; Wang, Jianpo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2015)
Lithistid sponge- Calathium-microbial reefs were widespread on the Yangtze Platform during the Early Ordovician and are well studied. However, the biological affinity and the role of Calathium in these reefs have remained unclear up to now. We document lithistid sponge-. Calathium reefs from the Upper Hunghuayuan Formation (Early Floian) at Huanghuachang in Hubei, South China. These reefs have a three-dimensional skeletal framework that is mostly produced by Calathium and lithistid sponges. Calathium had a critical role in reef construction, as demonstrated by well-developed lateral outgrowths, which connected individuals of the same species and with lithistid sponges. Bryozoans, stromatoporoids and microbial components were secondary reef builders. Morphological, constructional and functional analyses provide evidence that Calathium was a sponge-grade metazoan rather than a receptaculitid alga as previously thought. At the dawn of the Ordovician Radiation, these small-scaled patch reefs thus represent the initial rebound of metazoan-dominated reefs after the Late-Early Cambrian archaeocyath reef crisis. Gradual global cooling through the Early Ordovician may have been a key driver for the return of metazoan reef
UnivIS-Import:2015-04-02:Pub.2015.nat.dgeo.IGM.LP.earlyo
Keywords: Calathium; Global cooling; Lithistid sponges; Reefs; Yangtze Platform

Early Ordovician sponge-Calathium-microbial reefs on the Yangtze Platform margin of the South China Block - Li, Qijian; Lin, Yue; Kießling, Wolfgang (Gff, 2014)
Early Ordovician (late Tremadocian to early Floian) reefs on the Yangtze Platform margin of the Hunghuayuan Formation at Zhangzhai section in southeastern Guizhou, South China show three types of reefs in two broad categories: microbial-dominated (stromatolite and lithistid sponge-Calathium-calcimicrobial) reefs and metazoan-dominated (lithistid sponge-Calathium) reefs. These reef types represent different communities controlled by varying environmental settings. Stromatolites tended to develop in the shallow subtidal zone, whereas unlaminated calcimicrobial mounds and metazoan-dominated reefs thrived at greater depths. This is the first report on metazoan-dominated reefs at the platform margin of the Hunghuayuan Formation. © 2014 © 2014 Taylor & Francis.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.earlyo
Keywords: calathid; Early Ordovician; metazoan-dominated reefs; microbialite; Yangtze Platform margin

Early Silurian positive δ13C excursions and their relationships to glaciations, sea-level changes and extinction events: Discussion - Cramer, Bradley D.; Munnecke, Axel (Geological Journal, 2008)
Keywords: Silurian; d13C excursions; glaciation; sea-level changes; extinction events

Early Silurian (Telychian) bryozoan reefs in the epeiric sea of South China: Are heterotroph metazoan buildups promoted by internal waves? - Munnecke, Axel; Li, Qijian; Ernst, Andrej; Yu, Shenyang; Li, Yue (Sedimentary Geology, 2018)

Echinoderm Research 2010. 7th European Conference on Echinoderms, Göttingen, October 2-9, 2010. Abstract Volume and Field Guide to Excursions - Reich, Mike; Reitner, Joachim; Roden, Vanessa; Thuy, Ben (Universitätsdrucke Göttingen, 2010)

Ecological change during the early Emsian (Devonian) in the Tafilalt (Morocco), the origin of the Ammonoidea, and the first African pyrgocystid edrioasteroids, machaerids and phyllocarids - Klug, Christian; Korn, Dieter; Rücklin, Martin; Schemm-Gregory, Mena; de Baets, Kenneth; Mapes, Royal H.; Kröger, Björn (Palaeontographica Abteilung A-Palaozoologie-Stratigraphie, 2008)
The majority of the macrofossils from the two faunas are systematically described; the following new taxa are introduced: the bivalve Eonuculoma babini n. gen. et sp., the orthoceratids Chebbioceras erfoudense n. gen. et sp., Infundibuloceras brevimira n. gen. et sp. and Plagiostomoceras hassichebbiense n. sp., the bactritoid Cyrtobactrites scheffoldi n. sp., the ammonoid Metabactrites ernsti n. sp., and the machaerid Aulakolepos rugatus n. sp., the phyllocarids Nahecaris jannae n. sp.and N. malvinae n. sp. as well as the edrioasteroid Rhenopyrgus flos n. sp. The latter taxa represent the first records of the families Pyrgocystidae, Lepidocoleidae and of phyllocarid carapaces from Africa.
Keywords: Emsian; cephalopoda; machaeridia; phyllocarida; edrioasteroidea; Morocco

Ecological, taxonomic, and taphonomic components of the post-Paleozoic increase in sample-level species diversity of marine benthos - Kowalewski, Michal; Kießling, Wolfgang; Aberhan, Martin; Fürsich, Franz; Scarponi, Daniele; Barbour, Susan L.; Hoffmeister, Alan P. (Paleobiology, 2006)
Biological veracity of the sharp diversity increase observed in many analyses of the post-Paleozoic marine fossil record has been debated vigorously in recent years. To assess this question for sample-level ("alpha") diversity, we used bulk samples of shelly invertebrates, representing three major fossil groups (brachiopods, bivalves, and gastropods), to compare the Jurassic and late Cenozoic sample-level diversity of marine benthos. After restricting the data set to single-bed, whole-fauna, bulk samples (n ≥ 30 specimens) from comparable open marine siliciclastic facies, we were able to retain 427 samples (255 Jurassic and 172 late Cenozoic), with most of those samples originating from our own empirical work. Regardless of the diversity metric applied, the initial results suggest that standardized sample-level species (or genus) diversity, driven by evenness and/or richness of the most common taxa, increased between the Jurassic and late Cenozoic by at least a factor of 1.6. When the data are partitioned into the three dominant higher taxa, it becomes clear that (1) the bivalves, which dominated the samples for both time intervals, increased in sample-level diversity between the Jurassic and the late Cenozoic by a much smaller factor than the total fauna; (2) the removal of brachiopods, which were a noticeable component of the Jurassic samples, did not significantly affect standardized sample-level diversity estimates; and (3) the gastropods, which were rare in the Jurassic but common in many late Cenozoic samples, contributed notably to the increase in sample-level diversity observed between the two time intervals. Parallel to these changes, the samples revealed secular trends in ecological structure, including Jurassic to late Cenozoic increases in proportion of (1) infauna, (2) mobile forms, and (3) non-suspension-feeding organisms. These trends mostly persist when data are restricted to bivalves. Supplementary analyses indicate that these patterns cannot be attributed to sampling heterogeneities in paleolatitudinal range, lithology, or paleoenvironment of deposition. Likewise, when data are restricted to samples dominated by species with originally aragonitic shells, the observed temporal changes persist at a comparable magnitude, suggesting that the pervasive loss of aragonite in the older fossil record is unlikely to have been the primary cause of the observed patterns. The comparable ratio of identified to unidentified species and genera, observed when comparing the Jurassic and late Cenozoic samples, indicates that the relatively poorer (mold/cast) preservation of Jurassic aragonite species also is unlikely to have been responsible for the observed patterns. However, the diagenesis-related taphonomic and methodological artifacts cannot be ruled out as an at least partial contributor to the observed post-Paleozoic changes in diversity, taxonomic composition, and ecology (the outcomes of the three tests of the diagenetic bias available to us are incongruent). The study demonstrates that the post-Paleozoic trends in the sample-level diversity, ecology, and taxonomic structure of common taxa can be replicated across multiple studies. However, the diversity increase estimated here is much less prominent than suggested by many previous analyses. The results also narrow the list of causative explanations down to two testable hypotheses. The first is diagenetic bias - a spurious trend driven by either (a) increasing taphonomic loss of small specimens in the older fossil record or (b) a shift in sampling procedures between predominantly lithified rocks of the Mesozoic and predominately unlithified, and therefore sievable, sediments of the late Cenozoic. The second hypothesis is genuine biological changes - macroevolutionary trends in the structure of marine benthic associations through time, consistent with predictions of several related models such as evolutionary escalation, increased ecospace utilization, and the Mesozoic marine revolution. Future studies should focus on testing these two rival models, a key remaining challenge for identifying the primary causative mechanism for the long-term changes in sample-level diversity, ecology, and taxonomic structure observed in the Phanerozoic marine fossil record. © 2006 The Paleontological Society. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2006.nat.dgeo.IGM.LP.ecolog
Keywords: taxonomy; ecology; diversity; post-Paleozoic; marine benthos; sample-level

Editorial: Crustose coralline red algae frameworks and rhodoliths: Past and present - Rebelo, Ana Cristina; Teichert, Sebastian; Bracchi, Valentina A.; Rasser, Michael W.; Basso, Daniela (Frontiers in Earth Science, 2022)

Effect of varying CA2/CA ratios in Calcium-Aluminate-Calcite-mixtures analysed by combined QXRD, µ-CT and flexural-strength testing - Goergens, Julian; Belli, Renan; Schulbert, Christian; Götz-Neunhoeffer, Friedlinde (4th International Conference on the Chemistry of Construction Materials - ICCCM 2022, 2022)
Common calcium aluminate cements (CAC) may vary in their CA2 to CA ratio. While CA is the main phase of most CACs and is responsible for the initial strength, the CA2 phase has also received more attention in the last few decades. The reason for this is the higher Al-content of CA2 and thus the ability to produce more AH3 than CA as well as a higher thermic stability. In Calciumsulfoaluminate-cements (CSA), AH3 is considered to promote strength [1]. A gradual increase in the CA2 content and thus a change in the CA2/CA ratio in the clinker in CAC can be achieved by mixing of two cements, one CA-rich and one CA2-rich CAC. According to this approach, two industrial CACs were mixed in this work and six different CA2/CA-ratios were analysed with the following methods: QXRD after 1, 7 and 28 days of hydration demonstrates the quantitative progress of hydration, the clinker phase hydration degree as well as changes in AH3 and other hydrate phase quantities over time. Micro-computer tomography (µ-CT) of selected mixtures after 28 days enables a three-dimensional, non-destructive view of the inside of the sample, porosity and density heterogenities. The newly introduced B3B-method [2] for testing of the flexural strength in combination with the data evaluation according to Weibull (all mixes after 7 and 28 days) allows an interpretation of the mechanical properties. The combination of these three methodologies reveals that the mechanical properties deteriorate significantly from a CA2/CA ratio of 70:30 on to higher ones. The reasons for this are the macro-porosity, insufficient amounts of CA in the non-hydrated residue and differences in viscosity. [1] Chang J, Zhang Y, Shang X, Zhao X, Yu X. Effects of amorphous AH3 phase on mechanical properties and hydration process of C4A3š-CšH2-CH-H2O system. Construction and Building Materials 2017:133:314–322. [2] Börger A, Supancic P, Danzer R. The ball on three balls test for strength testing of brittle discs: stress distribution in the disc. J Eur Ceram Soc. 2002;22:1425-36. <

Effects of diagenesis on the astrochronological approach of defining stratigraphic boundaries in calcareous rhythmites: The Tortonian GSSP - Westphal, Hildegard; Munnecke, Axel; Brandano, Marco (Lethaia, 2008)
Since the establishment of astrochronology, calcareous rhythmites are frequently used as the basis of high-resolution chronostratigraphy. In particular for the Neogene, calcareous rhythmites serve as stratotypes and for absolute dating of stratigraphic boundaries (Global Stratotype Sections and Points -GSSPs). However, the exact mechanisms responsible for the formation of the rhythmic intercalation of lithologies in such successions are complex and not easily reconstructed. To a large extent this is the effect of diagenetic modifications of the original sediment. Here, two examples of Neogene calcareous rhythmites are studied; the Monte dei Corvi section and the Monte Gibliscemi section. The first is the GSSP location of the Serravallian-Tortonian boundary, whereas the second is an auxiliary stratotype for the same boundary. During the past years, astrochronological approaches were applied to these successions to considerably increase time resolution compared to the elaborated biostratigraphic database. The present study focuses on micropetrographic, trace element and clay mineralogical methods in order to gain a better understanding of the genesis of the rhythmites. In the Monte Gibliscemi section, sediment parameters that are robust against diagenetic change clearly reflect primary differences, i.e. cyclical environmental changes. In contrast, no clear primary signal is determined for the Monte dei Corvi section on a couplet scale, leaving the origin of the rhythm ambiguous. This impedes the interpretation of the latter and the comparability between the two successions, and also compromises any bed-by-bed correlation between the two. The unclear origin of the rhythmites of Monte dei Corvi introduces uncertainty into the applicability of astrochronology to this succession. © Journal compilation © 2008 The Lethaia Foundatio
Keywords: Astrochronology; Calcareous rhythmites; rhythmites; GSSP; diagenesis; stratigraphic boundaries; Tortonian

Ein "Dropstone" im Belemnitenschlachtfeld von Mistelgau - Schulbert, Christian (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dgeo.IGM.LP.eindro

Elemental systematics of the calcitic skeleton of Corallium rubrum and implications for the Mg/Ca temperature proxy - Chaabane, S.; López Correa, Matthias; Ziveri, P.; Trotter, J.; Kallel, N.; Douville, E.; McCulloch, M.; Taviani, M.; Linares, C.; Montagna, P. (Chemical Geology, 2019)
The high-Mg calcite skeleton of Corallium rubrum was analyzed from living colonies collected from a wide range of depths (15 m to 607 m) and environmental settings in the Mediterranean Sea. An overarching goal was to better understand the calcification process and incorporation of elements into the slow-growing skeleton of both shallow and deep-water specimens, and more specifically, to clarify the veracity of geochemical proxies for reconstructing seawater temperatures. The coral internal structure including growth bands were determined by scanning electronic microscopy (SEM) and petrographic techniques. Trace elements (Li, B, Mg, Sr and Ba) compositions of the coral skeleton were obtained by solution and laser ablation inductively coupled plasma mass spectrometry (ICP-MS). Results show that the skeleton of the deep-water specimens has an internal microstructure similar to shallow-water colonies, with the medullar and the annular zones clearly distinguishable in both shallow and deep-water specimens. In general, the bands of the deep-water samples are very thin and equidistant compared to the irregular banding of the shallow-water specimens. Banding differences relate to the contrasting environmental dynamics, with the shallow-water specimens being exposed to large seasonal fluctuations compared to the relative stable conditions of those inhabiting bathyal depths. The inner medullar and outer annular portions differ in their trace element concentrations: Mg/Ca, Sr/Ca and Li/Ca ratios are higher in the medullar zone and seem to be influenced by growth kinetics, whereas B/Ca and Ba/Ca are similar in both zones and hence unaffected by growth rate. The variability of elemental ratios is lower in the deep-water specimens. Growth bands are highly correlated to Mg/Ca, Sr/Ca and Li/Ca, suggesting common mechanism(s) controlling the incorporation of these elements into the coral skeleton. Mg/Ca ratios were especially depleted in the dark bands. Although the mean Mg/Ca of each specimen is positively correlated to ambient seawater temperature, the intra-annual variations and amplitudes differ and do not correlate to the band widths. These findings suggest that intra- and inter-annual variations of Mg/Ca cannot be used to reconstruct a continuous time-series of long-term seasonal temperature records. However, the mean Mg/Ca composition can serve as a valuable proxy to estimate mean palaeoseawater temperature at a given site within the Mediterranean.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Calcite skeleton; Corallium rubrum; Growth bands; Mediterranean Sea; Red coral; Temperature proxy; Trace elements

Elevation-driven ecological isolation promotes diversification on Mediterranean islands - Steinbauer, Manuel; Irl, Severin; Beierkuhnlein, Carl (Acta Oecologica-International Journal of Ecology, 2013)
The percentage of single island neo-endemic species (an indicator for evolutionary diversification) was found to be independent of geographic distance to the continent in the case of the Aegean archipelago. It was concluded that speciation is independent of geographic isolation, while evolutionary processes are rather enhanced by habitat heterogeneity. An island's maximum elevation was used as an indicator for habitat heterogeneity. In contrast, we argue that habitat heterogeneity (= habitat diversity, i.e. the richness in different habitats) may be positively related to biotic richness, but a positive effect on speciation is yet to be proven. For any other type of heterogeneity, we propose a precise wording, especially when assessing its effect on speciation processes. Alternatively, we propose that elevation-driven ecological isolation causes the pattern of endemic species on high-elevation islands. Environmental filtering along an elevational gradient differentiates ecosystems, leading to an increase of isolation with elevation. The reason is that comparable ecosystems are much farther apart than is the case for lowland ecosystems. In addition, ecosystems on neighboring islands or on the continent that may be source regions for colonizing species are small in area in high elevations in comparison with low elevation ecosystems. Consequently, an increased speciation rate resulting in a larger percentage of single island endemic species can be expected for higher elevations on islands and high mountains. Support for this elevation-driven ecological isolation hypothesis comes from other islands in the Mediterranean region (e.g. Crete and Corsica), where an increase of the percentage of endemic species with elevation has been observed. Thus, the assessment of (genetic-) isolation should incorporate the distance to similar habitats instead of simple land-to-land connections.
Keywords: Crete; Environmental filter; Habitat diversity; Habitat heterogeneity; Island biogeography; Neo-endemic; PSIE; Single island endemic species; Speciation

Ellesmerian and Eurekan fault tectonics at the northern margin of Ellesmere Island (Canadian High Arctic) - Piepjohn, Karsten; von Gosen, Werner; Laeufer, Andreas; Mcclelland, William C.; Estrada, Solveig (Zeitschrift der Deutschen Gesellschaft für Geowissenschaften, 2013)
Keywords: Ellesmere island; Eurekan deformation; Ellesmerian orogeny; Pearya terrane; North margin of north america; Plate tectonics

Emergence patterns of locally novel plant communities driven by past climate change and modern anthropogenic impacts - Staples, Timothy L.; Kießling, Wolfgang; Pandolfi, John M. (Ecology Letters, 2022)
Anthropogenic disturbance and climate change can result in dramatic increases in the emergence of new, ecologically novel, communities of organisms. We used a standardised framework to detect local novel communities in 2135 pollen time series over the last 25,000 years. Eight thousand years of post-glacial warming coincided with a threefold increase in local novel community emergence relative to glacial estimates. Novel communities emerged predominantly at high latitudes and were linked to global and local temperature change across multi-millennial time intervals. In contrast, emergence of locally novel communities in the last 200 years, although already on par with glacial retreat estimates, occurred at midlatitudes and near high human population densities. Anthropogenic warming does not appear to be strongly associated with modern local novel communities, but may drive widespread emergence in the future, with legacy effects for millennia after warming abates.
CRIS-Team Scopus Importer:2022-05-20
Keywords: anthropogenic warming; dispersal; fossil pollen assemblage; glacial retreat; human impacts; novel ecosystems; post-glacial warming; quaternary; temperature change

Emsian Ammonoidea and the age of the Hunsruck Slate (Rhenish Mountains, Western Germany) - de Baets, Kenneth; Klug, Christian; Korn, Dieter; Bartels, Christoph; Poschmann, Markus (Palaeontographica Abteilung A-Palaozoologie-Stratigraphie, 2013)
The ammonoids from the well-studied German Fossillagerstatte of the Hunsruck Slate have the reputation of being the oldest known representatives of this cephalopod group. This material is of great interest not only because of the global scarcity of the earliest ammonoids, but also because it includes the first record of stratigraphically-controlled specimens, which could be assigned to the middle Kaub Formation in the Bundenbach/Gemunden area. Accordingly, some of the Hunsruck Slate ammonoids are indeed the stratigraphically oldest ammonoids because they are associated with the index dacryoconarid Nowakia praecursor and thus derive from the Nowakia zlichovensis Biozone of the early Emsian (Zlichovian), while younger dacryoconarids and other ammonoid samples (Mimagoniatites fecundus, Mimosphinctes tripartitus) indicate the Nowakia barrandei to N elegans biozones. In spite of this special importance, these Early Devonian cephalopods have never been revised comprehensively. Our study includes more than 300 Hunsruck Slate specimens from both public and private collections. For the first time, ammonoids from the Altlay Hunsriick Slate in the Northern Hunsruck/Mosel region are reported, while all the materials from older collections derive from the middle Kaub Formation of the Central Hunsriick Basin (central Hunsriick, Taunus). These early ammonoids thus prove to be a valuable source of information for biostratigraphic correlation within the Hunsriick Slate and with early Emsian occurrences in other regions. Based on conch characters (geometry, ornament, suture lines) and ontogenetic traits, we describe the species Metabactrites fuchsi n. sp., Ivoites hunsrueckianus (ERBEN 1960), Ivoites schindewolfi n. sp., ?Ivoites sp., Ivoites opitzi n. sp., Anetoceras mittmeyeri n. sp., Erbenoceras advolvens (ERBEN 1960), Erbenoceras solitarium (BARRANDE 1865), Chebbites sp., Mimosphinctes primigenitus (ERBEN 1965), Mimosphinctes tripartitus EICHENBERG, 1931, Gyroceratites heinricherbeni n. sp., ?Teicherticeras sp., and Mimagoniatites fecundus (BARRANDE 1865). Supposedly endemic species of the Hunsriick Slate such as "Anetoceras recticostatum ERBEN, 1962" and "Mimagoniatites falcistria (FucHs 1915)" are here synonymized with the widely distributed species Erbenoceras solitarium and Mimagoniatites fecundus, both known to occur also outside Europe. Furthermore, we studied their taphonomy and assigned them to seven groups of preservation. The results of this taphonomic study corroborate previous interpretations of the depositional environment and diagenesis. We also discuss the evolution of the shell in the earliest ammonoids and their closest relatives as well as structures ("Opitzian pits") possibly caused by parasitic infestations of these early Emsian ammonoids.
Keywords: Ammonoidea; Hunsriick Slate; Early Devonian; systematics; biostratigraphy; taphonomy; macroevolution; paleoecology; parasite; pearl

Endemism increases species' climate change risk in areas of global biodiversity importance - Manes, Stella; Costello, Mark J.; Beckett, Heath; Debnath, Anindita; Devenish-Nelson, Eleanor; Grey, Kerry Anne; Jenkins, Rhosanna; Khan, Tasnuva Ferdous Ming; Kießling, Wolfgang; Krause, Cristina; Maharaj, Shobha S.; Midgley, Guy F.; et al. (Biological Conservation, 2021)
Climate change affects life at global scales and across systems but is of special concern in areas that are disproportionately rich in biological diversity and uniqueness. Using a meta-analytical approach, we analysed >8000 risk projections of the projected impact of climate change on 273 areas of exceptional biodiversity, including terrestrial and marine environments. We found that climate change is projected to negatively impact all assessed areas, but endemic species are consistently more adversely impacted. Terrestrial endemics are projected to be 2.7 and 10 times more impacted than non-endemic natives and introduced species respectively, the latter being overall unaffected by climate change. We defined a high risk of extinction as a loss of >80% due to climate change alone. Of endemic species, 34% and 46% in terrestrial and marine ecosystems, and 100% and 84% of island and mountain species were projected to face high extinction risk respectively. A doubling of warming is projected to disproportionately increase extinction risks for endemic and non-endemic native species. Thus, reducing extinction risks requires both adaptation responses in biodiversity rich-spots and enhanced climate change mitigation.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Biodiversity hotspots; Extinction risk; Global-200 ecoregions; Introduced species

Endolithic bioerosion in cephalopods from the upper Carboniferous Buckhorn Asphalt Quarry Lagerstätte (Oklahoma, USA) - Seuß, Barbara; Nützel, Alexander (9th International Bioerosion Workshop, 2017)
Deposits of the Pennsylvanian (upper Carboniferous) Buckhorn Asphalt Quarry in southern Oklahoma, USA, are of mixed siliciclastic-carbonatic composition; however,crucial is the high content of hydrocarbons, that intruded the sediments during or onlyshortly after deposition. These hydrocarbons impregnated not only the deposits but more important, the fossils within. The result of this intense soaking with hydrocarbons, that altered into asphalt afterwards, was an upper Carboniferous (Pennsylvanian) Lagerstätte of outstanding quality; e.g., preservation of delicate shell ornamentation and juvenile shells, preservation of color patterns on naticopsids, as well as original shell microstructure and mineralogy in different taxa (Bandel et al. 2002; Seuss et al. 2009, 2012a, b; Ernst et al. 2016). In addition, the fauna is high diverse with approximately 150 different taxa reported so far (Seuss et al. 2009). Many shells show intense bioerosion on their surface and borings are also well visible in thin sections. In an earlier study on the Buckhorn bioeroders Wisshak et al. (2008) studied and interpreted the ichnocenosis present in Buckhorn fossils. The study was mainly based on gastropod and bivalve shells and yielded an assemblage of 18 known and one new ichnospecies. The ichnocoenosis was the most diverse record of ichnotaxa of that age and contains 13 first, including nine oldest, appearances for the Carboniferous (Wisshak et al. 2008, Table 2) and it represents the shallow euphotic zone II–III following the ichnobathymetric scheme of Glaub (1994) and Vogel et al. (1995). Because the first study focussed on shallow marine, benthic organisms (i.e., gastropods, bivalves) a second study was performed recently to investigate shells ofnektonic taxa that are more prone to transportation after death of the animal. These are, for the study, orthoconic and coiled nautiloids and ammonoids (goniatites). The shells derive from a coquina that represents the deepest section of a cyclotheme that comprises the Buckhorn Asphalt Quarry’s deposits (compare Seuss et al. 2009, Fig. 6). In total 32 remains of orthoconic and 28 remains of the shells of coiled nautiloids and ammonoids are included in this analysis. Synthetic resin casts were prepared and preliminary results prove the presence of 25-30 ichnotaxa. Compared to studies on recent Nautilus (Seuss et al. 2015a, b, 2016) diversity is similar; however, the taxa differ distinctly. In the Buckhorn cephalopods representatives of the cyanobacteria are most diverse and most abundant, in orthoconic specimens, are the chlorophyte trace Ichnoreticulina elegans and a new ichnospecies of Scolecia (produced by cyanobacterium?) while in coiled cephalopods Flagrichnus profundus (produced by the fungus Schizochytrium sp.) and for ms of ‘very thin’ / ‘super thin’ traces dominate the association (rhodophyte / unknown heterotroph). A minimum of two ichnotaxa is reported for the first time; this number might be extended by so far unidentified traces of presumable foraminiferan origin. Despite the high diversity of traces, no ichnocoenosis was identified that would help in the identification of the relative bathymetry of the deposits and their fossil remain

End-Wenlock terminal Mulde carbon isotope excursion in Gotland, Sweden: Integration of stratigraphy and taphonomy for correlations across restricted facies and specialized faunas - Jarochowska, Emilia; Bremer, Oskar; Pröpster, Stephanie; Heidlas, Daniel; Vandenbroucke, Thijs R.A.; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
The decline of the upper peak of the Homerian Mulde carbon isotope excursion (CIE) is used in low- to mid-paleolatitudes as a marker for the Wenlock/Ludlow boundary, which is otherwise difficult to constrain in carbonate successions. In the Midland Platform (England) the CIE ends just below the boundary or ranges through it, whereas in Baltic sections it has been placed substantially below the inferred base of the Ludlow Stage. Difficulties in correlating the Baltic sections are caused by widespread development of lagoons and sabkhas with specialized conodont and vertebrate faunas. We describe here a lagoonal section from Gothemshammar, eastern Gotland (Sweden), spanning the entire upper peak of the Mulde CIE. Based on integrated conodont, δC and sequence stratigraphy, a hardground present at the lowering limb of the CIE is correlated with a sequence boundary present across the Baltic Basin, in the Midland Platform, and the southern shelf of Laurentia. This sequence boundary corresponds to a global eustatic regression and can serve as a correlative horizon in restricted facies with depauperate or specialized fauna. The Wenlock-Ludlow boundary is placed in the transgressive strata overlying this boundary. Species richness and abundance of thelodonts, anaspids, and osteostracans at Gothemshammar represent one of the first diversity peaks of vertebrates in the Silurian. Associated conodonts are characteristic for late Wenlock marginal-marine environments and distinguished by large, robust elements. We quantitatively assess the conodont assemblages to evaluate to which degree the overrepresentation of large elements in these facies is produced by taphonomic processes. The taphonomic alteration differs between species and facies, but is lowest for the shallow-water specialist Ctenognathodus murchisoni. Regardless, the use of this species as an index taxon is discouraged based on its strong facies affinity. Instead, the integrated approach proposed here indicates that the Wenlock/Ludlow boundary is situated lower in the Baltic sections than previously identifie
Keywords: Conodont; Deformation; Fish; Palynomorph; Taphonomy; Vertebrate

Enforced Symmetry: The Necessity of Symmetric Waxing and Waning - Hohmann, Niklas; Jarochowska, Emilia (PeerJ, 2019)
A fundamental question in ecology is how the success of a taxon changes through time and what drives this change. This question is commonly approached using trajectories averaged over a group of taxa. Using results from probability theory, we show that averaged trajectories will be more symmetric as the number of averaged trajectories increases, even if none of the original trajectories they were derived from is symmetric. This effect is not only based on averaging, but also on the introduction of noise and the incorporation of a priori known origination and extinction times. This implies that averaged trajectories are not suitable for deriving information about the processes driving the success of taxa. In particular, symmetric waxing and waning, which is commonly observed and interpreted to be linked to a number of different paleobiological processes, does not allow drawing any conclusions about the nature of the underlying process. We present a nonparametric test that avoids the problems introduced by averaging and allows to test hypotheses regarding the success of taxa through time.<br
Keywords: Symmetry; Ecology; Limit theorems; Range size; Occupancy; Diversity; Extinction risk; Nonparametric statistics; Ordination; Averaging; Stochastic process

Enigmatic encrusting fossils from the Upper Devonian of Russia: probable Rothpletzella microproblematica preserved in three dimensions - Zatoń, Michał; Jarochowska, Emilia (Historical Biology, 2018)
Intriguing microfossils encrusting certain Upper Devonian brachiopod shells from the Central Devonian Field, Russia, are reported for the first time. The fossils are pyritized, have fan-shaped morphologies and are formed by tightly-packed branches which divide dichotomously at different points in their development. The organisms preserved grew horizontally on shelly substrates. Comparisons with similar fossils known from the literature indicate that they do not represent any animal taxon commonly encrusting hard substrates. Instead, the morphology, organization and growth mode of these fossils are most similar to microfossils known under the name Rothpletzella, which so far have only been known from thin sections. Rothpletzella is a problematicum for which algal affinities have been proposed. The preserved branches of the fossils described here are too large for cyanobacterial cells. Their large size suggests their placement, along with other described Rothpletzella fossils, within the green algae order Bryopsidales. It is suggested that originally, these organisms possessed thalli encased within a thin, delicate calcified sheath. After burial the thalli underwent pyritization via sulphate reduction mediated by bacterial activity within low pH, dysoxic microenvironment, and their sheath dissolved. As three-dimensionally preserved, these algae provide a new, previously unrecognized, component within the Devonian encrusting communitie
Keywords: Epibionts; Frasnian; algae; pyritization; palaeoecology

Entwicklung der marinen Biodiversität. - Kießling, Wolfgang (Humboldt-Spektrum, 2007)
Keywords: Biodiversität; Evolution; marine Organismen

Environmental and evolutionary drivers of diversity patterns in the tea family (Theaceae s.s.) across China - Rao, Mide; Steinbauer, Manuel; Xiang, Xiaoguo; Mi, Xiangcheng; Zhang, Jingtun; Svenning, Jens-Christian (Ecology and Evolution, 2018)
Subtropical forest is recognized as an important global vegetation type with high levels of plant species richness. However, the mechanisms underlying its diversity are still poorly understood. Notably, species richness may be controlled by contemporary environment, but also by evolutionary dynamics (e.g., time-for-speciation or evolutionary rates), with the latter predicting relations between species richness and phylogenetic assemblage structure. Here, we assess the relative roles of these factors in shaping species diversity patterns at several taxonomic scales in a major subtropical plant group, the tea family (Theaceae s.s.) across China (145 species). To this end, we assessed the inter-relations between species richness, phylogenetic assemblage structure (net related index) and key environmental variables (minimum temperature of the coldest month, mean annual precipitation, soil pH), using generalized linear models and spatial linear models. We found that species richness is significantly related to environmental variables, especially decreasing with soil pH both across the whole family and within the tribe Theeae. Family-level species richness is unrelated to phylogenetic structure, providing no support for time-for-speciation or evolutionary rate effects. However, within the tribe Theeae, species richness was related to phylogenetic structure with an U-shaped relationship, a more complex relation than time-for-speciation or evolutionary rate hypothesis would predict. Overall, these results suggest that Theaceae species richness patterns within China are primarily driven by shallow-time environmentally-driven dynamics, albeit the nested patterns of its subgroups (notably Theeae) exhibit evolutionarily linked patterns. Our findings show that environmental and evolutionary processes interact in complex ways to shape species richness patterns within the subtropical forest biome.<br

Environmental determinants of marine benthic biodiversity dynamics through Triassic-Jurassic times - Kießling, Wolfgang; Aberhan, Martin (Paleobiology, 2007)
Ecology is thought to be of crucial importance in determining taxonomic turnover at geological time scales, yet general links between ecology and biodiversity dynamics are still poorly explored in deep time. Here we analyze the relationships between the environmental affinities of Triassic-Jurassic marine benthic genera and their biodiversity dynamics, using a large, taxonomically vetted data set of Triassic-Jurassic taxonomic occurrences. On the basis of binomial probabilities of proportional occurrence counts, we identify environmental affinities of genera for (1) carbonate versus siliciclastic substrates, (2) onshore versus offshore depositional environments, (3) reefs versus level-bottom communities, and (4) tropical versus non-tropical latitudinal zones. Genera with affinities for carbonates, onshore environments, and reefs have higher turnover rates than genera with affinities for siliciclastic, offshore, and level-bottom settings. Differences in faunal turnover are largely due to differences in origination rates. Whereas previous studies have highlighted the direct influence of physical and biological factors in exploring environmental controls on evolutionary rates, our analyses show that the patterns can largely be explained by the partitioning of higher taxa with different evolutionary tempos among environments. The relatively slowly evolving bivalves are concentrated in siliciclastic rocks and in level-bottom communities. Furthermore, separate analyses on bivalves did not produce significant differences in turnover rates between environmental settings. The relationship between biodiversity dynamics and environments in our data set is thus governed by the partitioning of higher taxa within environmental categories and not directly due to greater chances of origination in particular settings. As this partitioning probably has ecological reasons rather than being a simple sampling artifact, we propose an indirect environmental control on evolutionary rates. Affinities for latitudinal zones are not linked to systematically different turnover rates, possibly because of paleoclimatic fluctuations and latitudinal migrations of taxa. However, the strong extinction spike of tropical genera in the Rhaetian calls for an important paleoclimatic component in the end-Triassic mass extinction. © 2007 The Paleontological Society. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LP.enviro

Environmentally controlled succession in a late Pleistocene coral reef (Sinai, Egypt) - Mewis, H.; Kießling, Wolfgang (Coral Reefs, 2013)
The concept of ecological succession has been frequently applied in the study of ancient reefs. Whereas Paleozoic and Mesozoic reefs are commonly thought to reveal an autogenic primary-climax zonation, patterns in Neogene and Quaternary reefs are much more diverse. Here, we describe a well-preserved late Pleistocene coral reef from Dahab on Sinai Peninsula (Egypt), which shows a distinct zonation that resembles an ecological succession. In contrast to classical examples of ecological successions, species composition, paleoenvironmental conditions, and coral biodiversity of the Dahab reef indicate an allogenic, sea-level controlled community change, from marginal marine to reef slope and back reef. A review of the literature confirms that autogenic, short-term successions are virtually absent in Quaternary reefs. We predict that long generation times of corals make it unlikely that classical autogenic successions develop in reefs at all, unless environmental conditions are unusually stable. © 2012 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.enviro_1
Keywords: Community ecology; Coral reef; Diversity; Ecological succession; Pleistocene; Red Sea

Equatorial decline of reef corals during the last Pleistocene interglacial - Kießling, Wolfgang; Simpson, Carl; Beck, Brian; Mewis, Heike; Pandolfi, John M. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
The Last Interglacial (LIG; ca. 125,000 y ago) resulted from rapid global warming and reached global mean temperatures exceeding those of today. The LIG thus offers the opportunity to study how life may respond to future global warming. Using global occurrence databases and applying sampling- standardization, we compared reef coral diversity and distributions between the LIG and modern. Latitudinal diversity patterns are characterized by a tropical plateau today but were characterized by a pronounced equatorial trough during the LIG. This trough is governed by substantial range shifts away from the equator. Range shifts affected both leading and trailing edges of species range limits and were much more pronounced in the Northern Hemisphere than south of the equator. We argue that interglacial warming was responsible for the loss of equatorial diversity. Hemispheric differences in insolation during the LIG may explain the asymmetrical response. The equatorial retractions are surprisingly strong given that only small temperature changes have been reported in the LIG tropics. Our results suggest that the poleward range expansions of reef corals occurring with intensified global warming today may soon be followed by equatorial range retractions.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.equato
Keywords: Biodiversity; Climate change; Paleobiology

Ethics, law, and politics in palaeontological research: The case of Myanmar amber - Dunne, Emma; Raja, Nussaïbah Begum; Stewens, Paul P.; Zin-Maung-Maung-Thein,; Zaw, Khin (Communications Biology, 2022)
Fossil material in amber from Myanmar can provide important insights into mid-Cretaceous forest ecosystems. However, Myanmar amber has been receiving increased international attention due to reported links between amber mining and the ongoing humanitarian crisis in northern Myanmar, as well as the legal issues associated with its exportation. Here, we conduct a bibliometric analysis of Myanmar amber publications (1990–2021) and demonstrate how research interest in Myanmar amber is explicitly linked to major political, legal, and economic changes. An analysis of the authorship networks for publications on amber inclusions reveals how current research practices have excluded Myanmar researchers from the field. In addition, the international trade of Myanmar amber with fossil inclusions falls into a legal ‘grey-zone’ which continues to be exploited. This case study vividly demonstrates that systemic changes, alongside an increased awareness of inequitable research practices amongst the broader scientific and allied communities, are urgently needed to curb illegal practices in palaeontology.
CRIS-Team Scopus Importer:2022-10-14

Evidence for Palaeozoic orthoconic cephalopods with bimineralic shells - de Baets, Kenneth; Munnecke, Axel (Palaeontology, 2018)
Based on the aragonite composition of extant and exceptionally preserved fossil cephalopods going back to the early Palaeozoic, it is commonly assumed that all externally shelled cephalopods had an aragonitic shell wall. We demonstrate herein that at least two taxa of Siluro-Devonian orthoconic nautiloids (Dawsonoceras, Spyroceras) had an original bimineralic shell, which developed convergently with gastropods and bivalve

Evidence of parallel evolution in the dental elements of Sweetognathus conodonts - Petryshen, W.; Henderson, C. M.; de Baets, Kenneth; Jarochowska, Emilia (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2020)
The repeated emergence of similar morphologies in the dental elements of Permian Sweetognathus conodonts has been a hypothesized example of parallel evolution. To test if morphological parallelisms occur between isolated Sweetognathus lineages, this study uses two-dimensional-based geometric morphometrics combined with a revised and expanded phylogeny of Permian Sweetognathus conodonts to quantify dental element trait distributions and compare the phenotypic trajectories between lineages. A hierarchical clustering method was used to identify recurrent species pairs based on principal component scores describing their morphological variation, with the further incorporation of widely used ecological metrics such as limiting similarity and morphological overlap. Our research implies that a major contributor to conodont diversity in Palaeozoic marine trophic networks is the emergence of recurrent parallel morphologies via disruptive and directional selection. This study illustrates the mechanisms through which conodonts achieved their status as hyper-diverse predators and scavengers, contributing substantially to the complexity of Palaeozoic marine communities.
CRIS-Team Scopus Importer:2020-11-27
Keywords: conodont trophic networks; parallel evolution; Sweetognathus

Evolutionary diversification of reef corals: a comparison of the molecular and fossil records - Simpson, Carl; Kießling, Wolfgang; Mewis, Heike; Baron-Szabo, Rosemarie; Müller, Johannes (Evolution, 2011)
Understanding historical patterns of diversity dynamics is of paramount importance for many evolutionary questions. The fossil record has long been the only source of information on patterns of diversification, but the molecular record, derived from time-calibrated phylogenies, is becoming an important additional resource. Both fossil and molecular approaches have shortcomings and biases. These have been well studied for fossil data but much less so for molecular data and empirical comparisons between approaches are lacking. Here, we compare the patterns of diversification derived from fossil and molecular data in scleractinian reef coral species. We also assess the robustness of molecular diversification rates to poor taxon sampling. We find that the temporal pattern of molecular diversification rates is robust to incomplete sampling when rates are calculated per interval. The major obstacle of molecular methods is that rate estimates are distorted because diversification rates can never be negative, whereas the fossil record suffers from incomplete preservation and inconsistent taxonomy. Nevertheless, the molecular pattern of diversification is comparable to the pattern we observe in the fossil record, with the timing of major diversification pulses coinciding in each dataset. For example, both agree that the end-Triassic coral extinction was a catastrophic bottleneck in scleractinian evolution. © 2011 The Author(s). Evolution© 2011 The Society for the Study of Evolution..
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.evolut
Keywords: Diversification; Extinction; Fossils; Molecular phylogenies; Reef corals; Speciation

Evolutionary History of Cephalopod Pathologies Linked with Parasitism - de Baets, Kenneth; Hoffmann, René; Mironenko, Aleksandr (The Evolution and Fossil Record of Parasitism: Coevolution and Paleoparasitological Techniques, 2021)
Extant cephalopod soft tissues are commonly infested by various lineages of parasites making it plausible that extinct cephalopods also had a variety of parasites. Direct evidence of such a relationship is rare, due to the low preservation potential of soft tissues of fossil cephalopods and parasites alike, and the relatively scarce infestation of mineralized tissue by parasites. Evidence for infestations in the fossil record is, therefore, overall rare and limited to shell pathologies. Comparative studies on these structures in extant cephalopods are also not very numerous. Based on similar bauplans and biomineralization pathways, parasite-induced pathologies in bivalves and gastropods can inform about their causes. The position of these features might reveal their parasitic nature. The restriction of these structures to certain cephalopod lineages might indicate the influence of phylogeny, anatomy and potential role of ecology (feeding, mode of life) on infestation risks. However, preservation and research biases might also contribute to differences between externally and internally shelled cephalopods. Other long-term associations with detriment to cephalopods such as epizoa and bioerosion as well as other malformations, which can be confused with parasitic causes, are briefly discussed.
Keywords: Paleopathology; Blister-pearls; Volume-changing pathologies; Asymmetry; Apertural shell growth; Gigantism; Parasitosis

Evolutionary implications of an exceptionally preserved Carboniferous microboring assemblage in the Buckhorn Asphalt Lagerstätte (Oklahoma, USA) - Wisshak, Max; Seuß, Barbara; Nützel, Alexander (Current Developments in Bioerosion, 2008)
In the Buckhorn Asphalt deposit, exceptional preservation of mollusc shells with original aragonitic mineralogy, owing to an early impregnation with migrating hydrocarbons, provides a 'preservational window' for studying a Late Palaeozoic microboring assemblage. The evaluation of thin-sections, bioclast surface features, and SEM analysis of epoxy resin casts reveals a total of 18 known ichnospecies and the new ichnotaxon Aurimorpha varia - reflecting the most diverse Palaeozoic microboring assemblage known to date. The ichno-inventory is dominated by the cyanobacterial traces Eurygonum nodosum, Scolecia filosa, and Fascichnus dactylus, complemented by the common Fascichnus frutex, Planobola macrogota and Cavernula coccidia, and the chlorophyte traces Cavernula pediculata and Rhopalia catenata. Presumable borings of heterotrophs are rare albeit diverse constituents of the microboring assemblage. The ichnocoenosis composition indicates a palaeoenvironment in the shallow-euphotic zone and is in many respects 'modern'. The fact that 17 out of the 19 recorded ichnospecies are also known to neoichnology in closely similar ichnocoenoses of today's shallow-euphotic seas underlines the pronounced longevity of microendolithic taxa and promotes their value as deep-time palaeoenvironmental indicator. Two thirds of the recorded ichnotaxa were reported for the first time from Carboniferous strata, thereby extending the known stratigraphic range of Cavernula pediculata, Cavernula coccidia, Rhopalia catenata, Rhopalia spinosa, Scolecia serrata, Polyactina fastigata, Saccomorpha terminalis, and Aurimorpha varia igen. n., isp. n. back into the Palaeozoic. This shows that at least 21 ichnospecies, including a high number of modern ichnotaxa, were established as early as the late Palaeozoic and reflects an increasing abundance and potential competition by chlorophyte algae and heterotroph microborers breaking the former strong dominance of endolithic cyanobacteria in microborer communities. The curve of Phanerozoic ichnospecies diversity suggests that the evolution of microbioerosion agents is to a certain degree parallel to that of the macroborers with main radiations in the Ordovician and Devonian. However, according to the current state of knowledge, the end-Permian mass extinction event seemingly had little or no impact on the diversity and evolution of microborers. Thus, diversity patterns of micorborings differ from those of marine invertebrates, most of which have a minimum in standing diversity at the Permian/Triassic boundary and a general turn-over from typical Palaeozoic to modern evolutionary faunas. © 2008 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-20:Pub.2008.nat.dgeo.IGM.LP.evolut
Keywords: Aurimorpha varia; Bioerosion; Buckhorn Asphalt; Evolution; Lagerstätte; Microborings; Pennsylvanian

Evolutionary Patterns of Ammonoids: Phenotypic Trends, Convergence, and Parallel Evolution - Monnet, Claude; Klug, Christian; de Baets, Kenneth (Ammonoid Paleobiology: From macroevolution to paleogeography, 2015)

Evolution of the Early Paleozoic mélange at the eastern margin of the Argentine Precordillera - von Gosen, Werner; Buggisch, Werner; Lehnert, Oliver (Journal of South American Earth Sciences, 1995)
At the eastern margin of the Argentine Precordillera, Early Paleozoic clastic sediments occur which are interpreted to represent sedimentary mélange deposits of (? Ordovician-) Silurian age. Their olistolith content as well as different pebble types from conglomerate olistoliths provide information about the sedimentary history and the source areas of clastic input during preSilurian times. Gravitational sliding of the olistoliths into an eastern basin was followed by a compressional event during Late Devonian to pre-Upper Carboniferous times. The latter is interpreted to be the result of a ± W-E crustal shortening between the Eastern Precordillera and a basement complex to the east. Late Tertiary compression affected the already steeply inclined and deformed deposits. There was no evidence found to postulate large-scale strike-slip faulting between the Eastern Precordillera and the Sierras Pampeanas Basement Complex during Paleozoic and/or Tertiary times. The formation of both the eastern clastic deposits of the Precordillera and the western slope of the Cambro-Ordovician carbonate platform is interpreted to be the result of large-scale crustal extension with block rotations during Middle to Late Ordovician times. © 1995.
UnivIS-Import:2015-03-05:Pub.1995.nat.dgeo.IGM.LG.evolut

Evolution of the particle size distribution of tricalcium silicate during hydration by synchrotron X-ray nano-tomography - Neubauer, Jürgen; Sowoidnich, T.; Valentini, L.; Schulbert, Christian; Naber, Christoph; Rößler, C.; DaSilva, J.; Bellmann, F. (Cement and Concrete Research, 2022)
The particle size distribution of tricalcium silicate (C3S) is essential for the modelling of early C3S hydration kinetics. In this study, this parameter is analysed during the main hydration period until the first 20 h by synchrotron near-field ptychographic (NF-PXCT) and holographic (HXCT) computed nano-tomography. Additionally, X-ray diffraction, 29Si NMR, thermal analysis, scanning electron microscopy, and inductively coupled plasma-optical emission spectroscopy were used to investigate the system evolution. The time-dependent pore solution composition is also provided to gain further information. HXCT and NF-PXCT show comparable values regarding the evolution of the C3S particle size distribution during hydration, indicating that C3S particles smaller than 1.3 μm are completely dissolved after 20 h of hydration. The results can be reasonably reproduced by numerical models if for all particle sizes a constant reacted rim thickness for each degree of hydration is assumed. Data on the aqueous phase composition are also provided.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Holography (B); Hydration (A); Near-field ptychography (B); Synchrotron nano-tomography (B); Tricalcium silicate (D)

Evolutionszentrum Korallenriff - Kießling, Wolfgang (GIT Labor-Fachzeitschrift, 2010)
Keywords: Riffbiologie; Evolution

Exceptional bryozoan assemblage of a microbial-dominated reef from the early Wenlock of Gotland, Sweden - Ernst, Andrej; Munnecke, Axel; Oswald, Irina (Gff, 2015)
Eleven bryozoan species were described from Nors Stenbrott (Gotland, Sweden), represented by six trepostomes, four cystoporates and one fenestrate. Three genera with three species are new: two cystoporates Acantholunaria expansa gen. n. sp. n. and Curviporamonostylata gen. n. sp. n., and a trepostome Stellatotrypa hirsuta gen. n. sp. n. Two trepostome species are new: Leptotrypa perforata sp. n. and Leptotrypa enodis sp. n. The described bryozoan fauna is dominated by thin encrusting taxa which are involved in intensive interactions with calcimicrobes in bryozoan-microbial crusts in the reef. The bryozoan-microbial crusts (bryoliths) show certain sequences by microbes, encrusting bryozoans and tabulate corals. Multiple self-overgrowth of bryozoans occurs frequently and is interpreted as a defensive tactic against microbial fouling. Bryozoans avoid vicinity to tabulate corals, apparently due to strong competition for substrate. The bryozoan fauna from Nors Stenbrott is highly endemic, only two species are known elsewhere (North America and Great Britain).
Keywords: taxonomy; bryozoa; Gotland; Silurian; reefs; palaeoecology

Exceptional cameral deposits in a sublethally injured Carboniferous orthoconic nautiloid from the Buckhorn Asphalt Lagerstätte in Oklahoma, USA - Seuß, Barbara; Mapes, Royal H.; Klug, Christian; Nützel, Alexander (Acta Palaeontologica Polonica, 2012)
The cameral and intrasiphonal deposits of a Pennsylvanian straight nautiloid (Pseudorthoceratidae) are studied in order to understand the formation of these deposits. The specimens from the Buckhorn Asphalt deposit (Oklahoma) are exceptionally preserved including original aragonite and microstructures. The specimen investigated survived a predation attempt and shows bite marks on the phragmocone. This is the second report of an ectocochleate cephalopod and first report of an orthoconic nautiloid which survived massive damage of conch and siphuncle. For the first time, a high-magnesium calcitic mineralogy of cameral deposits is documented. These deposits were formed in alternation with aragonite in a chamber which was perforated during the unsuccessful predation attempt. The animal formed the chamber deposits throughout its entire lifetime and the siphuncle played a major role in formation of the cameral deposits.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.except
Keywords: Buckhorn Asphalt; cameral deposits; Carboniferous; high Mg-calcite (HMC); Nautiloidea; North America; Oklahoma; predation; Pseudorthoceratidae; sublethal damage

Exceptional preservation of bryozoans from the Buckhorn Asphalt Quarry, Oklahoma, USA - Seuß, Barbara; Ernst, Andrej; Taylor, Paul; Nützel, Alexander (Jahrestagung der Paläontologischen Gesellschaft, 2016)
The Pennsylvanian (Desmoinesian–Virgilian) Buckhorn Asphalt Quarry in Oklahoma, USA is well known for its exceptional preservation of a diverse marine invertebrate fauna. Results from the latest study focusing on the Buckhorn bryozoans are presented. Nine genera and species are recognized, two of them new (Stenophragmidium buckhornensis and Streblotrypa (S.) heltzelae). Some skeletal characteristics that are usually lost during diagenesis are uniquely preserved. These include small to large (5-50µm in diameter) node-like surface expressions of styles that most likely strengthened the skeleton or were for attachment of the soft tissue rather than defense. ‘Nanoperforations’ observed in Streblotrypa (Streblotrypa) heltzelae, Stenophragmidium buckhornensis and Rhombocladia delicatula are tiny holes with a diameter of only 0.5 µm countersunk into the laminated skeletal walls. Such structures are unknown from other bryozoans (recent and fossil) and their genesis – produced by microendoliths or by the bryozoans themselves? – is unclear. The most likely hypothesis is that they are due to symbionts (e.g. bacteria) that lived embedded in the growing walls of the bryozoan zooids. In fractured branches of S. (S.) heltzelae, closely spaced ‘granule’ bands on the walls of the autozooids were found. Again, such structures have not been observed elsewhere and their origin and function are enigmatic. Mural spines are reported from R. delicata and Stenoporella sp. Spinose hemiphragms in some trepostomes are new features of unknown function. Finally, a transverse fibrous fabric found in the fenestrate Septopora blanda is reminiscent of a fabric common in post-Palaeozoic cyclostome bryozoans but hitherto not reported in palaeostomates from the Palaeozoi

Exceptional preservation of Carboniferous bryozoans in the Buckhorn Asphalt Quarry of Oklahoma, USA - Taylor, Paul; Seuß, Barbara; Ernst, Andrej (13th Larwood Symposium, 2015)
The Late Carboniferous Buckhorn Asphalt Quarry exposes an ‘Impregnation Fossil Lagerstätte’ (Seuss et al. 2009), famous for its high-quality preservation of molluscs and other fossils. Some of the fossils conserve pristine aragonite or high-Mg calcite, mineral phases seldom preserved in Palaeozoic deposits. Located 10 km south of Sulphur, Oklahoma, the Buckhorn Asphalt Quarry was worked commercially in the 1920s and 1930s for road-paving asphalt. The Buckhorn Asphalt Quarry deposit comprises mixed siliciclastic–carbonate, mostly shallow-water sediments belonging to the Boggy Formation (Deese Group). The impregnating asphalt was derived from hydrocarbons that migrated into the sediments during or shortly after deposition, infilling pore spaces, sealing the sediment and fossils from circulating pore waters and inhibiting diagenesis and cementation. Although bryozoans have been recorded previously from the Buckhorn Asphalt Quarry, they have never been studied in any detail. The fauna is dominated by rhabdomesine cryptostomes and trepostomes, with fewer fenestrates. Chambers of the zooids are largely empty of sediment or cement, which has enabled the observation of some enigmatic internal skeletal features under SEM. For instance, transverse rows of granules line the chambers of the rhabdomesine Streblotrypa, and the hemiphragms of a tabuliporid trepostome have peculiar spinose outgrowths on their proximal edges. Also puzzling is the occurrence in several species of submicron-sized pits on internal wall surfaces. Although superficially resembling microendoliths (Wisshak et al. 2008), the pits may be too small for such an origin to be correct (M. Wisshak, pers. comm.), and the laminae of the bryozoan skeletons appear to be deflected around them suggesting formation during the growth of the host bryozoan skeleton

Exceptional Preservation of Molluscs in the Buckhorn Asphalt - Seuß, Barbara; Nützel, Alexander; Schulbert, Christian (World Congress of Malacology, 2007)
The Late Carboniferous (Desmoinesian, approx. 306 m years) sediments of the Buckhorn Asphalt Quarry (Oklahoma, USA) contain the best preserved Palaeozoic mollusc fauna world wide. Molluscs are commonly preserved in original aragonite including shell microstructures, though aragonite is normally dissolved or recrystallised shortly after deposition. Even larval shells and colour patterns are preserved. The good preservation of fossils was caused by Ordovician oil which intruded into the sediments simultaneously to or shortly after deposition, sealing pore space and preventing recrystallisation via circulating pore waters. The oil then transformed into asphalt loosing its volatiles. The fauna of the Buckhorn Asphalt is dominated by mollusc species, especially by cephalopods and small gastropods. For the purpose of inferring the depositional environment and Palaeoecology, thin sections were prepared from samples of all main lithologies. Asphaltic rocks were dissolved in a Soxhlet apparatus using methylene chloride as solvent (asphalt content is up to 20%). The dissolved samples were sieved (2 mm, 500 µm, 125 µm) and picked. Fossils, especially small gastropods were documented with SEM- and light microscope pictures. Bioerosion in the Buckhorn fossils is common and could be proved using SEM-photographs of fossils and casts, as well as with thin sections. At least 50 gastropod species, two coiled and three orthocone nautiloids have been documented, however brachiopods and bivalves are rare. The rich marine fauna is furthermore represented by ostracods, foraminifers, echinoderms, and bryozoans. Vertebrate remains like fish teeth are rare. First results suggest that most fossils lived in shallow water as is indicated by a diverse assemblage of bioeroders within the mollusc shells as well as by the presence of large land plant remains. The fossil material is mixed with siliciclastic sediment which is conglomeratic sometimes, and was transported over a relatively steep slope or in channel

Exceptional Preservation of Molluscs in the Buckhorn Asphalt - Seuß, Barbara; Nützel, Alexander; Schulbert, Christian (Annual Meeting of the Paläontologische Gesellschaft, 2007)
The Late Carboniferous Buckhorn Asphalt Quarry contains the best preserved Palaeozoic molluscs known world wide. The molluscs are commonly present in their original aragonitic preservation. Shell microstructures, larval shells, and colour patterns are commonly preserved. The good preservation of the fossil molluscs from the Buckhorn Asphalt was caused by Ordovician oil intruding the sediments simultaneously to or short after deposition, sealing pore space and preventing recrystallisation. The oil transformed into asphalt loosing its volatiles. The fauna of the Buckhorn Asphalt Quarry is dominated by molluscs, especially by cephalopods and small gastropods. The great abundance of molluscs and the unique preservation make the Buckhorn Asphalt one of the most important fossil Lagerstätten for Palaeozoic molluscs. The Buckhorn Asphalt Quarry is located near Sulphur, Oklahoma (USA), in the Arbuckle Mountains. It exposes a suite of clastic Carboniferous sediments including siliciclastic limestones, mollusc coquinas, conglomerates, and sandstones. The mollusc bearing sediments from the Buckhorn Asphalt Quarry are of Late Carboniferous (Desmoinesian, 308 - 306.5 Ma) age. Deposition of the sediments took place near the palaeoequator during that time. For documentation from which facies the fossils derive thin section were prepared. The high asphalt amount made is necessary to impregnate the rock samples with synthetic resin before preparing the thin section. To remove the asphalt of the samples and dissolve them a Soxhlet apparatus had to be used. Dissolved sediments were further disaggregated with tensides to remove hydrophobic matter, and then the material was wet-sieved. The fossils of the Buckhorn Asphalt Quarry allowed us to study a unique Palaeozoic assemblage of microborers which were studied in thin sections, casts and etchings. It turned out, that the detected ichno-fossils represent the most diverse Palaeozoic assemblage of micro-bioeroders proved yet. The Buckhorn Asphalt Quarry is an outstanding source of information, as it is one of the very few Palaeozoic deposits in which mollusc shells are preserved in almost unaltered composition. Original shell structures and mineralogy, protoconchs or prodissoconchs are commonly preserved. Colour preservation of naticopsids is present. Gastropods ( 50 species) are the most diverse group in the faunal assemblage. Ammonites and nautiloids are very abundant, bivalves are common. Moreover, a rich marine invertebrate fauna including e.g. brachiopods, echinoderms, bryozoans, ostracods, foraminifera is present. Vertebrate remains are rare, remains of land plants are up to several decimetres in size. The exceptional preservation mollusc shells provides a “preservational window“ for studying a Late Palaeozoic microboring assemblage revealing a total of 18 known ichnospecies and the new ichnotaxon Aurimorpha varia – the most diverse Palaeozoic microboring assemblage known to date. First results suggest that most fossils including the gastropods lived in shallow water as is indicated by the diverse assemblage of bioeroders within the mollusc shells as well as by the presence of large plant remains. The fossil material was mixed with siliciclastic sediment, some of them conglomeratic, and transported over a relatively steep slope or in channels by mass flow events. Data about early ontogenetic mollusc shells and shell microstructure provide important information for phylogeny and taxonomy. We can also study heterochronic processes and compare larval and adult shell morphologies. The fact that shells are commonly unaltered by diagenesis and are present in their original mineralogical composition allows the study of original isotope signals in order to reconstruct palaeo-environmental condition

Exceptions to the temperature–size rule: no Lilliput Effect in end-Permian ostracods (Crustacea) from Aras Valley (northwest Iran) - Nätscher, Paulina; Gliwa, Jana; de Baets, Kenneth; Ghaderi, Abbas; Korn, Dieter (Palaeontology, 2023)
The body size of marine ectotherms is often negatively correlated with ambient water temperature, as seen in many clades during the hyperthermal crisis of the end-Permian mass extinction (c. 252 Ma). However, in the case of ostracods, size changes during ancient hyperthermal events are rarely quantified. In this study, we evaluate the body size changes of ostracods in the Aras Valley section (northwest Iran) in response to the drastic warming during the end-Permian mass extinction at three taxonomic levels: class, order, species. At the assemblage level, the warming triggers a complete species turnover in the Aras Valley section, with larger, newly emerging species dominating the immediate post-extinction assemblage for a short time. Individual ostracod species and instars do not show dwarfing or a change in body size as an adaptation to the temperature stress during the end-Permian crisis. This may indicate that the ostracods in the Aras Valley section might have been exceptions to the temperature–size rule (TSR), using an adaptation mechanism that does not involve a decrease in body size. This adaptation might be similar to the accelerated development despite constant instar body sizes that can be observed in some recent experimental studies of ostracod responses to thermal stress.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Aras Valley section; body size; mass extinction; Ostracoda; Permian–Triassic

Experimental and quantum chemical study оn the DNA/protein binding and the biological activity of a rhodium(iii) complex with 1,2,4-triazole as an inert ligand - Petrović, Angelina; Živanović, Marko; Puchta, Ralph; Ćoćić, Dušan; Scheurer, Andreas; Milivojevic, Nevena; Bogojeski, Jovana (Dalton Transactions, 2020)
The synthesis and structural characterization of a newly synthesized mononuclear rhodium(iii) complex, Rhtrz, with a ligand (2,2,6-bis((4S,7R)-7,8,8-trimethyl-4,5,6,7-tetrahydro-1H-4,7-methanoindazol-3-yl)pyridine) and a ligand of 1,2,4-triazole, are presented in this paper. The kinetic interactions of the Rhtrz complex with essential biomolecules such as 5-GMP, L-Met, and GSH were examined. The study of the biological interactions was focused on the binding properties of the Rhtrz complex with CT-DNA and serum albumin. These interactions were investigated using UV-vis spectrophotometry, fluorescence spectroscopy, viscosity measurements, thermal denaturation studies, and electrophoresis. Fluorescence competition experiments with site-markers for BSA were used to locate the binding site of the Rhtrz-complex to the BSA. Molecular docking studies were carried out to obtain detailed binding information of the complex with CT-DNA, BSA, and HSA. Furthermore, the apparent distance between the donor (HSA) and acceptor (Rhtrz) was determined using fluorescence resonance energy transfer (FRET). The thermodynamic properties and relative stabilities of the Rhtrz complex were examined, constructing the two model equation by DFT calculations (B3LYP(CPCM)/LANL2DZp). In vitro cytotoxicity and redox status on the human epithelial colorectal cancer cell line (HCT-116) and healthy human fibroblast cell line (MRC-5) were also investigated.
CRIS-Team Scopus Importer:2020-07-03

Exploring the limits of morphospace: Ontogeny and ecology of late Viséan ammonoids from the Tafilalt, Morocco - Klug, Christian; de Baets, Kenneth; Korn, Dieter (Acta Palaeontologica Polonica, 2016)
Early late Visean ammonoid assemblages in Morocco are composed of diverse and well-preserved specimens. The material was found in a plain in the Tafilalt (eastern Anti-Atlas). Here, we describe mass-occurrences of juvenile specimens, in which subadult and adult specimens occur in low numbers. The juveniles of some species display a conch morphology that differs fundamentally from the adult stages. Accordingly, we emend the species diagnoses of Goniatites lazarus as well as Calygirtyoceras darkaouaense, introduce the species Entogonites bucheri sp. nov., and discuss possible ecological implications of the morphologic changes throughout ontogeny. In particular, we compare the changes in conch morphology through ontogeny in the light of Pareto Optimiality according to which the morphology of organisms would fill a polygon or polyhedron in morphospace. Data points in one of the vorteces of the polyhedron indicate optimisation for the corresponding task. Although shape is not a proof of function, it appears plausible that juvenile conchs were selected rather for compactness while adult conchs were positively selected for conchs with improved hydrodynamic properties. This appears plausible because at small conch diameters, swimming movements will not suffice for effective translocation and a planktonic mode of life is likely.
Keywords: Ammonoidea; morphospace; palaeoecology; Visean; Morocco

Exploring the oxygen and carbon isotopic composition of the Mediterranean red coral (Corallium rubrum) for seawater temperature reconstructions - Chaabane, Sonia; López Correa, Matthias; Montagna, Paolo; Kallel, Néjib; Taviani, Marco; Linares, Christina; Ziveri, Patrizia (Marine Chemistry, 2016)
Here we provide first evidence that the stable oxygen and carbon isotopic composition (δ18O, δ13C) of the high-magnesium calcite skeleton red coral Corallium rubrum can be used as a reliable seawater temperature proxy. This is based upon the analyses of living colonies of C. rubrum from different depths and localities in the Western Mediterranean Sea. The assessment of the growth rates has been established through the analysis of growth band patterns. The δ18O and δ13C compositions show large variability with a significant difference between the branches and the bases of the colonies. In both coral portions, the δ18O and δ13C values are highly correlated and show well-defined linear trends. Following the “lines technique” approach developed by Smith et al. (2000) for scleractinian aragonitic deep-water corals, our data have been combined with published values for the deep-sea gorgonian corals Isididae and Coralliidae from Kimball et al. (2014) and Hill et al. (2011) resulting in the following δ18O temperature equation:T°C=−5.05±0.24×δ18Ointercept+14.26±0.43R2=0.962pvalue<0.0001 The error associated with this equation is ± 0.5 °C at the mean temperature of the data set, ± 0.7 °C for corals living in 2 °C water and ± 1 °C for coral living in warmer water (17 °C). The highly significant δ18Ointercept vs. temperature relationship combined with the “lines technique” method can be reliably applied to the calcitic skeleton to obtain calcification temperature estimates in the past, although this approach requires the knowledge of the past δ18O and δ13C composition of seawater and it is labor and time intensive.
UnivIS-Import:2017-01-09:Pub.2016.nat.dgeo.IGM.LP.explor_8
Keywords: Growth rings; Mediterranean Sea; Red coral; Seawater temperature; δ; δ

Extended abstract - Sauk megasequence supersequences, southern Great Basin: Second-Order accomodation events in the southwestern Cordilleran margin plattform. In Derby, J.R., Fritz, R.D., Longacre, S., Morgan, W.A. & Sternbach, C.A.: The great American carbonate bank: The Geology and economic resources of the Cambrian-Ordovician Sauk megasequence of Laurentia. - Keller, Martin; Cooper, John D.; Lehnert, Oliver (AAPG Memoir, 2012)
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LG.extend

Extinction and recovery patterns of scleractinian corals at the Cretaceous-Tertiary boundary - Kießling, Wolfgang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2004)
The extinction and recovery of scleractinian corals at the Cretaceous-Tertiary (K-T) boundary was analyzed based on a global database of taxonomically revised late Campanian to Paleocene coral collections. In contrast to earlier statements, our results indicate that extinction rates of corals were only moderate in comparison to other marine invertebrates. We have calculated a 30% extinction rate for Maastrichtian coral genera occurring in more than one stratigraphic stage and more than one geographic region. Reverse rarefaction suggests that some 45% of all coral species became extinct. Photosymbiotic (zooxanthellate) corals were significantly more affected by the extinction than azooxanthellate corals; colonial forms were hit harder than solitary forms, and among colonial forms an elevated integration of corallites raised extinction risk. Abundance, as measured by the number of taxonomic occurrences, had apparently no influence on survivorship, but a wide geographic distribution significantly reduced extinction risk. As in bivalves and echinoids neither species richness within genera nor larval type had an effect on survivorship. An indistinct latitudinal gradient is visible in the extinction, but this is exclusively due to a higher proportion of extinction-resistant azooxanthellate corals in higher-latitude assemblages. No significant geographic hotspot could be recognized, neither in overall extinction rates nor in the extinction of endemic clades. More clades than previously recognized passed through the K-T boundary only to become extinct within the Danian. These failed survivors were apparently limited to regions outside the Americas. Recovery as defined by the proportional increase of newly evolved genera, was more rapid for zooxanthellate corals than previously assumed and less uniform geographically than the extinction. Although newly evolved Danian azooxanthellate genera were significantly more common than new zooxanthellate genera, the difference nearly disappeared by the late Paleocene suggesting a more rapid recovery of zooxanthellate corals in comparison to previous analyses. New Paleocene genera were apparently concentrated in low latitudes, suggesting that the tropics formed a source of evolutionary novelty in the recovery phase. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dgeo.IGM.LP.extinc
Keywords: Corals; Cretaceous-Tertiary boundary; Evolution; Mass extinction; Reefs

Extinction risk controlled by interaction of long-term and short-term climate change - Mathes, Gregor; van Dijk, Jeroen; Kießling, Wolfgang; Steinbauer, Manuel J. (Nature Ecology & Evolution, 2021)
Assessing extinction risk from climate drivers is a major goal of conservation science. Few studies, however, include a long-term perspective of climate change. Without explicit integration, such long-term temperature trends and their interactions with short-term climate change may be so dominant that they blur or even reverse the apparent direct relationship between climate change and extinction. Here we evaluate how observed genus-level extinctions of arthropods, bivalves, cnidarians, echinoderms, foraminifera, gastropods, mammals and reptiles in the geological past can be predicted from the interaction of long-term temperature trends with short-term climate change. We compare synergistic palaeoclimate interaction (a short-term change on top of a long-term trend in the same direction) to antagonistic palaeoclimate interaction such as long-term cooling followed by short-term warming. Synergistic palaeoclimate interaction increases extinction risk by up to 40%. The memory of palaeoclimate interaction including the climate history experienced by ancestral lineages can be up to 60 Myr long. The effect size of palaeoclimate interaction is similar to other key factors such as geographic range, abundance or clade membership. Insights arising from this previously unknown driver of extinction risk might attenuate recent predictions of climate-change-induced biodiversity loss.
CRIS-Team WoS Importer:2021-02-12

Extinction trajectories of benthic organisms across the Triassic-Jurassic boundary - Kießling, Wolfgang; Aberhan, Martin; Brenneis, Benjamin; Wagner, Peter (Palaeogeography, Palaeoclimatology, Palaeoecology, 2007)
We analysed diversity and abundance patterns of benthic organisms across the Triassic-Jurassic (T-J) boundary based on the Paleobiology Database (PBDB), which compiles palaeontological collection data on a global scale. While Sepkoski's [Sepkoski, J.J. Jr., 2002. A compendium of fossil marine animal genera. Bulletins of American Paleontology 363, 1-563] compendium on the stratigraphic ranges of marine animal genera suggests that the dominant macrobenthic groups of the Late Triassic experienced significant extinctions prior to the T-J boundary, a significant end-Triassic extinction peak is evident from PBDB's data. This Rhaetian extinction peak is found in both an analysis of the raw data of stratigraphic ranges and a sample-standardized analysis of occurrence data; 41% of all mesobenthic and macrobenthic genera crossing the Norian-Rhaetian boundary became extinct within the Rhaetian. Although this rate suffices to characterize the end-Triassic extinction as a true mass extinction against a Middle Triassic to Middle Jurassic background, significantly reduced Rhaetian origination rates add to the strong diversity depletion in the earliest Jurassic. As for other mass extinctions, evidence for selective extinction is meagre when the analysis is limited to the boundary interval alone and when focused on taxonomic and ecological characteristics of individual genera. When taxa are separated by environmental preferences, however, several determinants of extinction risk become evident, suggesting that reef dwellers had a significantly higher extinction risk than level-bottom dwellers, taxa with an inshore preference were more strongly affected than offshore taxa, taxa preferring carbonate substrates were more strongly hit than taxa preferring siliciclastic substrates and taxa preferentially inhabiting low latitudes had higher extinction rates than taxa more common at intermediate and high latitudes. Much of this selectivity is not independent and also seen in the intervals of background extinctions suggesting that the end-Triassic mass extinction represents an intensification of background extinctions but not a qualitatively different macroevolutionary regime. One possible exception is related to preferences for depositional environments suggesting a selective Rhaetian extinction in reefs and inshore settings. © 2006 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LP.extinc
Keywords: Jurassic; Level-bottom communities; Mass extinctions; Reefs; Rhaetian; Selectivity; Triassic

Extreme reefs: Analyses of modern bryostromatolite ("bryolith") reefs from marginal environments in the Netherlands with comparisons to ancient analogues - Harrison, G. William M.; Claußen, Anna Lene; Schulbert, Christian; Munnecke, Axel (EGU General Assembly Conference Abstracts, 2020)

Fabric transitions from shell accumulations to reefs: an introduction with Palaeozoic examples - Álvaro, José-Javier; Aretz, Markus; Boulvain, Frédéric; Munnecke, Axel; Vachard, Daniel; Vennin, Emmanuelle (Geological Society, London, Special Publication, 2007)
<p id="p-2" style="-webkit-font-smoothing: antialiased; margin: 0px 0px 15px; padding: 0px; border: 0px; outline: 0px; vertical-align: baseline; font-variant-numeric: inherit; font-stretch: inherit; font-size: 14px; line-height: inherit; font-family: Verdana, Helvetica, Arial, sans-serif; word-wrap: break-word; color: rgb(0, 0, 0);"> One unresolved conceptual problem in some Palaeozoic sedimentary strata is the boundary between the concepts of ‘shell concentration’ and ‘reef’. In fact, numerous bioclastic strata are transitional coquina-reef deposits, because either distinct frame-building skeletons are not commonly preserved in growth position, or skeletal remains are episodically encrusted by ‘stabilizer’ (reef-like) organisms, such as calcareous and problematic algae, encrusting microbes, bryozoans, foraminifers and sponges. The term ‘parabiostrome’, coined by Kershaw, can be used to describe some stratiform bioclastic deposits formed through the growth and destruction, by fair-weather wave and storm wave action, of meadows and carpets bearing frame-building (archaeocyaths, bryozoans, corals, stromatoporoids, etc.) and/or epibenthic, non-frame-building (e.g. pelmatozoan echinoderms, spiculate sponges and many brachiopods) organisms. <p id="p-3" style="-webkit-font-smoothing: antialiased; margin: 0px 0px 15px; padding: 0px; border: 0px; outline: 0px; vertical-align: baseline; font-variant-numeric: inherit; font-stretch: inherit; font-size: 14px; line-height: inherit; font-family: Verdana, Helvetica, Arial, sans-serif; word-wrap: break-word; color: rgb(0, 0, 0);"> This paper documents six Palaeozoic examples of stabilized coquinas leading to (pseudo)reef frameworks. Some of them formed by storm processes (generating reef soles, aborted reefs or being part of mounds) on ramps and shelves and were consolidated by either encrusting organisms or early diagenesic processes, whereas others, bioclastic-dominated shoals in barrier shelves, were episodically stabilized by encrusting organisms, indicating distinct episodes in which shoals ceased their lateral migration.
Keywords: Palaeozoic; stratigraphy; Fabrics; Fabric transitions; shell accumulations; Reefs

Facies and fauna of the Pennsylvanian Buckhorn Asphalt Quarry deposit: a review and new data on an important Palaeozoic fossil Lagerstätte with aragonite preservation - Seuß, Barbara; Nützel, Alexander; Mapes, Royal H.; Yancey, Thomas E. (Facies, 2009)
The Pennsylvanian Buckhorn Asphalt Quarry contains the best-preserved Palaeozoic mollusc fauna in the world. Early impregnation of mixed siliciclastic-carbonate rocks (mudstones, pack to grainstones, shell beds, and conglomerates) with hydrocarbons prevented aragonite destruction ("Impregnation Fossil Lagerstätte"). The exceptional preservation comprises shell microstructures, microornaments and early ontogenetic shells. Most gastropods had planktotrophic larval development indicating a high primary production although the remains of phytoplankton are very rare in this and other Late Palaeozoic deposits. Deposition occurred close to a shallow-water coastal area. Mass flow processes (density currents) triggered by storms were involved in the transport mechanisms of some units. Shells of benthic molluscs yield the most diverse known Palaeozoic microboring assemblage, indicating at least partly euphotic conditions. The invertebrate fauna comprises about 160 species and is dominated by molluscs, which is unusual for a Palaeozoic deposit, suggesting that aragonite dissolution produces a major bias in the fossil record. However, most mollusc genera in the Buckhorn deposit are also known from other Pennsylvanian occurrences as recrystallised shells. This shows that preservation bias via preferential aragonite dissolution may be overestimated. © Springer-Verlag 2009.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.facies
Keywords: "Impregnation Fossil Lagerstätte"; Aragonite preservation; Buckhorn Asphalt; Facies; Oil migration; Pennsylvanian

Facies and fauna of Triassic to Early Jurassic deposits from the Hochfelln Massif (Northern Calcareous Alps, Bavaria) - Seuß, Barbara; Nützel, Alexander; Höfling, Richard; Schulbert, Christian (System Earth - Biosphere Coupling, 2005)
A suite of Early Mesozoic (Late Triassic, Norian to Early Jurassic) calcareous beds was studied from the Hochfelln Massif in the Northern Calcareous Alps (Bavaria, South Germany). The main part of the Hochfelln Mountain is built up by the Hauptdolomit Group consisting of thick peritidal deposits and overlain by basin deposits of the Rhaetian Kössen Formation and Rhaetian reefoidal limestone with corals. Unlike many other sections in the Tethys realm, coral growth seems to continue into the Jurassic or starts again relatively early within the Early Jurassic. Silicified corals and other marine invertebrates are present in the calcareous, micritic Hochfelln Beds. A reexamination of previously collected ammonite material indicates the presence of Coroniceras sp. which suggests an Early Sinemurian age for the Hochfelln Beds (= Hochfellnkalk). Abundant sponge spicules (spiculites) suggest that sponges were the source for the silicification. The historical gastropod collection (Bayerische Staatssammlung für Paläontologie (BSP), Munich) from the Hochfelln Mountain was reexamined and new material was collected. The Hochfelln gastropod fauna yields a total of 28 species. It represents one of the richest Early Jurassic gastropod faunas of Germany and the Northern Calcareous Alps. The generic assignments of several species were changed and twelve species were newly reported some of which are undescribed. The relatively diverse Early Sinemurian gastropod fauna together with the coral growth on top of the Hochfelln Mountain indicate rapid recovery from the end-Triassic biotic crisi

Facies characterization of Mid-Mesozoic deep-water sediments by quantitative analysis of siliceous microfaunas - Kießling, Wolfgang (Facies, 1996)
Keywords: Antarctic Peninsula; Deep water; Early cretacious; Jurassic; Oman Mountains; Radiolaria; Southern Alps; Sponge spicules

Facies development across the Late Silurian Lau Event based on temperate carbonates of the Prague Basin (Czech Republic) - Gocke, Martina; Lehnert, Oliver; Fryda, Jiri (Facies, 2012)
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LG.facies

Facies development and sequence stratigraphy of the Ludfordian (Upper Silurian) deposits in the Zbruch River Valley, Podolia, western Ukraine: Local facies overprint on the δ13Ccarb record of a global stable carbon isotope excursion - Jarochowska, Emilia; Kozłowski, Wojciech (Facies, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.facies
Keywords: Baltica; Lacustrine environments; Lau Event; Microbial dolomite precipitation; Stable carbon isotopes

Facies from Palaeozoic Reefs and Bioaccumulations - Vennin, Emmanuelle; Aretz, Markus; Boulvain, Frédéric; Munnecke, Axel (2007)
Keywords: Facies; Palaeozoic; Reefs; Bioaccumulations

Facies of two important Early Triassic gastropod lagerstätten: implications for diversity patterns in the aftermath of the end-Permian mass extinction - Nützel, Alexander; Schulbert, Christian (Facies, 2005)
Two important lagerstätten of Early Triassic gastropods, the Sinbad Limestone (Utah, USA) and the Gastropod Oolite (North Italy) yield about 40% of all described Early Triassic species. This great contribution to the global diversity and the exceptional good preservation render high information content, which characterizes fossil lagerstätten. The Smithian Sinbad Limestone contains the most diverse Early Triassic gastropod fauna. At the type locality, it occurs in single, probably storm-induced shell bed within a series of high energy deposits underlain by intertidal microbial mats and subtidal oolite/peloid shoals. The main shell bed contains about 40 invertebrate taxa. Gastropods, scaphopods, and bivalves are most abundant and form an assemblage, which is dominated by small neritaemorphs, the opisthobranch Cylindrobullina convexa and the scaphopod Plagioglypta (annulated tubes). This assemblage lived on shallow, subtidal soft-bottoms based on sedimentological and ecological characteristics. The Dienerian (to Smithian?) Gastropod Oolite Member (North Italy) has extremely abundant, probably salinity-controlled gastropod faunas with low species richness. Almost monospecific assemblages of Pseudomurchisonia kokeni as well as assemblages with about four species are present in the Gastropod Oolite. Modern hydrobiid mudsnail faunas which are adapted to strongly fluctuating salinity in intertidal to shallow subtidal coastal areas form probably a suitable model for the Gastropod Oolite biota. Gastropods from the Werfen- and Moenkopi-Formation lagerstätten are well preserved compared to other Early Triassic deposits. The high contribution to the global diversity of just two sites suggests very incomplete sampling and preservational bias. However, the low richness of the major faunas reflects depauperate Early Triassic faunas and slow recovery from the Permian/Triassic crisis. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LP.facies
Keywords: Early Triassic; Gastropoda; Italy; Permian/Triassic mass extinction; Recovery; USA

Facilitation of coral reef growth by coralline red algae – patterns during the last 150 million years - Teichert, Sebastian; Steinbauer, Manuel; Kießling, Wolfgang (macro 2019 – Bridging local patterns and global challenges, 2019)
Aim: Modern crustose coralline red algae (CCA) play a key role in the construction of coral reefs. It is unclear, however, if their function as consolidators of coral reefs was similar pronounced in the geological past. Accordingly, we tested (1) when the presence of CCA was crucial for the formation of coral reefs throughout the last 150 Ma. We further investigated if (2) the capacity of CCA to reinforce coral reefs suffered two transient crises as a result of the diversification of major herbivore groups. Location: The study involves reef structures from tropical and subtropical environments on a global scale, ranging from the Cretaceous (145.5 Ma) to the Pleistocene (0.01 Ma). Methods: For 736 reef sites, we tested if the fractions of coral reefs are positively correlated with the fractions of those reefs with CCA as secondary reef builders. Implementing generalized linear models (GLM), we tested if fluctuations in the functioning of CCA as secondary reef builders can be explained by the diversification of herbivores or other potential explanatory variables – sea level, δ18O, CO2 and CCA species diversity. Results: The presence of CCA was found to positively correlate with the abundance of coral reefs throughout the analysed period. Model results show that the probability that reefs contain CCA as major reef builders increases with CCA diversity and δ18O while the presence of newly evolved herbivores has a negative effect. High correlations between explanatory variables limit the interpretation of model results. Main conclusions: The presence of CCA is crucial for the formation of coral reefs. This facilitation suffered two crises probably linked to diversification of major herbivore groups. As CCA have evolved adaptations to grazing pressure they now facilitate the formation of modern coral reefs.<br

Fanthalamia kadiri nov. sp., a new "Sphinctozoan" sponge from the Triassic (Carnian) of Turkey - Senowbari-Daryan, Baba; Link, Michael; Garcia-Bellido, Diego C. (Studia Universitatis Babes-Bolyai : Geologia, 2003)
A new sphinctozoid sponge - Fanthalamia kadiri - is described from the Upper Triassic (Carnian) of Antalya area, southern Turkey. This is the second species of the genus Fanthalamia found in Upper Triassic of Turkey.
UnivIS-Import:2015-04-14:Pub.2003.nat.dgeo.IGM.LP.fantha
Keywords: sponge; Sphinctozoa; Triassic; Carnian; Turkey

Fast-growing species shape the evolution of reef corals - Siqueira, Alexandre C.; Kießling, Wolfgang; Bellwood, David R. (Nature Communications, 2022)
Ecological interactions are ubiquitous on tropical coral reefs, where sessile organisms coexist in limited space. Within these high-diversity systems, reef-building scleractinian corals form an intricate interaction network. The role of biotic interactions among reef corals is well established on ecological timescales. However, its potential effect on macroevolutionary patterns remains unclear. By analysing the rich fossil record of Scleractinia, we show that reef coral biodiversity experienced marked evolutionary rate shifts in the last 3 million years, possibly driven by biotic interactions. Our models suggest that there was an overwhelming effect of staghorn corals (family Acroporidae) on the fossil diversity trajectories of other coral groups. Staghorn corals showed an unparalleled spike in diversification during the Pleistocene. But surprisingly, their expansion was linked with increases in both extinction and speciation rates in other coral families, driving a nine-fold increase in lineage turnover. These results reveal a double-edged effect of diversity dependency on reef evolution. Given their fast growth, staghorn corals may have increased extinction rates via competitive interactions, while promoting speciation through their role as ecosystem engineers. This suggests that recent widespread human-mediated reductions in staghorn coral cover, may be disrupting the key macroevolutionary processes that established modern coral reef ecosystems.
CRIS-Team Scopus Importer:2022-05-20

Faunal and facies changes through the mid Homerian (late Wenlock, Silurian) positive carbon isotope excursion in Podolia, western Ukraine - Jarochowska, Emilia; Munnecke, Axel; Frisch, Konstantin; Ray, David C.; Castagner, Ariane (Lethaia, 2016)
The late Wenlock is characterized by two global regressive-transgressive eustatic cycles in association with a double-peaked positive carbon isotope excursion. The onset of the excursion coincides with an extinction event affecting graptolites (the lundgreni event) and proposed to affect conodonts (the Mulde Event) and proliferation of non-skeletal carbonates. In order to test the hypothesized relationships between eustatic and ecological changes, the tropical carbonate Homerian succession in Podolia has been examined with respect to conodont, sequence and δC stratigraphy. Four depositional sequences (DS) have been identified. The onset of the δC excursion occurs at the boundary between DS1 and DS2, corresponding to a forced regression of proposed glacioeustatic origin. The following rapid eustatic transgression associated with the highest δC values of 5.2‰ includes a higher-order shallowing episode recorded in Podolia as normal regression and a boundary between DS2 and DS3. This interval is distinguished by the presence of oncoids and thrombolitic buildups. The latest Wenlock eustatic fall and the corresponding second peak of the δC excursion corresponds in Podolia to a stratigraphic gap. The first δC peak (top of DS1 and DS2) corresponds to the O. bohemica longa conodont Zone, the interval between the two peaks (DS3) - to K. ortus absidata and C. murchisoni zones, and DS4 is tentatively placed in the lowermost Ludlow Series. The record of relative sea-level changes in Podolia is consistent with reconstructions based on successions in England and Sweden. The moderate drop in conodont taxonomic richness may reflect the primary depositional control over their proposed extinctio
Keywords: Baltica; Conodonts; Extinction; Lundgreni Event; Mulde Event; Sequence stratigraphy

Faunal evidence for reduced productivity and uncoordinated recovery in Southern Hemisphere Cretaceous/Paleogene boundary sections - Kießling, Wolfgang; et al. (Geology, 2007)
The mass extinction at the Cretaceous-Paleogene boundary is generally explained by a severe crisis in primary productivity, following a catastrophic bolide impact. Consistent with this scenario, Danian mollusk-dominated benthic shelf ecosystems of southern middle paleolatitudes (Neuquén Basin, Argentina) are characterized by (1) a stratigraphically limited low in macrofossil abundances; (2) an increase in starvation-resistant, nonplanktotrophic deposit feeders and chemosymbionts; (3) a reduction in the average body size of individuals; and (4) individuals with inactive lifestyles being more common than in the late Maastrichtian. Return to pre-extinction conditions of the various synecological attributes occurred over unequal time spans, indicating that recovery was uncoordinated with respect to ecological traits. Global comparison of ecological patterns suggests that reduced food supply (1) was a controlling factor in both hemispheres; (2) affected macrobenthic marine faunas at various distances from the Chiexulub impact site; and (3) was more effective in silicielastic environments as compared to oligotrophic carbonate settings. © 2007 Geological Society of America.
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LP.faunal
Keywords: Cretaceous-Paleogene boundary; Ecology; Mass extinction; Productivity; Southern Hemisphere

Faunenumschwung im frühen Jura Frankens - Nützel, Alexander; Schulbert, Christian (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2017)
In Franken ähneln sich Fazies und Ablagerungsbedingungen vor und nach dem Posidonienschiefer-Ereignis . Es handelt sich um aerobe bis dysaerobe Weichböden in nahezu gleicher paläogeographischer Position. Auch die Faunen weisen Gemeinsamkeiten auf, z. B. die generelle Kleinwüchsigkeit der benthischen Organismen sowie die Dominanz von Gastropoden und Muscheln. Ranghäufigkeiten der Gastropoden deuten auf eine ähnliche community-Struktur in Mistelgau und Buttenheim hin, bei der jeweils wenige Arten stark dominieren. Ophiurenossikel sind sowohl in Buttenheim als auch in Mistelgau sehr häufig. Trotz dieser Gemeinsamkeiten ist in den Faunen vor und nach dem Posidonienschiefer-Ereignis ein deutlicher taxonomischer Faunenumschwung (turnover) zu verzeichnen, der auf Artebene 100% beträgt und auf Gattungsgebene 60% überschreitet. Dies zeigt, dass die benthische Fauna des Amaltheentons dem Schwarzschieferereignis mit Anoxia nicht lateral auswich (Refugien) und nach dessen Ende das Südwestdeutsche Becken wiederbesiedelte. Vielmehr starben diese Faunen weitgehend aus und wurden nach dem Ende der anoxischen Periode durch Neueinwanderung ersetzt. Abweichend von diesem Muster, gibt es einige Arten, wie den holoplanktonischen Gastropoden Coelodiscus minutus oder die opportunistische Muschel Bositra buchi, die im Posidonienschiefer massenhaft auftreten und dann, z. B. in Mistelgau, weiterhin mindestens bis ins Aalenium vorkommen.<br
Keywords: Jura; Gastropoden; Bivalven; Pliensbachium; Massenaussterben

Ferruginous coated grains of microbial origin from the Lower Devonian (Pragian) of the Prague Basin (Czech Republic) – Petrological and geochemical perspective - Vodrážková, Stanislava; Kumpan, Tomáš; Vodrážka, Radek; Frýda, Jiří; Čopjaková, Renata; Koubová, Magdalena; Munnecke, Axel; Kalvoda, Jiří; Holá, Markéta (Sedimentary Geology, 2022)
A unique occurrence of ironstone lenses represented by ferruginous oncoids is reported from the offshore Řeporyje Limestone (Lower Devonian, Pragian) from the Prague Basin (the Stydlé Vody Quarry). The oncoidal cortices show distinct arrangement of hematite/chamosite and/or iron-bearing calcite laminae, which are irregular, wavy and with a relatively high degree of inheritance of shape of the topography of the underlying laminae. Micro-domes and bulges, comparable to those observed in stromatolites and laminae overgrowing topographic irregularities represented by agglutinated foraminifers cemented to oncoid surfaces, were fairly commonly observed. The foraminifers probably represent the earliest representatives of agglutinated foraminifera encrusting surfaces of ferruginous grains. The surfaces of oncoids are wavy and often wrinkled. Although no microbial remains that could have been directly associated with oncoidal growth were recorded, we regard above mentioned features as indicators of biogenicity of the precipitates. We could only speculate the nature of the microbial consortia, but we regard the alternation of Fe2+ (chamosite, iron-bearing calcite) and Fe3+ (hematite) phases as a result of coupled oxidation - reduction processes related to passive and/or active microbial metabolic activities (precipitation of ferrihydrite – hematite precursor) and passive mineral authigenesis mediated by microorganisms (precipitation of chamosite precursor). Spatially restricted occurrence of the oncoidal lenses along with Al/Al + Fe + Mn vs. Fe/Ti, Nd vs. Ce/Ce*, Eu/Sm vs. Sm/Yb and other crossplots suggest that hydrothermal fluids were the most probable source of ferrous iron. Since most of the known oolitic or oncolitic ironstones represent rather large sedimentary bodies deposited around storm wave base to shallow subtidal environments under influence of upwelled anoxic watermasses or continental runoff, the reported oncolitic mounds represent a specific example of ironstones formation.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Ironstones; Microbialites; Oncoids; REE geochemistry; Trace elements geochemistry

Fibrous dolomite formation at a Miocene methane seep may reflect Neoproterozoic aragonite-dolomite sea conditions - Lu, Yang; Paulmann, Carsten; Mihailova, Boriana; Malcherek, Thomas; Birgel, Daniel; López Correa, Matthias; Lin, Zhiyong; Lu, Liuyi; Milker, Yvonne; Peckmann, Jörn (Communications Earth & Environment, 2023)
Fibrous dolomite widely formed in Neoproterozoic marine sedimentary environments, but apparently disappeared in the Phanerozoic. Here, fibrous dolomite is recognised in a Miocene methane seep limestone (Marmorito, Italy) by synchrotron X-ray diffraction, length slow crystal optics and primary zonation under cathodoluminescence, which is unexpected. Low δ13C values and their negative correlation with MgCO3 contents indicate a formation driven by highly alkaline pore waters and catalysis of dissolved sulphide generated by sulphate-driven anaerobic oxidation of methane. Cementing cavities of reefal carbonate, Neoproterozoic fibrous dolomite might have formed under sulphate-reducing conditions like Quaternary reef microbialites. Since the cavities of Neoproterozoic reefs were restricted microenvironments, the formation of fibrous dolomite was possibly favoured by catalysis similar to its Miocene seep counterpart. Our findings reinforce the concept of penecontemporaneous dolomite formation by sulphide catalysis and contribute to our understanding of the environmental conditions of the Neoproterozoic.
CRIS-Team Scopus Importer:2023-10-20

Filograna (colonial serpulid worm tubes) from Upper Triassic (Norian) reef boulders of Taurus Mts. (southern Turkey) - Senowbari-Daryan, Baba; Link, Michael (Facies, 2005)
Two colonial serpulid worm tubes - Filograna taurica n. sp. and Filograna serialis n. sp. - from the Upper Triassic (Norian) reef boulders occurring in Taurus Mts. (south Turkey) are described. As bafflers, both species of Filograna build microbioherms reaching dimensions of up to 15 cm. Both species were not known either in Turkey or in any other Triassic localities of the Tethyan realm. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LP.filogr
Keywords: Annelids; Filograna; Norian; Reef; Serpulids; Taurus; Triassic; Turkey

Filograna minor nov sp (Worm tube) from the middle triassic (Anisian) reef boulders of the Karaburun Peninsula, Western Turkey - Senowbari-Daryan, Baba; Link, Michael; Isintek, Ismail (Turkish Journal of Earth Sciences, 2007)
A colonial serpulid worm tube, Filograna minor nov. sp., from the Anisian reef boulders of the Karaburun Peninsula, Western Turkey is described. The Filograna-bearing boulders occur together with Anisian reef boulders within the Upper Anisian siliciclastic deposits of the Gerence Formation. Filograna minor differs from the Norian species Filograna serialis, described by Senowbari-Daryan and Link from the Taurus Mountains, by the smaller dimensions of the tubes. Copyright © TÜBİTAK.
UnivIS-Import:2015-04-14:Pub.2007.nat.dgeo.IGM.LP.filogr
Keywords: Anisian; Filograna; Karaburum Peninsula; Serpulid; Triassic; Turkey

First dinosaur from the Isle of Eigg (Valtos Sandstone Formation, Middle Jurassic), Scotland - Panciroli, Elsa; Funston, Gregory F.; Holwerda, Femke Marleen; Maidment, Susannah C.R.; Foffa, Davide; Larkin, Nigel; Challands, Tom; Depolo, Paige E.; Goldberg, Daniel; Humpage, Matthew; Ross, Dugald; Wilkinson, Mark; et al. (Earth and Environmental Science Transactions of the Royal Society of Edinburgh, 2020)
Dinosaur body fossil material is rare in Scotland, previously known almost exclusively from the Great Estuarine Group on the Isle of Skye. We report the first unequivocal dinosaur fossil from the Isle of Eigg, belonging to a Bathonian (Middle Jurassic) taxon of uncertain affinity. The limb bone NMS G.2020.10.1 is incomplete, but through a combination of anatomical comparison and osteohistology, we determine it most likely represents a stegosaur fibula. The overall proportions and cross-sectional geometry are similar to the fibulae of thyreophorans. Examination of the bone microstructure reveals a high degree of remodelling and randomly distributed longitudinal canals in the remaining primary cortical bone. This contrasts with the histological signal expected of theropod or sauropod limb bones, but is consistent with previous studies of thyreophorans, specifically stegosaurs. Previous dinosaur material from Skye and broadly contemporaneous sites in England belongs to this group, including Loricatosaurus and Sarcolestes and a number of indeterminate stegosaur specimens. Theropods such as Megalosaurus and sauropods such as Cetiosaurus are also known from these localities. Although we find strong evidence for a stegosaur affinity, diagnostic features are not observed on NMS G.2020.10.1, preventing us from referring it to any known genera. The presence of this large-bodied stegosaur on Eigg adds a significant new datapoint for dinosaur distribution in the Middle Jurassic of Scotland.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Bathonian; Great Estuarine Group; histology; Sauropoda; Theropoda; Thyreophora

First documentation of Middle Ordovician warm-water carbonates in the Mount Jolmo Lungma (Mount Everest) area, southern Xizang (Tibet), China, and its paleogeographic implications - Yu, Shenyang; Fang, Xiang; Munnecke, Axel; Li, Wenjie; Zhen, Yongyi; Li, Yue; Wang, Zhihao; Zhang, Yuandong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2019)
A Middle Ordovician limestone succession, representing part of the Alai Formation (middle part of the Chiatsun Group) of the Himalayan Orogenic Belt, is well exposed at Jiacun section in Nyalam County to the west of the Mount Jolmo Lungma (Mount Everest), southern Xizang (Tibet), China. The succession, though reported previously, has yet to be investigated in detail, especially in the aspects of precise dating, stratigraphic correlation and its paleogeographical affinities. In this contribution we document for the first time the conodont biostratigraphy, carbon isotope chemostratigraphy and microfacies analyses of this carbonate succession. The conodont fauna indicates a middle Darriwilian (Middle Ordovician) age corresponding to the Histiodella holodentata Biochronozone. The carbon isotope records have shown minor fluctuations of δ13C values, with only a small negative carbon excursion in the lower part. The microfacies analysis has resulted in the identification of seven microfacies, including micritic limestone, lithoclastic packstone, non-skeletal grainstone, bioclastic limestone, bioclastic-lithoclastic limestone, bioclastic-lithoclastic-oncoid limestone, and bioclastic-lithoclastic-oncoid-ooid limestone. From thin sections, fragments of crinoids, brachiopods, gastropods, trilobites, bryozoans and calcareous algae are identified. Abundant lithoclasts, cortoids, peloids, oncoids and ooids, together with the occurrences of dasyclad algae and hardgrounds, are also recognized, indicating a shallow- and warm-water marine environment, and a likely tropical or subtropical affinity. Comparison of the lithofacies and faunas of this limestone succession of the Alai Formation with coeval strata in the Zanskar-Spiti area (northern India), Nepal, Bhutan, Canning Basin (West Australia), Lhasa, Qiangtang, Sibumasu, Tarim and North China, suggests that during the Darriwilian these regions or terranes may have possessed a warm-water marine environment and were located in low-latitudinal zones. It seems likely that this region of the northeastern Gondwana and peri- Gondwana was protected from substantial influx of cool-water currents derived from high latitudes at that time.<br
Keywords: Carbonate microfacies; Chemostratigraphy; Conodont biostratigraphy; Darriwilian; Himalaya; Paleogeography

First record of coralline demosponges in the Pleistocene: implications for reef ecology - Kießling, Wolfgang; et al. (Coral Reefs, 2009)
We report the first discovery of coralline sponges from Pleistocene reef limestones of Vanuatu. Sponges of the genus Acanthochaetetes were identified from two reef terraces of Middle and Late Pleistocene age. As these sponges document cryptic habitats in modern coral reefs, they may be index fossils of cryptic habitats in the Pleistocene as well, thereby providing clues on growth conditions in fossil reefs. The small size of the discovered specimens may be attributed to the transient nature of their cryptic habitats, either due to reef growth or the occurrence of an unusual event. © Springer-Verlag 2009.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.firstr
Keywords: Acanthochaetetes; Chaetetidae; Cryptic habitat; Demospongiae; Pleistocene; Reef growth

First record of the Early Devonian ammonoid Teicherticeras from the Eifel (Germany): biogeographic and biostratigraphic importance - Übelacker, Christof; Jansen, Ulrich; de Baets, Kenneth (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2016)
We herein report the discovery of Teicherticeras cf. teicherti in the lower Emsian of the Eifel region (Germany), which is important for the correlation of the neritic Rhenish facies and the hemipelagic Hercynian facies as well as the alignment of regional brachiopod biozonation with global ammonoid biostratigraphy. The specimens are similar in morphology and ornamentation to early Teicherticeras species like T. senior and particularly T. teicherti. The temporal overlap of Anetoceras and Teicherticeras indicates a correlation of the Neichnerberg Formation with the upper part of the Praecursor Zone and lower part of the Barrandei Zone. Interestingly, Teicherticeras is also more widely distributed than Anetoceras, which might be related with its better dispersal capabilities and/or sampling biases against Anetoceratinae.
Keywords: Ammonoidea; Teicherticeratidae; Devonian; Emsian; Rhenish Mountains; biostratigraphy; biogeography

First record of the early Sheinwoodian carbon isotope excursion (ESCIE) from the Barrandian area of northwestern Perigondwana. - Fryda, Jiri; Lehnert, Oliver; Joachimski, Michael (Estonian Journal of Earth Sciences, 2015)
UnivIS-Import:2015-07-08:Pub.2015.nat.dgeo.IGM.LG.firstr

First record of the Middle Darriwilian δ13C excursion (MDICE) in southern Xizang (Tibet), China, and its implications - Yu, Shenyang; Fang, Xiang; Zhang, Yuandong; Zhen, Yong Yi; Li, Wenjie; Li, Yue; Munnecke, Axel (Carbonates and Evaporites, 2021)
The Ordovician Chiatsun Group, exposed at the Jiacun section, Nyalam, in southern Xizang (Tibet), China, is biostratigraphically one of the best constrained Ordovician sections in the Himalaya margin, and thus plays a key role in correlating the Ordovician strata of this region. The Chiatsun Group is subdivided into the Adang Formation, the Alai Formation, and the Jiaqu Formation, in stratigraphically ascending order. Based on limestone samples collected from the Alai and Jiaqu formations, the Darriwilian chemostratigraphy is established and confirmed by conodont biozonation data. The Middle Darriwilian δ13C excursion (MDICE) is recorded in the Himalaya margin for the first time, with an amplitude of about 2‰. Its rising limb starts near the boundary of the Histiodella holodentata and Histiodella kristinae zones, and the excursion reaches its maximum values in the Pygodus serra Zone. The decreasing limb is not exposed. The carbon isotope curve with its pronounced onset of the MDICE documents a high potential for chemostratigraphic correlations helping to disentangle the Kurgiakh orogeny in the Himalaya margin. The MDICE recorded in southern Xizang correlates well with that in Baltoscandia, Laurentia, the Argentine Precordillera, Siberia, South China, North China, and Tarim, and extends the distribution of the MDICE to a new block, and thereby strengthens its global significance.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Carbon isotope stratigraphy; Chiatsun Group; Darriwilian of Ordovician; Himalaya margin; Kurgiakh orogeny

First records of Asbestopluma hypogea Vacelet and Boury-Esnault, 1996 (Porifera, Demospongiae, Cladorhizidae) on seamounts and in bathyal settings of the Mediterranean Sea - Aguilar, Ricardo; López Correa, Matthias; Calcinai, Barbara; Pastor, Xavier; de la Torriente, Ana; Garcia, Silvia (Zootaxa, 2011)
The carnivorous sponge Asbestopluma hypogea, was known only from shallow submarine caves (-15 to -26 m) in the Western Mediterranean Sea and the Adriatic. Herein A. hypogea is reported from outside of caves, on seamounts in the Alboran Sea (-167 m), off the Balearics (-100 m) and north off Sicily (-660 m), and along steep bathyal escarpments in the Strait of Sicily (∼700 m). These deeper ROV-based findings of A. hypogea are conform to the typical deep-sea occurrence of the Cladorhizidae. Copyright © 2011 Magnolia Press.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.firstr
Keywords: Carnivorous sponges; Cladorhizidae; Western mediterranean

First report of Archaeoscyphia rectilinearis (Porifera) from the Wenlock of Gotland, Sweden - Rhebergen, Freek; Munnecke, Axel; Jarochowska, Emilia (GFF, 2016)
A specimen of the orchocladinid sponge Archaeoscyphia rectilinearis de Freitas (1989) is presented here as the first representative of the Anthaspidellidae from Wenlock strata on Gotland (Sweden). Other coeval occurrences are not yet known from the Silurian of Baltica. This specimen forms a link between the recently described sponge assemblage from Llandovery (Telychian) strata on Gotland and those from Wenlock to Ludlow strata from Arctic Canada. In addition, the specimen fills a gap in the fossil record of Silurian non-stromatoporoid sponges, which are poorly known worldwide.
Keywords: Demospongea; Gotland; Orchocladina; Porifera; Silurian; Wenlock

Fluctuations in the carbonate production of Phanerozoic reefs - Kießling, Wolfgang; Flügel, Erik; Golonka, Jan (Carbonate platform systems: components and interactions, 2000)
A comprehensive database on Phanerozoic reefs is used to evaluate the carbonate production of reefs through time. Net, gross and export carbonate productions of 2760 Phanerozoic reefs are calculated and the cumulative production for 32 time slices is evaluated. The total amount of carbonate produced in the reef ecosystem in a given time slice is a function of global reef abundance, average reef size and the relative amount of carbonate exported from the reefs. Carbonate production of reefs is usually low, but characterized by prominent peaks in the mid-Silurian Givetian-Frasnian, the Late Triassic, the Late Jurassic, the mid-Cretaceous and the Neogene. The determinants of reefal carbonate production are correlated with a variety of intrinsic and extrinsic parameters such as palaeogeographic setting, dominant biota, reef type, bioerosion, petrographic composition, eustatic sea level, oceanic crust production rates, atmospheric CO 2 concentrations, and global nutrient level. The calculated carbonate production, however, is rarely correlated with particular Earth system parameters. This implies that either the controls on reefal carbonate production are too complex to allow reliable predictions, or biotic factors represent more important controls than physico-chemical parameters. The constructed curve of Phanerozoic reefal carbonate export production is also poorly correlated with proposed curves of global shallow-water carbonate production suggesting that reefs rarely contributed in a quantitatively significant way to the global carbonate budget.
UnivIS-Import:2015-04-20:Pub.2000.nat.dgeo.IGM.LP.fluctu

Foraminifera from the Norian Rhaetian reef carbonates of the Taurus Mountains (Saklıkent, Turkey) - Senowbari-Daryan, Baba; Link, Michael (Geologica Carpathica, 2017)
Norian–Rhaetian reef carbonates are exposed in several localities in Taurus Mountains. They predominately contain hypercalcified sponges, followed by scleractinian corals and other less numerous organisms. A coherent Norian–Rhaetian reef structure is exposed near the small town of Saklıkent, west of Antalya. Foraminifers occur in reef carbonates of Saklıkent by numerous genera as shown in this paper. Two species — Siculocosta taurica and Siculocosta sadati — are described as new. The foraminiferal association of Saklıkent is similar or almost identical to the associations known from the Norian–Rhaetian reefs of Sicily, Northern Calcareous Alps, and Greece but shows less similarity to the foraminiferal association from the Apennines, Italy. The most abundant foraminifers are milioliporoids, particularly galeanellids and cucurbitids. Some sessile and agglutinated foraminifers, including Alpinophragmium perforatum Flügel, which mostly occurs abundantly in the Norian–Rhaetian reef carbonates, could not be found in the Saklıkent reef. This association of foraminifera is reported for the first time from a Norian–Rhaetian reef in the Taurus Mountains of Turkey.
UnivIS-Import:2017-11-07:Pub.2017.nat.dgeo.IGM.LP.forami
Keywords: Foraminifera; Upper Triassic; reef; Saklıkent; Taurus Mountains; Turkey

Formation of deglacial microbialites in coral reefs off Tahiti (IODP 310) involving sulfate-reducing bacteria - Heindel, Katrin; Birgel, Daniel; Peckmann, Joern; Kuhnert, Henning; Westphal, Hildegard (Palaios, 2010)
Keywords: coral reef; LA-ICP-MS; last sea-level rise; lipid biomarker; organomineralization

fossilbrush: An R package for automated detection and resolution of anomalies in palaeontological occurrence data - Flannery-Sutherland, Joseph T.; Raja, Nussaïbah Begum; Kocsis, Ádám; Kießling, Wolfgang (Methods in Ecology and Evolution, 2022)
Fossil occurrence databases are indispensable resources to the palaeontological community, yet present unique data cleaning challenges. Many studies devote significant attention to cleaning fossil occurrence data prior to analysis, but such efforts are typically bespoke and difficult to reproduce. There are also no standardised methods to detect and resolve errors despite the development of an ecosystem of cleaning tools fuelled by the concurrent growth of neontological occurrence databases. As fossil occurrence databases continue to increase in size, the demand for standardised, automated and reproducible methods to improve data quality will only grow. Here, we present semi-automated cleaning solutions to address these issues with a new R package fossilbrush. We apply our cleaning protocols to the Paleobiology Database to assess the prevalence of anomalous entries and the efficacy and impact of our methods. We find that anomalies may be effectively resolved by comparison against a published compendium of stratigraphic ranges, improving the stratigraphic quality of the data, and through methods which detect outliers in taxon-wise occurrence stratigraphic distributions. Despite this, anomalous entries remain prevalent throughout major clades, with often more than 30% of genera in major fossil groups (e.g. bivalves, echinoderms) displaying stratigraphically suspect occurrence records. Our methods provide a way to flag and resolve anomalous taxonomic data before downstream palaeobiological analysis and may also aid in the automation and targeting of future cleaning efforts. We stress, however, that our methods are semi-automated and are primarily for the detection of potential anomalies for further scrutiny, as full automation should not be a substitute for expert vetting. We note that some of our methods do not rely on external databases for anomaly resolution and so are also applicable to occurrences in neontological databases, expanding the utility of the fossilbrush R package.
CRIS-Team WoS Importer:2022-09-02

Fossil Focus: Ammonoids - de Baets, Kenneth; Hoffmann, René; Sessa, Jocelyn A.; Klug, Christian (Palaeontology [online], 2016)
Ammonoids (Ammonoidea) are an extinct group of marine invertebrates with an external shell. They were cephalopods, and hence closely related to modern cuttlefish, squid, octopuses and the pearly nautilus. In a non-scientific context, they are commonly called ammonites, but that term really includes only Jurassic and Cretaceous forms in its stricter scientific sense. The Ammonoidea as a whole lived from the Early Devonian to the earliest Palaeogene period, covering a timespan of about 350 million years. Normally, only their shells, also called conchs, or their internal moulds are found in the fossil record. Conchs from adult ammonoids range from about 5 millimetres to 2 metres in diameter. Due to the large diversity (taxonomic richness), disparity (morphological richness), nearly global distribution and abundance of their shells in the fossil record, ammonoids have been valued by geologists, palaeontologists, biologists and fossil collectors alike. They have been particularly useful for studies of biodiversity and for correlating and assigning relative ages to rocks (the field of biostratigraphy). Ammonoids have also proved valuable for studying the processes and patterns of evolution, because they repeatedly evolved towards more coiled, larger and/or more complex conchs. They probably had a large variety of life modes and reproductive strategies, but despite the widespread attention that they have received, there are still several controversies concerning the group’s palaeoecology, anatomy and evolutionary relationships.

Fossilien aus der Opalinuston-Formation von Mistelgau - Schulbert, Christian (Der Steinkern, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.fossil
Keywords: Opalinuston-Formation; Mistelgau

Fossilized leftover falls as sources of palaeoecological data: a ‘pabulite’ comprising a crustacean, a belemnite and a vertebrate from the Early Jurassic Posidonia Shale - Klug, Christian; Schweigert, Günter; Hoffmann, René; Weis, Robert; de Baets, Kenneth (Swiss Journal of Palaeontology, 2021)
Especially in Lagerstätten with exceptionally preserved fossils, we can sometimes recognize fossilized remains of meals of animals. We suggest the term leftover fall for the event and the term pabulite for the fossilized meal when it never entered the digestive tract (difference to regurgitalites). Usually, pabulites are incomplete organismal remains and show traces of the predation. Pabulites have a great potential to inform about predation as well as anatomical detail, which is invisible otherwise. Here, we document a pabulite comprising the belemnite Passaloteuthis laevigata from the Toarcian of the Holzmaden region. Most of its soft parts are missing while the arm crown is one of the best preserved that is known. Its arms embrace an exuvia of a crustacean. We suggest that the belemnite represents the remnant of the food of a predatory fish such as the shark Hybodus.
Created from Fastlane, Scopus look-up
Keywords: Anatomy; Belemnitida; Cephalopoda; Palaeoecology; Taphonomy; Toarcian

Fossil liberation: a model to explain high biodiversity in the Triassic Cassian Formation - Roden, Vanessa; Hausmann, Imelda M.; Nützel, Alexander; Seuß, Barbara; Reich, Mike; Urlichs, Max; Hagdorn, Hans; Kießling, Wolfgang (Palaeontology, 2019)
With 1429 animal species, the Triassic Cassian Formation in the Dolomites, Southern Alps (Italy), yields the highest species richness reported from any spatially constrained pre‐Quaternary formation known to science. The high preserved diversity is partly attributable to a high primary diversity governed by the tropical setting, increasing alpha diversity, and the breadth of habitats spurring beta diversity. More important is the excellent preservation of fossils and the ease with which they can be extracted from the poorly lithified sediments. We propose the term ‘liberation Lagerstätten’ to capture this preservational window. In contrast to conservation Lagerstätten, liberation Lagerstätten like the Cassian Formation originate from normal marine conditions but low‐grade diagenesis. Molluscs contribute substantially to species richness, comprising 67% of all invertebrate species in the Cassian Formation. The gastropod dominance (39% of all species) is nearly as great as in Recent tropical settings, contradicting the concept of a substantial Cenozoic rise.<br
Keywords: diversity; Cassian Formation; gastropod dominance; aragonite preservation; fossil

Fossil Parasites - de Baets, Kenneth; Littlewood, D. Timothy J. (Academic Press, 2015)
Parasitism is a dominant life history strategy and we know it has existed for millions of years. Detecting parasitism in the fossil record is problematic because we rarely see direct evidence and usually must rely on indirect evidence to infer its existence. This unique volume takes a broad and systematic view of direct and indirect evidence for parasitism in the fossil recor

Fossil Trafficking, Fraud, and Fakery - Raja Schoob, Nussaibah Begum; Dunne, Emma (Art Crime in Context, 2022)
The fascination with ancient flora and fauna is a centuries-old phenomenon and is one of the main drivers of fossil crimes. Fossils have been sought by the rich and famous since the advent of colonialism, propelling development in the field of palaeontology but also in how fossils make their way through various, sometimes illegal, corridors to end up in museums and collections across the world. As demand for fossils increased in the nineteenth century, so did commercial avenues for these objects that were being sold not only to private individuals but also to scientific institutions. The most complete and visually impressive fossils in terms of size or uniqueness determine the market value of these fossils with some selling for millions of United States dollars. This has also led to the tampering or forging of fossils by many dealers in an attempt to inflate prices. While fossil crimes have been prevalent for centuries, the legal frameworks within which these crimes can be controlled or stopped are regularly challenged or even circumvented not only due to the lack of enforcements of these regulations but also due to how paleontological objects are classified in the first place as well as other legal loopholes.<br

From patterns to processes: The future of reef research - Kießling, Wolfgang; Flügel, Erik; Golonka, Jan (Phanerozoic reef patterns, 2002)
UnivIS-Import:2015-04-20:Pub.2002.nat.dgeo.IGM.LP.frompa

Fuzzy seas - Kießling, Wolfgang (Geology, 2015)
UnivIS-Import:2015-07-08:Pub.2015.nat.dgeo.IGM.LP.fuzzys

Gaining insights from past reefs to inform understanding of coral reef response to global climate change - Pandolfi, John; Kießling, Wolfgang (Current Opinion in Environmental Sustainability, 2014)
Global climate change is feared to lead to the collapse of living coral reefs, whose component organisms can respond in but three ways: migration, adaptation, and extinction. Because ancient reefs have been exposed to multiple episodes of environmental change, the fossil record provides an important resource for understanding the range of responses of coral reefs to climate change. Reef development has been slowed or stopped repeatedly in the history of life during periods of climate change. Whilst current conditions might be beyond some of the environmental ranges experienced throughout much of earth's history, coral reefs have shown a remarkable resilience to past climate change. Their fate today lies in the interaction between climate change and local anthropogenic stressors that have devastated a large proportion of living reef ecosystems. © 2013 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.gainin

Gastropoda - Seuß, Barbara; Nützel, Alexander (IGCP 596 Climate Change and Biodiversity Patterns in the Mid-Palaeozoic, 2016)

Gastropods from the Early/Middle Jurassic transition of Franconia (Southern Germany). - Schulbert, Christian; Nützel, Alexander (Bulletin of Geosciences, 2013)
A rich gastropod fauna is decribed from the Early/Middle Jurassic boundary (late Toarcian/early Aalenian) of Franconia (N Bavaria, South Germany). It comprises 35 nominate species and additional 9 species are treated in open nomenclature. With a few exceptions, the studied material comes from the Jurensismergel and the Opalinuston formations of the Mistelgau clay pit near Bayreuth. These sediments represent marine soft bottom environments. Gastropods are the most diverse and the most abundant group of the benthic communities in the Mistelgau clay pit. Bivalves, ophiurid and crinoid ossicles as well as foraminifera are also abundant. Among the bivalves, the paper pecten Bositra buchi and the inoceramid Pseudomytiloides dubium are especially abundant. Most of the members of the benthic fauna are small (< 15 mm) or even minute. Only the bivalve Pseudomytiloides dubium, some of the vetigastropods (e.g., Pleurotomarioidea) and the family Gordenellidae (Turritelloidea and Proacirsa) attain a size larger than 2 cm. However, these large species are rare. The most abundant gastropods are the caenogastropod species Coelodiscus minutus and Toarctocera subpunctata. Both species are especially abundant in the lowermost portions of the sampled section. Towards the Aalenian, an increase in diversity can be observed. This reflects recovery from the late Pliensbachian/early Toarcian extinction event. This event was connected with early Toarcian anoxia in Central and Northern Europe including black shale deposition (Posidonienschiefer). The studied gastropod fauna lived during still impoverished but improving environmental conditions. The relatively high diversity and abundance of the benthos suggest aerobic or dysaerobic conditions, however with possible fluctuations of oxygen concentrations. The fauna was also constrained by soft bottom conditions. 12 species are described as new: Mistelgauia monarii, Hummelgauia microstriata, Jurilda zapfi Schulbert, Nützel & Gründel sp. nov., Franconicilda juliae, Carinathilda? dieneri, Conusella convexa, Cossmannina eggmaieri, Sinuarbullina? mistelgauensis, Striactaeonina waltschewi Schulbert, Nützel & Gründel sp. nov., Striactaeonina richterorum Schulbert, Nützel & Gründel sp. nov., Parvulactaeon imprimum Schulbert, Nützel & Gründel sp. nov. and Parvulactaeon inclinatum Schulbert, Nützel & Gründel sp. nov. Three genera are described as new: Hummelgauia, Mistelgauia and Franconicilda. The family Coelodiscidae Gründel&Nützel fam. nov. is described as new based on the probably holoplanktonic gastropod genus Coelodiscus.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.gastro
Keywords: Aalenian; Gastropoda; Germany; Jurassic; Toarcian

Genesis of microbialites as contemporaneous framework components of deglacial coral reefs, Tahiti (IODP 310) - Westphal, Hildegard; Heindel, Katrin; Brandano, Marco; Peckmann, Joern (Facies, 2010)
Keywords: IODP 310; Microbialites; Nutrients; Reef development; Tahiti

Genome-wide transcriptomic analysis of response to low temperature reveals candidate genes determining divergent cold-sensitivity of maize inbred lines - Sobkowiak, Alicja; Jończyk, Maciej; Jarochowska, Emilia; Biecek, Przemyslaw; Trzcinska-Danielewicz, Joanna; Leipner, Jörg; Fronk, Jan; Sowinski, Pawel (Plant Molecular Biology, 2014)
Keywords: Gene ontology; Low temperature; qRT PCR; QTL; Transcriptomics; Zea mays

Geo-biology of Mediterranean deep-water coral ecosystems - Taviani, Marco; Angeletti, Lorenzo; Antolini, Bruno; Ceregato, Alessandro; Froglia, Carlo; López Correa, Matthias; Montagna, Paolo; Remia, Alessandro; Trincardi, Fabio; Vertino, Agostina (Marine Research at CNR, 2011)
Cold (or deep) water corals (CWC) are a spectacular and widespread component of the ocean biota. Highly structured CWC ecosystems serve as biodiversity hotspots suggesting the need for the proper management of these unique habitats. Among the most relevant actors in promoting the growth of conspicuous structures (deep water reefs and mounds) are branching stony corals like Lophelia pertusa and Madrepora oculata. These widespread frame-builders occur also in the Mediterranean basin and are the backbone of Recent CWC provinces identified thus far in the Ionian Sea (Santa Maria di Leuca), South Adriatic Sea, Strait of Sicily, Catalan-Provenc¸al canyons and Alboran Sea. CWC seem strongly influenced by oceanographic factors coupled with proper substrata, such as steep (canyon heads, seamount walls etc) or rugged (slumped blocks) topographies. Dead pre-Modern coral assemblages are present in the entire Sea. These submerged fossil assemblages have been mostly U/Th and 14C dated at the latest Pleistocene documenting propitious basin-wide conditions for their successful growth during glacial periods.
UnivIS-Import:2015-04-20:Pub.2011.nat.dgeo.IGM.LP.geobio
Keywords: cold-water corals

Geochronology of igneous rocks in the Sierra Norte de Córdoba (Argentina): implications for the Pampean evolution at the western Gondwana margin. - von Gosen, Werner; Mcclelland, W. C.; Loske, W.; Martinez, J. C.; Prozzi, C. (Lithosphere, 2014)
UnivIS-Import:2015-10-26:Pub.2014.nat.dgeo.IGM.LG.geochr

Geographical distribution and extinction risk: Lessons from Triassic-Jurassic marine benthic organisms - Kießling, Wolfgang; et al. (Journal of Biogeography, 2007)
Aim: To evaluate the influence of geographical distribution on the extinction risk of benthic marine invertebrates using data from the fossil record, both during times of background extinction and across a mass-extinction episode. Total geographical range is contrasted with proxies of global abundance to assess the relationships between the two essential components of geographical distribution and extinction risk. Location: A global occurrence data base of fossil benthic macro-organisms from the Triassic and Jurassic periods was used for this study. Methods: Geographical distributions and biodiversity dynamics were assessed for each genus (all taxa) or species (bivalves) based on a sample-standardized data set and palaeogeographical reconstructions. Geographical ranges were measured by the maximum great circle distance of a taxon within a stratigraphic interval. Global abundance was assessed by the number of localities at which a taxon was recorded. Widespread and rare taxa were separated using median and percentile values of the frequency distributions of occurrences. Results: The frequency distribution of geographical ranges is very similar to that for modern taxa. Although no significant correlation could be established between local abundance and geographical range, proxies of global abundance are strongly correlated with geographical range. Taxon longevities are correlated with both mean geographical range and mean global abundance, but range size appears to be more critical than abundance in determining extinction risk. These results are valid when geographical distribution is treated as a trait of taxa and when assessed for individual geological stages. Main conclusions: Geographical distribution is a key predictor of extinction risk of Triassic and Jurassic benthic marine invertebrates. An important exception is in the end-Triassic mass extinction, which equally affected geographically restricted and widespread genera, as well as common and rare genera. This suggests that global diversity crises may curtail the role of geographical distribution in determining extinction risk. © 2007 The Authors.
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LP.geogra
Keywords: Abundance; Background extinction; Geographical range; Jurassic; Marine invertebrates; Mass extinction; Origination; Triassic

Geographical limits to species-range shifts are suggested by climate velocity - Burrows, Michael T.; Schoeman, David S.; Richardson, Anthony J.; Molinos, Jorge Garcia; Hoffmann, Ary; Buckley, Lauren B.; Moore, Pippa J.; Brown, Christopher J.; Bruno, John F.; Duarte, Carlos M.; Halpern, Benjamin S.; Hoegh-Guldberg, Ove; et al. (Nature, 2014)
The reorganization of patterns of species diversity driven by anthropogenic climate change, and the consequences for humans, are not yet fully understood or appreciated. Nevertheless, changes in climate conditions are useful for predicting shifts in species distributions at global and local scales. Here we use the velocity of climate change to derive spatial trajectories for climatic niches from 1960 to 2009 (ref. 7) and from 2006 to 2100, and use the properties of these trajectories to infer changes in species distributions. Coastlines act as barriers and locally cooler areas act as attractors for trajectories, creating source and sink areas for local climatic conditions. Climate source areas indicate where locally novel conditions are not connected to areas where similar climates previously occurred, and are thereby inaccessible to climate migrants tracking isotherms: 16% of global surface area for 1960 to 2009, and 34% of ocean for the 'business as usual' climate scenario (representative concentration pathway (RCP) 8.5)8 representing continued use of fossil fuels without mitigation. Climate sink areas are where climate conditions locally disappear, potentially blocking the movement of climate migrants. Sink areas comprise 1.0% of ocean area and 3.6% of land and are prevalent on coasts and high ground. Using this approach to infer shifts in species distributions gives global and regional maps of the expected direction and rate of shifts of climate migrants, and suggests areas of potential loss of species richness. © 2014 Macmillan Publishers Limited.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.geogra

Geographie des Todes - Kießling, Wolfgang (Theatrum naturae, 2001)
Keywords: Geographie

Geologic and biologic controls on the evolution of reefs - Kießling, Wolfgang (Annual Review of Ecology Evolution and Systematics, 2009)
The shallow, tropical reef environment differs from other marine environments in its more intense competition for space, more limited nutrient concentrations, proliferation of clonal animals, and greater habitat complexity. The evolutionary consequences of these ecologic peculiarities are still poorly understood, but they seem to cause greater turnover rates of reef taxa than nonreef taxa and an especially volatile record of reefs on geologic timescales. The boom and bust pattern of Phanerozoic reef construction is impossible to explain by linear responses to physicochemical changes. Threshold effects appear to be involved not only in reef crises but also in reef expansions. Long-term climate change seems to influence the biotic composition of reefs, but neither climate nor sea-level nor chemical changes in the oceans can elucidate the waxing and waning of reefs. Biological factors affecting spatial competition are thus probably more important than geologic controls on reef evolution. Copyright © 2009 by Annual Reviews. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.geolog
Keywords: Climate change; Corals; Habitat area; Macroevolutionary resilience; Mass extinctions; Nutrients; Photosymbiosis

Geology of northeast Ellesmere Island adjacent to Kane Basin and Kennedy Channel, Nunavut. - Lee, Carmen; Lehnert, Oliver; Nowlan, Godfrey (Bulletin of the Geological Survey of Canada, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dgeo.IGM.LG.cretac

Geowissenschaftliche Sammlungen - Höfling, Richard; Schulbert, Christian; Baier, Alfons (Die Sammlungen der Universität Erlangen-Nürnberg. Begleitband zur Ausstellung "Ausgepackt. Die Sammlungen der Universität Erlangen-Nürnberg" 20. Mai bis 29. Juli 2007, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dgeo.IGM.LAG.geowis

German paleontology in the early 21st century. - Kießling, Wolfgang; Nützel, Alexander (Palaeontologia Electronica, 2010)
German paleontology has a long tradition and is still very active and innovative in many fields. Fields with the highest impacts are Neogene to Recent micropaleontology with paleoceanographic and climate focus as well as geobiology and paleoecology. Systematic paleontology is well represented in Germany and leading taxonomic exper- tise is present for many groups although the impact of this resear ch is necessarily low. Conservation of this expertise is important but visibility should be enhanced by cooper- ation with researchers from other disciplines . Analytical paleobiology is too weak in Germany with a few exceptions, as is the de ep-time perspective of evo-devo research and efforts should be made not to fall further behind here. The greatest risk for German paleontology is the continued closure of university departments and the replacement of retired paleontologists by non-paleontologists. This threatens the future of our students in science and the paleontological research community may fall below a critical mass which is needed for innovative research. Some of these problems fa ll in the responsibility of th e paleontologists themselves (e.g., lack of innovative approaches, appare nt absence of practical/ economic applica- bility, tactical mistakes) but others are the re sult of administrative actions to save or shift resources independent of the quality of research and teaching.
Keywords: Germany; Palaeontology; Academics

Givetian/Frasnian (Middle/Upper Devonian) transition in the eastern Taurides, Turkey - Ozkan, Recep; Nazik, Atike; Munnecke, Axel; Demiray, Dilek Gulnur; Schindler, Eberhard; Ozbek, Tuba Aydin; Zor, Emine Seker; Yilmaz, Isak; Brocke, Rainer; Sancay, Recep Hayrettin; Wilde, Volker; Yalcin, Mehmet Namik (Turkish Journal of Earth Sciences, 2019)
Devonian strata, including siliciclastic and carbonate rocks that were deposited in shallow marine to coastal environments, are widely distributed in the eastern Taurides of southern Turkey. To document the regional formation of the Givetian (Middle Devonian)/Frasnian (Upper Devonian) boundary, a section in the eastern Taurides was studied in high resolution with regard to biostratigraphy, microfacies, sequence stratigraphy, and the global Frasne Event. The integrated biostratigraphic investigation was based on calcareous benthic foraminifers, ostracods, conodonts, and palynomorphs, which provide a biostratigraphic frame that allows to recognize the Givetian/Frasnian boundary. On the basis of the lithological variation in the outcrop as well as on depositional textures and biotic components as observed in thin sections, fourteen microfacies types of both siliciclastic and carbonate rocks can be distinguished. These microfacies are interpreted to have been deposited in settings that range from distal shelf to lagoonal depositional environments. The sequence stratigraphic interpretation allows to recognize two successive depositional sequences. The first one is a complete sequence including lowstand systems tract deposits, overlain by transgressive systems tract and highstand systems tract deposits. The second sequence is only represented by transgressive systems tract sediments. The Givetian/Frasnian boundary corresponds to the highstand systems tract of Sequence 1. The late Givetian Frasne Event can be detected lithologically and can be compared with other areas. Its position is confirmed biostratigraphically.
CRIS-Team WoS Importer:2019-04-02

Givetian/Frasnian (Middle/Upper Devonian) transition in the eastern Taurides, Turkey - Özkan, Recep; Nazik, Atike; Munnecke, Axel; Saydam Demiray, Dilek Gülnur; Schindler, Eberhard; Aydin Özbek, Tuba; Şeker Zor, Emine; Yilmaz, Isak; Brocke, Rainer; Hayrettin Sancay, Recep; Wilde, Volker; Yalçın, Mehmet Namık (Turkish Journal of Earth Sciences, 2019)
Devonian strata, including siliciclastic and carbonate rocks that were deposited in shallow marine to coastal environments, are widely distributed in the eastern Taurides of southern Turkey. To document the regional formation of the Givetian (Middle Devonian)/ Frasnian (Upper Devonian) boundary, a section in the eastern Taurides was studied in high resolution with regard to biostratigraphy, microfacies, sequence stratigraphy, and the global Frasne Event. The integrated biostratigraphic investigation was based on calcareous benthic foraminifers, ostracods, conodonts, and palynomorphs, which provide a biostratigraphic frame that allows to recognize the Givetian/Frasnian boundary. On the basis of the lithological variation in the outcrop as well as on depositional textures and biotic components as observed in thin sections, fourteen microfacies types of both siliciclastic and carbonate rocks can be distinguished. These microfacies are interpreted to have been deposited in settings that range from distal shelf to lagoonal depositional environments. The sequence stratigraphic interpretation allows to recognize two successive depositional sequences. The first one is a complete sequence including lowstand systems tract deposits, overlain by transgressive systems tract and highstand systems tract deposits. The second sequence is only represented by transgressive systems tract sediments. The Givetian/Frasnian boundary corresponds to the highstand systems tract of Sequence 1. The late Givetian Frasne Event can be detected lithologically and can be compared with other areas. Its position is confirmed biostratigraphically.<br
Keywords: Foraminifers; ostracods; conodonts; palynomorphs; microfacies analysis; sequence stratigraphy; Frasne Event; North Gondwanan margin

Glendonite-bearing concretions from the upper Pliensbachian (Lower Jurassic) of South Germany: indicators for a massive cooling in the European epicontinental sea - Merkel, Anna; Munnecke, Axel (Facies, 2023)
The Pliensbachian–Toarcian transition was characterised by a drastic turnover from a cool climate to a period of rapid global warming. While the warming associated with the Early Toarcian Oceanic Anoxic Event is rather well-studied, the cause, intensity and extent of the preceding cooling in the late Pliensbachian are still discussed. Occurrences of glendonite play an important role in this debate, since glendonite is a pseudomorph after the cryophilic carbonate mineral ikaite. This study describes the first glendonite-bearing carbonate concretions from South Germany (Buttenheim clay pit, northern Franconian Alb), which represent the southernmost glendonite occurrence in the late Pliensbachian documented so far. Based on petrographical and sedimentological investigations as well as stable isotope analyses it is concluded that a low temperature was the main factor for ikaite formation in the studied section, suggesting that the late Pliensbachian cooling had a more far-reaching impact on the temperature of the European epicontinental sea than previously assumed. To explain the low temperatures required for ikaite precipitation, a model for the sea-ice driven formation of cold bottom-water masses on the continental shelf is proposed. The occurrence of several layers containing reworked hiatus concretions in the studied outcrop is interpreted as the result of recurrent sea-level falls caused by multiple glacial pulses characterising the overall cool climate in the late Pliensbachian.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Glaciation; Glendonite; Hiatus concretions; Late Pliensbachian climate; Stable isotopes

Global endemics-area relationships of vascular plants - Hobohm, Carsten; Janišová, Monika; Steinbauer, Manuel; Landi, Sara; Field, Richard; Vanderplank, Sula; Beierkuhnlein, Carl; Grytnes, John Arvid; Vetaas, Ole Reidar; Fidelis, Alessandra; de Nascimento, Lea; Clark, Vincent Ralph; et al. (Perspectives in Ecology and Conservation, 2019)
Endemics–Area Relationships (EARs)are fundamental in theoretical and applied biogeography for understanding distribution patterns and promoting biodiversity conservation. However, calculating EARs for vascular plant species from existing data is problematic because of biased knowledge of endemic species distributions and differences between taxonomies. We aimed to overcome these challenges by developing a new standardized global dataset based on expert knowledge to produce a set of global EARs. We developed a nested circle design, with grain sizes of 10 4 , 10 5 , 10 6 , 10 7 , and 10 8 km 2 , respectively, and a global distribution of plots based on a stratified random scheme. The number of vascular plant species endemic to each circle was then estimated independently by five experts randomly chosen from a pool of 23, as both a minimum and a maximum value (lower and upper bounds of the estimation), taking into account the limitations of current knowledge and varied species concepts in existing taxonomies. This procedure resulted in a dataset of 3000 expert estimates. Based on the data, we produced three global EARs for endemic species richness using minimum, maximum and average estimates. As a validation, we used all three models to extrapolate to the entire world, producing estimates of 284,493 (minimum), 398,364 (maximum)and 312,243 (average)vascular plant species. These figures conform to the range of taxonomists’ estimates. From the models, we calculated the average area needed to harbour a single endemic species as 12,875 km 2 (range 9675–20,529). The global vascular plant EARs we calculated represent the first standardized, quantitative expectations of plant endemism at any given scale (sampling unit size). These EARs allow us to provide a clear answer to a long-standing but elusive biogeographical question: how to assess whether any area on the surface of the Earth is rich or poor in endemics relative to the average.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Distribution of land and sea; Expert knowledge; Global reference; Minimum and maximum estimates; Zero-endemic plots

Global imprint of climate change on marine life - Kießling, Wolfgang; Poloczanska, Elvira S.; Brown, Christopher J.; Sydeman, William J.; Kiessling, Wolfgang; Schoeman, David S.; Moore, Pippa J.; Brander, Keith; Bruno, John F.; Buckley, Lauren B.; Burrows, Michael T.; Duarte, Carlos M.; et al. (Nature Climate Change, 2013)
Past meta-analyses of the response of marine organisms to climate change have examined a limited range of locations, taxonomic groups and/or biological responses. This has precluded a robust overview of the effect of climate change in the global ocean. Here, we synthesized all available studies of the consistency of marine ecological observations with expectations under climate change. This yielded a meta-database of 1,735 marine biological responses for which either regional or global climate change was considered as a driver. Included were instances of marine taxa responding as expected, in a manner inconsistent with expectations, and taxa demonstrating no response. From this database, 81-83% of all observations for distribution, phenology, community composition, abundance, demography and calcification across taxa and ocean basins were consistent with the expected impacts of climate change. Of the species responding to climate change, rates of distribution shifts were, on average, consistent with those required to track ocean surface temperature changes. Conversely, we did not find a relationship between regional shifts in spring phenology and the seasonality of temperature. Rates of observed shifts in species' distributions and phenology are comparable to, or greater, than those for terrestrial systems. © 2013 Macmillan Publishers Limited. All rights reserved .
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.global

Global Island Monitoring Scheme (GIMS): a proposal for the long‐term coordinated survey and monitoring of native island forest biota - Borges, Paulo A. V.; Cardoso, Pedro; Kreft, Holger; Whittaker, Robert; Fattorini, Simone; Emerson, Brent C.; Gil, Artur; Gillespie, Rosemary G.; Matthews, Thomas J.; Santos, Ana M. C.; Steinbauer, Manuel; Thébaud, Christophe; et al. (Biodiversity and Conservation, 2018)
Islands harbour evolutionary and ecologically unique biota, which are currently disproportionately threatened by a multitude of anthropogenic factors, including habitat loss, invasive species and climate change. Native forests on oceanic islands are important refu- gia for endemic species, many of which are rare and highly threatened. Long-term monitor- ing schemes for those biota and ecosystems are urgently needed: (i) to provide quantitative baselines for detecting changes within island ecosystems, (ii) to evaluate the effectiveness of conservation and management actions, and (iii) to identify general ecological patterns and processes using multiple island systems as repeated ‘natural experiments’. In this contribu- tion, we call for a Global Island Monitoring Scheme (GIMS) for monitoring the remaining native island forests, using bryophytes, vascular plants, selected groups of arthropods and vertebrates as model taxa. As a basis for the GIMS, we also present new, optimized monitor- ing protocols for bryophytes and arthropods that were developed based on former standard- ized inventory protocols. Effective inventorying and monitoring of native island forests will require: (i) permanent plots covering diverse ecological gradients (e.g. elevation, age of ter- rain, anthropogenic disturbance); (ii) a multiple-taxa approach that is based on standardized and replicable protocols; (iii) a common set of indicator taxa and community properties that are indicative of native island forests’ welfare, building on, and harmonized with existing sampling and monitoring efforts; (iv) capacity building and training of local researchers, col- laboration and continuous dialogue with local stakeholders; and (v) long-term commitment by funding agencies to maintain a global network of native island forest monitoring plots.
Keywords: Beta-diversity; Ecological gradients; Forest monitoring protocols; Island conservation; Long-term monitoring; Sampling standardization

Global mass wasting during the Middle Ordovician: Meteoritic trigger or plate-tectonic environment? - Meinhold, Guido; Arslan, Arzu; Lehnert, Oliver; Stampfli, Gerard M. (Gondwana Research, 2011)
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LG.global

Global ocean conveyor lowers extinction risk in the deep sea - Henry, Lea-Anne; Frank, Norbert; Hebbeln, Dierk; Wienberg, Claudia; Robinson, Laura; van de Flierdt, Tina; Dahl, Mikael; Douarin, Mélanie; Morrison, Cheryl L.; López Correa, Matthias; Rogers, Alex D.; Ruckelshausen, Mario; et al. (Deep-Sea Research, 2014)
General paradigms of species extinction risk are urgently needed as global habitat loss and rapid climate change threaten Earth with what could be its sixth mass extinction. Using the stony coral Lophelia pertusa as a model organism with the potential for wide larval dispersal, we investigated how the global ocean conveyor drove an unprecedented post-glacial range expansion in Earth's largest biome, the deep sea. We compiled a unique ocean-scale dataset of published radiocarbon and uranium-series dates of fossil corals, the sedimentary protactinium-thorium record of Atlantic meridional overturning circulation (AMOC) strength, authigenic neodymium and lead isotopic ratios of circulation pathways, and coral biogeography, and integrated new Bayesian estimates of historic gene flow. Our compilation shows how the export of Southern Ocean and Mediterranean waters after the Younger Dryas 11.6. kyr ago simultaneously triggered two dispersal events in the western and eastern Atlantic respectively. Each pathway injected larvae from refugia into ocean currents powered by a re-invigorated AMOC that led to the fastest postglacial range expansion ever recorded, covering 7500. km in under 400 years. In addition to its role in modulating global climate, our study illuminates how the ocean conveyor creates broad geographic ranges that lower extinction risk in the deep sea. © 2014 The Authors.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.global
Keywords: Atlantic meridional overturning circulation; Climate change; Connectivity; Deep sea; Extinction; Larval dispersal

Global warming generates predictable extinctions of warm- and cold-water marine benthic invertebrates via thermal habitat loss - Reddin, Carl J.; Aberhan, Martin; Raja, Nussaïbah Begum; Kocsis, Ádám (Global Change Biology, 2022)
Anthropogenic global warming is redistributing marine life and may threaten tropical benthic invertebrates with several potential extinction mechanisms. The net impact of climate change on geographical extinction risk nevertheless remains uncertain. Evidence of widespread climate-driven extinctions and of potentially unidentified mechanisms exists in the fossil record. We quantify organism extinction risk across thermal habitats, estimated by paleoclimate reconstructions, over the past 300 million years. Extinction patterns at seven known events of rapid global warming (hyperthermals) differ significantly from typical patterns, resembling those driven by global geometry under simulated global warming. As isotherms move poleward with warming, the interaction between the geometry of the globe and the temperature-latitude relationship causes an uneven loss of thermal habitat and a bimodal latitudinal distribution of extinctions. Genera with thermal optima warmer than similar to 21 degrees C show raised extinction odds, while extinction odds continually increase for genera with optima below similar to 11 degrees C. Genera preferring intermediate temperatures generally have no additional extinction risk during hyperthermals, except under extreme conditions as the end-Permian mass extinction. Widespread present-day climate-driven range shifts indicate that occupancy loss is already underway. Given the most-likely projections of modern warming, our model, validated by seven past hyperthermal events, indicates that sustained warming has the potential to annihilate cold-water habitat and its endemic species completely within centuries.
CRIS-Team WoS Importer:2022-07-29

Gradual warming prior to the end-Permian mass extinction - Gliwa, Jana; Wiedenbeck, Michael; Schobben, Martin; Ullmann, Clemenz; Kießling, Wolfgang; Ghaderi, Abbas; Struck, Ulrich; Korn, Dieter (Palaeontology, 2022)
The biggest known mass extinction in the history of animal life occurred at the Permian-Triassic boundary and has often been linked to global warming. Previous studies have suggested that a geologically rapid (<40 kyr) temperature increase of more than 10 degrees C occurred simultaneously with the main extinction pulse. This hypothesis is challenged by geochemical and palaeontological data indicating profound environmental perturbations and a temperature rise prior to the main extinction. Using secondary ion mass spectrometry (SIMS), we measured oxygen isotope ratios from Changhsingian (late Permian) ostracods of north-western Iran. Our data show that ambient seawater temperature began to rise at least 300 kyr prior to the main extinction event. Gradual warming by approximately 12 degrees C was probably responsible for initial environmental degradation that eventually culminated in the global end-Permian mass extinction.
CRIS-Team WoS Importer:2022-09-16

Graptoloid evolutionary rates track ordovician-Silurian global climate change - Cooper, Roger A.; Munnecke, Axel; Sadler, Peter M.; Crampton, James S. (Geological Magazine, 2014)
Graptoloid evolutionary dynamics show a marked contrast from the Ordovician to the Silurian. Subdued extinction and origination rates during the Ordovician give way, during the late Katian, to rates that were highly volatile and of higher mean value through the Silurian, reflecting the significantly shorter lifespan of Silurian species. These patterns are revealed in high-resolution rate curves derived from the CONOP (constrained optimization) scaled and calibrated global composite sequence of 2094 graptoloid species. The end-Ordovician mass depletion was driven primarily by an elevated extinction rate which lasted for c. 1.2 Ma with two main spikes during the Hirnantian. The early Silurian recovery, although initiated by a peak in origination rate, was maintained by a complex interplay of origination and extinction rates, with both rates rising and falling sharply. The global δC curve echoes the graptoloid evolutionary rates pattern; the prominent and well-known positive isotope excursions during the Late Ordovician and Silurian lie on or close to times of sharp decline in graptoloid species richness, commonly associated with extinction rate spikes. The graptoloid and isotope data point to a relatively steady marine environment in the Ordovician with mainly background extinction rates, changing during the Katian to a more volatile climatic regime that prevailed through the Silurian, with several sharp extinction episodes triggered by environmental crises. The correlation of graptoloid species diversity with isotopic ratios was positive in the Ordovician and negative in the Silurian, suggesting different causal linkages. Throughout the history of the graptoloid clade all major depletions in species richness except for one were caused by elevated extinction rate rather than decreased origination rate. © Cambridge University Press 201
Keywords: climatic forcing; diversity; extinction; plankton

GrassPlot - a database of multi-scale plant diversity in Palaearctic grasslands - Dengler, Juergen; Wagner, Viktoria; Dembicz, Iwona; Garcia-Mijangos, Itziar; Naqinezhad, Alireza; Boch, Steffen; Chiarucci, Alessandro; Conradi, Timo; Filibeck, Goffredo; Guarino, Riccardo; Janisova, Monika; Steinbauer, Manuel; et al. (Phytocoenologia, 2018)
GrassPlot is a collaborative vegetation-plot database organised by the Eurasian Dry Grassland Group (EDGG) and listed in the Global Index of Vegetation-Plot Databases (GIVD ID EU-00-003). GrassPlot collects plot records (relevés) from grasslands and other open habitats of the Palaearctic biogeographic realm. It focuses on precisely delimited plots of eight standard grain sizes (0.0001; 0.001; ... 1,000 m ) and on nested-plot series with at least four different grain sizes. The usage of GrassPlot is regulated through bylaws that intend to balance the interests of data contributors and data users. The current version (v. 1.00) contains data for approximately 170,000 plots of different sizes and 2,800 nested-plot series. The key components are richness data and metadata. However, most included datasets also encompass compositional data. About 14,000 plots have near-complete records of terricolous bryophytes and lichens in addition to vascular plants. At present, GrassPlot contains data from 36 countries throughout the Palaearctic, spread across elevational gradients and major grassland types. GrassPlot with its multi-scale and multi-taxon focus complements the larger international vegetation-plot databases, such as the European Vegetation Archive (EVA) and the global database “sPlot”. Its main aim is to facilitate studies on the scale- and taxon-dependency of biodiversity patterns and drivers along macroecological gradients. GrassPlot is a dynamic database and will expand through new data collection coordinated by the elected Coordinating Board. We invite researchers with suitable data to join GrassPlot. Researchers with project ideas addressable with GrassPlot data are welcome to submit proposals to the Governing Board

Growth allometry and dental topography in Upper Triassic conodonts support trophic differentiation and molar-like element function - Kelz, Valentin; Guenser, Pauline; Rigo, Manuel; Jarochowska, Emilia (Paleobiology, 2023)
Conodont elements have high rates of morphological evolution, but the drivers of this disparity are debated. Positive allometric relationships between dimensions of food-processing surfaces and entire P1 elements have been used to argue that these elements performed mechanical digestion. If involved in food processing, the surface of the element should grow at a rate proportional to the increase in energy requirements of the animal. This inference of function relies on the assumption that the energy requirements of the animal grew faster (≃ mass0.75) than the tooth area (≃ mass0.67). We reevaluate this assumption based on metabolic rates across animals and calculate the allometry in platform-bearing P1 elements of Late Triassic co-occurring taxa, Metapolygnathus communisti and Epigondolella rigoi, using 3D models of ontogenetic series. Positive allometry is found in platform and element dimensions in both species, supporting a grasping-tooth hypothesis, based on the assumption that metabolic rate in conodonts scaled with body mass similarly to that in fish and ectotherms. We also calculate the curvature of the P1 platform surface using the Dirichlet normal energy (DNE) as a proxy for diet. DNE values increase with body mass, supporting the assumption that conodont metabolic rates increased faster than mass0.67. We finally find that adults in both taxa differ in their food bases, which supports trophic diversification as an important driver of the remarkable disparity of conodont elements.
CRIS-Team Scopus Importer:2023-03-31

Growth and feeding ecology of coniform conodonts - Leonhard, Isabella; Shirley, Bryan; Murdock, Duncan J. E.; Repetski, John; Jarochowska, Emilia (PeerJ, 2021)
Conodonts were the first vertebrates to develop mineralized dental tools, known as elements. Recent research suggests that conodonts were macrophagous predators and/or scavengers but we do not know how this feeding habit emerged in the earliest coniform conodonts, since most studies focus on the derived, 'complex' conodonts. Previous modelling of element position and mechanical properties indicate they were capable of food processing. A direct test would be provided through evidence of in vivo element crown tissue damage or through in vivo incorporated chemical proxies for a shift in their trophic position during ontogeny. Here we focus on coniform elements from two conodont taxa, the phylogenetically primitive Proconodontus muelleri Miller, 1969 from the late Cambrian and the more derived Panderodus equicostatus Rhodes, 1954 from the Silurian. Proposing that this extremely small sample is, however, representative for these taxa, we aim to describe in detail the growth of an element from each of these taxa in order to the test the following hypotheses: (1) Panderodus and Proconodontus processed hard food, which led to damage of their elements consistent with prey capture function; and (2) both genera shifted towards higher trophic levels during ontogeny. We employed backscatter electron (BSE) imaging, energy-dispersive X-ray spectroscopy (EDX) and synchrotron radiation X-ray tomographic microscopy (SRXTM) to identify growth increments, wear and damage surfaces, and the Sr/Ca ratio in bioapatite as a proxy for the trophic position. Using these data, we can identify whether they exhibit determinate or indeterminate growth and whether both species followed linear or allometric growth dynamics. Growth increments (27 in Pa. equicostatus and 58 in Pr. muelleri) were formed in bundles of 4-7 increments in Pa. equicostatus and 7-9 in Pr. muelleri. We interpret the bundles as analogous to Retzius periodicity in vertebrate teeth. Based on applied optimal resource allocation models, internal periodicity might explain indeterminate growth in both species. They also allow us to interpret the almost linear growth of both individuals as an indicator that there was no size-dependent increase in mortality in the ecosystems where they lived e.g., as would be the case in the presence of larger predators. Our findings show that periodic growth was present in early conodonts and preceded tissue repair in response to wear and damage. We found no microwear and the Sr/Ca ratio, and therefore the trophic position, did not change substantially during the lifetimes of either individual. Trophic ecology of coniform conodonts differed from the predatory and/or scavenger lifestyle documented for "complex" conodonts. We propose that conodonts adapted their life histories to top-down controlled ecosystems during the Nekton Revolution.
CRIS-Team WoS Importer:2021-12-31

Growth interruptions in Arctic rhodoliths correspond to water depth and rhodolith morphology - Schlüter, Moritz; Pyko, Ines; Wisshak, Max; Schulbert, Christian; Teichert, Sebastian (Minerals, 2021)
Coralline algae that form rhodoliths are widespread globally and their skeletal growth patterns have been used as (paleo-) environmental proxies in a variety of studies. However, growth interruptions (hiati) within their calcareous skeletons are regarded as problematic in this context. Here we investigated how hiati in the growth of Arctic rhodoliths from the Svalbard archipelago correspond to their environment and morphology. Using X-ray micro-computed tomography and stepwise model selections, we found that rhodoliths from deeper waters are subject to more frequent hiatus formation. In addition, rhodoliths with a higher sphericity (i.e., roundness) are less often affected by such growth interruptions. We conclude that these correlations are mainly regulated by hydrodynamics, because, in deeper waters, rhodoliths are not turned frequently enough to prevent a dieback of coralline algal thalli forming on the underside of the rhodolith. In this coherence, spheroidal rhodoliths are turned more easily, therefore shortening the amount of time between turnover events. Moreover, the incidence of light is more advantageous in shallower waters where rhodoliths exhibit a greater share of their surface to diffused ambient light, thus enabling thallus growth also on the down-facing surface of the rhodoliths. In consequence, information on the frequency of hiatus formation combined with rhodolith morphology might serve as a valuable proxy for (paleo-)environmental reconstructions in respect to light availability and the hydrodynamic regim
Keywords: coralline algae; environmental proxies; growth increments; polar carbonates; Svalbard; X-ray micro-computed tomography

Growth trajectories of some major ammonoid sub-clades revealed by serial grinding tomography data - Naglik, Carole; Monnet, Claude; Götz, Stefan; Kolb, Christian; de Baets, Kenneth; Tajika, Amane; Klug, Christian (Lethaia, 2015)
Molluscs such as ammonoids record their growth in their accretionary shells, making them ideal for the study of evolutionary changes in ontogeny through time. Standard methods usually focus on two-dimensional data and do not quantify empirical changes in shell and chamber volumes through ontogeny, which can possibly be important to disentangle phylogeny, interspecific variation and palaeobiology of these extinct cephalopods. Tomographic and computational methods offer the opportunity to empirically study volumetric changes in shell and chamber volumes through ontogeny of major ammonoid sub-clades in three dimensions (3-D). Here, we document (1) the growth of chamber and septal volumes through ontogeny and (2) differences in ontogenetic changes between species from each of three major sub-clades of Palaeozoic ammonoids throughout their early phylogeny. The data used are three-dimensional reconstructions of specimens that have been subjected to grinding tomography. The following species were studied: the agoniatitid Fidelites clariondi and anarcestid Diallagites lenticulifer (Middle Devonian) and the Early Carboniferous goniatitid Goniatites multiliratus. Chamber and septum volumes were plotted against the septum number and the shell diameter (proxies for growth) in the three species; although differences are small, the trajectories are more similar among the most derived Diallagites and Goniatites compared with the more widely umbilicate Fidelites. Our comparisons show a good correlation between the 3-D and the 2-D measurements. In all three species, both volumes follow exponential trends with deviations in very early ontogeny (resolution artefacts) and near maturity (mature modifications in shell growth). Additionally, we analyse the intraspecific differences in the volume data between two specimens of Normannites (Middle Jurassic).
Keywords: 3-D reconstruction; allometry; ammonoidea; ontogeny; palaeozoic; tomography; volumes

Gypsum evaporites in a patch reef of the upper Slite Group in the Silurian (Wenlock) of Gotland, Sweden - Färber, Claudia; Munnecke, Axel (GFF, 2014)
Calcite pseudomorphs after gypsum are observed in a patch reef in the upper Slite Group (Wenlock) on north-east (NE) Gotland (Sweden). The idiomorphic pseudomorphs occur (a) in silt-sized carbonate sediment in former moldic pores, (b) in the micritic matrix of bioclastic rudstones and (c) in the thrombolitic matrix of the reef. The dominance of stenohaline organisms in the reef indicates normal marine salinities during reef growth. The development of evaporitic conditions and the formation of evaporitic minerals therefore postdate reef growth. The authigenic gypsum crystals are interpreted to be formed by downward percolating hypersaline brines which existed on an extremely shallow carbonate platform during the early Homerian (latest Cyrtograptus lundgreni graptolite Zone) regression. © 2013 © 2013 Taylor & Franci
Keywords: evaporites; Gotland; gypsum; reef; Silurian; Slite

Habitat characteristics and carbonate cycling of macrophyte-supported polar carbonate factories (Svalbard)) - Cruise No. MSM55 – June 11 – June 29, 2016 – Reykjavik (Iceland) – Longyearbyen (Norway) - Wisshak, Max; Bartholomä, Alexander; Beuck, Lydia; Büscher, Janina; Freiwald, André; Halfar, Jochen; Hetzinger, Steffen; van Heugten, Bart; Hissmann, Karen; Holler, Peter; Meyer, Neele; Neumann, Hermann; et al. (2017)

Habitat effects and sampling bias on Phanerozoic reef distribution - Kießling, Wolfgang (Facies, 2005)
Incomplete preservation, heterogeneous geographic sampling, uncertainties in palaeogeographic reconstructions and inconsistencies of reef definitions bias global reef patterns observed in the geological record. This sampling bias is added to a biological habitat area effect, which is thought to be of paramount importance for modern reefs. To evaluate the importance of sampling bias of ancient reefs, I first tested the habitat area effect and sampling bias for modern tropical reefs and then evaluated these factors for pre-Pleistocene Phanerozoic reefs. Results suggest that habitat area, although significantly affecting Phanerozoic reef patterns, is considerably less important than sampling bias. Sampling bias is more controlled by socioeconomic factors than by geological processes such as subduction of oceanic crust or sea-level fluctuations. Reefs are more likely to be sampled in rich countries, irrespective of geological and ecological controls. The numeric and geographic distribution of reefs as currently recorded in the published literature is thus probably largely artifactual, which may explain the scarcity of significant correlations between reef distribution patterns and inferred physico-chemical controls. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LP.habita

Harnessing stratigraphic bias at the section scale: Conodont diversity in the Homerian (Silurian) of the Midland Platform, England - Jarochowska, Emilia; Ray, David C.; Röstel, Philipp; Worton, Graham J.; Munnecke, Axel (Palaeontology, 2018)
Keywords: Conodonts; Diversity; Extinction; Mulde event; Sequence stratigraphy; Wenlock

Heterastridium (Hydrozoa) from the Norian of Iran and Turkey - Senowbari-Daryan, Baba; Link, Michael (Palaeontographica, Abteilung A, Band 314, Lieferung 4-6, 2019)
The spherical hydrozoan genus Heterastridium Reuss is reported worldwide from Norian marine deposits in association with reef and other shallow-water organisms as well as with deep water organisms at some localities, the latter being result of transportation. Untill now 29 taxa of Heterastridium were described by previous authors, either as “species”, “subspecies”, “variety” or “forma”. Three species (H. conglobatum Reuss, H. lobatum Reuss and H. disciforme Gerth) are considered to be valid species. All other former taxa are synonyms of Heterastridium conglobatum representing different ontogenetic growth stages. Heterastridium is an index fossil of the Norian. Based on almost 1000 fossils from central Iran, on about 80 specimens from south Turkey and on about 100 thin-sections from morphologically differently structured and sized specimens, the following results have been obtained: (a) Generally, the surface of the small specimens, about 20 mm in diameter, is covered by large elements, called humps or spines in this paper. The development of the surface elements starts from the centre as small columns, becoming thicker by splitting when the specimen reached a diameter of about 20 mm. This first ontogenetic stage is characterised by small humps and/or warts. (b) By repeated spliting of the humps the middle-sized (young adults) and large specimens (adults) developed. The adult stage of Heterastridium conglobatum is characterised by small and equally distributed elements (warts). (c) Morphologically differently sized and structured specimens, described as “species”, “subspecies”, “variety” or “forma” by previous authors, are different ontogenetic growth stages of the species Heterastridium conglobatum Reuss. (d) In addition to H. conglobatum, Heterastridium lobatum Reuss and H. disciforme Schäfer & Grant-Mackie are valid species, which are differentiated by external morphological features (shape) and by an internally different architecture. Heterastridium has been classified as hydrozoan by previous authors and this view is followed here. This genus is a cosmopolitan index fossil of the Norian stage. Its occurrences in the Carnian and Rhaetian rocks, as described by some authors, is not proven and doubtful. Heterastridium is known from most continents, the main occurrence being the Tethyan realm. Some specimens of Heterastridium contain a biogenic object in the centre. It can be assumed that the colonisation of the core object by Heterastridium has most probably taken place at the sea floor followed by a rolling and may be later intermittently floating mode of life. The internal differences of Heterastridium and the Cretaceous genus Parkeria Carpenter are discussed.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Heterastridium; Hydrozoa; Iran; Kasımlar Formation; Nayband Formation; Norian Tethys; Taurus Mountains; Turkey; Upper Triassic

High beta diversity in a Triassic reef basin assemblage - Roden, Vanessa; Kießling, Wolfgang (Crossing the Palaeontological- Ecological Gap, 2018)

High diversity in the Triassic Cassian Formation - Roden, Vanessa; Hausmann, Imelda M.; Seuß, Barbara; Nützel, Alexander; Kießling, Wolfgang (GeoBonn2018, Living Earth, 2018)
The Middle to Upper Triassic Cassian Formation (Dolomites, Northern Italy) is the most diverse early Mesozoic ecosystem worldwide. A compilation of taxa described from the Cassian Formation contains 1336 species after revision. The species richness is very high compared with other fossil lagerstätten known for their diversity. For example, 228 species are reported in the Early Cambrian Chengjiang biota, 280 from the Upper Carboniferous Mazon Creek fauna, 491 from the Eocene London Clay, 147 from the Lower Devonian Hunsrück Slate, a literature compilation of the Upper Carboniferous Finis Shale of Texas yields 332 species, and a total of 861 animal species is reported from the Upper Jurassic Solnhofen Formation. Although the Cassian Formation stands out in the fossil context, a much higher species richness is recorded in Recent tropical ecosystems. For example, a comprehensive survey in New Caledonia, south-west Pacific, yielded 2738 species of molluscs alone (P. Bouchet et al., 2002). With gastropods comprising 70 % of mollusc species (53 % of all species), it is clear that aragonite preservation has a large impact on the diversity of the Cassian fauna. In general, fossil lagerstätten can yield highly diverse communities due to preservational effects. To assess the degree to which the Cassian diversity is driven by a lagerstätten effect, we compare the proportion of stratigraphic singletons among well-known lagerstätten (Chengjiang biota, Hunsrück Slate, Mazon Creek fauna, Solnhofen, London Clay). Among those, the Cassian Formation yields the lowest proportion of singleton genera (17%), and next to lowest proportion of singleton species (68%). The lagerstätten effect is therefore lower than in most other datasets. We consequently conclude that intensive taxonomic work and preservational bias are not the only factors contributing to the high diversity. Beyond the large area (at least 500 km2) and variety of environments covered by the Cassian Formation, yielding a very high beta diversity (mean proportional dissimilarity of 0.94), as well as aragonite preservation, the favorable living conditions in this tropical reef-basin allowed a high dlyiverse fauna to flouris

High resolution correlation of the Homerian carbon isotope excursion (Silurian) across the interior of the Midland Platform (Avalonia), UK - Ray, David C.; Jarochowska, Emilia; Röstel, Philipp; Worton, Graham J.; Munnecke, Axel; Wheeley, James R.; Boomer, Ian (Geological Magazine, 2019)

High-resolution geochemical record of environmental changes during MIS 3 from the northern Alps (Nesseltalgraben, Germany) - Mayr, Christoph; Stojakowits, Philipp; Lempe, Bernhard; Blaauw, Maarten; Diersche, Volker; Grohganz, Madleen; Correa, Matthias López; Ohlendorf, Christian; Reimer, Paula; Zolitschka, Bernd (Quaternary Science Reviews, 2019)
Ravine slopes at the recently discovered Nesseltalgraben site in southeastern Germany provide a unique last glacial sediment record for the Northern Calcareous Alps. The 21 m-long profile is dominated by fine-grained lacustrine-palustrine sediments overlain by several metres of glacifluvial gravels and lodgement tills of the Last Glacial Maximum and underlain by a diamicton. The age model includes 29 radiocarbon analyses and one paleomagnetic anomaly (Laschamp event) together providing a modelled age range from c. 59 to 29.6 ka cal BP, i.e. Marine Isotope Stage (MIS) 3. Apart from a description of the lithofacies, X-ray-fluorescence (XRF) scanning and elemental analyses provide high-resolution records of the geochemical composition. Multivariate analyses of XRF data separate Ca from other major elements. Carbonate contents, represented by Ca and total inorganic carbon, reach maxima in repeatedly occurring calcareous silty to sandy layers and are related to glacigenic origin. These indicate repeated inner-alpine local glaciations during stadials of MIS 3. Scanning electron microscopy and XRF data confirm the detrital origin of these layers. In contrast, organic matter and elements more resistant to chemical weathering (Si, Ti, Zr) accumulated during interstadials and concurrently elevated Rb/Sr ratios indicate intensified weathering. The high-frequency proxy variations determined for Nesseltalgraben reflect interstadial-stadial climate variability comparable with oxygen-isotope records from Greenland ice cores and Alpine speleothems. Thus, Nesseltalgraben is among the very few independently dated sediment records from continental Europe covering the entire MIS 3 and reflecting the full Dansgaard-Oeschger climate variability.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Central Europe; Dansgaard-Oeschger cycles; Glaciation; Grain-size analyses; Greenland interstadials; Lacustrine-palustrine sediment; Middle Würmian; Paleoclimatology; Pleistocene; Radiocarbon dating

High-resolution microtaphofacies analysis of a carbonate tidal channel and tidally influenced lagoon, Pigeon Creek, San Salvador Island, Bahamas - Jarochowska, Emilia (Palaios, 2012)
Taphonomic processes can substantially affect grain composition and textural parameters of carbonate sediment, but can also produce taphonomic signatures that provide supplemental information on the environment of deposition. The aim of the present study is a microtaphofacies analysis of a tidal channelmetahaline lagoon system (North Branch of Pigeon Creek, San Salvador Island, Bahamas). Samples (39 in total) were collected in 13 sites in three zones located along the channel: in the inlet, in the middle part, and in the inner lagoon. Grain composition and taphonomic features - abrasion, boring, calcification, encrustation, fragmentation, and dissolution - were recorded using (1) examination of loose grains belonging to the sand-size fraction, and (2) point counting in thin sections produced from sediment samples. Proportions of different grain types were not correlated in thin sections and loose sediment samples from the same sites, with the exception of algae, which were systematically recorded in thin section in higher proportions. In examination of loose grains, abrasion, fragmentation, and calcification were the most useful taphonomic features, but not in thin sections; only fragmentation rates were correlated between the two proxies. Taphonomic information did not distinguish new facies in surface sediment, but was useful in refining environmental resolution and broadened the interpretation of the environment of deposition. Discrimination between sites based on compositional and textural characteristics of the sediment was improved more by increasing the number of replicates by site than by inclusion of taphonomic data. Application of recognized microtaphofacies to the fossil record is limited, because very little of grain diversity and taphonomic information can be recovered from analysis of thin sections. © 2012 SEPM (Society for Sedimentary Geology).
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.highre

History and development of ABCDEFG: a data standard for geosciences - Petersen, Mareike; Glöckler, Falko; Kießling, Wolfgang; Döring, Markus; Fichtmüller, David; Laphakorn, Lertsutham; Baltruschat, Brian; Hoffmann, Jana (FOSSIL RECORD, 2018)
Museums and their collections have specially customized databases in order to optimally gather and record their contents and associated metadata associated with their specimens. To share, exchange, and publish data, an appropriate data standard is essential. ABCD (Access to Biological Collection Data) is a standard for biological collection units, including living and preserved specimen, together with field observation data. Its extension, EFG (Extension for Geo-science), enables sharing and publishing data related to paleontological, mineralogical, and petrological objects. The standard is very granular and allows detailed descriptions, including information about the collection event itself, the holding institution, stratigraphy, chemical analysis, and host rock. The standard extension was developed in 2006 and has been used since then by different initiatives and applied for the publication of collection-related data in domain-specific and interdisciplinary portals.

Homogenizing and diversifying effects of intensive agricultural land-use on plant species beta diversity in Central Europe — A call to adapt our conservation measures - Buhk, Constanze; Alt, Martin; Steinbauer, Manuel; Beierkuhnlein, Carl; Warren, Steven D.; Jentsch, Anke (Science of the Total Environment, 2017)
The prevention of biodiversity loss in agricultural landscapes to protect ecosystem stability and functions is of major importance to stabilize overall diversity. Intense agriculture leads to a loss in species richness and homogenization of species pools, but the processes behind are poorly understood due to a lack of systematic case studies: The specific impacts by agriculture in contrast to other land-use creating open habitat are not studied as such landscapes hardly exist in temperate regions. Applying systematic grids, we compared the plant species distribution at the landscape scale between an active military training areas in Europe and an adjacent rather intensively used agricultural landscape. As the study areas differ mainly in the type of disturbance regime (agricultural vs. non-agricultural), differences in species pattern can be traced back more or less directly to the management. Species trait analyses and multiple measures of beta diversity were applied to differentiate between species similarities between plots, distance-decay, or nestedness. Contrary to our expectation, overall beta diversity in the agricultural area was not reduced but increased under agricultural. This was probably the result of species nestedness due to fragmentation. The natural process of increasing dissimilarity with distance (distance-decay) was suppressed by intense agricultural land-use, generalist and long-distance dispersers gained importance, while rare species lost continuity. There are two independent processes that need to be addressed separately to halt biodiversity loss in agricultural land. There is a need to conserve semi-natural open habitat patches of diverse size to favor poor dispersers and specialist species. At the same time, we stress the importance of mediating biotic homogenization caused by the decrease of distance-decay: The spread of long-distance dispersers in agricultural fields may be acceptable, however, optimized fertilizer input and erosion control are needed to stop the homogenization of environmental gradients due to nitrogen input into semi-natural habitat.
Keywords: Biotic homogenization; Conservation; Dissimilarity; Distance-decay; Intense agricultural land-use; Landscape eutrophication

Host-Guest Complexes of [TriPip222], the Piperazine Analogue of [2.2.2]: Prediction of Ion Selectivity by Quantum Chemical Calculations VIII[#] - Begel, Svetlana; Scheurer, Andreas; Puchta, Ralph; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2016)
Keywords: Cryptand; Complexation; Quantum chemical calculation; Host-guest complex

Hotspots of cenozoic tropical marine biodiversity - Yasuhara, Moriaki; Huang, Huai Hsuan May; Reuter, Markus; Tian, Skye Yunshu; Cybulski, Jonathan D.; O'Dea, Aaron; Mamo, Briony L.; Cotton, Laura J.; Martino, Emanuela Di; Feng, Ran; Tabor, Clay R.; Reygondeau, Gabriel; et al. (CRC Press, 2022)
Hotspots of tropical marine biodiversity are areas that harbour disproportionately large numbers of species compared to surrounding regions. The richness and location of these hotspots have changed throughout the Cenozoic. Here, we review the global dynamics of Cenozoic tropical marine biodiversity hotspots, including the four major hotspots of the Indo-Australian Archipelago (IAA), western Tethys (present Mediterranean), Arabian Sea and Caribbean Sea. Our review supports the 'Hopping Hotspots' model, which proposes that the locations of peak biodiversity are related to Tethyan faunai elements and track broad-scale shallow-marine habitats and high coastal complexity created by the collision of tectonic plates. A null hypothesis is the 'Whack-A-Mole' model, which proposes that hotspots occur in habitats suitable for high diversity regardless of taxonomie identity or faunai elements. Earlier 'Centre-of theories (e.g. centres of origin with diversity decreasing with distance from supposed areas of exceptionally high rates of speciation, for which easy connection to adjacent regions to the east and west is important) were based on the analysis of recent biotas with no palaeontological foundation, and may better explain diversity dynamics within a hotspot rather than those between hotspots. More recently, however, human disturbance is massively disrupting these natural patterns.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Fossil records; Global patterns; Neogene; Paleobiology; Paleogene; Species diversity gradients; Tropics

How does Citizen Science matter for policy? Analyzing the impact of citizen science in policy making - Almomani, Abeer; Awai, Erdoo Paula; Bonn, Aletta; de Barros, Ingrid Almeida; Friedly, Colleen; Gharesifard, Mohammad; Hecker, Susanne; Kartika, Erlinda Cahya; Kraft, Anne; Matthus, Elsa; Peter, Maria; Raja Schoob, Nussaibah Begum; et al. (iDiv Annual Conference 2019, 2019)
Citizen Science has been proven to support policy making (Bio Innovation Service, 2018),yet harnessing the full potential of Citizen Science requires further understanding of the particular areas of the policy development process where different Citizen Science projects have contributed. Using the policy cycle framework (Howlett&Ramesh, 2003) we assessed 500 Citizen Science projects reported in EU inventory and conducted in-depth analysis of 25 case studies. Our study aims to determine the impact of citizen science projects on the policy cycle.<br

How does sea level correlate with sea-water chemistry? A progress report from the Ordovician and Silurian - Munnecke, Axel; Calner, Michael; Harper, David A.T. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
Keywords: Sea-water chemistry; Ordovician; Silurian

How to differentiate facilitation and environmentally driven co-existence - Steinbauer, Manuel; Beierkuhnlein, Carl; Khan, Mohammed A. S. Arfin; Harter, David E. V.; Irl, Severin D. H.; Jentsch, Anke; Schweiger, Andreas H.; Svenning, Jens-Christian; Dengler, Jurgen (Journal of Vegetation Science, 2016)
Positive plant–plant interactions (i.e. facilitation) receive increasing attention as a potentially important driver of community assembly. We conducted a systematic literature review indicating broad support for positive effects of potential facilitator species. However, a large majority of the reviewed studies (83% for field studies, 57% for experiments) share a similar risk of misinterpretation as they assess facilitative effects by comparing plots inhabited by a potential facilitator with randomly placed control plots nearby (paired sampling). As the distribution of facilitator species may itself be environmentally driven, species co-existence caused by facilitation cannot exclusively be separated from environmental effects (habitat sharing). Based on simulated plant communities and sampling protocols, we show how non-random co-existence can occur in the absence of facilitation. This is relevant because both the effect of spatial environmental heterogeneity and of facilitation (stress-gradient hypothesis) are expected to increase with environmental harshness. Nevertheless, 58% of facilitation studies neither undertook measures to minimize potential biases in their sampling approaches nor did they acknowledge such limitations in the discussion. Attention to this problem has significantly decreased in recent years. We propose that facilitation studies could be improved by (1) using random sampling for association studies, (2) co-analysing environmental factors, or (3) experimentally establishing presumed facilitators. Experimental approaches mimicking facilitative plant characteristics can help to identify facilitation mechanisms. Combining approaches and including functional traits of the involved species should further strengthen inference.
Keywords: Correlation; Cushion plant; Environmental favourability; Harsh environment; Interspecific; Mutualism; Plant–plant interaction; Positive interaction; Simulation; Spatial pattern; Species richness; Statistical inference

Hydrocarbon-seep deposits in the lower Permian Angie Formation, Central Lhasa Block, Tibet - Liu, Chao; An, Xianyin; Algeo, Thomas J.; Munnecke, Axel; Zhang, Yujie; Zhu, Tongxing (Gondwana Research, 2021)
Methane seepage along continental margins has been linked to climatic warming, yet it is uncertain whether such seepage took place during the Permian, a period that witnessed a transition from an icehouse to a greenhouse world. To address this issue, we investigated calcareous concretions and layers within mudstones/shales of the Kungurian Angie Formation in the Xainza area, central Tibet. A combination of petrographic, mineralogical, elemental, and carbon‑sulfur isotopic analyses provide strong evidence for a hydrocarbon-seep origin of these carbonates, with thermogenic methane and crude oil being the most likely carbon sources. Our dataset also indicates that, although fueled by a common deep-buried hydrocarbon reservoir, these layers and concretions experienced different biogeochemical processes due to variable rates of cold-seep fluid flux combined with persistently low sulfate concentrations in bottom waters of the Bangong-Nujiang Tethyan Ocean. A biogeochemical switch from sulfate-dependent to iron oxide-coupled anaerobic oxidation of methane in the sulfate-methane transition zone, likely triggered by sulfate exhaustion, was inferred to affect carbonate layer formation near the sediment-water interface. If true, this switch, together with common vent structures, would have resulted in escape of large amounts of methane directly to the ocean-atmosphere system. The hydrocarbon seeps in the central Lhasa Block was approximately coeval with rapid climate warming in the peri-Gondwanan region during the early Kungurian. Although further investigations are required in the future, this study demonstrates a possible causal relationship between regional tectonic evolution, hydrocarbon seepage, and global climate change.
CRIS-Team Scopus Importer:2020-12-25
Keywords: AOM; Cold seep; Greenhouse; Kungurian; Stable isotopes

Hypercalcified inozoan sponges from the Norian reef carbonates of Turkey - Senowbari-Daryan, Baba; Link, Michael (Revue de Paléobiologie, 2016)
Hypercalcified sponges, including the chambered “Sphinctozoans”, un-chambered “Inozoans”, chaetetids and spongiomorphid-like representatives are the most abundant reef builders in Norian reef boulders from several localities in the Taurus Mountains, southern Turkey. Numerous samples, containing hypercalcified sponges and other reef organisms were collected from these reef boulders in the Dereköy basinal sediments exposed west of Antalya and Kasımlar Basin deposits, north of Antalya. The inozoan fauna of these boulders are described in this paper. 31 species (18 new), belonging to 18 genera (5 new) and 7 families were recognized. Following genera and species are described as new: Preperonidella asymmetrica nov. sp., Milysa polysiphonata nov. gen., nov. sp., M. askomorpha nov. sp., Daharella triassica nov. sp., Acoelia norica nov. sp., Tyanada irregularis nov. gen, nov. sp., Taurispongia oligocanalis nov. gen., nov. sp., T. polycanalis nov. sp., T. tenuis nov. sp., T. lamellicanalis nov. sp., T. fascifera nov. sp., T. siderifera nov. sp., T. lamellata nov. sp., T. polyforma nov. sp., Wildspongia? krystyni nov. sp., Caelispongia topukensis nov. gen., nov. sp., Tenuipariespongia taurica nov. sp., Obscurospongia chaetetiformis nov. gen., nov. sp. The sponge fauna of the Norian reef boulders of Dereköy Basin (Dereköy localities) differs distinctly from reef boulders of the Kasımlar Basin. Also the high diversity of sponges and other reef organisms in Dereköy Basin and the ecological conditions of the growth style of organisms separates the faunal associations of both basins. The Turkish species are compared with time equivalent inozoan fauna from the Northern Calcareous Alps (NCA) from Sicily and from Iran in species level. Among 33 described species of inozoans from Turkey 6 species are known from the Alps, 8 from Sicily and 7 from Iran. The Norian inozoan fauna of Taurus Mts. shows 19.3% similarity to the Norian fauna of the Alps, 25.8% to the fauna of Sicily and 22.5% to the Iranian. It can be stated, that 18 (54.5%) out of 33 described species of inozoans of the Norian boulders from this region are described as new and are endemic. The most endemic and peculiar species were collected from the Dereköy localities.
UnivIS-Import:2017-11-07:Pub.2016.nat.dgeo.IGM.LP.hyperc
Keywords: Inozoa; Norian; Sponges; Taurus Mountains; Triassic; Turkey

Hypercalcified segmented sponges ("sphinctozoans) from the Upper Triassic (Norian) reef boulders of Taurus Mountains (southern Turkey) - Senowbari-Daryan, Baba; Link, Michael (Facies, 2011)
Upper Triassic Norian reef boulders, exposed in a locality near the fountain "Tavuk Cesme" ("Chicken Fountain") in Taurus Mountains, southern Turkey yielded a large number of hypercalcified sponges, including "sphinctozoans", "inozoans", "spongiomorphids", and "chaetetids". The sphinctozoans from this locality are described in this paper. Geologically, this locality belongs to the Anamas-Akseki autochthonous. The reef boulders of this locality are exposed near the "Tavuk Cesme" fountain, located at the road, leading from the town of Aksu to Yenisarbademli. The following taxa are described: Amblysiphonella taurica nov. sp., Anthalythalamia riedeli Senowbari-Daryan, Calabrisiphonella sphaerica nov. sp., Calabrisiphonella cuifi nov. sp., Cinnabaria minima Senowbari-Daryan, Colospongia recta nov. sp., Colospongia sp. 1, Colospongia sp. 2, Colospongia sp. 3, Cryptocoelia compacta nov. sp., Cryptocoelia? sp., Deningeria crassireticulata Senowbari-Daryan, Zühlke, Bechstädt and Flügel, Discosiphonella minima Senowbari-Daryan and Link, Gigantothalamia ovoidalis Senowbari-Daryan, Hajarispongia dipoyrazensis nov. sp., Hajarispongia cortexifera nov. sp., Kashanella irregularis Senowbari-Daryan, Kashanella cylindrica nov. sp., Parauvanella ferdowsensis Senowbari-Daryan, Parastylothalamia cylindrica nov. gen., nov. sp., Asiphothalamia polyosculata nov. gen, nov. sp., Sollasia norica nov. sp., and Thaumastocoelia sphaeroida Senowbari-Daryan. The most abundant sponge is Amblysiphonella taurica nov. sp. followed by Hajarispongia dipoyrazensis nov. sp., Colospongia and Discosiphonella minima Senowbari-Daryan and Link are also relatively abundant. The stylothalamid sponge Parastylothalamia nov. gen. is an abundant sponge genus in other Norian reefs of the Taurus Mountains, but is rare at the "Tavuk Cesme" locality. © 2011 Her Majesty the Queen in Rights of UK.
UnivIS-Import:2015-04-14:Pub.2011.nat.dgeo.IGM.LP.hyperc_5
Keywords: Norian; Reef; Sphinctozoa; Sponge; Taurus Mountains; Triassic; Turkey

Ignoring Fossil Age Uncertainty Leads to Inaccurate Topology and Divergence Time Estimates in Time Calibrated Tree Inference - Barido-Sottani, Joelle; Van Tiel, Nina M. A.; Hopkins, Melanie J.; Wright, David F.; Stadler, Tanja; Warnock, Rachel (Frontiers in Ecology and Evolution, 2020)
Time calibrated trees are challenging to estimate for many extinct groups of species due to the incompleteness of the rock and fossil records. Additionally, the precise age of a sample is typically not known as it may have occurred at any time during the time interval spanned by the rock layer. Bayesian phylogenetic approaches provide a coherent framework for incorporating multiple sources of evidence and uncertainty. In this study, we simulate datasets with characteristics typical of Palaeozoic marine invertebrates, in terms of character and taxon sampling. We use these datasets to examine the impact of different age handling methods on estimated topologies and divergence times obtained using the fossilized birth-death process. Our results reiterate the importance of modeling fossil age uncertainty, although we find that the relative impact of fossil age uncertainty depends on both fossil taxon sampling and character sampling. Sampling the fossil ages as part of the inference gives topology and divergence time estimates that are as good as those obtained by fixing ages to the truth, whereas fixing fossil ages to incorrect values results in higher error and lower coverage. The relative effect increases with increased fossil and character sampling. Modeling fossil age uncertainty is thus critical, as fixing incorrect fossil ages will negate the benefits of improved fossil and character sampling.
CRIS-Team WoS Importer:2020-08-07

ImageJ and 3D Slicer : open source 2 / 3D morphometric software - Pye, Fiona; Raja Schoob, Nussaibah Begum; Shirley, Bryan; Kocsis, Ádám; Hohmann, Niklas; Murdock, Ducan JE; Jarochowska, Emilia (Open Data and Analysis: from morphology to evolutionary patterns, 2019)
In a world where an increasing number of resources are hidden behind paywalls and monthly subscriptions, it is becoming crucial for the scientific community to invest energy into freely available, community-maintained systems. Open-source software projects offer a solution, with freely available code which users can utilise and modify, under an open source licence. In addition to software accessibility and methodological repeatability, this also enables and encourages the development of new tools. As palaeontology moves towards data driven methodologies, it is becoming more important to acquire and provide high quality data through reproducible systematic procedures. Within the field of morphometrics, it is vital to adopt digital methods that help mitigate human bias from data collection. In addition,m mathematically founded approaches can reduce subjective decisions which plague classical data. This can be further developed through automation, which increases the efficiency of data collection and analysis. With these concepts in mind, we introduce two open-source shape analysis software, that arose from projects within the medical imaging field. These are ImageJ, an image processing program with batch processing features, and 3DSlicer which focuses on 3D informatics and visualisation. They are easily extensible using common programming languages, with 3DSlicer containing an internal python interactor, and ImageJ allowing the incorporation of several programming languages within its interface alongside its own simplified macro language. Additional features created by other users are readily available, on GitHub or through the software itself. In the examples presented, an ImageJ plugin “FossilJ” has been developed which provides semi-automated morphometric bivalve data collection. 3DSlicer is used with the extension SPHARM-PDM, applied to synchrotron scans of coniform conodonts for comparative morphometrics, for which small assistant tools have been created.

Impact of ocean acidification and warming on the Mediterranean mussel (Mytilus galloprovincialis) - Gazeau, Frédéric; Alliouane, Samir; Bock, Christian; Bramanti, Lorenzo; López Correa, Matthias; Gentile, Miriam; Hirse, Timo; Pörtner, Hans-Otto; Ziveri, Patrizia (frontiers in Marine Science, 2014)
In order to assess the effects of ocean acidification and warming on the Mediterranean mussel (Mytilus galloprovincialis), specimens were reared in aquarium tanks and exposed to elevated conditions of temperature (+3°C) and acidity (−0.3 pH units) for a period of 10 months. The whole system comprised a factorial experimental design with 4 treatments (3 aquaria per treatment): control, lowered pH, elevated temperature, and lowered pH/elevated temperature. Mortality was estimated on a weekly basis and every 2 months, various biometrical parameters and physiological processes were measured: somatic and shell growth, metabolic rates and body fluid acid-base parameters. Mussels were highly sensitive to warming, with 100% mortality observed under elevated temperature at the end of our experiment in October. Mortality rates increased drastically in summer, when water temperature exceeded 25°C. In contrast, our results suggest that survival of this species will not be affected by a pH decrease of 0.3 in the Mediterranean Sea. Somatic and shell growth did not appear very sensitive to ocean acidification and warming during most of the experiment, but were reduced, after summer, in the lowered pH treatment. This was consistent with measured shell net dissolution and observed loss of periostracum, as well as uncompensated extracellular acidosis in the lowered pH treatment indicating a progressive insufficiency in acid-base regulation capacity. However, based on the present dataset, we cannot elucidate if these decreases in growth and regulation capacities after summer are a consequence of lower pH levels during that period or a consequence of a combined effect of acidification and warming. To summarize, while ocean acidification will potentially contribute to lower growth rates, especially in summer when mussels are exposed to sub-optimal conditions, ocean warming will likely pose more serious threats to Mediterranean mussels in this region in the coming decades.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.impact
Keywords: ocean acidification

Impacts of global climate change on the floras of oceanic islands - Projections, implications and current knowledge - Harter, David; Irl, Severin; Seo, Bumsuk; Steinbauer, Manuel; Gillespie, Rosemary; Triantis, Kostas; Fernández-Palacios, José Maria; Beierkuhnlein, Carl (Perspectives in Plant Ecology Evolution and Systematics, 2015)
Recent climate projections indicate substantial environmental alterations in oceanic island regions during the 21st century, setting up profound threats to insular floras. Inherent characteristics of island species and ecosystems (e.g. small population sizes, low habitat availability, isolated evolution, low functional redundancy) cause a particular vulnerability. Strong local anthropogenic pressures interact with climate change impacts and increase threats. Owing to the high degree of endemism in their floras, a disproportionally high potential for global biodiversity loss originates from climate change impacts on oceanic islands. We reviewed a growing body of research, finding evidence of emerging climate change influences as well as high potentials of future impacts on insular species and ecosystems. Threats from global climate change are not evenly distributed among the world's oceanic islands but rather vary with intrinsic (e.g. island area, structure, age and ecological complexity) and extrinsic factors (regional character, magnitude and rate of climatic alterations, local human influences). The greatest flora vulnerabilities to climate change impacts can be expected on islands of small area, low elevation and homogeneous topography. Islands of low functional redundancies will particularly suffer from high rates of co-modifications and co-extinctions due to climate-change-driven disruptions of ecological interactions. High threat potentials come from synergistic interactions between different factors, especially between climatic changes and local anthropogenic encroachments on native species and ecosystems. In addition, human responses to climate change can cause strong indirect impacts on island floras, making highly populated islands very vulnerable to secondary (derivative) effects. We provide an integrated overview of climate change-driven processes affecting oceanic island plants and depict knowledge gaps and uncertainties. The suitability of oceanic islands and their ecosystems for potential research on the field of climate change ecology is highlighted and implications for adequate research approaches are given.
Keywords: Global warming; Island biogeography; Island endemics; Oceanic buffering; Sea-level rise; Susceptibility

Improving the relevance of paleontology to climate change policy - Kießling, Wolfgang; Smith, Jansen; Raja, Nussaïbah Begum (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Paleontology has provided invaluable basic knowledge on the history of life on Earth. The discipline can also provide substantial knowledge to societal challenges such as climate change. The long-term perspective of climate change impacts on natural systems is both a unique selling point and a major obstacle to becoming more pertinent for policy-relevant bodies like the Intergovernmental Panel on Climate Change (IPCC). Repeated experiments on the impacts of climate change without anthropogenic disturbance facilitate the extraction of climate triggers in biodiversity changes. At the same time, the long timescales over which paleontological changes are usually assessed are beyond the scope of policymakers. Based on first-hand experience with the IPCC and a quantitative analysis of its cited literature, we argue that the differences in temporal scope are less of an issue than inappropriate framing and reporting of most paleontological publications. Accepting that some obstacles will remain, paleontology can quickly improve its relevance by targeting climate change impacts more directly and focusing on effect sizes and relevance for projections, particularly on higher-end climate change scenarios.
CRIS-Team Scopus Importer:2023-02-17
Keywords: biodiversity; climate change; IPCC; paleobiology

INCORPORATING INFORMATION ON VARYING SEDIMENTATION RATES INTO PALEONTOLOGICAL ANALYSES - Hohmann, Niklas (Palaios, 2021)
Stratigraphic changes in the clustering of first or last taxon occurrences are a joint expression of evolutionary, ecological, taphonomic, and sedimentological processes. Sedimentation rates control the degree of sedimentary dilution and condensation and thus alter the time contained in a given thickness of sediment. However, it remains poorly explored quantitatively how distinct the stratigraphic patterns in the first and last occurrences can be under different deposition models with a constant thickness of accumulated sediment. Here, I present an algorithm that translates ecological or evolutionary signals between time and stratigraphic height. It is implemented for R Software as the package DAIME and complemented by tools to quantify the uncertainties associated with the construction of deposition models. By modeling the stratigraphic expression of the K/Pg extinction and an earlier extinction pulse potentially linked to Deccan volcanism on Seymour Island under varying sedimentation rates, I show that (1) clustering of last occurrences similar to 250 kyr prior to the K/Pg boundary can be equally explained by a stronger earlier extinction pulse or prolonged intervals with reduced sediment accumulation rate, but (2) when the temporal variability in sedimentation rate is known, the most plausible extinction dynamics can still be identified. The approach is applicable for any type of information transported as a part of the sedimentary record (e.g., fossils or trace elements) or data derived from it (e.g., isotope ratios and rates of morphological evolution).
CRIS-Team WoS Importer:2021-05-14

Increased extinction in the emergence of novel ecological communities - Pandolfi, John M.; Staples, Timothy L.; Kießling, Wolfgang (Science, 2020)
Environmental change is transforming ecological assemblages into new configurations, resulting in novel communities. We developed a robust methodology to detect novel communities, examine patterns of emergence, and quantify probabilities of local demographic turnover in transitions to and from novel communities. Using a global dataset of Cenozoic marine plankton communities, we found that the probability of local extinction, origination, and emigration during transitions to a novel community increased two to four times that of background community changes. Although rare, novel communities were five times more likely than chance to shift into another novel state. For marine plankton communities at a 100,000-year time grain, novel communities were sensitive to further extinctions and substantial community change.
CRIS-Team Scopus Importer:2020-10-23

Increase in marine provinciality over the last 250 million years governed more by climate change than plate tectonics - Kocsis, Ádám; Reddin, Carl James; Scotese, Christopher R.; Valdes, Paul J.; Kießling, Wolfgang (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2021)
Amidst long-term fluctuations of the abiotic environment, the degree to which life organizes into distinct biogeographic provinces (provinciality) can reveal the fundamental drivers of global biodiversity. Our understanding of present-day biogeography implies that changes in the distribution of continents across climatic zones have predictable effects on habitat distribution, dispersal barriers and the evolution of provinciality. To assess marine provinciality through the Phanerozoic, here we (a) simulate provinces based on palaeogeographic reconstructions and global climate models and (b) contrast them with empirically derived provinces that we define using network analysis of fossil occurrences. Simulated and empirical patterns match reasonably well and consistently suggest a greater than 15% increase in provinciality since the Mesozoic era. Although both factors played a role, the simulations imply that the effect of the latitudinal temperature gradient has been twice as important in determining marine provinciality as continental configuration.
CRIS-Team WoS Importer:2021-09-03

Increase of island endemism with altitude - speciation processes on oceanic islands - Steinbauer, Manuel; Otto, Rüdiger; Naranjo-Cigala, Augustin; Beierkuhnlein, Carl; Fernández-Palacios, José Maria (Ecography, 2012)
Understanding speciation on oceanic islands is a major topic in current research on island biogeography. Within this context, it is not an easy task to differentiate between the influence of elevation as an indicator for habitat diversity and island age as an indicator for the time available for diversification. One reason for this is that erosion processes reduce the elevation of islands over time. In addition, the geographic distance to source ecosystems might differ among habitats, which could lead to habitat-specific reduction of species immigration, niche occupation and diversification. We used the percentage of single island endemic species (pSIE) in five different zonal ecosystems (distributed in altitude) on the Canary Islands as an indicator for diversification. We tested whether diversification increases with altitude due to a greater ecological isolation of high elevation ecosystems on oceanic islands under the assumption of a low elevation source region on the mainland. In addition we tested whether the ‘hump-shaped’ (unimodal) relationship between pSIE and island age as well as the linear relationship between species richness and pSIE is consistent across spatial scales. We also analyse a potential influence of island area and habitat area. We found that pSIE increases with elevation. The relations between species richness as well as age with pSIE are consistent across scales. We conclude that high elevation ecosystems are ecologically isolated. Surprisingly, the altitudinal belt with the strongest human influences has the highest values of pSIE. We successfully transfer the ‘general dynamic theory of island biogeography’ to the ecosystem scale, which provides multiple opportunities for future studies. With this approach we find that the effects of elevation on diversification can be separated from those of island age.

Increasing the equitability of data citation in paleontology: capacity building for the big data future - Smith, Jansen A.; Raja, Nussaïbah Begum; Clements, Thomas; Dimitrijevic, Danijela; Dowding, Elizabeth; Dunne, Emma; Gee, Bryan M.; Godoy, Pedro L.; Lombardi, Elizabeth M.; Mulvey, Laura; Nätscher, Paulina; Reddin, Carl J.; et al. (Paleobiology, 2023)
Data compilations expand the scope of research; however, data citation practice lags behind advances in data use. It remains uncommon for data users to credit data producers in professionally meaningful ways. In paleontology, databases like the Paleobiology Database (PBDB) enable assessment of patterns and processes spanning millions of years, up to global scale. The status quo for data citation creates an imbalance wherein publications drawing data from the PBDB receive significantly more citations (median: 4.3 ± 3.5 citations/year) than the publications producing the data (1.4 ± 1.3 citations/year). By accounting for data reuse where citations were neglected, the projected citation rate for data-provisioning publications approached parity (4.2 ± 2.2 citations/year) and the impact factor of paleontological journals (n = 55) increased by an average of 13.4% (maximum increase = 57.8%) in 2019. Without rebalancing the distribution of scientific credit, emerging “big data” research in paleontology—and science in general—is at risk of undercutting itself through a systematic devaluation of the work that is foundational to the discipline.<br
Keywords: Biodiversity; Open science; Paleobiology Database; Specimen-based; Taxonomy

Influence of different CA2/CA-ratios on hydration degree, AH3 content and flexural strength investigated for a binder formulation of calcium aluminate cement with calcite - Goergens, Julian; Belli, Renan; Schulbert, Christian; Götz-Neunhoeffer, Friedlinde (Cement and Concrete Research, 2023)
The study was aimed to investigate the influence of the CA2/CA-ratio in an application-orientated binder formulation of calcium aluminate cement (CAC) with calcite. Six mixtures containing varying fractions of two calcium aluminate cements with different CA2- and CA contents, calcite and additives were investigated after 1, 7 and 28 d at 23 °C. By means of QXRD the hydration degrees of CA2 and CA, as well as hydrate phase contents, especially AH3, were determined and correlated with the mechanical response under biaxial flexural stress and pore size distribution using micro-computed tomography (μCT) of three contrastive mixtures. The strength values increase slightly up to a CA2/CA ratio of 70:30, above this ratio the mechanical properties deteriorate significantly. The macro-porosity acting as strength-limiting defects correlate well with this threshold, though not the content of AH3 or the degree of hydration of CA.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Bending strength(C); CaCO; Calcium aluminate cement (D); Hydration (A); X-ray diffraction (B)

Influence of tree hollow characteristics on saproxylic beetle diversity in a managed forest - Schauer, Bastian; Steinbauer, Manuel; Vailshery, Lionel; Müller, Jörg; Feldhaar, Heike; Obermaier, Elisabeth (Biodiversity and Conservation, 2018)
Tree hollows are key structures in forest ecosystems constituting long-lasting habitats and nutritional resources for many saproxylic arthropod species. Due to diverse microhabitat structures and conditions in tree hollows, they can support a broad range of species. However, in the past intensive management practices in parts of Europe reduced the abundance of tree hollows, resulting in a decrease and endangerment of species specialised in this tree habitat. We investigated 40 beech trees with hollows in 2014 and a subset of 23 of these trees in 2015 in a managed forest landscape in Germany. Using emergence traps we collected 89 beetle species of which 33% were on the Bavarian Red List. We described the tree characteristics, physical hollow characteristics, and their surrounding environment investigating their influence on α-diversity of non-Red List and Red List species. Furthermore, we investigated spatial (between tree hollows) and temporal (same tree hollow but different years) β-diversity, considering the importance of turnover and nestedness components on β-diversity. α-Diversity decreased with increasing decomposition of wood mould and increased with increasing area of hollow entrance in both years. Additional characteristics differed between years and between non-Red List and Red List species. β-Diversity was related to diameter at breast height, number of surrounding tree hollows, area of hollow entrance and a temperature gradient. We found a higher species turnover than nestedness between tree hollows and between years, indicating highly dynamic beetle communities spatially as well as temporally. To support and maintain the diversity of saproxylic beetles inhabiting tree hollows, the heterogeneity of microhabitats is important and should be supported by maintaining the diversity of differently structured and sized tree hollows.

Instantiations of Multiscale Kinship in Pressing‐Defect Distributions in Yttria‐Stabilized Zirconias by Powder Partitioning - Pereira, Raíssa Monteiro; Lohbauer, Ulrich; Schulbert, Christian; Göken, Mathias; Wurmshuber, Michael; Campos, Tiago Bastos Moreira; Thim, Gilmar Patrocínio; Mieller, Björn; Belli, Renan (Advanced Engineering Materials, 2024)
Modern dry pressing of ceramic powders using spray-dried granulates cannot avoid the occurrence of defects related to persisting inter- and intra-granulate interstitial voids. These constitute the parent defect size population limiting the application of polycrystalline ceramics in high-stress conditions. The mitigation of such defects could widen the range of application in technical and biomedical engineering, reduce the safety range for design, and extend the lifetime of components. Herein, the Weibull size-effect on strength in size-partitioned Yttria-stabilized zirconias (YSZ) feedstocks is used to explore the viability of changing the density distribution of granulate sizes as an effective strategy to obtain a denser particle packing that could reduce the size distribution of strength-limiting pressing defects. In a direct assessment of critical defect size using multiscale strength testing with a dataset of ≈1300 values, the success of such an approach in increasing the strength reliability for small volume components is demonstrated, along with its ultimate failure in altering the defect size distribution in sintered YSZ ceramics across several length scales. Finally, it is shown that granule morphology (spherical or dimpled) fails to affect the defect density and size distribution in YSZ ceramics.<br
Keywords: powder processing; pressing defects; strength; Weibull statistics; zirconia ceramics

Integrated bio- and lithofacies analysis of coarse-grained, tide-dominated deltaic environments across the Cretaceous/Paleogene boundary in Patagonia, Argentina - Scasso, R. A.; Aberhan, M.; Ruiz, L.; Weidemeyer, S.; Medina, F. A.; Kießling, Wolfgang (Cretaceous Research, 2012)
Four facies associations representing, from sea to land, namely (1) tidal bars in distal delta front, (2) proximal tidal bar complexes, (3) tidal channel and tidal flat deposits, and (4) multi-episodic, tide-influenced channels, resulted from the bio- and lithofacies analysis of the siliciclastic Cretaceous/Paleogene Lefipán Formation (Patagonia, Argentina). Lithofacies analysis indicates the existence of coarse-grained, tide-dominated deltas fed with sediments of braided rivers, a rare type of delta that was developed at the western margin of a large marine embayment during the Cretaceous/Paleogene (K/Pg) boundary interval. Differences in taxonomic composition and ecological structure of the biofacies revealed variations in environmental factors, with salinity exerting the principal influence on biofacies. Salinity varied from oligohaline and mesohaline in the deltaic, high-stress environments, as typified by monospecific bivalve assemblages, to diverse and trophically more complex associations, indicating more normal marine and stable conditions. Thus, the biofacies provided an independent tool to check the results of the lithofacies analysis in complex transitional environments. A comparison of Maastrichtian and Danian faunas suggests that the K/Pg boundary event disrupted the stable Maastrichtian communities via the extinction of dominating species, leading to less diverse but more varied Danian assemblages. A shift in trophic structure to increased percentages of deposit-feeders in the Danian was not a direct consequence of impact-related environmental perturbations at the boundary in the studied onshore environment. This contrasts with previous studies of siliciclastic offshore settings, where such a shift in trophic composition was interpreted as the consequence of a productivity crisis at the boundary. © 2012 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.integr
Keywords: Biofacies; K/Pg; Lithofacies; Patagonia; Salinity; Tide-dominated delta

Integrating Fossil Observations Into Phylogenetics Using the Fossilized Birth-Death Model - Wright, April M.; Bapst, David W.; Barido-Sottani, Joelle; Warnock, Rachel (Annual Review of Ecology Evolution and Systematics, 2022)
Over the past decade, a new set of methods for estimating dated trees has emerged. Originally referred to as the fossilized birth-death (FBD) process, this single model has expanded to a family of models that allows researchers to coestimate evolutionary parameters (e.g., diversification, sampling) and patterns alongside divergence times for a variety of applications from paleobiology to real-time epidemiology. We provide an overview of this family of models. We explore the ways in which these models correspond to methods in quantitative paleobiology, as the FBD process provides a framework through which neontological and paleontological approaches to phylogenetics and macroevolution can be unified. We also provide an overview of challenges associated with applying FBD models, particularly with an eye toward the fossil record. We conclude this review by discussing several exciting avenues for the inclusion of fossil data in phylogenetic analyses.
CRIS-Team WoS Importer:2022-12-30

Interactions of zinc(II) complexes with 5′-GMP and their cytotoxic activity - Soldatovic, Tanja V.; Selimovic, Enisa; Smit, Biljana; Asanin, Darko; Planojevic, Nevena S.; Markovic, Snezana D.; Puchta, Ralph; Alzoubi, Basam M. (Journal of Coordination Chemistry, 2019)
The mechanism of substitution from tetrahedral [ZnCl 2 (en)] and square-pyramidal [ZnCl 2 (terpy)] complexes (where en = 1,2-diaminoethane or ethylenediamine and terpy = 2,2′:6′,2′′-terpyridine) by guanosine-5′-monophosphate (5′-GMP) have been investigated by 1 H NMR spectroscopy. The substitution reaction of [ZnCl 2 (terpy)] complex is faster than the reaction of [ZnCl 2 (en)], which was finished after 48 h. Information about the structures of the final products in solution were obtained from the DFT calculations (B3LYP/6-31G(d)) and experimental 1 H NMR data acquired during the course of the reaction. The cytotoxic activity of zinc(II) complexes was tested on human breast cancer cell line MDA-MB-231, human colon cancer cell line HCT-116 and normal human lung fibroblast cell line MRC-5. Both complexes reduced cell viabilities, while [ZnCl 2 (terpy)] was significantly cytotoxic on MDA-MB-231 after 72 h, and HCT-116 after 24 h without dose dependence. The differences in reactivity toward 5′-GMP and cytotoxic activity of Zn(II) complexes may be attributed to the very stable square-pyramidal geometry of [ZnCl 2 (terpy)] in solution, while weak ligand effect of the en compared to the terpy affected slow interaction of tetrahedral [ZnCl 2 (en)] complex with the target bio-molecule.
CRIS-Team Scopus Importer:2019-05-17
Keywords: 1H NMR; anticancer cytotoxic activity; DFT calculations; guanosine-5′-monophosphate; structure-reactivity correlation; Zinc(II) complexes

International Symposium on Early Palaeozoic Plaeogeography and Palaeoclimate, September 2004, Erlangen, Germany - Abstracts and Field Guides - Munnecke, Axel; Servais, Thomas; Schulbert, Christian; et al. (2004)
Keywords: Symposium; Early Palaeozoic; Palaeogeography; Palaeoclimate

Interplay of Autogenic and Allogenic Processes On the Formation of Shallow Carbonate Cycles in a Synrift Setting (Lower Pliensbachian, Traras Mountains, NW Algeria) - Belkhedim, Salim; Jarochowska, Emilia; Benhamou, Miloud; Nemra, Abdelkrim; Sadji, Radouane; Munnecke, Axel (Journal of Sedimentary Research, 2019)
Meter-scale shallowing-upward cycles are recorded in many carbonate successions around the world. It is often difficult to recognize whether they represent autocycles, formed through intrinsic controls, or allocycles, resulting from orbital forcing or tectonic movements, or both. Here, we review the criteria used in the identification of the two types of cyclicity and apply them to two newly described lower Pliensbachian outcrops in the Traras Mountains, northwestern Algeria. Throughout the investigation of six sections, the deposits are suggested to have formed in intertidal-supratidal to shallow subtidal environments on a tropical ramp in the Western Tethys. In this area, shallowing-upward small-scale peritidal and subtidal cycles have been shown to be, and are assumed to be, ordered. The carbon isotope data mirror the recorded cycles and indicate different lengths of subaerial exposures. These cycles, in a developed within synrift setting, have been interpreted as produced mainly by autocyclic processes, but interacting with allocyclic factors. Peritidal cycles are thought to be generated by progradation of intertidal and supratidal flats into lagoonal sediments, while subtidal cycles are interpreted to have been controlled by lateral migration of shoals. The impact of the minor fluctuations of eustatic sea level is weakly marked, and only long subaerial exposure can reveal the contribution of these fluctuations to the formation of the recorded cycles. Tectonic movements resulting from spreading of the Tethys arc interpreted to have controlled cycle distribution and thickness at a regional scale. However, synsedimentary tectonic features are rare in the studied area; this suggests that sediment transport would control the thickness and duration of cycles instead of the rate at which accommodation was created.
CRIS-Team WoS Importer:2019-09-20

Intraspecific variability through ontogeny in early ammonoids - de Baets, Kenneth; Klug, Christian; Monnet, Claude (Paleobiology, 2013)
Mollusks in general and ammonoids in particular are known to display a sometimes profound morphological intraspecific variability of their shell. Although this phenomenon is of greatest importance, it has rarely been investigated and quantified. It is especially crucial for taxonomy and incidentally for biodiversity analyses to account for it, because otherwise, the number of described species might exceed that of actual species within any group. Early ammonoids (Early Devonian, Paleozoic) typically suffer from this bias. For instance, most specimens from the same layer and the same region (e.g., the Erbenoceras beds of the Moroccan eastern Anti-Atlas studied here) differ morphologically from each other. Depending on the importance given to certain morphological characters, therefore, one could create a new species for almost every specimen. In this study, we measured nearly 100 such specimens from a restricted stratigraphic interval and quantified their intraspecific variability. There is a variable but strong overlap of the quantified shell characters at most ontogenetic stages, and only two species are here separated rather than the four previously recognized in Morocco. When ontogenetic trajectories of the Moroccan specimens are compared with coeval faunas from other regions (assigned to other species), a strong overlap between the morphospaces occupied by these taxa becomes apparent. The justification of some of these latter species is thus questionable even if their mean values in some conch parameters differ considerably from the mean values of the Moroccan species. Hence, the number of currently valid species of these loosely coiled early ammonoids is probably much too high. Extreme caution must therefore be taken when examining the diversity of groups in which the intraspecific variability is poorly known.

Isotopic niches of sympatric Gentoo and Chinstrap Penguins: evidence of competition for Antarctic krill? - Dimitrijevic, Danijela; Paiva, Vitor H.; Ramos, Jaime A.; Seco, José; Ceia, Felipe R.; Chipev, Nesho; Valente, Tiago; Barbosa, Andrés; Xavier, José C. (Polar Biology, 2018)
As climate change, among other factors, is increasingly affecting Antarctic marine systems, competition for price may increase between predators, particularly in the Antarctic Peninsula which has warmed more than elsewhere. Under such a context, we tested the feeding and trophic ecology of Gentoo ( Pygoscelis papua ) and Chinstrap ( Pygoscelis antarctica ) penguins breeding in sympatry at Livingston Island (Antarctic Peninsula) in a single season. We compared the diets of adults (from faecal samples, and stable isotopes in feathers and blood) and chicks (from stomach contents, and stable isotopes in down feathers, toenails and muscles of chicks that had died of unknown causes). Antarctic krill Euphausia superba dominated the diet of both species, although Gentoo Penguins fed on larger Antarctic krill than did Chinstrap Penguins. Stable isotope analyzes of adult tissues revealed that both species fed at different niches in successive years, as depicted by the different levels δ 13C in feathers (showing values ​​from the previous breeding season) and whole blood (showing values ​​from the current season). Tissues collected from chicks confirmed their diet over different time scales (ie days to weeks): Gentoo Penguins fed at a higher trophic level (possibly due to a more varied diet) and in different habitats than Chinstrap Penguins, providing evidence of isotopic niche separation of penguins. Our results may be relevant to the monitoring programs of the Convention on the Conservation of Antarctic Marine Living Resources (CCAMLR) and suggest that adult scats, and stomach contents and tissues of recently died chicks, can be used in such programs.<br

Jurassic shift from abiotic to biotic control on marine ecological success - Eichenseer, Kilian; Balthasar, Uwe; Smart, Christopher W.; Stander, Julian; Haaga, Kristian A.; Kießling, Wolfgang (Nature Geoscience, 2019)
Environmental change and biotic interactions both govern the evolution of the biosphere, but the relative importance of these drivers over geological time remains largely unknown. Previous work suggests that, unlike environmental parameters, diversity dynamics differ profoundly between the Palaeozoic and post-Palaeozoic eras. Here we use the fossil record to test the hypothesis that the influence of ocean chemistry and climate on the ecological success of marine calcifiers decreased throughout the Phanerozoic eon. Marine calcifiers build skeletons of calcite or aragonite, and the precipitation of these calcium carbonate polymorphs is governed by the magnesium-to-calcium ratio and temperature in abiotic systems. We developed an environmental forcing model based on secular changes of ocean chemistry and temperature and assessed how well the model predicts the proliferation of skeletal taxa with respect to calcium carbonate polymorphs. Abiotic forcing governs the ecological success of aragonitic calcifiers from the Ordovician to the Middle Jurassic, but not thereafter. This regime shift coincides with the proliferation of calcareous plankton in the mid-Mesozoic. The deposition of biomineralizing plankton on the ocean floor buffers CO2 excursions and stabilizes Earth’s biochemical cycle, and thus mitigates the evolutionary impact of environmental change on the marine biota.
CRIS-Team Scopus Importer:2019-07-16

Kalk-Mergel-Wechselfolgen - Ein Blick hinter die Kulissen - Munnecke, Axel (Geowissenschaftliche Mitteilungen, 2016)
Keywords: Kalk-Mergel-Wechselfolgen; Kalk; Mergel; Diagenese; Kompaktion

Keratose sponges in ancient carbonates – A problem of interpretation - Neuweiler, Fritz; Kershaw, Stephen; Boulvain, Frédéric; Matysik, Michał; Sendino, Consuelo; McMenamin, Mark; Munnecke, Axel (Sedimentology, 2022)
Reports of diverse vermiform and peloidal structures in Neoproterozoic to Mesozoic open marine to peritidal carbonates include cases interpreted to be keratose sponges. However, living keratose sponges have elaborate, highly elastic skeletons of spongin (a mesoscopic end-member of a hierarchical assemblage of collagenous structures) lacking spicules, thus have poor preservation potential in contrast to the more easily fossilized spicule-bearing sponges. Such interpreted fossil keratose sponges comprise diverse layered, network, amalgamated, granular and variegated microfabrics of narrow curved, branching, vesicular–cellular to irregular areas of calcite cement, thought to represent former spongin, embedded in microcrystalline to peloidal carbonate. Interpreted keratose sponges are presented in publications almost entirely in two-dimensional (thin section) studies, usually displayed normal to bedding, lacking mesoscopic three-dimensional views in support of a sponge body fossil. For these structures to be keratose sponges critically requires conversion of the spongin skeleton into the calcite cement component, under shallow-burial conditions and this must have occurred prior to compaction. However, there is no robust petrographic–geochemical evidence that the fine-grained carbonate component originated from sponge mummification (automicritic body fossils via calcification of structural tissue components) because in the majority of cases the fine-grained component is homogenous and thus likely to be deposited sediment. Thus, despite numerous studies, verification of fossil keratose sponges is lacking. Although some may be sponges, all can be otherwise explained. Alternatives include: (i) meiofaunal activity; (ii) layered microbial (spongiostromate) accretion; (iii) sedimentary peloidal to clotted micrites; (iv) fluid escape and capture resulting in bird's eye to vuggy porosities; and (v) moulds of siliceous sponge spicules. Uncertainty of keratose sponge identification is fundamental and far-reaching for understanding: (i) microfacies and diagenesis where they occur; (ii) fossil assemblages; and (iii) wider aspects of origins of animal clades, sponge ecology, evolution and the systemic recovery from mass extinctions. Thus, alternative explanations must be considered.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Automicrite; metazoan evolution; microfacies analysis; mummification; sponge taphonomy

Kinetics, mechanism and density functional theory calculations on base hydrolysis of α-amino acid esters catalyzed by [Pd(AEMP)(H2O)2]2+ (AEMP = 2-(2-aminoethyl)-1-methylpyrrolidine) - Shoukry, Mohamed M.; Shehata, Mohamed R.; Ragab, Mona S.; Ćorćić, Dušan; Puchta, Ralph; van Eldik, Rudi (Reaction Kinetics Mechanisms and Catalysis, 2020)
Abstract: Pd(AEMP)Cl2 (AEMP = 2-(2-aminoethyl)-1-methylpyrrolidine) was synthesized and characterized by spectral and thermal measurements.[Pd(AEMP)(H2O)2]2+ reacts with amino acid esters (L) to form mixed ligand [Pd(AEMP)L]2+ complexes. The kinetics of the base hydrolysis of [Pd(AEMP)L]2+ was studied by a pH-stat technique and the corresponding rate constants are reported. The coordinated glycine methyl ester is hydrolyzed efficiently, whereas the coordinated methionine- and histidine- methyl esters undergo hydrolysis with a much lower catalytic activity. The catalytic effect is controlled by the mode of coordination of the ester to the Pd(II) complex. Possible mechanisms for these reactions are considered. Activation parameters were determined experimentally for the hydrolysis of the coordinated glycine methyl ester. DFT calculations (B3LYP/def2svp) were applied to gain further insight into the possible mechanism of the base hydrolysis of the amino acid esters. The calculations are discussed in reference to the reported experimental data. Graphic abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-02-25
Keywords: 2-(2-Aminoethyl)-1-methylpyrrolidine; Amino acid ester; Catalytic hydrolysis; DFT calculations; Pd(II); pH-stat technique

Klimawandel und Veränderung der Biodiversität in der Erdgeschichte. - Königshof, Peter; Suttner, Thomas J; Kießling, Wolfgang (Natur, Forschung, Museum, 2012)
Keywords: Climate change; Biodiversity; Evolution; Extinction

Krisen als Chance: Lernen aus der Evolution - Kießling, Wolfgang (Darwin meets Business, 2010)
Keywords: Extinctions; Biodiversity; Applied Paleobiology

Last Glacial deep water corals from the Red Sea - Taviani, Marco; López Correa, Matthias; Zibrowius, Helmut; Montagna, Paolo; McCulloch, Malcolm; Ligi, Marco (Bulletin of Marine Science, 2007)
The present Red Sea deep-sea benthos appears impoverished with respect to the adjacent Indian mother-ocean as a result of severe filters, represented by an extremely shallow sill, high salinity, and high temperature. Today, the Red Sea basin hosts a still poorly known deep-water coral fauna of Indian Ocean affinity. During the Pleistocene, conditions were at times suitable as proven by the findings of last glacial corals (Javania insignis Duncan, 1876, and Trochocyathus virgatus sensu Marenzeller, 1907 (not Alcock, 1902), and, possibly, Guynia annulata Duncan, 1872) from seamounts in the north-central part of the basin. A subfossil J. insignis from the Coral Sea peak has been U-series-dated at 26,590 ± 120 yrs. This represents the first documentation regarding the presence of deep-water corals in the Red Sea during the late Pleistocene and predates the postulated basin-wide extinction of normal marine biota that took place at the Last Glacial Maximum. © 2007 Rosenstiel School of Marine and Atmospheric Science of the University of Miami.
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LP.lastgl

Late Jurassic fishes from Longing Gap, Antarctic Peninsula - Arratia, Gloria; Scasso, R. A.; Kießling, Wolfgang (Journal of Vertebrate Paleontology, 2004)
Few records of Late Jurassic fishes have been reported previously from Antarctica. They include an indeterminate teleost from the Ameghino (Nordenskjöld) Formation at Longing Gap and two incomplete aspidorhynchiforms from James Ross Island, all of presumed Late Jurassic age. New fish material recently recovered in the Upper Jurassic of Longing Gap is described. The new material consists of one piece of body squamation, which, based on the structure of the scales, corresponds to a new genus and species (Ameghinichthys antarcticus gen. et sp. nov.) of an indeterminate actinopterygian family; one aspidorhynchiform identified as Vinctifer sp. due to the structure and distribution of the scales; and numerous specimens of a new ichthyodectiform, Antarctithrissops seymouri gen. et sp. nov. This new genus differs from European ichthyodectiforms in the shape of the preopercle, the presence of long sensory preopercular branches almost reaching the posterior margin of the bone, and the uncommon structure of the scales, with a fine layer of bone obscuring the circuli. The presence of Vinctifer in the Antarctic is consistent with its other Gondwanan records. The Ichthyodectiformes, previously known from four European genera, extends the distribution of the group to the southernmost part of the Southern Hemisphere during the Late Jurassic. In contrast to most non-teleostean fishes, the known Late Jurassic teleosts apparently are species endemic to restricted areas in the Southern Hemisphere. © 2004 by the Society of Vertebrate Paleontology.
UnivIS-Import:2015-03-09:Pub.2004.nat.dgeo.IGM.LP.lateju

Late Jurassic (Oxfordian-Kimmeridgian) brachiopods of the El Bayadh Area (Central Saharan Atlas, Algeria): biostratigraphy, stratigraphic revision, Paleobiogeography and paleoecology - Mahboubi, Chikh Younes; Radulovic, Barbara V.; Ouali Mehadji, Abdelkader; Ayoub-Hannaa, Wagih; Munnecke, Axel (Historical Biology, 2021)
The Upper Jurassic rocks of the El Bayadh Area (Central Saharan Atlas, Algeria) are composed of mixed siliciclastic-carbonate rocks, which were roughly assigned to a Kimmeridgian-Hauterivian age in previous studies. Based on our studies, the succession can be subdivided into five new formations; from base to top: the Theniet Et-Temar, Ksel, Laguremi, Boualem, and the Sfissifa formations. Brachiopod faunas have been recorded from two levels. The lower one is located in the Theniet Et-Temar Formation, and the upper one in the Sfissifa Formation. Two brachiopod species Lacunosella (Lacunosella) arolica and Moeschia alata from the first level and Xestosina arguta from the second level have been recorded for the first time not only in Algeria but also in Africa. Based on the new findings, the age of the studied section can be restricted to the middle Oxfordian at the base and to the upper Kimmeridgian at the top. The stratigraphic successions between the two levels (70 m) are nearly barren except for dinosaur footprints, which were tentatively assigned to a Lower Cretaceous age by previous workers. However, this succession can be attributed to an upper Oxfordian-lower Kimmeridgian age now based on its brachiopod faunas.
CRIS-Team WoS Importer:2021-02-05

Late Jurassic radiolarians from the Antarctic Peninsula - Kießling, Wolfgang (Micropaleontology, 1999)
Radiolarian faunas from the type section of the mostly Late Jurassic Ameghino Formation (= Nordenskjold Formation) on the Antarctic Peninsula (Longing Gap, northern Graham Land) are described taxonomically, analyzed stratigraphically and interpreted paleoecologically, based on quantitative observations. Three hundred and fifty-nine species have been discovered in total; some two hundred of them are probably new. Twenty-eight new species and three new subspecies are described. The most abundant and characteristic species are used to present a regional radiolarian stratigraphy. The radiolarian faunas show distinct high-latitude characteristics. They are demarcated by high abundances of Parvicingula s.1. and spongy spumellarians, whereas Tethyan taxa like Mirifusus, Ristola, Tethysetta, Tritrabs, Syringocapsidae, Spongocapsulidae, and Xitidae are absent or very rare. The average diversity is high, but significantly lower than in coeval Tethyan samples. Cluster analysis reveals a major change in faunal composition near the early-late Tithonian boundary. The characteristics of the Antarctic radiolarian faunas allow an Austral Province to be defined extending from circum-Antarctica to northeast Australia. The Austral radiolarian province is similar to the Northern Tethys and Southern Boreal Provinces sensu Pessagno and Blome (1986), but exhibits some differences. The new data allow the biogeographic scheme of Pessagno and Blome (1986) to be revised and permit the introduction of a preliminary global paleobiogeographic map for the Tithonia
UnivIS-Import:2015-03-05:Pub.1999.nat.dgeo.IGM.LP.lateju

Late Jurassic temperatures for the southern Tethyan margin based on belemnites δ18O from the Ouarsenis Mountains, northwestern Algeria - Sadji, Radouane; Munnecke, Axel; Benhamou, Miloud; Alberti, Matthias; Belkhedim, Salim; Ramdane, Nabil (Palaeogeography, Palaeoclimatology, Palaeoecology, 2021)
This study presents the first record of stable carbon and oxygen isotopes of well-preserved belemnites and bulk sediment from the Upper Jurassic pelagic carbonates of the Ouarsenis Mountains (northwestern Algeria), which were deposited at the southern margin of the Tethys ocean. Cathodoluminescence and scanning electron microscopy was used to eliminate potentially diagenetically altered specimens (brachiopods, aptychi, and some belemnites). Ultimately, 55 belemnite specimens were used to reconstruct water temperatures for the Middle Oxfordian to the Early Tithonian. Their δ18Ocarb values ranged from −0.35‰ to −3.88‰, suggesting warm and mostly stable temperature conditions during the Late Jurassic. Using a δ18Osea value of 0‰ for the tropical palaeolatitude of 15–20°N, the δ18Ocarb values of the well-preserved belemnite rostra translate into average temperatures of 27.8 °C in the Middle Oxfordian (Gregoryceras transversarium Zone), 27.0 to 27.5 °C in the Late Oxfordian (Epipeltoceras bimmamatum and Idoceras planula zones, respectively), 26.2 °C in the Early Kimmeridgian, and 27.3 °C in the Early Tithonian (Hybonoticeras hybonotum Zone).
CRIS-Team Scopus Importer:2021-01-29
Keywords: Bulk sediment; Palaeoclimate; Pelagic carbonates; Stable isotopes; Tropical palaeolatitude

Late Jurassic (Volgian) radiolarians from Central Spitsbergen - A preliminary study - Nakrem, Hans Arne; Kießling, Wolfgang (Norwegian Journal of Geology, 2012)

Late Ordovician microbial reefs in the Lianglitag Formation (Bachu, Tarim, NW China) - Zhang, Yuanyuan; Li, Yue; Munnecke, Axel (Facies, 2014)
Reefs in the Late Ordovician are usually built up by metazoans, whereas in the Early and Middle Ordovician microbial reefs are dominating. In the Late Ordovician (Katian) Lianglitag Formation, at Bachu, Tarim, NW China, however, three distinct stages of thrombolithic microbial reefs are exposed. The lower and upper reef intervals are characterized by widespread microbial carbonates with almost constant thicknesses (biostromes). The middle reef interval exposes dome-like mounds, and shows a higher diversity of reef-building and reef-dwelling organisms. Calcareous algae such as Vermiporella are abundant, but also other components such as fragments of Halysis, brachiopods, molluscs, echinoderms, bryozoans, and trilobites have been found in the microbial reef units. The purpose of this study is to describe for the first time the composition and microfacies of the reefs in this remote area. Especially the question of whether or not these Late Ordovician reefs represent remnants of the Early/Middle Ordovician microbial-dominated reef type just lacking Calathium and lithistid sponge is addressed. The results indicate that the local conditions on the leeward side of the carbonate platform, where waters are less well agitated and thus less well oxygenated, and probably also characterized by temporarily elevated water temperatures hampering the growth of metazoan reefs, were responsible for the proliferation of the Late Ordovician microbial reefs in the Bachu area. © 2014 Springer-Verlag Berlin Heidelber
Keywords: Biotic structures; Katian; Late Ordovician; Microbial reefs; NW China; Tarim

Late Paleozoic and Late Triassic limestones from North Palawan Block (Philippines): Microfacies and paleogeographical implications - Kießling, Wolfgang; et al. (Facies, 2000)
Selected Late Paleozoic and Triassic limestone exposures were studied on northern Palawan Island, Philippines, with regard to microfacies, stratigraphy and facies interpretation. Although some of the outcrops were already reported in literature, we present the first detailed microfacies study. Late Paleozoic carbonates in the El Nido area are represented by widley distributed Permian and locally very restricted Carboniferous limestones. Of particular interest is the first report of Carboniferous limestones in the Philippines dated by fossils. Fusulinids indicate a 'Middle' Carboniferous (Moscovian-Kasimovian) age of the Paglugaban Formation only known from Paglugaban Island. The Permian Minilog Formation consists mostly of fusulinid wackestones and dasycladacean wacke-/packstones. Fusulinid datings (neoschwagerinids and verbeekinids) provide a Guadalupian (Wordian-Capitanian) age. The depositional setting of the Middle Permian carbonates corresponds to a distally steepened ramp with biostromes built by alatoconchid bivalves locally associated with richthofeniid brachiopods. Late Triassic limestones occur in isolated exposures on and around Busuanga Island (Calamian Islands). The age of the investigated carbonates is Rhaetian based on the occurrence of Triasina hantkeni Majzon. Microfacies data indicate the existence of reefs (Malajon Island) and carbonate platforms (Kalampisanan Islands, Busuanga Island, Coron Island). Reef boundstones are characterized by abundant solenoporacean red algae, coralline sponges and corals. Platform carbonates yield a broad spectrum of microfacies types, predominantly wacke- and packstones with abundant involutinid foraminifera and some calcareous algae. These facies types correspond to platform carbonates known from other parts of Southeast Asia (Eastern Sulawesi and Banda Basin; Malay Peninsula and Malay Basin). The Philippine platform carbonates were deposited on and around seamounts surrounded by deeper water radiolarian cherts. The new data on facies and age of the Philippine Permian and Triassic carbonates contradict a close paleogeographical connection between the North Palawan Block and South China and arise problems for the currently proposed origin of the North Palawan Block at the paleomargin of South China. We hypothesize that North Palawan was part of the Indochina Block during the Carboniferous and Permian, separated from the Indochina Block during the Middle Permian and collided with the South China Block in the Late Cretaceous.
UnivIS-Import:2015-03-09:Pub.2000.nat.dgeo.IGM.LP.latepa
Keywords: Carbonate ramps and platforms; Carboniferous; Late Triassic; Microfacies analysis; Middle Permian; Paleogeography; Philippines (Palawan); Reefs

Late Pennsylvanian fishes from the Finis Shale of North-Central Texas - Ivanov, Alexander; Seuß, Barbara (54th Annual Meeting, South-Central Section of the GSA, 2020)
The fossil-rich deposits from the Finis Shale (Graham Formation) at the "spillway section" near Jacksboro (North-Central Texas) are dated as early Virgilian (early Gzhelian; Late Pennsylvanian) in age. The Finis Shale is part of a cyclothem and represents the shallowing upwards sequence at this outcrop. The shale deposits are capped by phylloid algae and fusulinid carbonates of the Jacksboro Limestone. Various chondrichthyan macroremains such as Glikmanius, Orodus, Campyloprion, or Petalodus are known from these deposits. A diverse assemblage of fish microremains is now discovered in and described from the Finis Shale deposits. The micro-fossil assemblage includes numerous chondrichthyan teeth and scales, while acanthodian scales and actinopterygian teeth and scales are rare. The chondrichthyan microremains are taxonomically more diverse and represented by teeth of the bransonelliform Bransonella nebraskensis Johnson, by the symmoriiform Denaea cf. williamsi Ginter et Hansen, and yet undetermined stethacanthids. The ctenacanthiforms Heslerodus divergens (Trautschold) and Glikmanius sp., sphenacanthid euselachians, the neoselachian Cooleyella amazonensis Duffin, Richter et Neis, the petalodontids Euglossodus sp. and cf. Tanaodus sp., and eugeneodontid remains are also preserved. Symmoriiform denticles and chondrichthyan scales of various types are also found. The new occurrence of fishes demonstrates the presence of chondrichthyan taxa with different food specialization in the early Virgilian faunal communit

Late quaternary climate change shapes island biodiversity - Weigelt, Patrick; Steinbauer, Manuel; Cabral, Juliano; Kreft, Holger (Nature, 2016)
Island biogeographical models consider islands either as geologically static with biodiversity resulting from ecologically neutral immigration–extinction dynamics1, or as geologically dynamic with biodiversity resulting from immigration–speciation–extinction dynamics influenced by changes in island characteristics over millions of years2. Present climate and spatial arrangement of islands, however, are rather exceptional compared to most of the Late Quaternary, which is characterized by recurrent cooler and drier glacial periods. These climatic oscillations over short geological timescales strongly affected sea levels3,4 and caused massive changes in island area, isolation and connectivity5, orders of magnitude faster than the geological processes of island formation, subsidence and erosion considered in island theory2,6. Consequences of these oscillations for present biodiversity remain unassessed5,7. Here we analyse the effects of present and Last Glacial Maximum (LGM) island area, isolation, elevation and climate on key components of angiosperm diversity on islands worldwide. We find that post-LGM changes in island characteristics, especially in area, have left a strong imprint on present diversity of endemic species. Specifically, the number and proportion of endemic species today is significantly higher on islands that were larger during the LGM. Native species richness, in turn, is mostly determined by present island characteristics. We conclude that an appreciation of Late Quaternary environmental change is essential to understand patterns of island endemism and its underlying evolutionary dynamics.

Late Wenlock carbon isotope excursions and associated conodont fauna in the Podlasie Depression, eastern Poland: a not-so-big crisis? - Jarochowska, Emilia; Munnecke, Axel (Geological Journal, 2016)
The middle Silurian ‘big crisis’ refers to a graptolite extinction event and faunal turnover at the onset of a double-peaked positive carbon isotope excursion. The crisis has been proposed to affect conodonts, giving rise to a sophisticated palaeoecological model of their stepwise extinction, known as the Mulde Event. However, the impact of the event on conodont faunas outside Gotland and the Silurian Baltic Basin remains unknown. Here, it is examined in the Widowo IG-1 core (E Poland). The middle Silurian succession in this core represents foreshoal, shoal, and lagoonal settings on a tropical carbonate ramp on the shelf of the Eastern European Craton. Three positive δC excursions have been identified; the two upper excursions correlate with the Mulde isotope anomaly and with two global eustatic regressions. Conodont species proposed to be affected by the extinction event either were not observed or ranged through the extinction interval. Changes in their frequencies are best explained by the sequence stratigraphic architecture of the late Wenlock strata in the Widowo IG-1 core. The little impact of the ‘big crisis’ may reflect facies homogeneity across the studied interval, supporting the hypothesis that the late Wenlock conodont turnover in epicontinental settings was primarily driven by eustatically controlled facies shifts. Copyright © 2015 John Wiley & Sons, Lt
Keywords: Baltica; extinction; gamma ray stratigraphy; Homerian; lundgreni event; Mulde Event; sequence stratigraphy

Latitudinal trends in Cenozoic reef patterns and their relationship to climate. Carbonate Systems during the Oligocene-Miocene climatic transition - Perrin, Christine; Kießling, Wolfgang (IAS Special Publications, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.latitu

Life's complexity cast in stone - Kießling, Wolfgang (Science, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IGM.LP.lifesc

Limestone-marl alternations: A warm-water phenomenon? - Westphal, Hildegard; Munnecke, Axel (Geology, 2003)
Ancient limestone-marl alternations are concentrated in settings analogous to loci of aragonite accumulation in the modern world. They typically occur on shelves in the tropical-subtropical climate belt, are far more abundant on passive continental margins than on active ones, and are rare in upwelling zones. In recent studies, aragonite was proposed to play an important role in differential diagenesis typical of most limestone-marl alternations. The coincidence of depositional settings of ancient limestone-marl alternations and modern aragonite accumulation is a strong case for this hypothesis. If confirmed, it could provide a valuable tool for broad-scale paleoenvironmental interpretations. An additional, different type of limestone-marl alternations resulted from the Cretaceous explosion in productivity of calcitic plankton: these pelagic ones are fundamentally different in their style of diagenesi
Keywords: Aragonite; Differential diagenesis; Global maps; Limestone-marl alternations; Paleoenvironment; Rhythmites

Limestone - Marl alternations in epeiric sea settings - Witnesses of environmental changes or diagnesis? - Westphal, Hildegard; Munnecke, Axel; Böhm, Florian; Bornholdt, Stefan (2008)
Limestone-marl alternations are widespread and typical sediments of epeiric basins and are present in varying abundance throughout the Phanerozoic. In many cases, their rhythmic appearance has been interpreted as a direct response to orbital forcing. However, it is a challenge to unequivocally prove a sedimentary origin of the rhythmic intercalation of the two lithologies. This difficulty arises from differential diagenesis that alters calcareous beds in different ways than interlayers (marls), causing a loss of comparability between the final lithologies. Differential diagenesis, between other effects, causes passive enrichment of the inert non-carbonate fraction in interlayers, where calcium carbonate is dissolved, as well as passive dilution in limestone beds, which get cemented by imported calcium carbonate. Therefore, reliable information about primary systematic differences in the precursor sediments is preserved only in constituents that are not modified during diagenesis. Such diagenetically inert components include the spectra of organic-walled microfossils (but not their absolute concentration in the bulk sediment) and the ratios of certain trace elements (also not their absolute concentrations). Systematic differences in diagenetically inert components can provide unequivocal proof of primary differences. In the limestone-marl alternations, we have studied however, such aspects do not directly reflect the lithological rhythm, shedding doubt on limestone-marl alternations as direct archives of environmental change. Box-model computer simulations visualize possible effects of early diagenetic change acting on the precursors of limestone-marl alternations, independent of the presence or absence of a primary sedimentary rhythm. The simulations demonstrate that diagenesis has the potential to seriously distort any primary rhythm present in the pristine sediment. In particular, differential compaction acting mainly on the marl interlayers induces distortions of the ratios of the original frequencies. These simulations emphasize the difficulties in conducting frequency analyses on relative carbonate contents in real-world succession
Keywords: anactualism; aragonite; aragonite sea; calcite; calcite sea; cellular automaton; cementation; compaction; computer simulation; diagenesis; differential diagenesis; dissolution; distortion; environmental archive; environmental conditions; insolubles; limestone-marl alternation; Milankovitch; model; overprint; palynomorphs; sedimentary record; self- organization; stratigraphic record; rhythmites

Li/Mg systematics in scleractinian corals: Calibration of the thermometer - Montagna, Paolo; McCulloch, Malcolm; Douville, Eric; López Correa, Matthias; Trotter, Julie; Rodolfo-Metalpa, Ricardo; Dissard, Delphine; Ferrier-Pagès, Christine; Frank, Norbert; Freiwald, André; Goldstein, Steve; Mazzoli, Claudio; et al. (Geochimica Et Cosmochimica Acta, 2014)
We show that the Li/Mg systematics of a large suite of aragonitic coral skeletons, representing a wide range of species inhabiting disparate environments, provides a robust proxy for ambient seawater temperature. The corals encompass both zooxanthellate and azooxanthellate species (Acropora sp., Porites sp., Cladocora caespitosa, Lophelia pertusa, Madrepora oculata and Flabellum impensum) collected from shallow, intermediate, and deep-water habitats, as well as specimens cultured in tanks under temperature-controlled conditions. The Li/Mg ratios observed in corals from these diverse tropical, temperate, and deep-water environments are shown to be highly correlated with temperature, giving an exponential temperature relationship of: Li/Mg (mmol/mol)=5.41 exp (-0.049*T) (r2=0.975, n=49). Based on the standard error of the Li/Mg versus temperature correlation, we obtain a typical precision of ±0.9°C for the wide range of species analysed, similar or better than that of other less robust coral temperature proxies such as Sr/Ca ratios.The robustness and species independent character of the Li/Mg temperature proxy is shown to be the result of the normalization of Li to Mg, effectively eliminating the precipitation efficiency component such that temperature remains as the main controller of coral Li/Mg compositions. This is inferred from analysis of corresponding Li/Ca and Mg/Ca ratios with both ratios showing strong microstructure-related co-variations between the fibrous aragonite and centres of calcification, a characteristic that we attribute to varying physiological controls on growth rate. Furthermore, Li/Ca ratios show an offset between more rapidly growing zooxanthellate and azooxanthellate corals, and hence only an approximately inverse relationship to seawater temperature. Mg/Ca ratios show very strong physiological controls on growth rate but no significant dependence with temperature, except possibly for Acropora sp. and Porites sp. A strong positive correlation is nevertheless found between Li/Ca and Mg/Ca ratios at similar temperatures, indicating that both Li and Mg are subject to control by similar growth mechanisms, specifically the mass fraction of aragonite precipitated during calcification, which is shown to be consistent with a Rayleigh-based elemental fractionation model.The highly coherent array defined by Li/Mg versus temperature is thus largely independent of coral calcification mechanisms, with the strong temperature dependence reflecting the greater sensitivity of the Kd Li/Ca partition coefficient relative to Kd Mg/Ca. Accordingly, Li/Mg ratios exhibit a highly coherent exponential correlation with temperature, thereby providing a more robust tool for reconstructing paleo-seawater temperatures. © 2014 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.limgsy

Lithological dependence of aragonite preservation in monospecific gastropod deposits of the Miocene Mainz Basin: Implications for the (dia-)genesis of limestone–marl alternations - Nohl, Theresa; Wetterich, Jannick; Fobbe, Nicholas; Munnecke, Axel (Journal of Sedimentary Research, 2020)

LITHOLOGY CONTROLS AMMONOID SIZE DISTRIBUTIONS - de Baets, Kenneth; Jarochowska, Emilia; Buchwald, Stella Zora; Klug, Christian; Korn, Dieter (Palaios, 2022)
Body-size distributions of organisms across environments in space and time are a powerful source of information on ecological and evolutionary processes. However, most studies only focus on selected parameters of size distributions (e.g., central tendency or extremes) and rarely take into account entire distributions and how they are affected by the collection style and facies. Here we analyze the impact of facies, region, taxonomy, and collection style over size distributions using diameter as a proxy of Late Devonian ammonoids in their entirety using non-metric multidimensional scaling and PERMANOVA based on Kolmogorov distance. The effects are then compared with effects on mean sizes. In all analyses, lithology was the dominant effect, with sizes greater by 59% in marls and by 33% in limestones, as compared to black shales. The effect of complete sampling style was a decrease in size by 11%. Kurtosis was an important parameter differentiating size distributions, with platykurtic distributions in marls and leptokurtic distributions in limestones, suggesting that this parameter may reflect different degrees of time averaging. Most size distributions were positively skewed, but most strongly in marls. Complete sampling led to skewness values close to zero (symmetrical distributions) and high kurtosis.
CRIS-Team WoS Importer:2023-02-10

Living to the range limit: Consumer isotopic variation increases with environmental stress - Reddin, Carl James; O'Connor, Nessa; Harrod, Chris (PeerJ, 2016)
Keywords: Diet; Intertidal; Isotopic niche; Littorinid; Physiological condition; Range limit; Stable isotopes; Stress gradient; Trophic niche width; Trophic variation

Long-term relationships between ecological stability and biodiversity in Phanerozoic reefs - Kießling, Wolfgang (Nature, 2005)
High biodiversity has been shown to enhance ecological stability on small spatial scales and over intervals of weeks to decades. It remains unclear, however, whether this diversity-stability relationship can be scaled up to regional scales, or to longer timescales. Without empirical validation at larger scales, the implications of the diversity-stability relationship for both ecology and long-term conservation strategies cannot readily be resolved. Here I show that in biogenic reefs, ecological stability is related to taxonomic diversity on million-year timescales. The higher the mean reef diversity in a particular time interval, the smaller the change in skeletal density, style of reef building and biotic reef types in the subsequent time interval. Because the relationships apply to a wide spectrum of disturbance regimes and reef types, these results support the hypothesis that species richness itself promotes ecological stability. Carbonate production by reefs, while closely correlated with reef diversity without temporal lag, is not stabilized by reef diversity over these long timescales. This suggests that ecological stability and productivity may be decoupled in natural ecosystems.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LP.longte

Lost in transition – the selective compaction of a halysitid coral and its implications for diagenesis and time - Nohl, Theresa; Munnecke, Axel (GeoBonn2018 - Living Earth, 2018)

Lower Palaeozoic geology of southern Sweden - Calner, Mikael; Erlström, Mikael; Lehnert, Oliver; Ahlberg, Per (The Lower Palaeozoic of southern Sweden and the Oslo Region, Norway. Field Guide for the 3rd Annual Meeting of the IGCP project 591, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LG.lowerp_5

Manitouscolex a new palaescolecidan genus from the Lower Ordovician of Colorado - Lehnert, Oliver; Kraft, Petr (Journal of Paleontology, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IGM.LG.manito

Mapping intrashell variation in Mg/Ca of brachiopods to external growth lines: Mg enrichment corresponds to seasonal growth slowdown - Müller, Tamás; Tomašových, Adam; López Correa, Matthias; Mertz-Kraus, Regina; Mikuš, Tomáš (Chemical Geology, 2022)
Determining secular changes in seawater temperature and Mg/Ca ratio is of high importance in paleooceanographic, paleoenvironmental and paleoecological studies. On the one hand, intra-shell variation in Mg/Ca in brachiopod shells is used to reconstruct historical changes in temperature and in seasonality. On the other hand, intra-shell analyses show a weak relationship between Mg/Ca and δ18O, but a positive correlation between Mg/Ca and Sr/Ca, and an increase of Mg/Ca at growth lines, indicating that Mg/Ca does not simply track seawater temperature alone. Internal growth lines are rarely visible in brachiopod shells, and the relation between growth lines that mark growth slowdown or cessation and Mg/Ca fluctuation is thus not properly understood. Here, using four species of extant brachiopods from the NE Pacific and the SW Pacific, from environments with low seasonality in seawater temperature (<5 °C), and two species of Late Triassic brachiopods (Western Carpathians), we measure intra-shell ontogenetic variation in Mg/Ca, S/Ca and Sr/Ca with laser ablation ICP-MS and electron microprobe. In contrast to previous studies, we map variation in Mg, S, and Sr to external growth lines. We find that, first, zones of Mg/Ca enrichment in the secondary layer form 10–50 μm-thick discrete bands or clusters of micrometric bands that consistently terminate at major external, predominantly annual growth lines that are associated with distinct notches that correspond to mantle retractions in most species. These bands generate distinct peaks in Mg/Ca that stand above low, more uniformly distributed background Mg/Ca values along laser-ablation and microprobe transects. The magnitude of Mg/Ca in these bands is comparable to Mg/Ca in the primary layer, exceeding background values of Mg/Ca in the secondary layer by 5–20 mmol/mol (by a factor of two to five). Second, Mg enrichment in discrete bands is closely associated with an increase in S concentrations in the secondary layer. Therefore, even when Mg and S uptake is expected to be highest under fast precipitation rate, these empirical observations show that Mg and S enrichment occur in the zones that were precipitated at times of a significant growth reduction (e.g., in cold-temperate brachiopods studied here during winters when primary productivity is low). The mechanisms for this paradox are unclear but can be related to uptake of Mg by amorphous calcium carbonate (ACC) to delay the transformation of ACC to calcite during the formation of growth lines. Therefore, intra-shell variation in Mg/Ca in brachiopods with major growth lines is primarily determined by seasonal decline or cessation in shell growth and not by seasonal changes in seawater temperature.
Keywords: Brachiopoda; Biomineralization; Mg/Ca ratio; S/Ca ratio; Sr/Ca ratio; Growth rate; Seasonality

Mapping paleocoastlines and continental flooding during the Phanerozoic - Kocsis, Ádám; Scotese, Christopher R. (Earth-Science Reviews, 2021)
Sea levels shape the face of the Earth, define processes of sedimentation, and influence the evolution of life via the distribution of habitats. Ancient topographies can be reconstructed using the history and understanding of tectonic processes, lithological evidence, and present-day topographies. Paleogeographic reconstructions must accommodate ever newer sources of geological data, so we can refine and improve our model of ancient topography and bathymetry. Here, we assess the accuracy of a set of Phanerozoic digital paleogeographic maps by testing the proposed distribution of flooded shallow seas and land using fossil occurrence data from the Paleobiology Database. After noting a moderate match, we modified the positions of the coastlines and continental margins of these topographic models to reflect times of maximum transgression. Using the updated paleogeographic maps, we outline the changes of land and shallow marine areas over time and suggest ways they can be used for further investigations of our planet's history.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Coastlines; Continental flooding; Fossils; Global; Paleogeography; Phanerozoic; Reconstruction

Marine benthic invertebrates from the Upper Jurassic of northern Ethiopia and their biogeographic affinities - Kießling, Wolfgang; Pandey, Dhirendra; Schemm-Gregory, Mena; Mewis, Heike; Aberhan, Martin (Journal of African Earth Sciences, 2011)
We present the first modern description of corals, brachiopods and bivalves from the Antalo Limestone in the Mekele Outlier of northern Ethiopia. This fauna is largely of Oxfordian age and lived in shallow subtidal environments and in small patch reefs. In combining our new data with fossil occurrence data from the Paleobiology Database, we conducted multidimensional scaling analyses to assess biogeographic patterns and the delineation of the Ethiopian Province for the Callovian to Kimmeridgian stages. Results suggest that an Ethiopian Province is indeed evident for our focal groups, but this is more confined than traditionally assumed. The so defined Ethiopian Province includes Tunisia, the Levant, Arabia and much of East Africa, but excludes Tanzania and India. The special status of India and Tanzania is perhaps due to latitudinal gradients in faunal composition. © 2010 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.marine
Keywords: Biogeography; Bivalves; Brachiopods; Corals; Ethiopia; Jurassic

Marine Biodiversity and Geographic Distributions Are Independent on Large Scales - Antell, Gwen S.; Kießling, Wolfgang; Aberhan, Martin; Saupe, Erin E. (Current Biology, 2020)
Fundamental ecological and evolutionary theories, such as community saturation and diversity-dependent diversification, assume that biotic competition restricts resource use, and thus limits realized niche breadth and geographic range size [1–3]. This principle is called competitive exclusion. The corollary (ecological release) posits that, after competitors disappear from a region, species that were previously excluded will invade. Hundreds of field experiments have demonstrated ecological release in living populations. However, few of these studies were conducted in marine environments, and almost no work extended beyond 10 years and 1,000 km2 [4, 5]. In limited investigation of marine taxa at larger spatiotemporal scales, macroecologists and paleobiologists have observed little evidence of competitive exclusion [6–9]. Here, we quantified spatial trends in the rich and densely sampled fossil history of brachiopods and bivalves, while accounting for inconsistent sampling coverage through time using a new method of spatial standardization. The number of potential competitors in a region did not explain the geographic distribution of constituent species or genera. Furthermore, although ecological release predicts species to expand after extinction events, survivors of intervals with net species loss expanded as rarely as species in other intervals. Regression model estimates indicated different spatial responses of brachiopods and bivalves, and of habitat specialists and generalists, but no effect from changes in number of potential competitors. Biotic competition may control the distribution of populations, but, on larger spatiotemporal scales, non-competitive factors may have driven biogeographic patterns of brachiopods and bivalves. Long-standing ecological and evolutionary theories assume that competition between individuals controls the cumulative resource use and geographic ranges of species. Antell et al. demonstrate that spatial distributions of marine invertebrates are incongruent with this expectation throughout the last 485 million years.
CRIS-Team Scopus Importer:2020-01-07
Keywords: bivalves; brachiopods; competition; diversity-dependent diversification; ecological release; fossil record; macroecology; niche partitioning; spatial scale; species distributions

Marine clade sensitivities to climate change conform across timescales - Reddin, Carl James; Nätscher, Paulina; Kocsis, Ádám; Pörtner, Hans Otto; Kießling, Wolfgang (Nature Climate Change, 2020)
Rapid climate change is postulated to cause marine extinctions, especially among climate-sensitive clades, traits and regions1–6. This premise is based on two hypotheses: (1) known individual physiological sensitivities scale up to macroecological selectivity patterns4,7,8 and (2) ancient hyperthermal events are appropriate models to anticipate ecological winners and losers of anthropogenic climate change9. Yet these hypotheses have largely escaped quantitative appraisal. Here we show that experimental responses of modern marine ectotherms to single and combined climate-related stressors (such as seawater warming, hypoxia and acidification) align with Phanerozoic fossil extinction regimes across clades and functional traits. Of climate-related stressors, the synergistic interaction between warming and hypoxia10, encumbering aerobic metabolism, has the greatest potency as a proximate driver of extinction. All else being equal8, this synergy particularly imperils modern warm-water organisms. Modern–fossil agreement is strongest at intermediate–high extinction intensities and hyperthermal events but may fail at extreme extinction events, perhaps due to rising prominences of, and interactions among, additional biotic and abiotic stressors. According to results from marine ectotherms, clade-based sensitivity of individuals to climate-related stressors scales up from subannual experiments and decadal range-shift response magnitudes11, to extinction selectivity patterns at ancient climate-related stressor events and the Phanerozoic durations of genera.
CRIS-Team Scopus Importer:2020-02-25

Marine invertebrate migrations trace climate change over 450 million years - Reddin, Carl James; Kocsis, Ádám; Kießling, Wolfgang (Global Ecology and Biogeography, 2018)
Aim Poleward migration is a clear response of marine organisms to current global warming but the generality and geographical uniformity of this response are unclear. Marine fossils are expected to record the range shift responses of taxa and ecosystems to past climate change. However, unequal sampling (natural and human) in time and space biases the fossil record, restricting previous studies of ancient migrations to individual taxa and events. We expect that temporal changes in the latitudinal distribution of surviving taxa will reveal range shifts to trace global climate change. Location Global. Time period Post‐Cambrian Phanerozoic aeon. Major taxa studied Well‐fossilized marine benthic invertebrates comprising stony corals, bivalves, gastropods, brachiopods, trilobites and calcifying sponges. Methods We track deviations in the latitudinal distribution of range centres of age boundary crossing taxa from the expected distribution, and compare responses across latitudes. We build deviation time series, spanning hundreds of million years, from fossil occurrences and test correlations with seawater temperature estimates derived from stable oxygen isotopes of fossils. Results Seawater temperature and latitudinal deviations from sampling are positively correlated over the post‐Cambrian Phanerozoic. Simulations suggest that sampling patterns are highly unlikely to drive this putative signal of range shifts. Systematically accounting for known sampling issues strengthens this correlation, so that climate is capable of explaining nearly a third of the variance in ancient latitudinal range shifts. The relationship is stronger in low latitude taxa than higher latitude taxa, and in warm ages than cool ages. Main conclusions Latitudinal range shifts occurred in concert with climate change throughout the post‐Cambrian Phanerozoic. Low latitude taxa show the clearest climate‐migration signal through time, corroborating predictions of their shift in a warming future.
Keywords: d18O; fossil; latitude; out of the tropics; Paleobiology Database; Phanerozoic; sampling bias; time series

Marine sepiolite in Middle Permian carbonates of South China: implications for secular variation of Phanerozoic seawater chemistry. - Yan, Jiaxin; Munnecke, Axel; Steuber, Thomas; Carlson, E.H.; Xiao, Yilin (Journal of Sedimentary Research, 2005)
t is now widely accepted that the composition of seawater varied significantly during the Phanerozoic, and that the Mg/Ca ratio of seawater is a major factor in synchronized secular oscillations in the mineralogical composition of marine evaporites and nonskeletal as well as biogenic carbonates. However, the nature of the Mg sink is still subject to debate. We describe early diagenetic sepiolite from the Chihsia Formation (middle Permian) of South China. The Mg incorporated in sepiolite likely was furnished by stabilization of high-Mg calcite, and silica was derived from siliceous fossils. Two factors facilitated the accumulation of sepiolite in the Chihsia Formation. The first is a Chihsian depositional environment of an intra-oceanic carbonate platform that lacked detrital terrestrial input, which enhanced the availability of biogenic silica for sepiolite formation. The second is the chemical composition of Permian seawater, as the precipitation of high-Mg calcite was aided by a high Mg/Ca ratio associated with an aragonite sea. The formation of sepiolite is significant in constraining the recycling flux of Mg during recrystallization of carbonate sediments with a high proportion of high-Mg calcite (periods of aragonite seas). Worldwide, major occurrences of marine sepiolite and palygorskite in the Phanerozoic correlate with periods of aragonite seas. This temporal distribution implies that minerals of the sepiolite-palygorskite group play an important role in the geochemical recycling of Mg, and that major sepiolite and palygorskite deposits indicate episodes of high Mg concentrations in seawater. The formation of sepiolite also was probably related to an abundance of silica-secreting organisms, which interacted with the chemical evolution of Phanerozoic seawater. In addition, authigenic sepiolite and palygorskite are not indicators of arid and semiarid climate
Keywords: Sepiolite; China; Permian; Seawater chemistry

Mass extinctions and clade extinctions in the history of brachiopods: Brief review and a post-paleozoic case study - Vörös, Attila; Kocsis, Ádám; Pálfy, József (Rivista Italiana Di Paleontologia E Stratigrafia, 2019)
Brachiopods are a key group in Phanerozoic marine diversity analyses for their excellent fossil record and distinctive evolutionary history. A genus-level survey of raw diversity trajectories allows the identification of the Brachiopod Big Five, episodes of major genus losses in the phylum which are compared with the established Big Five mass extinctions of Phanerozoic marine invertebrates. The two lists differ in that the end-Cretaceous extinction appears subdued for brachiopods, whereas the mid-Carboniferous is recognized as an event with significant loss of brachiopod genera. At a higher taxonomic level, a review of temporal ranges of rhynchonelliform orders reveals episodes of synchronous termination of multiple orders, here termed clade extinctions. The end-Ordovician, Late Devonian and end-Permian events are registered as both mass extinctions and clade extinctions. The Late Cambrian and the Early Jurassic are identified as the other two clade extinction events. Coincident with the Early Toarcian oceanic anoxic event, the last clade extinction of brachiopods is defined by the disappearance of the last two spire-bearing orders, Athyridida and Spiriferinida. Their diversity trajectory through the recovery after the end-Permian crisis parallels that of the extant terebratulides and rhynchonellides until a Late Triassic peak but diverge afterwards. The end-Triassic diversity decline and Toarcian vanishing of spire-bearers correspond with contraction in their spatial distribution. The observed patterns and extinction selectivity may be explained both ecologically and physiologically. The specialized adaptation of morphologically diverse spire-bearers, as well as their fixed lophophore and passive feeding put them at a disadvantage at times of environmental crises, manifest in their end-Triassic near-extinction and Toarcian demise. Similar analyses of other clade extinctions may further improve our understanding of drivers and processes of extinction.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Biotic crises; Diversity; End-triassic; Rhynchonelliformea; Spire-bearers; Toarcian

Massive corals in Paleocene siliciclastic sediments of Chubut (Patagonia, Argentina) - Kießling, Wolfgang; et al. (Facies, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LP.massiv

Mass occurrence of the large solitary rugose coral Phaulactis angusta at the boundary Lower/Upper Visby Formation in the Silurian of Gotland, Sweden: palaeoecology and depositional implications - Adomat, Friederike; Munnecke, Axel; Kido, Erika (GFF, 2016)
The boundary between the Lower and Upper Visby formations on Gotland (Sweden), which roughly correlates with the Llandovery–Wenlock boundary, is characterised by a mass occurrence of the large solitary rugose coral Phaulactis angusta. This coral-rich layer can be followed for some 50 km along the north-west coast of Gotland. The mass occurrence coincides with the onset of a pronounced, globally recognised δC and δO excursions in the lower Sheinwoodian. Altogether 31 specimens of P. angusta from eight localities were examined. We demonstrate that the corals preferred to grow in an upright position. Attachment structures were not observed, and therefore a liberosessile life strategy is suggested. Some corallites show an abrupt change in growth direction accompanied by a decrease in diameter. These features mostly occur in later growth stages and may be explained by disturbances in the growth due to toppling or tilting of the corals. Many specimens were able to change their growth axes, but finally died after such an event. Most specimens in the outcrops show a flattened upper surface, which is interpreted as a result of post-mortem abrasion. Epibiontic bryozoan encrustation took place mostly while the corals where alive, whereas stromatoporoid encrustation and Trypanites borings occurred post-mortem. The repeated growth, tilting and erosion of the corallites of P. angusta demonstrate that the Phaulactis layer represents a condensed interval, characterised by multiple pulses of sediment accumulation and erosio
Keywords: Gotland; Ireviken event; rugose corals; Silurian

Matera building stones: Chemical, mineralogical and petrophysical characterization of the calcarenite di gravina formation - Bonomo, A. E.; Lezzerini, M.; Prosser, G.; Munnecke, Axel; Koch, Roman; Rizzo, G. (2019 IMEKO TC4 International Conference on Metrology for Archaeology and Cultural Heritage, MetroArchaeo 2019, 2019)
Matera (Basilicata, southern Italy) was awarded the World Heritage Site status by the UNESCO since 1993, and has been named the European Capital of Culture in 2019. It is one of the most ancient towns in the world, whose historical centre was totally built by a weakly lithified and highly porous lower Pleistocene sedimentary building stone, known as Gravina Calcarenite. This easily workable rock was quarried since prehistoric times, and it was used for building different kinds of constructions from the rupestrian settlement to gorgeous historic palaces during the XVIII century. Calcarenite, however, can be an extremely heterogeneous building material depending on the composition of the particles and their characteristics. After a geological survey, it was possible to recognize two main varieties of this building stone, which were in turn subdivided into six lithofacies (corresponding to sub-typologies of building stones). As a first approach, we have characterized, in terms of building stone quality, six lithofacies: basal bioclastic calcarenite, calcirudite-microconglomerate lithofacies, lithoclastic calcarenite, large bivalve bioclastic calcarenite, rhodolith bioclastic calcarenite, and fine bioclastic calcarenite. We focused on the three typologies that were mainly used as building stone (lithoclastic calcarenite, large bivalve bioclastic calcarenite, and fine bioclastic calcarenite). Mineralogical, petrographical and petrophysical analyses have been carried out according to European standard rules to highlight the main characteristics of the different calcarenite types when used as building stones. These three lithofacies show different petrophysical behavior indicating that large bivalve calcarenite and lithoclastic calcarenite lithofacies have slightly different but characteristic mechanical properties related to the primary influence of grain composition, early cementation and micrite contents. Moreover, fine bioclastic calcarenite lithofacies results to be the worst building stone because it is intensely heterogeneous in porosity, cementation and general petrophysical features because of its intense bioturbation.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Building stone; Cultural heritage; Petrographic characterization; Petrophysical properties

Matera building stones: Comparison between bioclastic and lithoclastic calcarenites - Bonomo, Agnese Emanuela; Lezzerini, Marco; Prosser, Giacomo; Munnecke, Axel; Koch, Roman; Rizzo, Giovanna (Building Materials, Materials Design and Applications, 2019)
Matera (Basilicata, southern Italy) was awarded World Heritage Site status by the UNESCO since 1993, and it will be the European Capital of Culture in 2019. It is one of the most ancient towns in the world, whose historical centre was totally built by only a moderately lithified and highly porous sedimentary building stone, known as Gravina Calcarenite. This easily workable rock was quarried since prehistoric times, and it was used for building different kind of constructions from the rupestrian settlement to the gorgeous historic palace during the XVIII century. Calcarenite, however, can be an extremely heterogeneous building material depending on the composition of the particles and their characteristics. After a geological survey, it was possible to recognize two main varieties of this building stone, which were in turn subdivided into six sub-typologies. As a first approach, we have characterized, in terms of building stone quality, the two main varieties: the bioclastic calcarenite and the lithoclastic calcarenite, sampled in the quarrying area to the North of Matera. The bioclastic calcarenite is from a new quarry in the upper part of the Calcarenite Formation, while the lithoclastic calcarenite is from an old quarry, inactive since 1965, in the lower part of the same formation. Mineralogical, petrographic and petrophysical tests have been carried out according to European Standards rules to highlight the main characteristics of different calcarenite types when used as building stone. Despite of their compositional differences, the bioclastic and lithoclastic calcarenite are both pure limestones with slightly different amounts of non-carbonates (silt quartz, clay minerals). The slightly different but characteristic mechanical properties clearly characterize the primary influence of grain composition, early cementation and micrite contents.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Building stone; Italian Unesco site; Petrographic characterization; Physical and mechanical properties

Matera’s Old Quarries: Geological and Historical Archives That Need Protection and Valorization - Bonomo, A. E.; Acito, A. M.; Prosser, G.; Rizzo, G.; Munnecke, Axel; Koch, Roman; Bentivenga, M. (Geoheritage, 2019)
The Sassi of Matera, UNESCO site since 1993, represents a human settlement completely integrated in the natural landscape. There, the development of the community is closely connected to the geology since prehistoric times. The Calcarenite di Gravina, a Pleistocene poorly lithified limestone onlapping a large area of the Apulian foreland in southern Italy, is the building stone that people used to carve their houses inside, and build the town outside. The use of calcarenite for housing began in the prehistory with the first human settlement, deepening natural caves which served as dwellings, while the mining activity began in the third century B.C., increasing until the nineteenth century in connection with the urban development of Matera. The calcarenite was carved out on site and used to build houses. In the eighteenth century, the great urban development of the city gave way to large mining activities in the northern area of Matera. Geomorphological analysis through aerial photographs and a geological survey in this area have been carried out to investigate the historical quarrying activities. In the present study, six quarry areas along the Appia Antica road are valuated: the Madonna delle Vergini topographic high; Cava della Palomba; Parco Scultura–Cava Paradiso; Cava del Sole, the Monumental Quarry Remains; Via Ridola inside the Piano, the highest area of Sassi. They represent peculiar and important examples to be safeguarded and valued. Their geomorphological, geostratigraphical and palaeontological elements provide useful information for understanding the territory evolution in the last two millennia.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Geo-valorization; Geological itinerary; Mining activities; Reused quarries; Soft limestone

Maximum rates of climate change are systematically underestimated in the geological record - Kießling, Wolfgang; Kemp, David B.; Eichenseer, Kilian (Nature Communications, 2015)
Recently observed rates of environmental change are typically much higher than those inferred for the geological past. At the same time, the magnitudes of ancient changes were often substantially greater than those established in recent history. The most pertinent disparity, however, between recent and geological rates is the timespan over which the rates are measured, which typically differ by several orders of magnitude. Here we show that rates of marked temperature changes inferred from proxy data in Earth history scale with measurement timespan as an approximate power law across nearly six orders of magnitude (102 to >107 years). This scaling reveals how climate signals measured in the geological record alias transient variability, even during the most pronounced climatic perturbations of the Phanerozoic. Our findings indicate that the true attainable pace of climate change on timescales of greatest societal relevance is underestimated in geological archives.
UnivIS-Import:2017-01-09:Pub.2015.nat.dgeo.IGM.LP.maximu

Mechanisms and drivers of belemnite body-size dynamics across the Pliensbachian–Toarcian crisis - Costa Rita, Patrícia; Nätscher, Paulina; Duarte, Luís V.; Weis, Robert; de Baets, Kenneth (Royal Society Open Science, 2019)
Body-size reduction is considered an important response to current climate warming and has been observed during past biotic crises, including the Pliensbachian–Toarcian crisis, a second-order mass extinction. However, in fossil cephalopod studies, the mechanisms and their potential link with climate are rarely investigated and palaeobiological scales of organization are not usually differentiated. Here, we hypothesize that belemnites reduce their adult size across the Pliensbachian–Toarcian boundary warming event. Belemnite body-size dynamics across the Pliensbachian–Toarcian boundary in the Peniche section (Lusitanian Basin, Portugal) were analysed based on the newly collected field data. We disentangle the mechanisms and the environmental drivers of the size fluctuations observed from the individual to the assemblage scale. Despite the lack of a major taxonomic turnover, a 40% decrease in rostrum volume is observed across the Pliensbachian–Toarcian boundary, before the Toarcian Oceanic Anoxic Event where belemnites go locally extinct. The pattern is mainly driven by a reduction in adult size of the two dominant species, Pseudohastites longiformis and Passaloteuthis bisulcata. Belemnite-size distribution is best correlated with fluctuations in a palaeotemperature proxy (stable oxygen isotopes); however, potential indirect effects of volcanism and carbon cycle perturbations may also play a role. This highlights the complex interplay between environmental stressors (warming, deoxygenation, nutrient input) and biotic variables (productivity, competition, migration) associated with these hyperthermal events in driving belemnite body-siz
Keywords: cephalopods; Lilliput effect; Pliensbachian–Toarcian boundary event; Toarcian oceanic anoxic event; climate warming; computed tomography

Mechanistic insight on the chemistry of potential Pt antitumor agents as revealed by collaborative research performed in Kragujevac and Erlangen - Petrović, Biljana; Jovanović, Snezana; Puchta, Ralph; van Eldik, Rudi (Inorganica Chimica Acta, 2019)
This personal account reports on the mechanistic insight gained on the chemistry of potential Pt antitumor agents based on the collaborative research between the groups of Živadin Bugarčić in Kragujevac (Serbia) and Rudi van Eldik in Erlangen (Germany). The work focuses on different mononuclear Pt(II) and Pt(IV), as well as dinuclear Pt(II) complexes, the tuning of their lability through steric and electronic (σ-donor and π-acceptor) effects, their interaction with sulfur- and nitrogen-donor bio-relevant nucleophiles, the elucidation of structure-reactivity relationships, and DFT calculations on ground, transition and product state complexes. It presents an overview of the investigated systems and reveals mechanistic information on the basis of spectroscopic and kinetic measurements.
CRIS-Team Scopus Importer:2019-06-21
Keywords: DFT calculations; Di-nuclear Pt(II) complexes; Kinetics; Mechanism; Pt(II) complexes; Pt(IV) complexes

Mechanistic neutral models show that sampling biases drive the apparent explosion of early tetrapod diversity - Dunne, Emma; Thompson, Samuel E.D.; Butler, Richard J.; Rosindell, James; Close, Roger A. (Nature Ecology & Evolution, 2023)
Estimates of deep-time biodiversity typically rely on statistical methods to mitigate the impacts of sampling biases in the fossil record. However, these methods are limited by the spatial and temporal scale of the underlying data. Here we use a spatially explicit mechanistic model, based on neutral theory, to test hypotheses of early tetrapod diversity change during the late Carboniferous and early Permian, critical intervals for the diversification of vertebrate life on land. Our simulations suggest that apparent increases in early tetrapod diversity were not driven by local endemism following the ‘Carboniferous rainforest collapse’. Instead, changes in face-value diversity can be explained by variation in sampling intensity through time. Our results further demonstrate the importance of accounting for sampling biases in analyses of the fossil record and highlight the vast potential of mechanistic models, including neutral models, for testing hypotheses in palaeobiology.
CRIS-Team Scopus Importer:2023-08-11

Meeresschildkrötenschutz - Schulbert, Christian; Römheld, Julia (Vogelschutz, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LP.meeres

Meiobenthos and ocean acidification: Effects on meiobenthic communities inhabiting Mediterranean cold shallow CO2-vents - Cocozza di Montanara, A.; Baldrighi, E.; López Correa, Matthias; Chianese, E.; Appolloni, L.; Simoncini, N.; Sandulli, R.; Zeppilli, D.; Semprucci, F.; Gambi, M. C.; Ferrigno, F.; Donnarumma, L. (Estuarine Coastal and Shelf Science, 2024)
Ocean acidification is causing major changes in marine ecosystems, with varying levels of impact, depending both on the habitat and the studied organisms. Here, we investigated for the first time the meiobenthos and nematode fauna inhabiting the sediments around Castello Aragonese (Ischia, Italy), characterized by variable pH values due to coastal volcanic CO2 venting. In this scenario, nematode functional diversity changed according to different pH levels and grain size: maturity index was higher at most acidic stations and trophic composition spanned from the dominance of predators in the acidic stations, to the high abundance of non-selective deposit feeders and epistrate feeders in the ambient-pH stations. Overall, the present study revealed a relatively high tolerance of meiobenthos and nematodes to lower pH conditions. However, an in-depth analysis of nematode fauna showed differences in their assemblages at different pH levels with few nematode genera rather adapted to the extreme environmental conditions at the acidic stations.
CRIS-Team Scopus Importer:2024-04-05
Keywords: CO; Community composition; Functional diversity; Ischia vents; Mediterranean sea; Meiofauna; Nematodes

Mesozoic–Cenozoic bioevents - Kießling, Wolfgang; Lazarus, David; Zeller, Ulrich (Palaeogeography, Palaeoclimatology, Palaeoecology, 2004)
Keywords: Biodiversity; Evolution; Extinctions

Metal-induced malformations in early Palaeozoic plankton are harbingers of mass extinction - Vandenbroucke, Thijs R.A.; Emsbo, Poul; Munnecke, Axel; Nuns, Nicolas; Duponchel, Ludovic; Lepot, Kevin; Quijada, Melesio; Paris, Florentin; Servais, Thomas; Kießling, Wolfgang (Nature Communications, 2015)
Glacial episodes have been linked to Ordovician-Silurian extinction events, but cooling itself may not be solely responsible for these extinctions. Teratological (malformed) assemblages of fossil plankton that correlate precisely with the extinction events can help identify alternate drivers of extinction. Here we show that metal poisoning may have caused these aberrant morphologies during a late Silurian (Pridoli) event. Malformations coincide with a dramatic increase of metals (Fe, Mo, Pb, Mn and As) in the fossils and their host rocks. Metallic toxins are known to cause a teratological response in modern organisms, which is now routinely used as a proxy to assess oceanic metal contamination. Similarly, our study identifies metal-induced teratology as a deep-time, palaeobiological monitor of palaeo-ocean chemistry. The redox-sensitive character of enriched metals supports emerging 'oceanic anoxic event' models. Our data suggest that spreading anoxia and redox cycling of harmful metals was a contributing kill mechanism during these devastating Ordovician-Silurian palaeobiological event
Keywords: Metal-induced; Mass extinction; Silurian; Palaeozoic plankton; Palaeobiological events

Microbial bioerosion of erratic sub-fossil Nautilus shells in a karstic cenote (Lifou, Loyalty Islands, New Caledonia) - Seuß, Barbara; Wisshak, Max; Mapes, Royal H.; Hembree, Daniel I.; Landman, Neil; Lignier, Vincent (Ichnos-An International Journal For Plant and Animal Traces, 2016)
UnivIS-Import:2016-06-01:Pub.2016.nat.dgeo.IGM.LP.microb
Keywords: Bioerosion; Cenote; Holocene; Ichnocoenosis; Karst; Nautilus; New Caledonia; Taphonomy

Microbially induced wrinkle structures in Middle Devonian siliciclastics from the Prague Basin, Czech Republic - Vodrážková, Stanislava; Vodrážka, Radek; Munnecke, Axel; Franců, Juraj; Al‐Bassam, Khaldoun; Halodová, Patricie; Tonarová, Petra (Lethaia, 2018)
The occurrence of wrinkle structures in Middle Devonian deep‐water siliciclastic sequences of the Prague Basin (Roblín Member, Srbsko Formation, Givetian) is reported and interpreted to be microbially induced. Current and/or gravitational forces are considered the simplest explanation of the origin of these structures. Taking into account the tectonic activity linked with ongoing Variscan orogeny, the wrinkle structures could also be interpreted as soft sediment deformation structures originating due to exposure of mat‐bearing sediment to seismic shocks. The distribution of n‐alkanes and isoprenoids suggests two types of prevailing biological sources, namely phytoplankton, representing organic material from the water column, and benthic bacteria. Judging from the sedimentary facies and lack of petrographic characteristics suggestive of light competition, the microbial mats are interpreted to be formed by non‐autotrophic bacteri

Microbioerosion in Tahitian reefs: A record of environmental change during the last deglacial sea-level rise (IODP 310) - Heindel, Katrin; Wisshak, Max; Westphal, Hildegard (Lethaia, 2008)
The main motivation for Integrated Ocean Drilling Program Expedition 310 to the Tahitian Archipelago was the assumption that the last deglacial sea-level rise is precisely recorded in the coral reefs of this far-field site. The Tahitian deglacial succession typically consists of coral framework subsequently encrusted by coralline algae and microbialites. The high abundance of microbialites is uncommon for shallow-water coral reefs, and the environmental conditions favouring their development are still poorly understood. Microbioerosion patterns in the three principal framework components (corals, coralline algae, microbialites) are studied with respect to relative light availability during coral growth and subsequent encrustation, in order to constrain the palaeobathymetry and the relative timing of the encrustation. Unexpectedly for a tropical, light-flooded setting, ichnotaxa typical for the deep-euphotic to dysphotic zone dominate. The key ichnotaxa for the shallow euphotic zone are scarce in the analysed sample set, and are restricted to the base of the deglacial succession, thus reflecting the deglacial sea-level rise. At the base of the deglacial reef succession, the ichnocoenoses present in the corals indicate shallower bathymetries than those in the encrusting microbialites. This is in agreement with radiocarbon data that indicate a time gap of more than 600 years between coral death and microbialite formation. At the top of the deglacial reef succession, in contrast, the microbioerosion patterns in the three framework components indicate a uniform palaeobathymetry, and radiocarbon ages imply that encrustation took place shortly after coral demise. An enigma arises from the fact that the ichnocoenoses imply photic conditions that appear very deep for zooxanthellate coral growth. During the deglacial sea-level rise increased nutrients and fluvial influx may have led to (seasonal?) eutrophication, condensing the photic zonation. This would have exerted stress on the coral ecosystem and played a significant role in initiating microbialite development.

Microfacies analysis and 3D reconstruction of bioturbated sediments in the calcarenite di Gravina formation (southern Italy) - Bonomo, Agnese Emanuela; Munnecke, Axel; Schulbert, Christian; Prosser, Giacomo (Marine and Petroleum Geology, 2021)
The Calcarenite di Gravina is a poorly lithified, heterogeneous bio-lithoclastic Plio-Pleistocene limestone formed in a temperate shallow-water setting. Since prehistoric times it has been used for construction, as witnessed by the “Sassi”, the old city center of Matera (southern Italy). Here, the relatively distal, fine-grained bioclastic grain-packstone is characterized by large bioturbation structures of crustaceans. The aim of this work is to understand how bioturbation controls texture, porosity, permeability, and the cementation of the calcarenite. Crustaceans such as Callianassa are known to produce vertical burrows and sort grains. A bioturbated calcarenite level, outcropping in the Parco Scultura- Cava Paradiso in La Palomba (Matera northern area), has been selected as case study. Large rock samples including fossil traces and surrounding rocks have been analysed. Optical microscope and SEM observations show a close connection between sediment sorting and cementation, and 3D analyses by means of CT scans indicate that the internal structure and the connected porosity of the samples is a function of the cementation. Moreover, the porosity network is reconstructed in 3D in order to derive the real connected porosity variations and their implications for the evolution in terms of diagenesis and alteration of the rocks. Indeed, a cementation gradient from the external lining of the burrows to the internal part of the trace fossil is observed. Cementation is less pronounced outside of the trace fossil. Cluster analysis of point-counting results allows to identify four sub-facies characterized by differences in composition, cementation and porosity. One of them is present in the interior of the burrows while the other two characterize the external lining (crust) and storage chamber of crustacean burrows. The last sub-facies occurs in the area surrounding the trace fossils and shows a weaker cementation. The presence of a cementation gradient inside the trace fossil is explained through a diagenetic model that considers the contribution of different factors. The geochemical environments allow the CaCO3 precipitation inside the burrows starting from the lining to the internal area thanks to the microbial actions, water circulation and relative oxygenation of fluids. Dissolution of aragonitic components probably represents the principal source of CaCO3. Variation in cementation and porosity are quite moderate, but capable of generating major differences in the resistance to weathering. From this study it emerges how the diagenetic processes lead to significant changes in the bioturbated fabric, making the burrows less permeable than the surrounding sediment. This is confirmed by the selective erosion that brings to light very well-preserved traces of Callianassidae even on building stones.
CRIS-Team Scopus Importer:2021-01-08
Keywords: 3D porosity; Bioturbation; Diagenesis; microCT-scan modelling

Microfacies and carbon isotope records of Mississippian carbonates from the isolated Bama Platform of Youjiang Basin, South China: Possible responses to climate-driven upwelling - Liu, Chao; Jarochowska, Emilia; Du, Yuansheng; Vachard, Daniel; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2015)
Changes in Mississippian global paleogeography derived from the reconfiguration of the continents have been suggested to result in a change in oceanic circulation, carbon cycling, as well as in global cooling. Here, integrated δC chemostratigraphy and foraminiferal biostratigraphy across the Mississippian (late Tournaisian, Visean, early Serpukhovian; MFZ6-MFZ16 foraminiferal biozones) of the Gongchuan section located in the isolated Bama Platform in the Youjiang Basin, South China, are presented. The δC trend shows an abrupt decline during late Visean (Asbian-early Brigantian; MFZ13-14). This decline is also observed in subequatorial western Euramerica, whereas coeval sections in subequatorial eastern Euramerica show consistently elevated δC values across the entire Visean. The δC decline in western Euramerica and the South China Block (eastern Paleo-Tethys) coincides with a global regression with a suggested glacioeustatic origin, the onset of high-frequency climate and sea-level oscillations, and the closure of the Rheic seaway between Euramerica and Gondwana. We propose a model explaining the divergence of δC records resulting from the closure of the Rheic seaway and development of upwelling zones in the western margin of Euramerica and the eastern Paleo-Tethys realm. Quantitative microfacies analysis across the Mississippian succession in the Gongchuan section shows facies-independent disappearance of corals and increased proportion of cortoids and filter-feeding organisms at the onset of the Asbian δC decline, which may support an increase in nutrient level that can be expected as a result of upwellin
Keywords: Euramerica; Foraminiferal zones; Late Paleozoic Ice Age; Paleo-Tethys; Point-counting; Visean

Microfacies, depositional environments and meter-scale cycles of the middle jurassic Tuwaiq Mountain formation, central Saudi Arabia - El-Yamani, Mahmoud Samir; Al-Ramadan, Khalid; Munnecke, Axel; Cantrell, Dave; Abdulghani, Waleed; Reub, Lukas (Journal of African Earth Sciences, 2018)

Microplastic contamination of the drilling bivalve Hiatella arctica in Arctic rhodolith beds - Teichert, Sebastian; Löder, Martin; Pyko, Ines; Mordek, Marlene; Schulbert, Christian; Wisshak, Max; Laforsch, Christian (Scientific Reports, 2021)
There is an increasing number of studies reporting microplastic (MP) contamination in the Arctic environment. We analysed MP abundance in samples from a marine Arctic ecosystem that has not been investigated in this context and that features a high biodiversity: hollow rhodoliths gouged by the bivalve Hiatella arctica. This bivalve is a filter feeder that potentially accumulates MPs and may therefore reflect MP contamination of the rhodolith ecosystem at northern Svalbard. Our analyses revealed that 100% of the examined specimens were contaminated with MP, ranging between one and 184 MP particles per bivalve in samples from two water depths. Polymer composition and abundance differed strongly between both water depths: samples from 40 m water depth showed a generally higher concentration of MPs and were clearly dominated by polystyrene, samples from 27 m water depth were more balanced in composition, mainly consisting of polyethylene, polyethylene terephthalate, and polypropylene. Long-term consequences of MP contamination in the investigated bivalve species and for the rhodolith bed ecosystem are yet unclear. However, the uptake of MPs may potentially impact H. arctica and consequently its functioning as ecosystem engineers in Arctic rhodolith bed

Microplastic pollution as a possible threat for an arctic reef system and its association of ecosystem engineers - Pyko, Ines; Löder, Martin; Schulbert, Christian; Wisshak, Max; Laforsch, Christian; Munnecke, Axel; Teichert, Sebastian (54th European Marine Biology Symposium, 2019)
The coralline red alga Lithothamnion glaciale forms rigid frameworks of magnesium calcite. The shelfs around the high arctic Svalbard archipelago (northern Norway) are intensely covered by these so-called rhodoliths. Drilled by boring mussels of the species Hiatella arctica , many rhodoliths become hollow ecospheres, inhabited by a great variety of benthic taxa. Thereby, these rhodolith communities can be regardedas arctic reef structures and increase the local biodiversity significantly, comparable to corals in the tropics. They also provide a possible nursery ground for fish. We report the first findings of microplastic ingested by individuals of H. arctica. Altogether, we identified eight different types of polymers via F-spectroscopy within the rhodolith-colonizing bivalves. The potential consequences for the bivalves can be manifold, including a negative impact on their function as an ecosystem-engineering organism. This would also affect the complete ecosystem of the Svalbard Shelf and its biodiversity.
Keywords: Arctic; biodiversity; ecosystem engineers; microplastic

Microproblematic organisms from the Norian-Rhaetian reefal carbonates of Saklikent, Taurus Mountains, southern Turkey - Senowbari-Daryan, Baba; Link, Michael (Facies, 2018)
UnivIS-Import:2018-09-05:Pub.2018.nat.dgeo.IGM.LP.microp

Microstructures of modern sea pen axes – a tool for the systematics of fossil pennatulaceans (Octocorallia) - Roden, Vanessa; Reich, Mike (Terra Nostra 2012/3, 2012)

Middle Ordovician sea-level changes and the evolution of the Ordovician conodont genus Cahabagnathus Bergström, 1983. - Leslie, Stephen Andrew; Lehnert, Oliver (Journal of Paleontology, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LG.middle

Middle to Upper Jurassic bivalves of the southwestern Morondava Basin (Madagascar) - Fürsich, Franz; Ayoub-Hannaa, Wagih; Heinze, Michael (Zitteliana, 2019)

Migration von Weichmachern und Beschichtungen während der extrakorporalen Perfusion in der Kardiotechnik - Münch, Frank; Göen, Thomas; Schulbert, Christian; Cesnjevar, Robert; Ihlenburg, Katharina Susanne (Abstracts der 40. Internationalen Jahrestagung der DGfK und 3. Fokustagung Herz, 2011)
UnivIS-Import:2017-12-18:Pub.2011.nat.dgeo.IGM.LP.migrat

Mineralogy and elemental geochemistry of pyrite coal-balls, Datong Coalfield, Shanxi Province, China: Implications for differentiation mechanism - Hao, Huidi; Huang, Wenhui; Hao, Ruilin; Mu, Nana; Wen, Long; Yu, Chunlan (Ore Geology Reviews, 2023)
The pyrite coal-balls found in No.9 coal of Taiyuan Formation in Dongzhouyao Mine of Datong Coalfield were selected to investigate its mineralogy and elemental geochemistry using optical microscope observation, scanning electron microscopy combined with an energy-dispersive X-ray spectrometer (SEM-EDX), inductively coupled plasma mass spectrometry analysis (ICP-MS), laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS), and electron probe micro-analysis (EPMA). Due to the high content of pyrite, the major-element oxides in the coal-ball samples were mainly Fe2O3, with an average of 62.68 %. LA-ICP-MS results showed that coal-balls were enriched in Tl (CC = 32.79), Pb (CC = 9.22), and Mo (CC = 2.07), while the coals in the same layer were enriched in Ga (CC = 5.31), Tl (CC = 3.66), and Li (CC = 2.27). Affinities to S or Fe and the variation of elemental concentration in the environment during the formation of coal-balls were the primary factor of the elemental differentiation between coals and coal-balls, as well as within coal-balls. The coal-balls formed in four stages in a marine-continental transition environment, with Fe from terrestrial sources and S from marine phases, and its physical origin is basically consistent with that of some Carboniferous-Permian coals in the Datong Coalfield. According to the formation sequence and geochemical characteristics, four periods of pyrite coal-balls evolution have been proposed.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Coal-balls; Datong Coalfield; Formation mechanism; Geochemical characteristics; Mineralogical characteristics

Mismatches of threat status and actual extinctions in Quaternary reef corals - Raja, Nussaïbah Begum; Lauchstedt, Andreas; Pandolfi, John M.; Kim, Sun W.; Budd, Ann F.; Kießling, Wolfgang (GSA 2020 Connects Online, 2020)
Species traits and spatial distributions influence the extinction risk of species as a result of abiotic and biotic change. We performed a comparative assessment of the relationship between traits and extinction risk of reef corals in the modern oceans against Plio-Pleistocene reef corals. We chose the Plio-Pleistocene as most of the corals during this time are still present today and their traits are thus comparable to those of modern corals. As such, the regional extinctions of reef corals during this time, attributed to climate change, may shed light on which traits contribute to the resilience or vulnerability of reef building corals in the face of contemporary ocean warming. We applied predictive modelling using two morphological and two distributional traits of 585 extant reef coral species together with data on extinction risk as reported by the International Union for Conservation of Nature (IUCN). This model was then validated against the fossil corals. Although our model performed well in the prediction of the extinction risk of modern corals (82% match), the match between our modelled extinction risk and observed extinction during the Plio-Pleistocene was not better than random. This suggests that either 1) the IUCN status for reef corals may not reflect true extinction risk, or 2) the drivers of extinction during the Plio-Pleistocene may be considerably different from the conditions currently observed in the oceans. This underlines the need to incorporate fossil data when assessing the vulnerability of extant species to climate chang

Mistelgau - Schulbert, Christian (2010)
Keywords: Tongrube; Unterer Jura; Mittlerer Jura; Mistelgau

Modern brackish bryostromatolites (“bryoliths”) from Zeeland (Netherlands) - Harrison, G. William M.; Claußen, Anna Lene; Schulbert, Christian; Munnecke, Axel (Palaeobiodiversity and Palaeoenvironments, 2021)
Bryostromatolites are found in stressed environments from the Paleozoic to the Recent. They are formed by alternating layers of bryozoans and microbes. This study investigates recent bryostromatolites in brackish ponds in the Netherlands to better understand ancient analogues and the environments which hosted them. They formed a fringing reef at the site Ronde Weel and a barrier reef at Kaaskenswater. The ponds had low biodiversity with only one bivalve species, two gastropod species, one ostracod species, and three diatom species comprising most of the easily fossilizable taxa; one isopod species, one decapod species, and two polychaete species were also present. Observations of microbial layers and cementation practices indicate that an alternation of bryozoan-favouring conditions and microbe-favouring conditions is essential to forming bryostromatolites. The collected bryostromatolites only had tiny living bryozoan patches. Water tests confirmed a brackish environment but with enriched arsenic and titanium concentrations and periodic euxinia. The extreme environment explains the lack of biodiversity and may provide information about the environments in which past bryostromatolites formed.<br
Keywords: Bryozoan; Bryostromatolite; Reef

Modularity explains large-scale reef booms in Earth’s history - Raja, Nussaïbah Begum; Pandolfi, John M.; Kießling, Wolfgang (Facies, 2023)
Drivers of reef decline are well known both today and in the geological past. Considerably less is known about the preconditions for a pantropical expansion of coral reefs. The geological record of reef building is characterised by considerably long intervals with very limited reef expansion and geologically brief (< 20 million years) episodes of prolific, pantropical reef growth. Here, we propose a new "co-occurrence hypothesis" (COH), which posits that reefs thrive when fast-growing hypercalcifiers co-occur with encrusting organisms such as calcifying microbes or coralline algae to construct wave-resistant structures. While there is little evidence of the effect of abiotic drivers on reef proliferation, we find that positive co-occurrence patterns are significantly more common in reefal as compared to non-reefal communities, suggesting that biological interactions are more relevant in reefs than in non-reefs. Supporting COH, we also show that reefs after the end-Permian mass extinction became more modular in nature with limited membership in reef assemblages during reef booms than in typical periods of reef growth (background intervals). Modularity in reefs may have led to the stabilisation of reef ecosystems, giving them the ability to recover from small perturbations, promoting reefal carbonate accretion and prolific reef growth.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Co-occurrence; Modularity; Palaeobiology; Reefs

Morphological characters and ontogenetic development of deep-sea species of the genus Caryophyllia - Vertino, Agostina; Stolarski, Jarosław; Schulbert, Christian (13th International Symposium onFossil Cnidaria and PoriferaModena, ABSTRACT BOOK, 2019)
The genus Caryophyllia is known from shallow- to deep-waters in all oceans and seas of the planet and itincludes 66 valid Recent species. Though frequently reported as fossil, at least since the Upper Jurassic, thedistribution of valid Caryophyllia species in the paleontological record is still unknown. Only consideringthe Neogene and Pleistocene deposits of the Mediterranean, over 100 species are mentioned in the ancientliterature but they have never been revised following modern taxonomic concepts. The diagnostic taxonomic character that distinguishes the genus Caryophyllia from the other genera ofthe family Caryophylliidae is the presence of pali before the penultimate, rarely the antepenultimate cycle ofsepta. Mitochondrial 16S rRNA phylogeny analyses of modern species support grouping Caryophyllia in oneclade, however, two other taxa included in this clade (Crispatotrochus rugosus and Dasmosmilia lymani) donot develop pali (Crispatotrochus) or develop structures called paliform lobes before all but the last septalcycle. The distinction between pali and paliform lobes remains ambiguous not only in Caryophyllia but inseveral other scleractinian taxa. For that reason, precise documentation of ontogenetic development of bothskeletal structures is of general importance for scleractinian coral researchers. This study aims at describing the morphological variability and ontogenetic development of deep-sea Caryophyllia species collected from Pleistocene deposits of southern Italy and from modern seafloors of theMediterranean and the NE Atlantic. By analysing SEM and micro-CT images, as well as polished and thinsections, particular attention has been devoted to (1) the micromorphology of the coral wall and calicularfeatures and (2) the arrangement and ontogenetic development of pal
Keywords: Corals; Cariophyllia; micro-CT; µCT; ontogeny

Morphological disparity and ontogeny of the endemic heteromorph ammonite genus Aegocrioceras (Early Cretaceous, Hauterivian, NW-Germany) - Hoffmann, René; Weinkauf, Manuel; Wiedenroth, Kurt; Goeddertz, Peter; de Baets, Kenneth (Palaeogeography, Palaeoclimatology, Palaeoecology, 2019)
Despite the fact that heteromorph ammonites often show a large range of intraspecific variation, that variation has rarely been quantified. Here, we quantify the intraspecific variation and ontogeny of 85 newly collected specimens of the Hauterivian endemic ammonite genus Aegocrioceras. All specimens were collected from concretions in the recently exposed bed 82 in the clay pit Resse in NW Germany (Lower Saxony Basin). Data for the conch morphology (diameter, whorl height, whorl interspace, rib spacing) were collected in 45° steps using the new software CONCH©. The CONCH© software will be made officially available with this publication. All ammonites were a priori identified as A. bicarinatum or A. semicinctum. An assessment of the intra- and interspecific variation as well as the ontogeny of this assemblage demonstrates the presence of just one species, i.e., A. bicarinatum. Comparison with the type material of A. bicarinatum and A. semicinctum reveals a large morphological overlap of different conch parameters and does not support a separation of both forms as distinct species. The analyzed assemblage of A. bicarinatum has a high variation in conch morphology including whorl interspace, umbilical width, and whorl expansion. Furthermore, the changes in intraspecific variation through ontogeny were quantified and the presence or absence of sexual dimorphism within the assemblage is discusse
Keywords: Aegocrioceras bicarinatum; Aegocrioceras semicinctum; Systematics; Sexual dimorphism; Morphometric measurement software CONCH©

Morphological response accompanying size reduction of belemnites during an Early Jurassic hyperthermal event modulated by life history - Nätscher, Paulina; Dera, Guillaume; Reddin, Carl J.; Rita, Patrícia; de Baets, Kenneth (Scientific Reports, 2021)
One of the most common responses of marine ectotherms to rapid warming is a reduction in body size, but the underlying reasons are unclear. Body size reductions have been documented alongside rapid warming events in the fossil record, such as across the Pliensbachian-Toarcian boundary (PToB) event ( 183 Mya). As individuals grow, parallel changes in morphology can indicate details of their ecological response to environmental crises, such as changes in resource acquisition, which may anticipate future climate impacts. Here we show that the morphological growth of a marine predator belemnite species (extinct coleoid cephalopods) changed significantly over the PToB warming event. Increasing robustness at different ontogenetic stages likely results from indirect consequences of warming, like resource scarcity or hypercalcification, pointing toward varying ecological tolerances among species. The results of this study stress the importance of taking life history into account as well as phylogeny when studying impacts of environmental stressors on marine organisms.
CRIS-Team Scopus Importer:2021-08-06

Morphological traits of reef corals predict extinction risk but not conservation status - Raja, Nussaïbah Begum; Lauchstedt, Andreas; Pandolfi, John M.; Kim, Sun W.; Budd, Ann F.; Kießling, Wolfgang (Global Ecology and Biogeography, 2021)
Aim The current assessment of extinction risk in reef corals by the International Union for Conservation of Nature (IUCN) has been criticized, because coral life-history traits associated with resilience are not reflected in the conservation status. We aimed to carry out a quantitative assessment of the link between reef coral traits and species extinction risk informed by extinctions of reef corals observed in the fossil record. Location Global. Time period Plio-Pleistocene and present day. Major taxa studied Scleractinian reef corals. Methods We used morphological traits, phylogenetic information and evidence of extinction during the Plio-Pleistocene to predict the extinction risk of contemporary reef corals. Our model was trained using 138 Caribbean fossil coral species and an automatic machine learning algorithm. We then used this model to predict the extinction risk of 674 modern coral species. Results Model validation confirmed 77% accuracy in predicting extinction risk of fossil corals. Extinction risk predicted by our model showed a near-random (57%) match with the IUCN conservation status. Our model also suggested that corals in the Least Concern or Near Threatened categories might be at higher risk of extinction than currently believed. Main conclusions Morphological traits of fossil corals linked to their extinction risk in the Plio-Pleistocene Caribbean Sea are known to reflect the vulnerability of extant corals. However, the results from our fossil-calibrated model do not match the IUCN assessment of reef corals, with increased overall extinction risk. This does not necessarily indicate near-future extinction risk, because fossil extinctions are spread over thousands of years. However, we show the applicability of using fossil data to inform the extinction risk of modern corals and recommend that future assessments of extinction risk of reef corals should consider incorporating the relationship between morphological traits and resilience, calibrated by fossil data, to maximize the utility of the extinction risk assessment. <br
Keywords: extinction risk; fossil record; predictive modelling; Red List; reef corals; traits

Morphological variability of peteinoid acritarchs from the Middle Ordovician of Öland, Sweden, and implications for acritarch classification - Kroeck, David M.; Eriksson, Mats E.; Lindskog, Anders; Munnecke, Axel; Dubois, Michel; Regnier, Sylvie; Servais, Thomas (Palynology, 2021)
Investigation of large populations of peteinoid acritarchs recovered from Middle Ordovician strata of the Hälludden and Horns Udde quarry sections (Öland, Sweden) allows for statistical analyses based on morphometric measurements. The results indicate the presence of assemblages with a continuous variability of morphotypes, thus a distinction of different peteinoid acritarch taxa in the sections proved to be impossible. This challenges the currently accepted classification based on a differentiation into the three genera Peteinosphaeridium, Cycloposphaeridium and Liliosphaeridium, and a multitude of different species; individual taxa are essentially arbitrary as morphotypes intergrade. Investigations on modern dinoflagellates show that these can develop variable cyst morphologies depending on environmental factors. By analogy, it can be hypothesised that the different morphologies observed among the peteinoid acritarchs from Öland are cysts produced by only very few phytoplanktic organisms (or even a single species) with high morphological variability.
CRIS-Team Scopus Importer:2021-06-04
Keywords: ecophenotypism; Palaeozoic Darriwilian; Phytoplankton; taxonomy

Morphology and systematics of fossil and recent sea pens (Octocorallia: Pennatulacea) - Roden, Vanessa; Reich, Mike (12th International Symposium on Fossil Cnidaria and Porifera 2015 - Abstract Volume, 2015)

Mosses like it rough-growth form specific responses of mosses, herbaceous and woody plants to micro-relief heterogeneity - Leutner, Benjamin; Steinbauer, Manuel; Müller, Carina; Früh, Andrea; Irl, Severin; Jentsch, Anke; Beierkuhnlein, Carl (Diversity, 2012)
Micro-relief heterogeneity can lead to substantial variability in microclimate and hence niche opportunities on a small scale. We explored the relationship between plant species richness and small-scale heterogeneity of micro-relief on the subtropical island of La Palma, Canary Islands. Overall, we sampled 40 plots in laurel and pine forests at four altitudinal bands. Species richness was recorded separately for various growth forms (i.e., mosses, herbaceous and woody plants). Site conditions such as altitude, slope, aspect, and tree density were measured. Micro-relief heterogeneity was characterized by surface structure and a subsequently derived surface heterogeneity index. The effect of micro-relief heterogeneity on species richness was analysed by means of linear mixed effect models and variance partitioning. Effects of micro-relief heterogeneity on species richness varied considerably between growth forms. While moss richness was affected significantly by micro-relief heterogeneity, herbaceous and woody plants richness responded mainly to larger-scale site conditions such as aspect and tree density. Our results stress the importance of small-scale relief heterogeneity for the explanation of spatial patterns of species richness. This poses new challenges as small-scale heterogeneity is largely underrepresented, e.g. with regard to its application in species distribution models.
Keywords: Altitudinal gradient; Biodiversity; Bitterlich; Climate change; Habitat heterogeneity; Laurel forest; Micro-topography; Northernness; Species diversity; Topographic variability

Multiproxy approach to understanding the origin of Cretaceous pelagic limestone-marl alternations (DSDP site 391, Blake-Bahama Basin) - Westphal, Hildegard; Munnecke, Axel; Pross, Jörg; Herrle, Jens; Munnecke, Axel; Munnecke, Axel (Sedimentology, 2004)
Limestone-marl alternations are usually directly interpreted to reflect cyclic palaeoenvironmental signals. However, uncertainty in such interpretations stems from the differential diagenesis that most limestone-marl alternations have undergone. Differential diagenesis results in markedly different alterations between limestones and marls and in the loss of comparability of many measurable parameters. For an unequivocal interpretation of the origin of rhythmic alternations, diagenetically robust parameters or parameters that clearly indicate the degree of diagenetic bias are required. The present study uses a multiproxy approach (independent biotic, sedimentary and geochemical parameters) in order to unravel the palaeoenvironmental signal recorded in Valanginian (Early Cretaceous) limestone-marl alternations from the Blake-Bahama Basin (DSDP site 391). Using this approach, terrestrial and marine influences can be distinguished, changes in nutrient levels estimated and prediagenetic differences in the non-carbonate fraction constrained. Surprisingly, no systematic variations in any of these parameters were observed between limestone and marl layers, implying that none of these was directly responsible for the formation of the rhythmic alternation. Hence, none of the current models of sedimentary formation of limestone-marl rhythmites is applicable here. Calcareous nannofossils are equally well preserved in limestone and marl layers, ruling out their dissolution in marl layers as a source of the calcite cement in the limestone beds. Sr values of 700-900 p.p.m. indicate that aragonite may have been present in the original, pelagic sediment. The assumption of fine-grained sedimentary aragonite imported from nearby carbonate platforms as the source of the cement would explain a number of otherwise enigmatic features in these rhythmites, including the source of the calcite cement observed in the limestones, the equally good preservation of calcareous nannofossils in limestones and marls and the higher concentration of calcareous nannofossils in marl layers. The study demonstrates that examination of diagenetically inert parameters or parameters in which diagenetic effects can be filtered can yield unexpected results. Clearly, careful analysis of such parameters needs to be undertaken in order to make reliable palaeoenvironmental interpretations from rhythmite successions. © 2004 International Association of Sedimentologist
Keywords: Calcareous nannofossils; Cretaceous; Differential diagenesis; DSDP; Limestone-marl alternations; Palynomorphs

Mustelids from Sackdilling Cave (Bavaria, Germany) and their biostratigraphic significance - Marciszak, Adrian; Ambros, Dieta Carola; Hilpert, Brigitte (Geobios, 2021)
Sackdilling Cave is a karst fissure filled with a fossiliferous breccia including abundant fossil remains, mostly snails and small mammals. The taxonomic status of mustelid remains from this cave was previously regarded as controversial and, consequently, different authors listed different species from the locality. A detailed revision of the material shows the presence of five mustelid species: Meles sp., Martes vetus, Mustela strandi, Mustela palerminea, and Mustela praenivalis. Among them, especially noteworthy is the presence of the type specimen of Martes vetus. The Sackdilling holotype resembles Martes foina and differs from that of Martes martes in a short and broad viscerocranium; wide and less extended forward incisor row; compressed, short and wide temporal region; large, strongly inflated and convex tympanic bullae; and narrow P3 with weak lingual bulge. Some dental characters are specific for Martes vetus and show some intermediate values between Martes foina than Martes martes. Among them are the P4 protocone length and the M1 trigon length. The revised material from Sackdilling Cave of Mustela palerminea and Mustela praenivalis was compared with that from other Early and early Middle Pleistocene sites of Europe and showed the presence of intermediate characters. Subsequently, based on the entire mustelid assemblage and other faunal elements (mainly rodents), the age of this fauna was estimated as ca. 0.9-0.7 Ma. (C) 2021 Elsevier Masson SAS. All rights reserved.
CRIS-Team WoS Importer:2021-11-19

Mythos Drache: Schwingen, Schuppen, Schwefeldämpfe. Ein studentisches Forschungsprojekt auf Spurensuche - Link, Michael (Skeptiker, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dgeo.IGM.LP.mythos

Neodymium isotopes of central Mediterranean phosphatic hardgrounds reveal Miocene paleoceanography - Cornacchia, Irene; Brandano, Marco; Agostini, Samuele; Munnecke, Axel (Geology, 2022)
Understanding the causes of the formation of hardgrounds provides insights on the oceanographic evolution of a basin. Phosphate-rich hardground formation interrupted carbonate ramp deposition in the Mediterranean during the Miocene. We analyzed the epsilon(Nd) record of three central Mediterranean hardgrounds to identify the origin of the phosphate-rich waters that formed them within the frame of Mediterranean Miocene paleoceanographic evolution. The Nd isotopes suggest that eastern Mediterranean deep waters were controlled by runoff, in contrast to Atlantic and Indian Ocean waters. This Nd isotope record attests to the weakening of Mediterranean circulation during the Miocene due to closure of the Indian Gateway. Limited exchange with Atlantic shallow seawater led to long residence times for deep waters in the basin. This record indicates the role of upwelling in formation of phosphate hardgrounds and shows the influence of global climate change and local paleoceanographic conditions.
CRIS-Team WoS Importer:2022-06-24

Neptunian dykes in the Devonian carbonate buildup Aferdou El Mrakib (eastern Anti-Atlas, Morocco) and implications for its growth - Tessitore, Lorena; Naglik, Carole; de Baets, Kenneth; Galfetti, Thomas; Klug, Christian (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2016)
Aferdou El Mrakib is the largest single carbonate buildup in the eastern Anti-Atlas, Morocco. Its sediments are intersected by several Neptunian dykes. Herein, we compare their facies, spatial arrangement and the associated fauna to that of Neptunian dykes from other mound localities in Morocco and elsewhere in order to assess their origin as well as that of the mound. One of the studied dykes is filled with pisoids. Its facies suggests some kind of seep origin, but the carbon and oxygen isotopic values have only slightly negative signatures, which might be diagenetic, thus prohibiting further interpretation. Nevertheless, the unique occurrence of pisoids at a depth of c. 50 metres below the mound surface within a dyke is herein interpreted as supporting the presence of a source with a considerable discharge.
Keywords: Morocco; Devonian; Maider Basin; carbonate buildups; Neptunian dykes; pisoids

Neuaufschluss des berühmten Schwarzjura-Profils am historischen Ludwig-Donau-Main-Kanal bei Dörlbach/Mittelfranken - Arp, Gernot; Schulbert, Christian; Seuß, Barbara; Aiglstorfer, Manuela; Havlik, Philipe; Krause, Thorsten; Waltschew, Anton; Strobl, Christian (GMIT - Geowissenschaftliche Mitteilungen, 2011)
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.neuauf

New biostratigraphic and chemostratigraphic data from the Chicotte Formation (Llandovery, Anticosti Island, Laurentia) compared with the Viki core (Estonia, Baltica) - Munnecke, Axel; Männik, Peep (Estonian Journal of Earth Sciences, 2009)
Due to the lack of biostratigraphically useful graptolites in the crinoidal and reefal Chicotte Formation on Anticosti Island (Québec, Canada), the precise chronostratigraphic position of the formation is not known. New stable carbon isotope and conodont data and a comparison with the detailed conodont distribution and δC development in the Viki core (Estonia) suggest an early Telychian age (Pterospathodus eopennatus to P. a. angulatus zones) for at least the lower half of the formation. This interval is characterized by a small but distinct positive excursion in δC, with peak values of + 3.2% and + 2.8% VPDB in the lowermost 10-15 m of the Chicotte Formation on Anticosti and in the Viki core, respectively.
Keywords: conodonts; stable carbon isotopes; Anticosti; Estonia; Llandovery; Telychian

New chemostratigraphic through the Middle Mulde Event interval (Silurian, Wenlock), Gotland, Sweden - Calner, Mikael; Lehnert, Oliver; Jeppsson, Lennart (Gff, 2012)
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LG.newche

New constraints on the last aragonite-calcite sea transition from early Jurassic ooids - Vulpius, Sara; Kießling, Wolfgang (Facies, 2018)
Calcite and aragonite seas are commonly distinguished based on the prevailing primary mineralogy of ooids and carbonate cements over time. Secular oscillations of these seas are usually attributed to changes in ocean chemistry and paleoclimate. While the veracity of such oscillations has been verified by independent data and modeling approaches, the timing of the transition from one ocean state to the other remains poorly resolved. Here, the timing of the last aragonite-calcite sea transition is estimated by assessing the preservation of Early Jurassic ooids from the Trento Platform in northern Italy. Point counting of ooid-bearing limestones from four distinct stratigraphic levels provides a contrasting pattern: Hettangian and Sinemurian ooids are all poorly preserved and were probably predominantly originally aragonitic, whereas Pliensbachian and Toarcian ooids are excellently preserved, suggesting a primary calcitic mineralogy. Although calcitic ooids may have already been common in the Late Triassic, it is proposed that the last aragonite-calcite sea transition occurred in the Early Jurassic between the Sinemurian and Pliensbachian, at least in this subtropical region. Therefore, the selective extinction of aragonite-secreting organisms at the end-Triassic mass extinction cannot be attributed to secular changes in ocean chemistry.
Keywords: Ooid; Calcite; Aragonite; Lower to Middle Jurassic; Italy; Northern Alps

New exposure of the Ludwigskanal section near Dorlbach - a key section for the Lower Jurassic in the Franconian Alb, Southern Germany - Arp, Gernot; Aiglstorfer, Manuela; Havlik, Philipe; Krause, Thorsten; Schulbert, Christian; Seppelt, Stephan (Zeitschrift der Deutschen Gesellschaft für Geowissenschaften, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.newexp

New monofunctional platinum(II) and palladium(II) complexes: Studies of the nucleophilic substitution reactions, DNA/BSA interaction, and cytotoxic activity - Cocic, Dugan; Jovanovic, Snaana; Radisavljevic, Snezana; Korzekwa, Jana; Scheurer, Andreas; Puchta, Ralph; Baskic, Dejan; Todorovic, Danijela; Popovic, Suzana; Matic, Sanja; Petrovic, Biljana (Journal of Inorganic Biochemistry, 2018)
Keywords: Kinetics; DNA; DFT; Cytotoxicity; Pd(II) and Pt(II) complexes; BSA

New Ordovician-Silurian drill cores from the Siljan impact structure in central Sweden - an integral part of the Swedish Deep Drilling Program - Lehnert, Oliver; Meinhold, Guido; Bergström, Stig M.; Calner, Mikael; Ebbestad, Jan Ove; Egenhoff, Sven; Frisk, Asa; Hannah, Judith L.; Högström, Annette E. S.; Huff, Warren D.; Juhlin, Christopher; Maletz, Jörg; et al. (Gff, 2012)
New drill cores from the largest known impact structure in Europe, the relict of the Siljan meteorite crater, provide new possibilities to reconstruct Early Palaeozoic marine environments and ecosystems, and to document changes in sedimentary facies, sea level and palaeoclimate in Baltoscandia. The impact crater is an important target of the project "Concentric Impact Structures in the Palaeozoic" within the framework of the "Swedish Deep Drilling Program". Two core sections, Mora 001 and Solberga 1, have been analysed. The sedimentary successions of these core sections include strata of late Tremadocian through late Wenlock ages. Our preliminary studies show not only that several of the classical Palaeozoic units of Sweden are represented in the area, but also that other significantly different facies are preserved in the Siljan district. An erosional unconformity representing a substantial hiatus occurs between Middle Ordovician limestone and a Llandovery-Wenlock (Silurian) shale succession in the western part of the Siljan structure and suggests an extended period of uplift and erosion. This may be related to forebulge migration due to flexural loading by the Caledonian thrust sheet to the west. Thus, this part of Sweden, previously regarded as a stable cratonic area, presumably was affected by the Caledonian collision between Baltica and Laurentia. © 2012 Copyright Geologiska Föreningen.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LG.neword
Keywords: impact structure; Ordovician; Siljan district; Silurian; stratigraphy; Sweden

New radiolarians from the earliest Cretaceous of the Sultanate of Oman (Wahrah Formation, Jebel Buwaydah) - Kießling, Wolfgang (Palaeontologische Zeitschrift, 1995)

New radiometric datings of different cave bear sites in Germany - results and interpretations - Rosendahl, Wilfried; Döppes, Doris; Joger, Ulrich; Laskowski, Rainer; López Correa, Matthias; Nielbock, Ralf; Wrede, Volker (Bulletin de la Société d'histoire naturelle de Toulouse, 2005)
New radiometric dates from seven cave bear sites in Germany were achieved during the last two years. The dates were obtained for four sites from bone samples, for one site from two stalagmites and from another site from charcoal and bones. The bones and the charcoal have been dated with the AMS 14C-method and the stalagmites with the TIMS-U/Th-method. Sites are briefly described and all dates with their analytic values are presented and discussed in methodological and paleoclimatic context. Radiocarbon ages were calibrated using calPal2004 (www.calPal.de) and paleoclimatic interpretation was made by correlation with the GISP2 ice core δ18O-curve (Stuiver & Grootes, 2000), GI = Greenland Interstadial of the GIPS2 ice core.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LP.newrad
Keywords: cave bear

New records of early Middle Jurassic belemnites in the French Subalpine Basin and their paleobiogeographic significance - Mariotti, Nino; Weis, Robert; di Cencio, Andrea; Clément, Arnaud; de Baets, Kenneth (Geobios, 2012)
A biostratigraphic and systematic study based on belemnites collected along with ammonites was performed on four sections in the Subalpine Basin (SE France): Lac du Castillon and La Baurne (Castellane area), Galabrun and Grand Lara (Gap area). The specimens, originating from hemi-pelagic marllimestone alternations in the lower part of the "Calcaires a Zoophycos" Formation, are dated from Middle Aalenian (Murchisonae Zone) to Lower Bajocian (Humphriesianum Zone). Five belemnite taxa (Megateuthis elliptica, Holcobelus munieri, H. trauthi, Pachybelemnopsis roettingensis, Hibolithes sp.) have been identified, and two more taxa are reported in an open nomenclature (Belemnitida incertae sedis sp. 1 and sp. 2). The biostratigraphic range of the belemnite fauna is established. The new findings contribute to a more detailed understanding of the paleobiogeography of holcobelid belemnites that flourished at the northern margin of the Tethys Ocean and formed a distinct sub-Mediterranean fauna. The association herein described is similar to the fauna of the Calabro-Peloritani Arc (Calabria, Italy), a further hint for the supposed paleogeographic position of the latter during the Middle Jurassic. (C) 2012 Elsevier Masson SAS. All rights reserved.
Keywords: Holcobelidae; Megateuthididae; Mesohibolithidae; Middle Jurassic; Subalpine Basin; Biostratigraphy; Paleobiogeography

New SEM observations of keriothecal walls: Implications for the evolution of fusulinida - Vachard, Daniel; Munnecke, Axel; Servais, Thomas; Munnecke, Axel; Munnecke, Axel (Journal of Foraminiferal Research, 2004)
This study presents new scanning electron microscopy (SEM) observations of Paleozoic foraminifera. It focuses especially on the wall of three Fusulinida, Sakmarella moelleri, Paraskinnerella skinneri, and Taiyuanella furoni, that belong to the Schwagerinoidea, which are fusulinids with keriothecal test walls. In addition, Eostaffella sp. is investigated as an example of the microstructure of the microgranular imperforate tectum. The fillings of the keriothecal alveoles of Sakmarella, Paraskinnerella, and Taiyuanella yield diverse, characteristic flower-like structures that indicate a gradual evolution of the microstucture of the tests. Sakmarella and Paraskinnerella have flowers with a narrow center, and Taiyuanella has a larger center. The true keriothecal structure, described, for example, in Triticites, is distinguished from these structures by simply filled alveoles. The term "anthotheca" is introduced for the structure with narrow-centered flowers. It can be distinguished from the large-centered flower structure identified as Zhuang's (1989) stalactotheca. Following a literature review of previous work on keriothecal structures, several morphofunctional hypotheses are discussed, including the housing of symbiotic algae or cyanobacteria, which leads to the new interpretation that the flowers of the antho- and stalactothecal structures are induced by algal endosymbionts. In addition, we discuss the monophyly of keriothecal fusulinids. The transition from diaphanothecal to keriothecal forms recognized since Thompson (1964) is reinterpreted in terms of relationships with symbiotic algae or cyanobacteria. The Schwagerinoidea constitute an important group in understanding the evolution of larger foraminifera in the late Paleozoic.

Noble guests in organic cages–encapsulation of noble gases by cryptophane - Ćoćić, Dušan; Puchta, Ralph; van Eldik, Rudi (Journal of Coordination Chemistry, 2020)
With the application of DFT calculations (ωB97XD/def2-SVP/SVPfit), the ability and mechanism of noble gas encapsulation by cryptophane was investigated. Based on the applied model reaction, by monitoring geometric changes and investigating the non-covalent interactions between the studied hosts and the noble gases, the size of the host did not necessarily play a decisive role in the selective encapsulation of the guests. Rather the adjustment of the host’s interior and functionalization of its “gates” can be significant in tuning the affinity of cryptophanes.
CRIS-Team Scopus Importer:2020-10-02
Keywords: cryptophane; DFT; host-guest chemistry; Noble gases

No (Cambrian) explosion and no (Ordovician) event: A single long-term radiation in the early Palaeozoic - Servais, Thomas; Cascales-Miñana, Borja; Harper, David A.T.; Lefebvre, Bertrand; Munnecke, Axel; Wang, Wenhui; Zhang, Yuandong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)
The Cambrian ‘Explosion’, located by many authors between 540 and 520 million years ago (Ma), is considered to be an abrupt appearance in the fossil record of most animal phyla, with a sudden increase of complex morphologies across metazoan groups. In a few recent papers, the Great Ordovician Biodiversification ‘Event’ (GOBE) has similarly been restricted to a single dramatic biodiversification ‘event’ in the Darriwilian Stage of the Middle Ordovician Series, between 470 and 455 Ma, although historically the biodiversification is considered as an aggregation of radiation ‘events’ capturing a large and complex increase of taxonomic diversity of marine invertebrates covering the entire Ordovician. A review of biodiversity curves of marine organisms during the early Palaeozoic, including some based on data in the Paleobiology Database (PBDB) and the Geobiodiversity Database (GBDB), points towards a single, large-scale, long-term early Palaeozoic radiation of life that already started in the late Precambrian. An abrupt ‘explosion’ of diversity in the Cambrian or a significant ‘event’ in the Ordovician are not visible in our biodiversity studies, because they are either regional, or only reflect a single group of organisms. It is evident that the datasets remain incomplete, in particular those for many geographical areas and for several fossil groups, that are not covered by the PBDB and GBDB; also, such areas remain so far poorly or entirely unstudied. Some recently published biodiversity curves have to be considered with care, as the truly global diversity estimates of marine organisms during the early Palaeozoic remain elusive. Here, we argue that published curves of taxonomic richness, which show distinct periods of diversification, cannot sufficiently be disentangled from biases. We therefore question the existence of a distinct Cambrian ‘Explosion’ and global Ordovician ‘Event’ in the global datasets. Both terms, Cambrian ‘Explosion’ and Great Ordovician Biodiversification ‘Event should be used as conceptional terms only. The first represents the appearance of almost all animal phyla during the late Precambrian and early Cambrian, whereas the second term embraces the numerous and complex radiations that occurred during the entire Ordovician.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Biodiversity; Cambrian Explosion; Geobiodiversity Database; Great Ordovician Biodiversification Event; Paleobiology Database; Radiation

Norithamnium madoniensis Senowbari-Daryan, Keupp, Abate & Vartis-Matarangas, 2002 in the Anisian reef boulders from Karaburun Peninsula, Turkey - Senowbari-Daryan, Baba; Link, Michael (Journal of alpine geology, 2007)
From the Anisian reef boulders embedded within the Gerence Formation in Karaburun Peninsula, Turkey the species Norithamnium madoniensis (Corallinales, Rhodophyta) is described. The genus was known until now from the Norian-Rhaetian reef limestones of Sicily, Greece, and Austria. The Anisian of Karaburun is the fourth locality and probably the oldest occurrence.
UnivIS-Import:2015-04-14:Pub.2007.nat.dgeo.IGM.LP.norith
Keywords: Algae; Corallinales; Rhodophyta; Norithamnium; Anisian; Karaburun; Turkey

Normal giants? Temporal and latitudinal shifts of Palaeozoic marine invertebrate gigantism and global change - Klug, Christian; de Baets, Kenneth; Kröger, Björn; Bell, Mark Alan; Korn, Dieter; Payne, Jonathan Louis; de Baets, Kenneth (Lethaia, 2015)
During and after the Cambrian explosion, very large marine invertebrate species have evolved in several groups. Gigantism in Carboniferous land invertebrates has been explained by a peak in atmospheric oxygen concentrations, but Palaeozoic marine invertebrate gigantism has not been studied empirically and explained comprehensively. By quantifying the spatiotemporal distribution of the largest representatives of some of the major marine invertebrate clades (orthoconic cephalopods, ammonoids, trilobites, marine eurypterids), we assessed possible links between environmental parameters (atmospheric or oceanic oxygen concentrations, ocean water temperature or sea level) and maximum body size, but we could not find a straightforward relationship between both. Nevertheless, marine invertebrate gigantism within these groups was temporally concentrated within intervals of high taxonomic diversity (Ordovician, Devonian) and spatially correlated with latitudes of high occurrence frequency. Regardless of whether temporal and spatial variation in sampled diversity and occurrence frequency reflect true biological patterns or sampling controls, we find no evidence that the occurrences of giants in these groups were controlled by optimal conditions other than those that controlled the group as a whole; if these conditions shift latitudinally, occurrences of giants will shift as well. It is tempting to attribute these shifts to contemporary changes in temperature, oxygen concentrations in the atmosphere and the oceans as well as global palaeogeography over time, but further collection-based studies are necessary on finer stratigraphic and phylogenetic resolution to corroborate such hypotheses and rule out sampling or collection biases.
Keywords: Arthropoda; Cephalopoda; macroecology; mass extinctions; palaeodiversity; palaeogeography; Palaeozoic

North Atlantic intermediate water variability over the past 20,000 years - Yasuhara, Moriaki; deMenocal, Peter B.; Dwyer, Gary S.; Cronin, Thomas M.; Okahashi, Hisayo; Huang, Huai-Hsuan (Geology, 2019)
North Atlantic intermediate-water temperature variations based on ostracod Mg/Ca ratios from Ocean Drilling Program (ODP) Hole 1055B document a series of multi-centennial-scale abrupt warming events throughout the last deglaciation and Holocene (up to 3 °C). These events are coherent with abrupt climate reversals including Heinrich event 1, the Younger Dryas-Intra-Allerød cold period, and Holocene North Atlantic Deep Water (NADW) reduction periods. Deglacial-Holocene warm events were likely related to reduction in the strength of the upper NADW (Labrador Sea Water). We also found a long-term cooling trend in the ODP 1055 Mg/Ca record indicating continuous Labrador Sea Water strengthening throughout the Holocene. Our results help to better understand deglacial-Holocene upper NADW dynamics that remain poorly understood but can be important for regional and global climates.
CRIS-Team Scopus Importer:2019-07-09

Northeastern Atlantic cold-water coral reefs and climate - Frank, Norbert; Freiwald, André; López Correa, Matthias; Wienberg, Claudia; Eisele, Markus; Hebbeln, Dierk; van Rooij, David; Henriet, Jean-Pierre; Colin, Christophe; van Weering, Tjeerd; de Haas, Henk; Buhl-Mortensen, Pål; et al. (Geology, 2011)
U-series age patterns obtained on reef framework-forming cold-water corals collected over a nearly 6000-km-long continental margin sector, extending from off Mauritania (17°N; northwest Africa) to the southwestern Barents Sea (70°N; northeastern Europe), reveal strong climate infl uences on the geographical distribution and sustained development of these ecosystems. Over the past three glacial-interglacial cycles, framework-forming cold-water corals (Lophelia pertusa and Madrepora oculata) seem to have predominantly populated reefs, canyons, and patches in the temperate East Atlantic and the Mediterranean Sea. Above 50°N corals colonize reefs in the northern East Atlantic primarily during warm climate periods with the biogeographic limit advancing from 50°N to 70°N. We propose that north-south oscillations of the biogeographic limit of reef developments are paced by ice ages and may occur synchronously with north-south displacement of cold nutrient-rich intermediate waters and surface productivity related to changes of the polar front. © 2011 Geological Society of America.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.northe

Notes on Palaeontological Societies - Reich, Mike; Gehler, Alexander; Roden, Vanessa (Jahrestagung der Paläontologischen Gesellschaft. 8.-10. September 2008, Erlangen, 2008)

Oases of biodiversity: Early Devonian palaeoecology of Hamar Laghdad, Morocco - Klug, Christian; Samankassou, Elias; Pohle, Alexander; de Baets, Kenneth; Franchi, Fulvio; Korn, Dieter (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2018)
The mudmound locality of Hamar Laghdad (Tafilalt Platform) contains possibly the greatest palaeobiodiversity, both horizontally in the surrounding sediments and stratigraphically through the Devonian sedimentary succession of the Moroccan eastern Anti-Atlas. From the Ordovician to the Devonian, sediments of the Hamar Laghdad region and their fossil contents tend to differ slightly from those in time-equivalent strata of other parts of the Tafilalt Platform. Our research provides a description of the sedimentological and palaeontological record of Hamar Laghdad covering the Lochkovian to Givetian interval. We use alpha-diversity data based on macrofossils from selected fossiliferous strata and compare the results with the relative abundance of bioclasts in polished sections. We show that the palaeobiodiversity of Hamar Laghdad was similar to that of the southern Tafilalt with a normal diversity during the Pragian, i.e. prior to mudmound initiation and growth. By contrast, the layers covering the massive mudmound carbonates (e.g., when their activity had ceased) show a high diversity during the latest Emsian with a trophic nucleus comprising 36 species. This fauna, here exemplified by the ‘Red Fauna’ (from the Red Cliff), is dominated by benthic suspension feeders (corals, brachiopods and crinoids) and cephalopods. The shift in biodiversity is most likely related to the local occurrence of a favourable environmental setting, characterized by a temporally and spatially varying topography. It is assumed that this setting was influenced by sea-level fluctuations, currents and nutrient availabilit

Ocean and Coastal Ecosystems and their Services, in: Climate Change 2022: Impacts, Adaptation and Vulnerability. Working Group II Contribution to the IPCC Sixth Assessment Report - Cooley, Sarah; Schoeman, David; Bopp, Laurent; Boyd, Philip; Donner, Simon; Ghebrehiwet, Dawit Yemane; Ito, Shin-Ichi; Kießling, Wolfgang; Martinetto, Paulina; Ojea, Elena; Racault, Marie-Fanny; Rost, Björn; et al. (Climate Change 2022: Impacts, Adaptation and Vulnerability. Working Group II Contribution to the IPCC Sixth Assessment Report, 2022)
Anthropogenic climate change has exposed ocean and coastal ecosystems to conditions that are unprecedented over millennia (high confidence2), and this has greatly impacted life in the ocean and along its coasts (very high confidence). Fundamental changes in the physical and chemical characteristics of the ocean acting individually and together are changing the timing of seasonal activities (very high confidence), distribution (very high confidence), and abundance (very high confidence) of oceanic and coastal organisms, from microbes to mammals and from individuals to ecosystems, in every region. Evidence of these changes is apparent from multi-decadal observations, laboratory studies and mesocosms, as well as meta-analyses of published data. Geographic range shifts of marine species generally follow the pace and direction of climate warming (high confidence): surface warming since the 1950s has shifted marine taxa and communities poleward at an average (mean ± very likely range) of 59.2 ± 15.5 km per decade (high confidence), with substantial variation in responses among taxa and regions. Seasonal events occur 4.3 ± 1.8 to 7.5 ± 1.5 days earlier per decade among planktonic organisms (very high confidence) and on average 3 ± 2.1 days earlier per decade for fish (very high confidence). Warming, acidification and deoxygenation are altering ecological communities by increasing the spread of physiologically sub-optimal conditions for many marine fish and invertebrates (medium confidence). These and other responses have subsequently driven habitat loss (very high confidence), population declines (high confidence), increased risks of species extirpations and extinctions (medium confidence) and rearrangement of marine food web
Keywords: anthropogenic; climate; change; geographic range shifts; range; shifts; marine; species; warming; acidification; deoxygenation; invertebrates; fish; extinctions; rearrangement

Oceanic island biogeography through the lens of the general dynamic model: Assessment and prospect - Borregaard, Michael K.; Amorim, Isabel R.; Borges, Paulo A. V.; Cabral, Juliano S.; Fernandez-Palacios, Jose M.; Field, Richard; Heaney, Lawrence R.; Kreft, Holger; Matthews, Thomas J.; Olesen, Jens M.; Price, Jonathan; Rigal, Francois; et al. (Biological Reviews, 2017)
The general dynamic model of oceanic island biogeography (GDM) has added a new dimension to theoretical island biogeography in recognizing that geological processes are key drivers of the evolutionary processes of diversification and extinction within remote islands. It provides a dynamic and essentially non-equilibrium framework generating novel predictions for emergent diversity properties of oceanic islands and archipelagos. Its publication in 2008 coincided with, and spurred on, renewed attention to the dynamics of remote islands. We review progress, both in testing the GDM's predictions and in developing and enhancing ecological–evolutionary understanding of oceanic island systems through the lens of the GDM. In particular, we focus on four main themes: (i) macroecological tests using a space-for-time rationale; (ii) extensions of theory to islands following different patterns of ontogeny; (iii) the implications of GDM dynamics for lineage diversification and trait evolution; and (iv) the potential for downscaling GDM dynamics to local-scale ecological patterns and processes within islands. We also consider the implications of the GDM for understanding patterns of non-native species diversity. We demonstrate the vitality of the field of island biogeography by identifying a range of potentially productive lines for future research.
Keywords: Archipelago; Diversity theory; General dynamic model; Island biogeography; Island evolution; Trait evolution; Volcanic islands

On Paleozoic platycerate gastropods - Nützel, Alexander; Ebbestad, Jan Ove; Seuß, Barbara; Munnecke, Axel; Mapes, Royal H.; Cook, Alex G. (Zitteliana, 2023)

On the potential for ocean acidification to be a general cause of ancient reef crises - Kießling, Wolfgang; Simpson, Carl (Global Change Biology, 2011)
Anthropogenic rise in the carbon dioxide concentration in the atmosphere leads to global warming and acidification of the oceans. Ocean acidification (OA) is harmful to many organisms but especially to those that build massive skeletons of calcium carbonate, such as reef corals. Here, we test the recent suggestion that OA leads not only to declining calcification of reef corals and reduced growth rates of reefs but may also have been a trigger of ancient reef crises and mass extinctions in the sea. We analyse the fossil record of biogenic reefs and marine organisms to (1) assess the timing and intensity of ancient reef crises, (2) check which reef crises were concurrent with inferred pulses of carbon dioxide concentrations and (3) evaluate the correlation between reef crises and mass extinctions and their selectivity in terms of inferred physiological buffering. We conclude that four of five global metazoan reef crises in the last 500 Myr were probably at least partially governed by OA and rapid global warming. However, only two of the big five mass extinctions show geological evidence of OA. © 2010 Blackwell Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.onthep
Keywords: Climate change; Mass extinctions; Ocean acidification; Phanerozoic; Reefs

Optimizing sampling approaches along ecological gradients - Schweiger, Andreas H.; Irl, Severin D. H.; Steinbauer, Manuel; Dengler, Juergen; Beierkuhnlein, Carl (Methods in Ecology and Evolution, 2016)
Natural scientists and especially ecologists use manipulative experiments or field observations along gradients to differentiate patterns driven by processes from those caused by random noise. A well-conceived sampling design is essential for identifying, analysing and reporting underlying patterns in a statistically solid and reproducible manner, given the normal restrictions in labour, time and money. However, a technical guideline about an adequate sampling design to maximize prediction success under restricted resources is lacking. This study aims at developing such a solid and reproducible guideline for sampling along gradients in all fields of ecology and science in general. We conducted simulations with artificial data for five common response types known in ecology, each represented by a simple function (no response, linear, exponential, symmetric unimodal and asymmetric unimodal). In the simulations, we accounted for different levels of random and systematic error, the two sources of noise in ecological data. We quantified prediction success for varying total sample size, number of locations sampled along a spatial/temporal gradient and number of replicates per sampled location. The number of replicates becomes more important with increasing random error, whereas replicates become less relevant for a systematic error bigger than 20% of total variation. Thus, if high levels of systematic error are indicated or expected (e.g. in field studies with spatial autocorrelation, unaccountable additional environmental drivers or population clustering), continuous sampling with little to no replication is recommended. In contrast, sampling designs with replications are recommended in studies that can control for systematic errors. In a setting that is characteristic for ecological experiments and field studies strictly controlling for undeterminable systematic error (random error ≥10% and systematic error ≤10% of total variation), prediction success was best for an intermediate number of sampled locations along the gradient (10–15) and a low number of replicates per location (3). Our findings from reproducible, statistical simulations will help design appropriate and efficient sampling approaches and avoid erroneous conclusions based on studies with flawed sampling design, which is currently one of the main targets of public criticism against science.
Keywords: ANOVA; Curve fitting; Ecological experiment; Experimental design; Model selection; Regression analysis; Replication; Sampling design; Simulation

Ordination analysis in sedimentology, geochemistry and palaeoenvironment-Background, current trends and recommendations - Bialik, Or M.; Jarochowska, Emilia; Grossowicz, Michal (Depositional Record, 2021)
Ordination is the name given to a group of methods used to analyse multiple variables without preceding hypotheses. Over the last few decades, the use of these methods in Earth science in general, and notably in analyses of sedimentary sources, has dramatically increased. However, with limited resources oriented towards Earth scientists on the topic, the application of ordination analysis is at times suboptimal and misuse by authors can occur. This text was written for researchers with little to no experience with ordination with the aim of exposing them to the utility and the pitfalls of this branch of exploratory statistics. To do so, a detailed review of three ordination methods is offered: principal component analysis, non-metric multidimensional scaling and detrended correspondence analysis. A survey of 163 publications in Earth science is presented, in which these ordination methods were used together with a summary of how, why and on what type of data ordination was used. With common mistakes outlined and misuses in those publications identified. Notably, issues were found with reproducibility, documentation, data set dimensions and transformations. Based on this survey, a recommended workflow is offered for Earth scientists who wish to apply ordination. Additionally, this article is accompanied by highly annotated R scripts for novice users to use these methods.
CRIS-Team WoS Importer:2021-09-24

Ordovician and Silurian sea-water chemistry, sea level, and climate: A synopsis - Munnecke, Axel; Calner, Michael; Harper, David A.T.; Servais, Thomas (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
Following the Cambrian Explosion and the appearance in the fossil record of most animal phyla associated with a range of new body plans, the Ordovician and Silurian periods witnessed three subsequent major biotic events: the Great Ordovician Biodiversification Event, the end-Ordovician extinction (the first animal extinction and second largest of the five mass extinctions of the Phanerozoic), and the Early Silurian post-extinction recovery. There are currently no simple explanations for these three major events. Combined extrinsic (geological) and intrinsic (biological) factors probably drove the biodiversifications and radiations, and the appearance and disappearance of marine habitats have to be analysed in the frame of changing palaeogeography, palaeoclimate and sea-water chemistry. The present paper reviews the relationships of the three biotic events to chemical and physical processes occurring in the ocean and atmosphere during the Ordovician and Silurian, including sea-level changes, geochemical proxies (δC, δO, Sr/Sr) of the ocean waters, and the evolution of the atmosphere (oxygen and carbon dioxide content). © 2010 Elsevier B.
Keywords: Climate; Ordovician; Sea level; Silurian; Stable isotopes

Ordovician paleokarst, quartz sand and climate - Keller, Martin; Lehnert, Oliver (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LG.ordovi

Ordovician stable carbon isotope stratigraphy in the Tarim Basin, NW China - Zhang, Yuandong; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
The Tarim Basin, located in NW-China, represents one of China's major palaeoplates. Its palaeogeographic position in the Ordovician, however, is debated. In this study we present biostratigraphically controlled stable carbon isotope data from some 600 samples spanning almost the entire Ordovician in order to provide a tool that can be used for future chemostratigraphic correlations. The data correlate well with results from South China, and several major global δC excursions such as the MDICE (Dw2/3), SAICE (Sa2), GICE (Ka1), and Whitewater excursion (Ka4) are documented for the first time from the Tarim Basin. Major sedimentary gaps are detected in the lower Floian between the Penglaiba and Yinshan formations, in the upper Darriwilian to lower Sandbian between the Dawangou and Saergan (or Kanling) formations, and in the latest Sandbian between the Kanling and Qilang formations as well as between the Tumuxiuke and Lianglitag formations. Three scenarios for the depositional history of the late Darriwilian to early Sandbian Saergan Formation, which represents an important hydrocarbon source rock in the Tarim Basin, are discussed with respect to their bio- and chemostratigraphic implications. The mid-upper Ordovician rocks recording high δC values have been deposited during transgressive or highstand intervals, whereas the regressive intervals are mostly missing. This results in a stacking of several positive excursions, and thus chemostratigraphic correlation without biostratigraphic control might produce misleading results, especially for shallow-water carbonates.
Keywords: Chemostratigraphy; Ordovician; Source rocks; Stable carbon isotope; Tarim

Ordovician stratigraphy and sedimentary facies of the Stumsnäs 1 core from the southern Siljan Ring, central Sweden. - Lehnert, Oliver; Meinhold, Guido; Arslan, Arzu; Ebbestad, Jan Ove; Calner, Mikael (Gff, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LG.ordovi

Organic-walled microfossils incertae sedis from the Ordovician of the Argentine Precordillera and Bohemia - Heuse, Thomas; Lehnert, Oliver; Kraft, Petr (Acta Universitatis Carolinae - Geologica, 1997)

Origination and dispersal dynamics of Cenozoic marine plankton - Raja, Nussaïbah Begum; Kießling, Wolfgang (Annual Meeting of the Paleontological Society (Paläontologische Gesellschaft) 2019, 2019)

Origin of planktotrophy - evidence from early molluscs: a response to Freeman and Lundelius. - Nützel, Alexander; Lehnert, Oliver; Fryda, Jiri (Evolution & Development, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LG.origin

Origin of planktotrophy - evidence from early molluscs - Nützel, Alexander; Lehnert, Oliver; Fryda, Jiri (Evolution & Development, 2006)
The size of early ontogenetic shells (protoconchs) of ancient benthic molluscs suggests that feeding larvae occurred at about 490 myr (approximately, transition from Cambrian to Ordovician). Most studied Ordovician protoconchs were smaller than Cambrian ones, indicating smaller Ordovician eggs and hatchlings. This suggests substitution of nutritious reserve matter such as yolk by plankton as an energy source for larvae. The observed size change represents the first direct empiric evidence for a late Cambrian to Ordovician switch to planktotrophy in invertebrate larvae. It corroborates previous hypotheses about a possible polyphyly of planktotrophy. These hypotheses were primarily based on molecular clock data of extant clades with different types of larva, change in the overall body size, as well as increasing predation pressure on Early Paleozoic sea floors. The Early Ordovician is characterized by an explosive radiation of benthic suspension feeders and it was suggested that planktotrophy would prolongate escape from benthic predation on hatchlings. This biological escalation hypothesis does not fully explain why planktotrophy and suspension feeding became important at the same time, during a major biodiversification. An additional factor that probably included availability of nutrients must have played a role. We speculate that an increasing nutrient supply and availability of photoautotrophic plankton in world oceans have facilitated both planktotrophy and suspension feeding, which does not exclude a contemporaneous predation-driven escalation. It is very likely that the evolution of planktotrophy as well as increasing predation contributed to the Ordovician radiation. © 2006 The Author(s).
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IGM.LP.assess_9

Origin of the Cretaceous olistostromes in the Oman mountains (Sultanate of Oman): Evidence from clay minerals - Mattern, Frank; Scharf, Andreas; Pracejus, Bernhard; Al Shibli, Issa S. A.; Al Kabani, Bader M. S.; Al Qasmi, Waleed Y. A.; Kießling, Wolfgang; Callegari, Ivan (Journal of African Earth Sciences, 2022)
Mid- to Late Cretaceous olistostrome generation ensued sequentially, linked to progressive southwest-directed thrusting of the Semail Ophiolite towards and over Arabia - at first in the northeastern part of the oceanic Hawasina Basin (Umar Sub-Basin) and then in its southwestern part (Hamrat Duru-Sub-Basin). Thrusting steepened slopes, causing seismic tremors, which destabilized slope sediments and triggering olistostrome formation. Ophiolite thrusting over Arabia created the Aruma Foreland Basin. Olistostrome formation in the foredeep ensued last and on the flank of the uplifting forebulge. As olistoliths, Olistostrome 1 contains radiolarian limestone, plain micrite, allodapic limestone, basalt, amygdaloidal basalt, radiolarian chert and coarse, massive limestone with crystalline texture (Oman Exotics). These olistoliths "float" in shale, containing illite/muscovite, vermiculite and kaolinite. Olistostrome 1 formed in the Umar Sub-Basin. Olistostrome 2 is associated with the Late Albian to Coniacian Nayid Formation of the Hamrat Duru Sub-Basin. It is characterized by olistoliths of graded limestones (calc-turbidites) with angular shelfal limestone lithoclasts. The olistoliths are embedded in shale with unidentifiable clay minerals. Olistostrome 2 formed in the Hamrat Duru Sub-Basin, postdating Olistostrome 1. Olistostrome 3 is associated with the Upper Cretaceous Aruma Foreland Basin and characterized by olistoliths, like lithoclastic packstone (calcarenite), dolomitic limestone, and sandstone with carbonate lithoclasts. The matrix of the olistoliths is a pyrophyllite- and kaolinite-bearing shale. Olistostrome 3 formed in the foredeep as the youngest olistostrome. The different clay mineralogy of Olistostrome 1 and Olistostrome 3, reflects their different basinal origin. Shale samples taken from conventional sediments (no olistostromes) of the syn-tectonic and post-tectonic Aruma units show some resemblance in their clay mineralogy as they contain detritus from the Oman Mountains. Olistolith types of both Hawasina olistostromes differ significantly. The reviewed and novel data may serve as a guideline for future olistostrome studies in the Oman Mountains and may be particularly helpful in identifying the basinal origin of olistostromes in case of fault-bounded olistostromes, unexposed olistostrome contacts and inconclusive olistoliths. Evaluating matrix shales of olistostromes leads to important decision criteria, such as color, oxygenation state and clay mineralogy, to determine the paleogeographic basin position.
CRIS-Team WoS Importer:2022-06-24

Osmium and lithium isotope evidence for weathering feedbacks linked to orbitally paced organic carbon burial and Silurian glaciations - Sproson, Adam D.; Pogge von Strandmann, Philip A.E.; Selby, David; Jarochowska, Emilia; Frýda, Jiří; Hladil, Jindřich; Loydell, David K.; Slavík, Ladislav; Calner, Mikael; Maier, Georg; Munnecke, Axel; Lenton, Timothy M. (Earth and Planetary Science Letters, 2022)
The Ordovician (∼487 to 443 Ma) ended with the formation of extensive Southern Hemisphere ice sheets, known as the Hirnantian glaciation, and the second largest mass extinction in Earth History. It was followed by the Silurian (∼443 to 419 Ma), one of the most climatically unstable periods of the Phanerozoic as evidenced by several large scale (>5‰) carbon isotope (δ13C) perturbations associated with further extinction events. Despite several decades of research, the cause of these environmental instabilities remains enigmatic. Here, we provide osmium (187Os/188Os) and lithium (δ7Li) isotope measurements of marine sedimentary rocks that cover four Silurian δ13C excursions. Osmium and Li isotope records resemble those previously recorded for the Hirnantian glaciation suggesting a similar causal mechanism. When combined with a new dynamic carbon-osmium-lithium biogeochemical model we suggest that astronomical forcing of the marine organic carbon cycle, as opposed to a decline in volcanic arc degassing or the rise of early land plants, resulted in drawdown of atmospheric CO2, triggering continental scale glaciation, intense global cooling and eustatic sea-level lows recognised in the geological record. Lower atmospheric pCO2 and temperatures during the Hirnantian and Silurian glaciations suppressed CO2 removal by silicate weathering, driving 187Os/188Os and δ7Li variability, supporting the existence of climate-regulating feedbacks.
CRIS-Team Scopus Importer:2021-11-12
Keywords: eccentricity and precession; Hirnantian glaciation; orbital obliquity; osmium (; silicate weathering; Silurian palaeoclimate

Osteological revision of the holotype of the Middle Jurassic sauropod dinosaur Patagosaurus fariasi Bonaparte, 1979 (Sauropoda: Cetiosauridae) - Holwerda, Femke Marleen; Rauhut, Oliver W. M.; Pol, Diego (Geodiversitas, 2021)
Middle Jurassic sauropod taxa are poorly known, due to a stratigraphic bias of localities yielding body fossils. One such locality is Cerro Condor North, Canadon Asfalto Formation, Patagonia, Argentina, dated to latest Early-Middle Jurassic. From this locality, the holotype of Patagosaurus fariasi Bonaparte 1986 is revised. The material consists of the axial skeleton, the pelvic girdle, and the right femur. Patagosaurus is mainly characterised by a combination of features mainly identified on the axial skeleton, including the following: 1) cervical centra with low Elongation Index; 2) high projection of the postzygodiapophyseal lamina; 3) deep anterior pleurocoels that are sometimes compartmentalized in cervicals; 4) high projection of the neural arch and spine in dorsal vertebrae and anterior(most) caudal vertebrae; 5) deep pneumatic foramina in posterior dorsals which connect into an internal pneumatic chamber, and 6) anterior caudal vertebrae with 'saddle' shaped neural spines. Diagnostic features on the appendicular skeleton include: 1) a transversely wide and anteroposteriorly short femur; 2) a medial placement of the fourth trochanter on the femur; and 3) an anteroposteriorly elongated ilium with a rounded dorsal rim, with hook-shaped anterior lobe. The characters that are diagnostic for Patagosaurus are discussed, and the osteology of Patagosaurus is compared to that of Early and Middle Jurassic (eu)sauropods from both Laurasia and Gondwana.
CRIS-Team WoS Importer:2021-10-01

Ostracod eye size: A taxonomy-free indicator of the Paleocene-Eocene Thermal Maximum sea level - Tian, Skye Yunshu; Yasuhara, Moriaki; Robinson, Marci M.; Huang, Huai-Hsuan (Marine Micropaleontology, 2021)
Deep-time sea-level changes associated with the Paleocene-Eocene Thermal Maximum (PETM) are of great interest to paleoceanographers and paleontologists, especially in shallow marine settings, like the Atlantic Coastal Plain PETM sections of the Eastern North American Continental Shelf. Accurate paleo-water depth reconstruction is essential to properly interpret and contextualize any PETM-associated paleoceanographic and paleoecological changes that are depth-dependent. In addition, our understanding on eustatic sea-level changes in the greenhouse world without polar ice sheets remains limited. Despite this importance of an accurate and robust paleodepth reconstruction, all water depth estimation methods applied for the shallow marine PETM sections suffer from uncertainties and intrinsic/logical flaws. It is therefore important to develop and apply an independent water depth proxy to complement and validate paleodepth estimates derived from the traditional estimation methods based on sedimentary fossil components and lithological features. Here we present the relative eye size of sighted ostracods as a taxonomy-free water depth proxy and apply it to shallow-marine PETM paleodepth reconstruction of the Mattawoman Creek-Billingsley Road (MCBR) core in Maryland, eastern USA. We identified a significant and rapid reduction in water depth of 40 m within the carbon isotope excursion (CIE) onset consistent with the previous estimation based on benthic foraminifer species associations. This ostracod-eye-based paleodepth reconstruction improves current understanding on the regional paleobathymetry of the Salisbury Embayment and facilitates future studies on continental shelf paleoceanography and paleoecology during the PETM, a rapid, extreme global warming event under long-term greenhouse conditions, which possibly parallels the ongoing anthropogenic warming.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Ostracod relative eye size; Paleocene-Eocene Thermal Maximum; Paleodepth reconstruction; Salisbury Embayment

Out of the extratropics: the evolution of the latitudinal diversity gradient of Cenozoic marine plankton - Raja, Nussaïbah Begum; Kießling, Wolfgang (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2021)
Many ecological and evolutionary hypotheses have been proposed to explain the latitudinal diversity gradient, i.e. the increase in species richness from the poles to the tropics. Among the evolutionary hypotheses, the ‘out of the tropics’ (OTT) hypothesis has received considerable attention. The OTT posits that the tropics are both a cradle and source of biodiversity for extratropical regions. To test the generality of the OTT hypothesis, we explored the spatial biodiversity dynamics of unicellular marine plankton over the Cenozoic era (the last 66 Myr). We find large-scale climatic changes during the Cenozoic shaped the diversification and dispersal of marine plankton. Origination was generally more likely in the extratropics and net dispersal was towards the tropics rather than in the opposite direction, especially during the warmer climates of the early Cenozoic. Although migration proportions varied among major plankton groups and climate phases, we provide evidence that the extratropics were a source of tropical microplankton biodiversity over the last 66 Myr.<br
Keywords: macroevolution; biodiversity; marine plankton; climate change; biogeography

Overcoming the coupled climate and biodiversity crises and their societal impacts - Pörtner, H. O.; Scholes, R. J.; Arneth, A.; Barnes, D. K.A.; Burrows, M. T.; Diamond, S. E.; Duarte, C. M.; Kießling, Wolfgang; Leadley, P.; Managi, S.; McElwee, P.; Midgley, G.; et al. (Science, 2023)
Earth's biodiversity and human societies face pollution, overconsumption of natural resources, urbanization, demographic shifts, social and economic inequalities, and habitat loss, many of which are exacerbated by climate change. Here, we review links among climate, biodiversity, and society and develop a roadmap toward sustainability. These include limiting warming to 1.5°C and effectively conserving and restoring functional ecosystems on 30 to 50% of land, freshwater, and ocean "scapes." We envision a mosaic of interconnected protected and shared spaces, including intensively used spaces, to strengthen self-sustaining biodiversity, the capacity of people and nature to adapt to and mitigate climate change, and nature's contributions to people. Fostering interlinked human, ecosystem, and planetary health for a livable future urgently requires bold implementation of transformative policy interventions through interconnected institutions, governance, and social systems from local to global levels.
CRIS-Team Scopus Importer:2023-04-28

Oversimplification risks too much: A response to 'How predictable are mass extinction events?' - Reddin, Carl J.; Aberhan, Martin; Dimitrijević, Danijela; Dowding, Elizabeth; Kocsis, Ádám; Mathes, Gregor; Nätscher, Paulina; Patzkowsky, Mark E.; Kießling, Wolfgang (Royal Society Open Science, 2023)
CRIS-Team Scopus Importer:2023-09-15

Oxygen and stable carbon isotopes from a nautiloid from the middle Pennsylvanian (Late Carboniferous) impregnation Lagerstätte "Buckhorn Asphalt Quarry" - Primary paleo-environmental signals versus diagenesis - Seuß, Barbara; Titschack, Jürgen; Seifert, Severin; Neubauer, Jürgen; Nützel, Alexander (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)

Oyster-dominated macrobenthic associations in the Cenomanian of Djebel Bouarif (Aures Mountains, Northeastern Algeria) - Aouissi, Riadh; Abdelhady, Ahmed Awad; Martinez, Sergio; Ahmed, Mohamed S.; Hannaa, Wagih; Jain, Sreepat; Salmi-Laouar, Sihem (Cretaceous Research, 2023)
In the Batna area of Algeria, the Cenomanian is represented by the Smail Marls Formation, a highly fossiliferous unit with a diverse benthic macrofauna (mainly of ostreid bivalves). A total of 1090 specimens belonging to 65 macrobenthic species were identified from 19 stratigraphic samples. The macrofaunal communities were quantitively analyzed using the hierarchical clustering (HC), nonmetric multidimensional scaling (NMDS), and permutational analysis of variance (PERMANOVA). Five distinct associations are recognized: 1) Costagyra olisiponensis, 2) Rhynchostreon suborbiculatum, 3) Aspidiscus cristatus, 4) Rhynchostreon suborbiculatum-Mecaster ameliae, and 5) Pycnodonte vesicularis. Data suggests that during the Cenomanian, the dominance of high-energy opportunistic oyster species within the soft marly sediments are related to their adaptive strategies. The changes noted in the community structure are attributed to sea-level fluctuations, rate of sedimentation and the prevailing hydrodynamics. Towards the uppermost Cenomanian and the Cenomanian–Turonian boundary, the oysters become rare due to eustatic sea-level rise and this decline coincides with increasing predation intensity on oysters and the destruction of their shallower habitats.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Benthic associations; Bivalves; North Africa; Paleoenvironmental reconstruction; Upper Cretaceous

Palaeobotryllus and friends: Cambro-Ordovician record of probable ascidian tunicates - Lehnert, Oliver; Miller, James F.; Cochrane, Karen (Acta Universitatis Carolinae - Geologica, 1999)

Palaeoecology of tropical marine invertebrate assemblages from the Late Triassic of Misurina, Dolomites, Italy - Hausmann, Imelda M.; Nuetzel, Alexander; Roden, Vanessa; Reich, Mike (Acta Palaeontologica Polonica, 2021)
Two marine invertebrate fossil assemblages from the Late Triassic Cassian Formation (Dolomites, northern Italy) were examined to assess their diversity and palaeoecology. Surface and bulk samples from the localities Misurina Landslide and Lago Antorno were taken and analysed separately. Both benthic assemblages are relatively similar in taxonomic composition. Gastropods form the most abundant and diverse group, followed by bivalves. Disarticulated echinoderm ossicles are also common in the bulk sample from Misurina Landslide, but they are rare at Lago Antorno. The Misurina Landslide outcrop has yielded two echinoderm Palaeozoic holdovers, the ophiocistioid Linguaserra triassica and plates of putative proterocidarids, supporting the earlier hypothesis that such basins acted as refugia. The gastropod species Coelostylina conica, Prostylifer paludinaris, and Ampezzopleura hybridopsis are characteristic elements of both assemblages. The gastropod Jurilda elongata, however, is the most abundant species at Misurina Landslide, whereas juveniles of the gastropod species Dentineritaria neritina dominate the assemblage from Lago Antorno. Newly described gastropod taxa are Angulatella bizzarinii Nützel and Hausmann gen. et sp. nov., Bandellina compacta Nützel and Hausmann sp. nov., and Ampezzogyra angulata Nützel and Hausmann sp. nov. Fifty-seven invertebrate species were found in the bulk sample from Misurina Landslide and 26 species were recovered from the bulk sample from Lago Antorno. However, sample size from Lago Antorno was much smaller than that from Misurina. Diversity indices (Shannon, Simpson, Berger-Parker) show similar moderate diversities in both assemblages. Rarefaction curves and rank-abundance distributions also point to very similar diversities and ecological structures of the fossil assemblages. Both assemblages are autochthonous or parautochthonous, stemming from basinal, soft-bottom habitats. Their taxonomic composition differs significantly from that of other faunas known from the Cassian Formation. The tropical marine Cassian palaeoecosystem was highly complex and its diversity is still far from being fully explored.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Alps; Carnian; Cassian Formation; Diversity; Echinodermata; Ladinian; Mollusca; Small body size

Palaeokarst evidence for widespread regression and subaerial exposure in the middle Katian (Upper Ordovician) of Baltoscandia: significance for global climate. - Calner, Mikael; Lehnert, Oliver; Nolvak, Jaak (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
We report on widespread and contemporary palaeokarst in the middle Katian (Upper Ordovician) of Sweden, Estonia and Latvia, the first major palaeokarst horizon to be reported from the Ordovician of Baltoscandia. The solution features occur within a few metres of thick zone of limestone immediately below the widespread Fjäcka Shale and are related to an unconformity with preserved palaeorelief in the Slandrom Limestone in Sweden and the time-equivalent Saunja Formation in Estonia and Latvia. Facies evidence for a karst origin comes from several outcrops and core sections and includes 1) frequent karren-like morphologies interpreted as 'Swiss-cheese' karst [. sensu Baceta et al., 2001], 2) local occurrences of solution/collapse breccia, 3) presence of bladed pseudospar crystals in solution cavities, and 4) carbon isotope values indicating meteoric influence to the succession. These findings are herein put in context with previously reported, large-scale erosional channels that may cut down several tens of metres below the Fjäcka Shale in the subsurface Baltic Sea area, and with regional, anomalous thickness variations in the Slandrom Limestone and Saunja Formation, all together forming strong support for regional exposure of the Baltoscandian continent in the middle Katian. High-resolution stable isotopic data show that the regression and lowstand of sea-level overlap with the Waynesville carbon isotope excursion. It resulted in basin-wide cessation of carbonate production near the Amorphognathus superbus and A. ordovicicus conodont zonal boundary. The contemporary development of palaeokarst in different confacies belts of the basin suggests that this was an extraordinary sea-level lowstand, herein interpreted as reflecting a middle Katian glaciation. © 2009 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LG.palaeo
Keywords: Baltoscandia; Fjäcka Shale; Katian; Ordovician; Palaeokarst; Saunja Formation; Slandrom Limestone

Palaeontological and facial features of the Upper Jurassic Hochstegen Marble (Tauern Window, Eastern Alps) - Kießling, Wolfgang (Terra Nova, 1992)

Palaeozoic calcareous plankton: Evidence from the Silurian of Gotland - Munnecke, Axel; Servais, Thomas (Lethaia, 2008)
In order to investigate whether or not equivalents to modern calcareous plankton existed in Palaeozoic times, extremely well-preserved successions have to be investigated. The Silurian strata on Gotland (Sweden) are exceptionally well preserved because they have not experienced deep burial conditions and tectonic stress, due to their position on the stable Baltic Shield. Scanning electron microscope investigations of polished, slightly etched rock surfaces revealed the presence of a variety of calcareous micro- and nannofossils. Among these organisms, many can be termed 'calcispheres' (60-100 μm in diameter), whereas others due to their size range (nannofossils) are informally termed herein as 'nannospheres' (10-25 μm in diameter). The systematic attribution of these fossils is unknown (incertae sedis). Mesozoic calcispheres are usually attributed to calcareous cysts of dinoflagellates following comparisons of ultrastructure with modern species. The abundance of different calcispheres in the Silurian sediments of Gotland and the observation that many of the calcareous microfossils occur in distinctly different facies as well as their spherical shape indicate that they probably belong to calcareous micro- and nannoplankton. We therefore conclude that calcareous plankton most probably existed already during the Palaeozoic, but can only be observed under conditions of exceptional preservation. © 2008 The Authors, Journal compilation © 2008 The Lethaia Foundation.
Keywords: Calcareous plankton; Palaeozoic; Silurian; Gotland; Nannofossils; Baltic Shield

Palaeozoic evolution of animal mouthparts - Klug, Christian; Frey, Linda; Pohle, Alexander; de Baets, Kenneth; Korn, Dieter (Bulletin of Geosciences, 2017)
During the Palaeozoic, a diversification in modes of life occurred that included a wide range of predators. Major macroecological events include the Cambrian Explosion (including the Agronomic Substrate Revolution and the here introduced ’Ediacaran-Cambrian Mouthpart Armament’), the Great Ordovician Biodiversification Event, the Palaeozoic Plankton Revolution, the Siluro-Devonian Jaw Armament (newly introduced herein) and the Devonian Nekton Revolution. Here, we discuss the evolutionary advancement in oral equipment, i.e. the Palaeozoic evolution of mouthparts and jaws in a macroecological context. It appears that particularly the latest Neoproterozoic to Cambrian and the Silurian to Devonian were phases when important innovations in the evolution of oral structures occurred.
Keywords: Gnathostomata; Cephalopoda; evolution; convergence; diversity; nekton; jaws

Palaeozoic Reefs and Bioaccumulations: Climatic and Evolutionary Controls - Álvaro, José-Javier; Aretz, Markus; Boulvain, Frédéric; Munnecke, Axel; Vachard, Daniel; Vennin, Emmanuelle (2007)
The difficulty of studying reefs and shell accumulations rests primarily on its multidisciplinary position crossing numerous disciplines, such as biostratigraphy, geochemistry, palaeobiology, palaeoecology, petrology, sedimentology and taphonomy. The facies characterization of these bioclastic-bearing strata is, like many other biosedimentary structures, a process that requires the acquisition and integration of a wide and multiscale diversity of observations, which include field (global geometries), sample (fabrics) and thin-section (textures) scales. When we organized an international meeting focused on 'Climatic and Evolutionary Controls on Palaeozoic Reefs and Bioaccumulations' (7-9 September 2005, Paris, France), it was our intention to provide a forum for discussing the evolution of reefs, shell accumulations and their transitional deposits. We invited specialists on a wide range of taxonomic groups, siliciclasticmixed carbonate platforms and Palaeozoic ages to introduce a number of topics that are the focus of current research in the world of Palaeozoic benthic communities. The result of their contributions is presented in this Special Publication, which shows the complexity of intrareef synecological relationships and the diversity of concepts used to characterize both reefs and bioaccumulations. The editors offer, in the introductory paper (, lvaro et al.), a discussion about concepts and definitions related to reefs and bioaccumulations. The transition between the concepts of reef and shell accumulation is gradual, as illustrated by some Palaeozoic examples, where reworked coquinas were episodically stabilized by encrusting communities and/or early diagenetic cements, in some cases forming the sole for future frame-building fabrics. Three Cambrian works are focused on shell-rich phosphorites from the Montagne Noire, France (Clausen & ,iAvaro), and microbial and archaeocyathanmicrobial reef complexes from Sardinia, Italy (Gandin et al.) and the High Atlas, Morocco (Alvaro & Clausen), the latter directly controlled by volcanogenic turbidity. The increase in biodiversity recorded in Ordovician bioaccumulations is illustrated by the characterization of a distinct echinoderm assemblage rich in ophiuroids and stylophorans (Hunter et al.). Kershaw et al. show that some Silurian reefs from Gotland and the UK have sharp boundaries, with the surrounding sediments terminating abruptly against the reef edge, and the sharp margins made up of automicrites; the sharp reef edges indicate coherence of the micritic fabric, interpreted as a lithified wall against which bedded limestones were deposited. Hubmann & Suttner provide a review of Alpine Late Silurian-Late Devonian reefs and pavements, spanning a wide range of different autochthonous carbonates (e.g. brachiopod pavements, algal reefs, stromatoporoidcoral patch reefs) as well as allochthonous accumulations (e.g. serpulid accumulations). Two related papers offer an updated synthesis of the establishment of a carbonate platform (Mabille & Boulvain) and the sea-level-controlled evolution of Devonian mounds and atolls in the Dinant Synclinorium from Belgium (Boulvain). Examples for the youngest reefs of the Middle Palaeozoic reef community of stromatoporoids and corals are described from the latest Frasnian of Belgium (Poty & Chevalier). The struggle to establish a successful reef assemblage in the aftermath of the Kellwasser events and the importance of microbial communities in Famennian and Carboniferous reefs is described from Belgium (Aretz & Chevalier). The influence of palaeobathymetry and local synsedimentary tectonics in the establishment of carbonate factories is discussed in two papers focused on the development of Carboniferous chaetetid 'reefs' (Almaz n-Vazquez et al.) and neighbouring crinoidal thickets (Buitr6n-S nchez et aL) in Sonora, Mexico, whereas the documentation of sea-floor instability related to the evolution of the Permian foreland basin recorded in the southern Urals is characterized by Vennin. The input of cool waters within tropical PermoCarboniferous seas is analysed in Oman by Weidlich, and opens a large field of future discussions. Th6ry et al. provide new insights into the latest Permian reefs and bioaccumulations from eastern Europe and the Caucasus. And, finally, Zapalski et al. offer an estimation of palaeoenvironmental changes based on the distribution of late Middle Devonian tabulae in tabulate corals from northern France. One of the messages of this collection of papers is the wide diversity of sedimentary geometries and facies displayed by reefs, shell accumulations and transitional composite deposits. Readers will find that the papers in this Special Publication cover specific nomenclatural problems, evidenced by the widespread terminology used to describe skeletal assemblages. Rather than attempt a complete revision of terms, we have touched on some of the major issues at this stage of development in the field: the major climatic, environmental and evolutionary factors that controlled the Palaeozoic development of shell accumulations and reefs. We hope that this volume attracts the attention of everyone interested in the fascinating diversity of Palaeozoic reefs and shell accumulation. It will be useful to senior undergraduate and postgraduate students of Earth Sciences and engineering. We also hope that it may prove useful to professionals who explore and economically exploit Palaeozoic skeletal-rich strata. The editors would like to thank all contributors and referees for their rapid and stimulating collaboration. Thanks also for their suggestions, discussions, editorial work and constructive review
Keywords: Palaeozoic; Reefs; Bioaccumulations; Climate; Evolutionary Controls

Palaeozoic stromatoporoid diagenesis: a synthesis - Kershaw, Stephen; Munnecke, Axel; Jarochowska, Emilia; Young, Graham (Facies, 2021)
Palaeozoic stromatoporoids, throughout their 100-million + year history (Middle Ordovician to Late Devonian and rare Carboniferous), are better preserved than originally aragonite molluscs, but less well-preserved than low magnesium-calcite brachiopods, bryozoans, trilobites and corals. However, the original mineralogy of stromatoporoids remains unresolved, and details of their diagenesis are patchy. This study of approximately 2000 stromatoporoids and the literature recognises three diagenetic stages, applicable throughout their geological history. Timing of processes may vary in and between stages; some components are not always present. Stage 1, on or just below sediment surface, comprises the following: micrite filling of upper gallery space after death, then filling of any remaining space by non-ferroan then ferroan calcite in decreasing oxygen of pore-waters; partial lithification of associated sediment from which stromatoporoids may be exhumed and redeposited, evidence of general early lithification of middle Palaeozoic shallow-marine carbonates; microdolomite formation, with the Mg interpreted to have been derived from original high-Mg calcite (HMC) mineralogy (likely overlaps Stage 2). Stage 2, short distance below sediment surface, comprising the following: fabric-retentive recrystallisation (FRR) of stromatoporoid skeletons forming fabric-retentive irregular calcite (FRIC), mostly orientated normal to growth layers, best seen in cross-polarised light. FRIC stops at stromatoporoid margins in contact with sediment and bioclasts. FRIC geometry varies, indicating some taxonomic control. Evidence that FRIC formed early in diagenetic history includes syntaxial continuation of FRIC into some sub-stromatoporoid cavities (Type 1 cement), although others were pre-occupied by early cement fills (Type 2 cement) formed before FRR, preventing syntaxial continuation of FRIC into cavities. Likely contemporaneous with FRIC formation, stromatoporoids in argillaceous micrites drew carbonate from adjacent sediment during reorganisation of argillaceous micrite into limestone–marl rhythms that are also early diagenetic. Stage 3, largely shallow burial, comprises the following: dissolution and silicification, but these may have occurred earlier in stromatoporoid diagenetic histories (more data required); burial pressure dissolution forming stylolites.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Hypercalcified sponges; Stromatoporoids; Tabulates; Taphonomy

Palaeozoic stromatoporoids and chaetetids analysed using Electron Backscatter Diffraction (EBSD); implications for original mineralogy and microstructure - Balthasar, Uwe; Kershaw, Stephen; Da Silva, Anne-Christine; Seuß, Barbara; Cusack, Maggie; Eichenseer, Kilian; Chung, Peter (Facies, 2021)

Palaxius salataensis Brönnimann, Cros and Zaninetti, 1972, the oldest crustacean microcoprolite from the early Carboniferous of Guangxi, South China - Senowbari-Daryan, Baba; El Rab, Amro Gad; Heindel, Katrin; Gischler, Eberhard; Peckmann, Joern (Palaeontologische Zeitschrift, 2017)
Palaxius salataensis Brönnimann, Cros and Zaninetti, 1972, is described from early Carboniferous stromatolite mounds of a fore-reef slope setting from Laibin, Guangxi, South China. This is the oldest occurrence of internally structured crustacean coprolites. The geographic distribution and stratigraphic range of the ichnospecies as well as paleoecological implications of this new record of P. salataensis are discussed.
UnivIS-Import:2017-12-18:Pub.2017.nat.dgeo.IGM.LP.palaxi
Keywords: Carboniferous; Guangxi; Microcoprolite; Palaxius; South China

Paleobiogeography, high-resolution stratigraphy, and the future of Paleozoic biostratigraphy: Fine-scale diachroneity of the Wenlock (Silurian) conodont Kockelella walliseri - Cramer, Bradley D.; Kleffner, Mark A.; Brett, Carlton E.; Mclaughlin, Patrick I.; Jeppsson, Lennart; Munnecke, Axel; Samtleben, Christian (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
The Wenlock Epoch of the Silurian Period has become one of the chronostratigraphically best-constrained intervals of the Paleozoic. The integration of multiple chronostratigraphic tools, such as conodont and graptolite biostratigraphy, sequence stratigraphy, and δC chemostratigraphy, has greatly improved global chronostratigraphic correlation and portions of the Wenlock can now be correlated with precision better than ±100kyr. Additionally, such detailed and integrated chronostratigraphy provides an opportunity to evaluate the fidelity of individual chronostratigraphic tools. Here, we use conodont biostratigraphy, sequence stratigraphy and carbon isotope (δC) chemostratigraphy to demonstrate that the conodont Kockelella walliseri, an important guide fossil for middle and upper Sheinwoodian strata (lower stage of the Wenlock Series), first appears at least one full stratigraphic sequence lower in Laurentia than in Baltica. Rather than serving as a demonstration of the unreliability of conodont biostratigraphy, this example serves to demonstrate the promise of high-resolution Paleozoic stratigraphy. The temporal difference between the two first occurrences was likely less than 1million years, and although it is conceptually understood that speciation and colonization must have been non-instantaneous events, Paleozoic paleobiogeographic variability on such short timescales (tens to hundreds of kyr) traditionally has been ignored or considered to be of little practical importance. The expansion of high-resolution Paleozoic stratigraphy in the future will require robust biostratigraphic zonations that embrace the integration of multiple chronostratigraphic tools as well as the paleobiogeographic variability in ranges that they will inevitably demonstrate. In addition, a better understanding of the paleobiogeographic migration histories of marine organisms will provide a unique tool for future Paleozoic paleoceanography and paleobiology research. © 2010 Elsevier B.
Keywords: Carbon isotope; Chronostratigraphy; Conodont zonation; Ireviken Event; Paleobiogeography; Sequence stratigraphy; Silurian; Wenlock

Paleobiogeography of Lower-Middle Devonian Conulariids from southwest Gondwana - Rodrigues Ribeiro, Victor; Dowding, Elizabeth; Nascimento Sousa, Felipe; Augusto Carbonaro, Fábio; Pirani Ghilardi, Renato (Journal of South American Earth Sciences, 2023)
The bioregionalization of the Devonian fauna in southwest Gondwana has been extensively studied, focusing on the occurrences of brachiopods and trilobites, however, little attention has been given to Conulariids. The main goal of this paper is to propose a bioregionalization for the Conulariids (Conularia albertensis, C. quichua, C. sp., Paraconularia africana, P. ulrichana, and Reticulaconularia baini) from the Lower-Middle Devonian in southwest Gondwana. After a clustering analysis and diversity tests we have identified two distinct bioregions for Conulariids: the Amazon and southwest Gondwana, in the Amazon region the diversity is low, and can be attributed to scarcity of palaeontological data on the area. On the other hand, in the southwest Gondwana bioregion, diversity ranges from moderate to relatively high, which helps define a second-order bioregion, the Andeo-South Africa and Interior Gondwana. The first includes areas where diversity has higher values bordering southwest Gondwana (Bolivian Chaco-Peru, Zorritas-NOA-South Bolivia, South Africa and Malvinas areas). Further, in the Interior Gondwana bioregion are the Parnaíba (Parnaíba Basin), Alto Garças (north and northwest of Paraná Basin), Paraná (south of Paraná Basin, Uruguay and Paraguay) areas, where the diversity is slightly lower when compared to the Andeo-South Africa bioregion.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Bioregion; Clustering; Diversity; Paleontology; South America

Paleoclimatic significance of Phanerozoic reefs - Kießling, Wolfgang (Geology, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dgeo.IGM.LP.paleoc

Paleoenvironmental significance of the monospecific biostromes in the Campanian-Maastrichtian Duwi Formation (Eastern Desert, Egypt) - Abdelhady, Ahmed Awad; Seuß, Barbara; Fürsich, Franz; Ali, Ahmed; Abdel-Racheem, Khalaf H.M.; Mohamed, Ramadan S.A. (Sedimentary Geology, 2020)

Paleoenvironment of the lower–middle cambrian evaporite series in the tarim basin and its impact on the organic matter enrichment of shallow water source rocks - Wei, Mingyang; Bao, Zhidong; Munnecke, Axel; Liu, Wei; Harrison, G. William M.; Zhang, Hua; Zhang, Demin; Li, Zongfeng; Xu, Xiting; Lu, Kai; Shen, Zheng (Minerals, 2021)
Just as in deep-water sedimentary environments, productive source rocks can be developed in an evaporitic platform, where claystones are interbedded with evaporites and carbonates. However, the impact of the paleoenvironment on the organic matter enrichment of shallow water source rocks in an evaporite series has not been well explored. In this study, two wells in the central uplift of the Tarim Basin were systematically sampled and analyzed for a basic geochemical study, including major elements, trace elements, and total organic carbon (TOC), to understand the relationship between TOC and the paleoenvironmental parameters, such as paleosalinity, redox, paleoclimate, paleo-seawater depth, and paleoproductivity. The results show that the Lower–Middle Cambrian mainly developed in a fluctuating salinity, weak anoxic to anoxic, continuous dry and hot, and proper shallow water environment. The interfingering section of evaporites, carbonates, and claystones of the Awatag Fm. have higher paleoproductivity and higher enrichment of organic matter. Paleosalinity, redox, paleoclimate, paleo-seawater depth, and paleoproductivity jointly control the organic matter enrichment of shallow water source rocks in the evaporite series. The degree of enrichment of organic matter in shallow water source rocks first increases and then decreases with the increase in paleosalinity. All the samples with high content of organic matter come from the shallower environment of the Awatag Fm.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Evaporite series; Lower–Middle Cambrian; Paleoenvironment; Shallow water source rock; Tarim Basin

Paleontological Museum of the University of Zürich: Exhibition Guide - de Baets, Kenneth; Brinkmann, Winand (Universität Zürich, 2012)

PaleoReef - a database on Phanerozoic reefs - Kießling, Wolfgang; et al. (SEPM Special Publication, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IGM.LP.paleor_86

Paleoreef Maps: Evaluation of a comprehensive database of Phanerozoic reefs - Kießling, Wolfgang; et al. (Aapg Bulletin, 1999)
To get a better understanding of controls on reef development through time, we created a comprehensive database on Phanerozoic reefs. The database currently comprises 2470 reefs and contains information about geographic position/paleo-position, age, reef type, dimensions, environmental setting, paleontological and petrographical features, and reservoir quality of each buildup. Reef data were analyzed in two qualitatively different ways. The first type of analysis was by visualization of paleogeographic reef distribution maps. Five examples (Late Devonian, Early Permian, Late Triassic, Late Jurassic, middle Miocene) are presented to show the potential of paleoreef maps for paleogeographic and paleoclimatological reconstructions. The second type of analysis was a numerical processing of coded reef characteristics to realize major trends in reef evolution and properties of reef carbonates. The analysis of paleolatitudinal reef distributions through time shows pronounced asymmetries in some time slices, probably related to climatic asymmetries rather than controlled by plate tectonic evolution alone. The dominance of particular reef builders through time suggests that there are seven cycles of Phanerozoic reef development. First curves for the Phanerozoic distribution of bio-erosion in reefs, bathymetric setting, and debris potential of reefs are presented. The observed pattern in the temporal and spatial distribution of reefs with reservoir quality may assist in hydrocarbon exploration. Statistical tests on the dependencies of reefal reservoir quality suggest that large size, high debris potential, low paleolatitude, high amount of marine aragonite cement, and a platform/shelf edge setting favor reservoir quality. Reefal reservoirs are significantly enhanced in times of high evaporite sedimentation, elevated burial of organic carbon, low oceanic crust production, low atmospheric CO2 content, and cool paleoclimate, as well as when they are present in aragonite oceans.
UnivIS-Import:2015-03-05:Pub.1999.nat.dgeo.IGM.LP.paleor

Paleozoic origins of cheilostome bryozoans and their parental care inferred by a new genome-skimmed phylogeny - Orr, Russell J.S.; Martino, Emanuela Di; Ramsfjell, Mali H.; Gordon, Dennis P.; Berning, Björn; Chowdhury, Ismael; Craig, Sean; Cumming, Robyn L.; Figuerola, Blanca; Florence, Wayne; Harmelin, Jean Georges; Hirose, Masato; et al. (Science Advances, 2022)
Phylogenetic relationships and the timing of evolutionary events are essential for understanding evolution on longer time scales. Cheilostome bryozoans are a group of ubiquitous, species-rich, marine colonial organisms with an excellent fossil record but lack phylogenetic relationships inferred from molecular data. We present genome-skimmed data for 395 cheilostomes and combine these with 315 published sequences to infer relationships and the timing of key events among c. 500 cheilostome species. We find that named cheilostome genera and species are phylogenetically coherent, rendering fossil or contemporary specimens readily delimited using only skeletal morphology. Our phylogeny shows that parental care in the form of brooding evolved several times independently but was never lost in cheilostomes. Our fossil calibration, robust to varied assumptions, indicates that the cheilostome lineage and parental care therein could have Paleozoic origins, much older than the first known fossil record of cheilostomes in the Late Jurassic.
CRIS-Team Scopus Importer:2022-04-15

Parallel evolution controlled by adaptation and covariation in ammonoid cephalopods - Monnet, Claude; de Baets, Kenneth; Klug, Christian (BMC Evolutionary Biology, 2011)
Conclusions: The morphological evolution of these two Devonian ammonoid lineages follows a near parallel evolutionary path for some important shell characters during several million years and through their phylogeny. Evolution of some traits (involution, umbilical lid) appears to be mainly driven by adaptation to improve the hydrodynamic properties of the shell, whereas other characters (sutural complexity) evolved due to covariation with features that play a central role in the morphogenesis of mollusc shells. This example provides evidence that parallel evolution can be driven simultaneously by different factors such as covariation (constructional constraints) and adaptation (natural selection).

Parasites of Ammonoids - de Baets, Kenneth; Keupp, Helmut; Klug, Christian (Ammonoid Paleobiology: From anatomy to Ecology, 2015)

Past and future decline of tropical pelagic biodiversity - Yasuhara, Moriaki; Wei, Chih Lin; Kucera, Michal; Costello, Mark J.; Tittensor, Derek P.; Kießling, Wolfgang; Bonebrake, Timothy C.; Tabor, Clay R.; Feng, Ran; Baselga, Andrés; Kretschmer, Kerstin; Kusumoto, Buntarou; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
A major research question concerning global pelagic biodiversity remains unanswered: when did the apparent tropical biodiversity depression (i.e., bimodality of latitudinal diversity gradient [LDG]) begin? The bimodal LDG may be a consequence of recent ocean warming or of deep-time evolutionary speciation and extinction processes. Using rich fossil datasets of planktonic foraminifers, we show here that a unimodal (or only weakly bimodal) diversity gradient, with a plateau in the tropics, occurred during the last ice age and has since then developed into a bimodal gradient through species distribution shifts driven by postglacial ocean warming. The bimodal LDG likely emerged before the Anthropocene and industrialization, and perhaps ∼15,000 y ago, indicating a strong environmental control of tropical diversity even before the start of anthropogenic warming. However, our model projections suggest that future anthropogenic warming further diminishes tropical pelagic diversity to a level not seen in millions of years.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Climate change; Last Glacial Maximum; Latitudinal diversity gradients; Planktonic foraminifera; Temperature

Patterns and drivers of phytodiversity in steppe grasslands of Central Podolia (Ukraine) - Kuzemko, Anna A.; Steinbauer, Manuel; Becker, Thomas; Didukh, Yakiv P.; Dolnik, Christian; Jeschke, Michael; Naqinezhad, Alireza; Ugurlu, Emin; Vassilev, Kiril; Dengler, Juergen (Biodiversity and Conservation, 2016)
We asked: (i) Which environmental factors determine the level of α-diversity at several scales and β-diversity in steppic grasslands? (ii) How do the effects of environmental factors on α- and β-diversity vary between the different taxonomic groups (vascular plants, bryophytes, lichens)? We sampled nested-plot series ranging from 0.0001 to 100 m2 and additional 10-m2 plots, covering different vegetation types and management regimes in steppes and semi-natural dry grasslands of Central Podolia (Ukraine). We recorded all terricolous taxa and used topographic, soil, land-use and climatic variables as predictors. Richness-environment relationships at different scales and across taxonomic groups were assessed with multimodel inference. We also fitted power-law species-area relationships, using the exponent (z value) as a measure of β-diversity. In general, the richness values in the study region were intermediate compared to those known from similar grasslands throughout the Palaearctic, but for 1 cm2 we found seven species of vascular plants, a new world record. Heat index was the most important factor for vascular plants and bryophytes (negative relation), while lichen diversity depended mainly on stone and rock cover (positive). The explanatory power of climate-related variables increased with increasing grain size, while anthropogenic burning was the most important factor for richness patterns at the finest grain sizes (positive effect). The z values showed more variation at the finest grain sizes, but no significant differences in their mean between scales. The results highlight the importance of integrating scale into ecological analyses and nature conservation assessments in order to understand and manage biological diversity in steppe ecosystems.
Keywords: Biodiversity; Bryophyte; Lichen; Scale dependence; Species richness; Species-area relationship

Patterns and processes of ancient reef crises - Kießling, Wolfgang (The Paleontological Society Papers, 2011)
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.patter

Patterns of island treeline elevation - a global perspective - Irl, Severin D. H.; Anthelme, Fabien; Harter, David E. V.; Jentsch, Anke; Lotter, Elisabeth; Steinbauer, Manuel; Beierkuhnlein, Carl (Ecography, 2016)
Treeline research has strongly focused on mountain systems on the mainland. However, island treelines offer the opportunity to contribute to the global framework on treeline elevation due to their island-specific attributes such as isolation, small area, low species richness and relative youth. We hypothesize that, similar to the mainland, latitude-driven temperature variation is the most important determinant of island treeline elevation on a global scale. To test this hypothesis, we compared mainland with island treeline elevations. Then we focused 1) on the global effects of latitude, 2) on the regional effects of island type (continental vs oceanic islands) and 3) the local effects of several specific island characteristics (age, area, maximum island elevation, isolation and plant species richness). We collected a global dataset of islands (n = 86) by applying a stratified design using GoogleEarth and the Global Island Database. For each island we extracted data on latitude and local characteristics. Treeline elevation decreased from the mainland through continental to oceanic islands. Island treeline elevation followed a hump-shaped latitudinal distribution, which is fundamentally different from the mainland double-hump. Higher maximum island elevation generated higher treeline elevation and was found the best single predictor of island treeline elevation, even better than latitude. Lower island treeline elevation may be the result of a low mass elevation effect (MEE) influencing island climates and an increasingly impoverished species pool but also trade wind inversion-associated aridity. The maximum island elevation effect possibly results from an increasing mass elevation effect (MEE) with increasing island elevation but also range shifts during climatic fluctuations and the summit syndrome (i.e. high wind speeds and poor soils in peak regions). Investigating islands in treeline research has enabled disentangling the global effect of latitude from regional and local effects and, at least for islands, a comprehensive quantification of the MEE.

Patterns of Phanerozoic carbonate platform sedimentation - Kießling, Wolfgang; et al. (Lethaia, 2003)
Carbonate platforms changed substantially in spatial extent, geometry, composition and palaeogeographical distribution through the Phanerozoic. Although reef construction and carbonate platform development are intimately linked today, this was not the case for most of the Phanerozoic. Carbonate production by non-enzymatic precipitation and non-reefal organisms is mostly responsible for this decoupling. Non-reefal carbonate production was especially prolific during times of depressed reef growth, balancing losses in reef carbonate production. Palaeogeographical distribution and spatial extent of Phanerozoic carbonate platforms exhibit trends related to continental drift, evolutionary patterns within carbonate platform biotas, climatic change and, possibly, variations in ocean chemistry. Continental drift moved large Palaeozoic tropical shelf areas into higher latitudes, thereby reducing the potential size of tropical platforms. However, the combined global size of carbonate platforms shows no significant decline through the Phanerozoic, suggesting that availability of tropical shelf areas was not a major control of platform area. This is explained by the limited platform coverage of low-latitude shelves (42% maximum) and occasional high-latitude excursions of platform carbonates. We speculate that reduced tropical shelf area in the icehouse tropics forced the migration of the many carbonate-secreting organisms into higher latitudes and, where terrigenous input was sufficiently low, extensive carbonate platform could develop.
UnivIS-Import:2015-03-09:Pub.2003.nat.dgeo.IGM.LP.patter
Keywords: Carbonate platforms; Palaeoclimate; Palaeogeography; Phanerozoic; Reefs

Patterns of Phanerozoic reef crises - Flügel, Erik; Kießling, Wolfgang (Phanerozoic reef patterns, 2002)
UnivIS-Import:2015-04-20:Pub.2002.nat.dgeo.IGM.LP.patter

Pelagic palaeoecology: the importance of recent constraints on ammonoid palaeobiology and life history - Ritterbush, Kathleen A.; Hoffmann, René; de Baets, Kenneth; Lukeneder, Alexander (Journal of Zoology, 2014)
A review of fossil evidence supports a pelagic mode of life (in the water column) of ammonoids, but they may have spent their life close to the seabottom (demersal), planktonically, or nektonically depending upon the ontogenetic stage and taxon. There are good indications for a planktonic mode of life of ammonoid hatchlings, but a broad range of reproductive strategies might have existed (egg-laying, fecundity). Isotope and biogeographical studies indicate that some forms migrated or swam for considerable distances, whereas others may have been primarily transported by oceanic currents during early and/or late ontogeny. Diverse ammonoid habitats are also supported by evidence from predator-prey relationships derived from characteristic injuries and exceptional fossil finds, which indicate chiefly predatory or scavenging lifestyles. Sublethal injuries preserved in some ammonoid shells, as well as rare stomach and coprolite contents, provide evidence of predation by other cephalopods, arthropods and various jawed vertebrates. Various lines of evidence suggest that different groups of ammonoids had quite different ecologies, but shell shape alone can only give upper constraints on ammonoid capabilities, a matter that needs to be considered when interpreting their diversity and evolutionary history.
Keywords: predator-prey relationships; habitat; anatomy; reproductive strategy; isotope analysis; palaeoecology

Pendant bioconstructions cemented by microbial carbonate in submerged marine caves (Holocene, SE Sicily) - Adriano, Guido; Heindel, Katrin; Birgel, Daniel; Antonietta, Rosso; Mastandrea, Adelaide; Sanfilippo, R.; Russo, Franco; Peckmann, Jörn (Palaeogeography, Palaeoclimatology, Palaeoecology, 2013)
Keywords: Autochthonous micrite; Biostalactites; Serpulids; Sicily; Submerged caves; Sulfate-reducing bacteria

Pennsylvanian Bryozoans of Exceptional Preservation from the Buckhorn Asphalt Quarry, Oklahoma - Seuß, Barbara; Taylor, Paul; Ernst, Andrej; Nützel, Alexander (GSA Annual Meeting, 2016)
The Pennsylvanian (Desmoinesian–Virgilian) Buckhorn Asphalt Quarry (Boggy Formation, Deese Group) in Oklahoma, USA is well known for its exceptional preservation of a diverse marine invertebrate fauna. This includes preservation of original shell material, microscopic characters on shells, or color patterns. Preservation is exceptionally because of early impregnation with hydrocarbons that soaked sediments and fossils. Results from the latest study and the first focusing exclusively on the Buckhorn bryozoans are presented. Nine genera and species are recognized, two of them are new (Stenophragmidium buckhornensis and Streblotrypa (S.) heltzelae) and two genera (Shishoviclema, Shulgapora) are identified in North American strata for the first time. Some skeletal characteristics that are usually lost during diagenesis are uniquely preserved or seen for the first time in Paleozoic bryozoans. These include small to large (5-50 µm in diameter) node-like surface expressions of styles that most likely strengthened the skeleton or were for attachment of the soft tissue rather than defense. ‘Nanoperforations’ observed in S. (S.) heltzelae, S. buckhornensis and Rhombocladia delicatula are tiny holes with a diameter of only 0.5 µm countersunk (bevelled) into the laminated skeletal walls. Such structures are unknown from other bryozoans (recent and fossil) and their genesis – produced by small-sized symbionts (bacteria?), by microendoliths or by the bryozoans themselves? – is unclear. The most likely hypothesis is that they are due to symbionts that lived embedded in the growing walls of the bryozoan zooids. In fractured branches of S. (S.) heltzelae, closely spaced ‘granule’ bands (diameter of granules approximately 6 µm) on the walls of the autozooids were found. Again, such structures have not been observed elsewhere and their origin and function are enigmatic. Mural spines (of varied size and morphology depending on the genus) are reported from R. delicata and Stenoporella sp. Spinose hemiphragms, with spines of 3-30 µm in length, are new features of unknown function found in some trepostomes. Finally, a transverse fibrous fabric found in the fenestrate Septopora blanda is reminiscent of a fabric common in post-Paleozoic cyclostome bryozoans but hitherto not reported in palaeostomates from the Paleozoi

Pennsylvanian in North Central Texas, USA - The Finis Shale - Seuß, Barbara; Mapes, Royal H. (IGCP 596 Climate Change and Biodiversity Patterns in the Mid-Palaeozoic, 2016)

Pennsylvanian of Southern Oklahoma (Upper Carboniferous, USA) - The Buckhorn Asphalt Quarry - Seuß, Barbara (IGCP 596 Climate Change and Biodiversity Patterns in the Mid-Palaeozoic, 2016)
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.oxygen
Keywords: Cameral deposits; Diagenetic end-members; Oxygen isotopes; Pennsylvanian; Stable carbon isotopes; XRD-GADDS

Persistent ecological shifts in marine molluscan assemblages across the end-Cretaceous mass extinction - Kießling, Wolfgang; Aberhan, Martin; Kiessling, Wolfgang (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Contemporary biodiversity loss and population declines threaten to push the biosphere toward a tipping point with irreversible effects on ecosystem composition and function. As a potential example of a global-scale regime shift in the geological past, we assessed ecological changes across the end-Cretaceous mass extinction based on molluscan assemblages at four well-studied sites. By contrasting preextinction and postextinction rank abundance and numerical abundance in 19 molluscan modes of life-each defined as a unique combination of mobility level, feeding mode, and position relative to the substrate-we find distinct shifts in ecospace utilization, which significantly exceed predictions from null models. The magnitude of change in functional traits relative to normal temporal fluctuations at far-flung sites indicates that molluscan assemblages shifted to differently structured systems and faunal response was global. The strengths of temporal ecological shifts, however, are mostly within the range of preextinction site-to-site variability, demonstrating that local ecological turnover was similar to geographic variation over a broad latitudinal range. In conjunction with varied site-specific temporal patterns of individual modes of life, these spatial and temporal heterogeneities argue against a concerted phase shift of molluscan assemblages from one well-defined regime to another. At a broader ecological level, by contrast, congruent tendencies emerge and suggest deterministic processes. These patterns comprise the well-known increase of deposit-feeding mollusks in postextinction assemblages and increases in predators and predator-resistant modes of life, i.e., those characterized by elevated mobility and infaunal life habits.
UnivIS-Import:2015-07-08:Pub.2015.nat.dgeo.IGM.LP.persis
Keywords: Ecospace; End-Cretaceous mass extinction; Functional groups; Mollusks; Regime shift

Phanerozoic marine biodiversity: a fresh look at data, methods, patterns and processes. Global biodiversity, extinction intervals and biogeographic perturbations through time - Aberhan, Martin; Kießling, Wolfgang (Global Biodiversity, Extinction Intervals and Biogeographic Perturbations Through Time, 2012)
UnivIS-Import:2015-04-20:Pub.2012.nat.dgeo.IGM.LP.phaner

Phanerozoic parasitism and marine metazoan diversity: dilution versus amplification - de Baets, Kenneth; Huntley, John Warren; Scarponi, Daniele; Klompmaker, Adiël A.; Skawina, Aleksandra (Philosophical Transactions of the Royal Society B-Biological Sciences, 2021)
Growing evidence suggests that biodiversity mediates parasite prevalence. We have compiled the first global database on occurrences and prevalence of marine parasitism throughout the Phanerozoic and assess the relationship with biodiversity to test if there is support for amplification or dilution of parasitism at the macroevolutionary scale. Median prevalence values by era are 5% for the Paleozoic, 4% for the Mesozoic, and a significant increase to 10% for the Cenozoic. We calculated period-level shareholder quorum sub-sampled (SQS) estimates of mean sampled diversity, three-timer (3T) origination rates, and 3T extinction rates for the most abundant host clades in the Paleobiology Database to compare to both occurrences of parasitism and the more informative parasite prevalence values. Generalized linear models (GLMs) of parasite occurrences and SQS diversity measures support both the amplification (all taxa pooled, crinoids and blastoids, and molluscs) and dilution hypotheses (arthropods, cnidarians, and bivalves). GLMs of prevalence and SQS diversity measures support the amplification hypothesis (all taxa pooled and molluscs). Though likely scale-dependent, parasitism has increased through the Phanerozoic and clear patterns primarily support the amplification of parasitism with biodiversity in the history of life. This article is part of the theme issue ‘Infectious disease macroecology: parasite diversity and dynamics across the globe’.
Keywords: paleopathology; Phanerozoic; paleoparasitolog; marine disease; Metazoa; biodiversity

Phanerozoic Reef Patterns - Kießling, Wolfgang; Flügel, Erik; Golonka, Jan (Society for Sedimentary Geology (SEPM), 2002)
UnivIS-Import:2015-05-08:Pub.2002.nat.dgeo.IGM.LP.frompa
Keywords: Reefs; Geology

Phanerozoic reef trends based on the Paleoreefs database - Kießling, Wolfgang (The History and Sedimentology of Ancient Reef Systems, 2001)
UnivIS-Import:2015-04-20:Pub.2001.nat.dgeo.IGM.LP.phaner

Phanerozoic time scale and definition of time slices - Golonka, Jan; Kießling, Wolfgang (Phanerozoic Reef Patterns, 2002)
UnivIS-Import:2015-04-20:Pub.2002.nat.dgeo.IGM.LP.phaner

Phanerozoic trends in skeletal mineralogy driven by mass extinctions - Kießling, Wolfgang; et al. (Nature Geoscience, 2008)
Marine calcifying organisms that produce sediments and build reefs generally have skeletons and shells that are composed of either aragonite or calcite. Long-term changes in the estimated Mg/Ca ratios of sea water tend to correspond to changes in the prevailing mineralogy of these creatures. High Mg/Ca ratios are expected to favour the spread of aragonitic organisms, whereas calcitic taxa are thought to benefit from low Mg/Ca ratios. Here we test these patterns throughout the Phanerozoic eon and assess the relative impacts of changing ocean chemistry and mass extinctions on the evolutionary success of calcifying organisms. We find that mass extinctions are more important in regulating long-term patterns of skeletal mineralogy than the Mg/Ca ratios of the global oceans. Furthermore, selective recovery from mass extinctions is usually more important than selective extinction, in driving the Phanerozoic pattern of skeletal mineralogy. But even in the recovery phase there is no clear connection between changes in the dominance of aragonite or calcite and the Mg/Ca ratio of the oceans, thus providing further evidence for the complexity of biotic recoveries. © 2008 Macmillan Publishers Limited.
UnivIS-Import:2015-03-09:Pub.2008.nat.dgeo.IGM.LP.phaner

Phanerozoic trends in the global diversity of marine invertebrates - Alroy, John; Aberhan, Martin; Fürsich, Franz; Bottjer, David; Foote, Michael; Harries, Peter; Hendy, Austin; Holland, Steven; Ivany, Linda; Kießling, Wolfgang (Science, 2008)
It has previously been thought that there was a steep Cretaceous and Cenozoic radiation of marine invertebrates. This pattern can be replicated with a new data set of fossil occurrences representing 3.5 million specimens, but only when older analytical protocols are used. Moreover, analyses that employ sampling standardization and more robust counting methods show a modest rise in diversity with no clear trend after the mid-Cretaceous. Globally, locally, and at both high and low latitudes, diversity was less than twice as high in the Neogene as in the mid-Paleozoic. The ratio of global to local richness has changed little, and a latitudinal diversity gradient was present in the early Paleozoic.
UnivIS-Import:2015-04-14:Pub.2008.nat.dgeo.IGM.LP.phaner_3

Phanerozoic trends in the global geographic disparity of marine biotas - Kießling, Wolfgang; et al. (Paleobiology, 2009)
Previous analyses of the history of Phanerozoic marine biodiversity suggested that the post-Paleozoic increase observed at the family level and below was caused, in part, by an increase in global provinciality associated with the breakup of Pangea. Efforts to characterize the Phanerozoic history of provinciality, however, have been compromised by interval-to-interval variations in the methods and standards used by researchers to calibrate the number of provinces. With the development of comprehensive, occurrence-based data repositories such as the Paleobiology Database (PaleoDB), it is now possible to analyze directly the degree of global compositional disparity as a function of geographic distance (geo-disparity) and changes thereof throughout the history of marine animal life. Here, we present a protocol for assessing the Phanerozoic history of geo-disparity, and we apply it to stratigraphic bins arrayed throughout the Phanerozoic for which data were accessed from the PaleoDB. Our analyses provide no indication of a secular Phanerozoic increase in geo-disparity. Furthermore, fundamental characteristics of geo-disparity may have changed from era to era in concert with changes to marine venues, although these patterns will require further scrutiny in future investigations. © 2009 The Paleontological Society. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.phaner

Phasenanalyse und Spurenelementgehalte von Riffsanden der Seychellen - Bausch, Walter; Krumm, Stefan; Munnecke, Axel (Erlanger Beiträge zur Petrographischen Mineralogie, 2012)
Riffsande der Seychellen-Inseln setzen sich im Mittel aus knapp 60 % Aragonit und knapp 30 % Mg-Calcit zusammen. Quarz und zwei andere Calcit-Varietäten stellen den Rest. Häufigstes Spurenelement ist Magnesium mit 1,6 %, gefolgt von Strontium mit 4550 ppm (Mittelwerte; bei erheblicher Streubreite). Extrapoliert auf reine Komponenten, finden sich 6-7 % Mg im Mg-Calcit, sowie 7160 ppm Sr im Aragonit. Eine Gleichung der negativen Korrelation Sr/Mg kann festgelegt werden. Die Riffsande variieren auch in den Korngrößen. Grobe Sande enthalten relativ mehr Mg-Calcit, feine Sande relativ mehr Aragonit. Konsequenterweise variieren auch die Spurenelementgehalte sinngemäß: feine Sande führen relativ mehr Sr, grobe Sande relativ mehr Mg.
Keywords: Calcit; Riffsande; Seychellen; Aragonit; Mg-Calcit; Strontium; Sr; Spurenelemente

Physical and environmental drivers of Paleozoic tetrapod dispersal across Pangaea - Brocklehurst, Neil; Dunne, Emma; Cashmore, Daniel; Frӧbisch, Jӧrg (Nature Communications, 2018)
The Carboniferous and Permian were crucial intervals in the establishment of terrestrial ecosystems, which occurred alongside substantial environmental and climate changes throughout the globe, as well as the final assembly of the supercontinent of Pangaea. The influence of these changes on tetrapod biogeography is highly contentious, with some authors suggesting a cosmopolitan fauna resulting from a lack of barriers, and some identifying provincialism. Here we carry out a detailed historical biogeographic analysis of late Paleozoic tetrapods to study the patterns of dispersal and vicariance. A likelihood-based approach to infer ancestral areas is combined with stochastic mapping to assess rates of vicariance and dispersal. Both the late Carboniferous and the end-Guadalupian are characterised by a decrease in dispersal and a vicariance peak in amniotes and amphibians. The first of these shifts is attributed to orogenic activity, the second to increasing climate heterogeneity.<br

Phytoplankton dynamics across the Ordovician/Silurian boundary at low palaeolatitudes: correlations with carbon isotopic and glacial events. - Delabroye, Aurelien; Munnecke, Axel; Vecoli, Marco; Copper, Paul; Tribovillard, Nicolas; Joachimski, Michael; Desrochers, Andre; Servais, Thomas; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
The Late Ordovician culminated in a major glacial period that has been related to one of the strongest mass extinctions recorded during the Phanerozoic. During this interval, Anticosti Island (Québec, eastern Canada) was located at low to intermediate palaeolatitudes (15-30° S) on the eastern margin of Laurentia. It displays a relatively complete section across the Ordovician-Silurian (O/S) boundary. Upper Ordovician to Lower Silurian strata of Anticosti studied here comprise the Vauréal (Katian), Ellis Bay (Hirnantian) and Becscie (latest Hirnantian-Rhuddanian) formations. Phytoplankton dynamics inferred from the acritarch content of these strata are locally compared with new geochemical environmental proxies (δ13C), with recent palynological data from Baltica and also with phytoplankton dynamics as described from near-polar, high latitude localities of the Gondwana region. Two positive excursions of the carbon isotope record have been identified in the lower and upper Ellis Bay Formation.Overall, phytoplankton trends are as follows: (1) as with chitinozoans, conodonts, brachiopods and corals, acritarchs from Anticosti display a major turn-over during the early Hirnantian (uppermost Vauréal Formation-lower Ellis Bay Formation), with the appearance of taxa that exhibit Silurian affinities (e.g., Tylotopalla sp., Ammonidium sp., Oppilatala sp., Evittia sp., Dilatisphaera spp.). High polymorphism for some common taxa is observed in the interval corresponding to the first δ13C positive excursion. Using sequence stratigraphy, this period may be related to a first glacially driven sea-level drawdown corresponding to terrestrial ice-sheet growth on Gondwana, such as recorded in Morocco. (2) Subsequently, during the late Hirnantian of Anticosti (uppermost Ellis Bay Formation), phytoplanktic communities suffered a crisis, exemplified by the disappearance of several typical, large Late Ordovician taxa (i.e., Orthosphaeridium spp., Peteinosphaeridium spp., large Baltisphaeridum spp., Sacculidium sp.). The lower Becscie strata, corresponding to the time of deglaciation at the O/S boundary interval, only contain a low diversity assemblage dominated by large acritarchs of the genus Hoegklintia and other morphologically related forms, and a few tolerant and long-ranging taxa (e.g., Evittia remota, Micrhystridium spp., leiospheres). Despite a possible taphonomic bias in the uppermost Ellis Bay Formation, the major crisis in the late Hirnantian coincides with the second δ13C excursion and a second, stronger glacially-driven sea-level fall corresponding to the time of the maximum extend of the ice sheets on Gondwana. (3) Such phytoplankton events have also been detected in Gondwanan ice-center area, but with "typical Ordovician taxa crises" occurring apparently later when plotted against positive carbon isotope excursions, as also observed in Baltica. This time-lag may be linked to a basin configuration of the studied areas, where environmental stress consequently differed or linked to the presence of omission surfaces coupled with preservation bias of acritarch assemblages in the uppermost Ordovician strata of Anticosti. In addition to their biostratigraphic and palaeobiogeographic utility, acritarchs turn out to be more specific in highlighting palaeoenvironmental conditions. © 2011 Elsevier B.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LG.phytop
Keywords: Baltica; Carbon isotopes; Gondwana; Laurentia; Ordovician-Silurian boundary; Phytoplankton

Plant invasion and speciation along elevational gradients on the oceanic island La Palma, Canary Islands - Steinbauer, Manuel; Irl, Severin D. H.; Maria Gonzalez-Mancebo, Juana; Breiner, Frank T.; Hernandez-Hernandez, Raquel; Hopfenmueller, Sebastian; Kidane, Yohannes; Jentsch, Anke; Beierkuhnlein, Carl (Ecology and Evolution, 2017)
Ecosystems that provide environmental opportunities but are poor in species and functional richness generally support speciation as well as invasion processes. These processes are expected not to be equally effective along elevational gradients due to specific ecological, spatial, and anthropogenic filters, thus controlling the dispersal and establishment of species. Here, we investigate speciation and invasion processes along elevational gradients. We assess the vascular plant species richness as well as the number and percentage of endemic species and non-native species systematically along three elevational gradients covering large parts of the climatic range of La Palma, Canary Islands. Species richness was negatively correlated with elevation, while the percentage of Canary endemic species showed a positive relationship. However, the percentage of Canary–Madeira endemics did not show a relationship with elevation. Non-native species richness (indicating invasion) peaked at 500 m elevation and showed a consistent decline until about 1,200 m elevation. Above that limit, no non-native species were present in the studied elevational gradients. Ecological, anthropogenic, and spatial filters control richness, diversification, and invasion with elevation. With increase in elevation, richness decreases due to species–area relationships. Ecological limitations of native ruderal species related to anthropogenic pressure are in line with the absence of non-native species from high elevations indicating directional ecological filtering. Increase in ecological isolation with elevation drives diversification and thus increased percentages of Canary endemics. The best preserved eastern transect, including mature laurel forests, is an exception. The high percentage of Canary–Madeira endemics indicates the cloud forest's environmental uniqueness—and thus ecological isolation—beyond the Macaronesian islands.
Keywords: alien species; altitudinal gradient; colonization; diversification; diversity; endemism; exotic; high-elevation ecosystems; island biogeography

Plant responses to climatic extremes: Within-species variation equals among-species variation - Malyshev, Andrey V.; Khan, Mohammed A. S. Arfin; Beierkuhnlein, Carl; Steinbauer, Manuel; Henry, Hugh A. L.; Jentsch, Anke; Dengler, Juergen; Willner, Evelin; Kreyling, Juergen (Global Change Biology, 2016)
Within-species and among-species differences in growth responses to a changing climate have been well documented, yet the relative magnitude of within-species vs. among-species variation has remained largely unexplored. This missing comparison impedes our ability to make general predictions of biodiversity change and to project future species distributions using models. We present a direct comparison of among- versus within-species variation in response to three of the main stresses anticipated with climate change: drought, warming, and frost. Two earlier experiments had experimentally induced (i) summer drought and (ii) spring frost for four common European grass species and their ecotypes from across Europe. To supplement existing data, a third experiment was carried out, to compare variation among species from different functional groups to within-species variation. Here, we simulated (iii) winter warming plus frost for four grasses, two nonleguminous, and two leguminous forbs, in addition to eleven European ecotypes of the widespread grass Arrhenatherum elatius. For each experiment, we measured: (i) C/N ratio and biomass, (ii) chlorophyll content and biomass, and (iii) plant greenness, root 15N uptake, and live and dead tissue mass. Using coefficients of variation (CVs) for each experiment and response parameter, a total of 156 within- vs. among-species comparisons were conducted, comparing within-species variation in each of four species with among-species variation for each seed origin (five countries). Of the six significant differences, within-species CVs were higher than among-species CVs in four cases. Partitioning of variance within each treatment in two of the three experiments showed that within-species variability (ecotypes) could explain an additional 9% of response variation after accounting for the among-species variation. Our observation that within-species variation was generally as high as among-species variation emphasizes the importance of including both within- and among-species variability in ecological theory (e.g., the insurance hypothesis) and for practical applications (e.g., biodiversity conservation).
Keywords: Disturbance; Extreme climatic events; Genetic diversity; Inter-specific variation; Intraspecific variation; Niche models; Provenance

Plasticity and seasonality of the vertical migration behaviour of Antarctic krill using acoustic data from fishing vessels - Bahlburg, Dominik; Hüppe, Lukas; Böhrer, Thomas; Thorpe, Sally E.; Murphy, Eugene J.; Berger, Uta; Meyer, Bettina (Royal Society Open Science, 2023)
Understanding the vertical migration behaviour of Antarctic krill is important for understanding spatial distribution, ecophysiology, trophic interactions and carbon fluxes of this Southern Ocean key species. In this study, we analysed an eight-month continuous dataset recorded with an ES80 echosounder on board a commercial krill fishing vessel in the southwest Atlantic sector of the Southern Ocean. Our analysis supports the existing hypothesis that krill swarms migrate into deeper waters during winter but also reveals a high degree of variability in vertical migration behaviour within seasons, even at small spatial scales. During summer, we found that behaviour associated with prolonged surface presence primarily occurred at low surface chlorophyll a concentrations whereas multiple ascent-descent cycles per day occurred when surface chlorophyll a concentrations were elevated. The high plasticity, with some krill swarms behaving differently in the same location at the same time, suggests that krill behaviour is not a purely environmentally driven process. Differences in life stage, physiology and type of predator are likely other important drivers. Finally, our study demonstrates new ways of using data from krill fishing vessels, and with the routine collection of additional information in potential future projects, they have great potential to significantly advance our understanding of krill ecology.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Antarctic krill; seasonal vertical migration; vertical migration behaviour

Plastikmüllbelastung im Nordpolarmeer - Analyse der Mikroplastikkontamination arktischer Bohrmuscheln - Teichert, Sebastian; Löder, Martin; Pyko, Ines; Schulbert, Christian; Wisshak, Max; Laforsch, Christian (GIT Labor-Fachzeitschrift, 2022)

Pleistocene to Recent scleractinian deep-water corals and coral facies in the Eastern Mediterranean - Taviani, Marco; Vertino, Agostina; López Correa, Matthias; Savini, Alessandra; De Mol, Ben; Remia, Alessandro; Montagna, Paolo; Angeletti, Lorenzo; Zibrowius, Helmut; Alves, Tiago; Salomidi, Maria; Ritt, Bénédicte; et al. (Facies, 2011)
Recent investigations of the Eastern Mediterranean Sea carried out during the GECO cruise with RV Urania provided a substantial number of new cold-water coral (CWC) records, including branching and solitary scleractinian species. These new sites are located along steep escarpments and on topographic highs along the margins of Crete, Karpathos, and Rhodes. The majority of the corals represent fossil occurrences, predominantly Late Pleistocene assemblages. Our research documents that the Eastern Mediterranean Basin has been colonized by CWC at favorable times during the Last Glacial, in particular during the Younger Dryas. Schizocyathus fissilis is reported for the first time for the Mediterranean, while the finding of Ceratotrochus magnaghii represents the first record for the Eastern Mediterranean. Various coral facies occur on the southerly island slopes of Crete, Karpathos, and Rhodes, including hardgrounds and loose skeletal sediments. Hardgrounds occur on steep topographies between ca. 500 and 1,700 m, and can conveniently be subdivided as (1) Neopycnodonte-Desmophyllum framestone, (2) Desmophyllum-Caryophyllia framestone, (3) Madrepora-Lophelia rudstone, (4) Pelagic mudstone and wackestone, and (5) Siliciclastic-carbonate conglomerate and breccia. Unconsolidated skeletal sediments containing corals mainly occur on gentler topographic situations between ca. 140 and 600 m and can be subdivided as: (A) Lophelia-Madrepora rubble, (B) Dendrophyllia rubble, (C) Stenocyathus rubble, (D) Caryophyllia calveri rubble, and (E) fine-grained sediment with octocoral axes. Many of these facies types are also present in the western part of the Mediterranean and have fossil representatives from the Pleistocene to the Recent. Radiocarbon dating (AMS- 14C) reveals Younger Dryas ages between 12.4 and 12.0 ka cal BP for Lophelia pertusa and Madrepora oculata. Desmophyllum dianthus occurs during the Last Glacial Maximum (21.8 ka cal BP) and the Younger Dryas (11.7 ka cal BP), as well as during the Late Holocene and subrecent times (4.4-0.6 ka cal BP). Caryophyllia sarsiae occurs during the Late Glacial (15.5 ka cal BP), while Caryophyllia calveri occurs during the Early Preboreal (10.8 ka cal BP). The ages for the framework-constructing corals L. pertusa and M. oculata are coherent with their temporal predominance during the Younger Dryas in other parts of the Mediterranean. © 2010 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.pleist
Keywords: Cold-water corals; Eastern Mediterranean; Facies; Holocene; Late Pleistocene

Positive sport-biosphere interactions? − Cross-country skiing delays spring phenology of meadow vegetation - Steinbauer, Manuel; Kreyling, Jürgen; Stöhr, Caroline; Audorff, Volker (Basic and Applied Ecology, 2018)
Space requirements by winter sports and accelerating global warming are usually perceived as stressors for mountain meadow plant communities. Cross-country ski track preparation (i.e. grooming), however, might retard effects of climate change and, being limited in space requirements, might increase abiotic heterogeneity. The effect of cross-country ski tracks on meadow vegetation was quantified along a representative ski track that had been operated for 30 years in the Fichtelgebirge, a low mountain range in central Europe. Paired sampling was implemented to assess the effect of skiing operations on snow and soil properties, plant phenology, biomass production and species composition. Additionally, boosted regression tree analyses were used to quantify the relative importance of the cross-country ski track compared to other environmental conditions. The cross-country ski track strongly increased snow density, enhanced soil frost, and retarded snowmelt, thereby delaying flower phenology (by 2.1 days) and the early development stages of plant species on the track. However, biomass, species richness and species composition were unaffected by skiing operations except for one species (Leontodon autumnalis) showing exclusive occurrence on the track while four others showed reduced relative occurrence on the track. While snow and soil properties were influenced by cross-country ski track preparation, natural environmental variability was more influential for species composition and biomass production than the ski track. We therefore conclude that the ski track – without artificial snow – did not negatively affect species composition. By delaying flower phenology, effects of the ski track even counteracted global warming to some degree. Due to their small spatial extent in the landscape, these ski tracks may add to environmental heterogeneity and thus support sustaining diverse species compositions during environmental changes.

Possible oceanic circulation patterns, surface water currents and upwelling zones in the Early Palaeozoic - Servais, Thomas; Danelian, Taniel; Harper, David A.T.; Munnecke, Axel (GFF, 2014)
As global reconstructions for the Early Palaeozoic (Cambrian, Ordovician and Silurian periods) are now becoming more reliable, ancient atmospheric and oceanic circulation patterns may now be modelled with increasing confidence. Here we examine previous studies on Early Palaeozoic palaeoceanography. It is assumed that past circulation patterns were governed by the same factors that govern them today. We here introduce some hypothetical base maps that predict the possible locations of ancient surface water currents, the position of oceanic gyres and possible ancient upwelling zones. © 2014 © 2014 Taylor & Franci
Keywords: Early Palaeozoic; palaeoceanography; palaeogeography; upwelling zones

Post-glacial microbialite formation in coral reefs of the Pacific, Atlantic, and Indian Oceans - Heindel, Katrin; Birgel, Daniel; Brunner, Benjamin; Thiel, Volker; Westphal, Hildegard; Gischler, Eberhard; Ziegenbalg, Simone; Cabioch, Guy; Sjövall, Peter; Peckmann, Jörn (Chemical Geology, 2012)
Keywords: Coral reef; EPS-mineralization; Fertilization; Microbial mat; Sulfate-reducing bacteria; Volcanic hinterland

Preboreal onset of Norwegian cold-water coral growth beyond the Arctic Circle revealed by radiocarbon and U-series dating and neodymium isotopes - López Correa, Matthias; Montagna, Paolo; Joseph, Nina; Rüggeberg, Andres; Fietzke, Jan; Flögel, Sascha; Dorschel, Boris; Goldstein, Steve; Wheeler, Andrew; Freiwald, André (Quaternary Science Reviews, 2012)
Cold-water coral mounds of Lophelia pertusa are widespread across the Scandinavian shelf, which was completely ice-covered during the Last Glacial Maximum between 22 to 18ka BP. Rapid deglacial meltdown of the Fennoscandian inland ice and the retreat of its ice-streams freed most of the shelf of ice by 15ka BP. However, cold-water coral growth commenced only after the Pleistocene-Holocene transition at 11.65ka BP, when modern-like climatic patterns and oceanographic conditions were established. A tight climatic coupling has been constrained with U-series ages. Coupled 14C ages provide local reservoir ages from various gravity cores in a fjord-setting in Stjernsund at 70°N and on the open shelf in Trænadjupet at 66°N. Reinvestigation of earlier 14C coral chronologies suggests that coral ecosystems widely established themselves across the entire 3000km long Scandinavian shelf prior to 10ka BP. The earliest occurrence of Madrepora oculata at 2.4ka BP suggests a late Holocene colonization of the Norwegian shelf, which is linked to a prominent mound growth hiatus in Trænadjupet (64°N). Mound growth rates near the northern biogeographic boundary of L.pertusa with up to 614cmka -1 during certain growth periods are much higher than the previously reported fastest rates of 220cmka -1 from the Irish margin. Contemporaneous rapid fjordbasin sedimentation is slower with 63cmka -1. Matrix 14C ages overlap with coral 14C ages from the same horizon. This indicates rapid framework construction and efficient trapping of background sediment. Hiatuses are frequent in on-mound sediments and only short periods of coral growth are recorded. Coupled Δ 14C and ε Nd values indicate a persistent Holocene inflow of the North Atlantic Current in Stjernsund, but also deglacial meltwater mixing during the early Holocene prior to 9.5ka BP. Reservoir ages are overall close to the surface marine reservoir age, but ΔR is highly localized. © 2011 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.prebor

Predicting extinction from fossil trajectories of geographical ranges in benthic marine molluscs - Tietje, Melanie; Kießling, Wolfgang (Journal of Biogeography, 2013)
Aim: The geographical ranges of marine taxa wax and wane in a nearly symmetrical fashion over their durations. We use this pattern as well as the age distribution of genera to predict the time of extinction of extant genera of benthic marine molluscs. Location: A global occurrence database (Paleobiology Database) of fossil marine molluscs from the Mesozoic and Cenozoic eras was used for this study. Methods: For the geographical range method, we determined the average trajectories of geographical range size for extinct genera of bivalves and gastropods. The maxima of these trajectories were used as landmarks for predicting the time of extinction for extant genera. Prediction was done by cross-multiplication, using the time elapsed until the maximum was reached and the position of the landmark. For the duration-frequency method, we calculated the time of extinction based on probabilities derived from the frequency distribution of stratigraphic ranges (durations) of all extinct genera. The accuracy and precision of predictions were tested with extinct genera and then applied to extant genera. Results: On average, bivalve and gastropod extinct genera reached their maximum geographical range size at 62% and 50% of their total duration. The accuracy of predictions ranged from -3.1 to 11.0 million years (Myr) for both groups, and the precision ranged from 13.6 to 19.5 Myr. Only a small subset of extant genera was suitable for prediction with the geographical range method, mainly because the geographical ranges of most extant genera are still rising on geological time-scales. The second method provided a similar prediction quality, but showed a substantial decrease in quality when predicting long-duration (> 100 Myr) genera. Main conclusions: The mean probability for an accurate prediction using the geographical range approach is 57% with a precision of ± 15 Myr. Prediction is possible only for genera whose peak geographical range has already elapsed (17% of extant bivalves, 16% of extant gastropods). The duration-frequency approach does not have this prerequisite and is therefore applicable to many more genera, but prediction quality declines with duration. The two methods therefore complement each other and can supplement the various efforts used to estimate extinction risk. © 2012 Blackwell Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.predic
Keywords: Cenozoic; Extinction; Geographical range; Marine biogeography; Marine molluscs; Mesozoic; Prediction

Prediction of ion selectivity by quantum chemical calculations X: A recent (personal) review - Puchta, Ralph; Begel, Svetlana; van Eldik, Rudi (Computational Chemistry, 2019)
In this review we present a simple and robust method to investigate the ion selectivity of cryptands based on quantum chemical methods. Based on easily understandable model equations and fundamental structural consideration one can rationalize or predict the observed selectivity and the underlying structural conditions. Additionally, we can learn unhampered from neighboring effects the changes in the cryptand to host the ions most effectively. The performance of this concept is demonstrated on several well known cryptands from different supramolecular groups like Lehn and others.
CRIS-Team Scopus Importer:2019-08-23
Keywords: DFT; Main group ions; Selective ion complexation; 2-Cryptands

Preliminary Estimation of Paleoproductivity via TOC and Habitat Types: Which Method Is More Reliable? —A Case Study on the Ordovician–Silurian Transitional Black Shales of the Upper Yangtze Platform, South China - Wenbo, Su; Yongbiao, Wang; Cramer, Bradley D.; Munnecke, Axel; Zhiming, Li; Lipu, Fu (Journal of China University of Geosciences, 2008)
New total organic carbon (TOC) data from the two Ordovician-Silurian transitional graptolite-bearing black shale intervals, the Wufeng Formation and the Longmaxi Formation in Central Guizhou and West Hubei, respectively, as well as previously reported TOC data from the same intervals in other places on the Yangtze platform of South China, have been used to produce an initial estimate of the primary paleoproductivity via a conventional inverse method (i.e., R). The values of the R are estimated to be 32 (43-21) gC/(m·a) (Wufeng Formation) and 21 (27-16) gC/(m·a) (Longmaxi Formation). Also, simultaneously, the habitat types (i.e., HT; cf., BA: benthic assemblage) and their temporal and spatial changes have been documented from the same succession, and an initial estimate of the primary paleoproductivity has been produced using a forward method (i.e., R). Being bounded mainly by the peritidal to inner-shelf environment shelly-facies or mixed-facies successions with BA1 to BA3 faunas both at the top and the base, which indicates the habitat types from HT II to HT III, the biohabitat type of the two graptolite-bearing black shale intervals can be limited to HT III to HT IV, corresponding to the inner shelf to the outer shelf, with depths from roughly 60 m to 200-300 m. Based on the current data from the South China Sea and the southern part of the East China Sea, values of R should be about 100 to 400 gC/(m·a). The difference in the results via the two methods suggests that paleoproductivity estimates from the geological strata need to be made cautiously, with particular attention paid to the paleogeographic setting, oxic-anoxic conditions, as also the preservation factor of organic carbon. © 2008 China University of Geosciences.
Keywords: primary productivity; black shale; TOC; habitat type (HT); Ordovician; Silurian transition; South China

Pre-mass extinction decline of latest Permian ammonoids - Kießling, Wolfgang; Schobben, Martin; Ghaderi, Abbas; Hairapetian, Vachik; Leda, Lucyna; Korn, Dieter (Geology, 2018)
The devastating end-Permian mass extinction is widely considered to have been caused by large-scale and rapid greenhouse gas release by Siberian magmatism. Although the proximate extinction mechanisms are disputed, there is widespread agreement that a major extinction pulse occurred immediately below the biostratigraphically defined Permian-Triassic boundary. Our statistical analyses of stratigraphic confidence intervals do not comply with a single end-Permian extinction pulse of ammonoids in Iran. High turnover rates and extinction pulses are observed over the last 700 k.y. of the Permian period in two widely separated sections representative of a larger area. Analyses of body sizes and morphological complexity support a gradual decline over the same interval. Similar pre-mass extinction declines and disturbances of the carbon cycle have sometimes been reported from other regions, suggesting a widespread, but often overlooked, environmental deterioration at a global scale, well before the traditional main extinction pulse.

Prevailing anoxia in the Kungurian (Permian) of South China: Possible response to divergent climate trends between the tropics and Gondwana - Liu, Chao; Jarochowska, Emilia; Du, Yuansheng; Munnecke, Axel; Dai, Xianduo (Gondwana Research, 2017)
Keywords: Early–Middle Permian; Icehouse–greenhouse climate transition; Ocean stagnation; Primary productivity

Primary versus diagenetic isotope signals in Pseudorthoceras sp. from the Buckhorn Asphalt Quarry (mid-Pennsylvanian, Oklahoma) - a detailed study of cameral deposits - Seuß, Barbara; Titschack, Jürgen; Nützel, Alexander (Annual Meeting of the Paläontologische Gesellschaft, 2010)
Oxygen and carbon stable isotope studies of well-preserved fossils present an important data source for palaeoclimatic studies. Commonly, the older the fossils, the less good they are preserved. The Buckhorn Asphalt Quarry Lagerstätte from the mid-Pennsylvanian of Oklahoma is one of the few Palaeozoic examples, where original (metastable) shell material, such as aragonite and high magnesium calcite (HMC) is found, due to their early post-mortal hydrocarbon impregnation. The Buckhorn Asphalt Quarry is characterised by fossiliferous sediments soaked with hydrocarbons, which commonly prevented diagenesis. This study presents microstructural, mineralogical and stable isotope data from Pseudorthoceras sp. (two chambers with their cameral deposits). Therefore data from thin section analysis, scanning electron microscope (SEM) combined with an energy disperse x-ray (EDX), and x-ray diffraction (XRD) with a general area detection diffraction system (GADDS) analysis were combined. XRD-GADDS is a relatively new method to investigate the shells mineralogy and allows the non-destructive, site-specific identification of mineral phases. Altogether seven microstructures were differed in the sections drilled for isotope dating. These could be divided into two primary mineralogies, aragonite and HMC. We don’t have any knowledge of cameral deposits with a HMC mineralogy or found any evidence of this in literature. The only partially unaltered preserved microstructure is the nacre of the septum. All other microstructures exhibit a partial or complete alteration to low magnesium calcite (LMC), or in case of the primary HMC to LMC and dolomite. According to the isotope signature the diagenesis took place most likely in the meteoric environment. The partial diagenesis results in isotope values, which plot along a linear trend between the two end-members. This linear trend could easily be misinterpreted as kinetic vital effect, if no sorrow phase control was performed. The isotopic signal of the primary nacre of the septum suggest a normal marine environment for these nektonic molluscs, with tropical temperatures of 14°C to 15°C (δ18Oseawater 1.5 ‰, a typical value for modern tropical marginal seas

Productivity controlled cold-water coral growth periods during the last glacial off Mauritania - Frank, Norbert; Wienberg, Claudia; Hebbeln, Dierk; López Correa, Matthias; Douville, Eric; Freiwald, André; Eisele, Markus (Marine Geology, 2011)
Cold-water corals are widely distributed along the Atlantic continental margin with varying growth patterns in relation to their specific environment. Here, we investigate the long-term development of cold-water corals that once thrived on a low-latitude (17°40'N) cold-water coral mound in the Banda Mound Province off Mauritania during the last glacial-interglacial cycle. U/Th dates obtained from 20 specimens of the cold-water coral Lophelia pertusa, revealed three distinct periods of coral growth during the last glacial at 65 to 57. kyr. BP, 45 to 32. kyr. BP and 14. kyr. BP, thus comprising the cool periods of Marine Isotopic Stages (MIS) 2-4. These coral growth periods occur during periods of increased productivity in the region, emphasizing that productivity seems to be the major steering factor for coral growth off Mauritania, which is one of the major upwelling regions in the world. This pattern differs from the well studied coral mounds off Ireland, where the current regime predominantly influences the prosperity of the cold-water corals. Moreover, coral growth off Ireland takes place during rather warm interglacial and interstadial periods, whereas off Mauritania coral growth is restricted to glacial and stadial periods. However, the on-mound sedimentation patterns off Mauritania largely resemble the observations reported from the Irish mounds. The bulk of the preserved sediments derives from periods of coral growth, whereas during periods without corals hardly any net sedimentation or mound growth took place. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.produc
Keywords: Banda Mound Province; Carbonate mounds; Cold-water corals; Lophelia; NW-Africa; Primary productivity

Proliferation and demise of deep-sea corals in the Mediterranean during the Younger Dryas - McCulloch, Malcolm; Taviani, Marco; Montagna, Paolo; López Correa, Matthias; Remia, Alessandro; Mortimer, Graham (Earth and Planetary Science Letters, 2010)
Uranium-series and radiocarbon ages are reported for deep-sea corals Madrepora oculata, Desmophyllum dianthus, Lophelia pertusa and Caryophyllia smithii from the Mediterranean Sea. U-series dating indicates that deep-sea corals have persisted in the Mediterranean for over 480,000years, especially during cool interstadial periods. The most prolific period of growth however appears to have occurred within the Younger Dryas (YD) period from 12,900 to 11,700years BP followed by a short ( 330years) phase of post-YD coral growth from 11,230 to 10,900years BP. This indicates that deep-sea corals were prolific in the Mediterranean not only during the return to the more glacial-like conditions of the YD, but also following the rapid deglaciation and transition to warmer conditions that followed the end of the YD. Surprisingly, there is a paucity Last Glacial Maximum (LGM) coral ages, implying they were largely absent during this period when cold-water conditions were more prevalent. Radiocarbon ages show that the intermediate depth waters of the Mediterranean generally had increment14C compositions similar to surface waters, indicating that these waters were extremely well ventilated. The only exception is a narrow period in the YD (12,500±100years BP) when several samples of Lophelia pertusa from the Ionian Sea had increment14C values falling significantly below the marine curve. Using a refined approach, isolation ages (τisol) of 300years to 500years are estimated for these intermediate (800-1000m) depth waters relative to surface marine waters, indicating a reduction or absence of deep-water formation in the Ionian and adjacent Adriatic Seas during the YD. Contrary to previous findings, we find no evidence for widespread intrusion of low increment14C Atlantic waters into the Mediterranean. Prolific growth of deep-sea corals in the Mediterranean ended abruptly at 10,900years BP, with many of the coral-bearing mounds on the continental slopes being draped in a thin veneer of mud. Their demise is attributed to a number of factors, including the direct loss of habitat due to high sedimentation that accompanied glacial meltwater pulses, together with rising temperatures that would have finally pervaded the deeper water of the Mediterranean following the onset of Holocene warming. © 2010 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.prolif
Keywords: Deep-sea corals; Demise; Environment; Prolific; U-series dating; Younger Dryas

Promoting origination - Kießling, Wolfgang (Nature Geoscience, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.promot

Proterozoic evolution of the North Atlantic - Arctic Caledonides: Insight from detrital zircon analysis of metasedimentary rocks from the Pearya Terrane, Canadian High Arctic. - Malone, Shawn J.; Mcclelland, William C.; von Gosen, Werner; Piepjohn, Karsten (Journal of Geology, 2014)
The Pearya Terrane, recognized as the only exotic terrane along the Canadian Arctic margin, includes a Neoproterozoic–early Paleozoic basinal or passive-margin metasedimentary sequence that is structurally juxtaposed with arc-related Paleozoic rocks and a metamorphic basement complex containing early Neoproterozoic orthogneiss. The Neoproterozoic siliciclastic sequence is similar to other clastic sections formed at the breakup of Rodinia, but its paleogeographic origin and crustal affinity are uncertain. Detrital zircon age spectra from seven samples reveal three groups: Group A, with numerous peaks at c. 1100–1800 Ma and the youngest population at c. 1020 Ma; Group B, defined by a dominant c. 970 Ma age peak; and Group C, with dominant peaks from c. 970–1800 Ma and a small population of c. 635–710 Ma grains. Spectra from Group A resemble data from the latest Mesoproterozoic units in Svalbard, East Greenland, and the Scandinavian Caledonides, with the ubiquitous Mesoproterozoic ages observed in all these regions compatible with derivation from the Grenville-Sveconorwegian Orogen of Laurentia and Baltica. The dominance of 930–970 Ma ages in Group B reflects input from magmatic rocks of this age in Pearya and Sval-bard, while the 635–710 Ma ages observed in Group C overlap with magmatic ages observed in the Arctic Alaska–Chukotka Terrane and units in the Taimyr-Timanide region. The Neoproterozoic siliciclastic strata of the Pearya Terrane originated distal to northeastern Laurentia, in a position similar to that of the constituent terranes of Svalbard and the Eleonore Bay Supergroup of East Greenland, and they record deposition along a Neoproterozoic convergent margin active during the prolonged breakup of Rodinia.
UnivIS-Import:2015-10-26:Pub.2014.nat.dgeo.IGM.LG.proter

Provenance of Palaeozoic sediments during subduction of Palaeotethys: detrital zircon ages and the analysis of olistoliths from Chios Island, Greece. - Meinhold, Guido; Lehnert, Oliver; Reischmann, Thomas; Kostopoulos, Dimitrios; Matukov, Dmitry; Sergeev, Sergej (Palaeogeography, Palaeoclimatology, Palaeoecology, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dgeo.IGM.LG.proven

Putative ichnogenus Paralanicichnites Ghare and Badve 1981 from the Palaeogene of the Kachchh Basin (India) is a coral - Kulkarni, Kantimati G.; Sikilkar, Namra (Annales Societatis Geologorum Poloniae, 2020)
Structures, reported as the trace fossil, Paralanicichnites conflueris, were described from the Palaeogene rocks of the Kachchh (Kutch) District, Gujarat State, India, by Ghare and Badve as a new ichnogenus and ichnospecies. Restudy of the type specimens revealed that the form described as a burrow in fact is a scleractinian coral, as evidenced by its phaceloid morphology, septate calcareous exoskeleton, and twelve primary septa. It appears that there is also confusion regarding the exact geological formation, from which the specimens under consideration were taken by the original authors, as well as the age assigned by them.
CRIS-Team WoS Importer:2020-09-11

Putting the F into FBD analysis: tree constraints or morphological data? - Barido-Sottani, Joëlle; Pohle, Alexander; De Baets, Kenneth; Murdock, Duncan; Warnock, Rachel (Palaeontology, 2023)
The fossilized birth–death (FBD) process provides an ideal model for inferring phylogenies from both extant and fossil taxa. Using this approach, fossils are directly integrated into the tree, leading to a statistically coherent prior on divergence times. Since fossils are typically not associated with molecular sequences, additional information is required to place fossils in the tree. We use simulations to evaluate two different approaches to handling fossil placement in FBD analyses: using topological constraints, where the user specifies monophyletic clades based on established taxonomy, or using total-evidence analyses, which use a morphological data matrix in addition to the molecular alignment. We also explore how rate variation in fossil recovery or diversification rates impacts these approaches. We find that the extant topology is well recovered under all methods of fossil placement. Divergence times are similarly well recovered across all methods, with the exception of constraints which contain errors. We see similar patterns in datasets which include rate variation, however, relative errors in extant divergence times increase when more variation is included in the dataset, for all approaches using topological constraints, and particularly for constraints with errors. Finally, we show that trees recovered under the FBD model are more accurate than those estimated using non-time calibrated inference. Overall, we show that both fossil placement approaches are reliable even when including uncertainty. Our results underscore the importance of core taxonomic research, including morphological data collection and species descriptions, irrespective of the approach to handling phylogenetic uncertainty using the FBD process.
CRIS-Team Scopus Importer:2023-11-24
Keywords: fossilized birth–death; morphological data; phylogenetic inference; taxonomy; topological constraints; total-evidence

Quantification of wall surface heterogeneity and its influence on species diversity at medieval castles - implications for the environmentally friendly preservation of cultural heritage - Steinbauer, Manuel; Gohlke, Andreas; Mahler, Christine; Schmiedinger, Andreas; Beierkuhnlein, Carl (Journal of Cultural Heritage, 2013)
Historic buildings are important for cultural history and provide a variety of habitats for animals and plants. Especially structural heterogeneity of wall surfaces is perceived to support biological diversity. Nevertheless, in traditional approaches goals of biodiversity preservation and monument restoration are perceived to interfere and to be mutually exclusive. As a consequence, priority is often given to constructional restoration accepting the loss of local populations and biodiversity. At walls of medieval castles, including an experimental restoration project where conventional and less intensive restoration techniques were applied, we relate species composition and richness to wall properties. Especially wall surface structure is quantified using a novel approach. The study focuses on lichens, mosses and vascular plants. Boosted regression tree analyses and non-metric multidimensional scaling techniques are applied to detect the influence of abiotic site conditions on biodiversity. We find species richness to be promoted by wall surface heterogeneity. However, species composition is more affected by restoration approaches than species richness. Lichen composition varies considerably while vascular plants and mosses are less affected by wall properties. We suggest strategies that are combining both societal targets, the preservation of historic monuments and of species diversity. Careful restoration is capable of supporting both, the maintenance of cultural heritage and of rare and unique anthropogenic habitats. Wall surface heterogeneity needs to be witnessed for both aspects as it affects both species composition as well as the effectiveness of cleaning methods.
Keywords: Biodegradation; Biodeterioration; Historic buildings; Monuments; Nature conservation; Wall vegetation

Quantifying the Effects of Changing Deposition Rates and Hiatii on the Stratigraphic Distribution of Fossils - Hohmann, Niklas (2018)
Keywords: Stratigraphy; Paleontology; Statistics; Stratigraphic Paleobiology; Data Processing; Measure Theory; Information Theory

Quantitative analysis of suture lines in Carboniferous ammonoids - Wegerer, Michael; de Baets, Kenneth; Korn, Dieter (FOSSIL RECORD, 2018)
Two morphometric methods are applied and compared for the analysis of suture lines in Early Carboniferous ammonoids of the superfamilies Pericycloidea, Girtyoceratoidea and Goniatitoidea. We analysed (1) classic metric data (proportions of the width and depths or heights of lobes and saddles) using multivariate statistic methods and (2) outline data of the external lobe and the ventrolateral saddle of the same ammonoid taxa using the elliptic Fourier analysis. Both methods lead to similar results and simultaneously demonstrate ontogenetic and phylogenetic trends of these ammonoids. Our results are consistent with three previously suggested evolutionary patterns: (1) a general decrease of the amplitude of lobes and saddles, (2) a proportional widening of the external lobe and (3) a heightening of the median saddl

Quantitative biochronology of Devonian ammonoids from Morocco and proposals for a refined unitary association method - Monnet, Claude; Klug, Christian; Goudemand, Nicolas; de Baets, Kenneth; Bucher, Hugo (Lethaia, 2011)
Based on a rich dataset, the biostratigraphy of the late Emsian and the Eifelian (Early-Middle Devonian) ammonoids from the Moroccan Tafilalt is re-evaluated. We processed this dataset (comprising 53 species from 15 sections) with the unitary association method (UAM), by means of the UA-graph freeware. This led to the construction of a sequence of 17 UAs (maximal sets of actually or virtually coexisting taxa), which are grouped into 10 laterally reproducible association zones. This biostratigraphical subdivision of this interval is in some parts finer than the classically used empirical stratigraphical scheme and than a previous graphic correlation analysis. It enabled us to measure regional ammonoid diversity of this interval in detail. The UAM is a powerful biochronological method, which benefits from complementary tools to analyse conflicting intertaxon stratigraphical relationships inherent to complex biostratigraphical datasets. In cases of under-constrained superpositional relationships between the taxa, the UAM can yield results, which are not parsimonious in terms of reconstructed virtual coexistences. We suggest several additions to complement the algorithmic steps of the method. The most important is the exhaustive or heuristic reconstruction of possible solutions resolving the observed biostratigraphical contradictions (conflicting inter-taxon superpositional relationships and cycles between maximal cliques) and the selection among the solutions of the most-parsimonious one(s) in terms of reconstructed virtual coexistences. Multiple equivalent results may then be processed with standard consensus techniques. Finally, the robustness of the results can be tested by bootstrapping methods to provide confidence estimates on the ranges and associations of studied taxa.
Keywords: Ammonites; Anti-Atlas; biostratigraphy; correlation; zonation; diversity

Radiolarian biodiversity dynamics through the Triassic and Jurassic: implications for proximate causes of the end-Triassic mass extinction - Kocsis, Ádám; Kießling, Wolfgang; Palfy, Jozsef (Paleobiology, 2014)
Within a 60-Myr interval in the Late Triassic to Early Jurassic, a major mass extinction took place at the end of Triassic, and several biotic and environmental events of lesser magnitude have been recognized. Climate warming, ocean acidification, and a biocalcification crisis figure prominently in scenarios for the end-Triassic event and have been also suggested for the early Toarcian. Radiolarians, as the most abundant silica-secreting marine microfossils of the time, provide a control group against marine calcareous taxa in testing selectivity and responses to changing environmental parameters. We analyzed the origination and extinction rates of radiolarians, using data from the Paleobiology Database and employing sampling standardization, the recently developed gap-filler equations and an improved stratigraphic resolution at the substage level. The major end-Triassic event is well-supported by a late Rhaetian peak in extinction rates. Because calcifying and siliceous organisms appear similarly affected, we consider global warming a more likely proximate trigger of the extinctions than ocean acidification. The previously reported smaller events of radiolarian turnover fail to register above background levels in our analyses. The apparent early Norian extinction peak is not significant compared to the long-term trajectory, and is probably a sampling artifact. The Toarcian Oceanic Anoxic Event, previously also thought to have caused a significant radiolarian turnover, did not significantly affect the group. Radiolarian diversity history appears unique and complexly forced, as its trajectory parallels major calcareous fossil groups at some events and deviates at other

Radiolarian biodiversity dynamics through the Triassic and Jurassic: implications for proximate causes of the end-Triassic mass extinction - Kocsis, Adam T.; Kießling, Wolfgang; Palfy, Jozsef (Paleobiology, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.radiol

Radiolarian diversity patterns in the latest Jurassic-earliest Cretaceous - Kießling, Wolfgang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2002)
The global diversity patterns of latest Jurassic-earliest Cretaceous (Tithonian-Berriasian) radiolarian faunas were analyzed based on samples from the European Alps, Oman, Philippines and Antarctica and an extensive literature survey. Several measures of diversity were applied to faunas from tropical (Oman, Mexico, Pacific), subtropical (Alps, California, Philippines, Japan), and subpolar (Antarctic Peninsula, New Zealand, Northern Russia) localities. Original diversity patterns are obscured by taxonomic, sedimentological, and preservational biases. Qualitative and quantitative corrections of these biases indicated a significant diversity gradient from tropical-subtropical to subpolar latitudes, but no significant difference between tropical and subtropical assemblages. The latitudinal diversity gradient was apparently asymmetrical, being steeper in the Northern Hemisphere than in the Southern Hemisphere. In the Southern Hemisphere the diversity gradient was similar to the one observed in modern radiolarian sedimentary assemblages. Considering the more equable climate of the Tithonian-Berriasian, it appears unlikely that temperature was the only control of the observed diversity patterns. The results substantiate the notion of latitudinal diversity gradients as a time-invariant feature of the Earth, possibly driven by gradients in biome size. © 2002 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IGM.LP.radiol
Keywords: Biodiversity; Cretaceous; Jurassic; Paleogeography; Radiolarians

Radiolarian faunal characteristics in Oligocene sediments of the Kerguelen Plateau, Leg 183, Site 1138 - Kießling, Wolfgang; et al. (Proceedings of the Ocean Drilling Program: Scientific Results, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IGM.LP.radiol_7

Ramp morphology controlling the facies differentiation of a Late Ordovician reef complex at Bachu, Tarim Block, NW China - Zhang, Yuandong; Munnecke, Axel; Wang, Jianpo; Lin, Yue (Lethaia, 2015)
A carbonate ramp in the shallow-marine northwestern part of the Central Tarim Uplift, Bachu, NW China, exhibits an extraordinary Late Ordovician reef complex along the Lianglitag Mountains, exposed for a distance of about 25 km. Seven localities within the 'Middle Red Limestone' of the Upper Member of the Lianglitag Formation (Katian, Late Ordovician) illustrated the changes in biofacies and lithofacies: northern, seaward-directed patch reefs are replaced towards the south by coeval grain banks. The patch reef units are dominated by microbial and calcareous algal components. The reefs at the northernmost locality are knoll-shaped, kalyptra-shaped or irregularly shaped with sizes of individual reefs increasing from about 2 m in height and diameter. Stratigraphically upward, reefs notably expand to larger structures by several mounds coalescing; they are generally about 10 m thick and tens of metres in lateral extent. The maximum thickness of the main patch reef is more than 30 m, and its diameter is around 100 m. The reefal units turn into biostromes with gentler relief southward and still further south grade into banks composed of peloids and coated grains. The southernmost locality is still a shallow-water bank, and the coastline is not documented in the study area. The present evidence indicates that the Late Ordovician palaeo-oceanography provided a number of environments for the optimal growth of carbonate build-ups; microbial-calcareous algal communities could thrive in areas where the innovative metazoan reef frameworks consisting of corals and stromatoporoids did not play a significant role. The ramp morphology, especially changes in water depth, controlled the configuration of the reef complex.
Keywords: Bachu; Late Ordovician; Lianglitag Formation; NW China; Reef complex; Tarim Block

Reading traces of the past - the Burghöhle Wolfsegg as meeting place for humans, cave lions and co. Spurenlesen in der Vergangenheit - die Burghohle Wolfsegg als Treffpunkt fur Mensch, Hohlenlowe und Co. - Hilpert, Brigitte (Mitteilungen - Verbandes der Deutschen Hohlen- und Karstforscher, 2023)
On the occasion of a tour into the "Burghohle Wolfsegg" in the Franconian Alb (Bavaria), the castle complex was also visited. The faunal remains found there originate from various sites in the cave and are described for the first time. A faunal complex was excavated from the Barenkeller in 1985. The fauna determined here with brown bear (Ursus arctos), cave bear (Ursus spelaeus), cave lion (Panthera leo spelaea) as well as some herbivores can be placed in a rather cool to cold climatic phase of the late Pleistocene around 60,000 - 20,000 years BP. Of particular note is an upper arm bone of a cave lion on which cut marks were found. This is the first such evidence for a cave in the Franconian Alb. Some cut and impact marks on other bones also prove the presence of humans and their impact on animal carcasses or hunted prey. All the material shows traces of various transport phases that led via a former cave room and a shaft step to its current site. At the Rittersaal site, finds were recovered in the 1980s and 1990s. The fauna consists of various domestic animals such as cattle, pigs, sheep/goats, horses and dogs. Wild animals such as red deer (Cervus elaphus) and some predators also occur. Accompanying finds such as pottery shards, a barrel stopper and other human remains prove that the finds can be considered as kitchen waste of the Middle Ages and more recent periods. In 2018, further finds were recovered during the removal of a pile of earth on the wall of the castle building, which are likely to date from the 15th - 17th centuries. In addition to pottery sherds, the find complex consists of fragmented bones of cattle, pig, sheep/goat and horse, with evidence of red deer alongside. Traces of the cutting of the carcasses suggest an interpretation as kitchen waste.
CRIS-Team Scopus Importer:2023-09-22

Rebuilding biodiversity of Patagonian marine molluscs after the end-Cretaceous mass extinction - Aberhan, Martin; Kießling, Wolfgang (PLoS ONE, 2014)
We analysed field-collected quantitative data of benthic marine molluscs across the Cretaceous-Palaeogene boundary in Patagonia to identify patterns and processes of biodiversity reconstruction after the end-Cretaceous mass extinction. We contrast diversity dynamics from nearshore environments with those from offshore environments. In both settings, Early Palaeogene (Danian) assemblages are strongly dominated by surviving lineages, many of which changed their relative abundance from being rare before the extinction event to becoming the new dominant forms. Only a few of the species in the Danian assemblages were newly evolved. In offshore environments, however, two newly evolved Danian bivalve species attained ecological dominance by replacing two ecologically equivalent species that disappeared at the end of the Cretaceous. In both settings, the total number of Danian genera at a locality remained below the total number of late Cretaceous (Maastrichtian) genera at that locality. We suggest that biotic interactions, in particular incumbency effects, suppressed post-extinction diversity and prevented the compensation of diversity loss by originating and invading taxa. Contrary to the total number of genera at localities, diversity at the level of individual fossiliferous horizons before and after the boundary is indistinguishable in offshore environments. This indicates an evolutionary rapid rebound to pre-extinction values within less than ca 0.5 million years. In nearshore environments, by contrast, diversity of fossiliferous horizons was reduced in the Danian, and this lowered diversity lasted for the entire studied post-extinction interval. In this heterogeneous environment, low connectivity among populations may have retarded the recolonisation of nearshore habitats by survivors. © 2014 Aberhan, Kiessling.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LP.rebuil

Recent advances in heteromorph ammonoid palaeobiology - Hoffmann, René; Slattery, Joshua S.; Kruta, Isabelle; Linzmeier, Benjamin J.; Lemanis, Robert E.; Mironenko, Aleksandr; Goolaerts, Stijn; de Baets, Kenneth; Peterman, David J.; Klug, Christian (Biological Reviews, 2021)
Heteromorphs are ammonoids forming a conch with detached whorls (open coiling) or non-planispiral coiling. Such aberrant forms appeared convergently four times within this extinct group of cephalopods. Since Wiedmann's seminal paper in this journal, the palaeobiology of heteromorphs has advanced substantially. Combining direct evidence from their fossil record, indirect insights from phylogenetic bracketing, and physical as well as virtual models, we reach an improved understanding of heteromorph ammonoid palaeobiology. Their anatomy, buoyancy, locomotion, predators, diet, palaeoecology, and extinction are discussed. Based on phylogenetic bracketing with nautiloids and coleoids, heteromorphs like other ammonoids had 10 arms, a well-developed brain, lens eyes, a buccal mass with a radula and a smaller upper as well as a larger lower jaw, and ammonia in their soft tissue. Heteromorphs likely lacked arm suckers, hooks, tentacles, a hood, and an ink sac. All Cretaceous heteromorphs share an aptychus-type lower jaw with a lamellar calcitic covering. Differences in radular tooth morphology and size in heteromorphs suggest a microphagous diet. Stomach contents of heteromorphs comprise planktic crustaceans, gastropods, and crinoids, suggesting a zooplanktic diet. Forms with a U-shaped body chamber (ancylocone) are regarded as suspension feeders, whereas orthoconic forms additionally might have consumed benthic prey. Heteromorphs could achieve near-neutral buoyancy regardless of conch shape or ontogeny. Orthoconic heteromorphs likely had a vertical orientation, whereas ancylocone heteromorphs had a near-horizontal aperture pointing upwards. Heteromorphs with a U-shaped body chamber are more stable hydrodynamically than modern Nautilus and were unable substantially to modify their orientation by active locomotion, i.e. they had no or limited access to benthic prey at adulthood. Pathologies reported for heteromorphs were likely inflicted by crustaceans, fish, marine reptiles, and other cephalopods. Pathologies on Ptychoceras corroborates an external shell and rejects the endocochleate hypothesis. Devonian, Triassic, and Jurassic heteromorphs had a preference for deep-subtidal to offshore facies but are rare in shallow-subtidal, slope, and bathyal facies. Early Cretaceous heteromorphs preferred deep-subtidal to bathyal facies. Late Cretaceous heteromorphs are common in shallow-subtidal to offshore facies. Oxygen isotope data suggest rapid growth and a demersal habitat for adult Discoscaphites and Baculites. A benthic embryonic stage, planktic hatchlings, and a habitat change after one whorl is proposed for Hoploscaphites. Carbon isotope data indicate that some Baculites lived throughout their lives at cold seeps. Adaptation to a planktic life habit potentially drove selection towards smaller hatchlings, implying high fecundity and an ecological role of the hatchlings as micro- and mesoplankton. The Chicxulub impact at the Cretaceous/Paleogene (K/Pg) boundary 66 million years ago is the likely trigger for the extinction of ammonoids. Ammonoids likely persisted after this event for 40–500 thousand years and are exclusively represented by heteromorphs. The ammonoid extinction is linked to their small hatchling sizes, planktotrophic diets, and higher metabolic rates than in nautilids, which survived the K/Pg mass extinction event.
CRIS-Team Scopus Importer:2021-01-22
Keywords: anatomy; cephalopods; facies distribution; geochemistry; heteromorph ammonoids; palaeobiology

Recognition of the Boda event in the Pin Formation of northern India based on new d13C and conodont data. - Buggisch, Werner; Lehnert, Oliver; Joachimski, Michael; et al. (Acta Palaeontologica Sinica, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LG.recogn

Reconstructing Depositional Rates and Their Effect on Paleoenvironmental Proxies: The Case of the Lau Carbon Isotope Excursion in Gotland, Sweden - Jarochowska, Emilia; Nohl, Theresa; Grohganz, Madleen; Hohmann, Niklas; Vandenbroucke, Thijs; Munnecke, Axel (Paleoceanography and Paleoclimatology, 2020)
Variations in depositional rates affect the temporal depositional resolutions of proxies used for paleoenvironmental reconstructions; for example, condensation can make reconstructed environmental changes appear very abrupt. This is commonly addressed by transforming proxy data using age models, but this approach is limited to situations where numerical ages are available or can be reliably inferred by correlation. Here we propose a new solution, in which relative age models are constructed based on proxies for depositional rates. As a case study, we use the onset of the late Silurian Lau Carbon Isotope Excursion (LCIE) in Gotland, Sweden. The studied succession is a gradual record of shallowing upward in a tropical, neritic carbonate platform. As proxies for depositional rates we tested thorium concentration, carbonate content, and the concentration of pelagic palynomorphs. These three proxies were used to create relative age models using the previously published DAIME model. We applied these models to transform the δ13Ccarb values as well as concentrations of selected redox‐sensitive elements. The three relative age models yielded qualitatively similar results. In our case study, variations in depositional rates resulted in peaks of redox proxies appearing up to 76% higher when taken at face value, compared to when accounting for these rates. In the most extreme cases, our corrections resulted in a reversal in the stratigraphic trend of elemental concentrations. This approach can be applied and developed across depositional setting and types of paleoenvironmental proxies. It provides a flexible tool for developing quantitative models to improve our understanding of the stratigraphic record.<br

Reconstructing the environmental conditions around the Silurian Ireviken Event using the carbon isotope composition of bulk and palynomorph organic matter - Vandenbroucke, Thijs R.A.; Munnecke, Axel; Leng, Melanie J.; Bickert, Torsten; Hints, Olle; Gelsthorpe, David; Maier, Georg; Servais, Thomas (Geochemistry Geophysics Geosystems, 2013)
The carbon isotope composition (δ13C) of bulk organic matter and two palynomorph groups (scolecodonts and chitinozoans) from the Llandovery-Wenlock strata of Gotland (E Sweden) are compared to gain knowledge about carbon cycling in the Silurian (sub)tropical shelf environment. The δ13C values of the palynomorphs are mostly lower than the δ13C values of the bulk organic matter, and the δ13C values of the benthic scolecodonts are lower than those of the planktonic chitinozoans. While the difference between bulk and palynomorph δ13C may be in part a function of trophic state, the lower values of the scolecodonts relative to those of chitinozoans, which are assumed to live in the well-mixed water column, might imply an infaunal mode of life for the polychaetes that carried the scolecodonts. Lower δ13C for the scolecodonts in the middle of the section may represent variations in primary marine productivity (supported by acritarch abundance data), oxidation of organic matter in the bottom waters, or genera effects. In general, however, trends between the three data sets are parallel, indicating similarities in the low frequency, environmentally forced controls. The δ13C data show a decreasing trend from the base of the section, up to a horizon well below the base of the Upper Visby Formation. At this level, and therefore probably several 10 kyr before the δ13C increase in the carbonates, the δ13C organic values increase by ∼1‰. This perhaps is an expression of a changed composition of the bulk organic matter associated with the extinction events prior to the Llandovery-Wenlock boundary. ©2013. American Geophysical Union. All Rights Reserve
Keywords: bulk organic matter; carbon isotopes; chitinozoans; Gotland; Llandovery-Wenlock; scolecodonts; trophic chain

Reconstructing time and diagenesis of limestone-marl alternations from the selective compaction of colonies of the tabulate coral Halysites - Nohl, Theresa; Munnecke, Axel (Bulletin of Geosciences, 2019)

Reconstruction of the trophic levels of a fossil fish community from the Late Jurassic Solnhofen Archipelago - Dimitrijevic, Danijela; Ebert, Martin; Kölbl-Ebert, Martina; Munnecke, Axel (EGU 2020, 2020)
Trophic interactions of extinct fishes are central to our understanding of evolution, paleoecology, and their role in the paleo communities, but can be challenging, as these are limited by the incompleteness of the fossil record and by a lack of behavioral data. The extensive fossil record of Actinopterygii comes mostly from Conservation deposits. They provide exceptionally rich information on fossil ecosystems and open outstanding windows into the evolution of life. The best-preserved Late Jurassic actinopterygians are known from the Solnhofen Archipelago, Germany. Despite that the ichthyofauna diversity of the Solnhofen Archipelago has been extensively explored in the last several decades, the dietary preferences of most fish remain unknown or have to be deduced by analogy from dentition and jaw morphology. The aim of this study was to reconstruct the trophic levels of Late Jurassic fish assemblages using Sr / Ca and Ba / Ca measured from phosphatic fish remains, mostly ganoin and cycloid scales recovered from the Ettling locality, which is characterized by exceptionally well-preserved fossil fishes and moderate diagenetic alteration. We classified fish species into four trophic levels (durophagous, lower, middle, and higher trophic level) based on morphology available from the literature. Mean values ​​of Sr, Ca, Ba and their ratios measured by Thermo Scientific iCAP Q inductively coupled plasma mass spectrometer in this study are in accordance with the mean values ​​of previous studies. Differences in values ​​between cleaned and uncleaned samples showed that the cleaning process successfully isolated primary dietary Sr content while dissolving away the diagenetic strontium present in carbonate in the pore spaces. All trophic levels showed low variation of Sr / Ca (0.003 - 0.008 μg / g) and high variation of Ba / Ca values ​​(0.0003 - 0.0014 μg / g). The results showed significant differences between the middle and higher trophic levels (p = 0.03), while durophagous and lower trophic levels fell into the same range of values ​​as the higher trophic level. We demonstrate that the enamel of fossil vertebrates from the Solnhofen Archipelago still contains near-in vivo Sr, Ba, and Ca. The clear distinction between middle and higher trophic levels offers a new functional perspective on the ecological and evolutionary relationships among fishes. However, future studies should not neglect the importance of diagenetic alteration of the samples; proper sample cleaning before measuring isotopic signatures, and careful selection of the analyzed tissue (ie tooth enamel instead of scales or bones due to its resistance to diagenesis).<br

Red Devonian trilobites with green eyes from Morocco and the silicification of the trilobite exoskeleton - Klug, Christian; Schulz, Hartmut; de Baets, Kenneth (Acta Palaeontologica Polonica, 2009)
Latest Emsian (Early Devonian) sediments at the famous mud-mound- and trilobite-locality Hamar Laghdad (Tafilalt, Morocco) yielded some red-coloured remains of phacopid trilobites. Closer examination revealed that the eyes of these phacopids are often greenish in colour. EDX-analyses showed that the lenses retained their original calcitic composition, possibly greenish due to Fe- and Mn-impurities, while most of the exoskeleton was silicified. The silicified parts contain elevated concentrations of iron which causes the red colour. This phenomenon is explained by the porosity of the exoskeleton in contrast to the homogeneous and massive construction of the lenses and their Mg-content. These incompletely silicified trilobites enabled a reconstruction of the silicification process in trilobites. Their diagenetic alteration probably occurred as a result of events associated with the Cretaceous transgression.
Keywords: Trilobita; taphonomy; diagenesis; silicification; transgression; mud-mounds; Devonian; Morocco

Re-description and neotypification of Archamphiroa jurassica Steinmann 1930, a calcareous red alga from the Jurassic of Argentina - Bucur, Ioan I.; Kießling, Wolfgang; Scasso, Roberto A. (Journal of Paleontology, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.redesc

Reducing taxonomic noise in problematic fossils: Revision of the incertae sedis genus allonema based on shape analysis - Jarochowska, Emilia; Hierl, Florian; Vinn, Olev; Munnecke, Axel (Bulletin of Geosciences, 2016)
Organisms of unknown biological affinity are widespread in Paleozoic ecosystems and play key ecological roles. Recognition of these roles relies on consistent identification and sound taxonomy, yet many microproblematica lack complex morphological features that could be the basis for qualitative taxonomic diagnoses. Allonema is an incertae sedis calcareous sclerobiont widespread in Paleozoic carbonates. At least seven species of Allonema have been proposed, but their diagnoses based on size ranges overlap. In this work, dimensions of 590 individuals from the Silurian of Estonia and Sweden have been measured. Regression analysis of the dimensions revealed two groups, overlapping in size ranges, but differing significantly in proportions. These groups could be matched with previously described A. botellus and A. moniliforme, but both showed a wider range of sizes than previously reported. Another previously described species, A. minimum, fell within the range of dimensions of A. moniliforme and is proposed to be its junior synonym. Differences in proportions revealed in the study do not seem to be dependent on sedimentary environment or local growth conditions such as competition for space, and thus may represent consistent interspecific variability. Although the affinity of Allonema remains unknown, this quantitative approach to its taxonomy reduces unnecessary species in the genus. The success of this approach may encourage its application to other microproblematica populating the fossil record.
Keywords: Baltica; Devonian; Encrusters; Microproblematica; Pseudobryozoans; Sclerobionts; Wetheredella

Reef-building red algae from an uppermost Permian reef complex as a fossil analogue of modern coralline algal ridges - Chen, Weihan; Wang, Yongbiao; Huang, Yafei; Wang, Tan; Yi, Zhixing; Kießling, Wolfgang (Facies, 2020)
Calcareous red algae have been important components in reefal facies since the Mesozoic but their volumetric contribution to Palaeozoic reefs was usually low. Here, we report a reef-building community dominated by Parachaetetes, a genus of solenoporacean red algae, overgrowing uppermost Permian sponge reefs in Cili (Hunan Province, South China). The fossil assemblage in the community consists of about 88% Parachaetetes, 7% rugose corals, and 5% reef-dwelling organisms, including gastropods, brachiopods, foraminifera and Tubiphytes. Although the biodiversity of this community is far lower than that in modern reefs, the association of red algae and rugose corals shares several attributes with the coral–coralline algal communities of modern tropical reefs. Analysis of sedimentary facies indicates that the reef-building Parachaetetes grew in a turbulent setting near the margin of a carbonate platform, perhaps in a reef-crest environment known from modern coralgal reefs. Although calcifying red algae have been recorded from the Cambrian onwards, this is the oldest site where crustose red algae played a dominant role in reef construction.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Late Permian; Palaeoecology; Reef; Rugose coral; Solenoporacean; South china

Reef expansion during the Triassic: Spread of photosymbiosis balancing climatic cooling - Kießling, Wolfgang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
The PaleoReefs Database indicates that reef abundance increased profoundly during the Triassic period, from a pronounced low in the Early Triassic to a major peak in the Norian. This expansion is also evident when standardizing for sampling. Corresponding to the reef expansion is a relative increase of scleractinian corals as reef builders, whereas the contribution of hypercalcifying sponges and microbes decreased during the Triassic. The numerical expansion of corals is paralleled by a proportional increase of morphological features that are suggestive of photosymbiosis, such that the Norian reef boom might be explained by the spread of photosymbiosis in corals. The geographical expansion of reefs was far less pronounced especially concerning palaeolatitude. Late Triassic reef growth was limited to more or less the same latitudinal range as modern reefs. As oxygen isotope data and new modeling results indicate declining temperatures and CO2 concentrations during the Late Triassic, the lack of latitudinal expansion might be attributed to global cooling. Reef development during the Triassic can thus be explained by the evolutionary spread of photosymbiosis balancing the effects of climatic cooling. © 2009 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.reefex
Keywords: Climate; Corals; Evolution; Photosymbiosis; Reefs; Triassic

Reef Fish Beware! Aggressive Mimicry in a Pycnodontid? - Kölbl-Ebert, Martina; Ebert, Martin; Bellwood, David R.; Schulbert, Christian (Abstracts of the 90th Annual Meeting of the Paläontologische Gesellschaft, 2019)
Pycnodontiformes are an extinct order of Actinopterygian fishes, present from the Late Triassic (Norian) to the Eocene. Their mostly deep, laterally compressed bodies and comparatively large fins indicate that these fishes were mostly highly manoeuvrable reef fish. With their characteristic durophagous dentition, columnar to incisiform anterior teeth (on premaxilla and dentary) and the posterior crushing teeth of the prearticular and vomer, the whole group was highly specialized as predators on hard-shelled organisms. In 2016, however, a new pycnodontid was found in the quarry of Ettling (Markt Pförring, Bavaria; Late Jurassic) by the excavation team of the Jura-Museum Eichstätt. The most striking feature of this new pycnodontid, Piranhamesodon pinnatomus Kölbl-Ebert et al., 2018 (JME-ETT4103), is its unusual dentition: It has long, pointed teeth at the front (on premaxilla and dentary), dagger-shaped teeth with a sharp, posterior cutting edge along the exterior-most tooth row of the vomer, and triangular teeth with serrations on their anterior margin along the exterior-most tooth row of the prearticulars. As revealed by CT-scanning, the inner teeth of prearticular and vomer are limpet-shaped cones on a columnar tooth base. The “fangs” along the exterior-most tooth row of the prearticulars and vomer of Piranhamesodon pinnatomus interact like scissors; a comparison of their functional morphology with other actinopterygians stress the exceptional high bite-force (a legacy of their pycnodont ancestry), which is comparable to modern piranhas, suggesting a completely unusual mode of predation compared to all other known pycnodontids. We propose this species to have exploited aggressive mimicry: Seemingly harmless and inconspicuous through the typical pycnodontid shape and possibly aided by corresponding colouring, it may have approached and then attacked unsuspecting other fish in the reef, biting and tearing a mouthful of flesh or fin from their unwary prey. Alternatively, it may also have acted at least occasionally as scavenger.<br
Keywords: Pycnodontiformes; Piranhamesodon; Late Jurassic; Ettling

Reefmounds im unteren Wenlock auf Gotland: Beispiele früher Korallenriffe - Samtleben, Christian; Munnecke, Axel (Meyniana, 1999)
Die Reefmounds im unteren Wenlock auf Gotland sind im doppelten Sinne Riffe in einem Frühstadium: Einerseits bilden sie die erste Phase in der Entwicklung der silurischen Riffkomplexe auf Gotland, andererseits stellen sie in der erdgeschichtlichen Entwicklung moderner Korallenriffe ein Beispiel früher Riffbildungen mit einer nur wenig ausgebildeten Internstruktur und Synökologie dar.   The reefmounds in the Lower Wenlockian of Gotland represent in a twofold sense early stages of reef development. On the one hand, they form the first stage in the development of the reef succession on Gotland, on the other hand, they are early examples of reef formation in the geological history of coral reefs, lacking important criteria of modern reefs like strict internal structure, framework, and complex synecology.
Keywords: Reefmounds; Silurian; Gotland; Cnidaria

Reefs as cradles of evolution and sources of biodiversity in the Phanerozoic - Kießling, Wolfgang; Simpson, Carl; Foote, Michael (Science, 2010)
Large-scale biodiversity gradients among environments and habitats are usually attributed to a complex array of ecological and evolutionary factors. We tested the evolutionary component of such gradients by compiling the environments of the geologically oldest occurrences of marine genera and using sampling standardization to assess if originations tended to be clustered in particular environments. Shallow, tropical environments and carbonate substrates all tend to have harbored high origination rates. Diversity within these environments tended to be preferentially generated in reefs, probably because of their habitat complexity. Reefs were also prolific at exporting diversity to other environments, which might be a consequence of low-diversity habitats being more susceptible to invasions.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.reefsa

Reefs - Kießling, Wolfgang (Encyclopedia of Sediments and Sedimentary Rocks, 2003)
UnivIS-Import:2015-04-20:Pub.2003.nat.dgeo.IGM.LP.reefs

Re-evaluating the general dynamic theory of oceanic island biogeography - Steinbauer, Manuel; Dolos, Klara; Field, Richard; Reineking, Björn; Beierkuhnlein, Carl (Frontiers of Biogeography, 2013)
The general dynamic model of oceanic island biogeography integrates temporal changes in ecological circumstances with diversification processes, and has stimulated current research in island biogeography. In the original publication, a set of testable hypotheses was analysed using regression models: specifically, whether island data for four diversity indices are consistent with the ‘B ATT2’ model, in which B is a diversity index, A is log(area) and T is time. The four indices were species richness, the number and percentage of single‐island endemic species, and a diversification index. Whether the relationships between these indices and time are unimodal (i.e., ‘hump‐shaped’) was a key focus, based on the characteristic ontogeny of a volcanic oceanic island. However, the significance testing unintentionally used zero, rather than the mean of the diversity index, as the null hypothesis, greatly inflating F‐ values and reducing P‐values compared with the standard regression approach. Here we first re‐analyze the data used to evaluate the general dynamic model in the seminal paper, using the standard null hypothesis, to provide an important qualification of its empirical results. This supports the significance of about half the original tests, the rest becoming non‐significant but mostly suggestive of the hypothesized relationship. Then we expand the original analysis by testing additional, theoretically derived functional relationships between the diversity indices, island area and time, within the framework of the ATT2 model and using a mixed‐effects modelling approach. This shows that species richness peaks earlier in island life‐cycles than endemism. Area has a greater effect on species richness and the number of single‐island endemics than on the proportion of single‐island endemics and the diversification index, and was always better fit as a log–log relationship than as a semi‐log one. Finally, the richness–time relationship is positively skewed, the initial rise happening much more quickly than the later decline.

Regional geology of the Skåne province, Sweden - Calner, Mikael; Erlström, Mikael; Eriksson, Mats; Lehnert, Oliver; Ahlberg, Per (The Lower Palaeozoic of southern Sweden and the Oslo Region, Norway. Field Guide for the 3rd Annual Meeting of the IGCP project 591., 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LG.lowerp

Regional geology of the Västergötland province, Sweden - Ahlberg, Per; Calner, Mikael; Lehnert, Oliver; Wickström, Linda (The Lower Palaeozoic of southern Sweden and the Oslo Region, Norway. Field Guide for the 3rd Annual Meeting of the IGCP project 591., 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LG.region

Regionalization of precipitation in Mauritius: a statistical approach - Raja, Nussaïbah Begum; Aydin, Olgu (Meteorological Applications, 2019)
The aim of this study was to quantify the regional precipitation patterns of Mauritius using the total mean annual precipitation of 52 meteorological stations for the period 1981–2010. Principal component analysis was first used to determine the significant variables influencing precipitation in Mauritius. A cluster analysis was then applied to group the stations according to the significant variables identified. Finally, a spatial interpolation of precipitation in Mauritius using the kriging with external drift technique was carried out to examine the spatial distribution of precipitation on the island. The principal component analysis results showed that elevation and coastal proximity caused the most variance in the dataset with respect to precipitation. Using the cluster analysis and kriging results, six regions of precipitation were determined: three inland and three coastal regions. A decreasing gradient in precipitation between the southeast and northwest is observed due to the southeast trade winds and the altitudinal difference between the coastal areas and the central plateau. The central plateau represents a distinct precipitation zone which receives the highest precipitation on the island. The windward-facing south and eastern highlands experience orographic precipitation as a result of adiabatic air expansion and therefore are more humid. On the other hand, the northeast highlands region, together with the north and western coasts which lie in the leeward rain shadow, are notably drier.
CRIS-Team Scopus Importer:2019-07-02
Keywords: cluster analysis (CA); kriging; Mauritius; precipitation; principal component analysis (PCA); regional precipitation pattern

Reliable estimates of beta diversity with incomplete sampling - Roden, Vanessa; Kießling, Wolfgang (GSA Annual Meeting in Seattle, Washington, USA - 2017, 2017)

Reliable estimates of beta diversity with incomplete sampling - Roden, Vanessa; Kocsis, Ádám; Zuschin, Martin; Kießling, Wolfgang (Ecology, 2018)
Beta diversity, the compositional variation among communities or assemblages, is crucial to understanding the principles of diversity assembly. The mean pairwise proportional dissimilarity expresses overall heterogeneity of samples in a data set and is among the most widely used and most robust measures of beta diversity. Obtaining a complete list of taxa and their abundances requires substantial taxonomic expertise and is time consuming. In addition, the information is generally incomplete due to sampling biases. Based on the concept of the ecological significance of dominant taxa, we explore whether determining proportional dissimilarity can be simplified based on dominant species. Using simulations and six case studies, we assess the correlation between complete community compositional data and reduced subsets of a varying number of dominant species. We find that gross beta diversity is usually depicted accurately when only the 80th percentile or five of the most abundant species of each site is considered. In data sets with very high evenness, at least the 10 most abundant species should be included. Focusing on dominant species also maintains the rank-order of beta diversity among sites. Our new approach will allow ecologists and paleobiologists to produce a far greater amount of data on diversity patterns with less time and effort, supporting conservation studies and basic scienc
Keywords: beta diversity; Bray-Curtis dissimilarity; community composition; distance matrices; dominant species; heterogeneity; proportional dissimilarity; sampling

Remarks on the Permian dasycladalean alga Sinoporella leei Yabe, 1949 - Bucur, Ioan I.; Munnecke, Axel; Granier, Bruno; Yan, Jiaxin (Geobios, 2009)
Sinoporella leei was first described and illustrated by Yabe in 1949 as a new species and was ascribed to a new subgenus of the genus Triploporella (Steinmann). This alga was not illustrated again until Mu published 25-years later a photomicrograph of a longitudinal-tangential section. The recent finding of new specimens in Permian strata of the Guangxi region (South China) allows us to better illustrate this alga, and to improve our understanding of its morphology to the extent that we find it necessary to emend the current diagnosis. The new observations focus mainly on the morphology of the second-order laterals, on their relationship to the first-order laterals, and the connection of the first-order laterals to the main stem. These data suggest that Sinoporella represents a self-standing, discrete genus that differs from Triploporella. We also consider the lack of cystophores (cyst containers sensu De Castro) and the possible occurrence of individual cysts in the first order laterals as characteristics that do not accord with Barttolo's emended diagnosis of Triploporella. © 2009 Elsevier Masson SAS. All rights reserved.
Keywords: Dasycladalean alga; Permian; Sinoporella; First description

Resilience of cold-water scleractinian corals to ocean acidification: Boron isotopic systematics of pH and saturation state up-regulation - McCulloch, Malcolm; Trotter, Julie; Montagna, Paolo; Falter, Jim; Dunbar, Robert; Freiwald, André; Försterra, Günter; López Correa, Matthias; Maier, Cornelia; Rüggeberg, Andres; Taviani, Marco (Geochimica Et Cosmochimica Acta, 2012)
The boron isotope systematics has been determined for azooxanthellate scleractinian corals from a wide range of both deep-sea and shallow-water environments. The aragonitic coral species, Caryophyllia smithii, Desmophyllum dianthus, Enallopsammia rostrata, Lophelia pertusa, and Madrepora oculata, are all found to have relatively high δ 11B compositions ranging from 23.2‰ to 28.7‰. These values lie substantially above the pH-dependent inorganic seawater borate equilibrium curve, indicative of strong up-regulation of pH of the internal calcifying fluid (pH cf), being elevated by 0.6-0.8units (ΔpH) relative to ambient seawater. In contrast, the deep-sea calcitic coral Corallium sp. has a significantly lower δ 11B composition of 15.5‰, with a corresponding lower ΔpH value of 0.3units, reflecting the importance of mineralogical control on biological pH up-regulation.The solitary coral D. dianthus was sampled over a wide range of seawater pH T and shows an approximate linear correlation with ΔpH Desmo=6.43-0.71pH T (r 2=0.79). An improved correlation is however found with the closely related parameter of seawater aragonite saturation state, where ΔpH Desmo=1.09-0.14Ω arag (r 2=0.95), indicating the important control that carbonate saturation state has on calcification. The ability to up-regulate internal pH cf, and consequently Ω cf, of the calcifying fluid is therefore a process present in both azooxanthellate and zooxanthellate aragonitic corals, and is attributed to the action of Ca 2+-ATPase in modulating the proton gradient between seawater and the site of calcification. These findings also show that the boron isotopic compositions (δ 11B carb) of aragonitic corals are highly systematic and consistent with direct uptake of the borate species within the biologically controlled extracellular calcifying medium.We also show that the relatively strong up-regulation of pH and consequent elevation of the internal carbonate saturation state (Ω cf 8.5 to 13) at the site of calcification by cold-water corals, facilitates calcification at or in some cases below the aragonite saturation horizon, providing a greater ability to adapt to the already low and now decreasing carbonate ion concentrations. Although providing greater resilience to the effects of ocean acidification and enhancing rates of calcification with increasing temperature, the process of internal pH cf up-regulation has an associated energetic cost, and therefore growth-rate cost, of 10% per 0.1 pH unit decrease in seawater pH T. Furthermore, as the aragonite saturation horizon shoals with rapidly increasing pCO 2 and Ω arag<1, increased dissolution of the exposed skeleton will ultimately limit their survival in the deep oceans. © 2012 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.resili
Keywords: ocean acidification; coral calcification; biomineralization

Response - Kießling, Wolfgang (Science, 2010)

Response of an Arctic calcifying macro alga to increasing CO2 and temperature Levels: A habitat at risk? - Büdenbender, Jan; Hellemann, D.; Teichert, Sebastian; Stange, P.; Form, Armin; Riebesell, U. (EPOCA Final meeting, 2012)

Response of Siliceous Marine Organisms to the Permian-Triassic Climate Crisis Based on New Findings From Central Spitsbergen, Svalbard - Foster, W. J.; Asatryan, G.; Rauzi, S.; Botting, J. P.; Buchwald, S. Z.; Lazarus, D. B.; Isson, T.; Renaudie, J.; Kießling, Wolfgang (Paleoceanography and Paleoclimatology, 2023)
Siliceous marine ecosystems play a critical role in shaping the Earth's climate system by influencing rates of organic carbon burial and marine authigenic clay formation (i.e., reverse weathering). The ecological demise of silicifying organisms associated with the Permian-Triassic mass extinction is postulated to have elevated marine authigenic clay formation rates, resulting in a prolonged greenhouse climate during the Early Triassic. Yet, our understanding of the response of siliceous marine organisms during this critical interval is poor. Whilst radiolarians experienced the strongest diversity loss in their evolutionary history and perhaps also the greatest population decline of silica-secreting organisms during this event, only a small number of Griesbachian (post-extinction) localities that record siliceous organisms are known. Here, we report newly discovered latest Changhsingian to early Griesbachian (Clarkina meishanensis - Hindeodus parvus Zone) radiolarians and siliceous sponge spicules from Svalbard. This fauna documents the survival of a low-diversity radiolarian assemblage alongside stem-group hexactinellid sponges making this the first described account of post-extinction silica-secreting organisms from the Permian/Triassic boundary in a shallow marine shelf environment and a mid-northern paleolatitudinal setting. Our findings indicate that latitudinal diversity gradients for silica-secreting organisms following the mass extinction were significantly altered, and that silica productivity was restricted to high latitude and deep water thermal refugia. This result has potential to further shape our understanding of changes in marine dissolved silica levels and in turn rates of reverse weathering, with implications for our understanding of carbon cycle dynamics during this interval.
CRIS-Team Scopus Importer:2023-12-15
Keywords: climate response; hexactinellids; Permian-Triassic; radiolarians; thermal stress

Response to comments on "Statistical independence of escalatory ecological trends in Phanerozoic marine invertebrates - Kießling, Wolfgang; et al. (Science, 2006)
UnivIS-Import:2015-04-14:Pub.2006.nat.dgeo.IGM.LP.respon

REVEALING THE GENESIS OF LIMESTONE-MARL ALTERNATIONS: A TAPHONOMIC APPROACH - Nohl, Theresa; Jarochowska, Emilia; Munnecke, Axel (Palaios, 2019)

Revised correlation of Silurian Provincial Series of North America with global and regional chronostratigraphic units and δ13Ccarb chemostratigraphy - Cramer, Bradley D.; Brett, Carlton E.; Melchin, Michael J.; Männik, Peep; Kleffner, Mark A.; Mclaughlin, Patrick I.; Loydell, David K.; Munnecke, Axel; Jeppsson, Lennart; Corradini, Carlo; Brunton, Frank R.; Saltzman, Matthew Ross (Lethaia, 2011)
Recent revisions to the biostratigraphic and chronostratigraphic assignment of strata from the type area of the Niagaran Provincial Series (a regional chronostratigraphic unit) have demonstrated the need to revise the chronostratigraphic correlation of the Silurian System of North America. Recently, the working group to restudy the base of the Wenlock Series has developed an extremely high-resolution global chronostratigraphy for the Telychian and Sheinwoodian stages by integrating graptolite and conodont biostratigraphy with carbonate carbon isotope (δC) chemostratigraphy. This improved global chronostratigraphy has required such significant chronostratigraphic revisions to the North American succession that much of the Silurian System in North America is currently in a state of flux and needs further refinement. This report serves as an update of the progress on recalibrating the global chronostratigraphic correlation of North American Provincial Series and Stage boundaries in their type area. The revised North American classification is correlated with global series and stages as well as regional classifications used in the United Kingdom, the East Baltic, Australia, China, the Barrandian, and Altaj. Twenty-four potential stage slices, based primarily on graptolite and conodont zones and correlated to the global series and stages, are illustrated alongside a new composite δC curve for the Silurian. Conodont, graptolite, isotope, New York, Ontario, series, Silurian, stage. © 2010 The Authors, Journal compilation © 2010 The Lethaia Foundatio
Keywords: Chronostratigraphy; Silurian; Provincial Series; δ13C; Chemostratigraphy

Revisiting reef models in the Oligocene of northern Italy (Venetian Southern Alps) - Bosellini, Francesca R.; Vescogni, Alessandro; Kießling, Wolfgang; Zoboli, Alessandro; Di Giuseppe, Dario; Papazzoni, Cesare Andrea (Bollettino Della Societa Paleontologica Italiana, 2020)
The lower Oligocene coral communities and reefs exposed in the Lessini Shelf of northern Italy may record one of the oldest well-developed barrier reef/lagoon systems of the Cenozoic. However, the rimmed-shelf interpretation has been repeatedly challenged in favour of a ramp model with scattered corals. Based upon a re-analysis of selected localities in the Lessini Shelf, we here provide support for the barrier reef model based on four key observations: 1) systematic changes of coral growth-forms from branching in the proximal areas to massive at the platform margin; 2) a progressive increase of the hydrodynamic energy from the proximal belt towards the more distal environments in the Berici Hills; 3) the occurrence of shallow-water, euphotic conditions throughout the whole depositional system; and 4) the presence of restricted circulation in the proximal environments during sea-level lowstands, with lack of coral colonies. These features, together with the evidence of coral frameworks located on the southeastern edge of the Lessini Shelf, substantiate the occurrence of a reef-rimmed margin. The reefal rim acted as an efficient barrier, with the formation of a landward, wide lagoon protected from the action of waves and currents.
CRIS-Team WoS Importer:2021-01-29

Revisiting the identification of Syllipsimopodi bideni and timing of the decabrachian-octobrachian divergence - Klug, Christian; Stevens, Kevin; Hoffmann, René; Zatoń, Michał; Clements, Thomas; Košťák, Martin; Weis, Robert; De Baets, Kenneth; Lehmann, Jens; Vinther, Jakob; Fuchs, Dirk (Nature Communications, 2023)
CRIS-Team Scopus Importer:2023-12-15

Revisiting the long-term biodiversity dynamics of reef builders in a novel Bayesian framework - Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (13th International Symposium on Fossil Cnidaria, 2019)

Riffdiversität in der Erdgeschichte - Fossilbericht und Interpretationen. - Kießling, Wolfgang (Biodiversitätsforschung - Die Entschlüsselung der Artenvielfalt in Raum und Zeit., 2003)
Keywords: Riffe; Biodiversität; Riffevolution; Geobiologie

Rise and diversification of chondrichthyans in the Paleozoic - Schnetz, Lisa; Dunne, Emma; Feichtinger, Iris; Butler, Richard J.; Coates, Michael I.; Sansom, Ivan J. (Paleobiology, 2024)
The Paleozoic represents a key time interval in the origins and early diversification of chondrichthyans (cartilaginous fishes), but their diversity and macroevolution are largely obscured by heterogenous spatial and temporal sampling. The predominantly cartilaginous skeletons of chondrichthyans pose an additional limitation on their preservation potential and hence on the quality of their fossil record. Here, we use a newly compiled genus-level dataset and the application of sampling standardization methods to analyze global total-chondrichthyan diversity dynamics through time from their first appearance in the Ordovician through to the end of the Permian. Subsampled estimates of chondrichthyan genus richness were initially low in the Ordovician and Silurian but increased substantially in the Early Devonian. Richness reached its maximum in the middle Carboniferous before dropping across the Carboniferous/Permian boundary and gradually decreasing throughout the Permian. Sampling is higher in both the Devonian and Carboniferous compared with the Silurian and most of the Permian stages. Shark-like scales from the Ordovician are too limited to allow for some of the subsampling techniques. Our results detect two Paleozoic radiations in chondrichthyan diversity: the first in the earliest Devonian, led by acanthodians (stem-group chondrichthyans), which then decline rapidly by the Late Devonian, and the second in the earliest Carboniferous, led by holocephalans, which increase greatly in richness across the Devonian/Carboniferous boundary. Dispersal of chondrichthyans, specifically holocephalans, into deeper-water environments may reflect a niche expansion following the faunal displacement in the aftermath of the Hangenberg extinction event at the end of the Devonian.
CRIS-Team Scopus Importer:2024-04-19

Römische Keramik mit Marmormagerung: Herkunftsbestimmung mit Hilfe von stabilen Isotopen (Auerbergtöpfe aus Süddeutschland). - Flügel, C.; Joachimski, Michael; Flügel, Erik (Archäologisches Korrespondenzblatt, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dgeo.IGM.LG.rmisch

Rostrum size differences between Toarcian belemnite battlefields - Costa Rita, Patrícia; de Baets, Kenneth; Schlott, Martina (FOSSIL RECORD, 2018)
Body size changes have been reported across crisis intervals. Belemnites – now considered extinct stem-decabrachians – have rarely been investigated for this purpose, and the few studies have resulted in ambiguous outcomes. Here we investigate two Toarcian belemnite accumulations in southern Germany from a morphometric point of view with the support of computed tomography data. The aim of this study is to test whether a difference in size can be observed between the rostra of the two studied samples, from individual lineage to community, and which proxy is more reliable. A significant decrease in median size from the Early Toarcian (Dactylioceras tenuicostatum Zone) to the Middle Toarcian (Haugia variabilis Zone) is recognized. This is observed at the community level of organization, considering the whole assemblage, but also within Passaloteuthis–Acrocoelites lineage, at the genus level. It is also demonstrated that diameter-based measurements or maximum preserved length are not reliable proxies for size, and therefore apical length or three-dimensional approximations, such as the geometric mean or the post-phragmocone volume, are more advisable. This is especially important when comparing specimens with markedly different rostrum shapes. Further studies are, however, still necessary to disentangle the mechanisms behind the reduction in rostrum size within the Toarcian and their putative environmental cause

Saalfrank-type Fe2L3 host-guest complexes - Prediction of ion selectivity by quantum chemical calculations VII - Begel, Svetlana; Scheurer, Andreas; Puchta, Ralph (Journal of Coordination Chemistry, 2015)
Keywords: DFT; Metallocryptates; Metallocryptands; Selective ion complexation; Proton affinity

Sampling biases obscure the early diversification of the largest living vertebrate group - Henderson, Struan; Dunne, Emma; Giles, Sam (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2022)
Extant ray-finned fishes (Actinopterygii) dominate marine and freshwater environments, yet spatio-temporal diversity dynamics following their origin in the Palaeozoic are poorly understood. Previous studies investigate face-value patterns of richness, with only qualitative assessment of biases acting on the Palaeozoic actinopterygian fossil record. Here, we investigate palaeogeographic trends, reconstruct local richness and apply richness estimation techniques to a recently assembled occurrence database for Palaeozoic ray-finned fishes. We identify substantial fossil record biases, such as geographical bias in sampling centred around Europe and North America. Similarly, estimates of diversity are skewed by extreme unevenness in the occurrence distributions, reflecting historical biases in sampling and taxonomic practices, to the extent that evenness has an overriding effect on diversity estimates. Other than a genuine rise in diversity in the Tournaisian following the end-Devonian mass extinction, diversity estimates for Palaeozoic actinopterygians appear to lack biological signal, are heavily biased and are highly dependent on sampling. Increased sampling of poorly represented regions and expanding sampling beyond the literature to include museum collection data will be critical in obtaining accurate estimates of Palaeozoic actinopterygian diversity. In conjunction, applying diversity estimation techniques to well-sampled regional subsets of the 'global' dataset may identify accurate local diversity trends.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Actinopterygii; diversity; fossil record bias; Palaeozoic; sampling standardization

Sampling-standardized expansion and collapse of reef building in the Phanerozoic - Kießling, Wolfgang (Fossil Record, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dgeo.IGM.LP.sampli

Sauropod dinosaur fossils from the Kem Kem and extended ‘Continental Intercalaire’ of North Africa: A review - Holwerda, Femke Marleen (Journal of African Earth Sciences, 2020)
The Cretaceous (likely Aptian-Cenomanian) Kem Kem beds of Morocco are famous for their fossil-richness, including theropods, and several sauropod body fossils, such as Rebbachisaurus garasbae, as well as isolated sauropod teeth. Deposits from this particular age, however, stretch across Algeria and Tunisia, with possibly contemporaneous fossiliferous beds also being known from Egypt and Niger. Although the sediments of North Africa have yielded more complete sauropod specimens in recent years dated to either Cenomanian or Campanian-Maastrichtian, in general, these sites are not well-known. A recent study on isolated sauropod teeth from Morocco and Algeria revealed that a diverse sauropod fauna existed, and, moreover, evidence has been found of sauropod migration from Africa to Europe in the Cretaceous. In order to provide a better overview of the sauropod presence in the Albian-Cenomanian of North Africa, an overview of all sauropod material known from this time is necessary. Therefore, several previous reports on sauropod fossils and teeth from the Kem Kem and the ‘Continental Intercalaire’ of North Africa are here reviewed and summarized.
CRIS-Team Scopus Importer:2020-01-24
Keywords: Africa; Cenomanian; Cretaceous; Gondwana; Neosauropoda; Sauropoda

Scale- and taxon-dependent patterns of plant diversity in steppes of Khakassia, South Siberia (Russia) - Polyakova, Mariya A.; Dembicz, Iwona; Becker, Thomas; Becker, Ute; Demina, Olga N.; Ermakov, Nikolai; Filibeck, Goffredo; Guarino, Riccardo; Janisova, Monika; Jaunatre, Renaud; Kozub, Lukasz; Steinbauer, Manuel; et al. (Biodiversity and Conservation, 2016)
Keywords: Biodiversity; Bryophyte; Environmental factor; Lichen; Species richness; Species–area relationship

Schwankende Umweltbedingungen des süd-westdeutschen Oberjura dokumentiert in Kalk-Mergel-Wechselfolgen - Munnecke, Axel; Westphal, Hildegard (Jahresheft der Gesellschaft für Naturkunde in Württemberg, 2004)
The genesis of limestone-marl alternations such as those present in Upper Jurassic successions of SW Germany has a long history of controversial discussion. The origin of the rhythmic alternation of limestone beds and marl interlayers, the so-called couplets, has been addressed in numerous studies, and similarly the large-scale trends of limestone-dominated and marl-dominated intervals of the Upper Jurassic (Impressamergel, Wohlgebankte Kalke, and Lacunosamergel Formations) have been thoroughly studied. The intermediate scale, in contrast, the so-called bundles, has received markedly less attention. Here we focus on this intermediate scale. A general problem with deciphering of paleoenvironmental information recorded in calcareous successions is the usually pronounced diagenetic overprint that particularly affects mineralogically metastable primary constituents. Primary aragonite, for example, typically is transformed into diagenetically stable calcite. The mineralogical composition of the precursor sediment and the primary aragonite content in particular, however, reflect the environmental conditions under which the sediment was formed. Reconstructing the primary mineralogy therefore would yield valuable information on the palaeo-environment. For this task we employ a new model that allows for assessing the mineralogical composition of the precursor sediment, and apply this model to the example of SW Germany (Neuffen quarry). With this approach, variations of influx of shallow-water carbonate platform sediment into the depositional basin become visible, and are interpreted as fluctuations in biogenic carbonate productivitiy. Thus, new insight is gained into the fluctuating environmental conditions in the Jurassic Sea of SW Germany during the time of deposition of the Impressamergel, Wohlgebankte Kalke, and Lacunosamergel Formation
Keywords: Upper Jurassic; Genesis; Limestone-Marl alternations; SW Germany; Impressamergel; Wohlgebankte Kalke; Lacunosamergel Formations; Kalk-Mergel Wechselfolgen; Oberjura; Karbonate; Malm

Scientific collaborations between Latin America and Europe: An approach from science diplomacy towards international engagement - Echeverría-King, Luisa F.; Fossati, Aura; Raja, Nussaïbah Begum; Bonilla, Kleinsy; Urbani, Bernardo; Whiffen, Radenka Krsmanović; Vizinová, Tereza (Science and Public Policy, 2023)
International collaborations show asymmetries and imbalances that influence how countries take part in international relations. In this context, science diplomacy (SD) could offer possibilities towards building partnerships and meaningful engagement between Europe and Latin America. The purpose of this article is to analyse how scientific collaborations between Latin American and European researchers are carried out, observing trends, behaviours, and perceptions. Qualitative methodologies and the analysis of empirical data collected through a survey allow the extraction of relevant experiences from real cases of international joint projects. Findings indicate that addressing the asymmetries in the collaboration between partnering researchers from Europe and Latin America is essential, and SD approaches may facilitate such endeavour. SD may not represent a panacea; however, it seems to facilitate the internationalisation of research in terms of mobility, international scientific collaborations, and knowledge exchange with under-represented actors in traditional international scientific schemes, such as indigenous communities.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Europe-Latin America; Global South; science diplomacy; scientific collaborations; transnational research

Scientometric trends in Burmese amber research - Dunne, Emma; Raja, Nussaïbah Begum (Paleontological Association Annual Meeting, 2020)
Discoveries of fossil inclusions in Burmese (Myanmar) amber have attracted considerable attention due to their exquisite preservation, which offers an unparalleled window into Cretaceous forest ecosystems. However, research on Burmese amber has also attracted controversy due to its alleged role in funding internal conflict, resulting in a devastating humanitarian crisis. The palaeontological community is not yet unified on how to ethically adjust research practices in response to this situation. Using bibliometric methods and networks analyses, we investigated the scientometric trends in research publications on fossils in Burmese amber, and quantitatively examined the collaborative networks of their authors. We find that in the last 30 years, research activity on Burmese amber has generally increased, with a noticeable escalation within the last five years, coincident with the military takeover of the amber mines. The majority of publications are authored by researchers based in countries of the Global North and lack Burmese co-authors, indicating weak or absent collaborations with local researchers and communities. This practice of ‘parachute science’ is harmful generally, but in a conflict region it is acutely problematic because it erodes confidence about whether fossil specimens are – or even can be – ethically collected and trade

Scleractinian cold-water corals in the Gulf of Cádiz - First clues about their spatial and temporal distribution - Wienberg, Claudia; Hebbeln, Dierk; Hiske, Fink; Mienis, Furu; Dorschel, Boris; Vertino, Agostina; López Correa, Matthias; Freiwald, André (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
This paper presents the first compilation of information on the spatial distribution of scleractinian cold-water corals in the Gulf of Cádiz based on literature research and own observations (video footage, sediment samples). Scleractinian cold-water corals are widely distributed along the Spanish and Moroccan margins in the Gulf of Cádiz, where they are mainly associated with mud volcanoes, diapiric ridges, steep fault escarpments, and coral mounds. Dendrophyllia cornigera, Dendrophyllia alternata, Eguchipsammia cornucopia, Madrepora oculata and Lophelia pertusa are the most abundant reef-forming species. Today, they are almost solely present as isolated patches of fossil coral and coral rubble. The absence of living scleractinian corals is likely related to a reduced food supply caused by low productivity and diminished tidal effects. In contrast, during the past 48 kyr scleractinian corals were abundant in the Gulf of Cádiz, although their occurrence demonstrates no relationship with main climatic or oceanographic changes. Nevertheless, there exists a conspicuous relationship when the main species are considered separately. Dendrophylliids are associated with periods of relatively stable and warm conditions. The occurrence of L. pertusa mainly clusters within the last glacial when bottom current strength in the Gulf of Cádiz was enhanced and long-term stable conditions existed in terms of temperature. Madrepora oculata shows a higher tolerance to abrupt environmental changes. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.sclera
Keywords: Coral mounds; Dating; Glacial-interglacial cycle; Gulf of Cádiz; Mud volcanoes; Scleractinian cold-water corals; Spatial distribution

Sclerochronological insights into the environmental response of Corbula gibba from the Adriatic Sea - Strafella, Pierluigi; al-Fudhaili, Najat; de Winter, N.; López Correa, Matthias; Teichert, Sebastian; Scarcella, G; Nohl, Theresa (EGU General Assembly 2022, 2022)
Bivalve shells are accretionary biogenic carbonates that yield a record of the organisms’ life history, also with respect to the physiological response to the ambient environmental conditions. This is reflected by variations in the shells’ growth bands, their chemical composition, and morphological features, making them useful tools in paleobiology and paleoenvironmental reconstructions. Corbula gibba is an abundant bivalve species in the Adriatic Sea that is commonly used to resolve questions in age determinations, paleoenvironmental reconstructions and sequence stratigraphic studies [1,2]. Nevertheless, a detailed analysis of its response in growth bands and chemical signatures to environmental variations is currently missing. This study evaluates growth increments and chemical variations in Corbula gibba shells. The shells have been collected alive from the Western Adriatic Sea between Senigallia and Ancona to shed light on the reliability of the Corbula gibba as an archive for (paleo)environmental information. Mutvei's solution has been used [3] to stain the alternating dark and light bundles in the shell, enhancing the visualization of growth increments. High-resolution elemental profiles have been acquired across the outer shells layer using the non-destructive Micro X-ray fluorescence (µ-XRF) technique [4]. The results are compared to available climatic information for Ancona and indicate that Corbula gibba shells record detailed temporal changes in the environment such as tidal fluctuations caused by lunar cycl

Scleromochlus and the early evolution of Pterosauromorpha - Foffa, Davide; Dunne, Emma; Nesbitt, Sterling J.; Butler, Richard J.; Fraser, Nicholas C.; Brusatte, Stephen L.; Farnsworth, Alexander; Lunt, Daniel J.; Valdes, Paul J.; Walsh, Stig; Barrett, Paul M. (Nature, 2022)
Pterosaurs, the first vertebrates to evolve powered flight, were key components of Mesozoic terrestrial ecosystems from their sudden appearance in the Late Triassic until their demise at the end of the Cretaceous1–6. However, the origin and early evolution of pterosaurs are poorly understood owing to a substantial stratigraphic and morphological gap between these reptiles and their closest relatives6, Lagerpetidae7. Scleromochlus taylori, a tiny reptile from the early Late Triassic of Scotland discovered over a century ago, was hypothesized to be a key taxon closely related to pterosaurs8, but its poor preservation has limited previous studies and resulted in controversy over its phylogenetic position, with some even doubting its identification as an archosaur9. Here we use microcomputed tomographic scans to provide the first accurate whole-skeletal reconstruction and a revised diagnosis of Scleromochlus, revealing new anatomical details that conclusively identify it as a close pterosaur relative1 within Pterosauromorpha (the lagerpetid + pterosaur clade). Scleromochlus is anatomically more similar to lagerpetids than to pterosaurs and retains numerous features that were probably present in very early diverging members of Avemetatarsalia (bird-line archosaurs). These results support the hypothesis that the first flying reptiles evolved from tiny, probably facultatively bipedal, cursorial ancestors1.
CRIS-Team Scopus Importer:2022-10-21

Seasonal climatic fluctuations in the Late Triassic tropics - high-resolution oxygen isotope records from aragonitic bivalve shells (Cassian Formation, Northern Italy) - Nuetzel, A.; Joachimski, Michael; López Correa, Matthias (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
Three megalodontoid bivalves from the Upper Triassic Cassian Formation (N Italy, Dolomites) were sampled for δ13C and δ18O sclerochronology (n = 270). With more than 1000 described invertebrate species, the Cassian Formation has one of the best records of an Early Mesozoic tropical fauna. In addition, the Cassian Formation is one of the very few Triassic occurrences with original aragonite preservation, with all studied shells consisting of pristine aragonite. The presence of aragonite and crossed lamellar as well as fibrous prismatic shell microstructures shown for the first time for Triassic megalodontoids suggests absence or minimal impact of diagenetic alteration. The δ13C values range from 3.6 to 5.8‰ and show a distinct cyclicity in two studied shells whereas a third shell shows no obvious cyclicity. In one bivalve specimen, the cycles are somewhat offset from δ18O cycles and in the other specimen δ18O and δ13C curves are inversely correlated. Seasonal variation in freshwater runoff including nutrient input and subsequent changes in plankton productivity during dry and wet seasons may explain δ13C cyclicity. δ18O values show a pronounced cyclicity within each of the studied shells varying from - 3.6 to - 1.4‰. The variations in δ18O suggest a pronounced seasonality in Late Triassic tropical shallow waters of the western Tethys, with inferred seasonal temperature changes ranging from 24 to 32 °C. Influx of fresh water during the rainy seasons (mega-monsoon) or upwelling might also explain part of the variation in δ18O. The presented data suggest that the diverse Cassian fauna lived under conditions characterized by warm sea-surface waters with a pronounced seasonality. Similar conditions are reported for some modern tropical settings. © 2009 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LG.season
Keywords: Bivalves; Climate; Late Triassic; Sclerochronology; Seasonality

Sectioning of radiolarians under continuous observation - Kießling, Wolfgang; et al. (Fossil Record, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IGM.LP.sectio

Secular variations in the Phanerozoic reef ecosystem - Kießling, Wolfgang (Phanerozoic Reef Patterns, 2002)
UnivIS-Import:2015-04-20:Pub.2002.nat.dgeo.IGM.LP.secula

Sedimentary dykes and genetically related features in the Upper Jurassic Jhuran Formation of the Kachchh Rift Basin, Western India - Fursich, Franz T.; Alberti, Matthias; Pandey, Dhirendra K. (Journal of the Palaeontological Society of India, 2022)
In the Kimmeridgian-Tithonian Jhuran Formation of the Kachchh Rift Basin features such as sedimentary dykes, convolute bedding, and intraformational pillows are documented at several levels and localities. They are interpreted as having been produced by seismic events. Together with features, such as local intraformational unconformities and dying growth faults recorded earlier on in the literature they indicate that the basin was in a syn-rift stage until the end of the Jurassic. Interestingly, signs of seismic activity in the basin are far more conspicuous during the Oxfordian - Tithonian time interval than during the Middle Jurassic.
CRIS-Team WoS Importer:2023-02-10

Sedimentology of Middle Ordovician carbonates in the Argentine Precordillera: Evidence of regional relative sea-level changes - Keller, Martin; Eberlein, Stefan; Lehnert, Oliver (Geologische Rundschau, 1993)
Keywords: Early Ordovician; Argentine Precordillera; Sea-level changes

Seven rules for simulations in paleobiology - Barido-Sottani, Joëlle; Saupe, Erin E.; Smiley, Tara M.; Soul, Laura C.; Wright, April M.; Warnock, Rachel (Paleobiology, 2020)
Simulations are playing an increasingly important role in paleobiology. When designing a simulation study, many decisions have to be made and common challenges will be encountered along the way. Here, we outline seven rules for executing a good simulation study. We cover topics including the choice of study question, the empirical data used as a basis for the study, statistical and methodological concerns, how to validate the study, and how to ensure it can be reproduced and extended by others. We hope that these rules and the accompanying examples will guide paleobiologists when using simulation tools to address fundamental questions about the evolution of life.
CRIS-Team Scopus Importer:2020-11-27

Shallow-water aragonite recorded in bundles of limestone-marl alternations - The Upper Jurassic of SW Germany - Munnecke, Axel; Westphal, Hildegard; Munnecke, Axel; Munnecke, Axel (Sedimentary Geology, 2004)
Characteristically, limestone-marl alternations are conspicuous in outcrop because of differential weathering, the marls being predisposed to stronger deterioration. Superimposed on the bedding rhythms are in many cases lower-frequency meter-scale rhythms, so-called bundles. These bundles are eye-catching from a distance, and are typified by variations in thickness of limestone beds and marl interbeds. The palaeoenvironmental significance of the bundles received markedly less attention in the literature than the origin of the small-scale couplets. Here we focus on the palaeoenvironmental significance of the bundles by reconstructing the initial mineralogical composition. As an example, we present a classical limestone-marl alternation from the Upper Jurassic (Oxfordian-Kimmeridgian) of SW Germany that is typified by two orders of bundles superimposed on the limestone-marl couplets. Our method of reconstruction of the original mineralogical composition of the precursor sediment of limestone-marl alternations is based on a diagenesis model that assumes dissolution of aragonite and reprecipitation as calcite cement as the major mechanism of early diagenesis. Calculated initial clay, aragonite, and calcite contents show rhythmic variations on a scale of several meters that correspond to the bundles as seen in the outcrop. Limestone-dominated parts of the bundles correspond to intervals of elevated aragonite content in the precursor sediment, but not necessarily to elevated calcite contents. Additionally, an overlain fluctuation in initial mineralogy on the order of tens of meters (mega-bundles), reflecting the former local subdivision of the SW German Upper Jurassic into "Weißjura alpha", "beta", and "gamma", is observed. The limestone- dominated "Weißjura beta" (lower Kimmeridgian) is the interval with highest initial aragonite content. Our new method allows for quantification of initial mineralogical composition. As aragonite and calcite usually have different sources (shallow-water benthic versus planktic), this approach potentially adds significant new possibilities for palaeoceanographic interpretation of calcareous rhythmites. In the Jurassic example, the observed variations in reconstructed aragonite content are interpreted as variations in flooding events and related export of aragonitic material from marginal shallow-water platforms. © 2003 Elsevier B.V. All rights reserve
Keywords: Aragonite; Bundles; Couplets; Jurassic; Limestone; Marl

Shell architecture, element composition, and stable isotope signature of the giant deep-sea oyster Neopycnodonte zibrowii sp n. from the NE Atlantic - Wisshak, Max; López Correa, Matthias; Gofas, Serge; Salas, Carmen; Taviani, Marco; Jakobsen, Joachim; Freiwald, André (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
A conspicuous new deep-sea oyster, Neopycnodonte zibrowii sp. n., is described from the Azores Archipelago, where it thrives in 420 to >500 m water depth in high densities concealed underneath overhangs. The new species reaches a relatively large size, which may exceed 20 cm, and is characterised by a very unusual hinge line morphology, straight without a bulge of the resilium. It is compared to the extant Indo-Pacific Empressostrea kostini Huber and Lorenz, 2007 and to the cosmopolitan Neopycnodonte cochlear (Poli, 1791), which has a broadly sympatric distribution at shallower depths in the Azores and Bay of Biscay. Radiocarbon dating reveals that individuals reach an impressive lifespan of one to more than five centuries, placing them among the longest-lived molluscs known to date. They often grow on top of each other, forming stacks that resemble dish piles-an effective measure to optimise shell stability with minimal biomineralisation effort, but with the drawback of increased bioerosion ultimately leading to detachment. Three microstructure types are developed in N. zibrowii: (1) the cross-foliated, calcitic, dorsal to central endostracum and aragonitic ligostracum, (2) the porous vesicular structure of the calcitic ventral endostracum, and (3) the simple prismatic aragonitic myostracum. Foliated and vesicular shell portions show sub-millimetre-scale first-order increments delineated by conchiolin-rich growth breaks (interpreted as reproductive cyclicity), and less distinct second-order increments (interpreted as annual in nature). This pattern is clearly reflected by the elemental composition with the primary growth breaks lacking Ca and Sr but including Mg and S as organic matrix constituents. The second-order increments within the calcite are mirrored by moderately co-varying Mg/Ca and S/Ca fluctuations at stable Sr concentrations, reflecting varying proportions of organic matrix. Dorsal and central endostracum transects reveal a low inter-valve, but considerable inter-specimen variability with high Mg/Ca molar ratios and fluctuations (22.5±17.6 mmol/mol), low Sr/Ca values (0.2±0.1 mmol/mol), and a typical to high S/Ca content (6.9±2.2 mmol/mol), when compared to other calcitic bivalves. Unlike short-lived, shallow-water oysters, N. zibrowii thrives under very stable environmental conditions. Minimal temperature fluctuations and stable open marine salinity provide an optimal basis to recognise biological fractionation processes. Strong Mg/Ca fluctuations indicate a physiological control related to metabolism and biomineralisation, prohibiting the use of this ratio as a temperature or ocean chemistry proxy. Low Sr/Ca ratios indicate rather constant and low long-term accretion rates, while short-scale fluctuations may be attributed to short-term variations in growth rate and Mg incorporation. Oxygen isotopes yield a considerable spread of 1.8‰ with a mean of 2.0±0.3‰ δ18O V-PDB, and low correlation between different contemporaneous parts of the shell and between specimens. These values surprisingly exceed expected equilibrium conditions, calculated from in situ temperature data (annual mean 12.3±0.3 °C) and seawater isotopic composition (0.5±0.1‰ δ18O SMOW), by 0.5‰ on average. Such positively shifting vital effects, previously reported for limpets and barnacles, are often overlooked in high-temperature and high-amplitude settings and may be more common than is currently believed. Carbon isotopes range from 0.2 to 3.5‰ δ13C V-PDB (mean 1.8±0.7‰) and show an ontogenetic decrease, but may incorporate an environmental signal in adult portions, indicated by a strong correspondence of peaks between specimens. This signal is likely driven by a complex interplay of different factors, such as primary production, current-based food supply and metabolism. © 2008 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.shella
Keywords: Azores; Microstructure; Neopycnodonte zibrowii; Oyster; Stable isotopes; Trace elements

Significance of Detrended Correspondence Analysis (DCA) in palaeoecology and biostratigraphy: A case study from the Upper Cretaceous of Egypt - Ayoub-Hannaa, Wagih; Fürsich, Franz; Huntley, John Warren (Journal of African Earth Sciences, 2013)
The Cenomanian-Turonian macrofauna from the Sinai Peninsula, Egypt offers an excellent opportunity to test the applicability of gradient analysis in palaeoecology and biostratigraphy. Detrended Correspondence Analysis (DCA) is a simple multivariate technique for arranging species and samples along environmental gradients. In order to reconstruct palaeoecological patterns and biostratigraphy, 42 samples, 4564 individuals, and 132 species from three sections of eastern Sinai were subjected to DCA. Compared with other multivariate techniques such as cluster analysis, the macrobenthic associations (obtained by DCA) fall fully within or deviate only slightly from associations obtained by cluster analysis. However, DCA makes it possible to arrange these associations from completely random distribution (as tested by cluster analysis) to a temporal gradient. Therefore, it is possible to use this multivariate technique also as a useful tool in biostratigraphy. The first detrended correspondence axis (DC1) reflects a water-depth gradient from onshore to offshore, higher scores being typical of onshore samples from the southernmost section and lower scores being typical of offshore samples from the northern section. Overprinted on the DC1 axis is also a gradient of life and feeding modes, as samples with low scores are dominated by epifaunal species and samples with high scores display a higher proportion of shallow-infaunal taxa. With respect to the second detrended correspondence axis (DC2), substrate composition and water energy are overprinted on this axis as samples with low scores predominantly are coarse-grained carbonates (e.g., reefal rudstone), while samples with high scores primarily are mixed-siliciclastics/carbonates (e.g., marl), which are dominated by low-energy taxa. Because the substrate conditions are closely related to the water energy, the coarse-grained substrates were deposited under high water energy, while the marly facies was deposited under low-energy conditions. Excursions in DC2 scores, reflecting substrate composition and water energy, are used to reconstruct the macrobenthic associations; eight associations and two assemblages were recognized. High stress environments (low DC2 scores) were occupied by less diverse associations such as the Chondrodonta joannae association and the Pchelinsevia coquandiana-Praeradiolites biskraensis association. The latter association is stratigraphically followed by high-diversity associations such as the Ilymatogyra africana-Rhynchostreon suborbiculatum association, which preferred less-stressed environments (high DC2 scores). © 2013 Elsevier Ltd.
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.signif
Keywords: Biostratigraphy; Cenomanian-Turonian; Detrended Correspondence Analysis (DCA); Egypt; Palaeoecology; Sinai Peninsula

Silurian - Munnecke, Axel (Mémoires du Muséum national d'Histoire naturelle, 2007)
Keywords: Silurian

Silurian calcispheres (Calcitarcha) of Gotland (Sweden): Comparisons with calcareous dinoflagellates - Servais, Thomas; Munnecke, Axel; Versteegh, Gerard J.M. (Comptes Rendus Palevol, 2009)
Scanning electron microscope examinations of polished and etched surfaces of sediments from the Silurian carbonate platform of Gotland, Sweden, revealed the presence of numerous, morphologically diverse "calcispheres" (Calcitarcha). Some of these spherical calcareous microfossils display wall structures that are surprisingly similar to those of calcareous dinoflagellate cysts. In analogy to the interpretation of the biological affinities of Palaeozoic acritarchs as cysts of organisms that might have been the ancestors of organic-walled dinoflagellates, the Calcitarcha from Gotland can be compared and may possibly be related to organisms that may have been the ancestors of calcareous cyst-producing dinoflagellates that so far have not been observed before the Late Jurassic. © 2009 Académie des sciences.
Keywords: Calcitarcha Calcispheres Calcareous dinoflagellates Silurian Gotland

Silurian carbonate high-energy deposits of potential tsunami origin: Distinguishing lateral redeposition and time averaging using carbon isotope chemostratigraphy - Jarochowska, Emilia; Munnecke, Axel (Sedimentary Geology, 2015)
Stable carbon isotope curves are used as a precise stratigraphic tool in the Paleozoic, even though they are commonly based on shallow-water carbonate record, characterized by low stratigraphic completeness. Identification of episodes of large-scale redeposition and erosion may improve δ13Ccarb-based correlations. Here, a series of at least three episodes of high-energy onshore redeposition are described from the Makarivka Member (new unit) of the Ustya Formation from the Homerian (middle Silurian) of Podolia, Ukraine. The Makarivka Member is emplaced within a tidal flat succession. Its most prominent part is divided into a lower polymictic conglomerate of sand- to boulder-sized clasts representing a range of subtidal facies, and an upper heterolithic unit composed of grainstone and mudstone laminae. The aim of the study is to identify the mechanism of deposition of the allochthonous conglomeratic material in this Member. Based on analogies with recent tsunami deposits, the conglomerate is interpreted to reflect the strongest landward-directed current in the tsunami run-up phase, and the heterolith - alternating high-density landward currents, stagnant intervals allowing mud and land-derived debris to settle, and backwash flows. The tsunamite was deposited during an interval of decreasing isotopic values of the Mulde excursion, a global δ13C excursion reaching +5.2‰ in the studied sections. Clast redeposition in an interval characterized by rapidly changing δ13Ccarb offers the opportunity to evaluate the degree of temporal and spatial averaging caused by the tsunami. The clasts in the polymictic conglomerate show scattered δ13Ccarb values (-0.3‰ to +2.1‰) compared to homogenous (1.3‰ to 1.6‰) values in the matrix. The presence of clasts characterized by low δ13Ccarb values is explained by their decrease with bathymetry rather than erosion of pre-excursion strata, whereas high values characterize material entrained from the sea-floor and strata directly underlying the tsunamite. Close (1.3‰ and 1.5‰) average δ13Ccarb values suggest that the matrix of the conglomerate is potentially a product of clast grinding.
UnivIS-Import:2015-04-14:Pub.2015.nat.dgeo.IGM.LP.siluri
Keywords: Homerian; Positive carbon isotope excursion; Sequence stratigraphy; Temporal mixing; Transgressive lag; Wenlock

Skeletal microstructure and stable isotope signature of three bathyal solitary cold-water corals from the Azores - Marali, Soraya; Wisshak, Max; López Correa, Matthias; Freiwald, André (Palaeogeography, Palaeoclimatology, Palaeoecology, 2013)
Skeletons of cold-water corals are potential geochemical archives that record oceanographic parameters, such as bottom water temperature in the deep sea. In this study, the three solitary scleractinian species, Caryophyllia cyathus, Desmophyllum cristagalli and Stenocyathus vermiformis, were sampled from upper bathyal 500m water depths in the southern Faial Channel (Azores archipelago). The stable carbon isotope (δ13C) and oxygen isotope (δ18O) compositions of the corals were analysed and related to their skeletal architecture. Background data, including data from high-resolution temperature logs and on the ambient seawater isotopic composition, were compared with δ18O-based temperature reconstructions to test the suitability of these cold-water corals as geochemical archives and to explore the role of vital effects on skeletal geochemistry. Although all of the corals experienced identical and near-stable salinities and temperatures, the stable isotopic signatures vary within and among species. Both δ13C and δ18O values fluctuate in relation to growth bandings and are therefore most likely dependent on calcification rates and associated kinetic vital effects. The studied specimens are 13C depleted with respect to equilibrium with ambient seawater, indicating significant uptake of respired CO2 by their skeletons. Skeletal δ18O values vary by up to 3.6‰ among the growth bands of one of the coral specimens, translating into an unrealistic reconstructed temperature amplitude of 16°C. This contrasts with the minute intra-annual amplitude of the stable temperature regime (annual mean 12.30±0.25°C). Nevertheless, δ13C vs. δ18O regression lines can be used to deduce ambient temperatures by applying the lines technique (Smith et al., 2000; Palaios 15, 25-32), which yields temperatures that coincide with the measured maximum temperature range in the case of D. cristagalli and for most C. cyathus samples, but deviate by 2.95°C from the measured annual mean in the case of the S. vermiformis specimen. © 2012 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.skelet
Keywords: Caryophyllia; Desmophyllum; Lines technique; Stenocyathus; Temperature reconstruction

Skeletal reorganisation affects geochemical signals, exemplified in the stylasterid hydrocoral Errina dabneyi (Azores Archipelago) - Wisshak, Max; López Correa, Matthias; Zibrowius, Helmut; Jakobsen, Joachim; Freiwald, André (Marine Ecology-Progress Series, 2009)
The pure white fans of the stylasterid Errina dabneyi are a conspicuous feature on the upper bathyal slopes in Azorean waters and were documented and recovered alive with the aid of a submersible in the southern Faial Channel. Etched vacuum-epoxy-casts of the aragonite skeleton, studied by scanning electron microscopy, reveal the 3-dimensional internal architecture comprising coenosarc canal meshwork, dactylopores, gastropores and ampullae. Near the surface, the canals are narrow and interconnected in a regular 3-dimensional meshwork. Deeper inside the canals are less abundant, more irregular and wider. This pattern implies that the skeletal architecture is modified during growth, with more central canals being enlarged by dissolution, and other canals, gastropores and dactylopores in turn being filled with aragonite reprecipitates. The skeleton is primarily composed of irregular spherulitic aggregates and overprinting during growth is evident from ghost structures in the form of successive semi-spherulitic infill of former canals. Due to differential dissolution and reprecipitation, this internal rebuild process inevitably involves an alteration of initial geochemical signatures such as stable isotope ratios (δ18O and δ13C), trace element signals and the distribution of radiogenic isotopes of carbon and uranium. This has to be taken into account when applying radiometric dating techniques and when using stylasterids as a geochemical archive. © Inter-Research 2009.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.skelet
Keywords: Biomineralisation; Coenosarc canals; Epoxy-casting technique; Geochemical signals; Hydrozoa; Microstructure; Stable isotopes; Stylasteridae

Solenoporaceen aus den obertriassischen (Nor) Riffkalken des Taurusgebirges (Antalya-Gebiet, Südtürkei) - Senowbari-Daryan, Baba; Link, Michael (Palaeontologische Zeitschrift, 2005)
From the Upper Triassic (Norian) reef limestones north and west of Antalya (Taurus Mts., Turkey) the red algae (Solenoporaceans) Solenopora undata n. sp., Parachaetetes clatratus n. sp., Parachaetetes riedeli n. sp., Parachaetetes tauricus n. sp., and Tauristorea parallela n. gen., n. sp. are described. Tauristorea is characterized by cells orientated parallel to the substrate (vertically to the growth direction of the alga). In Solenopora undata and Parachaetetes clatratus some cavity structures occur, whose function as reproductive organs are discussed.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LP.soleno
Keywords: Algae; Solenopora; Parachaetetes; Tauristorea; Triassic; Norian; Antalya; Turkey

Sources identification and contamination assessment of heavy metals in soil of Middle Nile Delta, Egypt - Abu Khatita, Atef M.; Koch, Roman; Bamousa, Abdullah O. (Journal of Taibah University for Science, 2020)
Sedimentological and geochemical studies are integrated to determine the potential of heavy metals in the Middle Nile Delta soil. Four sources of trace elements were identified; a geogenic source includes Fe, Co, Cr, Ni and V, along with Ca that partly enhanced by anthropogenic input, and three dissimilar anthropogenic sources grouped the elements as follow; As, Pb, Zn Cu, Ba and P which derived mainly from industrial activities; Ba, Pb, Zn and Cu group is likely dispersed by traffic emissions, and P, As and Cu elements group which influenced by agrochemical application and drain water irrigation. The concentrations of studied elements increasing with decreasing the particle size. Moreover, two groups of mineral assemblages of soil are recognized; the first group deposited with one particle fraction and inherited from parent materials, The second one includes non-silicate minerals clasts, deposited with more than one fraction and most likely of anthropogenic source.
CRIS-Team WoS Importer:2020-06-23

Southward Migration of Arctic Ocean Species During the Last Glacial Period - Zhang, Penghui; Huang, Huai-Hsuan; Hong, Yuanyuan; Tian, Skye Yunshu; Liu, Jian; Il Lee, Yong; Chen, Jianwen; Liang, Jie; Wang, He; Yasuhara, Moriaki (Geophysical Research Letters, 2022)
The East Asian winter monsoon (EAWM) is associated with northerly surface winds affecting crop and livestock productivity and social and economic activities across East Asia. However, the relationship between EAWM dynamics and marine biota remains poorly understood. In this study, we analyzed fossil ostracods from sediment cores collected in the northwestern Pacific Ocean to detect the appearance/disappearance of circumpolar species during the late Quaternary. We compared our ostracod records, including dating results, with ice-rafted debris records from the Sea of Japan, and identified two southward migration events of Arctic ostracods at 120-100 ka (Marine Isotope Stage [MIS] 5d stadial) and 30-15 ka (MIS 3 and 2, peak Last Glacial), which corresponded to a strengthened EAWM system. Our results indicate that an intensified EAWM influenced the Yellow Sea Bottom Cold Water formation, lowered the winter water temperatures, and allowed Arctic ostracods to migrate southward into the Yellow Sea.
CRIS-Team WoS Importer:2023-03-03

Spatial and temporal variability in Mediterranean climate over the last millennium from vermetid isotope records and CMIP5/PMIP3 models - Amitai, Yael; Yam, Ruth; Montagna, Paolo; Devoti, Saverio; López Correa, Matthias; Shemesh, Aldo (Global and Planetary Change, 2020)
Stable isotope compositions of oxygen (δ18O) and carbon (δ13C) of the aragonite skeleton of the reef-building gastropod Dendropoma petreaum provide high-resolution records of the Mediterranean climate over the last millennium. In particular, the isotopic composition of vermetid cores collected from the west and east Mediterranean reveals that the different regions have had distinct thermal and primary production behaviors throughout the last millennium. The rate of warming in the recent Industrial Period is variable among the different regions of the Mediterranean Sea. The δ18O-derived Sea Surface Temperature (SST) anomalies show that the Eastern Mediterranean surface temperature is increasing much more rapidly than in the Western Mediterranean. Additionally, the signals of the Little Ice Age and of the Medieval Climate Anomaly are more apparent in the western and in the central Mediterranean while they are almost absent in the eastern Mediterranean. We aim to reconcile the SST temporal and spatial pattern with the variability of the North Atlantic Oscillation (NAO) and the South Asian Monsoon (SAM) climate systems by analyzing coupled atmosphere-ocean models from the CMIP5/PMIP3 projects that simulate the global climate of the past 1000 years. We show that even though the NAO is more dominant in the western Mediterranean SST, its latitudinal movement, on a centennial time scale, is evident in the eastern Mediterranean SST signal. We also discuss the Atlantic water inflow role in the observed similarities of the surface productivity signals and the Suess effect that prevail the Industrial Period signal in all regions of the Mediterranean.
CRIS-Team Scopus Importer:2020-03-27
Keywords: CMIP5/PMIP3 models; Dendropoma petreaum; Last Millennium; Mediterranean Sea; Vermetid

Spatial-temporal analysis of precipitation characteristics in Artvin, Turkey - Aydin, Olgu; Raja, Nussaïbah Begum (Theoretical and Applied Climatology, 2020)
The region of Artvin, located in the northeast of Turkey, usually experiences high-intensity precipitation events that occur within a short-time period. Along with other environmental impacts, these events also lead to flash floods in this region. The purpose of this study was to evaluate the changing spatial and temporal characteristics of precipitation on August 24, 2015 and November 11 to 12, 2015 that triggered flash floods and landslides in Artvin. We apply spatiotemporal (ST) kriging as a tool to investigate these ST patterns. The average hourly precipitation data were used, taking episodes of heavy rainfall into account. Our results show that precipitation reached the highest values of 30–50 mm between 8:00 and 9:00 pm in the Hopa district on August 24, 2015. On November 11, 2015, rainfall values reached ≥ 15 mm at 4:00 PM in the Borçka district. During both events occurred on November 12, 2015, it rained for 7 h continuously with precipitation values ranging between 5 and 10 mm. The duration of the precipitation lasted for 8 h. In addition, flood events also occurred in the districts of Arhavi and Murgul. This highlights that these districts are vulnerable in the Artvin region and paves the way for decision-makers to implement measures against flash floods in these at-risk districts. In conclusion, the analysis of spatiotemporal characteristics of heavy rainfall events represents an indispensable basis to ensure that necessary precautions regarding flash flood events in the city are take
Keywords: precipitation characteristics; flood events; space and time; kriging; artvin

Species–area relationships in continuous vegetation: Evidence from Palaearctic grasslands - Dengler, Jürgen; Matthews, Thomas J.; Steinbauer, Manuel; Wolfrum, Sebastian; Boch, Steffen; Chiarucci, Alessandro; Conradi, Timo; Dembicz, Iwona; Marcenò, Corrado; García-Mijangos, Itziar; Nowak, Arkadiusz; Storch, David; et al. (Journal of Biogeography, 2019)
Aim: Species–area relationships (SARs) are fundamental scaling laws in ecology although their shape is still disputed. At larger areas, power laws best represent SARs. Yet, it remains unclear whether SARs follow other shapes at finer spatial grains in continuous vegetation. We asked which function describes SARs best at small grains and explored how sampling methodology or the environment influence SAR shape. Location: Palaearctic grasslands and other non-forested habitats. Taxa: Vascular plants, bryophytes and lichens. Methods: We used the GrassPlot database, containing standardized vegetation-plot data from vascular plants, bryophytes and lichens spanning a wide range of grassland types throughout the Palaearctic and including 2,057 nested-plot series with at least seven grain sizes ranging from 1 cm2 to 1,024 m2. Using nonlinear regression, we assessed the appropriateness of different SAR functions (power, power quadratic, power breakpoint, logarithmic, Michaelis–Menten). Based on AICc, we tested whether the ranking of functions differed among taxonomic groups, methodological settings, biomes or vegetation types. Results: The power function was the most suitable function across the studied taxonomic groups. The superiority of this function increased from lichens to bryophytes to vascular plants to all three taxonomic groups together. The sampling method was highly influential as rooted presence sampling decreased the performance of the power function. By contrast, biome and vegetation type had practically no influence on the superiority of the power law. Main conclusions: We conclude that SARs of sessile organisms at smaller spatial grains are best approximated by a power function. This coincides with several other comprehensive studies of SARs at different grain sizes and for different taxa, thus supporting the general appropriateness of the power function for modelling species diversity over a wide range of grain sizes. The poor performance of the Michaelis–Menten function demonstrates that richness within plant communities generally does not approach any saturation, thus calling into question the concept of minimal area.
CRIS-Team Scopus Importer:2019-11-01
Keywords: logarithmic function; Michaelis–Menten function; minimal area; nested-plot sampling; nonlinear regression; Palaearctic grassland; plant biodiversity; power law; scaling law; species–area relationship (SAR)

Sponge-microbial build-ups from the lowermost Triassic Chanakhchi section in southern Armenia: Microfacies and stable carbon isotopes - Friesenbichler, Evelyn; Richoz, Sylvain; Baud, Aymon; Krystyn, Leopold; Sahakyan, Lilit; Vardanyan, Sargis; Peckmann, Joern; Reitner, Joachim; Heindel, Katrin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2018)

Sponge Takeover from End-Permian Mass Extinction to Early Induan Time: Records in Central Iran Microbial Buildups - Baud, Aymon; Richoz, Sylvain; Brandner, Rainer; Krystyn, Leopold; Heindel, Katrin; Mohtat, Tayebeh; Mohtat-Aghai, Parvin; Horacek, Micha (Frontiers in Earth Science, 2021)
The end-Permian mass extinction was the most severe biotic crisis in Earth’s history. In its direct aftermath, microbial communities were abundant on shallow-marine shelves around the Tethys. They colonized the space left vacant after the dramatic decline of skeletal metazoans. The presence of sponges and sponge microbial bioherms has largely gone unnoticed due to the sponges’ size and the cryptic method of preservation. In addition to sponge dominated facies recently described in South Armenia and Northwestern Iran, we describe here sponge-microbial bioherms cropping out in two well-known Permian-Triassic boundary localities: the Kuh-e Hambast section, south-east of Abadeh city and the more distal Shahreza section, near Isfahan. In both sections, the extinction horizon is located at the top of an upper Changhsingian ammonoid-rich nodular limestone, called Paratirolites limestone. At Kuh-e Hambast, the overlying decimetric thick shale deposit called “boundary clay,” the latest Permian in age, is conformably overlain by well-dated transgressive basal Triassic platy limestone containing four successive levels of decimeter to meter scale, elongated to form cup-shaped mounds made of branching columnar stromatolites. Sponge fibers from possibly keratose demosponge, are widely present in the lime mudstone matrix. At the Shahreza section, above the extinction level, the boundary clay is much thicker (3 m), with thin platy limestone intervals, and contains two main levels of decimeter to meter scale mounds of digitate microbialite crossing the Permian-Triassic boundary with similar sponge fibers. Three levels rich in thrombolite domes can be seen in the overlying 20 m platy limestone of earliest Triassic age. Sponge fibers and rare spicules are present in their micritic matrix. These sponge fibers and spicules which are abundant in the latest Permian post-extinction boundary clay, followed microbial buildups during the Griesbachian time.
CRIS-Team Scopus Importer:2021-06-18
Keywords: carbonate mounds; end-permian mass extinction; Induan; keratose demosponge; metazoan bioherms

Spumispongia merklei nov. sp. (Porifera) from the Upper Jurassic (South Germany, Swabian Alb, Blautal) - Senowbari-Daryan, Baba; Koch, Roman (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2012)
UnivIS-Import:2017-11-07:Pub.2012.nat.dgeo.IGM.LP.spumis

Spurenlesen in der Vergangenheit - die Burghöhle Wolfsegg als Treffpunkt für Mensch, Höhlenlöwe und Co. - Hilpert, Brigitte (Mitteilungen - Verbandes der Deutschen Hohlen- und Karstforscher, 2023)

Sr/Ca and Ba/Ca ratios support trophic partitioning within a Silurian conodont community from Gotland, Sweden - Terrill, David F.; Jarochowska, Emilia; Henderson, Charles M.; Shirley, Bryan; Bremer, Oskar (Paleobiology, 2022)
Conodonts were a highly diverse and abundant vertebrate group whose fossils are found in marine Paleozoic and Triassic strata around the world. They inhabited environments ranging from lagoons to open oceans and are represented by a wide variety of dental morphologies. Conodonts may have filled many different ecological niches and represent a significant proportion of nekton before the Devonian. Despite this, very little is known about trophic ecology of conodonts. While morphological diversity suggests a complex trophic structure within conodont communities, there is little evidence to support dietary niche partitioning among conodonts. We tested the hypothesis that individual conodont taxa occupied different trophic niches, using Sr/Ca and Ba/Ca ratios preserved in the dental elements of assemblages from Silurian strata of Gotland, Sweden. Sr/Ca and Ba/Ca have been shown to vary in vertebrate skeletal tissues depending on trophic positioning, although biological and environmental conditions can affect these ratios. Environmental influences were minimized by examining entire conodont communities from a tropical epeiric sea and by measuring strontium isotope ratios using thermal ionization mass spectrometry in the most metropolitan taxon (Ozarkodina confluens). Composition of white matter, a tissue unique to conodonts, was also analyzed using microprobe analysis, revealing significantly lower Sr concentrations than in surrounding lamellar tissue, suggesting taxon-specific histology should be considered when analyzing conodonts for geochemical data. Excluding taxa with highly variable quantities of white matter, the results show that each taxon preserves different Sr/Ca and Ba/Ca ratios with limited overlap, indicating variation in trophic positioning.
CRIS-Team Scopus Importer:2022-04-29

Stable carbon and oxygen isotope geochemistry as provenance indicator for the picture stones on Gotland (Sweden) - Hänsel, Patrick; Oehrl, Sigmund; Ideström, Lena; Widerström, Per; Reddin, Carl James; Munnecke, Axel (GFF, 2023)
The picture stones from Gotland are one of the most famous and exceptional groups of monuments known from Swedish Prehistory. These carved memorial stones and their extraordinarily rich imagery are a unique source for the study of Late Iron and Viking Age culture and in particular Scandinavian pre-Christian religions. The Gotlandic picture stones are mainly made from the thickly layered limestones surrounding the reefs and bioherms of Gotland’s carbonate platform from the middle part of the Silurian (latest Llandovery to Ludlow, Telychian–Ludfordian). However, the exact origins of the picture stones’ raw materials on Gotland have remained undetermined. In this paper, we investigate the geological origin of the raw material by isotope geochemistry. Whereas the oxygen (δ18O) and strontium isotope ratio (87Sr/86Sr) were strongly altered by diagenesis the carbon isotope ratio (δ13C) is quite stable. Because the different geological units on Gotland show specific isotope signatures, the δ13C values from picture stones can be used to assign them to the respective geological unit, and thus to the source area of the raw material. This also allows for an estimation of transport distance minima between the raw material source area and the find place of each sampled picture stone. Most of the picture stones seem to be produced from local material with short transport distances, less than 10 km and only a few were transported at a far distance exceeding 10 km. In summary, the transport distance was dependent mostly on the local availability of picture-stone-suitable rocks.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Carbon isotopes; Gotland; Iron Age; oxygen isotopes; picture stones; strontium isotopes; transport distances

Stable carbon isotope development and sea-level changes during the Late Ludlow (Silurian) of the Łysogóry region (Rzepin section, Holy Cross Mountains, Poland) - Kozłowski, Wojciech; Munnecke, Axel (Facies, 2010)
The Ludlow deposits of the Winnica Formation in the Rzepin section (Holy Cross Mountains, Poland) have been studied with respect to their facies evolution and stable carbon isotope ratios from whole-rock samples. The C-isotope curve of the Rzepin section records a distinct positive excursion with maximal values of +8.9‰. A Late Ludlow positive isotope excursion is known from different paleocontinents and thus is regarded as a global isotope event. The presence of the event allows for a chemostratigraphic correlation of the Rzepin profile with the classical, biostratigraphically well-dated Gotland section. The Ludlow deposits of the Holy Cross Mountains are interpreted in terms of sea-level changes during the isotope excursion. Because the Rzepin and Gotland sections are positioned on the opposite sides of the same foreland basin, a comparison of their sequence stratigraphy allows to test the regularities of the sea-level changes on the shelf of Baltica. In the present paper, a modified view of the recently published sequence stratigraphy of the Gotland succession is presented. Our results indicate that the positive Ludlow δC excursion is connected with prolonged low-stand conditions with small, internal transgressive pulses. © 2010 Springer-Verla
Keywords: C-isotope excursion; Gotland; Holy Cross Mountains; Ludlow; Poland; Sea-level changes; Upper Silurian

Stable carbon isotope stratigraphy in the Ordovician of South China - Munnecke, Axel; Zhang, Yuandong; Xiao, Liu; Cheng, Junfeng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
About 500 samples from 11 Ordovician sections in South China have been analysed for their δC composition. Four sections are located in the Yangtze platform region, the remaining seven sections in the Jiangnan slope region. The sections span more or less the entire Ordovician, but the sample resolution in its lower part (Tremadocian to Dapingian) is lower than in its upper part (Darriwilian to Hirnantian). Overall, the data show a good correlation with the published global isotope curve. At the Cambrian-Ordovician boundary positive values are observed. In the succeeding Tremadocian the values decrease and remain negative into the early Floian. In the late Floian, the values increase to slightly positive. The correlation of Dapingian rocks between the Yangtze and the Jiangnan regions is somewhat problematic which might be due to high siliciclastic input in the Yangtze section. In the Darriwilian a small positive excursion is observed in the Yangtze platform area, however, it is missing in the Jiangnan slope area. This excursion probably correlates with the mid-Darriwilian excursion (MDICE) reported from Baltoscandia. Both chemostratigraphy and conodont biostratigraphy indicate a possible gap between the Shihtzupu Formation and the Pagoda Formation, i.e. most of the Sandbian is probably not represented in the Upper Yangtze region. The earliest Katian is characterised by a pronounced positive excursion correlating with the well-known global Guttenberg excursion (GICE). In the late Katian at least one additional positive excursion was determined. The precise biostratigraphy, however, is not clear, and therefore it is not known which of the known four to five remaining Katian δC excursions identified in Baltica correlate(s) with the one(s) observed in the present study, and further biostratigraphic study is required. The lower part of the Hirnantian excursion (HICE) is probably not preserved, with only small remnants of the HICE observed near the base of the Kuanyinchiao Bed. © 2011 Elsevier B.
Keywords: Graptolites; Ordovician; South China; Stable carbon isotopes; Stratigraphy

Stable isotope signatures of Middle Paleozoic ahermatypic rugose corals - deciphering vital effects, alteration patterns, and palaeoecological implications - Jakubowicz, Michal; Berkowski, Blazej; López Correa, Matthias; Jarochowska, Emilia; Joachimski, Michael; Belka, Zdzislaw (PLoS ONE, 2015)
This study investigates stable isotope signatures of five species of Silurian and Devonian deep-water, ahermatypic rugose corals, providing new insights into isotopic fractionation effects exhibited by Palaeozoic rugosans, and possible role of diagenetic processes in modifying their original isotopic signals. To minimize the influence of intraskeletal cements on the observed signatures, the analysed specimens included unusual species either devoid of large intraskeletal open spaces ('button corals': Microcyclus, Palaeocyclus), or typified by particularly thick corallite walls (Calceola). The corals were collected at four localities in the Holy Cross Mountains (Poland), Mader Basin (Morocco) and on Gotland (Sweden), representing distinct diagenetic histories and different styles of diagenetic alteration. To evaluate the resistance of the corallites to diagenesis, we applied various microscopic and trace element preservation tests. Distinct differences between isotopic compositions of the least-altered and most-altered skeleton portions emphasise a critical role of material selection for geochemical studies of Palaeozoic corals. The least-altered parts of the specimens show marine or near-marine stable isotope signals and lack positive correlation between δ13C and δ18O. In terms of isotopic fractionation mechanisms, Palaeozoic rugosans must have differed considerably from modern deep-water scleractinians, typified by significant depletion in both 18O and 13C, and pronounced δ13C-δ18O co-variance. The fractionation effects exhibited by rugosans seem similar rather to the minor isotopic effects typical of modern non-scleractinian corals (octocorals and hydrocorals). The results of the present study add to growing evidence for significant differences between Scleractinia and Rugosa, and agree with recent studies indicating that calcification mechanisms developed independently in these two groups of cnidarians. Consequently, particular caution is needed in using scleractinians as analogues in isotopic studies of extinct coral lineages. Answering some of the pertinent palaeoecological questions, such as that of the possibility of photosymbiosis in Palaeozoic corals, may not be possible based on stable isotope data.
UnivIS-Import:2015-10-26:Pub.2015.nat.dgeo.IGM.LP.stable

Stable isotopes (δ18O and δ13C), trace and minor element compositions of Recent scleractinians and Last Glacial bivalves at the Santa Maria di Leuca deep-water coral province, Ionian Sea - López Correa, Matthias; Montagna, Paolo; Taviani, Marco; Vendrell-Simón, Begona; McCulloch, Malcolm (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2010)
The aragonitic skeletons of bathyal cold-water corals have a high potential as geochemical in situ archives for paleoceanography. Oxygen isotopes and stable carbon isotopes (δ18O and δ13C) have been analyzed, as well as trace and minor element compositions (e.g. Mg/Ca, Sr/Ca, U/Ca, B/Ca and P/Ca) in Lophelia pertusa, one of the most important frame-builders at the Santa Maria di Leuca (SML) deep-water coral hotspot in the Central Mediterranean. The Apulian Bank is swept by strong currents of the Adriatic Deep Water Outflow. The temperature of 13.9 °C is the highest temperature recorded for L. pertusa and provides an important end-member of environmental conditions for geochemical analyses on living Atlantic and Mediterranean cold-water corals. Temperature and salinity (38.77 PSU) are stable throughout the year, and thus virtually no changes should be observed in the stable oxygen isotope signal-if the coral precipitates its skeleton in equilibrium with seawater. We measured various marine properties, such as the seawater oxygen isotope composition (δ18Osw), stable carbon isotope composition (δ13CDIC) of dissolved inorganic carbon (DIC), and dissolved inorganic nutrient concentrations (PO4, NO3, NO2, NH3 and SiO2). Bottom water at the coral sites shows a mean oxygen isotope composition of 1.47‰ δ18Osw-VSMOW, and δ13CDIC showed a mean of 1.1‰ VPDB. A section of a living L. pertusa with a thick theca calcification was probed with a Merchantek MicroMill at a high spatial sampling resolution with 10 samples per 1 mm. This reduced the signal-smoothing inherent to conventional sampling. The δ18Oag of coral aragonite ranges between -2.0‰ and +2.8‰ VPDB and the δ13Cag ranges between -7.77‰ and +1.47‰ VPDB. The Gaussian data distribution for both parameters, including heavy equilibrium values, suggests the completeness of the captured isotopic variability. The strict linear correlation of δ13C and δ18O displays a strong 'kinetic' vital effect. The intercept of the δ13C/δ18O correlation line with the δ13CDIC-composition permits recognition of δ18O equilibrium values of aragonite and thus reconstruction of water temperatures despite strong disequilibrium precipitation. Since the environmental parameters (T, S and δ18Osw) are stable, the entire isotopic signal of the coral must be driven by biological fractionation and might reflect growth speed variations, potentially related to pH variations and changes in the saturation state of the calcifying fluid or seasonally varying nutrient availability. Laser ablation tracks show a trace element composition dependent to microstructural zones (fibrous aragonite vs. centres of calcification). The parabolic relation of the classical temperature proxies Mg/Ca and U/Ca point to trace element vital effects, rendering them unreliable in L. pertusa. The P/Ca ratio shows similar values as Desmophyllum dianthus, for which a linear dependence with seawater phosphate (DIP) has been previously demonstrated. Consequently L. pertusa might be an additional nutrient recorder at bathyal depths. From the same site we also analysed the stable isotopic composition of the Last Glacial pectinid bivalve Pseudamussium peslutrae, which has been radiocarbon-dated (AMS-14C) at 26.3 ka 14C yr BP. The isotope values of the shell calcite document a strongly differing glacial temperature-salinity regime preceding the Holocene coral growth above a prominent hiatus. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.stable
Keywords: Cold-water corals; Lophelia pertusa; Stable isotopes; Trace elements; Vital effects

Stable Sr-isotope, Sr/Ca, Mg/Ca, Li/Ca and Mg/Li ratios in the scleractinian cold-water coral Lophelia pertusa - Raddatz, Jacek; Liebetrau, Volker; Rüggeberg, Andres; Hathorne, Ed; Krabbenhöft, André; Eisenhauer, Anton; Böhm, Florian; Vollstaedt, Hauke; Fietzke, Jan; López Correa, Matthias; Freiwald, André; Dullo, Wolf-Christian (Chemical Geology, 2013)
The aragonitic skeletons of scleractinian cold-water corals can serve as valuable archives in paleoceanographic studies. The potential of δ88/86Sr, Sr/Ca, Mg/Ca, Li/Ca and Mg/Li ratios of the cold-water coral Lophelia pertusa to record intermediate water mass properties has been investigated. Here we used samples from several locations along the European continental margin spanning a large temperature range from 6 to 14°C. Stable strontium isotope measurements were carried out with the recently developed double spike TIMS technique and our results differ from those obtained with less precise methods. In contrast to the strong positive relationship with temperature of previous studies, our results suggest that δ88/86Sr measured in scleractinian cold-water corals is not controlled by seawater temperature, but reflects the Sr isotopic composition of seawater with an offset of δ88/86Sr=-0.196‰.As found in previous studies, the elemental ratios Sr/Ca, Li/Ca and Mg/Li measured in corals are significantly related to water temperature and do not correlate with salinity. Moreover, Sr/Ca ratios in L. pertusa display the expected inverse correlation with temperature. However, the variance in the Sr/Ca data severely limits the accuracy of paleotemperature estimates. The Li/Ca and Mg/Ca ratios reveal other influences besides temperature such as pH and/or growth or calcification rate. However, corresponding Mg/Li ratios in L. pertusa are more tightly related to temperature as they remove these secondary effects. In particular, the Mg/Li ratio in L. pertusa may serve as a new promising paleotemperature proxy for intermediate water masses. Our dataset represents the most extensive geochemical examination of L. pertusa to date, revealing a temperature sensitivity of 0.015. mol/mmol/°C for Mg/Li. However, using this temperature dependence and the precision of 5.3% (2SD) only temperature variations larger than . 1.5°C can be resolved with 95% confidence. © 2013 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.temper
Keywords: Cold-water corals; Lophelia pertusa; Mg/Li; Paleotemperature proxy; Sr/Ca; Stable strontium isotopes

Statistical independence of escalatory ecological trends in Phanerozoic marine invertebrates - Kießling, Wolfgang; et al. (Science, 2006)
Ecological interactions, such as predation and bioturbation, are thought to be fundamental determinants of macroevolutionary trends. A data set containing global occurrences of Phanerozoic fossils of benthic marine invertebrates shows escalatory trends in the relative frequency of ecological groups, such as carnivores and noncarnivorous infaunal or mobile organisms. Associations between these trends are either statistically insignificant or interpretable as preservational effects. Thus, there is no evidence that escalation drives macroecological trends at global and million-year time scales. We also find that taxonomic richness and occurrence data are cross-correlated, which justifies the traditional use of one as a proxy of the other.
UnivIS-Import:2015-04-14:Pub.2006.nat.dgeo.IGM.LP.statis

Stenolaemate bryozoans from the Graham Formation, Pennsylvanian (Virgilian) at Lost Creek Lake, Texas, USA - Ernst, Andrej; Claußen, Anna Lene; Seuß, Barbara; Wyse Jackson, Patrick (Palaeontologia Electronica, 2022)

Stratigraphical and δ13C records of Permo-Carboniferous platform carbonates, South China: Responses to late Paleozoic icehouse climate and icehouse-greenhouse transition - Liu, Chao; Jarochowska, Emilia; Du, Yuansheng; Vachard, Daniel; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Little attention has been focused on the stratigraphical imprints of the Late Paleozoic Ice Age on the equatorial eastern Paleo-Tethys. An integrated study of biostratigraphy, microfacies, and stable carbon isotope stratigraphy was carried out on Pennsylvanian-middle Guadalupian carbonates of the Gongchuan section in the Bama Platform, South China. It records seven cooling and two warming pulses in the pre-Kungurian interval, comparing with ice-proximal stratigraphical records and far-field indirect proxies in lower latitudes. A Kungurian negative δC excursion (from +4.4‰ at the base of the Kungurian to +1.6‰) recorded only in the subequatorial belt is documented here. It is followed by a global positive δC trend reaching +5.3‰ near the Cisuralian-Guadalupian boundary. Seven third-order shallowing-upward cycles are reported for the first time from the Kungurian succession. The duration of each cycle is estimated to ca. 1myr. These cycles are interpreted as being of glacioeustatic origin and mainly driven by long-period modulations of obliquity ( 1.2myr) under major pCO decreasing condition. This interpretation is supported by recent climate-ice sheet modeling and Cenozoic glaciation studies, which argue that astronomical forcing will be amplified by large-magnitude perturbations in the carbon cycle, when only localized ice-centers persist. Our results emphasize the need for integration of sedimentological and paleoclimatological proxies in elucidating the dynamics of the deglacial phases of the Late Paleozoic Ice Ag
Keywords: Carbon isotope; Kungurian; LPIA; Orbital forcing; Shallowing-upward cycles

Stratigraphic ranking of selected invertebrate fossils: A quantitative approach at different temporal and geographic scales - Abdelhady, Ahmed; Seuß, Barbara; Hassan, Hatem (Palaeontologia Electronica, 2019)
Fossil groups are used for biochronological dating of rocks for decades. This manuscript presents a quantitative approach to appraise and compare the quality of selected taxa as biostratigraphic markers. Based on species occurrence of ammonites, bivalves, and planktic and benthic foraminifers we evaluate the potential of these to rank them quantitatively. The spatiotemporal analyses of occurrence data (species duration, geographic range) were integrated in results of the Unitary Association method, which measures superpositional contradictions in addition to the generation of a number of UAs. The results indicate that Jurassic ammonites have the lowest species duration, and that the majority of species is confined to a single UA-zone. Additionally, ammonites have the lowest numbers of contradicted bio-events. However, planktic foraminifers are more valuable at least in the Cenozoic as they have a high geographic reproducibility and diversity, and higher ISP values. The bivalves and benthic foraminifers both show longer average species durations and more superpositional contradictions per species. Therefore, their biostratigraphic potential is more limited at an interregional scale. The shorter species durations of ammonites and planktic foraminifers in the studied sections can be attributed to their higher extinction rates. As an advantage to simple spatio-temporal analyses, the UA-method can accurately assess the stratigraphic potential of a given taxonomic group. The results obtained herein indicate that the life-habit has direct impact on the species duration and thus, the stratigraphic potential of the fossil groups. Based on the results achieved from this study, an index for ranking fossil groups (Index of Stratigraphic Potential ‘ISP’) is introduced.<br

Strengthening confidence in climate change impact science - O'Connor, Mary; Holding, Johnna; Kappel, Carrie; Duarte, C. M.; Brander, K.; Brown, C. J.; Bruno, J. F.; Buckley, L.; Burrows, M. T.; Halpern, B. S.; Kießling, Wolfgang; Moore, P.; et al. (Global Ecology and Biogeography, 2015)
Keywords: Abundance; Attribution; Climate change; Distribution; Hypothesis; Impacts; Marine; Phenology; Scientific method; Time series

Stromatoporoid-coral reefs and platform deposits from the Silurian of Gotland - Munnecke, Axel (Mémoires du Muséum national d'Histoire naturelle, 2007)
Keywords: Stromatoporoids; corals; reefs; platform deposits; Silurian; Gotland

Structural and elemental analysis of the freshwater, low-Mg calcite coralline alga Pneophyllum cetinaensis - Ragazzola, Federica; Kolzenburg, Regina; Zekonyte, Jurgita; Teichert, Sebastian; Jiang, Chulin; Žulevíc, Ante; Caragnano, Annalisa; Falace, Annalisa (Plants, 2020)

Structural and geochemical assessment of the coralline alga Tethysphytum antarcticum from Terra Nova Bay, Ross Sea, Antarctica - López Correa, Matthias; Teichert, Sebastian; Ragazzola, Federica; Cazorla Vázquez, Salvador; Engel, Felix; Hurle, Katrin; Mazzoli, Claudio; Kuklinski, Piotr; Raiteri, Giancarlo; Lombardi, Chiara (Minerals, 2023)
Crustose coralline algae (CCA) occur from the tropics to the poles in photic benthic environments. Here, we report on some of the world’s southernmost and coldest CCA sites in Terra Nova, Ross Sea, Antarctica at 74°41′ S. The recently described red alga Tethysphytum antarticum is investigated for its skeletal architecture, its mineralogical and geochemical composition, as well as for its taxonomic classification. A phylogenetic analysis based on molecular genetics and the sequencing of the photosystem II protein D1 (psbA) gave a perfect match with T. antarcticum. Histological sections and micro-CT-scans provide new diagnostic details for the conceptacles (the reproductive organs of the alga). X-ray diffractometry and electron-microprobe measurements yielded a clear high-Mg calcite ( 8 mol%) composition of the skeletal parts. Detailed back-scattered electron imaging of polished petrographic thin sections revealed a two-layered thallus (vegetative plant tissue), comprising an organic-rich irregularly calcified basal layer with rectangular cells, overlain by the main thallus. Elemental maps show relatively increased sulphur in the basal layer, clearly tied to organic cell walls. MgCO3 and SrCO3 were targeted with semiquantitative elemental mappings and in an ontogenetic quantitative spot transect. Compared with temperature (−1.95 °C to +1.08 °C), the MgCO3 (mol%) reflects this world’s coldest CCA site temperature with the lowest MgCO3 content of 7.9 ± 1.6 mol%. The along transect variability, however, shows with 6 mol% a larger MgCO3 variability than expected for the 3 °C intra-annual temperature amplitude in Terra Nova Bay. This implies that in low amplitude settings the biomineralisation control on Mg/Ca ratios can outcompete its temperature sensitivity. Mark-recapture studies, next to the environmental logger station La Zecca are suggested, to perform a detailed growth rate and biomineralisation quantificatio
Keywords: crustose coralline algae; Antarctica; taxonomy; phylogeny; thallus structure; biomineralization; geochemistry; climate change

Studies of the stability, nucleophilic substitution reactions, DNA/BSA interactions, cytotoxic activity, DFT and molecular docking of some tetra- and penta-coordinated gold(iii) complexes - Radisavljevic, Snezana; Kesic, Ana Dekovic; Cocic, Dusan; Puchta, Ralph; Senft, Laura; Milutinovic, Milena; Milivojevic, Nevena; Petrovic, Biljana (New Journal of Chemistry, 2020)
Two gold(iii) complexes, square-planar [Au(DPP)Cl-2](+)(1) and distorted square-pyramidal [Au(DMP)Cl-3] (2) (where DMP = 2,9-dimethyl-1,10-phenanthroline and DPP = 4,7-diphenyl-1,10-phenanthroline), were studied by different experimental methods. Their stability in water and in buffer solution (25 mM Hepes, 30 mM NaCl, pH = 7.2) was investigated by UV-Vis spectroscopy while their redox stability is confirmed by CV. Substitution reactions between complexes1and2, and biologically relevant ligands, such as thiourea (Tu), guanosine-5 '-monophosphate (5 '-GMP), glutathione (GSH) andl-methionine (l-Met), were studied by a stopped-flow technique, under the pseudo-first order conditions as a function of ligand concentration and temperature. According to the values of the activation parameters, all studied reactions followed an associative substitution mechanism. DNA binding studies of complexes1and2were performed by UV-Vis and fluorescence spectroscopy and viscosity measurements, as well as interactions with bovine serum albumin (BSA). Density functional theory (DFT) was implemented in order to analyse the wave function of the optimized structures to get better insight into the binding interactions between the inert ligands and gold(iii) center. The experimental results of binding studies with DNA and BSA were simulated and compared by performing a molecular docking study. All results demonstrate the strong connection between the reactivity of the complexes toward biologically important targets and their structural and electronic characteristics. The cytotoxic activity of complexes1and2against different cell lines (MDA-MB-231, HCT-116, and HaCaT) was evaluated 24 and 72 h after treatments. The results indicate reduced viability of cell lines in a time- and dose-dependent manner.
CRIS-Team WoS Importer:2020-07-24

Study on a fossil nautiloid – surprising insights - Seuß, Barbara (Annual Meeting of the Paläontologische Gesellschaft, 2012)
The Buckhorn Asphalt Quarry in Oklahoma, USA, yields a Desmoinesian (Upper Carboniferous) faunal assemblage of outstanding preservation caused by synsedimentary or contemporary impregnation of sediments and fauna with hydrocarbons. These hydrocarbons prevented diagenetic processes to a high degree. The faunal assemblage evolved in a (sub)tropical shallow marine setting and is, with more that 160 reported species, one of the most diverse Paleozoic faunas known to date. The succession is strongly dominated by molluscs, i.e., gastropods, cephalopods, and bivalves, accompanied by e.g., fusulinids, ostracods, echinoderms, and bryozoans. The sediments are mainly mixed siliciclastic-carbonatic and exhibit a single cycle of trans- and regression, with cephalopod-dominated sediments ("cephalopod coquina") representing the deepest marine deposits. Two cephalopod shell remains from the cephalopod coquina were selected for a detailed isotope study (O, C). One shell remain derives from a so far unidentified specimen, the second one from an orthoconic nautiloid which was tentatively assigned to Hebetorthoceras unicamera. Hebetorthoceras is characterized by preservation of two chambers of the phragmocone with nicely preserved cameral and siphuncular deposits. Before samples were prepared the shell remains were intensively studied by using SEM, EDX, XRD-GADDS, and by a series of thin sections. As expected, original shell microstructure and material were still preserved accompanied by parts influenced by diagenetic alteration. Anyhow, both altered and unaltered shell material and both, cameral deposits and shells were sampled with high resolution. Primary isotope signals were used to recalculate local paleotemperatures (unidentified remain: 28-31°C; Hebetorthoceras: 14-15°C) for the sea covering the area of the Buckhorn Asphalt Quarry. Samples exhibiting diagenetic alteration were used to reconstruct diagenetic pathways within the cephalopod remains. So far so good, if there weren't two distinct oval marks on the outside of Hebetorthoceras and the rather abnormal formation and mineralogy of the cameral deposits of this specific specimen. In a subsequent study both, the oval marks and the cameral deposits were examined and it turned out, that a) Hebetorthoceras was victim of a predator, b) this attack was sublethal, c) the specimen was able to precipitate further cameral deposits after the assault, d) it precipitated high magnesium-calcitic cameral deposits during lifetime, and e) the HMC was not a reaction to the heavy injury caused by the attack, but was even formed before. Please download the supplementary material for details on this presented stud

Subarctic Holocene climatic and oceanographic variability in Stjernsund, Northern Norway: evidence from benthic foraminifera and stable isotopes - Joseph, Nina; López Correa, Matthias; Schönfeld, Joachim; Rüggeberg, Andres; Freiwald, André (Boreas, 2013)
A high-resolution record, covering 9.3-0.2ka BP, from the sub-arctic Stjernsund (70°N) was studied for benthic foraminiferal faunas and stable isotopes, revealing three informally named main phases during the Holocene. The Early- to Mid-Holocene (9.3-5.0ka BP) was characterized by the strong influence of the North Atlantic Current (NAC), which prevented the reflection of the Holocene Climatic Optimum (HCO) in the bottom-water temperature. During the Mid-Holocene Transition (5.0-2.5ka BP), a turnover of benthic foraminiferal faunas occurred, Atlantic Water species decreased while Arctic-Polar species increased, and the oxygen isotope record showed larger fluctuations. Those variations correspond to a period of global climate change, to spatially more heterogeneous benthic foraminiferal faunas in the Nordic Seas region, and to regionally diverging terrestrial temperatures. The Cool Late Holocene (2.5-0.2ka BP) was characterized by increased abundances of Arctic-Polar species and a steady cooling trend reflected in the oxygen isotopes. In this period, our record differs considerably from those on the SW Barents Sea shelf and locations farther south. Therefore, we argue that regional atmospheric cooling triggered the late Holocene cooling trend. Several cold episodes centred at ∼8.3, ∼7.8, ∼6.5, ∼4.9, ∼3.9 and ∼3.3ka BP were identified from the benthic foraminiferal faunas and the δ18O record, which correlated with marine and atmospherically driven proxy records. This suggests that short-term cold events may result from reduced heat advection via the NAC or from colder air temperatures. © 2012 The Authors. Boreas © 2012 The Boreas Collegium.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.subarc

Survivorship dynamics of the flora of Devonian Angarida - Dowding, Elizabeth; Akulov, Nikolay Ivanovich; Mashchuk, Irina Mikhailovna (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2023)
Devonian plants in Siberia present protracted pioneer succession. Research into the survivorship dynamics of early plant communities upon the palaeocontinent Angarida have demonstrated that transgression and volcanogenic nutrient influx were key to the survival of colonizing plants. Taxic proportions show that migrating taxa entered Angarida from the southwest, Kuznetsk and Minusinsk basins, dispersing across the continent in waves through central areas northwards. The patterns of dispersal are consistent throughout the Devonian. Increased nutrient load from the active pulses of the Viluy-Yakutsk Large Igneous Province, biogeomorphic ecosystem engineering and the increased biomass of Angaridan plants are assisted by Late Devonian transgression. These cumulative factors can be linked to the Late Devonian marine extinctions observed in Siberia.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Devonian; Large Igneous Province; phytogeography; Siberia

Sweet home Lophelia: A multicolour journey into the microcosm of bioeroders from the Propeller Mound, Porcupine Seabight - Beuck, Lydia; Schulbert, Christian; Freiwald, André (Erlanger Geologische Abhandlungen, Sonderband 4, 2003)
Bioerosion (Neumann, 1966) describes the disintegration processes of hard substrates such as calcareous skeletons through the activity of organisms by mechanical removal of carbonates (bioabrasion) or by chemical dissolution (biocorrosion) and is a well-known process in the alteration of shallow-water coral reefs. Endolithic organisms live within the skeleton either for protection or nourishment. The different bioerosional processes result in a destruction of reefal frameworks. The study of these ichnocoenoses (endolithic trace communities) allows to reconstruct (paleo-)environments and applicable depth zonations of neritic environmental settings through the Phanerozoic era. The ichnodiversity in the course of time also forms integrals for the understanding of the longevity and fossilisation potential and will lead to the definition of ecologic "health conditions" of deep-water corals for a rapid large-scale assessment. In this presentation, the prevalent aphotic bioeroder community found within the skeleton of the cosmopolitan coral Lophelia pertusa from the Propeller Mound, Porcupine Seabight, sampled in 629 to 780 m water depth, is demonstrated using the vacuum-cast-embedding method with subsequent SEM analysis: Shown are coloured SEM pictures of resin casts with an accentuation of different boring organism group
Keywords: Lopheloa; Bioerosion; Propeller Mound; Porcupine Seabight

Synthesis of Camphor-Derived Bis(pyrazolylpyridine) Rhodium(III) Complexes: Structure-Reactivity Relationships and Biological Activity - Petrovic, Angelina; Milutinovic, Milan M.; Petri, Edward T.; Zivanovic, Marko; Milivojevic, Nevena; Puchta, Ralph; Scheurer, Andreas; Korzekwa, Jana; Klisuric, Olivera R.; Bogojeski, Jovana (Inorganic Chemistry, 2019)
Two novel rhodium(III) complexes, namely, [Rh III (X)Cl 3 ] (X = 2 2,6-bis((4S,7R)-7,8,8-trimethyl-4,5,6,7-tetrahydro-1H-4,7-methanoindazol-3-yl)pyridine or 2,6-bis((4S,7R)-1,7,8,8-tetramethyl-4,5,6,7-tetrahydro-1H-4,7-methanoindazol-3-yl)pyridine), were synthesized from camphor derivatives of a bis(pyrazolylpyridine), tridentate nitrogen-donor chelate system, giving [Rh III (H 2 L∗)Cl 3 ] (1a) and [Rh III (Me 2 L∗)Cl 3 ] (1b). A rhodium(III) terpyridine (terpy) ligand complex, [Rh III (terpy)Cl 3 ] (1c), was also synthesized. By single-crystal X-ray analysis, 1b crystallizes in an orthorhombic P2 1 2 1 2 1 system, with two molecules in the asymmetric unit. Tridentate coordination by the N,N,N-donor localizes the central nitrogen atom close to the rhodium(III) center. Compounds 1a and 1b were reactive toward l-methionine (l-Met), guanosine-5′-monophosphate (5′-GMP), and glutathione (GSH), with an order of reactivity of 5′-GMP > GSH > l-Met. The order of reactivity of the Rh III complexes was: 1b> 1a > 1c. The Rh III complexes showed affinity for calf thymus DNA and bovine serum albumin by UV-vis and emission spectral studies. Furthermore, 1b showed significant in vitro cytotoxicity against human epithelial colorectal carcinoma cells. Since the Rh III complexes have similar coordination modes, stability differences were evaluated by density functional theory (DFT) calculations (B3LYP(CPCM)/LANL2DZp). With (H 2 L∗) and (terpy) as model ligands, DFT calculations suggest that both tridentate ligand systems have similar stability. In addition, molecular docking suggests that all test compounds have affinity for the minor groove of DNA, while 1b and 1c have potential for DNA intercalation.
CRIS-Team Scopus Importer:2019-05-09

Syn-vivo bioerosion of Nautilus by endo- and epilithic foraminiferans (New Caledonia and Vanuatu) - Seuß, Barbara; Wisshak, Max; Mapes, Royal H.; Landman, Neil (PLoS ONE, 2015)
A variety of syn-vivo bioerosion traces produced by foraminiferans is recorded in shells of Nautilus sampled near New Caledonia and Vanuatu. These are two types of attachment scars of epilithic foraminiferans and two forms of previously undescribed microborings, a spiral-shaped and a dendritic one, both most likely being the work of endolithic 'naked' foraminiferans. Scanning electron microscopy of epoxy-resin casts of the latter revealed that these traces occur in clusters of up to many dozen individuals and potentially are substrate-specific. The foraminiferan traces are the sole signs of bioerosion in the studied Nautilus conchs, and neither traces of phototrophic nor other chemotrophic microendoliths were found. While the complete absence of photoautotrophic endoliths would be in good accordance with the life habit of Nautilus, which resides in aphotic deep marine environments and seeks shallower waters in the photic zone for feeding only during night-time, the absence of any microbial bioerosion may also be explained by an effective defence provided by the nautilid periostracum. Following this line of reasoning, the recorded foraminiferan bioerosion traces in turn would identify their trace makers as being specialized in their ability to penetrate the periostracum barrier and to bioerode the shell of modern Nautilus.
UnivIS-Import:2015-07-08:Pub.2015.nat.dgeo.IGM.LP.synviv

Systematic occurrences of malformed (teratological) acritarchs in the run-up of Early Palaeozoic δ13C isotope excursions - Munnecke, Axel; Delabroye, Aurélien; Servais, Thomas; Vandenbroucke, Thijs R.A.; Vecoli, Marco (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
The Late Ordovician and Silurian are characterised by several strong, global positive δC excursions. Some of them exceed +5‰ and thus belong to the strongest perturbations of the carbon cycle in the Phanerozoic. The onset of the excursions is characterised by extinction and/or turnover events of several groups of marine invertebrates. The causal mechanisms of the carbon cycle perturbations, however, are still unknown and currently a matter of vigorous scientific debate. Our own investigations in the Hirnantian (latest Ordovician) have shown that the onset of the major δC excursion (HICE) is characterised by very high abundances of acritarchs showing abnormal, teratological forms. A critical review of published reports of abnormal acritarchs from the Late Ordovician to Early Devonian, and a correlation of their occurrences with the global stable carbon isotope curve, show that high abundances of teratological forms of acritarchs are often coeval to the run-up of δC excursions. High abundances of teratological forms in modern marine protists are commonly observed in environments with a high degree of environmental stress. In the fossil record, the challenge is to attribute abnormal forms of organisms to specific environmental circumstances. Our study implies that they are somehow related to the global carbon cycle, i.e., to carbon isotopic composition of the ambient sea water, and that they share a common extrinsic cause with the contemporaneous extinction and/or turnover events in other fossil groups. © 2012 Elsevier B.
Keywords: Acritarchs; Anticosti; Gotland; Heavy metals; Ordovician; Silurian; Teratology

System controls of coastal and open ocean oxygen depletion - Pitcher, Grant C.; Aguirre-Velarde, Arturo; Breitburg, Denise; Cardich, Jorge; Carstensen, Jacob; Conley, Daniel J.; Dewitte, Boris; Engel, Anja; Espinoza-Morriberón, Dante; Flores, Georgina; Garçon, Véronique; Graco, Michelle; et al. (Progress in Oceanography, 2021)
The epoch of the Anthropocene, a period during which human activity has been the dominant influence on climate and the environment, has witnessed a decline in oxygen concentrations and an expansion of oxygen-depleted environments in both coastal and open ocean systems since the middle of the 20th century. This paper provides a review of system-specific drivers of low oxygen in a range of case studies representing marine systems in the open ocean, on continental shelves, in enclosed seas and in the coastal environment. Identification of similar and contrasting responses within and across system types and corresponding oxygen regimes is shown to be informative both in understanding and isolating key controlling processes and provides a sound basis for predicting change under anticipated future conditions. Case studies were selected to achieve a balance in system diversity and global coverage. Each case study describes system attributes, including the present-day oxygen environment and known trends in oxygen concentrations over time. Central to each case study is the identification of the physical and biogeochemical processes that determine oxygen concentrations through the tradeoff between ventilation and respiration. Spatial distributions of oxygen and time series of oxygen data provide the opportunity to identify trends in oxygen availability and have allowed various drivers of low oxygen to be distinguished through correlative and causative relationships. Deoxygenation results from a complex interplay of hydrographic and biogeochemical processes and the superposition of these processes, some additive and others subtractive, makes attribution to any particular driver challenging. System-specific models are therefore required to achieve a quantitative understanding of these processes and of the feedbacks between processes at varying scales.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Deoxygenation; Eutrophication; Global warming; Respiration; Stratification; Ventilation

Tales from a shale - taxonomy and analysis of life habits of bivalves from the Pennsylvanian Finis Shale (Virgilian) of North Central Texas - Friedel, Julia C.; Amler, Michael R.W.; Seuß, Barbara (Kölner Forum Geol. Paläont. 23, 2019)

Taphonomic and diagenetic implications of reduction spot formation in Cretaceous red beds from the Jiaolai Basin, Eastern China - Fu, Wenzhao; Turner, Peter; Clements, Thomas; Spencer, Alan R.T.; Yu, Jifeng; Yang, Yu; Guo, Bangjie; Ning, Zhenguo; Zhuo, Xizhun; Riley, Michael S.; Hilton, Jason (Journal of Asian Earth Sciences, 2023)
Green-grey coloured reduction spots are common in continental red beds through geological history and occur in a range of different lithologies and depositional environments, but their timing and mode of formation remain controversial. We investigate the Late Cretaceous to earliest Paleogene Jiaozhou Formation using borehole data from the Jiaolai Basin in Shandong province of eastern China, and consider the distribution, morphology, and geochemistry of reduction spots in these continental red beds to evaluate how the reduction spots formed. Here, we report a novel application of three-dimensional X-ray Computed Tomography (XCT) to analyse reduction spot morphology, composition and density. Our data show that individual reduction spots are spheroidal, tubular or irregular shaped, and often contain small, grey, dark brown or black organic cores, referred to as loci. Typically, reduction spots have a similar chemical composition to the host red beds, but with elevated levels of vanadium (V), lower levels of iron (Fe), and lower density. Isolated, small refractory fossils (e.g., charcoal) in the sediment alongside reduction spots but not within them indicates that microbial decay of organic labile (reactive) tissues in early diagenesis is an important control in reduction spot formation. We propose a new taphonomic model of reduction spot formation: post burial, during the primary sedimentary cycle in the groundwater zone, vanadium is released by intrastratal oxidation of titanomagnetite. Decay of organic matter creates localised reducing conditions resulting in the reduction of Fe3+ and the eventual depletion or removal of the resulting Fe2+ (altering the colour of the reduction spot). Simultaneously, the reduction of V4+ and the consequent lowering of the concentration of V as V2+ minerals occur in the reduction spot, explaining their lower density than the host sediment.
CRIS-Team Scopus Importer:2023-01-20
Keywords: 3D X-ray Computed Tomography analysis; Continental red beds; Diagenesis; Redox; Taphonomy; Vanadium

Taphonomic bias in limestones and marls – a quantitative palaeontological approach to the genesis of limestone-marl alternations - Nohl, Theresa; Munnecke, Axel; Jarochowska, Emilia (87th Annual Conference of the Paläontologische Gesellschaft, 2016)

Taphonomic bias in limestones and marls – a quantitative palaeontological approach to the genesis of limestone-marl alternations - Nohl, Theresa; Munnecke, Axel; Jarochowska, Emilia (8th Meeting on Taphonomy and Fossilization, 2019)

Taphonomy of backshore versus deep-marine collected nautilus macromphalus conchs (New Caledonia) - Seuß, Barbara; Hembree, Daniel I.; Wisshak, Max; Mapes, Royal H.; Landman, Neil (Palaios, 2015)

Taxonomical diversity and palaeobiogeographical affinity of belemnites from the Pliensbachian–Toarcian GSSP (Lusitanian Basin, Portugal) - Costa Rita, Patrícia; Duarte, Luís V.; Weis, Robert; de Baets, Kenneth (Papers in Palaeontology, 2021)
High‐resolution analysis of the late Pliensbachian – early Toarcian belemnite assemblages from the Peniche section (Lusitanian Basin) has enabled, for the first time, recognition of eight taxa of the suborder Belemnitina, previously reported from contemporaneous north‐west Tethyan and Arctic sections. The presence of Bairstowius amaliae sp. nov. in the late Pliensbachian (emaciatum Zone) represents a novelty given that hitherto the genus Bairstowius was known only from late Sinemurian and early Pliensbachian deposits. Additionally, the replacement of Bairstowius amaliae by Catateuthis longiforma, during the latest Pliensbachian, suggests an evolutionary relationship between the two taxa. This relationship suggests a new scenario for the subsequent development of endemic Toarcian Boreal–Arctic faunas, characterized by the occurrence of Catateuthis. Comparison of the Peniche belemnite fauna with coeval faunas from the Mediterranean/Submediterranean and Euro‐Boreal domains indicates taxonomic uniformity during the late Pliensbachian and early Toarcian (emaciatum and polymorphum Zones), in the north‐west Tethys. Despite the lack of a marked taxonomic turnover, the Pliensbachian–Toarcian boundary corresponds to a slight decrease in diversity observed not only in the Lusitanian Basin but also in coeval north‐western European basins. Ordination and cluster analyses indicate that the largest changes in belemnite diversity and palaeogeographical distribution occurred rather during the Toarcian Oceanic Anoxic Event (base of the levisoni Zone). This event is marked by the extinction of taxa, affecting more severely the Mediterranean/Submediterranean domain and resulting in a more pronounced provincial differentiation among north‐western European and Arctic belemnite faunas.<br

Taxonomy and diversity of slit-band gastropods (OrderPleurotomariida) and some slit bearing Caenogastropodafrom the Pennsylvanian of the USA - Karapunar, Baran; Nützel, Alexander; Seuß, Barbara; Mapes, Royal H. (Papers in Palaeontology, 2022)

Taxonomy, palaeoecology and palaeobiogeography of upper Cenomanian (Upper Cretaceous) oysters and plicatulids from southern Algeria - Benyoucef, Madani; Ghenim, Asma-Fethia; Ferre, Bruno; Ayoub-Hannaa, Wagih; Koci, Tomas; Adaci, Mohammed; Guendouz, Mohamed-Lassad; Zaoui, Djamila; Bendella, Mohamed; Bensalah, Mustapha (Historical Biology, 2021)
Palaeontological investigation of four lithostratigraphic sections documenting the upper Cenomanian shallow marine carbonates of three palaeogeographic domains of southern Algeria (western Saharan Atlas, Guir Basin and Tinrhert Hamada) has produced a comprehensive collection of large bivalve assemblages for taxonomic purposes. A first inventory list of late Cenomanian oysters and plicatulids from southern Algeria is now available and consists of 15 taxa as follows: Lopha syphax, Ostreidae gen. et sp. indet., Curvostrea rouvillei, Flemingostreidae gen. et sp. indet., Costagyra olisiponensis, Amphidonta obliquata, Ceratostreon flabellatum, Ilymatogyra africana, Rhynchostreon suborbiculatum, Gyrostrea delettrei, Gyrostrea sp. indet., Pycnodonte (Phygraea) vesicularis vesiculosa, Plicatula (Plicatula.) auressensis, Plicatula (Plicatula) batnensis, and Chondrodonta? sp. indet. These taxa build five distinctive oyster-facies patterns, all purportedly recognisable in the field for stratigraphic assignment and regional correlation. Scarce sclerobiontic assemblage (borings: Entobia, Gastrochaenolites and Oichnus; and epibionts: juvenile oysters, serpulid tubes and Berenicean-type bryozoa) observed within these oyster shell assemblages is also identified, briefly described and adressed. This first taxonomic analysis highlights three main palaeogeographic components within these oyster- and plicatuloid-assemblages: endemic Mediterranean, Tethyan-Atlantic and cosmopolitan taxa. Moreover, the present study on these late Cenomanian oyster assemblages provides a first inventory list and stratigraphical baseline data towards further datation and correlation at the regional scale.
CRIS-Team Scopus Importer:2021-11-05
Keywords: ichnology; Ostreoidea; Plicatuloidea; systematics; taphonomy

Tectonic blocks and molecular clocks - de Baets, Kenneth; Antonelli, Alexandre; Donoghue, Philip C. J. (Philosophical Transactions of the Royal Society B-Biological Sciences, 2016)
This article is part of the themed issue 'Dating species divergences using rocks and clocks'.
Keywords: molecular clock; calibration; fossil record; biogeography; tectonics

Tectonic structures in the Stumsnäs 1 core from the southern Siljan Ring, central Sweden: Ordovician sediments sandwiched between Proterozoic basement slivers. - Arslan, Arzu; Meinhold, Guido; Lehnert, Oliver (Gff, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LG.tecton

Testing for the effects of depositional rates in multiproxy models of environmental and faunal change: the Silurian Lau δ13C excursion - Grohganz, Madleen; Jarochowska, Emilia; Hohmann, Niklas; Munnecke, Axel (11th North American Paleontological Convention, 2019)

Testing the limits of Paleozoic chronostratigraphic correlation via high-resolution (<500 kyr) integrated conodont, graptolite, and carbon isotope (d13C-carb) biochemostratigraphy across the Llandovery-Wenlock (Silurian) boundary: Is a unified Phanerozoic timescale achievable? - Cramer, Bradley D.; Loydell, David K.; Samtleben, Christian; Munnecke, Axel; Kaljo, Dimitri; Maennik, Peep; Martma, Tonu; Jeppsson, Lennart; Kleffner, Mark A.; Barrick, James E.; Johnson, Craig A.; Emsbo, Poul; et al. (Geological Society of America Bulletin, 2010)
<p style="box-sizing: border-box; margin: 0px 0px 1rem; padding: 0px; border: 0px; font-variant-numeric: inherit; font-stretch: inherit; font-size: medium; line-height: 1.7em; font-family: Lato, sans-serif; vertical-align: baseline; color: rgb(51, 51, 51);"> The resolution and fidelity of global chronostratigraphic correlation are direct functions of the time period under consideration. By virtue of deep-ocean cores and astrochronology, the Cenozoic and Mesozoic time scales carry error bars of a few thousand years (k.y.) to a few hundred k.y. In contrast, most of the Paleozoic time scale carries error bars of plus or minus a few million years (m.y.), and chronostratigraphic control better than ±1 m.y. is considered “high resolution.” The general lack of Paleozoic abyssal sediments and paucity of orbitally tuned Paleozoic data series combined with the relative incompleteness of the Paleozoic stratigraphic record have proven historically to be such an obstacle to intercontinental chronostratigraphic correlation that resolving the Paleozoic time scale to the level achieved during the Mesozoic and Cenozoic was viewed as impractical, impossible, or both. <p style="box-sizing: border-box; margin: 0px 0px 1rem; padding: 0px; border: 0px; font-variant-numeric: inherit; font-stretch: inherit; font-size: medium; line-height: 1.7em; font-family: Lato, sans-serif; vertical-align: baseline; color: rgb(51, 51, 51);"> Here, we utilize integrated graptolite, conodont, and carbonate carbon isotope (δ<span style="box-sizing: border-box; margin: 0px 0.2em; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-weight: bold; font-stretch: inherit; font-size: 13px; line-height: inherit; font-family: "Source Sans Pro", sans-serif; vertical-align: baseline; position: relative; top: -0.75em;">13C<sub style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: inherit; font-family: inherit;">carb) data from three paleocontinents (Baltica, Avalonia, and Laurentia) to demonstrate chronostratigraphic control for upper Llandovery through middle Wenlock (Telychian–Sheinwoodian, ∼436–426 Ma) strata with a resolution of a few hundred k.y. The interval surrounding the base of the Wenlock Series can now be correlated globally with precision approaching 100 k.y., but some intervals (e.g., uppermost Telychian and upper Sheinwoodian) are either yet to be studied in sufficient detail or do not show sufficient biologic speciation and/or extinction or carbon isotopic features to delineate such small time slices. Although producing such resolution during the Paleozoic presents an array of challenges unique to the era, we have begun to demonstrate that erecting a Paleozoic time scale comparable to that of younger eras is achievable.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LG.testin
Keywords: chronostratigraphy; Paleozoic; chronostratigraphic correlation; conodont; graptolite; carbon isotope; dC13; stratigraphy; chemostratigraphy; Llandovery; Wenlock; boundary; time scale

Testing the role of biological interactions for the evolution of mid-Mesozoic marine benthic ecosystems - Aberhan, Martin; Kießling, Wolfgang; Fürsich, Franz (Paleobiology, 2006)
Evaluating the relative importance of biotic versus abiotic factors in governing macro-evolutionary patterns is a central question of paleobiology. Here, we analyzed patterns of changes in global relative abundances and diversity of ecological groups to infer the role of biological interactions as driving evolutionary forces in mid-Mesozoic macrobenthic marine ecosystems. Specifically, we tested the hypothesis of escalation, which states that macroevolutionary patterns were controlled by an increasing pressure exerted by enemies on their victims. Associated with evidence of increasing levels of predation and biogenic sediment reworking (bulldozing) is an increasing representation of predation- and disturbance-resistant groups in the fossil record. In particular, we observe increasing proportions of mobile organisms; a decline of vulnerable epifauna living freely on the substrate; and a trend toward infaunalization of the benthos. These trends were most pronounced in the paleotropics, i.e., the region where biological activity is thought to have been highest. The observation that these changes affected several biotic traits and occurred within independent clades argues against the overriding role of a single key adaptive innovation in causing shifts in ecological abundance. Also, changes in the abiotic environment cannot explain these faunal patterns because of lacking cross-correlations with physico-chemical parameters such as global sea level, climate, and seawater chemistry. We conclude that in marine benthic ecosystems of the mid Mesozoic, enemy-driven evolution, or escalation, was a plausible and important factor. © 2006 The Paleontological Society. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2006.nat.dgeo.IGM.LP.testin

Tethysocarnia cautica n. gen. n. sp., a sessile foraminifer from Late Ladinian and Carnian reefs of the western and southern Tethys - Senowbari-Daryan, Baba; Flügel, Erik; Preto, Nereo (Geologica et palaeontologica, 2001)
UnivIS-Import:2017-11-07:Pub.2001.nat.dgeo.IGM.LP.tethys

The apparent exponential radiation of Phanerozoic land vertebrates is an artefact of spatial sampling biases - Close, Roger; Benson, Roger; Alroy, John; Carrano, Matthew; Cleary, Terri; Mannion, Phillip; Dunne, Emma; Uhen, Mark; Butler, Richard (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2020)
There is no consensus about how terrestrial biodiversity was assembled through deep time, and in particular whether it has risen exponentially over the Phanerozoic. Using a database of 60 859 fossil occurrences, we show that the spatial extent of the worldwide terrestrial tetrapod fossil record itself expands exponentially through the Phanerozoic. Changes in spatial sampling explain up to 67% of the change in known fossil species counts, and these changes are decoupled from variation in habitable land area that existed through time. Spatial sampling therefore represents a real and profound sampling bias that cannot be explained as redundancy. To address this bias, we estimate terrestrial tetrapod diversity for palaeogeographical regions of approximately equal size. We find that regional-scale diversity was constrained over timespans of tens to hundreds of millions of years, and similar patterns are recovered for major subgroups, such as dinosaurs, mammals and squamates. Although the Cretaceous/Palaeogene mass extinction catalysed an abrupt two- to three-fold increase in regional diversity 66 million years ago, no further increases occurred, and recent levels of regional diversity do not exceed those of the Palaeogene. These results parallel those recovered in analyses of local community-level richness. Taken together, our findings strongly contradict past studies that suggested unbounded diversity increases at local and regional scales over the last 100 million years.<br

THE APPLICABILITY OF TAPHONOMIC BIAS IN LIMESTONES AND MARLS FOR ASSESSING DIAGENETIC LOSS - Nohl, Theresa; Munnecke, Axel; Jarochowska, Emilia (20th International Sedimentological Congress, 2018)

The biogeographical imprint of mass extinctions - Kocsis, Ádám; Reddin, Carl James; Kießling, Wolfgang (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2018)
Mass extinctions are defined by extinction rates significantly above background levels and have had substantial consequences for the evolution of life. Geographically selective extinctions, subsequent originations and species redistributions may have changed global biogeographical structure, but quantification of this change is lacking. In order to assess quantitatively the bio-geographical impact of mass extinctions, we outline time-traceable bioregions for benthic marine species across the Phanerozoic using a compositional network. Mass extinction events are visually recognizable in the geographical depiction of bioregions. The end-Permian extinction stands out with a severe reduction of provinciality. Time series of biogeographical turnover represent a novel aspect of the analysis of mass extinctions, confirming concentration of changes in the geographical distribution of benthic marine life.
Keywords: benthic; palaeobiology; mass extinctions; bioregions; networks

The Buckhorn Asphalt deposit – An unique fossil Lagerstätte from the Pennsylvanian of Oklahoma - Seuß, Barbara; Nützel, Alexander; Mapes, Royal H.; Yancey, Thomas E. (GSA, 2008)
The Pennsylvanian Buckhorn Asphalt in Southern Oklahoma contains the best-preserved Palaeozoic mollusc fauna in the world. Early impregnation of mixed carbonatic-siliciclastic rocks (mudstones, pack- to grainstones, shell beds, and conglomerates,) with hydrocarbons prevented aragonite destruction (“Impregnation Fossil Lagerstätte”). Exceptional preservation comprises shell microstructures, microornaments and early ontogenetic shells. Most gastropods had planktotrophic larval development indicating a high primary production although the remains of phytoplankton are very rare in Late Palaeozoic deposits. The deposition of the Buckhorn sediments occurred close to a coastal area partly involving mass flow processes (density currents) triggered by storms. Shells of benthic molluscs yield the most diverse known Palaeozoic microboring assemblage, indicating euphotic conditions prior to final deposition. The invertebrate fauna comprises about 155 species and at least 120 genera. The assemblage is strongly dominated by molluscs which is unusual for a Palaeozoic deposit and corroborates that aragonite dissolution produces a major bias in the fossil record. However, most mollusc genera are also known from other Pennsylvanian occurrences (replaced shells). This shows that preservation bias via preferential aragonite dissolution may be overestimate

The Chicxulub asteroid impact and mass extinction at the Cretaceous-Paleogene boundary - Kießling, Wolfgang; et al. (Science, 2010)
The Cretaceous-Paleogene boundary ∼65.5 million years ago marks one of the three largest mass extinctions in the past 500 million years. The extinction event coincided with a large asteroid impact at Chicxulub, Mexico, and occurred within the time of Deccan flood basalt volcanism in India. Here, we synthesize records of the global stratigraphy across this boundary to assess the proposed causes of the mass extinction. Notably, a single ejecta-rich deposit compositionally linked to the Chicxulub impact is globally distributed at the Cretaceous-Paleogene boundary. The temporal match between the ejecta layer and the onset of the extinctions and the agreement of ecological patterns in the fossil record with modeled environmental perturbations (for example, darkness and cooling) lead us to conclude that the Chicxulub impact triggered the mass extinction.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LAG.thechi

The cono-dos and cono-dont's of phosphatic microfossil preparation and microanalysis - Shirley, Bryan; Bestmann, Michel; Jarochowska, Emilia (Micron, 2020)
Scanning electron microscope (SEM) imaging of fossils allows unlocking ultrastructural information about their skeletal tissues, but sample preparation of biominerals forming their skeletons requires time, patience, and knowledge. SEM and associated analytical methods allow the observation of internal microstructure, shedding light on function, growth and chemistry. Sample preparation is the process by which material is fixed within a medium (e.g. epoxy resin), a transect created and surface defects removed. This step is arguably the most important in any SEM-based analysis, allowing for the acquisition of reliable, high quality data sets. When conducting any SEM-based technique, the presence of a flat surface is needed to collect consistent and reliable data. Surfaces with topography will both induce charging effects but will also compromise the reliability of data acquired. Techniques from material science are continuously adapted to palaeontological applications, in particular with respect to calcareous microfossils. However, similar studies have not been extensively conducted on bioapatite, owing in part to the difficulties faced in sample preparation alongside its susceptibility to electron beam damage. This case study focuses on conodonts, a marine vertebrate group ranging from the late Cambrian to the Late Triassic. They have been chosen as a model due to the abundance of material, complexity of internal tissues and previous work focused on histological features. With these phosphatic microfossils, we attempt to outline the process of sample preparation and provide information on how to avoid and overcome common pitfalls.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Conodont; Microanalysis; Preparation; Scanning electron microscopy; Ultrastructure

The Cyclostratigraphy Intercomparison Project (CIP): consistency, merits and pitfalls - Sinnesael, Matthias; De Vleeschouwer, David; Zeeden, Christian; Batenburg, Sietske J.; Da Silva, Anne-Christine; de Winter, Niels J.; Dinarès-Turell, Jaume; Drury, Anna Joy; Gambacorta, Gabriele; Hilgen, Frederik J.; Hinnov, Linda A.; Hudson, Alexander J. L.; et al. (Earth-Science Reviews, 2019)
Cyclostratigraphy is an important tool for understanding astronomical climate forcing and reading geological time in sedimentary sequences, provided that an imprint of insolation variations caused by Earth’s orbital eccentricity, obliquity and/or precession is preserved (Milankovitch forcing). Numerous stratigraphic and paleoclimate studies have applied cyclostratigraphy, but the robustness of the methodology and its dependence on the investigator have not been systematically evaluated. We developed the Cyclostratigraphy Intercomparison Project (CIP) to assess the robustness of cyclostratigraphic methods using an experimental design of three artificial cyclostratigraphic case studies with known input parameters. Each case study is designed to address specific challenges that are relevant to cyclostratigraphy. Case 1 represents an offshore research vessel environment, as only a drill-core photo and the approximate position of a late Miocene stage boundary are available for analysis. In Case 2, the Pleistocene proxy record displays clear nonlinear cyclical patterns and the interpretation is complicated by the presence of a hiatus. Case 3 represents a Late Devonian proxy record with a low signal-to-noise ratio with no specific theoretical astronomical solution available for this age. Each case was analyzed by a test group of 17-20 participants, with varying experience levels, methodological preferences and dedicated analysis time. During the CIP 2018 meeting in Brussels, Belgium, the ensuing analyses and discussion demonstrated that most participants did not arrive at a perfect solution, which may be partly explained by the limited amount of time spent on the exercises (∼4.5 hours per case). However, in all three cases, the median solution of all submitted analyses accurately approached the correct result and several participants obtained the exact correct answers. Interestingly, systematically better performances were obtained for cases that represented the data type and stratigraphic age that were closest to the individual participants’ experience. This experiment demonstrates that cyclostratigraphy is a powerful tool for deciphering time in sedimentary successions and, importantly, that it is a trainable skill. Finally, we emphasize the importance of an integrated stratigraphic approach and provide flexible guidelines on what good practices in cyclostratigraphy should include. Our case studies provide valuable insight into current common practices in cyclostratigraphy, their potential merits and pitfalls. Our work does not provide a quantitative measure of reliability and uncertainty of cyclostratigraphy, but rather constitutes a starting point for further discussions on how to move the maturing field of cyclostratigraphy forward.<br

The Devonian Nekton Revolution - Kießling, Wolfgang; et al. (Lethaia, 2010)
Traditional analyses of Early Phanerozoic marine diversity at the genus level show an explosive radiation of marine life until the Late Ordovician, followed by a phase of erratic decline continuing until the end of the Palaeozoic, whereas a more recent analysis extends the duration of this early radiation into the Devonian. This catch-all approach hides an evolutionary and ecological key event long after the Ordovician radiation: the rapid occupation of the free water column by animals during the Devonian. Here, we explore the timing of the occupation of the water column in the Palaeozoic and test the hypothesis that ecological escalation led to fundamental evolutionary changes in the mid-Palaeozoic marine water column. According to our analyses, demersal and nektonic modes of life were probably initially driven by competition in the diversity-saturated benthic habitats together with the availability of abundant planktonic food. Escalatory feedback then promoted the rapid rise of nekton in the Devonian as suggested by the sequence and tempo of water-column occupation. Devonian, diversity, ecology, food webs, nekton, plankton, radiation. © 2009 The Authors, Journal compilation © 2009 The Lethaia Foundation.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.thedev

The Digital Integrated Stratigraphy Project (DISP) - Munnecke, Axel; Cramer, Bradley D.; Boon, David P.; Kharwat, Ranyah; Aiken, Carlos L.; Schofield, David I. (Bulletin of Geosciences, 2012)
The Digital Integrated Stratigraphy Project (DISP) aims to eliminate the stratigraphical ambiguity associated with sam-ple position within a stratigraphical section. For example, it is often impractical or impossible to compare one author's measured section and data precisely against another author's geographically identical measured section and data due to discrepancies in the measured thicknesses of units, variations in the assignments of litho- and chronostratigraphical terms, and/or the precise line of measured sections between authors. The DISP will provide a solution to this problem by producing a precise 3-D digital rendering of the exposure using Terrestrial Laser Scanning (TLS) LiDAR, Real-Time Kinematic (RTK) Global Navigation Satellite Systems (GNSS), overlain digital photography, and GIS software to pro-duce a cm to mm-scale accurate digital version of a given exposure. Once available online as a permanent web-based digital resource for stratigraphy, researchers will be able to access the program and digital models of scanned exposures where they will have the means to log their sample positions directly onto the digital exposure while in the field, thus allow-ing unambiguous stratigraphical reference for future comparison. The Digital Integrated Stratigraphy Project represents the next generation of stratigraphical standard and can serve as the protocol for the future of high-resolution Palaeozoic Earth history research.
Keywords: GSSP; High-resolution; LiDAR; Palaeozoic; Silurian; Stratigraphy; Telychian

The early diversification of ray-finned fishes (Actinopterygii): hypotheses, challenges and future prospects - Henderson, Struan; Dunne, Emma; Fasey, Sophie A.; Giles, Sam (Biological Reviews, 2022)
Actinopterygii makes up half of living vertebrate diversity, and study of fossil members during their Palaeozoic rise to dominance has a long history of descriptive work. Although research interest into Palaeozoic actinopterygians has increased in recent years, broader patterns of diversity and diversity dynamics remain critically understudied. Past studies have investigated macroevolutionary trends in Palaeozoic actinopterygians in a piecemeal fashion, variably using existing compendia of vertebrates or literature-based searches. Here, we present a comprehensive occurrence-based dataset of actinopterygians spanning the whole of the Palaeozoic. We use this to produce the first through-Palaeozoic trends in genus and species counts for Actinopterygii. Diversity through time generally tracks metrics for sampling, while major taxonomic problems pervading the Palaeozoic actinopterygian record obscure diversity trends. Many described species are concentrated in several particularly problematic 'waste-basket' genera, hiding considerable morphological and taxonomic diversity. This taxonomic confusion also feeds into a limited understanding of phylogenetic relationships. A heavy sampling bias towards Europe and North America exists in both occurrence databases and available phylogenetic matrices, with other regions underrepresented despite yielding important data. Scrutiny of the extent to which spatial biases influence the actinopterygian record is lacking, as is research on other forms of bias. Low richness in some time periods may be linked to geological biases, while the effects of taphonomic biases on Palaeozoic actinopterygians have not yet been investigated. Efforts are already underway both to redescribe poorly defined taxa and to describe taxa from underrepresented regions, helping to address taxonomic issues and accuracy of occurrence data. New methods of sampling standardisation utilising up-to-date occurrence databases will be critical in teasing apart biological changes in diversity and those resulting from bias. Lastly, continued phylogenetic work will enable the use of phylogenetic comparative methods to elucidate the origins of actinopterygian biogeography and subsequent patterns of radiation throughout their rise to dominate aquatic faunas.
CRIS-Team WoS Importer:2022-10-21

The early Katian (Late Ordovician) reefs near Saku, northern Estonia and the age of the Saku Member, Vasalemma Formation. - Kroger, Bjorn; Hints, Linda; Lehnert, Oliver; Mannik, Peep; Joachimski, Michael (Estonian Journal of Earth Sciences, 2014)
Reefs developed simultaneously during the latest Sandbian/earliest Katian global Guttenberg Isotopic Carbon Excursion (GICE) in several places across Baltoscandia. Latest Sandbian/earliest Katian patch reefs are also described from the Vasalemma Formation of northern Estonia. The Saku Member of the Vasalemma Formation was previously considered as a proximal facies related to the reefs. However, the Saku Member clearly post-dates the GICE interval and ranges from the latest Keila to Rakvere in terms of regional stages. Some small reefs occur in direct proximity to the stratotype of the Saku Member. New δ13C data from the stratotype section and the adjacent reefs indicate that these reefs developed before the deposition of the Saku Member during the GICE interval. The chemostratigraphic data support the hypothesis of a short-time Baltoscandian reef growth event that terminated during the GICE interval.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LG.theear_6
Keywords: Carbon isotopes; Estonia; GICE excursion; Kope excursion; Oandu Stage; Ordovician reefs

The effect of small-scale topography on patterns of endemism within islands - Cutts, Vanessa; Katal, Negin; Löwer, Caroline; Algar, Adam C.; Steinbauer, Manuel; Irl, Severin D. H.; Beierkuhnlein, Carl; Field, Richard (Frontiers of Biogeography, 2019)
Topography influences evolutionary and ecological processes by isolating populations and enhancing habitat diversity. While the effects of large-scale topography on patterns of species richness and endemism are increasingly well documented, the direct effect of local topography on endemism is less understood. This study compares different aspects of topographic isolation, namely the isolating effect of deep barrancos (ravines) and the effect of increasing isolation with elevation in influencing patterns of plant endemism within a topographically diverse oceanic island (La Palma, Canary Islands, Spain). We collected plant presence-absence data from 75 plots in 8 barrancos on the northern coast of La Palma, spanning an elevation gradient from 95 to 674m a.s.l. Using mixed-effects models, we assessed the effect of barranco depth and elevation on the percentage of single-island endemics, multi-island endemics, and archipelago endemics. We found that percent endemism was not significantly correlated with barranco depth and correlated negatively with elevation within barrancos (rather than the expected positive relationship). The topographic barriers associated with the deep island barrancos thus appear insufficient to drive speciation through isolation in oceanic island plants. The decrease in endemism with elevation contradicts findings by previous broader-scale studies and it may reflect local influences, such as high habitat heterogeneity at low elevations.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Barranco; Elevation; Endemism; Islands; Isolation; La palma; Ravine; Topography

The effects of spatial scale and isoscape on consumer isotopic niche width - Reddin, Carl James; Bothwell, John; O'Connor, Nessa; Harrod, Chris (Functional Ecology, 2018)
1. The mean and variance of ecological variables are dependent on sampling attributes such as the coverage of environmental heterogeneity (sampling extent) and spatial scale. Trophic niche width is often approximated by bulk tissue stable isotopes of C and N, that is, the population isotopic niche. However, recent studies suggest that environmental heterogeneity (experienced by individuals) may be more important in defining the isotopic niche width than trophic variability. We hypothesised that isotopic niche width will increase monotonically with spatial scale, largely produced by environmental variation, for example, nutrient source.2. To refine this hypothesis, by describing the shapes of isotope scaling curves, we explored a previously published dataset describing three Chilean intertidal species representing different feeding guilds (grazing snails, suspension-feeding mussel). We tested these hypotheses on a new, larger dataset describing three functionally analogous intertidal species from Northern Ireland. We generated isotopic variance-area curves from a spatially explicit bootstrap and investigated the scale dependency of environment-isotope relationships, including wave exposure and sub-habitat heterogeneity.3. Spatial scale explained 50% of the variance in population isotopic niche widths (bivariate C-N ellipse area) by simple, nonlinear relationships. Finer scales (< 1-10 km lag) accounted for most variance. Scale dependence was strong for delta N-15 variance, of which > 40% was explained by modelling linear coefficients. A delta N-15 baseline gradient, or isoscape, dominated delta N-15 variance scaling patterns, from sheltered, terrestrially influenced embayments to exposed, pelagic-dominated coastline. Consumer delta C-13 variance had a weaker scale dependence, plateauing at mesoscales (> 20 km lag).4. We show that isotopic niche width is strongly dependent on sampling spatial extent, which controls the environmental heterogeneity experienced by individual consumers. Environmental heterogeneity must be accounted for before isotopic niche width can be considered to accurately represent trophic niche width. Studies conducted at different spatial scales are likely to identify different environmentisotope relationships.5. We recommend that spatial scale should be incorporated into sampling designs explicitly, easiest by maintaining a consistent lag distance or area within which populations are sampled. Identified isoscapes can be de-trended, where necessary.
Keywords: ellipse; limpets; marine; mussels; niche space; scale dependence; stable isotope ecology; trophic ecology

The effects of taxonomic standardization on occurrence-based estimates of diversity - Wagner, Peter; Aberhan, Martin; Hendy, Austin; Kießling, Wolfgang (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LP.theeff

The Evolution and Fossil Record of Parasitism: Coevolution and Paleoparasitological Techniques - de Baets, Kenneth; Huntley, John Warren (Springer, 2021)
This two-volume edited book highlights and reviews the potential of the fossil record to calibrate the origin and evolution of parasitism, and the techniques to understand the development of parasite-host associations and their relationships with environmental and ecological changes. The book deploys a broad and comprehensive approach, aimed at understanding the origins and developments of various parasite groups, in order to provide a wider evolutionary picture of parasitism as part of biodiversity. This is in contrast to most contributions by parasitologists in the literature that focus on circular lines of evidence, such as extrapolating from current host associations or distributions, to estimate constraints on the timing of the origin and evolution of various parasite groups. This approach is narrow and fails to provide the wider evolutionary picture of parasitism on, and as part of, biodiversity. Volume two focuses on the importance of direct host associations and host responses such as pathologies in the geological record to constrain the role of antagonistic interactions in driving the diversification and extinction of parasite-host relationships and disease. To better understand the impact on host populations, emphasis is given to arthropods, colonial metazoans, echinoderms, mollusks and vertebrates as hosts. In addition, novel techniques used to constrain interactions in deep time are discussed ranging from chemical and microscopic investigations of host remains, such as blood and coprolites, to the statistical inference of lateral transfer of transposons and host-parasite coevolutionary dynamics using molecular divergence time estimation.
Keywords: Identifying parasitism in the fossil record; viral fossils; Protistan parasites; Insects as parasitoids and parasites; extinct lineages of parasites; Evolutionary history; Co-divergence; host response; Paleoparasitology techniques; Parasite-induced traces; Molecular perspectives

The Evolution and Fossil Record of Parasitism: Identification and Macroevolution of Parasites - de Baets, Kenneth; Huntley, John Warren (Springer, 2021)
This two-volume edited book highlights and reviews the potential of the fossil record to calibrate the origin and evolution of parasitism, and the techniques to understand the development of parasite-host associations and their relationships with environmental and ecological changes. The book deploys a broad and comprehensive approach, aimed at understanding the origins and developments of various parasite groups, in order to provide a wider evolutionary picture of parasitism as part of biodiversity. This supplements contributions by parasitologists that mostly focus on extrapolating from current host associations or distributions, to estimate constraints on the timing of the origin and evolution of various parasite groups. This approach allows a wider evolutionary picture of parasitism on, and as part of, biodiversity. Volume one focuses on identifying parasitism in the fossil record, and sheds light on the distribution and ecological importance of parasite-host interactions over time. In order to better understand the evolutionary history of parasites and their relationship with changes in the environment, emphasis is given to viruses, bacteria, protista and plants as parasites. Particular attention is given to metazoans such as molluscs, cnidarians, crustaceans and insects as parasites. Researchers, specifically parasitologists, interested in the evolutionary history of parasite-host interactions, as well as students studying parasitism will find this book appealing. <br
Keywords: Bacteria as pathogens; Coprolites; Host responses; Identifying parasitism in the fossil record; Metazoa as parasites; Molecular perspectives; Paleoparasitology techniques; Parasite-induced traces and pathologies; Plants as parasites: Viral fossils

The first record of Early Devonian ammonoids from Belgium and their stratigraphic significance - de Baets, Kenneth; Goolaerts, Stijn; Jansen, Ulrich; Klug, Christian; Rietbergen, Tim (Geologica Belgica, 2013)
The first ammonoids from the Lower Emsian (Devonian) of Belgium are described. They belong to the Anetoceratinae, which show the most plesiomorphic characters of all ammonoids. This is the second report of Early Emsian ammonoids within the Rhenish facies of the Rhenish Slate Mountains (Belgium, Germany), in this case from the Belgian part of the Eifel (Burg Reuland). It highlights the possible importance of ammonoids for the correlation of the Emsian in its traditional German sense and the Emsian in the global sense as delimited by the GSSPs. Newly collected, age-significant brachiopods of the genera Arduspirifer and Euryspirifer and other previously reported fossils indicate a middle or late Early Emsian (Singhofen or Vallendar) age (in German sense) for this locality. We extend the range of Ivoites schindewolfi outside of the Hunsruck Basin and further corroborate an age younger than Ulmen for parts of the Hunsruck Slate.
Keywords: Ammonoidea; Brachiopoda; Early Devonian; Anetoceratinae; Systematics; biostratigraphy

The first sphinctozoan-bearing reef from an Ordovician back-arc basin - Li, Qijian; Li, Yue; Kießling, Wolfgang (Facies, 2015)
Although sphinctozoans, multi-chambered hypercalcified sponges, can be traced from the Cambrian, their reef-building capacity in the Early Paleozoic appears limited. The oldest sphinctozoan-coral-microbial reef‏ is documented here, from the Upper Sanqushan Formation (Late Katian) of southeast China. This is also the first report of Ordovician sphinctozoans from South China. The sponges occur in a >120-m-thick reef that is mainly constructed by calcimicrobes (Kordephyton, Renalcis, and Epiphyton) with a low abundance of in situ metazoans, predominantly sphinctozoan sponges (Corymbospongia) and rugose corals (mostly Palaeophyllum and Streptelasma). Tetradium is the only tabulate coral preserved in growth position. Crinoids and brachiopods are common reef dwellers. Dasycladacean algae are rare and probably transported and stromatactis is abundant. Bio- and litho-facies in this area as well as the characteristics of the microbialite suggest that the reef developed in a deeper subtidal setting that was unfavorable for most metazoan reef builders. In contrast to the high-energy stromatolite-sphinctozoan reefs from the Late Silurian, this case represents a low-energy community, indicating that the first reef-building sphinctozoans might have originated in a relatively deep-water environment on seamounts of a back-arc basin during the Late Ordovician.
UnivIS-Import:2015-10-26:Pub.2015.nat.dgeo.IGM.LP.thefir
Keywords: Back-arc basin; Late Katian; Microbialites; South China; Sphinctozoans; Stromatactis

The fish assemblage from the Pennsylvanian Buckhorn Asphalt Quarry Lagerstätte (Oklahoma, USA) - Ivanov, Alexander; Seuß, Barbara; Nützel, Alexander (Palaeontologische Zeitschrift, 2017)

The formation of micritic limestones and the development of limestone-marl alternations in the Silurian of Gotland, Sweden - Munnecke, Axel; Samtleben, Christian (Facies, 1996)
Micritic Iimestone-mari alternations make up the major part of the Silurian strata on Gotland (Sweden). Their position on the stable Baltic Shield protectcd them from deep burial and tectonic stress and allowed the preservation of early stages of burial diagenesis, incl uding lilhification. In the micritic Iimestones certain characteristics have been preserved (e.g., pitted microspar crystals, sharp bot;ndaries between microspar and components, Iack of deformation phenomena) that offcr insights into lheir formation. We suppose thc formation of lhese micritic Iimestones and Iimestone-mari alternations to be based on a rhylhmic diagenesis within an aragonite solution zone (ASZ) close below the sediment surface. The micritic Iimestones are the product of a poikilotopic cementation of carbonate muds which consisted of varying portions of aragonitic, calcitic and terrigenaus matter. Their microspar crystals show the primary size and shape of the cements lithifying the original carbonate mud. Dissolution of aragonite in the marls provided the carbonate for the lithification of the limestones. By cementation, lhe Iimestone beds evaded further compaclion. The marls, which already underwent a volume decrease by aragonite depletion, lacked cement and became more and more compacted due to increasing se overburden. Allhough field Observationsshow lhat primary differences in material influence lhe development of Iimestone-mari alternations lhey are notrequired for lheir formatio
Keywords: Iimestone; marl; micritic; carbonate

The formation of microbial-metazoan bioherms and biostromes following the latest Permian mass extinction - Heindel, Katrin; Foster, William J.; Richoz, Sylvain; Birgel, Daniel; Roden, Vanessa; Baud, Aymon; Brandner, Rainer; Krystyn, Leopold; Mohtat, Tayebeh; Koşun, Erdal; Twitchett, Richard J.; Reitner, Joachim; et al. (Gondwana Research, 2018)
Keywords: Microbial mat; Lipid biomarker; Keratose sponges; Early Triassic; Paleoecology; Cyanobacteria

The Fossil Record of Parasitism: Its Extent and Taphonomic Constraints - de Baets, Kenneth; Huntley, John Warren; Klompmaker, Adiël A.; Schiffbauer, James D.; Muscente, A. D. (The Evolution and Fossil Record of Parasitism, 2021)
The fossil record of parasites is limited thus far. A survey of the fossil record shows that some modes of preservation show a higher potential for the preservation of parasitic remains or parasite–host associations than generally recognized. A better understanding of the taphonomy of parasites is critical to better predict their preservation potential and, together with new techniques like computed tomography, can open the door for systematic screening of parasite sources in deep time. Phosphatization seems particularly fruitful to characterize anatomical details for microscopic parasites or pathogens. Amber deposits are rich in terrestrial parasitic ecdysozoans and their pathogens, but their extent does not bracket a single mass extinction. For particular parasite–host associations, preservation of direct evidence is unlikely, but traces they leave in skeletons and other host remains can be used to trace them back to the Mesozoic or even the Paleozoic. Vertebrate coprolites have yielded remains of endoparasites as far back as the Carboniferous, but a more systematic screening of coprolites is necessary to make them a successful source of parasitic remains as for the Quaternary. Parasites with preservable hard parts and/or characteristic pathologies have the best potential to track changes in marine disease prevalence in high resolution across extinction or environmental perturbations in deep time, but more studies need to report their sample sizes and prevalences.
Keywords: Parasite–host interactions; Evolution; Ecology; Pathogens; Taphonomy

The gastropods from the Pennsylvanian Buckhorn Asphalt Deposit (Oklahoma, USA) – an unique mollusc Lagerstätte - Nützel, Alexander; Seuß, Barbara (88. Jahrestagung der Paläontologischen Gesellschaft, 2017)

The general dynamic model of island biogeography revisited at the level of major flowering plant families - Lenzner, Bernd; Weigelt, Patrick; Kreft, Holger; Beierkuhnlein, Carl; Steinbauer, Manuel (Journal of Biogeography, 2017)
Aim: The general dynamic model (GDM) proposed by Whittaker et al. (2008) has become a widely accepted theoretical framework in island biogeography. In this study, we explore whether GDM predictions hold when overall plant diversity is deconstructed into major plant families.   Location: 101 islands from 14 oceanic archipelagos world-wide.   Methods: Occurrence data for all species of nine large, cosmopolitan flowering plant families were used to test predictions derived from the GDM. We analysed the effects of island area and age on species richness as well as number and percentage of single-island endemic species per family using mixed-effect models.   Results: Total species and endemic richness as well as the percentage of endemic species showed the predicted hump-shaped relationship with island age. The overall pattern was mainly driven by few species-rich plant families. Varying patterns were found for individual families, some of them opposing the general trend. In most cases, native and endemic species richness peaked much earlier in the island life cycle than suggested by the GDM. The contribution of area to the explained variation of all dependent variables was much higher than that of island age.   Main conclusions: The results suggest that biodiversity-age relationships reported for large taxonomic groups like plants are driven by only a few species-rich clades. The way these families influence the overall patterns of species richness and endemism is related to family-specific properties, such as evolutionary history or dispersal strategies. Deviances from the GDM predictions can hence largely be explained by family characteristics and considering taxon-specific traits may help to further improve the explanatory power of the GDM. Families not following the expectations, like Orchidaceae, may be particularly valuable candidates to unveil so far neglected drivers of island biogeographical patterns.
Keywords: general dynamic model; island biogeographical theory; island endemism; mixed-effect models; oceanic islands; scale effect

The geological record of ocean acidification - Hoenisch, Baerbel; Ridgwell, Andy; Schmidt, Daniela N.; Thomas, Ellen; Gibbs, Samantha J.; Sluijs, Appy; Zeebe, Richard; Kump, Lee; Martindale, Rowan C.; Greene, Sarah E.; Kießling, Wolfgang; Ries, Justin; et al. (Science, 2012)
Ocean acidification may have severe consequences for marine ecosystems; however, assessing its future impact is difficult because laboratory experiments and field observations are limited by their reduced ecologic complexity and sample period, respectively. In contrast, the geological record contains long-term evidence for a variety of global environmental perturbations, including ocean acidification plus their associated biotic responses. We review events exhibiting evidence for elevated atmospheric CO2, global warming, and ocean acidification over the past ∼300 million years of Earth's history, some with contemporaneous extinction or evolutionary turnover among marine calcifiers. Although similarities exist, no past event perfectly parallels future projections in terms of disrupting the balance of ocean carbonate chemistry - a consequence of the unprecedented rapidity of CO 2 release currently taking place.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.thegeo

The Geoscience Collections of the Göttingen University - Reich, Mike; Reitner, Joachim; Roden, Vanessa; Stegemann, Tanja R. (2013)

The Geoscientific Collections of the Göttingen University - Reich, Mike; Reitner, Joachim; Roden, Vanessa; Stegemann, Tanja R. (2009)

The Great Ordovician Biodiversification Event (GOBE): The palaeoecological dimension - Servais, Thomas; Owen, Alan W.; Harper, David A.T.; Kröger, Björn; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
The 'Great Ordovician Biodiversification Event' (GOBE) saw a spectacular increase in marine biodiversity at all taxonomic levels largely within the phyla established much earlier during the so-called 'Cambrian Explosion'. The diversification was probably the result of a combination of several geological and biological processes and the positive feedbacks resulting from them. The present paper reviews the palaeoecological dimension of the GOBE. It involved major increases in α, ß and γ biodiversity largely associated with the rise of the Paleozoic Evolutionary Fauna dominated by suspension feeders and involving a greater occupation of ecospace and more complex ecological structures in the Ecological Evolutionary Units P1 and P2. In the benthos, these include more complex food webs than those of the Cambrian, greater tiering, especially above the sediment-water interface, and the development of guild structures indicating increased competition between taxa for particular resources. The Ordovician is characterized by a profound change in reef composition, with a switch from microbial-dominated reefs in the Early and Middle Ordovician to metazoan-dominated reefs in the Late Ordovician. Increases in complexity of deep-water trace fossil assemblages began in the Early Ordovician and mark the increasing exploitation in that environment and the development of hardgrounds permitted bioerosion and encrusting strategies together with the appearance of cryptic communities.Within the water column, the GOBE involved a significant increase in the diversity of the phytoplankton and the development of a diverse zooplankton (including planktotrophic larvae from a range of invertebrate clades). This revolution in the plankton enabled the establishment of a diverse fauna of pelagic vertebrates, molluscs and arthropods and promoted the rise of suspension feeders in the benthos. An escalation amongst predators and thus community evolution may also have been a major driver of biodiversification. © 2010 Elsevier B.
Keywords: Biodiversification; Ordovician; Palaeoecology; Palaeoenvironment

The Hitchhiker's guide to island endemism: Biodiversity and endemic perennial plant species in roadside and surrounding vegetation - Irl, Severin; Steinbauer, Manuel; Epperlein, Lilith; Harter, David; Jentsch, Anke; Pätz, Susanne; Wohlfart, Christian; Beierkuhnlein, Carl (Biodiversity and Conservation, 2014)
Roadsides are habitats with very specific environmental conditions, often substantially differing from their natural surroundings. However, roads can have a positive effect on local vascular plant species richness. Endemic species on oceanic islands are considered to be less disturbance-adapted than native non-endemics and thus should be negatively affected by roads. Islands provide optimal conditions for testing this, as they possess a large share of clearly defined endemic species. This study focuses on a comparison of endemic plant species in roadside and surrounding communities and the interacting effects of elevation, vegetation type and trade wind-induced precipitation differences. We applied 96 circular plots with 50 m radius along two elevational gradients on the eastern (humid) and western (dry) slope of La Palma, Canary Islands, ranging from 100 to 2,400 m. Interestingly, we found roads to have a significant positive effect on endemic richness and the percentage of endemics as well as the same tendency for plant species richness after correcting for elevation and precipitation. Endemic species turnover was relatively high. The opening of cliffs during construction and, not to be overlooked, the protection from disturbances such as fire and omnipresent introduced herbivores (mainly rabbits or goats) probably leads to a positive effect of roads on endemics. In addition, many endemics might profit from species-specific dispersal capabilities well suited for roadside conditions. However, we do not argue for the use or even construction of roads for nature conservation but suggest protecting existing endemic populations because natural areas have a higher conservation value.
Keywords: Canary Islands; Disturbance; Elevational gradient; Endemic richness; Road ecology; Vascular plant species

The Homerian carbon isotope excursion (Silurian) within graptolitic successions on the Midland Platform (Avalonia), UK: implications for regional and global comparisons and correlations - Fry, Charlotte R.; Ray, David C.; Wheeley, James R.; Boomer, Ian; Jarochowska, Emilia; Loydell, David K. (GFF, 2017)

The Impact of Field Courses on Undergraduate Knowledge, Affect, Behavior, and Skills: A Scoping Review - Shinbrot, Xoco A.; Treibergs, Kira; Hernandez, Lina M. Arcila; Esparza, David; Ghezzi-Kopel, Kate; Goebel, Marc; Graham, Olivia J.; Heim, Ashley B.; Smith, Jansen; Smith, Michelle K. (Bioscience, 2022)
Field courses provide transformative learning experiences that support success and improve persistence for science, technology, engineering, and mathematics majors. But field courses have not increased proportionally with the number of students in the natural sciences. We conducted a scoping review to investigate the factors influencing undergraduate participation in and the outcomes from field courses in the United States. Our search yielded 61 articles, from which we classified the knowledge, affect, behavior, and skill-based outcomes resulting from field course participation. We found consistent reporting on course design but little reporting on demographics, which limits our understanding of who takes field courses. Cost was the most commonly reported barrier to student participation, and knowledge gains were the most commonly reported outcome. This scoping review underscores the need for more rigorous and evidence-based investigations of student outcomes in field courses. Understanding how field courses support or hinder student engagement is necessary to make them more accessible to all students.
CRIS-Team WoS Importer:2022-09-02

The impact of the Pliensbachian–Toarcian crisis on belemnite assemblages and size distribution - de Baets, Kenneth; Nätscher, Paulina; Rita, Patricia; Fara, Emmanuel; Neige, Pascal; Bardin, Jérémie; Dera, Guillaume; Duarte, Luís Vítor; Hughes, Zoe; Laschinger, Peter; Carlos Garcia-Ramos, Jose; Pinuela, Laura; et al. (Swiss Journal of Palaeontology, 2021)
The second-order Pliensbachian–Toarcian crisis affected major groups of marine organisms. While its impact has been intensively studied for ammonites, the response of belemnites is only currently emerging through quantitative studies. Novel overall and regional diversity analyses suggest that belemnite richness in the NW-Tethys drops at the Pliensbachian–Toarcian boundary, while overall diversity slightly increases in NW-Tethys assemblages during the Toarcian Oceanic Anoxic event (T-OAE), mostly driven by NW European assemblages (e.g., Yorkshire). The T-OAE coincides with marked taxonomic turnover within individual basins, which is associated with an increase in median rostrum size of specimens in taxa at most localities. The changes in median body size across the Pliensbachian–Toarcian boundary are less consistent and driven by changes in body size within individual lineages crossing the boundary. However, our analyses also illustrate differences in sampling across the Pliensbachian–Toarcian crisis, which needs to be considered in further studies.
Keywords: Cephalopoda; Belemnitida; Rarefraction; Rostrum size; Paleoecology; Sampling

The Importance of Fossils in Understanding the Evolution of Parasites and Their Vectors - de Baets, Kenneth; Littlewood, D. Timothy J. (Advances in Parasitology, 2015)
Knowledge concerning the diversity of parasitism and its reach across our current understanding of the tree of life has benefitted considerably from novel molecular phylogenetic methods. However, the timing of events and the resolution of the nature of the intimate relationships between parasites and their hosts in deep time remain problematic. Despite its vagaries, the fossil record provides the only direct evidence of parasites and parasitism in the fossil record of extant and extinct lineages. Here, we demonstrate the potential of the fossil record and other lines of geological evidence to calibrate the origin and evolution of parasitism by combining different kinds of dating evidence with novel molecular clock methodologies. Other novel methods promise to provide additional evidence for the presence or the life habit of pathogens and their vectors, including the discovery and analysis of ancient DNA and other biomolecules, as well as computed tomographic methods.

The influence of bioerosion on taphonomy - a case stuy using Nautilus macromphalus - Seuß, Barbara; Hembree, Daniel I.; Wisshak, Max; Mapes, Royal H. (GSA Annual meeting, 2017)
Bioerosion, i.e., chemical and mechanical degradation of largely carbonate skeletal material, was studied in detail in shells of Nautilus for the first time. Nautilus typically lives along slopes of coral reefs in water depths between 300-400 m, with a range of 100-700 m and occurs in the Indo-Pacific Ocean exclusively. After death of the animal its conch will either float (up to hundreds of km until it sinks or is washed onto the beach) or it will rapidly sink to the seafloor close to where Nautilus has lived and died. Two sets of N. macromphalus shells from New Caledonia are included in this study: 1) Backshore collected (from two beaches on Lifou (Loyalty Islands)) and 2) Deep-sea dredged (395 m: halfway from Grand Terre and the Isle of Pines; 589 m: western edge of the Lansdowne Bank west of Grand Terre). After preparing synthetic resin casts these were analyzed with the SEM and ichnotaxa were categorized semi-quantitatively in the plan view. In total, 30 ichnotaxa were identified, some of them are new. Seven ichnotaxa were produced by cyanobacteria and five traces by chlorophytes. Further traces were produced by sponges, fungi, foraminifers, and by rhodophytes. Six traces were produced by some unknown heterotroph and two have an unknown affinity so far. The 23 ichnotaxa occurring in the backshore ichnocoenosis contain eleven traces that are produced by phototrophic and ten by heterotrophic organisms; two forms are of unknown origin. The 15 traces from the 395 m sample contain both, traces of photoautotroph producers and those of heterotrophs. All of the eight taxa recorded from 589 m water depth are of heterotrophic origin. Interpretation of the results is largely based on the ichnobathymetrical scheme combining the key ichnospecies and the mode of penetration: 1) Backshore: Shallow euphotic zone III to the deep euphotic zone; key ichnotaxa of the intertidal are present as well reflecting transport from nearshore to backshore. 2) 398 m: Transport must have taken place from the deep euphotic zone down into the aphotic zone. 3) 589 m: The shell had rapidly sunk to the seafloor after death of the specimen into aphotic conditions and had likely stayed close to the living site of the anima

The influence of the bridgehead in Saalfrank-type cryptands: prediction of ion selectivity by quantum chemical calculations XII - Balović, Jelena; Ćoćić, Dušan; Puchta, Ralph; Scheurer, Andreas; van Eldik, Rudi (Journal of Coordination Chemistry, 2020)
We examined the cation selectivity of the Saalfrank-type 2-metallocryptands [Ga2R3] and [Fe2R3] (R: 1,1'-(pyridine-2,6-diyl)bis(2-(1H-tetrazol-5-yl)ethan-1-one)) with alkaline and earth alkaline metal ions by means of DFT calculations (B3LYP/LANL2DZp) to obtain a better insight into the influence of the bridge head metal ions responsible for the cryptands ion selectivity. Based on our DFT calculations, notably the application of model equations and geometric features regarding the flexibility of the 2-metallocryptands, we identified K+, Sr2+ and Ba2+ as the best fitting ions. While [Fe2R3] has a cavity a bit larger than [Ga2R3], it prefers the Ba2+ cation, whereas [Ga2R3] selects the smaller Sr2+ cation. The good flexibility of the investigated hosts is provided by the oxygen-donor moieties of the 2-metallocryptands.
CRIS-Team Scopus Importer:2020-07-24
Keywords: cryptand; DFT-study; Selective ion complexation

The Ireviken Event in the lower Silurian of Gotland, Sweden - Relation to similar Palaeozoic and Proterozoic events - Munnecke, Axel; Samtleben, Christian; Bickert, Torsten; Munnecke, Axel; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
For a long time, the Silurian was thought to represent a time of stable environmental conditions in the greenhouse period that followed the Late Ordovician glaciation. During the past decade, knowledge about the Silurian has increased markedly and today it is known that the conditions in the Silurian were much more variable than previously assumed. Detailed isotopic investigations have revealed several distinct positive excursions in both carbon and oxygen isotope values. In low latitudes, these periods of high C- and O-isotope values are in many cases characterised by the growth of reefs and the formation of extended carbonate platforms. The sediments deposited during these excursions contain impoverished fossil assemblages, especially with respect to conodonts, graptolites, and trilobites. A conspicuous isotope excursion coincident with facies changes and a marked mass extinction is observed near the Llandovery/Wenlock boundary. This event is called the 'Ireviken Event' after its type locality on the island of Gotland, Sweden (Jeppsson, L., 1987. In: Palaeobiology of Conodonts. Ellis Horwood Ltd., Chichester, pp. 129-145). Here, isotope data from nine sections at the NW coast of Gotland are presented that cover the time interval of the Ireviken Event. The δC mean values rise from +1.4‰ to +4.5‰, and the δO values increase from -5.6‰ to -5.0‰. The relative timing of stable isotope development, extinctions, and facies development is discussed. It is shown that first extinctions precede the isotope excursion. This indicates that extinction events and stable isotope development are only indirectly connected but might reflect the same causes. Other events characterised by similar relationships between positive isotope excursions, mass extinctions, and facies development are found in younger parts of the Silurian (late Wenlock and Ludlow), in the late Ordovician, the late Cambrian, and, with some reservations, in the Proterozoic. The similarities between these events indicate analogous controlling mechanisms. For the Silurian, climatic changes between humid and arid conditions in low latitudes were postulated in an earlier study of the authors. A palaeoceanographic/climatic model was postulated which is consistent with most of the sedimentological, palaeontological, and geochemical data. Here we demonstrate that this model may be applicable also for the older events. © 2003 Elsevier Science B.V. All rights reserve
Keywords: Bioevents; Cambrian; Mass extinction; Ordovician; Silurian; Stable isotope

The Late Paleozoic Ice Age (LPIA) – Turnover rates during a phase of major climatic changes - Seuß, Barbara; Roden, Vanessa; Kocsis, Ádám; Kießling, Wolfgang (Jahrestagung der Paläontologischen Gesellschaft in München, 2019)

The Loss of a Unique Palaeobotanical Site in Terceira Island Within the Azores UNESCO Global Geopark (Portugal) - Góis-Marques, Carlos A.; Elias, Rui B.; Steinbauer, Manuel; de Nascimento, Lea; Fernández-Palacios, José María; de Sequeira, Miguel Menezes; Madeira, José (Geoheritage, 2019)
Terceira Island (Azores archipelago, central Atlantic Ocean) presents a unique but poorly studied Quaternary palaeobotanical record. Among the sites referenced in the literature, Fanal Bay, within Angra do Heroísmo city, is known at least since the 1940s. Field prospection in the summer of 2016 revealed two layers of leaf fossils with an unexpected fossil abundance. The preliminary results showed that these represented autochthonous or para-autochthonous (T0) fossil assemblages, preserved by the emplacement of ash or lapilli layers by volcanic events, in a leaf litter of a laurel palaeoforest. Unfortunately, in 2018, the site was destroyed due to development works to consolidate and requalify the Fanal Bay cliff from further sea erosion. This prevented a detailed study and the ex situ preservation of an important palaeontological site, within the Azores UNESCO Global Geopark. With this work, we hope to call the attention to the need of implementing geoconservation strategies in order to prevent the destruction of important geoheritage within the Azores Islands and to transpose this warning to other geoconservationists in oceanic islands worldwide.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Anthropic impact; Azores Islands; Geoconservation; Macaronesia; Palaeobotany

The moral and legal imperative to return illegally exported fossils - Cisneros, Juan; Ghilardi, Aline Marcele; Raja Schoob, Nussaibah Begum; Stewens, Paul (Nature Ecology & Evolution, 2021)

The nature of Ordovician limestone-marl alternations in the Oslo-Asker District (Norway): Witnesses of primary glacio-eustasy or diagenetic rhythms? - Amberg, Chloé E. A.; Collart, Tim; Salenbien, Wout; Egger, Lisa Marie; Munnecke, Axel; Nielsen, Arne Thorshøj; Monnet, Claude; Hammer, Øyvind; Vandenbroucke, Thijs R.A. (Scientific Reports, 2016)
Ordovician limestone-marl alternations in the Oslo-Asker District have been interpreted as signaling glacio-eustatic lowstands, which would support a prolonged â €œ Early Palaeozoic Icehouseâ €. However, these rhythmites could alternatively reflect differential diagenesis, without sedimentary trigger. Here, we test both hypotheses through one Darriwilian and three Katian sections. Our methodology consists of a bed-by-bed analysis of palynological (chitinozoan) and geochemical (XRF) data, to evaluate whether the limestone/marl couplets reflect an original cyclic signal. The results reveal similar palynomorph assemblages in limestones and marls. Exceptions, which could be interpreted as reflecting palaeoclimatological fluctuations, exist at the species level: Ancyrochitina bornholmensis seems to be more abundant in the marl samples from the lower Frognerkilen Formation on Nakkholmen Island. However, these rare cases where chitinozoans differ between limestone/marl facies are deemed insufficient for the identification of original cyclicity. The geochemical data show a near-perfect correlation between insoluble elements in the limestone and the marls, which indicates a similar composition of the potential precursor sediment, also in the Frognerkilen Formation. This is consistent with the palynological data. Although an original cyclic pattern could still be recorded by other, uninvestigated parameters, our palaeontological and geochemical data combined do not support the presence of such a signa

The Occurrence Birth-Death Process for Combined-Evidence Analysis in Macroevolution and Epidemiology - Andreoletti, Jeremy; Zwaans, Antoine; Warnock, Rachel; Aguirre-Fernandez, Gabriel; Barido-Sottani, Joelle; Gupta, Ankit; Stadler, Tanja; Manceau, Marc (Systematic Biology, 2022)
Phylodynamic models generally aim at jointly inferring phylogenetic relationships, model parameters, and more recently, the number of lineages through time, based on molecular sequence data. In the fields of epidemiology and macroevolution, these models can be used to estimate, respectively, the past number of infected individuals (prevalence) or the past number of species (paleodiversity) through time. Recent years have seen the development of "total-evidence" analyses, which combine molecular and morphological data from extant and past sampled individuals in a unified Bayesian inference framework. Even sampled individuals characterized only by their sampling time, that is, lacking morphological and molecular data, which we call occurrences, provide invaluable information to estimate the past number of lineages. Here, we present new methodological developments around the fossilized birth-death process enabling us to (i) incorporate occurrence data in the likelihood function; (ii) consider piecewise-constant birth, death, and sampling rates; and (iii) estimate the past number of lineages, with or without knowledge of the underlying tree. We implement our method in the RevBayes software environment, enabling its use along with a large set of models of molecular and morphological evolution, and validate the inference workflow using simulations under a wide range of conditions. We finally illustrate our new implementation using two empirical data sets stemming from the fields of epidemiology and macroevolution. In epidemiology, we infer the prevalence of the coronavirus disease 2019 outbreak on the Diamond Princess ship, by taking into account jointly the case count record (occurrences) along with viral sequences for a fraction of infected individuals. In macroevolution, we infer the diversity trajectory of cetaceans using molecular and morphological data from extant taxa, morphological data from fossils, as well as numerous fossil occurrences. The joint modeling of occurrences and trees holds the promise to further bridge the gap between traditional epidemiology and pathogen genomics, as well as paleontology and molecular phylogenetics. [Birth-death model; epidemiology; fossils; macroevolution; occurrences; phylogenetics; skyline.]
CRIS-Team WoS Importer:2022-06-24

The oldest deep-boring bivalves? Evidence from the Silurian of Gotland (Sweden) - Claußen, Anna Lene; Munnecke, Axel; Wilson, Mark A.; Oswald, Irina (Facies, 2019)
Compared to modern counterparts, bioerosion is rare in Paleozoic reefs, especially macro-bioerosion. The unique and enigmatic Silurian reefs from Gotland (Sweden), composed of bryozoans and microbial laminates, show evidence of a large amount of bioerosion. The samples contain Trypanites trace fossils, as well as a large number of undescribed macroborings. Small articulated bivalve shells are preserved in some of these macroborings, identified from thin-sections. Three-dimensional images from micro-computed tomography (microCT) reveal an additional bivalve, which is occupying a bioerosion trace. This specimen is possibly contained in a different boring that can be classified as possibly clavate-shaped. Furthermore, evidence of nestling, such as a subsequent modification of the ichnofossils, the presence of bivalves that are much smaller than the trace, or the presence of additional specimens, is missing; therefore, it is most likely that the bivalves made the borings. This is evidence for the existence of deep-boring bivalves in the Silurian.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Bioerosion; Bryozoans; Endolithic bivalves; Paleozoic; Reefs; Tofta Formation

The oldest labechiid stromatoporoids from intraskeletal crypts in lithistid sponge Calathium reefs - Li, Qijian; Li, Yue; Kießling, Wolfgang (Lethaia, 2017)
UnivIS-Import:2017-03-24:Pub.2017.nat.dgeo.IGM.LP.theold
Keywords: Calathium; intraskeletal crypts; keratose sponges; labechiid stromatoporoids; reefs

The onset of the 'Ordovician Plankton Revolution' in the late Cambrian - Servais, Thomas; Perrier, Vincent; Danelian, Taniel; Klug, Christian; Martin, Ronald E.; Munnecke, Axel; Nowak, Hendrik; Nützel, Alexander; Vandenbroucke, Thijs R.A.; Williams, Mark; Rasmussen, Christian Mac Ørum (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
The ‘Great Ordovician Biodiversification Event’ comprises the rapid diversification of marine organisms during the Ordovician Period. It is now clear that this adaptive radiation started for some organisms already in the Cambrian and continued for others beyond the end of the Ordovician, making the ‘Great Ordovician Biodiversification Event’ part of a long-term late Proterozoic and Early Palaeozoic radiation, that in part is expressed by the fossil record as the ‘Cambrian Explosion.’ A significant diversification of different groups of the plankton is observed in the late Cambrian–Early Ordovician interval, leading to the subsequent ‘Ordovician Plankton Revolution.’ The possible causes of this ‘plankton revolution’ are currently debated. They include changes in palaeoclimate, palaeogeography or tectonic and volcanic activity, as well as a modified nutrient supply. In this context, the Steptoean Positive Carbon Isotope Excursion δ13Ccarb (SPICE) event in the late Cambrian (Paibian Stage, Furongian Series) has been related to a major increase in atmospheric O2 (from 10–18% to some 20 – 29%) and to increased oceanic nutrient availability. Here we analyze the diversification of the planktonic groups during the late Cambrian and Early Ordovician, in particular in relation to the SPICE event. Our analyses include the changing diversities of the phytoplankton (acritarchs), diverse groups of zooplankton (e.g., radiolarians, graptolites, chitinozoans) and the switch to a planktonic mode of life of fossil groups (e.g., arthropods, molluscs) that were part of the Cambrian benthos and that later occupied pelagic niches. In addition, we focus also on data indicating evidence for a late Cambrian to Ordovician origin of planktotrophy in invertebrate larvae. It can be concluded that none of the diversifications of the different planktonic organisms can be related directly to the SPICE event. However, a long term (10–20 million years) oxygenation pulse related to the SPICE event might have fuelled the explosion of phytoplankton diversity observed in the latest Cambrian–Early Ordovician that led to completely modified trophic structures permitting an increase in diversity and abundance of plankton-feeding groups during the Ordovicia
Keywords: Plankton; SPICE; Late Cambrian; Early Ordovician; Ordovician Plankton Revolution

The Ordovician Biodiversification: revolution in the oceanic trophic chain - Servais, Thomas; Lehnert, Oliver; Li, Jun; Mullins, Gary L.; Munnecke, Axel; Nützel, Alexander; Vecoli, Marco (Lethaia, 2008)
The Early Palaeozoic phytoplankton (acritarch) radiation paralleled a long-term increase in sea level between the Early Cambrian and the Late Ordovician. In the Late Cambrian, after the SPICE δ13C carb excursion, acritarchs underwent a major change in morphological disparity and their taxonomical diversity increased to reach highest values during the Middle Ordovician (Darriwilian). This highest phytoplankton diversity of the Palaeozoic was possibly the result of palaeogeography (greatest continental dispersal) and major orogenic and volcanic activity, which provided maximum ecospace and large amounts of nutrients. With its warm climate and high atmospheric CO2 levels, the Ordovician was similar to the Cretaceous: a period when phytoplankton diversity was at its maximum during the Mesozoic. With increased phytoplankton availability in the Late Cambrian and Ordovician a radiation of zooplanktonic organisms took place at the same time as a major diversification of suspension feeders. In addition, planktotrophy originated in invertebrate larvae during the Late Cambrian-Early Ordovician. These important changes in the trophic chain can be considered as a major palaeoecological revolution (part of the rise of the Palaeozoic Evolutionary Fauna of Sepkoski). There is now sufficient evidence that this trophic chain revolution was related to the diversification of the phytoplankton, of which the organic-walled fraction is partly preserved. © 2008 The Authors, Journal compilation © 2008 The Lethaia Foundatio
UnivIS-Import:2015-03-09:Pub.2008.nat.dgeo.IGM.LG.theord
Keywords: Acritarchs; Evolutionary radiation; Ordovician; Palaeoecology; Phytoplankton; Trophic chain

The origins and transformation of carbonate mud during early marine burial diagenesis and the fate of aragonite: A stratigraphic sedimentological perspective - Munnecke, Axel; Wright, V. Paul; Nohl, Theresa (Earth-Science Reviews, 2023)
The current understanding of the origins of modern carbonate muds and their early stages of transformations are reviewed. The fine-grained nature of such sediments makes them susceptible to intensive structural and chemical alteration at relatively shallow burial depths driven especially by mineral instability under microbially mediated reactions within the sediment associated with the decay of organic matter. Whereas the transformation of high Mg calcite (HMC) to low magnesian calcite (LMC) generally takes place incongruently and in situ, that of aragonite is predominantly via congruent dissolution. The loss of aragonite produces a huge potential flux of carbonate which is translocated within the sediment. Parallel to studies on Quaternary sediments, investigations in the stratigraphic record have shown that in low-energy settings the transformation of the aragonite component leads to the formation of diagenetic bedding (such as limestone-marl-alternations or LMAs), and related bipartite lithologies, some types of hardgrounds, secondary carbonate mudrocks, and to the significant modification of the original skeletal biota. There are uncertainties such as the exact sources for the precursor aragonite, where the released carbonates reprecipitate in the shallow sediment column, how much carbonate (and hence carbon) is back-fluxed to the water column, how this affects palaeoenvironmental proxies, and the environmental distributions of these processes. The evidence from the stratigraphic record, from settings where organic matter was able to accumulate promoting these transformations, is that these changes in carbonate-rich sediments took place very early, at shallow (decametre or less) burial depths, affecting what we now see from the micron to the outcrop scale. The complexity and inter-relationships of these fundamental processes has received more attention in recent years, though their implications still seem remarkably undervalued.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Bacterial decay of organic matter; Diagenetic bedding; Marine carbonate flux; Micrite; Microspar; Shallow burial marine diagenesis

The overlooked realities of sampling bias - Raja, Nussaïbah Begum; Dunne, Emma; Khan, Tasnuva Ferdous Ming; Nätscher, Paulina (GSA Annual Meeting 2020, 2020)
Analyses of past global biodiversity are severely hindered by sampling biases and gaps in the fossil record. These have previously been attributed to several geological and biological factors such as rock outcrop area, taxonomic definitions, fossil abundance, among others. In many cases, inferred so-called global diversity curves only reflect regional diversity of well-sampled localities. However, global compilations of fossil occurrences, such as from the Paleobiology Database (PBDB), not only reflect the physical aspects of the fossil record, but also document the historical compilation of this data over more than two centuries. In this study, we find that socioeconomic factors such as wealth, language and security may help to explain spatial variation in the compiled data of the PBDB. Countries with high per capita gross domestic product (GDP; implying greater access to research funds), a population with high English proficiency, and greater political stability were generally found to be the countries from which higher number of collections originated and documented in the PBDB. Similarly, we found that these countries also contributed to a majority of the compiled literature from which the data was extracted. The factors identified in this study influence fossil data collection, access and availability by determining who has access to specimens and the ability to do research. As such, efforts towards achieving an understanding of the “real” past global diversity will benefit from investing in scientific education, and more research and collaborations in countries at a disadvantage, with a focus on improving local geological and paleontological knowledg

The pace of shifting climate in marine and terrestrial ecosystems - Burrows, Michael T.; Schoeman, David S.; Buckley, Lauren B.; Moore, Pippa; Poloczanska, Elvira S.; Brander, Keith M.; Brown, Chris; Bruno, John F.; Duarte, Carlos M.; Halpern, Benjamin S.; Holding, Johnna; Kappel, Carrie V.; et al. (Science, 2011)
Climate change challenges organisms to adapt or move to track changes in environments in space and time. We used two measures of thermal shifts from analyses of global temperatures over the past 50 years to describe the pace of climate change that species should track: the velocity of climate change (geographic shifts of isotherms over time) and the shift in seasonal timing of temperatures. Both measures are higher in the ocean than on land at some latitudes, despite slower ocean warming. These indices give a complex mosaic of predicted range shifts and phenology changes that deviate from simple poleward migration and earlier springs or later falls. They also emphasize potential conservation concerns, because areas of high marine biodiversity often have greater velocities of climate change and seasonal shift
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.thepac

The Paleozoic evolution of the gastropod larval shell: larval armor and tight coiling as results of predation-driven heterochronic character displacement - Seuß, Barbara; Nützel, Alexander; Scholz, Henning; Frýda, Jiři (Evolution & Development, 2012)
Early and middle Paleozoic gastropod protoconchs generally differ strongly from their corresponding adult morphologies, that is, most known protoconchs are smooth and openly coiled, whereas the majority of adult shells are ornamented and tightly coiled. In contrast, larval and adult shells of late Paleozoic gastropods with planktotrophic larval development (Caenogastropoda, Neritimorpha) commonly resemble each other in shape and principle ornamentation. This is surprising because habitat and mode of life of planktonic larvae and benthic adults differ strongly from each other. Generally, late Paleozoic to Recent protoconchs are tightly coiled. This modern type of larval shell resembles the adult shell morphology and was obviously predisplaced onto the larval stage during the middle Paleozoic. The oldest known planktonic-armored (strongly ornamented) larval shells are known from the late Paleozoic. However, smooth larval shells are also common among the studied late Paleozoic gastropods. The appearance of larval armor at the beginning of the late Paleozoic could reflect an increase of predation pressure in the plankton. Although there are counter examples in which larval and adult shell morphology differ strongly from each other, there is statistical evidence for a heterochronic predisplacement of adult characters onto the larval stage. Larval and adult shells are built in the same way, by accretionary secretion at the mantle edge. It is likely that the same underlying gene expression is responsible for that. If so, similarities of larval and adult shell may be explained by gene sharing, whereas differences may be due to different (planktic vs. benthic life) epigenetic patterns. © 2012 Wiley Periodicals, Inc
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.thepal

The Paleozoic problematica Wetheredella and Allonema are two aspects of the same organism - Jarochowska, Emilia; Munnecke, Axel (Facies, 2014)
Wetheredella is a calcareous encrusting microproblematicum known only from its two-dimensional expression in thin-sections. It occurs in Cambrian through Permian rocks, often in association with Rothpletzella and Girvanella, probable calcifying cyanobacteria. We show that Wetheredella can be produced by sectioning of the Paleozoic incertae sedis sclerobiont Allonema, which has until now been recognized based on its surface, 3D aspect. Therefore, we propose that Wetheredella should be regarded as a junior synonym of Allonema. Structures resembling Wetheredella have also been obtained in thin-sections through another encrusting microproblematicum, Ascodictyon, which, however, differs in the ultrastructure of its wall, which consists of parallel calcite crystals in contrast to radial crystals in Allonema. Allonema specimens used in the study were extracted from the Middle Silurian Mulde Brick-clay Member (Gotland, Sweden), representing an off-platform environment below the photic zone. This, together with the primary calcitic, radial wall structure of Allonema argues against a cyanobacterial or algal affinity, which had been considered for Wetheredella. The taxonomic position of Allonema remains unresolved, but the sclerobiont shares many common characteristics with some Paleozoic encrusting foraminifers. Combining the occurrence data on Allonema in its surface aspect and the "Wetheredella" aspect recognized in thin-sections may shed more light on its affinity and paleoecological functions, particularly its association with cyanobacteria and its role as a framework-builder in Paleozoic reefs. © 2014 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-14:Pub.2014.nat.dgeo.IGM.LP.thepal
Keywords: Ascodictyon; Cyanobacteria; Pseudo-bryozoans; Ptychocladiidae; Rothpletzella; Tuberitinidae

The Permian-Triassic boundary interval as a model for forcing marine ecosystem collapse by long-term atmospheric oxygen drop - Kießling, Wolfgang; et al. (Geology, 2003)
Ecological traits of reefs across the Permian-Triassic boundary interval coincide with a modeled decline of atmospheric oxygen throughout the Permian Period. Selective extinction and recovery patterns within the reef system are observed both at the end of the middle Permian (end-Guadalupian) and at the Permian-Triassic boundary. The end-Guadalupian event selectively affected corals and broke down the cool-water carbonate factory. Sponges, however, were largely unaffected and bloomed in reefs toward the end of the Permian. The end-Permian total destruction of the metazoan reef system only left behind poorly diverse microbial communities. The temporal reef patterns are thus similar to spatial patterns of modern benthic communities approaching oxygen minimum zones. This observation suggests that a decline in oxygen concentrations was at least partly involved in the destruction of reefs, even where there is no direct evidence of oceanic anoxia.
UnivIS-Import:2015-03-09:Pub.2003.nat.dgeo.IGM.LP.permia
Keywords: Anoxia; Mass extinction; Permian; Recovery; Reefs; Triassic

The potential of carbonate ramps to record C-isotope shifts: insights from the upper Miocene of the Central Mediterranean area - Cornacchia, Irene; Munnecke, Axel; Brandano, Marco (Lethaia, 2020)
The late Miocene is a crucial interval for global climate evolution as well as for the regional geodynamic evolution of the Central Mediterranean area. It spans the transition from the warm Mid Miocene Climatic Optimum, associated with the major Monterey Carbon Isotope Excursion, to the cooler Pliocene, characterized by a bipolar glaciation. Within this climatic transition, during the early Tortonian, a positive carbon isotope excursion related to a global carbon cycle perturbation is recorded, named Carbon Maximum 7 (CM7). In this study, two upper Serravallian–lower Tortonian carbonate ramps of the Central Mediterranean have been analysed: the Latium-Abruzzi and the Apula ramps (Central Apennines, Central Italy). Carbon isotope ratios have been coupled with facies and microfacies analyses with the aims: (1) to identify the CM7 in the Central Mediterranean carbonate ramp successions; (2) to evaluate potential carbonate factory changes or demises related to the CM7; and (3) to discriminate the role of global vs regional factors in affecting the Mediterranean carbonate ramps. The two studied ramps show different evolutions due to regional geodynamics causes. The Latium-Abruzzi ramp drowns in the Tortonian, while the Apula shows a regressive trend, with upper Tortonian middle ramp facies overlying the lower Tortonian outer ramp. Despite the complex geodynamic setting, a positive carbon isotope shift has been identified in both ramps and correlated with the CM7. This positive carbon isotope shift may be linked to the strengthening of the global ocean circulation during the late Miocene cooling. This strengthening of the circulation enhanced the coastal upwelling, bringing nutrient-rich waters to the surface and triggering an enhanced primary productivity consistent with the CM7.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Apennines; C-isotopes; carbonate ramps; late Miocene; Mediterranean

The potential of coralline algae as SST proxy and for climate model evaluation: A New Zealand case study - Kropac, Elena; Mölg, Thomas; Teichert, Sebastian (EGU General Assembly 2022, 2022)
General circulation models (GCMs) are currently the most important tools for obtaining projections about future climate. In addition, they provide data input for regional atmospheric models that translate global climate change to regional and local scales where humans and environments face the impacts. To ensure the accurateness of their simulations, GCMs need to be evaluated as thoroughly as possible against past climate records, where one focus is on the so-called "historical period" (1850–present). However, the evaluation task is difficult for the period before World War II and earlier due to a frequent lack of reliable observations. This problem is exacerbated for the Southern Hemisphere, which has been notoriously understudied in comparison to the climate of the Northern Hemisphere. In New Zealand, variations in sea surface temperature (SST) are reflected on a variety of spatial and temporal scales and are statistically detectable through to temperature anomalies and glacier mass balance changes in the high mountains of the Southern Alps. The correct simulation of SST by GCMs is therefore crucial, especially when investigating the physical mechanisms that transform large-scale SST signals into local climate anomalies by using regional atmospheric modeling. In the project “NZ-PROXY”, we utilize crustose coralline algae (CCA) – a rather recently discovered proxy archive – to extend the observational time series of SST in the New Zealand region back to 1850. The SST reconstruction is then employed in GCM evaluation to reveal their skill in representing the large-scale climate of New Zealand. Finally, high-resolution sensitivity simulations are obtained from a regional atmospheric model to investigate the added value of the advanced GCM selection for regional climate modelin

The reefs of the Arctic - photoautotrophic ecosystem engineers endangered by microplastic and climate change? - Teichert, Sebastian; Löder, Martin; Laforsch, Christian; Pyko, Ines; Schulbert, Christian; Wisshak, Max (The Arctic Biodiversity Congress, 2018)
Large areas of the Svalbard shelf are covered by rhodoliths, coralline red algal structures which form a rigid framework of magnesium calcite. They act as ecosystem engineers, comparable to corals in tropical regions. Additionally, many rhodoliths are gouged by boring mussels and become hollow ecospheres which are intensely colonised by benthic organisms. The existence of both, solid and hollow rhodoliths has a significant impact on local biodiversity. However, this special ecosystem is threatened by the contamination with microplastic. We detected eight different types of microplastic within the bodies of the boring mussels, whereof polystyrene is the most common. If the particles are harmful to the mussels, their future role as niche providers is endangered and the consistency of the whole community is doubtful. Furthermore, we could show that the rhodoliths themselves are endangered by climate change in terms of increased glacial runoff, as coverage with sediments and reduced transparency of the water column are significantly impairing the growth conditions of the rhodoliths. This twofold environmental deterioration will have unpredictable consequences for the associated organisms. This special but extensive ecosystem plays a crucial role on Svalbard’s shelf biodiversity and should be included in future policy recommendations and strategic plans for biodiversity.<br

The relationship between the spectral diversity of satellite imagery, habitat heterogeneity, and plant species richness - Warren, Steven D.; Alt, Martin; Olson, Keith D.; Irl, Severin D. H.; Steinbauer, Manuel; Jentsch, Anke (Ecological Informatics, 2014)
Keywords: Biodiversity; Heterogeneous disturbance; IKONOS; Plant diversity; Remote sensing

The Return of Fossils Removed Under Colonial Rule - Dunne, Emma; Raja Schoob, Nussaibah Begum; Stewens, Paul (2022)
Debates on the restitution of colonial loot usually focus on art, antiquities, religious artefacts, and similar objects. Many fossils of considerable scientific and cultural value were also removed under colonial rule, yet they rarely feature in these discussions despite being classified as cultural objects. This article seeks to shed light on the colonial removal of fossils and explore potential avenues for their return under public international law. Instead of focusing on the (il-)legality of colonial takings, we argue that the right to access culture has developed from the right to participate in cultural life in Article 15(1)(a) of the International Covenant on Economic, Social and Cultural Rights (ICESCR), which provides, if not a solid legal basis, a valuable set of arguments for former colonies requesting the return of fossils looted from their countries/territories of origin. The case study of the negotiations on the return of the Broken Hill skull before the UNESCO Intergovernmental Committee for Promoting the Return of Cultural Property to its Countries of Origin or its Restitution in Case of Illicit Appropriation (ICPRCP) highlights the potential of this mechanism of dispute resolution with respect to fossils. <br

The Rio Sassito sedimentary succession (Ordovician): A pinpoint in the geodynamic evolution of the Argentine Precordillera - Keller, Martin; Lehnert, Oliver (Geologische Rundschau, 1998)
Keywords: Argentine Precordillera; Ordovician; Conodont biostratigraphy; Temperate-water carbonates; Paleogeography

Thermal maturity of Cambrian to Devonian rocks of northeastern Ellesmere Island - Harrison, J. C.; Nowlan, Godfrey; Lehnert, Oliver (Bulletin of the Geological Survey of Canada, 2008)

The role of extinction in large-scale diversity-stability relationships - Simpson, Carl; Kießling, Wolfgang (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2010)
More-diverse communities are thought to be ecologically stable because a greater number of ecological interactions among members allows for the increases in robustness and resilience. Diversity - stability relationships have mostly been studied on short ecological time scales but one study has identified such patterns over million-year time scales in reef communities. Here we propose and test a hypothesis for the mechanism of large-scale diversity - stability relationships in reefs. The extinction of community members destabilizes the community as a whole, unless there is sufficient diversity to buffer the community from the stochastic loss of members, thereby preventing collapse. If genera have high extinction rates, any variation in diversity among communities will result in a diversity-stability relationship. Conversely, in the absence of other mechanisms, the stability of low extinction communities is expected to be independent of diversity. We compare the extinction rates of six reef-building metazoan taxa to patterns of reef community stability and reef volume. We find that extinction of reef-builders occurs independent of reef volume, and that the strength of the diversity-stability relationship varies positively with extinction rate. © 2009 The Royal Society.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.therol
Keywords: Coloniality; Corals; Diversity-stability relationship; Extinction; Reefs

The role of liberation lagerstätten as windows into past biodiversity - Roden, Vanessa; Hausmann, Imelda M.; Nützel, Alexander; Seuß, Barbara; Reich, Mike; Urlichs, Max; Hagdorn, Hans; Kießling, Wolfgang (PaleoBios 36 (Supplement 1), 2019)

The r package divDyn for quantifying diversity dynamics using fossil sampling data - Kocsis, Ádám; Reddin, Carl James; Alroy, John; Kießling, Wolfgang (Methods in Ecology and Evolution, 2019)
Unbiased time series of diversity dynamics are vital for quantifying the grand history of life. Applications include identifying ancient mass extinctions and inferring both biotic and abiotic controls on diversification rates. We introduce divDyn, a new r package that facilitates the calculation of taxonomic richness, extinction and origination rates from time-binned fossil data. State-of-the-art counting protocols, and sampling standardization functions permit the reconstruction of biologically meaningful time series. Additional functions permit the partitioning of turnover rates by environmental affinity. Using divDyn, we display Phanerozoic-scale diversity dynamics of marine invertebrates. With the help of the core function and standard subsampling options, we revisit the hypothesis of declining taxonomic rates over time, mass extinctions and equilibrial diversity dynamics and assess their methodological dependency. Our results suggest that rates declined only over the early Phanerozoic, only three mass extinctions stand out clearly, and evidence of equilibrial dynamics is dependent on the used methods. The modular and fast implementation of published methods ensures traceability, reproducibility and comparability of future studies.
CRIS-Team Scopus Importer:2019-05-02
Keywords: diversity dynamics; extinction; fossil record; origination; Palaeobiology Database; subsampling

The scaling law of climate change and its relevance to assessing (palaeo)biological responses - Kießling, Wolfgang; Eichenseer, Kilian (EGU General Assembly Conference Abstracts, 2014)
It is often argued that current rates of climate change are unprecedented in the geological past. At the same time,the magnitudes of change were often much greater in deep time than they are in history. The most severe globalwarming in the Phanerozoic, with dramatic consequences for life, probably occurred across the Permian-Triassic (P-T) boundary when an increase of tropical water temperatures of 15 ̊C has been observed to occur over a timespan 0.8 myr (Sun et al. 2012), whereas global ocean warming over the last 50 years was 0.35 ̊C (Burrows et al. 2011). When transforming these data into rates of change the P-T rate was roughly 370 times smaller than the currentrate. We argue that the smaller rates of change inferred from geological proxy records are due to a scaling effect,that is, rates of climate change generally decrease with timespan of observation. We compiled from the published literature data on measured or inferred temperature changes and the timespansover which these changes were assessed. Our compilation currently comprises 120 values and covers timespansfrom 20 to 107years. A log-log plot of timespan versus rate of temperature change depicts a highly significantcorrelation (r2= 0.95) of a power-law relationship with an exponent of -0.87. Warming trends show a slightlylower exponent (-0.84) than cooling trends (-0.89) but the explained variance is better for the scaling of warmingtrends. Importantly, the scaled warming trend across the P-T boundary is higher than the current rates of warming. Similar scaling effects are well explored for sediment accumulation rates (Sadler 1981) and evolutionary rates(Gingerich 1993). These have been interpreted as being due to breaks in sedimentation and periods of stasis ortransient reversals, respectively. In case of climate change, transient reversals in general trends are the most likelyexplanation for the scaling relationship. Even relatively rapid intervals of warming, such as the Pleistocene inter-glacials, are not monotonic, but punctuated by short-term cooling intervals. The fossil record tells us that biodiversity responded dramatically to ancient intervals of climate warming. We cannow see that the apparently slower rates of change in some mass extinctions (Permian-Triassic, Triassic-Jurassic)were greater than today when the scaling law is considered. This reassures us that studying deep time patterns oforganismic response to climate change is a worthwhile endeavor that is relevant for predicting the future. References Burrows, M. T., Schoeman, D. S., Buckley, L. B., Moore, P., Poloczanska, E. S., Brander, K. M., Brown, C., Bruno,J. F., Duarte, C. M., Halpern, B. S., Holding, J., Kappel, C. V., Kiessling, W., O’Connor, M. I., Pandolfi, J. M.,Parmesan, C., Schwing, F. B., Sydeman, W. J., and Richardson, A. J.: The pace of shifting climate in marine andterrestrial ecosystems, Science, 334, 652-655, 2011. Gingerich, P. D.: Quantification and comparison of evolutionary rates, American Journal of Science, 293A, 453-478, 1993. Sadler, P. M.: Sediment accumulation rates and the completeness of stratigraphic sections, Journal of Geology, 89,569-584, 1981. Sun, Y., Joachimski, M. M., Wignall, P. B., Yan, C., Chen, Y., Jiang, H., Wang, L., and Lai, X.: Lethally hottemperatures during the Early Triassic greenhouse, Science, 338, 366-370, 201

The sediment composition and predictive mapping of facies on the Propeller Mound-A cold-water coral mound (Porcupine Seabight, NE Atlantic) - Heindel, Katrin; Titschack, Jürgen; Dorschel, Boris; Huvenne, Veerle A.I.; Freiwald, André (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Here we provide a detailed qualitative and quantitative insight on recent sediment composition and facies distribution of a cold-water coral (CWC) mound using the example of the Propeller Mound on the Irish continental margin (Hovland Mound Province, Porcupine Seabight). Five facies types on Propeller Mound are defined: (1) living coral framework, (2) coral rubble, (3) dropstone, (4) hardground, representing the on-mound facies, and (5) hemipelagic sediment facies, which describes the off-mound area. This facies definition is based on already published video-data recorded by Remotely Operated Vehicle (ROV), photo-data of gravity cores, box cores, and dredges from sediment surfaces as well as on the composition of the sediment fraction coarser than 125 μm, which has been analyzed on five selected box cores. Sediment compositions of the living coral framework and coral rubble facies are rather similar. Both sediment types are mainly produced by corals (34 and 35 wt%, respectively), planktonic foraminifers (22 and 29 wt%, respectively), benthic foraminifers (both 7 wt%), and molluscs (21 and 10 wt%, respectively), whereas the living coral framework characteristically features additional brachiopods (6 wt%). Hardgrounds are well-lithified coral rudstones rich in coral fragments (>30 surf%), foraminifers, echinoderms, and bivalves. The dropstone facies and the hemipelagic sediment typically carry high amounts of lithoclasts (36 and 53 wt%, respectively) and planktonic foraminifers (35 and 32 wt%, respectively); however, their faunal diversity is low compared with the coral-dominated facies (12 and <2 wt% coral fragments, 7 and 6 wt% benthic foraminifers, and 4 and 0 wt% balanids). Using the maximum likelihood algorithm within ArcGIS 9.2, spatial prediction maps of the previously described mound facies are calculated over Propeller Mound and are based on mound morphology parameters, ground-truthed with the sedimentary and faunal information from box cores, photographs, and video-data. This method is tested for the first time for CWC ecosystems and provides areal estimates of the predicted facies, as well as suggests further occurrences of living coral frameworks, coral rubble, and dropstones, which are not discovered in the area yet. Thus, sediment composition analysis combined with facies prediction mapping might provide a potential new tool to estimate living CWC occurrences and sediment/facies distributions on CWC mounds, which is an important prerequisite for budget calculations and definition of marine protected areas, and which will improve our understanding of CWC mound formation.

The Silurian of Gotland - Part I: Review of the stratigraphic framework, event stratigraphy, and stable carbon and oxygen isotope development - Calner, Michael; Jeppsson, Lennart; Munnecke, Axel (Erlanger geologische Abhandlungen, Sonderband 5, 2004)
Keywords: Silurian; Gotland; Carbon isotopes; Oxygen isotopes; stratigraphy

The Silurian transgression of a palaeo-shoreline: the area between Old Radnor and Presteigne, Welsh Borderlands - Ray, David C.; Jarochowska, Emilia; Hughes, Helen E.; Claußen, Anna Lene; Tingley, Arthur C.; Moseley, John; Bremer, Oskar (Lithosphere, 2021)
Quarries between Old Radnor and Presteigne, Welsh Borderlands, expose a Silurian nearshore succession, which onlaps a rocky palaeotopography of Neoproterozoic basement that had been uplifted along the Church Stretton Fault Zone. The succession documents the Aeronian to Sheinwoodian transgression of an island or islands, with the following sequence of events: deposition of shallow-marine sandstones (Folly Sandstone Formation); regional uplift; the preservation of a rocky-shoreline and associated deposits (Dolyhir Rudite Member); deposition of limestones characterised by a profusion of coralline algae and the abundant remains of reefs (Dolyhir and Nash Scar Limestone Formation); and finally the deposition of trilobitic silty-mudstones (basal Coalbrookdale Formation). Facies analysis, carbon isotope (δ13Ccarb) values, sequence stratigraphy and collections of bryozoans, conodonts, thelodonts and trilobites, have been used here as a means of refining our stratigraphic understanding of this unique succession. The revised stratigraphy demonstrates many similarities with the adjoining Midland Platform and the wider Silurian world. Notable features include the globally recognised early Sheinwoodian carbon isotope excursion, and sea-level changes of regional and global extent. As one of the best examples of its kind, the palaeo-shoreline and nearshore succession of Old Radnor and Presteigne acts as a depositional model for ancient rocky shores worldwid

The stability of coastal benthic biogeography over the last 10 million years - Kocsis, Ádám; Reddin, Carl James; Kießling, Wolfgang (Global Ecology and Biogeography, 2018)
Aim We demarcate marine benthic global bioregions based on fossil and recent occurrence data. Our main goal is to compare past and present biogeography and to extract major abiotic drivers of biogeographical patterns. We specifically test the hypothesis that global biogeography has changed markedly after the climatic fluctuations of the past 10 Myr. Location Worldwide. Time period Recent; late Miocene?Pleistocene interval. Major taxa studied Benthic taxa with a rich fossil record: Bivalvia, Brachiopoda, Bryozoa, Gastropoda, Echinodermata, Decapoda and reef corals. Methods We use occurrence data from the Ocean Biogeographic Information System (OBIS) and the Paleobiology Database to construct compositional networks and outline objective marine bioregions of benthic marine invertebrates using the 'infomap' community detection algorithm. We assess the association of modern bioregions with a variety of environmental parameters by applying multivariate statistical analyses, such as principal components analysis, random forests and multiple logistic regressions. Results Recent first-order bioregions for the coastal ocean are, in general, consistent across all taxa. Seawater temperature surpasses nutrients, primary production and salinity as a predictor of modern bioregion distributions. Despite substantial climatic variations, late Cenozoic biogeographical patterns recorded in fossils are very similar to modern ones. Main conclusions Biogeographical boundaries within oceans are strongly controlled by temperature gradients, but open oceanic and continental barriers determine the global biogeographical structure. The joint structure of a landmass distribution, deep ocean basins and the latitudinal temperature gradient defines bioregionalization of the benthic marine habitat, which did not change substantially over the past 10 Myr.
Keywords: global; invertebrates; marine; networks; palaeobiogeography; recent biogeography; temperature

The stratigraphic record of the Argentine Precordillera and its plate-tectonic background - Keller, Martin; Buggisch, Werner; Lehnert, Oliver; et al. (The Proto-Andean Margin of Gondwana, 1998)
UnivIS-Import:2015-04-20:Pub.1998.nat.dgeo.IGM.LG.thestr
Keywords: Argentinien; Präkordillere; Stratigraphie. Terrane

The transition from diagenesis to Low Grade Metamorphism in the Argentine Precordillera: An application of the Conodont Colour Alteration Index. - Keller, Martin; Lehnert, Oliver; Buggisch, Werner (Actas, v.1, 1993)
UnivIS-Import:2015-04-16:Pub.1993.nat.dgeo.IGM.LG.thetra

The unexpected species richness of Arctic rhodolith beds - Pyko, Ines; Wisshak, Max; Knebelsberger, Thomas; Halfar, Jochen; Hetzinger, Steffen; Teichert, Sebastian (56. European Marine Biology Symposium, 2023)
Rhodolith beds are an important benthic habitat created by so-called ecosystem engineers. Rhodoliths are free-living, photoautotrophic structures of calcium carbonate (CaCO3) formed by different species of crustose coralline algae (CCA). This particular group of red algae precipitate CaCO3 within their cell walls to form a stable skeleton and next to rhodoliths, they also form crusts of varying thickness on fixed substrates. The shelfs around the high Arctic Svalbard archipelago (Norway) are intensely covered by such rhodolith beds and cm-thick crusts of CCA in shallow waters. The beds occur in water depths of about 10 to 50 m and the algae can live for more than 100 years. Quantitative biodiversity analyses of samples collected by dredge and manned submersible indicate that rhodolith beds form coral reef like structures at higher latitudes and thus represent an important ecological resource. However, research methods outlined above only allow for a snapshot on biodiversity with a focus on the benthic fauna associated with rhodoliths. Furthermore, there are no studies in relation to biodiversity and the CCA crusts. We performed a multi-marker eDNA metabarcoding survey (COX1, rbCL, 16S, ITS) to assess the entire spectrum of potentially occurring species within the Arctic rhodolith beds as well as within the CCA crusts. First results indicate about 650 potentially occurring different taxa (species and genus level). This survey is a step forward in order to estimate the impact of CCA on Svalbard’s shelf biodiversity and provides a background for their inclusion in future policy recommendations and strategic plans for biodiversity conservatio

The Unitary Association method in biochronology and its potential stratigraphic power between benthic and planktic organisms: A case study on foraminifers from Paleocene–Eocene strata of southern Egypt - Abdelhady, Ahmed; Seuß, Barbara; El-Dawy, Mostafa; Obaidalla, Nageh; Hussien, Samar; Mahfouzd, Kamel (Geobios, 2018)
Although foraminifers have been extensively used for biochronology, no quantitative evaluation of the quality of their application is available. In this work we apply a quantitative approach – the Unitary Association (UA) method – to evaluate the relative quality of planktic and benthic foraminifers in biostratigraphy. Based on 12,321 specimens belonging to 65 planktic and 132 benthic foraminifer species in 117 samples from the Paleocene–Eocene strata of the Kharga-Baris Oases (Western Desert, Egypt), the potential stratigraphic resolution power of benthic foraminifers is quantitatively assessed and compared to planktic foraminifers. The UA method accounts for superpositional contradictions between sets of coexisting taxa and generates unitary associations, which are conceptually similar to Oppel zones. The analysis produced fifteen unitary associations for the Paleocene–Eocene benthic Foraminifera of the studied sections, instead of three classical zones; most of these unitary associations are easily identified by the restricted occurrence of a single species. Although planktic Foraminifera have a higher seriation reality leading to a more robust biozonation, benthic Foraminifera have a higher stratigraphic resolution, at least at such regional scale. Furthermore, there was a significant positive correlation between the number of unitary associations and the number of species (R = 0.78 for planktic and 0.70 for benthic foraminifers; both with p < 0.001). These results corroborate that quantitative techniques may lead to a higher resolution in biochronology, even when applied to poor biochronological markers. Moreover, in contrast to simple spatiotemporal analyses, the Unitary Association method can accurately assess the stratigraphic potential of a given taxonomic group.

The youngest ophiocistioid: a first Palaeozoic-type echinoderm group representative from the Mesozoic - Reich, Mike; Stegemann, Tanja R.; Hausmann, Imelda M.; Roden, Vanessa; Nützel, Alexander (Palaeontology, 2018)
Keywords: Carnian; echinoderms; Permian/Triassic fossil record; Italy; ophiocistioids

Thresholds and the species-area relationship: A synthetic analysis of habitat island datasets - Matthews, Thomas; Steinbauer, Manuel; Tzirkalli, Elli; Triantis, Kostas; Whittaker, Robert (Journal of Biogeography, 2014)
Aim: The application of island biogeography theory in habitat fragmentation research assumes a simple relationship between species richness and fragment area. However, previous work has suggested that in some cases thresholds can be detected, at which the form of the island species–area relationship (ISAR) changes abruptly. Piecewise regression has been advocated as a suitable statistical technique to model such thresholds. Here we first provide a comparative analysis of piecewise regression models to determine the prevalence and type of thresholds in habitat island ISARs. Second, we evaluate piecewise regression as a method for locating thresholds in the ISAR, with particular emphasis on the implications of data transformation. Location: World-wide. Methods: Seventy-six habitat island datasets were sourced from the literature. An information theoretic approach was employed to compare linear regression ISAR models with piecewise regression models. The models were applied to untransformed (species–area), semi-log (species–log area) and log–log (log species–log area) data. Three types of piecewise regression models were evaluated: continuous, discontinuous and zero slope. Model performance was compared using the Akaike information criterion. We also examined the influence on model performance of taxon, number of habitat islands, and area of smallest island. Results: Linear regression models performed best, although piecewise models were preferred in a number of cases. Cases in which no model was significant were most prevalent in untransformed space relative to the semi-log and log–log transformations. Piecewise fits were more prevalent in datasets with a larger numbers of islands. Main conclusions: Data transformation is a key part of model selection and needs to be explicitly considered, especially in terms of drawing inferences from models. Piecewise models, even if selected as the favoured model in our analyses, were often ecologically unintelligible in relation to area alone. When detected, breakpoint values ranged over five orders of magnitude, although with one exception all were under 50 ha. Our findings highlight the limitations of using individual threshold values to inform conservation practice.
Keywords: Breakpoint values; Conservation biogeography; Habitat islands; Island biogeography; Piecewise regression; Scale dependency; Small island effect; Species-area relationship; Thresholds

Toarctocera (Gastropoda, Aporrhaidae): a new genus from the Jurassic (Toarcian/Aalenian) of South Germany and the early evolutionary history of the family Aporrhaidae - Gründel, Joachim; Nützel, Alexander; Schulbert, Christian (Palaeontologische Zeitschrift, 2009)
Toarctocera, a new gastropod genus of the family Aporrhaidae (Stromboidea) is described for Rostellaria subpunctata. It occurs in Central Europe (S Germany, N Switzerland, and France) and is commonly one of the most abundant gastropods in Late Toarcian/Early Aalenian soft bottom faunas. Toarctocera subpunctata has extremely elongated apertural spines; this has been interpreted as an adaptation to extremely soft-bottom conditions (snowshoe strategy). The new genus represents one of the earliest certain aporrhaids (Stromboidea). Aporrhaids are probably as old as Late Triassic, and possible Triassic and Early Jurassic species are discussed. Spiniloma is proposed as a nomen novum in order to replace the homonym Spinigera and consequently the family Spinilomatinae replaces the Spinigeridae. The sister group of Stromboidea still needs to be identified. A previously suggested sister group relationship with the Heteropoda is seen as unlikely. © Springer-Verlag 2009.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.toarct
Keywords: Aporrhaidae; Gastropoda; Jurassic; Phylogeny; Stromboidea; Taxonomy

Topography-driven isolation, speciation and a global increase of endemism with elevation - Steinbauer, Manuel; Field, Richard; Grytnes, John-Arvid; Trigas, Panayiotis; Ah-Peng, Claudine; Attorre, Fabio; Birks, H. John B.; Borges, Paulo A. V.; Cardoso, Pedro; Chou, Chang-Hung; De Sanctis, Michele; De Sequeira, Miguel M.; et al. (Global Ecology and Biogeography, 2016)
Keywords: Altitude; biogeographical processes; diversity; ecological mechanisms; endemism; global relationship; isolation; latitudinal gradient; mixed-effects models; sky islands

Towards an assessment of true diversity in fossil ecosystems - Roden, Vanessa; Hausmann, Imelda M.; Nützel, Alexander; Reich, Mike; Kießling, Wolfgang (1st Palaeontological Virtual Congress. Book of abstracts. Palaeontology in a virtual era, 2018)

Towards a new paleotemperature proxy from reef coral occurrences - Lauchstedt, Andreas; Pandolfi, John; Kießling, Wolfgang (Scientific Reports, 2017)
Global mean temperature is thought to have exceeded that of today during the last interglacial episode (LIG, similar to 125,000 yrs b.p.) but robust paleoclimate data are still rare in low latitudes. Occurrence data of tropical reef corals may provide new proxies of low latitude sea-surface temperatures. Using modern reef coral distributions we developed a geographically explicit model of sea surface temperatures. Applying this model to coral occurrence data of the LIG provides a latitudinal U-shaped pattern of temperature anomalies with cooler than modern temperatures around the equator and warmer subtropical climes. Our results agree with previously published estimates of LIG temperatures and suggest a poleward broadening of the habitable zone for reef corals during the LIG.

Towards an unbiased estimate of fluctuations in reef abundance and volume during the Phanerozoic - Kießling, Wolfgang (Biogeosciences, 2006)
The globally preserved number and volume of ancient biogenic reefs is strongly biased by two factors: geological history and research intensity. These biases are sufficiently strong to cast doubts on the biological meaning of the recorded raw pattern. Without adjustment, it is hard to reliably identify factors potentially controlling the waxing and waning of this important ecosystem through time. Although it is currently impossible to completely compensate for the biases, I demonstrate here, based on a comprehensive database of ancient reefs, that spatiotemporal heterogeneities of the biases can largely be evened out by: (1) omitting oceanic reef sites and reef sites only known from subsurface exploration; (2) standardizing for economic factors known to affect research intensity; and (3) adjusting for sedimentary cycling processes. The resulting curves of fossil reef abundance and volume appear quite different from the original ones but the patterns of waxing and waning of the time series are not significantly altered and the overall volatility is not reduced. This suggests that both the raw curves and the adjusted curves correctly depict the basic timing of major reef blooms and declines. Nevertheless, the general pattern of the new curves (maximum proliferation in the middle Paleozoic, decline thereafter) is more in line with patterns of global cratonic carbonate sedimentation than the original curves. The adjusted curves should thus be preferred over the original ones for future tests of potential extrinsic controls of Phanerozoic reef development.
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IGM.LP.toward

Trace Fossil Evidence of Trematode-Bivalve Parasite-Host Interactions in Deep Time. - Huntley, John Warren; de Baets, Kenneth (Advances in Parasitology, 2015)
Parasitism is one of the most pervasive phenomena amongst modern eukaryotic life and yet, relative to other biotic interactions, almost nothing is known about its history in deep time. Digenean trematodes (Platyhelminthes) are complex life cycle parasites, which have practically no body fossil record, but induce the growth of characteristic malformations in the shells of their bivalve hosts. These malformations are readily preserved in the fossil record, but, until recently, have largely been overlooked by students of the fossil record. In this review, we present the various malformations induced by trematodes in bivalves, evaluate their distribution through deep time in the phylogenetic and ecological contexts of their bivalve hosts and explore how various taphonomic processes have likely biased our understanding of trematodes in deep time. Trematodes are known to negatively affect their bivalve hosts in a number of ways including castration, modifying growth rates, causing immobilization and, in some cases, altering host behaviour making the host more susceptible to their own predators. Digeneans are expected to be significant agents of natural selection. To that end, we discuss how bivalves may have adapted to their parasites via heterochrony and suggest a practical methodology for testing such hypotheses in deep tim
Keywords: Bivalve; Fossil; Mollusca; Paleoecology; Paleopathology; Parasitism; Trematode

Traits to live or traits to die? Tracing the development of functional diversity in trees during Cenozoic climate change - Wilkens, Vincent; Walentowitz, Anna; Teichert, Sebastian; Beierkuhnlein, Carl (Macroecology and Biogeography meeting, 2023)

Trajectories of Late Permian Jurassic radiolarian extinction rates: no evidence for an end-Triassic mass extinction - Kießling, Wolfgang; Danelian, Taniel (Fossil Record, 2011)
The hypothesis that ocean acidification was a proximate trigger of the marine end-Triassic mass extinction rests on the assumption that taxa that strongly invest in the secretion of calcium-carbonate skeletons were significantly more affected by the crisis than other taxa. An argument against this hypothesis is the great extinction toll of radiolarians that has been reported from work on local sections. Radiolarians have siliceous tests and thus should be less affected by ocean acidification. We compiled taxonomically vetted occurrences of late Permian and Mesozoic radiolarians and analyzed extinction dynamics of radiolarian genera. Although extinction rates were high at the end of the Triassic, there is no evidence for a mass extinction in radiolarians but rather significantly higher background extinction in the Triassic than in the Jurassic. Although the causes for this decline in background extinction levels remain unclear, the lack of a major evolutionary response to the end-Triassic event, gives support for the hypothesis that ocean acidification was involved in the dramatic extinctions of many calcifying taxa. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LP.trajec
Keywords: Ocean acidification; Radiolarians; Sampling standardization; Triassic

Transferring and implementing the general dynamic model of oceanic island biogeography at the scale of island fragments: The roles of geological age and topography in plant diversification in the Canaries - Otto, Ruediger; Whittaker, Robert J.; Von Gaisberg, Markus; Stierstorfer, Christian; Naranjo-Cigala, Agustin; Steinbauer, Manuel; Borregaard, Michael K.; Ramon Arevalo, Jose; Garzon-Machado, Victor; Del Arco, Marcelino; Maria Fernandez-Palacios, Jose (Journal of Biogeography, 2016)
Aim: The general dynamic model (GDM) of oceanic island biogeography integrates rates of immigration, speciation and extinction in relation to a humped trajectory of island area, species carrying capacity and topographic complexity through time, based on a simplified island ontogeny. In practice, many islands have more complex ontogenies, featuring surfaces of varying age. Here, we extend the GDM to apply at a local scale within islands, and test the predictions analytically within individual islands. Location: El Hierro, La Palma and Tenerife (Canary Islands). Methods: Following the GDM logic, we derive predictions for the distributions and richness of single island endemics (SIEs) across island landscapes of different age. We test these predictions by means of generalized linear models and binominal tests using gridded species occurrence data for vascular plant SIE species and a set of climatic, topographic and terrain age variables. We also examined phylogenetic divergence times for a subset of endemic lineages. Results: Geological age, in interaction with slope, and topographic variables, best explained SIE richness at the landscape scale. About 70% of SIEs had ranges strongly biased to, or largely restricted to old terrain. Available phylogenetic divergence times of SIEs of radiated plant lineages suggested an origin on the older parts of the islands. Metrics of anthropogenic disturbance and habitat availability were unrelated to the observed SIE pattern. Main conclusions: Our findings support the hypothesis that SIEs have evolved and accumulated on older and topographically complex terrain, while colonization processes predominate on the youngest parts. These results imply that evolutionary processes shape species distributions at the landscape scale within islands. This opens the perspective of extending the GDM framework to understand processes at a local scale within individual islands.
Keywords: Canary Islands; Endemic plants; Environmental heterogeneity; General dynamic model; Island biogeography; Island evolution; Landscape diversity; Oceanic islands; Spatial autocorrelation; Species richness patterns

Trend analysis of annual precipitation of Mauritius for the period 1981–2010 - Raja, Nussaïbah Begum; Aydin, Olgu (Meteorology and Atmospheric Physics, 2019)
This study researched the precipitation variability across 53 meteorological stations in Mauritius and different subregions of the island, over a 30-year study period (1981–2010). Time series was investigated for each 5-year interval and also for the whole study period. Non-parametric Mann–Kendall and Spearman’s rho statistical tests were used to detect trends in annual precipitation. A mix of positive (increasing) and negative (decreasing) trends was highlighted for the 5-year interval analysis. The statistical tests nevertheless agreed on the overall trend for Mauritius and the subregions. Most regions showed a decrease in precipitation during the period 1996–2000. This is attributed to the 1998–2000 drought period which was brought about by a moderate La Niña event. In general, an increase in precipitation levels was observed across the country during the study period. This increase is the result of an increase in extreme precipitation events in the region. On the other hand, two subregions, both located in the highlands, experienced a decline in precipitation levels. Since most of the reservoirs in Mauritius are located in these two subregions, this implies serious consequences for water availability in the country if existing storage capacities are kept.
CRIS-Team Scopus Importer:2019-07-19

Triassic-Jurassic carbonates from the Hochfelln Mountain (Northern Calcareous Alps) - Its facies, silicified fauna and implications for the end-Triassic biotic crisis - Seuß, Barbara; Höfling, Richard; Nützel, Alexander (Facies, 2005)
A suite of Early Mesozoic (Late Triassic, Norian to Early Jurassic) calcareous beds was studied from the Hochfelln Mountain in the Northern Calcareous Alps (NCA, South Germany). The Hauptdolomit Group consists of thick peritidal deposits and is overlain by basin deposits of the Rhaetian Kössen Formation and Rhaetian reefoidal limestone with corals. Unlike many other sections in the Tethys realm, coral growth seems to continue into the Jurassic or starts again relatively early within the Early Jurassic. Silicified corals and other marine invertebrates are present in the calcareous, micritic Hochfelln Beds. A re-examination of previously collected ammonite material indicates the presence of Coroniceras sp. which suggests an Early Sinemurian age for the Hochfelln Beds. Abundant sponge spicules (spiculites) suggest that sponges were the source for the silicification. The site produced one of the most diverse Early Jurassic (Sinemurian) gastropod faunas of the NCA (25-30 species, some undescribed). The relatively diverse Early Sinemurian gastropod fauna and coral growth indicate rapid recovery from the end-Triassic biotic crisis. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.profes.triass
Keywords: Corals; End-Triassic mass extinction; Gastropods; Hochfelln; Northern Calcareous Alps; Silicification; Triassic/Jurassic transition

Triassic Reefs of the Tethys - Flügel, Erik; Senowbari-Daryan, Baba (The History and Sedimentology of Ancient Reef Systems, 2001)
The evolution of Triassic reefs started with a long-lasting global crisis of the metazoan reef ecosystem after the Permian—Triassic mass extinction (about 12 Ma), followed by a relatively rapid recovery during the Middle Triassic. Reef systems were differentiated during the Upper Triassic but were severely affected by a global crisis at the Triassic—Jurasic boundary. The present contribution is focused on the biological controls of Triassic reefs, particularly in the Tethyan realm, and on the major changes in reef ecosystems recorded by differences in reef types and reef biota. The term “reef” as used in this chapter refers to bioconstructions characterized by (1) biological control during the formation of the structure (predominantly by sessile benthic organisms), (2) a laterally restricted topographic relief, and (3) (inferred) rigidity of the structure.
UnivIS-Import:2017-11-07:Pub.2001.nat.dgeo.IGM.LP.triass
Keywords: Middle Triassic; Northern Calcareous; Microbial Crust; Reef Mound; Triassic Reef

Trilobites as Hosts for Parasites: From Paleopathologies to Etiologies - de Baets, Kenneth; Budil, Petr; Fatka, Oldřich; Geyer, Gerd (The Evolution and Fossil Record of Parasitism, 2021)
Extant marine arthropods are afflicted by a variety of parasitic diseases making it plausible that extinct trilobites also had a variety of parasites. Direct evidence in the form of preserved parasite body fossils is lacking to date, which is not surprising considering the poor preservation potential of soft tissues of parasites and their hosts. Some of these interactions might leave traces and pathologies in their exoskeletons, which can be traced in deep time. Knowledge of the parasitic causes of pathologies in modern arthropods such as crustaceans and horseshoe crabs might, therefore, help to better interpret past afflictions and their potential culprits. Our review shows that a variety of structures have been attributed to parasitism—some more confidently than others. The restriction of these structures to particular trilobite lineages might indicate the influence of phylogeny, anatomy, and potential role of ecology (feeding, mode of life) on infestation risks. However, preservation and research biases might also contribute to differences between time intervals and individual trilobite lineages. Other interactions such as epizoa, bioerosion, as well as other structures, which have been confused with parasitic causes are briefly discussed. The culprits of many of these structures remain elusive.
Keywords: Paleopathology; Borings; Neoplasia; Shell disease syndrome; Parasitic infestations; Helminths Bacteria

Trilobites from the Red Fauna (latest Emsian, Devonian) of Hamar Laghdad, Morocco and their biodiversity - Crônier, Catherine; Oudot, Morgane; Klug, Christian; de Baets, Kenneth (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2018)
Trilobites are widespread in Early Devonian deposits of north Gondwana; some of the most emblematic ones were collected from the famous latest Emsian (Early Devonian) mudmound locality Hamar Laghdad in south-eastern Morocco. This locality is famous for its trilobites, especially for the conspicuous red-coloured remains of phacopid trilobites with often greenish eyes. Here, we present a taxonomic revision of the previously described trilobites from the so-called Red Fauna of Hamar Laghdad. We introduce the new taxa Harpes hamarlaghdadensis n. sp. and Morocops davidbrutoni n. sp. Phacopids dominate the trilobite assemblage from the Red Cliff at Hamar Laghdad in terms of the number of specimens (represented by Morocops) as a whole. Additionally, we focus on the description of trilobite diversity of this interval compared to Algerian assemblages.<br

Trophic relationships between the large scyphomedusa Chrysaora plocamia and the parasitic amphipod Hyperia curticephala - Riascos, J; Docmac, Felipe; Reddin, Carl James; Harrod, Chris (Marine Biology, 2015)

Tubes or cell sheet? A 3-D reconstruction of Halysis Høeg, 1932, from the Upper Ordovician of South China - Frisch, Konstantin; Munnecke, Axel; Schulbert, Christian; Zhang, Yuandong (Facies, 2012)
Halysis is a microfossil found in Ordovician to Devonian shallow-marine carbonates. Up to now, it is only known from thin-sections, and therefore its three-dimensional shape and its systematic position are controversial. Halysis is described as a chain-like microfossil with a shape of the single “chain links” ranging from circular to rounded rectangular. Given that Halysis commonly co-occurs with calcareous algae, it is assumed to also be an alga. Interpretations of the anatomy propose a filiform or tubiform shape. Even a unistratose sheet of cells has been discussed. Since Halysis is comparatively rare, its shape has not been resolved up to now. For the present study, 52 out of several hundred specimens from an Upper Ordovician shallow-water limestone of South China have been investigated in detail, which for the first time offers the opportunity to analyze a great number of sections through Halysis. A three-dimensional computer model of Halysis has been constructed in order to set up planes sectioning the model. These simulated sections have been compared to those from Halysis in thin-sections. The results show that Halysis represents a microfossil with a morphology consisting of parallel juxtaposed, partly branching tubes. A single sheet of cells, which was recently proposed as shape of Halysis, can clearly be excluded.
Keywords: Calcareous algae; Late Ordovician; South China; 3-D reconstruction; Halysis; Blender

Turnover rates of Paleozoic and modern taxa during the Late Paleozoic Ice Age - Seuß, Barbara; Roden, Vanessa; Kocsis, Ádám; Kießling, Wolfgang (GSA Annual Meeting, 2019)

Über das Alter und Altern von Gesteinen - Koch, Roman; Stollhofen, Harald (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2009)
UnivIS-Import:2015-04-14:Pub.2009.nat.dgeo.IGM.LG.berdas

Über die jurassische Gastropodenfauna der Tongrube Mistelgau bei Bayreuth - Schulbert, Christian; Nützel, Alexander (Berichte der Naturwissenschaftlichen Gesellschaft Bayreuth, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.berdie
Keywords: Gastropoden; Jura; Tongrube; Mistelgau

Ultrastructure of the epidermal gland system of Tetranchyroderma suecicum Boaden, 1960 (Gastrotricha: Macrodasyida) indicates a defensive function of its exudate - Schnier, Jannik; Ahlrichs, Wilko; Gruhl, Alexander; Schulbert, Christian; Teichert, Sebastian; Kieneke, Alexander (Zoomorphology, 2019)
Although the phylum Gastrotricha is known and studied for more than 150 years, some cell types, tissues and organ systems are still not well understood in terms of their morphology, ultrastructure, function and role. One of these features is the epidermal gland system (EGS). As yet, there is just a single detailed electron microscopic investigation of the epidermal glands of the species Turbanella cornuta Remane, 1925, plus scattered ultrastructural data of few additional species. We comprehensively investigated the epidermal glands of Tetranchyroderma suecicum Boaden, 1960 by means of serial sectioning and transmission electron microscopy (TEM) and with scanning electron microscopy. Furthermore, light microscopical, confocal laser scanning microscopical and micro-computed tomographical (μCT) techniques were additionally used for this investigation. Computer programs for 3D-reconstructions were used to analyse the data obtained by TEM and μCT. Tetranchyroderma suecicum possesses up to 100, mostly pairwise arranged, glandulocytes. Each single-celled gland con-tains a large anastomosing secretory cistern with granular content, has a very electron-dense cytoplasm, a basally positioned nucleus, peripherally arranged mitochondria and a cuticulated, ‘chimney-like’ apical neck, which carries the cellular pore. Each merocrine glandulocyte is associated with an adjacent ciliated sensory cell. There is currently no coherent hypothesis of the glandulocytes’ functional role, but different ideas are discussed. We refer to evidence that the secretory product of the EGS of Tetranchyroderma suecicum most likely acts as a repellent against potential predator
Keywords: marine meiofauna; benthos; defence mechanism; reconstruction; 3D modelling

Ultrastructures of porostromate microproblematica from a Mulde Event (Homerian, Silurian) Bioherm in Podolia, Western Ukraine - Castagner, Ariane; Jarochowska, Emilia; Munnecke, Axel; Desrochers, André (Estonian Journal of Earth Sciences, 2015)
The Mulde Event (Homerian, Wenlock) of the Silurian is characterized by a positive δ13C isotope excursion, a stepwise extinction of the hemipelagic fauna and an increase in non-skeletal deposits thought to be microbial, proliferating in shallow marine environments. There is little known about whether the proliferation of microbialites is due to reduced grazing, increased seawater saturation state or an increase in nutrient supply. We have studied a Mulde Event-associated buildup from the Muksha Formation in Bagovytsya, Podolia, Western Ukraine. This buildup differs from a typical Silurian skeletal reef in its low abundance of rugose and favositid corals. The framework of this reef is dominated by stromatoporoids, heliolitid corals and calcimicrobes, the last ones encrusting the stromatoporoids and shells and also forming oncoids. Several microproblematica are present, including Girvanella, Rothpletzella and Hedstroemia, along with Ortonella-like porostromate problematica. This study attempts to further identify the Ortonella-like porostromate problematica and Hedstroemia through SEM analyses which have revealed a recrystallized structure with microdolomite, indicating an originally high-Mg calcite composition. This suggests a red algal affinity or possibly a microbial origin. Our observations may help to constrain the environmental controls on the development of microbial- and microproblematica-dominated deposits during the Mulde Event.
UnivIS-Import:2015-04-14:Pub.2015.nat.dgeo.IGM.LP.ultras
Keywords: Calcimicrobes; Carbon isotope excursion; Hedstroemia; Microbialite; Reefs; Silurian

Understanding Palaeozoic stromatoporoid growth - Kershaw, Stephen; Munnecke, Axel; Jarochowska, Emilia (Earth-Science Reviews, 2018)
Stromatoporoids were abundant components of reefs, reef complexes and associated facies for ca. 100 million years between Middle Ordovician and end-Devonian time. A lot of environmental information stored in their skeletons may be used to develop: a) understanding of stromatoporoid growth controls; and b) interpretations of sedimentary environments in which they lived. General patterns of stromatoporoid distribution are well known, but knowledge of detailed interactions between stromatoporoids and their environments is poorly developed and under-used, potentially of great value in analysis of facies and palaeoecology. From a pool of several thousand specimens examined over four decades, this study identifies four key attributes of stromatoporoids that may be applied to enhance broad-scale knowledge of these fossils and their environments: 1) Substrates: Most stromatoporoids grew directly on wackestone to packstone substrates comprising micrite, clay and bioclasts. Evidence from the relationship between stromatoporoids and sediments demonstrates they were able to grow on soft substrates, but also leads to interpretation of partial lithification of the sea floor (and/or stabilisation by microbial filaments that may not be preserved) in mid-Palaeozoic carbonate facies, with potential implications for models of oceanic carbonate cycling. 2) Growth interruption: Almost all stromatoporoids examined show growth interruption, mostly caused by sedimentation and movement. Stromatoporoids normally recovered quickly and completely from interruption, thus were resilient to interruption events; 3) Associated organisms: Stromatoporoids have abundant associated organisms in two groups: (i) epibiotic encrusters and borers; and (ii) endobiotic organisms embedded in their structure, alive as the stromatoporoids grew. Epibionts used stromatoporoid surfaces that are presumed dead in almost all cases; some are associated with interruption events, but in most cases those were overgrown by successive stromatoporoid growth. Endobionts (mostly corals, plus spirorbids and others) are common to abundant in many stromatoporoid taxa. Stromatoporoid growth was little affected by presence of endobionts but in many cases (commonly restricted to certain stromatoporoid taxa) there was a complex biological interaction valuable in understanding controls on stromatoporoid development. 4) Growth form and taxonomy: Stromatoporoid assemblages are low diversity in almost all cases, regardless of age and facies, with two or three taxa much more abundant than the others. Some stromatoporoid taxa are limited to certain growth forms, thus taxonomic information is very important for facies analysis and palaeobiological interpretations. Stromatoporoids occur commonly with rugose and tabulate corals, both of which could also live on unconsolidated fine-grained substrates, therefore sediment-tolerance cannot be the only reason for stromatoporoid ability to outgrow corals in reefs. Arguments in the literature for photosymbiosis in both stromatoporoids and Palaeozoic corals are currently inconclusive for both fossil groups. Nevertheless, the sum of evidence indicates stromatoporoids were fast-growing, resilient and flexible benthic organisms, in a range of water depths, capable of dealing with soft substrates and largely unaffected by presence of endobionts. These characteristics are interpreted to have made stromatoporoids successful during mid-Palaeozoic time and valuable as tools in facies analysis. Recognition of the four key attributes which encompass all aspects of stromatoporoid growth controls makes palaeobiological study of stromatoporoids, in palaeoenvironmental reconstructions where they occur, readily accessible to researchers.
Keywords: Stromatoporoids Corals Symbionts Sedimentation Substrates Palaeozoic

Understanding the Great Ordovician Biodiversification Event (GOBE): Influences of paleogeography, paleoclimate, or paleoecology? - Servais, Thomas; Harper, David A.T.; Li, Jun; Munnecke, Axel; Owen, Alan W.; Sheehan, Peter M. (GSA Today, 2009)
"The Great Ordovician Biodiversification Event" (GOBE) was arguably the most important and sustained increase of marine biodiversity in Earth's history. During a short time span of 25 Ma, an "explosion" of diversity at the order, family, genus, and species level occurred. The combined effects of several geological and biological processes helped generate the GOBE. The peak of the GOBE correlates with unique paleogeography, featuring the greatest continental dispersal of the Paleozoic. Rapid sea-floor spreading during this time coincided with warm climates, high sea levels, and the largest tropical shelf area of the Phanerozoic. In addition, important ecological evolutionary changes took place, with the "explosion" of both zooplankton and suspension feeding organisms, possibly based on increased phytoplankton availability and high nutrient input to the oceans driven by intense volcanic activity. Extraterrestrial causes, in the form of asteroid impacts, have also been invoked to explain this remarkable even
Keywords: Great Ordovician Biodiversification Event; GOBE; biodiversity; Paleozoic; sea-floor spreading; zooplankton

Uneven spatial sampling distorts reconstructions of Phanerozoic seawater temperature - Jones, Lewis A.; Eichenseer, Kilian (Geology, 2022)
Paleotemperature proxy records are widely used to reconstruct the global climate throughout the Phanerozoic and to test macroevolutionary hypotheses. However, the spatial distribution of these records varies through time. This is problematic because heat is unevenly distributed across Earth's surface. Consequently, heterogeneous spatial sampling of proxy data has the potential to bias reconstructed temperature curves. We evaluated the spatiotemporal evolution of sampling using a compilation of Phanerozoic delta O-18 data. We tested the influence of variable spatial coverage on global estimates of paleotemperature by sampling a steep "modern-type" latitudinal temperature gradient and a flattened "Eocene-type" gradient, based on the spatial distribution of delta O-18 samples. We show that global paleotemperature is overestimated in similar to 70% of Phanerozoic stages. Perceived climatic trends for some intervals might be artifactually induced by shifts in paleolatitudinal sampling, with equatorward shifts in sampling concurring with warming trends, and poleward shifts concurring with cooling trends. Yet, the magnitude of some climatic perturbations might also be underestimated. For example, the observed Ordovician cooling trend may be underestimated due to an equatorward shift in sampling. Our findings suggest that while proxy records are vital for reconstructing Earth's paleotemperature in deep time, consideration of the spatial nature of these data is crucial to improving these reconstructions.
CRIS-Team WoS Importer:2022-02-11

Uneven spatial sampling in Phanerozoic palaeoclimate curves - Jones, Lewis A.; Eichenseer, Kilian (Annual Meeting of the Palaeontological Association, 2019)

Upper Cretaceous (Coniacian-Santonian) low diversity oyster-dominated macrofaunal association in the Eastern Desert of Egypt: Taphonomy versus ecology - Abdelhady, Ahmed Awad; Ayoub-Hannaa, Wagih; Ahmed, Mohamed S.; Hussain, Ali M. (Journal of African Earth Sciences, 2023)
In contrast to the Cenomanian-Turonian, the Coniacian-Santonian macroinvertebrates of the Middle East and North Africa are rarely investigated. Previous investigations indicated the occurrence of low diversity faunal associations, which can be attributed either to ecological (primary/biogenic) or taphonomic (secondary/sedimentologic) factors. The poorly preserved macrofauna of the Hawashia Formation (north Eastern Desert, Egypt) has been quantitively analyzed resulting in the identification of fifteen macrofaunal species including five bivalve, seven gastropod, two ammonite taxa, and one echinoid taxon. The occurrence of the ammonites Metatissotia fourneli Bayle and Texanites (T.) texanus Roemer confirm the Coniacian‒Santonian age for the Hawashia Formation. Based on litho- and biofacies, this fauna likely lived in a normal oxygen tidal-influenced shallow subtidal environment under arid conditions. Taphofacies indicates a low-energy regime with low sedimentation rate. Most shells are highly damaged (encrusted, bioeroded, and fragmented) due to their long residence time in the Taphonomic Active Zone (TAZ). Few of the benthic species have a wide geographic distribution (e.g., Oscillopha dichotoma), which generally imply low sea-level. In contrast, ammonites have been precariously recorded from Africa, Europe, and Asia in addition to South America, outlines a cosmopolitan attitude.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Hawashia formation; Macrofaunal associations; North Africa; Paleoecology; Taphofacies; Upper cretaceous

Upper Triassic reefs of southwestern Turkey: evidence of reef boulders (‘Cipits’) - Flügel, Erik; Link, Michael (Göttinger Arbeiten zur Geologie und Paläontologie, 1996)
Most Carnian and Norian reefs occurring in Southwestern Turkey (Antalya and Isparta region) are represented by redeposited reef talus (“Cipits”). The “Cipits” occur in “Cipit fields” within siliciclastic basinal sediments and represent redeposited parts of sponge and coral patch reefs. Lower Carnian Cipit blocks differ distinctly in faunal composition and association patterns from the Upper Norian/Rhaetina reefs.
Keywords: Cipit; reef; reef talus; sponge; coral; Carnain; Norian; Antalya; Isparta; Turkey

Using abundance data to assess the relative role of sampling biases and evolutionary radiations in Upper Muschelkalk ammonoids - Mcgowan, Alistair J.; Kießling, Wolfgang (Acta Palaeontologica Polonica, 2013)
The Middle Triassic ammonoid genus Ceratites diversified spectacularly within the Germanic Muschelkalk Basin during the Anisian/Ladian (244-232 Mya). Previous studies have interpreted this diversification as a sequence of rapid, endemic radiations from a few immigrant taxa. Here we investigate the possibility that geological and sampling biases, rather than ecological and evolutionary processes, are responsible for this pattern. A new specimen-based dataset of Ceratites species-richness and abundance was assembled. This dataset was combined with 1:200 000 geological maps in a geodatabase to facilitate geospatial analyses. One set of analyses compared species richness per geological map with the number of occurrences and localities per map. Per-map change in the amount of rock available to sample for fossils was also included as a variable. Of these three variables, number of occurrences is the most strongly correlated with richness. Variation in the amount of rock is not a strong determinant of species-richness. However, rarefaction of basin-wide species/abundance data demonstrates that differences in species-richness through time are not attributable to sample size differences. The average percent similarity among sites remained close to 50% throughout the Upper Muschelkalk. The rank abundance distribution (RAD) of species from the first interval of the Upper Muschelkalk is consistent with colonization of a disturbed environment, while the other two intervals have RADs consistent with more stable ecosystems. These results indicate that genuine ecological and evolutionary events are partly responsible for the observed differences in richness and abundance. Although changes in the RADs through time support changes in the ammonoid assemblage structure, the processes underlying increasing richness and change in RADs cannot be explained by increasing geographic distinctiveness or isolation among the ammonoid assemblages present at different localities. © 2013 A.J. McGowan and W. Kiessling. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LP.usinga
Keywords: Ammonoidea; Biodiversity; Ceratites; Muschelkalk; Palaeoecology; Rank abundance; Triassic

Variations in preservation of exceptional fossils within concretions - Saleh, Farid; Clements, Thomas; Perrier, Vincent; Daley, Allison C.; Antcliffe, Jonathan B. (Swiss Journal of Palaeontology, 2023)
Concretions are an interesting mode of preservation that can occasionally yield fossils with soft tissues. To properly interpret these fossils, an understanding of their fossilization is required. Probabilistic models are useful tools to identify variations between different Konservat-Lagerstätten that are separated spatially and temporally. However, the application of probabilistic modeling has been limited to Early Paleozoic Konservat-Lagerstätten preserved in shales. In this paper, the patterns of preservation of three concretionary Konservat-Lagerstätten—the Carboniferous Mazon Creek (USA) and Montceau-les-Mines (France), and the Silurian Herefordshire Lagerstätte (UK)—are analyzed using a statistical approach. It is demonstrated that the degree of biotic involvement, i.e., the degree to which a carcass dictates its own preservation, is connected to internal organ conditional probabilities—the probabilities of finding an internal organ associated with another structure such as biomineralized, sclerotized, cuticularized, or cellular body walls. In concretions that are externally forced with little biological mediation (e.g., Herefordshire), all internal organ conditional probabilities are uniform. As biological mediation in concretion formation becomes more pronounced, heterogeneities in conditional probabilities are introduced (e.g., Montceau-les-Mines and Mazon Creek). The three concretionary sites were also compared with previously investigated Konservat-Lagerstätten preserving fossils in shales to demonstrate how the developed probability framework aids in understanding the broad-scale functioning of preservation in Konservat-Lagerstätten.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Carboniferous; Concretions; Exceptional fossils; Konservat-Lagerstätte; Silurian

Variations in primary aragonite, calcite, and clay in fine-grained calcareous rhythmites of Cambrian to Jurassic age - an environmental archive? - Munnecke, Axel; Westphal, Hildegard (Facies, 2005)
Limestone-marl alternations represent a common type of fine-grained calcareous rhythmites during the entire Phanerozoic. Their diagenetic overprint, however, obliterates their value for palaeoenvironmental interpretations. The original mineralogical composition of the carbonate fraction (aragonite, high-Mg calcite, low-Mg calcite) would potentially yield important information on palaeoenvironmental conditions: for example shallow-water carbonate factories are usually characterised by extensive aragonite production, whereas pelagic carbonate production is dominated by calcitic organisms. Therefore, a reconstruction of the pre-diagenetic mineralogical composition of limestone-marl precursors would be desirable. A particularly conspicuous attribute of fine-grained calcareous rhythmites is the intercalation of two rock types that have undergone two entirely different diagenetic pathways (“differential diagenesis”). As indicated by earlier petrography work, in the interlayers selective aragonite dissolution has taken place, and the dissolved aragonite provided the cement for the limestones. Primary aragonite usually is not preserved in diagenetically mature fine-grained limestones. However, in a recently published paper a method is proposed to quantify the primary mineralogical composition of the precursor sediments of a fine-grained calcareous rhythmite. Here we apply this method to several published data sets from sections of Cambrian to Jurassic age. We try to answer the following questions: Where does the aragonite come from, especially during times of “calcite seas”? What is the impact of the enhanced pelagic carbonate production since the Late Jurassic on the formation of limestone-marl alternations? How much dissolved aragonite is lost to sea water during early marine burial diagenesis, i.e. how closed is the diagenetic system? As demonstrated for the five examples shown here, the new method for reconstructing primary mineralogy potentially provides insight into ancient depositional environments, surface productivity, and ocean chemistr
Keywords: Limestone-marl alternations; Differential diagenesis; Aragonite; Precursor sediment; Calcareous plankton; Phanerozoic

Vertebrate remains and conodonts in the upper Silurian Hamra and Sundre formations of Gotland, Sweden - Bremer, Oskar; Jarochowska, Emilia; Märss, Tiiu (GFF, 2019)
A long history of geological research on the island of Gotland, Sweden, has resulted in a detailed biostratigraphy based on conodonts for the Gotland sedimentary succession, but the relation between the Hamra and Sundre formations, the youngest strata on southern Gotland, has remained poorly resolved. These formations have also remained relatively poorly described in terms of vertebrates compared to other parts of the succession. A survey of museum collections and newly sampled material reveal that the taxonomical compositions and richness of vertebrate faunas remain similar compared to the underlying Burgsvik Sandstone and Oolite members. However, the relative abundance of the respective groups changes: Paralogania ludlowiensis and rare osteostracan remains of Tahulaspis sp. only occur in samples from the lower Hamra Formation, while Thelodus sculptilis becomes more common in samples from Sundre Formation. Conodont and isotope data give support to previous suggestions that the Hamra and Sundre formations may be largely isochronous, and it is possible that the observed differences in vertebrate faunas reflect changes in depositional setting. This interval on Gotland has been suggested to represent a hiatus in the East Baltic sections, where younger strata show an increased importance of acanthodians in the vertebrate faunas. Gotland could therefore give insights into the early stages of this diversification of gnathostomes during late Silurian times. However, this has to be done in combination with data from other areas, as well as with a review and revision of the scale-based taxonomy of Silurian acanthodians from the Baltic Basin.<br
Keywords: Vertebrate microremains; conodonts; isotope stratigraphy; upper Silurian; Gotland; Sweden

Victims of ancient hyperthermal events herald the fates of marine clades and traits under global warming - Reddin, Carl James; Kocsis, Ádám; Aberhan, Martin; Kießling, Wolfgang (Global Change Biology, 2020)
Organismic groups vary non-randomly in their vulnerability to extinction. However, it is unclear whether the same groups are consistently vulnerable, regardless of the dominant extinction drivers, or whether certain drivers have their own distinctive and predictable victims. Given the challenges presented by anthropogenic global warming, we focus on changes in extinction selectivity trends during ancient hyperthermal events: geologically rapid episodes of global warming. Focusing on the fossil record of the last 300 million years, we identify clades and traits of marine ectotherms that were more prone to extinction under the onset of six hyperthermal events than during other times. Hyperthermals enhanced the vulnerability of marine fauna that host photosymbionts, particularly zooxanthellate corals, the reef environments they provide, and genera with actively burrowing or swimming adult life-stages. The extinction risk of larger sized fauna also increased relative to non-hyperthermal times, while genera with a poorly buffered internal physiology did not become more vulnerable on average during hyperthermals. Hyperthermal-vulnerable clades include rhynchonelliform brachiopods and bony fish, whereas resistant clades include cartilaginous fish, and ostreid and venerid bivalves. These extinction responses in the geological past mirror modern responses of these groups to warming, including range-shift magnitudes, population losses, and experimental performance under climate-related stressors. Accordingly, extinction mechanisms distinctive to rapid global warming may be indicated, including sensitivity to warming-induced seawater deoxygenation. In anticipation of modern warming-driven marine extinctions, the trends illustrated in the fossil record offer an expedient preview.
CRIS-Team Scopus Importer:2020-12-04
Keywords: climate change; extinction; fossil; metabolic activity; photosymbiont; selectivity

Vision and the diversification of Phanerozoic marine invertebrates - Aberhan, Martin; Nuernberg, Sabine; Kießling, Wolfgang (Paleobiology, 2012)
Identifying biological traits that promote evolutionary success is fundamental for understanding biodiversity dynamics and for assessing the evolutionary response of organisms to global change. We tested the hypothesis that image-forming eyes have contributed to the diversification of taxa in the geological past. Using fossil occurrences in the Paleobiology Database, we analyzed the diversity and evolutionary rates of more than 17,000 Phanerozoic genera of marine invertebrates living on or above the shallow-water seafloor according to their visual capabilities. Analysis of the complete data set shows a peak in the proportional diversity of sighted genera early in the Phanerozoic, and their continuance at a relatively low and stable level after the Ordovician. As an explanation of this pattern we suggest that selection pressure to develop eyes rose in the Cambrian, and that behavioral constraints had a balancing effect thereafter. In contrast to the pooled data, a clade-level study of those subgroups that contain both sighted and blind genera revealed thatin trilobites, all epifaunal bivalves, pectinoid bivalves, gastropods, and echinodermssighted genera diversified more strongly than blind genera. This difference is controlled by significantly raised extinction rates of blind genera. These more finely resolved patterns support the hypothesis that good vision is a key trait that promoted preferential diversification. © 2012 The Paleontological Society. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.vision

Vitinellopsis nov. gen., a new calcareous alga (Chlorophyta, Bryopsidales) from the Silurian of Gotland (Sweden), and the tribe Vitinelleae nov. nom - Vachard, Daniel; Bucur, Ioan I.; Munnecke, Axel (Geobios, 2021)
The algal genus Vitinellopsis nov. gen. is well represented in the Silurian limestones of Gotland (Sweden). This new taxon is interpreted as a calcified codiacean alga (Chlorophyta, Bryopsidales). In the studied material, the calcareous wall of sparry calcite, probably originally aragonitic, appears well preserved. The subcylindrical thallus, with rounded ends, rarely bifurcated, measures up to 27 mm long and 2.5 mm wide. The medullar zone exhibits 4–6 longitudinal, subtly undulating siphons; the subcortical zone shows inflated, vesiculiform radial siphons, and the cortical zone displays small, relatively short acrophorous siphons. The status of the tribe Vitinelleae nomen novum, formerly Bothryelleae, is discussed. Given its abundance, ease of identification, and short stratigraphic range, Vitinellopsis gotlandica nov. gen., nov. sp. may prove useful for regional correlations, facies and paleobiogeographic studies.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Bryopsidales; Calcareous algae; Codiaceae; Gotland; New taxa; Silurian

Volcanism of the Central Atlantic magmatic province as the trigger of environmental and biotic changes around the Triassic-Jurassic boundary - Pálfy, József; Kocsis, Ádám (Special Paper of the Geological Society of America, 2014)
In the last decade, major advances have been made in our understanding of the end-Triassic mass extinction, related environmental changes, and volcanism of the Central Atlantic magmatic province. Studies of various fossil groups and synoptic analyses of global diversity document the extinction and subsequent recovery. The concomitant environmental changes are manifested in a series of carbon isotope excursions (CIE), suggesting perturbations in the global carbon cycle. Besides the earlier-recognized initial and main negative anomalies, a more complex picture is emerging with other CIEs, both negative and positive, prior to and following the Triassic-Jurassic boundary. The source of isotopically light carbon remains debated (methane from hydrate dissociation vs. thermogenic methane), but either process is capable of amplifying an initial warming, resulting in runaway greenhouse conditions. Excess CO2 entering the ocean causes acidification, an effective killing mechanism for heavily calcified marine biota that appears implicated in the reef crisis. The spatial and temporal extent of Central Atlantic magmatic province volcanism is established through a growing data set of radiometric ages. Since the Central Atlantic magmatic province is one of the largest Phanerozoic large igneous provinces, volcanic CO2-driven warming is plausible as a key factor in the chain of Triassic-Jurassic boundary events. Greenhouse warming may have been punctuated by short-term cooling episodes due to H2S emission and production of sulfate aerosols, a process more difficult to trace in the stratigraphic record. Taken together, recently generated data significantly increase the support for Central Atlantic magmatic province volcanism as a viable trigger for the environmental and biotic changes around the Triassic-Jurassic boundary.

Vorwort zum 60-jährigen Bestehen der der Geologischen Blätter für NO-Bayern - Koch, Roman; Baier, Alfons; Schulbert, Christian (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2011)
UnivIS-Import:2015-04-14:Pub.2011.nat.dgeo.IGM.LAG.vorwor

Wear, tear and systematic repair: testing models of growth dynamics in conodonts with high-resolution imaging - Shirley, Bryan; Grohganz, Madleen; Bestmann, Michel; Jarochowska, Emilia (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2018)
Conodont elements are the earliest mineralized vertebrate dental tools and the only ones capable of extensive repair. Two models of conodont growth, as well as the presence of a larval stage, have been hypothesized. We analysed normally and pathologically developed elements to test these hypotheses and identified three ontogenetic stages characterized by different anisometric growth and morphology. The distinction of these stages is independently corroborated by differences in tissue strontium (Sr) content. The onset of the last stage is marked by the appearance of wear resulting from mechanical food digestion. At least five episodes of damage and repair could be identified in the normally developed specimen. In the pathological element, function was compromised by the development of abnormal dent ides. This development can be reconstructed as addition of new growth centres out of the main growth axis during an episode of renewed growth. Our findings support the model of periodic retraction of elements and addition of new growth centres. Changes in Sr content coincident with distinct morphology and lack of wear in the early life stage indicate that conodonts might have assumed their mature feeding habit of predators or scavengers after an initial larval stage characterized by a different feeding mode.
Keywords: vertebrate; teeth; conodont; chordate; growth dynamics; apatite

Wechselspiel der Sphären: Fein verzahnte Kreisläufe steuern das System Erde. - Kenkmann, Thomas; Kießling, Wolfgang (Als das Leben laufen lernte, 2007)
Keywords: System Erde; Geobiologie; Evolution; Stoffkreisläufe

What caused the Ordovician biodiversification? - Munnecke, Axel; Servais, Thomas (Palaeogeography, Palaeoclimatology, Palaeoecology, 2007)
Keywords: Ordovician; Ordovician Radiation; IGCP; Palaeogeography; Palaeoclimate; Early Palaeozoic

What is boring? - Arctic reef structures as a habitat for boring organisms - Pyko, Ines; Munnecke, Axel; Schulbert, Christian; Wisshak, Max; Teichert, Sebastian (The Arctic Biodiversity Congress, 2018)
The coralline red algal species Lithothamnion glaciale forms rigid frameworks of magnesium calcite. These so called rhodoliths cover large areas of the Svalbard shelf. Thereby, the calcified structures act as ecosystem engineers, comparable to corals in tropical regions, providing habitat for a large variety of organisms. Drilled by boring mussels, many rhodoliths become hollow ecospheres and their interior is intensely colonized by benthic macro- and megafauna. Based on a non-destructive 3-D visualization analysis via micro-computed tomography (µCT), we investigated whether the calcified skeleton itself provides a habitat for certain microorganisms also. Here, we present a first overview of boring microorganisms in Svalbard’s rhodoliths. This study is a contribution to enhance our knowledge about the complicated interrelationships in this large-scale ecosystem. Therefore, it is a step forward in order to estimate the impact of the rhodoliths on Svalbard’s shelf biodiversity and provides a background for their inclusion in future policy recommendations and strategic plans for biodiversit

What is conservation paleobiology? Tracking 20 years of research and development - Dillon, Erin M; Pier, Jaleigh Q; Smith, Jansen A.; Raja Schoob, Nussaibah Begum; Dimitrijevic, Danijela; Austin, Elizabeth L; Cybulski, Jonathan D.; De Entrambasaguas, Julia; Durham, Stephen R; Grether, Carolin; Haldar, Himadri Sekhar; Kocáková, Kristína; et al. (Frontiers in Ecology and Evolution, 2022)
Conservation paleobiology has coalesced over the last two decades since its formal coining, united by the goal of applying geohistorical records to inform the conservation, management, and restoration of biodiversity and ecosystem services. Yet, the field is still attempting to form an identity distinct from its academic roots. Here, we ask a deceptively simple question: What is conservation paleobiology? To track its development as a field, we synthesize complementary perspectives from a survey of the scientific community that is familiar with conservation paleobiology and a systematic literature review of publications that use the term. We present an overview of conservation paleobiology’s research scope and compare survey participants’ perceptions of what it is and what it should be as a field. We find that conservation paleobiologists use a variety of geohistorical data in their work, although research is typified by near-time records of marine molluscs and terrestrial mammals collected over local to regional spatial scales. Our results also confirm the field’s broad disciplinary basis: survey participants indicated that conservation paleobiology can incorporate information from a wide range of disciplines spanning conservation biology, ecology, historical ecology, paleontology, and archaeology. Finally, we show that conservation paleobiologists have yet to reach a consensus on how applied the field should be in practice. The survey revealed that many participants thought the field should be more applied but that most do not currently engage with conservation practice. Reflecting on how conservation paleobiology has developed over the last two decades, we discuss opportunities to promote community cohesion, strengthen collaborations within conservation science, and align training priorities with the field’s identity as it continues to crystallize.<br

Where are all the fossil pennatulacean octocorals? The need for more research on modern sea pens - Roden, Vanessa; Reich, Mike (Beiträge zur Paläontologie 32, 2011)

Where traditional extinction estimates fall flat: using novel cophylogenetic methods to estimate extinction risk in platyhelminths - Mulvey, Laura; Warnock, Rachel; De Baets, Kenneth (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2022)
Today parasites comprise a huge proportion of living biodiversity and play a major role in shaping community structure. Given their ecological significance, parasite extinctions could result in massive cascading effects across ecosystems. It is therefore crucial that we have a way of estimating their extinction risk. Attempts to do this have often relied on information about host extinction risk, without explicitly incorporating information about the parasites. However, assuming an identical risk may be misleading. Here, we apply a novel metric to estimate the cophylogenetic extinction rate, Ec, of parasites with their hosts. This metric incorporates information about the evolutionary history of parasites and hosts that can be estimated using event-based cophylogenetic methods. To explore this metric, we investigated the use of different cophylogenetic methods to inform the Ec rate, based on the analysis of polystome parasites and their anuran hosts. We show using both parsimony- and model-based approaches that different methods can have a large effect on extinction risk estimation. Further, we demonstrate that model-based approaches offer greater potential to provide insights into cophylogenetic history and extinction risk.
CRIS-Team Scopus Importer:2022-09-09
Keywords: conservation; cophylogenetic extinction risk; cophylogenetics; host–parasite interactions; parasites; platyhelminths

Will arctic reefs disappear with ongoing global change? - Pyko, Ines; Munnecke, Axel; Teichert, Sebastian (macro 2019 – Bridging local patterns and global challenges, 2019)
Aim: The coralline red algal species Lithothamnion glaciale forms rigid frameworks of magnesium calcite. In the high Arctic, these so-called rhodoliths cover large areas of the Svalbard shelf. Thereby, the calcified structures act as ecosystem engineers, comparable to corals in tropical regions, providing habitat for a large variety of organisms. Furthermore, drilled by boring mussels, many rhodoliths become hollow ecospheres and their interior is intensely colonized by benthic macro- and megafauna. Within this study, we investigate whether the distribution pattern of these arctic reefs will be affected by ongoing global change. Rhodolith beds occur worldwide and have similar ecological impact. Because the effects of global change are projected to be most severe and fast within the Arctic, this ecosystem represents a very appropriate model also for the global impact on rhodolith communities. Location: This study involves rhodolith beds around the Svalbard shelf in the high Arctic. Methods: The distribution of L. glaciale is linked to local ranges of physical parameters like temperature, pH, light regime, and salinity. Following the RCP scenarios provided by the IPCC, we estimate the influence of anticipated large-scale shifts on the rhodoliths. Based on these results, we analyse the future functioning of rhodoliths as niche-providing ecosystem engineers. Results: The first results of this ongoing study indicate that increasing temperatures enhance the respiration of the algae. However, this effect will be outcompeted by reduced water transparency – and therefore reduced photosynthesis – induced by deglaciation. Main conclusions: The geographical distribution of Arctic rhodolith beds is threatened by global change. Due to their key role as ecosystem engineers, this might also result in a decrease of Arctic biodiversity.<br

Windward and leeward margins of an Upper Ordovician carbonate platform in the Central Tarim Uplift, Xinjiang, northwestern China - Zhang, Yuanyuan; Li, Yue; Wang, Guan; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
In the Central Uplift of the Tarim Basin, northwestern China, the Katian (Upper Ordovician) limestones of the Lianglitag Formation extend from outcrops in the Bachu area to the subsurface in the Tazhong Oil Field (TZOF) area. Reefs and inner platform deposits are the dominant facies throughout the formation. The reef composition illustrates a palaeoecologic gradient from microbial-dominated buildups on the northwestern margin to metazoan-dominated reefs on the eastern and southern margins of the platform. Between these areas no outcrops are present. In the present study, data including litho- and biofacies logs and correlations from eight wells are presented, six of them of the region between Bachu and Tazhong, and two wells along the former platform margin from the TZOF. Calcimicrobial carbonates are common in core from the inner platform part. Benthic biota documented here resembles that of the microbial mounds and bioclastic limestones in the Bachu outcrop area, and thus is considered as the eastward extension of this realm. However, metazoan-dominated boundstones formed by corals, stromatoporoids, sponges together with calcareous algae are abundant along the southern platform margin, and are similar in composition to the reefs of TZOF in the easternmost part of the platform. The palaeoecologic differentiation between microbial- and metazoan-dominated reefs suggests a strong environmental gradient from a well-oxygenated windward eastern and southern side of the platform, which favoured the open ocean and which was dominated by metazoan reefs, and the inner platform as well as the northwestern, leeward margin of the platform with warmer, less-oxygenated water, which favoured the growth of microbial carbonates. Assuming the trade winds as cause for the contrasting facies on both sides of the platform a palaeo-position of Tarim south of the ITCZ seems probable because a position north of it would require a post-Ordovician clockwise rotation of Tarim of about 90° which is possible but less probabl
Keywords: Palaeoecologic gradient; Palaeogeographic implication; Metazoan reef; Microbialite; Lianglitag Formation

Wirt-Gast-Komplexe von [bfu.bfu.bfu]: Vorhersage von Ionenselektivitäten mittels quantenchemischer Rechnungen XIII - Palmer, Ursula; Puchta, Ralph (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2020)
The CH2-O-C2H4-O-CH2 moieties in Lehn's cryptand [2.2.2] have been substituted by 2,2′-bifurane groups to get the cryptand [bfu.bfu.bfu]. The ion selectivity of this new cryptandwas investigated by DFT calculations (RB3LYP/LANL2DZp, RB3LYP/LACVP∗, RBP86/LANL2DZp and RBP86/LACVP∗) based on model equations and analysis of the [M ⊂ bfu.bfu.bfu]n+ cryptate structures. The cryptand [bfu.bfu.bfu] is best suited for the alkali cations Na+ and K+, and the alkaline earth cation Sr2+ followed by Ca2+. The cavity of [bfu.bfu.bfu] is thus similar to that in [phen.phen.phen] or [bpy.bpy.bpy]. The selectivity of [bfu.bfu.bfu] is due to the flexibility of the OCCO und CN·NC dihedral angles. The results are independent of the selected DFT methods.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Cryptates; DFT calculations; Selectivity of ion complexation; Supramolecular chemistry

Zlichovian faunas with early ammonoids from Morocco and their use for the correlation of the eastern Anti-Atlas and the western Dra Valley - de Baets, Kenneth; Klug, Christian; Plusquellec, Yves (Bulletin of Geosciences, 2010)
Two sections were sampled and measured at Mdaour-El-Kbir (Dra Valley, western Anti-Atlas) and at eastern Ouidane Chebbi (Tafilalt, eastern Anti-Atlas). In situ elements of two partially limonitized and one carbonatic fauna were found in both sections. We report this fauna from the upper Merz-Akhsai Formation and the lower Mdaour-el-Kbir Formation at Mdaour-el-Kbir for the first time. Based on these faunas, we recorded a correlation of the early Emsian (Zlichovian) strata in the Tafilalt and the Dra Valley regions, which are about 350 km apart. Additionally, new ammonoid finds (Teicherticeras cf. senior, Lenzites gesinae, Weyeroceras angustus) are figured and described including the stratigraphic context. The diagnoses of Lenzites gesinae and Weyeroceras angustus are emended. Tabulate corals (Michelinia mdaourensis sp. nov., Petridictyum sp.) found in both the Tafilalt and Dra Valley are figured and described for the first time.
Keywords: early Emsian; Ammonoidea; Tabulata; Micheliniidae; biostratigraphy; Anti-Atlas; Morocco

δ13C records across the late Silurian Lau event: New data from middle palaeo-latitudes of northern peri-Gondwana (Prague Basin, Czech Republic) - Lehnert, Oliver; Frýda, Jiři; Buggisch, Werner; Munnecke, Axel; Nützel, Alexander; Křiž, Jiři; Manda, Štěpán; Lehnert, Oliver (Palaeogeography, Palaeoclimatology, Palaeoecology, 2007)
During the late Silurian the Prague Basin was located in middle southern latitudes. In contrast to palaeocontinents positioned in tropical and subtropical latitudes like Baltica, no reefs are developed, which is in accordance with the predicted cooler water. The Prague Basin represents a relatively restricted and shallow rift basin with a complex tectonic history. Sections in different palaeoenvironments have been studied to document the most prominent Silurian stable carbon isotope excursion recorded during the late Silurian (Ludfordian) Lau Event from this part of peri-Gondwana. Deeper water deposits of the Kopanina Formation investigated in the present study were deposited on the slope-to-basin transition near the Kosov volcanic centre in the western part of Prague Basin. The sediments are developed as an alternation of dark, partly laminated limestones and marls with an increase of the limestone-marl ratio in the upper part of the succession. A pronounced positive carbon isotope excursion starts in the Neocullograptus kozlowskii graptolite and in the upper Polygnathoides siluricus conodont zone. The maximum of the shift is observed in the lower part of an interval characterised by the Ananaspis fecunda-Cyrthia postera community. The maximum values scatter around 8‰, which represent the highest values reported hitherto from the Prague Basin. In low latitudes, often a decrease of δC values towards deeper water settings is reported. In contrast, in the present study the δC values of about 8‰ are much higher than those recorded from the contemporaneous shallow-water sections studied in the classical Mušlovka and Požáry quarries. The most reasonable explanation is the presence of stratigraphical gaps in the shallow parts of the basin. As indicated by karstification these gaps were caused by a sea-level drop. Another effect of this sea-level fall was a strongly reduced sedimentation of the cephalopod limestone facies around volcanic and tectonic elevations. © 2006 Elsevier B.V. All rights reserve
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IGM.LG.d13cre
Keywords: Silurian; Ludlow; Lau Event; Stable isotopes; Prague Basin; Peri-Gondwana

Ammonites from the Oxfordian-Kimmeridgian boundary and the Lower-Upper Kimmeridgian of Kachchh, western India - Pandey, Dhirendra Kumar; Alberti, Matthias; Fürsich, Franz; Glowniak, Ewa; Olóriz Sáez, Federico (Volumina Jurassica, 2013)
Several new specimens of ammonites from the Oxfordian and Kimmeridgian of Kachchh, western India, are described and illustrated. The Oxfordian ammonites ?Subdiscosphinctes Malinowska, Perisphinctes Waagen, Dichotomoceras Buckman, and ?Larcheria Tintant, all from Bharodia in the Wagad Uplift, enable tentative biochronostratigraphic correlations with the uppermost Middle Oxfordian up to the lower Upper Oxfordian of the unified Submediterranean zonation, whereas the Kimmeridgian ammonites Streblites Hyatt, “Orthosphinctes” Schindewolf, Torquatisphinctes Spath, Pachysphinctes Dietrich, Katroliceras Spath, Aspidoceras Zittel, and Schaireria Checa reconfirm a stratigraphic gap embracing incompletely known parts of the uppermost Oxfordian and the Lower Kimmeridgian as known from the ammonite records of the Kachchh Mainland of the Kachchh Basin.
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.ammoni_2
Keywords: ammonites; Kachchh; India; Oxfordian-Kimmeridgian boundary

Ammonites from the Oxfordian strata of Gangta Bet, Kachchh, western India - Pandey, Dhirendra Kumar; Alberti, Matthias; Fürsich, Franz (Journal of the Palaeontological Society of India, 2013)
Gangta Bet, an islet situated in the salt marshes of the Great Rann of Kachchh, western India, is composed of Jurassic strata containing a rich fauna of Upper Oxfordian ammonites which are very rare in other parts of the Kachchh Basin. A detailed bed-by-bed collection yielded 148 ammonites belonging to 21 taxa which are briefly described and illustrated. The assemblage is strongly dominated by members of the genus Perisphinctes Waagen, 1869, which are excellent guide fossils enabling intrabasinal and intercontinental correlations e.g., with the ammonite zonation of Europe. While the oldest beds on the Gangta Bet did not yield ammonites indicative of a certain biozone, most of the recorded taxa can be assigned to the Bifurcatus Zone (Stenocycloides and Grossouvrei subzones) of the Upper Oxfordian.
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.ammoni
Keywords: Oxfordian; Ammonite; Saltmarsh; Zonation; Jurassic; Fossil; Fauna; Basin; Europe

Ammonites of the genera Peltoceras Waagen, 1871, Metapeltoceras Spath, 1931, and Euaspidoceras Spath, 1931 from the Upper Callovian and Oxfordian of Kachchh, western India, and their biostratigraphic potential - Pandey, Dhirendra Kumar; Alberti, Matthias; Fürsich, Franz (Journal of the Palaeontological Society of India, 2015)
Members of the family Aspidoceratidae Zittel, 1895 dominate the ammonite assemblage of the Upper Callovian of the Kachchh Basin. With the appearance of the genus Perisphinctes Waagen, 1869 in the Early Oxfordian they lose their dominance, but still form a relatively diverse group. In the present study, 32 ammonites from the Kachchh Basin in western India have been assigned to 18 taxa belonging to the genera Peltoceras Waagen, 1871, Metapeltoceras Spath, 1931, and Euaspidoceras Spath, 1931. Due to co-occurring ammonites as well as comparisons with European sections, most of these taxa can be attributed to ammonite zones of the Upper Callovian to lower Upper Oxfordian: Athleta Zone (Peltoceras kachhense, P. aff. kachhense, P. ponderosum, Metapeltoceras armiger, M. aff. armiger, M. cf. kumagunense, M flavum, Euaspidoceras acanthodes), Mariae-Cordatum zones (Euaspidoceras aff. babeanum), Cordatum Zone (Euaspidoceras waageni, E. simile, E. badiense), Cordatum-Transversarium zones (Euaspidoceras sparsispinum), PI icatilis-Bifurcatus zones (Euaspidoceras wagurense), and Bifurcatus Zone (Euaspidoceras varians, E. aff. jeanneti).
UnivIS-Import:2017-12-18:Pub.2015.nat.dgeo.IGM.LP.ammoni_5
Keywords: Ammonoids; taxonomy; biostratigraphy; Jurassic; Kachchh Basin; India

Biofacies, taphonomy and palaebiogeography of the Kamar-e-Mehdi Formation of east-central Iran, a Middle to Upper Jurassic shelf lagoon - Fürsich, Franz; Pan, Yan-Hong; Wilmsen, Markus; Majidifard, Mahmoud Reza (Facies, 2016)
The Callovian–Lower Kimmeridgian Kamar-e-Mehdi Formation of the western Tabas Block, part of the Central-East Iranian Microcontinent, represents the fill of an extensive carbonate shelf lagoon situated between a barrier carbonate platform in the east and the uplifted Yazd Block in the west. In the course of its development, the shelf lagoon experienced increasing isolation which, together with a climatic change to more arid conditions, led to deposition of evaporites and severe restriction of the benthic fauna. Sedimentation in the predominantly low-energy lagoon was controlled by an influx of fine-grained carbonate from the neighboring platform, biogenic carbonate production within the lagoon and episodic influx of siliciclastic material by high-density currents from the uplifted western margin. Much of the succession is composed of meter-scale asymmetric cycles that record decreasing terrigenous input as well as increasing shelliness and substrate firmness due to a decreasing sedimentation rate. They are interpreted as small-scale climatic cycles recording changes in humidity. Larger-scale cycles, comprising 250–400 m in thickness, document changes in terrigenous influx and may also be climate-controlled, although a tectonic origin cannot be excluded. The shelf lagoon was populated by several level-bottom communities and small patch reefs. The latter are of low diversity, composed of calcareous sponges, corals, or oysters, and are usually associated with thick microbial crusts. The level-bottom assemblages are dominated by bivalves, and rarely also by gastropods or brachiopods. Fossils occur scattered or concentrated in pavements and beds. Shell concentrations are autochthonous to allochthonous, most commonly parautochthonous. Concentrating agents were storm-induced flows and low sedimentation rates, less commonly also storm-waves. Within the small-scale cycles, infaunal assemblages prevail but are replaced by epifaunal assemblages at their top. The latter are commonly dominated by the bivalves <i style="margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; font-size: 13px; line-height: inherit; font-family: Arial, san-serif; vertical-align: baseline; color: rgb(50, 50, 50);">Pseudopecten tipperi and <i style="margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; font-size: 13px; line-height: inherit; font-family: Arial, san-serif; vertical-align: baseline; color: rgb(50, 50, 50);">Camptonectes (<i style="margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; font-size: 13px; line-height: inherit; font-family: Arial, san-serif; vertical-align: baseline; color: rgb(50, 50, 50);">Grandinectes) <i style="margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; font-size: 13px; line-height: inherit; font-family: Arial, san-serif; vertical-align: baseline; color: rgb(50, 50, 50);">teres, the two most characteristic faunal elements of the shelf lagoon. Diversity values of the benthic fauna were low to moderate. Environmental stress was mainly produced by elevated salinity values, at times possibly intensified by lowered oxygen values and soft substrate conditions. Paleobiogeographically, the benthic macrofauna exhibits a close relationship to that of European shelf seas but contains some immigrants from the southern shores of the Tethys and the northwestern Pacific. The degree of endemism was low (two taxa).
Keywords: Shelf lagoon; Jurassic; East-central Iran; Taphonomy; Paleoecology; Paleobiogeography

Bivalve concentrations in the Upper Jurassic of Portugal - Fürsich, Franz; Werner, Winfried; Schneider, Simon (Palaeobiodiversity and Palaeoenvironments, 2009)
UnivIS-Import:2017-12-18:Pub.2009.nat.dgeo.IGM.LP.bivalv

Brachiopods from the Middle to Upper Jurassic strata of Gangta Bet in the Kachchh Basin, western India - Mukherjee, Debahuti; Alberti, Matthias; Fürsich, Franz; Pandey, Dhirendra Kumar (Journal of the Palaeontological Society of India, 2017)
Gangta Bet, situated between the Wagad Uplift and Khadir Island in the Kachchh Basin, is composed of Callovian to Oxfordian fossiliferous sedimentary rocks, in which brachiopods are an important component, especially in a local marker horizon (the Brachiopod Bed). In total, six taxa are discussed here: Bihendulirhynchia brevicostata, Kallirhynchia versabilis, Mycerosia rostellata, Somalithyris jhalarensis, and two Kutchithyris species, K. euryptycha and K. ingluviosa. The genera Mycerosia and Bihendulirhynchia are new records from Kachchh and the occurring species have been previously known from the Middle to Upper Jurassic of Somalia, the Sinai Peninsula, Arabia, and the Northwest Frontier Province (Khyber Pakhtunkhwa) of Pakistan. Somalithyris, previously recorded from the Tithonian of Kachchh, is also present in the Callovian-Oxfordian Gangta member. This is the oldest record of the genus globally and the presence of the same species in Kachchh and Pakistan is also significant. These new descriptions from Kachchh are therefore of high palaeobiogeographic importance as they strengthen the existence of free faunal exchange between Kachchh, East Africa and Arabia during the Callovian- Oxfordian, and reveal a midway position of the North West Frontier Province of Pakistan.
UnivIS-Import:2018-02-22:Pub.2017.nat.dgeo.IGM.LP.brachi
Keywords: brachiopods; middle to upper Jurassic; Gangta Bet; Kachchh Basin; Western India; sedimentary rocks

Calcispongia from the Middle and Upper Jurassic of the Shotori Mountains, northeast Iran. Part I. Mammillopora Bronn, Tremospongia D´Orbigny, Stellispongia Goldfuss, Enaulofungia Fromentel, and Dehukia N. Gen - Senowbari-Daryan, Baba; Fürsich, Franz; Rashidi, Koorosh (Rivista Italiana Di Paleontologia E Stratigrafia, 2011)
Middle to Upper Jurassic shelf lagoon, platform, and slope deposits, called the Esfandiar Limestone Formation and Qal-eh Dokhtar Formation, respectively, are widespread in the Shotori Mountains of east-central Iran. Although small in-situ patch reefs are known only from the shelf lagoon, reef organisms (corals, sponges) are common as allochthonous components in slope deposits of the Qal-eh Dokhtar Formation and in proximal basinal silty marls of the Korond Formation. Here, some massive calcisponges, including the new genus Dehukia, are described comprising the taxa Mammillopora iranica n. sp., Mammillopora polyosculata n. sp., Tremospongia pulvinaria (Goldfuss), Tremospongia pellisfera n. sp., Dehukia maxima n. sp., Dehukia raisossadati, Dehukia media n. sp., Stellispongia stellata (Goldfuss), and Enaulofungia globosa n. sp.
UnivIS-Import:2017-12-18:Pub.2011.nat.dgeo.IGM.LP.calcis
Keywords: Sponges; Systematic; Mammillopora; Tremospongia; Stellispongia; Enaulofungia; Dehukia; Jurassic; Shotori Mountains; Iran

Callovian-Oxfordian (Jurassic) bivalves from the Kamar-e-Mehdi Formation of east-central Iran - Fürsich, Franz; Pan, Yan-Hong (Beringeria, 2014)
e Kamar-e-Mehdi Formation (Callovian – Oxfordian) is the ll of a shelf lagoon situated in the western and central parts of the so-called Tabas Block for a N-S distance of 200-300 km. From the predominantly ne-grained carbonates, which in the depocenter reach more than 1000 m in thickness, 69 taxa of bivalves are described, which dier greatly in their preservation depending on their original shell mineralogy. Aragonitic taxa are only preserved as internal or composite moulds, whereas calcitic taxa occur in shell preservation. New to science is the pectinid Camp- tonectes (Grandinectes) teres subgen. nov. et sp. nov. and the pholadomyid Agrawalimya tubularis sp. nov. Most of the taxa are common also in the Middle und Upper Jurassic of Europe. Exceptions are the genera Agrawalimya, which so far is known only from the Callovian of Kachchh, western India, and Neoburmesia, which is solely known from Japan.
UnivIS-Import:2017-12-18:Pub.2014.nat.dgeo.IGM.LP.callov
Keywords: Bivalvia; taxonomy; Callovian; Oxfordian east-central Iran

Casearia QUENSTEDT and Cypellia POMEL (Hexactinellida, Porifera) from the Jurassic of the Shotori Mountains, east-central Iran - Senowbari-Daryan, Baba; Fürsich, Franz (Rivista Italiana Di Paleontologia E Stratigrafia, 2013)
The hexactinellid sponge genera Casearia Quenstedt, Caseispongia Quenstedt, and Cypellia Pomel are all morphologically similar and externally annulated. Caseispongia is internally a chambered sponge, like the hypercalcified genus Amblysiphonella. The internal construction of almost all externally annulated specimens illustrated as Casearia by Quenstedt and some other authors is not known enough. Despite of this lack of knowledge the genus name Caseispongia is synonymized with Casearia based on observations of Muller and the description of Schmidel. Both genera were described originally from the Upper Jurassic of southern Germany. Hexactinellid sponges, described in this paper, are reported for the first time from the Jurassic of the Shotori Mountains in east-central Iran. The following species are new to science: Casearia tabasensis, Cypellia irregularis, C. cylindrica, and C. tabulata.
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.casear
Keywords: Casearia; Caseispongia; Cypellia; Iran; Jurassic; Porifera; Shotori Mountains

Cellicalichnus antiquus isp. nov., an Early - Middle Jurassic arthropod brood structure from the Shemshak Group of north-eastern Iran - Fürsich, Franz; Wilmsen, Markus; Taheri, Jafar (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2010)
The new ichnospecies Cellicalichnus antiquus from upper Lower to lower Middle Jurassic strata of the Shemshak Group of north-eastern Iran consists of bundles of horizontal tunnels, from which at regular intervals elongate cells opposing each other emerge. The burrow has been constructed in floodplain deposits of a braided river system. It is interpreted as an arthropod brood structure of either insects, most likely hymenopterans, which may belong to the ancestral stock of soil-dwelling bees, or else of terrestrial crustaceans (crayfishes). © 2009 Schweizerbart'sche Verlagsbuchhandlung, Stuttgart, Germany.
UnivIS-Import:2017-12-18:Pub.2010.nat.dgeo.IGM.LP.cellic
Keywords: Arthopods; Brood structure; Iran; Lower jurassic; Trace fossils

Dinosaur footprints from the Thaiat ridge and their palaeoenvironmental background, Jaisalmer Basin, Rajastan, India - Pienkowski, Grzegorz; Brański, Pawel; Pandey, Dhirendra Kumar; Schlögl, Ján; Alberti, Matthias; Fürsich, Franz (Volumina Jurassica, 2015)
Two dinosaur footprints: Eubrontes cf. giganteus and Grallator tenuis, both attributed to theropods, have been found in the Lower Jurassic Thaiat Member of the Lathi Formation at the Thaiat ridge, near Jaisalmer in western Rajasthan, India. The footprints were left in sediments of a tidal origin, located in profile a few meters above a marked transgressive/flooding surface. They show different states of preservation – the smaller Grallator tenuis represents a well-preserved concave epirelief footprint on the upper surface of a carbona-ceous sandstone containing nerineid gastropod shells, while the bigger Eubrontes cf. giganteus footprint shows a rare state of preservation as a positive epirelief on the top of a calcareous sandstone bed, where recent erosion exposed the footprint cast by removing the mud above and around the footprint. The Thaiat ridge section has been amended in its lower part, to indicate the marked transgressive surface. Geo-chemical analyses and calculated weathering indices (such as CIA) show that the hinterland climate was seasonal to semi-arid during deposition of that part of the succession.
UnivIS-Import:2017-12-18:Pub.2015.nat.dgeo.IGM.LP.dinosa
Keywords: Dinosaur footprints; Thaiat ridge; palaeoenvironment; Jaisalmer Basin; Rajasthan

Dispersal events of Triassic-Jurassic boundary faunas, and palaeoenvironment of Tibetan Himalaya - Yin, Jiarun; Fürsich, Franz (Science in China Series D-Earth Sciences, 2009)
End-Triassic ammonoid and bivalve faunas of the Germig area, Tibetan Himalaya, lived in a tropical, shallow-water environment during the Triassic-Jurassic boundary interval. High stratigraphic resolution based on ammonite-biochrons allows to tracing the place of origin of several faunal elements. The bivalves Aguilerella and Ctenostreon occurred first in the Tibetan Himalaya and migrated from there to the eastern South Pacific, exhibiting a pantropic dispersal pattern. This dispersal route is supported by the distribution pattern of the ammonites Choristoceras, Discamphiceras, Pleuroacanthites, and Psiloceras calliphyllum. A few taxa, which went extinct everywhere else by the end of the Triassic, survived in the Tibetan Himalaya into early Early Jurassic times. They include the ammonites Choristoceras and Eopsiloceras, and the bivalves Newaagia, Terquemia, Persia, Ryderia guangdongensis, and Cultriopsis angusta. This suggests that the Tibetan Himalaya may have played a refugia role in the course of the end-Triassic mass extinction.
UnivIS-Import:2017-12-18:Pub.2009.nat.dgeo.IGM.LP.disper
Keywords: end-Triassic mass extinction; paleobiogeography; bivalves; ammonites

Early Cretaceous volcanism and preservation of the Jehol Biota in western Liaoning, NE China - Jiang, Baoyu; Fürsich, Franz; Sha, Jin-Geng; Wang, Bo; Niu, Yazhuo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">The so-called Jehol Biota, an excellently preserved Early Cretaceous biota consisting of both lacustrine and terrestrial organisms, is one of the most important Mesozoic fossillagerstätten. Although there have been extensive palaeontological studies, little work has been done on the volcanic settings under which the biota was preserved. The Sihetun area is the most famous fossil locality of the Jehol Biota in western Liaoning, and the volcanic succession in that area is the most representative and best studied. We use a case study of the volcanic succession of the Lower Cretaceous Yixian Formation in the Sihetun area to reconstruct the volcanic complexes and their history, to propose a depositional model of the volcanic successions, and to understand the relationship between volcanic activity and fossil preservation in western Liaoning. The volcanic succession comprises four volcanic complexes, each with distinct products; a shield volcano, an intermediate multi-vent center, a volcanic lake (in summit caldera), and finally lava domes. The presence of a caldera is postulated from exposures which suggest the presence of an inner topographic wall, bounding faults, and intra-caldera fill. Frequent volcanic activities and widespread existence of volcanic lakes during the Early Cretaceous are thought to account for the exceptional preservation of invertebrates and vertebrates of the Jehol Biota in western Liaoning.
UnivIS-Import:2017-12-18:Pub.2011.nat.dgeo.IGM.LP.earlyc
Keywords: Early Cretaceous; Volcanism; Jehol Biota; Western Liaoning; NE China

Ecophenotypic plasticity versus evolutionary trends - morphological variability in Upper Jurassic bivalve shells from Portugal - Schneider, Simon; Fürsich, Franz; Schulz-Mirbach, Tanja; Werner, Winfried (Acta Geologica Polonica, 2010)
Upper Jurassic marginal marine strata of the Lusitanian Basin (central Portugal) yield a rich benthic macro fauna from which three bivalve target taxa, i.e., Arcomytilus, Isognomon, and Eomiodon, were chosen for morphometric studies, because of their abundance both in space and time and their variability in shell shape. The shells have been analysed with regard to outline shape (Fourier shape analysis), dimensions, ornamentation (Arcumytilus) and ligament arrangement (Isognomon). Additionally, data on co-occurring fauna and palaeotemperatures calculated from δ18O values have been recorded. The results of the morphometric analyses have been interpreted with regard to phytogeny and palaeoecology. In all target taxa, a distinct, rapid size increase at around the Early/Late Kimmeridgian boundary is evident. Potential causes for this process are discussed, and an increase in food availability is regarded the most likely scenario. In Isognomon rugosus, a distinct change in resilifer arrangement co-occurs with size increase, resulting in the evolution of an endemic species in the Lusitanian Basin, for which the name Isognomon lusitanicus is re-established. Like in several extant Mytilidae, morphological species characterisation in Arcomytilus turns out unsatisfactory, due to high intra-specific variability. However, Arcomytilus morrisii is still regarded as a valid species that evolved in the Lusitanian Basin. Despite high shape variability, Eomiodon securiformis is also considered to be a clearly distinguished species. For all target taxa morphologic variability is discussed with regard to environment, and variation between populations is delineated. The data suggest a weak correlation of facies and shell shape in Arcomytilus, while Isognomon lusitanicus seems to develop local varieties in different subbasins. Finally, the great morphologic plasticity of bivalves from rather distinct systematic entities is shown to result from different causes, thus demonstrating that careful studies of the involved species are a prerequisite to draw correct palaeoecological conclusions.
UnivIS-Import:2017-12-18:Pub.2010.nat.dgeo.IGM.LP.ecophe
Keywords: Bivalvia; ecophenotypy; Fourier shape analysis; Late Jurassic; morphometry; Portugal; size increase

Facies analysis of a higly cyclic sedimentary unit: the Late Hauterivian to Early Barremian Agua de la Mula Member of the Agrio Formation, Neuquén Basin, Argentina - Archuby, Fernando Miguel; Fürsich, Franz (Beringeria, 2010)
is article contains the facies analysis of the highly cyclic Upper Hauterivian to Lower Barremian Agua de la Mula Member of the Agrio Formation (Neuquén Basin, Argentina). e study was developed to test the hypothesis that the occurrence of particular facies can be predicted every time the sequence stratigraphic model can be applied. e multi-facetted approach based on detailed bed-by-bed collection of sedimentological, stratigraphic, ichnological, taphonomic, and palaeoecological data led a precise palaeoenvironmental interpretation within a controlled bio- and sequence-stratigraphic framework. e facies and facies associations are based mainly on lithological aspects. ree main groups of facies and facies as- sociations are distinguished: (a) siliciclastic, (b) mixed, and (c) carbonate. e rst group comprises facies and facies associations linked to regressive phases of short sequences (so-called dilution hemi-sequences) and is characterised by deposition of terrigenous siliciclastic material, while the second and third group include rocks varying widely in terms of composition that share a condensed nature (so-called starvation hemi-sequences). Together they form starvation/ dilution sequences. Siliciclastic facies dominate over mixed ones. Carbonate facies are the least represented. e distinct heterogeneity of facies types and successions correlates with both, the observed cyclic patterns and the upward reduction in siliciclastic input. e starvation/dilution sequences, which shape the cycle pattern, are present throughout the sections. ey consist of alternations of terrigenous-starved and terrigenous-diluted beds. Features of starvation/dilution sequences change according to their position within the sections, but there is always a contrast between the lower starved and the upper diluted hemisequence. Facies of starvation/dilution sequences are ner- or coarser-grained, following the deepening and shallowing trend, respectively of major sedimentary sequences. Predictions of facies occurrence can be improved, if the position within the sedimentary sequence (transgressive systems tract or regressive systems tract) is also considered. In this way, facies of starvation/dilution sequences corresponding to the early/late transgression and regression as well as to the maxi- mum ooding zone can be predicted. Superimposed cyclicities of dierent hierarchies alter the resulting patterns. Most of the Agua de la Mula Member of the study area can be interpreted to represent a siliciclastic open ramp. Carbonate-rich beds formed as concentrations of invertebrate hard-parts produced during terrigenous starvation in a siliciclastic system during transgressions rather than by increased carbonate production. e reduced terrigenous input observed in the last 150 m of the two investigated sections resulted in facies that can be better explained by carbonate models. However, even in this setting siliciclastic facies are well represented during major regressions.
UnivIS-Import:2017-12-18:Pub.2010.nat.dgeo.IGM.LP.facies
Keywords: sedimentary cycles; lower cretacious; argentina

High resolution ostracod records of borehole PRD05 and the late Quaternary palaeoenvironment in Pearl River Delta - Liu, Chun-lian; Fürsich, Franz; Dong, Yi-xin; Che, X.-G.; Zhuang, C. (Journal of Palaeogeography, 2008)
A high resolution study has been carried out on the sediments and ostracod faunas of borehole PRD05 drilled near the Xijiang inlet in the Pearl River Delta area. The analytical results suggest that the interplay between sea level fluctuations and river processes led to the environmental changes in the study area during the Late Quaternary. A fluvial environment began to develop before 26600a BP. Coarse-grained sediments at the bottom of the core indicate a very high energy condition. The reduction of grain size upwards implies a decrease of energy and fluvial overbank was developed. Between 26600 and 13400a BP,the environment was characterized by a flood plain. The upper part of the fluvial sediments experienced weathering and erosion during the last maximum glacial episode and was changed to the variegated clay. The postglacial transgression occurred around 13400a BP. In the first phase of transgression,a marsh environment dominated in the study area. At around 9000a BP,the rate of sea level rise rapidly increased and an estuary environment with marine-brackish ostracod faunas continuously existed until 4850a BP. Three second-order sea level fluctuations can be recognized based on the composition and abundance of ostracods. The maximum transgression occurred between 7500 and 7140a BP,evidenced by the highest diversity and abundance of ostracods in the borehole. Since 4850a BP,a regressive trend was recorded in the borehole. The environment gradually changed into a deltaic plain with the increased influence of river processes.
UnivIS-Import:2017-12-18:Pub.2008.nat.dgeo.IGM.LP.highre
Keywords: ostracods; paleoenvironment; Pearl River Delta

High resolution palaeoecological and taphonomic analysis of Early Cretaceous lake biota, western Liaoning (NE-China) - Fürsich, Franz; Sha, Jin-Geng; Jiang, Baoyu; Pan, Yan-Hong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2007)
The faunal content of eighteen bedding planes within the Jianshangou Unit of the Lower Cretaceous Yixian Formation of western Liaoning has been analysed in detail in order to understand the environmental and taphonomic framework of this famous lacustrine fossillagerstätte. The bedding planes were excavated within a 3 m thick section, which is composed of laminated mudstones, graded sandstones and mudstones, and horizontally stratified structureless sandstones and tuffs. All investigated bedding planes occur within the laminated mudstone facies and contain elements of the so-called Jehol Biota, in particular the conchostracan Eosestheria ovata, the ephemerid nymph Hexagenites trisetalis and the crustacean Liaoningogriphus quadripartitus. These three faunal elements occur in high abundance, originally possessed chitinous skeletons and are preserved as compressed, faintly mineralized coats or, in the case of Eosestheria, still possess organic material. The specimens do no represent exuviae, but body fossils. The fossils can be grouped into three low diversity associations, each characterized by one of the three taxa. The plan-view orientation of the taxa is invariably random and size frequency histograms are bimodal or polymodal. This indicates that the fauna is autochthonous and that the histograms reflect several recruitment phases. Apparently, the faunal elements suffered seasonal mass mortality caused by anoxic conditions, which became established in the lake during the summer months. Increased humidity during the winter led to mixing of the lake waters, re-establishment of oxic conditions and to deposition of a thin film of sediment. Such environmental conditions were episodically interrupted by flash floods and volcanic ash falls, which may have been responsible for the preservation of the more spectacular elements of the Jehol biota such as birds and feathered dinosaurs. © 2007 Elsevier B.V. All rights reserved.
UnivIS-Import:2017-12-18:Pub.2007.nat.dgeo.IGM.LP.highre
Keywords: China; Ecosystem; Lake; Liaoning; Lower Cretaceous; Taphonomy

Ichnology of lower Jurassic beach deposits in the Shemshak Formation at Shahmirzad, southeastern Alborz Mountains, Iran - Fürsich, Franz; Wilmsen, Markus; Seyed-Emami, Kazem (Facies, 2006)
A 19 m thick package of well-sorted lowermost Jurassic (Hettangian-Lower Sinemurian?) sandstones within the Shemshak Formation of the southeastern Alborz Mountains displays features characteristic of foreshore to upper shoreface environments such as tabular bedding, low-angle lamination, trough cross-stratification, parting lineation, and oscillation ripples. In contrast to most other beach successions recorded in the literature the sandstones contain a trace fossil assemblage characterised by low abundance but comparatively high diversity. The assemblage, comprising 14 ichnotaxa, is dominated by Palaeophycus heberti, Rhizocorallium irregulare, Gyrochorte comosa, and Parahaentzschelinia surlyki. Contrary to predictions, which assume a dominance of suspension-feeders in such high-energy environments, the trace fossil assemblage represents a variety of ethological groups ranging from suspension-feeders to deposit-feeders, detritus-feeders, scavengers, and a possible trap constructor (Ctenopholeus), whereby deposit-feeders predominate. This anomaly is explained by a high amount of organic detritus in the sediment, indicated by abundant plant material, and a position of the beach in the vicinity of a river mouth. © Springer-Verlag 2006.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.ichnol
Keywords: Alborz Mountains; Beach; Jurassic; Shemshak Formation; Trace fossils

Jurassic corals from the Jaisalmer Basin, western Rajasthan, India - Pandey, Dhirendra Kumar; Fürsich, Franz; Baron-Szabo, Rosemarie (Zitteliana, 2009)
The ﬁrst comprehensive taxonomic description of Jurassic corals from the Jaisalmer Basin, a pericratonic shelf basin on the northwestern slope of the Indian peninsular shield, is based on 75 specimens, which belong to ﬁve suborders, seven families, nine genera, and ten species. In Upper Bajocian rocks, all corals belong to the suborder Faviina, in Middle Bathonian rocks 75% of the specimens are members of the Stylinina, whereas corals occurring in the Tithonian all belong to the Caryophylliina.
UnivIS-Import:2017-12-18:Pub.2009.nat.dgeo.IGM.LP.jurass
Keywords: Jurassic; scleractinian corals; taxonomy; Jai-salmer Basin; India

Jurassic corals from the Shemshak Formation of the Alborz Mountains, Iran - Pandey, Dhirendra Kumar; Fürsich, Franz (Zitteliana, 2006)
Nineteen taxa of scleractinian corals are described and figured from the Toarcian-Lower Bajocian part of the Shemshak Formation of the Alborz Mountains. Dominant taxa are Isastrea, Microsolena, Trigerastraea, Periseris, and Collignonastraea. Most of these corals occur near the top of the formation (Lower Bajocian), close to the top of a large-scale shallowing cycle. Scattered specimens are found in transgressive lags of small-scale parasequences in the Toarcian part of the succession. Corals are very rare in the Shemshak Formation with the exception of Rian, NE of Semnan, where strongly reduced sedimentation rates facilitated the establishment of coral meadows and a patch reef in a mixed carbonate-siliciclastic setting on the crest of a tilted fault block.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.jurass
Keywords: Alborz Mountains; Jurassic; Scleractinia; Shemshak Formation; Taxonomy

Late Pleistocene to Holocene palaeoenvironmental changes documented by microfaunas and shell stable isotopes in the southern Pearl River delta plain, South China - Liu, Chun-lian; Fürsich, Franz; Wu, J.; Dong, Yi-xin; Yang, T.; Yin, Jiarun (Journal of Palaeogeography, 2013)
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.latepl

Lower Cretaceous corals from the Koppeh Dagh, NE-Iran - Pandey, Dhirendra Kumar; Fürsich, Franz; Baron-Szabo, Rosemarie; Wilmsen, Markus (Zitteliana, 2007)
A new section through parts of the Middle Aptian to Early Albian Sanganeh Formation at the southwestern margin of the Koppeh Dagh, NE-Iran, displays a succession of silty to fine-sandy marls between which limestone boulders and debris layers are intercalated at several levels. These boulders are olistoliths, derived from the edge of a nearby carbonate platform, long since eroded. Most of the olistoliths are reef limestones built of corals and calcareous sponges. At two levels, the reef fauna weathered out from the boulders and could be collected. Fourtyseven taxa of Scleractinia have been described and figured, which considerably extend our knowledge of the biodiversity of Cretaceous corals from the area. The corals show an interesting mixture of taxa known since the Middle Jurassic and those known only from the Cretaceous.
UnivIS-Import:2017-12-18:Pub.2007.nat.dgeo.IGM.LP.lowerc
Keywords: Lower cretaceous; NE-Iran; Scleractinia; Taxonomy

Macroinvertebrate palaeo-communities from the Jurassic succession of Gebel Maghara (Sinai, Egypt) - Abdelhady, Ahmed Awad; Fürsich, Franz (Journal of African Earth Sciences, 2014)
Macrobenthic palaeo-communities of the Middle and Upper Jurassic strata of G. Maghara, Egypt, were investigated to identify relationships with environmental parameters and to trace the temporal changes of the ecosystem associated with sea-level fluctuations. The quantitative analysis of a data matrix comprising 198 macrobenthic taxa in 138 samples collected from four sections identified nine associations and three assemblages, interpreted to be representative of their original environment. Non-Metric Multidimensional Scaling (NMDS) delineated the same degree of habitat partitioning as hierarchical clusters with very little overlap. Detrended Correspondence Analysis (DCA) identified water depth as the primary environmental gradient controlling the distribution of the fauna, while Axis 2 reflects substrate consistency. Community structure is related to the various ramp environments. Based on diversities, the associations and assemblages have been divided into two major groups, low-stress polyspecific associations and high-stress paucispecific associations. The low-stress polyspecific associations were interpreted to represent two different habitats, a high-energy, firm substrate habitat, in which epifaunal bivalves and brachiopods in addition to solitary corals dominated during advanced stages of transgression, and a low-energy, soft substrate habitat dominated by infaunal bivalves during the maximum flooding. The high-stress paucispecific associations are dominated by one or few taxa and occurred (1) in an oligotrophic setting that developed during episodes of sediment starvation in restricted inner ramp environments or during early transgression, (2) in a setting characterized by high sedimentation rates which developed during advanced regression, (3) in a distal prodelta setting with soft substrate and dysoxia during sea-level lowstand, and (4) in a high-energy shoal environment during peak regression. A combined stress involving a shortage in food supply, episodic dysoxia, in addition to a soupy substrate may have developed during maximum flooding episodes. Hydrodynamic conditions were most likely the main factor controlling the benthic communities. Hydrodynamic conditions influenced the substrate type, redistributed nutrients and were responsible for stratified water masses and hypoxia. Animal-sediment relationships in addition to replacement between bivalves and brachiopods are also discussed. Middle ramp settings were found to provide the best conditions for macrobenthos. © 2014 Elsevier Ltd.
UnivIS-Import:2017-12-18:Pub.2014.nat.dgeo.IGM.LP.macroi
Keywords: Ecosystem; G. Maghara; Jurassic; Macrobenthos; Ordination; Palaeoenvironments

Middle to Upper Triassic deep-water trace fossils from the Ashin Formation, Nakhlak area, Central Iran - Vaziri, Seyed Hamid; Fürsich, Franz (Journal of Sciences, Islamic Republic of Iran, 2007)
The up to 304 m thick, turbiditic, siliciclastic Ashin Formation (Upper Ladinian to Lower Carnian?) crops out widely in the Nakhlak area of central Iran. The rocks consist mainly of turbiditic volcaniclastic sandstones and shales that were deposited in distal parts of submarine fans of the continental slope to abyssal plain. Trace fossils occur commonly in the lower parts of the turbiditic volcaniclastic sandstones and belong to 17 ichnotaxa including ?Chondrites isp., Ctenopholeus kutscheri, Helminthopsis abeli, H. tenuis, H. hieroglyphica, Laevicyclus rotaeformis, Lorenzinia nowaki, Megagrapton isp., Ophiomorpha isp., Palaeophycus isp., Paleodictyon cf. maximum, Protopaleodictyon incompositum, Protovirgularia isp., and Thalassinoides isp. The trace fossil assemblage belongs to the deep-sea Nereites ichnofacies. In particular trace fossils such as Paleodictyon, Protopaleodictyon, Megagrapton and Lorenzinia indicate that the Ashin Formation represents a deep marine environment.
UnivIS-Import:2017-12-18:Pub.2007.nat.dgeo.IGM.LP.middle
Keywords: Trace fossils; Triassic; Ashin Formation; Nakhlak; Central Iran

Modeling shelliness and alteration in shell beds: variation in hardpart input and burial rates leads to opposing predictions - Tomašových, Adam; Fürsich, Franz; Olszewski, Thomas D. (Paleobiology, 2006)
Distinguishing the differential roles of hardpart-input rates and burial rates in the formation of shell beds is important in paleobiologic and sedimentologic studies, because high shelliness can reflect either high population density of shell producers or lack of sediment. The modeling in this paper shows that differences in the relative importance of burial rates and hardpart-input rates lead to distinct patterns with respect to the degree of shelliness and taphonomic alteration in shell beds. Our approach substantially complements other models because it allows computation of both shelliness and assemblage-level alteration. To estimate shelliness, we dissected hardpart-input rates into dead-shell production and shell destruction rates. To estimate assemblage-level alteration, we computed an alteration rate that describes how rapidly shells accrue postmortem damage. Under decreasing burial rates but constant hardpart-input rates, a positive correlation between alteration and shelliness is expected (Kidwell's R-sediment model). In contrast, under decreased destruction rates and/or increased dead-shell production rates and constant burial rates (Kidwell's R-hardpart model), a negative correlation between shelliness and alteration is expected. The contrasting predictions thus provide a theoretical basis for distinguishing whether high shell density in shell beds reflects passive shell accumulation due to a lack of sediment dilution or whether it instead reflects high shell input from a life assemblage. This approach should be applicable for any fossil assemblages that vary in shell density and assemblage-level alteration. An example from the Lower Jurassic of Morocco, which has shell-rich samples less altered than shell-poor samples, suggests that the higher shelliness correlates with higher community-level abundance and lower proportion of juveniles of the main shell producer, supporting the driving role of hardpart-input rates in the origin of the shell-rich samples in this case. This is of significance in paleoecologic analyses because variations in shelliness can directly reflect fluctuations in population density of shell producers. © 2006 The Paleontological Society. All rights reserved.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.modeli
Keywords: shell beds; shellines; burial rates; hardpart-input rates

New evidence on the lithostratigraphy of the Jurassic system in the northern Tabas Block, east-central Iran - Seyed-Emami, Kazem; Fürsich, Franz; Wilmsen, Markus (Geosciences, 2006)
The sedimentary pattern of the northern Tabas Block during the Jurassic period, apart from global sea-level fluctuations, was mainly governed by tectonic events of varying intensity and extent. These events took place during the Late Triassic (Early Cimmerian phase), Middle Bajocian (Mid-Cimmerian phase), Early Callovian, Late Oxfordian and Late Kimmeridgian/ Tithonian (Late Cimmerian phase). The importance and extent of these events and their influence on the facies pattern of the northern Tabas block are discussed. In this context the lithostratigraphy of the Jurassic strata in the northern Tabas Block is revised. The stratigraphic position of the Badamu and Parvadeh formations is briefly discussed and three facies types of the Hojedk Formation, belonging to different sedimentary environments, are reported. The Middle and Upper Jurassic Magu Group is subdivided into three new and genetically related subgroups, Le. the Upper Bajocian to Middle Callovian Baghamshah Sub group, the Lower Callovian to Middle Kimmeridgian Esfandiar Subgroup and the <st1:place style="color: rgb(0, 0, 0); font-family: Tahoma; font-size: 13.3333px;" w:st="on">Upper Kimmeridgian</st1:place> to Tithonian Garedu Sub group (Fig. 3). Furthermore the Qal' eh Dokhtar Formation is revised and three new formations, Le. the Sikhor Formation(Lower/Middle Callovian), Kamar-e-Mehdi Formation (Callovian to <st1:place style="color: rgb(0, 0, 0); font-family: Tahoma; font-size: 13.3333px;" w:st="on">Lower Kimmetidgian</st1:place>) and the Korond Formation (Upper Oxfordian to Middle Kimmeridgian) are established. This new subdivision will considerably facilitate the applicabilityof the lithostratigraphic scheme to future work.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.newevi
Keywords: Central Iran; Tabas Block; Shotori Range; Jurassic System; Stratigraphy; Paleontolgy

New occurrences of the trace fossil Paleodictyon in shallow marine environments: Examples from the Triassic-Jurassic of Iran - Fürsich, Franz; Taheri, Jafar; Wilmsen, Markus (Palaios, 2007)
The graphoglyptid trace fossil <em style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; font-size: 16px; line-height: inherit; font-family: Lato, sans-serif; vertical-align: baseline; color: rgb(51, 51, 51);">Paleodictyon, characterized by a stratiform hexagonal net, is a diagnostic member of the deep-water <em style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; font-size: 16px; line-height: inherit; font-family: Lato, sans-serif; vertical-align: baseline; color: rgb(51, 51, 51);">Nereites ichnofacies and usually found in deep-sea flysch successions. Scattered records of the trace fossil from shallower, lower-shelf-to-upper-slope environments, particularly since the mid-Mesozoic, have been substantially augmented by new data from Upper Triassic and Jurassic sedimentary basins of Iran. <em style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; font-size: 16px; line-height: inherit; font-family: Lato, sans-serif; vertical-align: baseline; color: rgb(51, 51, 51);">Paleodictyon has been found on the soles of mid-to-lower-shelf event beds produced by storm-induced currents and on the soles of prodelta turbidite deposits in the Upper Triassic Nayband Formation of east-central Iran, the lower Middle Jurassic Shemshak Formation of north-central Iran, the Middle Jurassic Kashafrud Formation of the Koppeh Dagh, and the Middle Jurassic Dalichai Formation of the Binalud Mountains. It appears that the bathymetric range of <em style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; font-size: 16px; line-height: inherit; font-family: Lato, sans-serif; vertical-align: baseline; color: rgb(51, 51, 51);">Paleodictyon throughout the Phanerozoic was considerably wider than generally assumed. The observed dominance of the trace fossil in deep-water flysch successions we interpret as being at least partially due to preservational effects. The conservation of the networks requires limited erosion, immediate casting and sealing of the exhumed negative epireliefs by sand, and limited subsequent bioturbation at deeper tiers. This restricts the trace fossil to event beds, either deep-sea turbidites or shallow-water storm beds in environments characterized by high-sedimentation rates. For bathymetric interpretations of paleoenvironments, whole ichnoassemblages should be used rather than single ichnotaxa to avoid erroneous conclusions.
UnivIS-Import:2017-12-18:Pub.2007.nat.dgeo.IGM.LP.newocc
Keywords: Paleodictyon; trace fossil; shallow marine environments; Triassic; Jurassic; Iran

Obituary. A. Seilacher 1925-2014 - Fürsich, Franz (2014)
UnivIS-Import:2017-12-18:Pub.2014.nat.dgeo.IGM.LP.obitua

Oldest camarasauromorph sauropod (Dinosauria) discovered in the Middle Jurassic (Bajocian) of the Khadir Island, Kachchh, western India - Moser, Markus; Mathur, Umesh B.; Fürsich, Franz; Pandey, Dhirendra Kumar; Mathur, Neera (Palaeontologische Zeitschrift, 2006)
Fragmentary isolated remains of large (up to 20 m or more) sauropods from the Middle Jurassic (Bajocian) Khadir Formation of Khadir Island (Kachchh, W India) are described and compared in detail. Three of the bone fragments (a metacarpal, a first pedal claw and a fibula) can be assigned with confidence to the Camarasauromorpha and represent the oldest known record of that derived dinosaur group. The new finds from western India further close a temporal and geographical gap in our knowledge of sauropods and contribute to understanding their early phylogeny.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.oldest
Keywords: Camarasauromorpha; Sauropoda; Dinosauria; morphology; phylogeny; Middle Jurassic

Porosphaera (Porifera), a globular sponge from the Upper Jurassic of the central Iran - Senowbari-Daryan, Baba; Fürsich, Franz; Wilmsen, Markus (Rivista Italiana Di Paleontologia E Stratigrafia, 2011)
Porosphaera, an abundant small spherical calcisponge, well known from Cretaceous strata of Europe, was found in Middle and Upper Jurassic deposits of east-central Iran. This is the first record of Porosphaera from the Jurassic, except for a questionable occurrence of the genus from the Upper Jurassic of Canada, described by Jansa et al. (1982). The following species are new: P. regularis n. sp., P. biporata n. sp., labyrinthica n. sp., and P.? asymmetrica n. sp.
UnivIS-Import:2017-12-18:Pub.2011.nat.dgeo.IGM.LP.porosp
Keywords: Calcisponges; Iran; Jurassic; Systematics

Preservation of autochthonous shell beds by positive feedback between increased hardpart-input rates and increased sedimentation rates - Tomašových, Adam; Fürsich, Franz; Wilmsen, Markus (Journal of Geology, 2006)
The preservation of nonrapidly buried autochthonous shell concentrations with noncementing epifaunal animals in life position presents a taphonomic dilemma if in fact an increase in shelliness is driven by a decrease in sedimentation rate. A 150‐cm‐thick, densely packed shell bed with brachiopods from the Lower Jurassic of Morocco shows lower levels of postmortem alteration than shell‐poor beds, indicating that its formation is primarily governed by variations in hardpart‐input rates. Varying dominance and size structure of the main shell producer, brachiopod Zeilleria rehmanni, indicate that its increased population density was the main trigger in the shell bed formation. Thinner and less common microbial crusts in the shell bed than in shell‐poor beds indicate that higher shelliness is not due to lack of sediment. On the basis of actualistic data from modern mussel and oyster shell beds, the suspension feeding of a high‐density population leads to high biodeposition rates through production of feces and pseudofeces, which substantially exceed natural sedimentation rates. In addition, shell‐rich areas preferentially trap more suspended sediment than shell‐poor areas. Therefore, an increase in population density of shelly biodeposit producers should lead to higher biodeposition rates. This assumption is supported by a positive correlation between brachiopod shelliness and pellet abundance. Both active biodeposition and passive trapping of sediment would have increased sedimentation rate, thus leading to a decreased rate of shell destruction through suppression of predators or borers as well as stabilization and protection of the shell concentration. Under optimum ecologic conditions, these processes result in a positive feedback between an increased hardpart‐input rate and increased biogenic sedimentation rate. This scenario thus provides one alternative pathway for formation of well‐preserved shell concentrations formed by epifaunal suspension feeders. Identifying the importance of biodeposition is of environmental significance because it implies that carbonate sediment was produced largely in situ and was directly or indirectly related to the activity of shell producers. Recognizing the role of varying hardpart‐input rates in shell concentration genesis is of ecologic significance because shelliness can directly reflect abundance fluctuations of shell producers.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.preser
Keywords: Autochthonous Shell Beds; sedimentation rate; brachiopods; Jurassic; Morocco

Pyrite formation and its control in black shales of the Buxin Formation (Lower Eocene) from the Sanshui Basin, Guangdong - Liu, Chun-lian; Dong, Yi-xin; Che, Ping; Fürsich, Franz; Shi, Gui-yong; Chen, Liang; Yan, Wei-shu (Acta Sedimentologica Sinica, 2006)
Analyses of TOC/S,TOC/DOP,S/Fe relationships and S-TOC-Femultiple linear regression were carried out to determine limiting factors for pyrite formation in black shales of the Honggang Member(Lower Eocene Bu-xin Formation) in the Sanshui Basin.Submember A,showing lower organic carbon and higher iron contents than the other submembers,deposited in oxygenated bottom waters.Bacterial sulfate reduction took place below the sediment-water interface,and pyrite was formed diagenetically and organic carbon was limited.Submember B and C are characterized by large variations in organic carbon content.Organic-rich(TOC4%) rocks deposited under anoxic environments,in which H_(2)S presented above the sediment water interface as well as within the sediments.Pyrite was formed syngenetically and confined by the duration during which iron detritus reacted with H_(2)S in the water column and by the availability of dissolved sulfate that decreased due to an increasing input of fresh waters.For organic-poor(TOC4%) sediments,pyrite was of syngenetic and diagenetic.Organic carbon-limited diagenetic pyrite added to the earlier formed syngenetic pyrite,which was controlled by the time that iron minerals remained in contact with H_(2)S in anoxic waters.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.pyrite
Keywords: pyrite formation; controls; black shale; Buxin Formation; Lower Eocene; Sanshui Basin

Record of Advenaster Hess, 1955 (Asteroidea) from the Bathonian Patcham Formation of Kala Jhar in Habo Dome, Kachchh Basin, India - Srivastava, Dinesh Kumar; Pandey, Dhirendra Kumar; Alberti, Matthias; Fürsich, Franz (Journal of the Palaeontological Society of India, 2010)
The asteroid genus Advenaster Hess, 1955 is being recorded and described for the first time from the Indian subcontinent. The specimen has been collected from limestone beds of the Middle Jurassic (Bathonian) Patcham Formation exposed in a deep gorge in the centre of the Habo Dome, south of the village Dhrang, Kachchh, India.
UnivIS-Import:2017-12-18:Pub.2010.nat.dgeo.IGM.LP.record
Keywords: Asteroidea; Advenaster; Patcham Formation; Middle Jurassic (Bathonian); Kachchh; India

Sedimentology, taphonomy, and palaeoecology of a laminated plattenkalk from the Kimmeridgian of the northern Franconian Alb (southern Germany) - Fürsich, Franz; Werner, Winfried; Schneider, Simon; Mäuser, Matthias (Palaeogeography, Palaeoclimatology, Palaeoecology, 2006)
<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">At Wattendorf in the northern Franconian Alb, southern Germany, centimetre- to decimetre-thick packages of finely laminated limestones (plattenkalk) occur intercalated between well bedded graded grainstones and rudstones that blanket a relief produced by now dolomitized microbialite-sponge reefs. These beds reach their greatest thickness in depressions between topographic highs and thin towards, and finally disappear on, the crests. The early Late Kimmeridgian graded packstone–bindstone alternations represent the earliest plattenkalk occurrence in southern Germany. The undisturbed lamination of the sediment strongly points to oxygen-free conditions on the seafloor and within the sediment, inimical to higher forms of life. The plattenkalk contains a diverse biota of benthic and nektonic organisms. Excavation of a 13 cm thick plattenkalk unit across an area of 80 m<span style="margin: 0px; padding: 0px; box-sizing: border-box; position: relative; top: -0.4em; vertical-align: baseline; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif;">2<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> produced 3500 fossils, which, with the exception of the bivalve <em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">Aulacomyella<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">, exhibit a random stratigraphic distribution. Two-thirds of the individuals had a benthic mode of life attached to hard substrate. This seems to contradict the evidence of oxygen-free conditions on the sea floor, such as undisturbed lamination, presence of articulated skeletons, and preservation of soft parts. However, palaeoecological and taphonomic analyses indicate that the benthic faunal elements are allochthonous having settled out of suspension and thus must have been derived from hard substrate areas of neighbouring topographic highs. Solely the bivalve <em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">Aulacomyella<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">, which occurs concentrated on a single bedding plane, may have colonised the plattenkalk depression during brief periods of oxygenation. Alternatively, a pseudoplanktonic mode of life, attached to floating sea weed, is envisaged for the bivalve. The formation of the plattenkalk is related to local and global factors: a drop in relative sea level caused the death of the microbialite-sponge reefs. Restricted circulation in depressions between the crests of the former reefs led to anoxic conditions and the formation of finely laminated sediments stabilised by microbial mats. The small depressions received sediment and skeletal elements of benthic organisms that were swept off neighbouring topographic highs by storms and that entered the depressions partly as turbidity currents, partly as suspension clouds. A rise in the relative sea level finally terminated the restricted circulation in the depressions and closed the taphonomic window that led to the preservation of the plattenkalk biota.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.sedime
Keywords: Plattenkalk; Upper Jurassic; Germany; Palaeoecology; Taphonomy

Stable isotope analyses of belemnites from the Kachchh Basin, western India: paleoclimatic implications for the Middle to Late Jurassic transition - Alberti, Matthias; Fürsich, Franz; Pandey, Dhirendra Kumar; Ramkumar, Muthuvairavasamy (Facies, 2012)
Stable isotope analyses of 61 diagenetically unaltered belemnite rostra from the Middle to Late Jurassic of the Kachchh Basin of western India suggest stable paleotemperatures across the Callovian-Oxfordian boundary ( 14°C). Only at the end of the Middle Oxfordian water temperatures drop for more than 3°C before reaching again higher values during the Kimmeridgian ( 12. 3°C). The data do not support polar glaciations proposed for the Middle to Late Jurassic transition, which necessarily would have led to a global temperature and sea-level minimum at the boundary. Callovian to Oxfordian rocks in the Kachchh Basin point to a gradual shallowing corresponding to a slight fall in relative sea level. However, the magnitude of this regression is comparatively small, and the sea-level minimum is reached in the late Early Oxfordian and not close to the boundary. Results from the Kachchh Basin therefore, imply almost stable climatic conditions during the Middle to Late Jurassic transition and do not show any evidence for polar glaciations. © 2011 Springer-Verlag.
UnivIS-Import:2017-12-18:Pub.2012.nat.dgeo.IGM.LP.stable
Keywords: India; Jurassic; Kachchh Basin; Oxygen and carbon isotopes; Paleoclimate

Stratigraphy and ammonite fauna of the upper Shemshak Formation (Toarcian - Aalenian) at Tazareh, eastern Alborz, Iran - Fürsich, Franz; et al. (Journal of Asian Earth Sciences, 2006)
With a thickness of 3900 m, the Tazareh section is one of the thickest developments of the Shemshak Formation in the Alborz range. It overlies with sharp and disconformable contact the limestones and dolomites of the Lower-Middle Triassic Elikah Formation and is topped, again with a disconformable contact, by the marls and limestones of the Middle Jurassic Dalichai Formation. The nearly exclusively siliciclastic succession represents a range of environments, from fluvial channels, flood plains, swamps and lake systems to storm-dominated shelf, and a comparatively deep marine and partly dysoxic basin. The segment of the section between 2300 and 3500 m is exclusively marine and contains a moderately diverse ammonite fauna, ranging from the Middle Toarcian to the Upper Aalenian. The ammonite fauna comprises 21 taxa, among them the new genus Shahrudites with two new species, Shahrudites asseretoi and S. stoecklini from the Middle Aalenian Bradfordensis Zone. The other ammonites from the Shemshak Formation at Tazareh (as elsewhere in North and Central Iran) are exclusively Tethyan in character and closely related to faunas from western and central Europe. An ammonite-based correlation of Toarcian-Aalenian successions of the eastern Alborz with time-equivalent strata of the Lut Block, part of the Central-East Iranian Microcontinent (ca. 500 km to the south), suggests a strong influence of synsedimentary tectonics during the deposition of the upper Shemshak Formation. © 2005 Elsevier Ltd. All rights reserved.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.strati_1
Keywords: Ammonites; Biostratigraphy; Correlation; Eastern Alborz; Iran; Jurassic; Shemshak Formation

Stratigraphy and depositional environments of the Upper Bajocian-Bathonian Kashafrud Formation (NE Iran) - Taheri, Jafar; Fürsich, Franz; Wilmsen, Markus (Volumina Jurassica, 2006)
The Upper Bajocian-Bathonian Kashafrud Formation is a thick (>2 km), siliciclastic sedimentary unit, distributed in a NW-SE-trending, 200 km long and 80 km wide outcrop belt in the area between the Koppeh Dagh and the Binalud Mountains (NE Iran). It was deposited in a strongly subsiding rift basin developing between the Iran Plate and Eurasia (Turan Plate) in response to Middle Jurassic crustal extension following the Mid-Cimmerian tectonic movements. The Kashafrud Basin is a southeastern prolongation of the South Caspian Basin, opening along the ocean suture which has been formed by the Late Triassic closure of the Palaeotethys (so-called Early Cimmerian orogeny). The stratigraphy and depositional environments of the Kashafrud Formation are the scope of this integrated analysis. Ten sections of the Kashafrud Formation were logged in detail and sampled for lithology, macro- and trace fossils, and facies analysis. At several localities, ammonites occur near the base of the formation, in every case providing a Late Bajocian age. Within the middle and upper parts of the Kashafrud Formation, ammonites are rare. However, in its uppermost part and at the base of the overlying unit (marls of the Chaman Bid Formation), ammonites of the genus Macrocephalites indicate an Early Callovian age. Thus, the Kashafrud Formation can be mainly assigned to the Upper Bajocian-Bathonian. Commonly, the Kashafrud Formation rests with angular unconformity on rocks affected by the Early Cimmerian orogeny. Based on thicknesses and principal facies development, two NW-SE-striking (basin-axis-parallel) zones can be differentiated, i.e., a more proximal one close to the Binalud Mountains in the SW and a distal one towards the Koppeh Dagh in the NE. Basal conglomerates tend to be thickest and coarsest in the proximal zone, at the southwestern basin margin. Rapid lateral thickness changes indicate a fault-controlled deposition (proximal alluvial fans or rockfalls). Up-section, the conglomerates are replaced by highly immature arcosic sandstones and pebbly sandstones of a short-headed braided river system grading into marine fan delta deposits. Rapid deposition and subsidence are indicated by the lack of significant maturation of the sediments even in settings above the fair-weather wave base. In some sections, basal conglomerates are thin and fluvial sediments missing, and the Kashafrud Formation directly starts with coarse-grained marine fan delta deposits. In all cases, a distinct fining-upward indicates a significant deepening trend. In the distal zone, basal conglomerates are thin and commonly marine as indicated by marine fossils. They are vertically replaced by basin plain (dark shales with rare ammonites) and intercalated submarine fan deposits (including coarse upper fan feeder channels, mid-fan leveed channel and inter-channel deposits, and well bedded shale-sandstone outer fan intercalations). Bioturbation is common in turbidite sequences and a deeper marine environment is indicated by rare graphoglyptids of the Nereites ichnofacies. Also in the distal part, a general fining- and thinning-upward trend indicates a deepening. All the observations can be integrated into a rift basin model for the Kashafrud Formation. The basin axis trend was roughly NW-SE and the stratigraphic and sedimentologic data indicate a main sediment input from the southwestern basin margin (Binalud). The northeastern basin margin is inferred below the Koppeh Dagh.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.strati_4
Keywords: IranBajocian-Bathonian; Kashafrud Formation; biostratigraphy; lithostratigraphy; facies analysis

Stratigraphy and palaeoenvironments of the Jurassic rocks of Kachchh - Field Guide - Fürsich, Franz; Alberti, Matthias; Pandey, Dhirendra Kumar (2013)
The Jurassic sedimentary succession of Kachchh represents the fill of a small rift basin situated at the western margin of the Indian Plate adjacent to the Malagasy Gulf. Jurassic rocks are exposed in three areas, the so-called lsland Belt, the Kachchh Mainland, and the Wagad Uplift. Rifting started in the Late Triassic documented by red beds and alluvial fans in cores from the Banni Plain. During the Early and early Middle Jurassic marine and non-marine conditions alternated. The corresponding sediments are exposed in the Island Belt of northern Kachchh. By Bathonian times and until the end of the Jurassic shallow marine facies prevailed. During the Bathonian, probably as result of a comparatively warm and arid climate, carbonates were widespread. In contrast, the remaining time slices are characterised by siliciclastic sediments. They range from silty clays in the low-energy, offshore areas to cross-bedded sandstones or ferruginous oolites in high-energy, shallow-water areas. Both carbonates and siliciclastics were deposited on ramps with a depth gradient towards the west and from the island Belt in the North to the Kachchh Mainland in the South. Sediment input was mainly from the north and from the east. The basin was subdivided by several E-W trending faults into sub-basins which corresponded to half grabens with somewhat differing sedimentation histories. The by far most interesting lithostratigraphic unit of the basin is the Oxfordian Dhosa Dolite member, a highly condensed unit that can be traced across the Kachchh Mainland for more than 100 km and that documents both offshore conditions and at least two phases of subaerial exposure followed by a major depositional gap comprising the Late Oxfordian and Early Kimmeridgian. Towards the end of the Jurassic rifting ceased and the basin became gradually filled with sediment from the east. The Kachchh Basin is well known for its rich macro invertebrate faunas, particularly ammonites, bivalves, brachiopods, and corals which belong to the Ethiopean faunal province. This field guide, prepared on the occasion of the 9th International Congress on the Jurassic System in Jaipur, India, attempts to give an overview of the present state of knowledge on the geology of the area. It starts with a general description of Kachchh, ranging from geographic aspects to its inhabitants, food and history. This is followed by an overview on the Jurassic geology including the lithofacies, various aspects of stratigraphy, faunal and floral composition, a chapter on palaeoecology, and concludes with a summary of the palaeoenvironmental evolution of the basin. The third section contains descriptions of 13 localities which allow to trace the development of the basin from the early Middle Jurassic to the Early Cretaceous.
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.strati
Keywords: Stratigraphy; palaeoenvironments; Jurassic rocks; Kachchh Basin; field guide

The Cimmerian Orogeny in Iran - a foreland perspective - Wilmsen, Markus; Fürsich, Franz; Seyed-Emami, Kazem; Majidifard, Mahmoud Reza (Terra Nova, 2009)
UnivIS-Import:2017-12-18:Pub.2009.nat.dgeo.IGM.LP.thecim

The Jehol Biota: Definition and distribution of exceptionally preserved relicts of a continental Early Cretaceous ecosystem - Pan, Yan-Hong; Sha, Jin-Geng; Zhou, Zhonghe; Fürsich, Franz (Cretaceous Research, 2013)
<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">Fossils from the “Jehol Biota” have been studied for nearly 90 years, and the term “Jehol Biota” has been extensively used and is well known today, largely thanks to the discovery of feathered dinosaurs, angiosperms, and numerous other exceptionally preserved fossils in the Lower Cretaceous of northeastern China. Ironically, however, what exactly the Jehol Biota represents and how it is defined has hardly been discussed. The lack of a precise definition of the Jehol Biota has hindered our understanding of such important issues as its palaeodiversity, its spatial and temporal distribution, and the pattern of radiation of the biota. In this paper, we propose that the Jehol Biota is defined by using a palaeoecological concept, and by combining ecological and taphonomic aspects, i.e., as organisms that lived in the Early Cretaceous volcanic-influenced environments of northeastern China, and were buried in lacustrine and rarely fluvial sediments, where most turned into exceptionally preserved fossils. The relationship between the Jehol Biota and the Jehol Group is also clarified. According to the revised definition, the Jehol Biota is so far only discovered in deposits of the Yixian and Jiufotang formations of western Liaoning, adjacent Inner Mongolia, and northern Hebei, and the Huajiying Formation of northern Hebei. Temporally it ranges from the Barremian to Aptian, i.e., for at least 10 Ma (130–120 Ma).
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.thejeh
Keywords: Jehol Biota; Palaeoecology; Taphonomy; Konservat-Lagerstätten; Jehol Group; Early Cretaceous; Northeastern China

The Oxfordian stable isotope record (δ18O, δ13C) of belemnites, brachiopods, and oysters from the Kachchh Basin (western India) and its potential for palaeoecologic, palaeoclimatic, and palaeogeographic reconstructions - Alberti, Matthias; Fürsich, Franz; Pandey, Dhirendra Kumar (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">The study combines the results of stable isotope (<em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">δ<span style="margin: 0px; padding: 0px; box-sizing: border-box; position: relative; top: -0.4em; vertical-align: baseline; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif;">13<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">C, <em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">δ<span style="margin: 0px; padding: 0px; box-sizing: border-box; position: relative; top: -0.4em; vertical-align: baseline; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif;">18<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">O) analyses of 187 belemnites, brachiopods, and oysters from the Middle to Upper Jurassic (Upper Callovian to Kimmeridgian) of the Kachchh Basin in western India. Generally, belemnites show lower <em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">δ<span style="margin: 0px; padding: 0px; box-sizing: border-box; position: relative; top: -0.4em; vertical-align: baseline; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif;">13<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">C and higher <em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">δ<span style="margin: 0px; padding: 0px; box-sizing: border-box; position: relative; top: -0.4em; vertical-align: baseline; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif;">18<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">O ratios than the benthic fauna. It is proposed that this discrepancy is caused by different life habitats of both groups with belemnites spending major parts of their life in deeper water outside the Kachchh Basin and entering shallow areas only occasionally (e.g., during seasonal migrations to spawning grounds). A mode of life as fast-swimming, nektonic predators similar to many modern squid species seems plausible. The study emphasises that results of stable isotope analyses should be evaluated separately for each fossil group. In addition to the influence of diagenetic alteration, weathering, salinity changes, and sea-level fluctuations, the ecology of the analysed fossil taxa has to be considered. Temperatures calculated from <em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">δ<span style="margin: 0px; padding: 0px; box-sizing: border-box; position: relative; top: -0.4em; vertical-align: baseline; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif;">18<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">O ratios point to relatively warm conditions around the Middle to Late Jurassic transition with no evidence for a glacial phase which had been proposed for this boundary. A distinct fall in temperatures is observed during the Middle Oxfordian reaching a minimum in the early Late Oxfordian. It is tempting to connect this event with the break-up of Gondwana causing stronger upwelling in the northwestern Tethys or alternatively the influx of polar water by the opening of the Transgondwanan Seaway. However, such connections cannot be verified without further data, preferably from localities in the southern Malagasy Gulf (e.g., Madagascar) and from younger horizons (Kimmeridgian–Tithonian).
UnivIS-Import:2017-12-18:Pub.2012.nat.dgeo.IGM.LP.theoxf
Keywords: Oxygen and carbon isotopes; Palaeoclimate; Palaeogeography; Palaeoecology; Jurassic; Kachchh Basin

The Shemshak Group (Lower - Middle Jurassic) of the Binalud Mountains, NE Iran: stratigraphy, depositional environments and geodynamic implications - Wilmsen, Markus; Fürsich, Franz; Taheri, Jafar (South Caspian to Central Iran basins, 2009)
The Lower–lower Middle Jurassic non-marine sedimentary succession of the Binalud Mountains of NE Iran is correlated with the Jurassic part of the Shemshak Group of the Alborz Mountains and subdivided into three formations: the Arefi, the Bazehowz and the Aghounj formations. The succession rests, with angular unconformity, on a metamorphic basement deformed during the Late Triassic Eo-Cimmerian orogeny. The lowermost unit, the Arefi Formation, is subdivided into a lower Derekhtoot Member and an upper Kurtian Member. The Derekhtoot Member (up to 750 m thick) consists of very coarse-grained, chaotic boulder beds, breccias and conglomerates representing rock-fall deposits and proximal–middle alluvial fans, deposited along steep fault scarps. The succeeding Kurtian Member (>300 m) comprises finer-grained conglomerates with well-rounded clasts, reflecting deposition in a proximal braided river system. The overlying Bazehowz Formation is more than 1000 m thick and consists of vertically stacked, decametre-scale channel-fill cycles of the middle reaches of a braided fluvial system. The uppermost unit, the Aghounj Formation, consists of at least 400 m of granule- to pebble-size, thick-bedded and large-scale trough cross-bedded quartz conglomerates and sandy interbeds of a proximal braided fluvial system. The overall succession fines upwards due to erosion, down to metamorphic basement, of a high-relief source area in the NE, and rests on Cimmerian basement, suggesting that the strata are intramontane deposits of the Cimmerian mountain chain in NE Iran. This interpretation has important implications concerning the position of the NW–SE-trending Eo-Cimmerian suture in NE Iran, which should be placed further SW than formerly assumed.
UnivIS-Import:2017-12-18:Pub.2009.nat.dgeo.IGM.LP.theshe
Keywords: Middle Jurassic; Binalud Mountains; Shemshak Group; Alborz Mountains; stratigraphy; depositional environments; geodynamic implications

The trace fossil Ctenopholeus Seilacher & Hemleben, 1966 from the Jurassic of India and Iran: distinction from related ichnogenera - Fürsich, Franz; Pandey, Dhirendra Kumar; Kashyab, Deepali; Wilmsen, Markus (Neues Jahrbuch fur Geologie und Palaontologie Monatshefte, 2006)
The relationship between the ichnogenera Saerichnites BILLINGS, 1886, Hormosiroidea SCHAFFER, 1928, and Ctenopholeus SEILACHER & HEMLEBEN, 1966 is discussed. Straight, curved to looped uniserial rows of closely spaced circular to subcircular pits or knobs (negative or positive epireliefs) have been accommodated in the ichnotaxon Ctenopholeus kutcheri SEILACHER & HEMLEBEN, 1966. They were found on a bedding plane with oscillation ripples in Upper Jurassic rocks of the Jaisalmer Basin, Rajasthan, and on flat surfaces with parting lineation in lower Jurassic sandstones of the Shemshak Formation of the eastern Alborz, Iran. In both cases, a shallow-water, high-energy environment is indicated. Evidence of a horizontal burrow situated below and connected to these pits/knobs confirms the interpretation of a three-dimensional burrow system consisting of a horizontal tunnel from which at close distance vertical shafts extended to the sediment water interface. In contrast to earlier interpretations of the burrow system as fodinichnion, it is here interpreted as an agrichnion, functioning as trap for small mobile organisms. © 2006 E. Schweizerbart'sche Verlagsbuchhandlung.
UnivIS-Import:2017-12-18:Pub.2006.nat.dgeo.IGM.LP.thetra
Keywords: Agrichnion; India; Iran; Jurassic; Trace fossils

The Wattendorf Plattenkalk (Upper Kimmeridgian) - a new conservation lagerstätte from the northern Franconian Alb, southern Germany - Fürsich, Franz; Mäuser, Matthias; Schneider, Simon; Werner, Winfried (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2007)
A new occurrence of fossiliferous plattenkalks from the lower Upper Kimmeridgian Eudoxus Zone at Wattendorf, northern Franconian Alb, is briefly described. The laminated micritic limestones consist of two types of microfacies, graded packstones and microbial bindstones. The plattenkalk facies occurs as several decimetre-thick intercalations between graded pack- to rudstones, which accumulated in depressions of a distinct submarine palaeorelief. This relief was formed by microbialite-sponge reefs, which are now preserved as massive dolostone. So far, more than 70 taxa have been recovered from the plattenkalk. The biota are dominated by benthic molluscs and brachiopods, but fossils present include also algae, plants, sponges, crustaceans, polychaetes, ammonites, belemnites, echinoderms, fishes, and fragments of reptiles. The ecological and taphonomic analysis of the benthic faunal elements shows that probably none of them were autochthonous, but that most of them were swept into the plattenkalk environment from neighbouring topographic highs via storm-produced suspension clouds. It cannot be excluded with certainty that the most common bivalve, Aulacomyella, episodically colonised the soupy substrate, but a pseudoplanktonic mode of life is regarded as more likely. It is proposed that the plattenkalk formed in small, restricted depressions of the topographic relief provided by dead microbialite-sponge reefs. In these depressions lack of circulation led to establishment of dysoxic to anoxic conditions favouring preservation of soft parts and of articulated skeletons. © 2007 E. Schweizerbart'sche Verlagsbuchhandlung.
UnivIS-Import:2017-12-18:Pub.2007.nat.dgeo.IGM.LP.thewat
Keywords: Biota; Environmental model; Franconian alb; Late Jurassic; Plattenkalk; Taphonomy

Upper Triassic (Norian) Cephalopods from the Ekrasar formation (Shemshak Group) of northern Alborz, Iran - Seyed-Emami, Kazem; Fürsich, Franz; Wilmsen, Markus; Majidifard, Mahmoud Reza; Shekarifard, Ali (Rivista Italiana Di Paleontologia E Stratigrafia, 2009)
The following ammonoid and nautiloid taxa are described for the first time from the Upper Triassic succession (Ekrasar Formation, Shemshak Group) of northern Alborz, Iran: Arcestes sp., Arcestes (Pararcestes?) sp., Thisbites cf. agricolae Mojsisovics, Stikinoceras cf. kerri Mc Learn, Giesbachites sp., Griesbachites cf. pseudomedleyanus Diener, Griesbachites cf. himalayanus Wang & He, and Proclydonautilus? sp. Palaeobiogeographically, the studied ammonoids are Tethyan in character, and stratigraphically attributed to the lower Lower Norian (Guembelites jandianus Zone, possibly also Malayites paulckei Zone). The biostratigraphic data of this study demonstrate the diachronous base of the Shemshak Group: it is older in the northern Alborz (lower Lower Norian), but younger in Central Iran and probably also in the southern Alborz (Middle Norian).
UnivIS-Import:2017-12-18:Pub.2009.nat.dgeo.IGM.LP.uppert
Keywords: Upper Triassic; Norian; Ammonoids; Shemshak Group; Ekrasar Formation; Alborz; Iran